Accelerating Distributed Optimization via Over-the-Air Computing - Mitsiou, Nikos A.; Bouzinis, Pavlos S.; Diamantoulakis, Panagiotis D.; Schober, Robert; Karagiannidis, George K. (IEEE Transactions on Communications, 2023)
Distributed optimization is ubiquitous in emerging applications, such as robust sensor network control, smart grid management, machine learning, resource slicing, and localization. However, the extensive data exchange among local and central nodes may cause a severe communication bottleneck. To overcome this challenge, over-the-air computing (AirComp) is a promising medium access technology, which exploits the superposition property of the wireless multiple access channel (MAC) and offers significant bandwidth savings. In this work, we propose an AirComp framework for general distributed convex optimization problems. Specifically, a distributed primal-dual (DPD) subgradient method is utilized for the optimization procedure. Under general assumptions, we prove that DPD-AirComp can asymptotically achieve zero expected constraint violation. Therefore, DPD-AirComp ensures the feasibility of the original problem, despite the presence of channel fading and additive noise. Moreover, with proper power control of the users’ signals, the expected non-zero optimality gap can also be mitigated. Two practical applications of the proposed framework are presented, namely, smart grid management and wireless resource allocation. Finally, numerical results confirm DPD-AirComp’s excellent performance, while it is also shown that DPD-AirComp converges an order of magnitude faster compared to two digital orthogonal multiple access schemes, specifically, time-division multiple access (TDMA), and orthogonal frequency-division multiple access (OFDMA).
CRIS-Team Scopus Importer:2023-07-07
Keywords: 6G; 6G mobile communication; Convergence; distributed optimization; large-scale optimization; Linear programming; non-orthogonal multiple access; Optimization; Over-the-air computing; primal-dual; Resource management; Servers; Smart grids; subgradient method

A Chemical Master Equation Model for Synaptic Molecular Communication - Lotter, Sebastian; Schäfer, Maximilian; Schober, Robert (2022 IEEE WIRELESS COMMUNICATIONS AND NETWORKING CONFERENCE (WCNC), 2022)
CRIS-Team WoS Importer:2022-08-12

Achievable Rate of the Half-Duplex Multi-Hop Buffer-Aided Relay Channel With Block Fading - Jamali Kooshkghazi, Vahid; Zlatanov, Nikola; Shoukry, Hebatallah; Schober, Robert (IEEE Transactions on Wireless Communications, 2015)
The half-duplex (HD) multi-hop relay channel consists of a source, multiple HD relays connected in series, and a destination where links are present only between adjacent nodes. In this paper, we focus on decode-and-forward relays and assume that the links are impaired by block fading and additive white Gaussian noise. We design a new protocol which, unlike the conventional protocols for the multi-hop relay channel, does not adhere to a fixed and predefined pattern of using the transmit, receive, and silent states of the nodes. In particular, the proposed protocol selects the optimal states of the nodes and the corresponding optimal transmission rates based on the instantaneous channel state information (CSI) of the involved links in each fading block such that the achievable average rate from source to destination is maximized. To enable adaptive scheduling of the states of the nodes, the relay nodes have to be equipped with buffers for temporary storage of the information received from the preceding node. Additionally, we discuss and address two practical challenges arising in the implementation of the optimal protocol, namely the unconstrained end-to-end delay due to data buffering at the relays and the required CSI overhead. Numerical results confirm the superiority of the proposed buffer-aided protocols compared to existing multi-hop relaying protocols.<br
Keywords: Relays; Protocols; High definition video; Fading; Buffer storage; Interference; Optimization

Achievable Rate Region of the Bidirectional Buffer-Aided Relay Channel With Block Fading - Jamali Kooshkghazi, Vahid; Zlatanov, Nikola; Ikhlef, Aissa; Schober, Robert (IEEE Transactions on Information Theory, 2014)
The bidirectional relay channel, in which two users communicate with each other through a relay node, is a simple but fundamental and practical network architecture. In this paper, we consider the block fading bidirectional relay channel with a decode-and-forward relay and propose efficient transmission strategies that exploit the block fading property of the channel. We assume that a direct link between the two users is not present and consider two transmission modes: 1) the multiple-access mode (both users transmit to the relay) and 2) the broadcast mode (the relay transmits to both users). Most existing relaying protocols assume a fixed schedule for using these transmission modes. In contrast, we abandon the restriction of having a fixed and predefined schedule and propose to optimize the selection of the transmission modes and the associated transmission rates based on the instantaneous channel state information (CSI) of the involved links. Thereby, we consider two different types of transmit power constraints: 1) a fixed transmit power for each node and 2) a per-node long-term power constraint. To enable the use of a nonpredefined schedule for transmission mode selection, the relay has to be equipped with two buffers for storage of the information received from both users. We develop new relaying protocols based on adaptive mode selection and provide the corresponding achievable long-term rate regions. In particular, based on the CSI of the involved links, the optimal transmission mode as well as the optimal transmission rates and/or the transmit powers of the nodes are chosen in each time slot to maximize the weighted sum rate of both users. By varying the weights assigned to the users, the boundary surface of the achievable long-term rate region of the proposed protocol can be obtained. In addition, we discuss and address two practical challenges for the implementation of the proposed protocols, namely, the availability of the knowledge of the channel statistics required for the implementation of the optimal protocols, and the increase of the end-to-end delay due to the data buffering. Numerical results confirm the superiority of the proposed buffer-aided protocols compared with existing bidirectional relaying protocols.<br
Keywords: Relays; Protocols; Fading; Buffer storage; Optimization; Schedules; Decoding

Achievable Rates for the Fading Half-Duplex Single Relay Selection Network Using Buffer-Aided Relaying - Zlatanov, Nikola; Jamali Kooshkghazi, Vahid; Schober, Robert (IEEE Transactions on Wireless Communications, 2015)
In the half-duplex single relay selection network, comprised of a source, M half-duplex relays, and a destination, only one relay is active at any given time, i.e., only one relay receives or transmits, and the other relays are inactive, i.e., they do not receive nor transmit. The capacity of this network, when all links are affected by independent slow time-continuous fading and additive white Gaussian noise (AWGN) , is still unknown, and only achievable average rates have been reported in the literature so far. In this paper, we present new achievable average rates for this network, which are larger than the best known average rates. These new average rates are achieved with a buffer-aided relaying protocol. Since the developed buffer-aided protocol introduces unbounded delay, we also devise a buffer-aided protocol which limits the delay at the expense of a decrease in rate. Moreover, we discuss the practical implementation of the proposed buffer-aided relaying protocols and show that they do not require more resources for channel state information acquisition than the existing relay selection protocols.<br
Keywords: Relays; Protocols; Delays; High definition video; Wireless communication; Rayleigh channels

Achievable rates for the fading three-hop half-duplex relay network using buffer-aided relaying - Shoukry, Hebatallah; Zlatanov, Nikola; Jamali Kooshkghazi, Vahid; Schober, Robert (2014 IEEE Global Communications Conference, 2014)
The fading three-hop half-duplex relay network consists of a source, two half-duplex relays, and a destination connected in series where links are present only between adjacent nodes. We assume that the links are impaired by time-continuous fading and additive white Gaussian noise. For this network, we design new protocols based on buffer-aided relaying and derive their achievable average rates. We first develop a buffer-aided protocol which maximizes the average rate, but, as a side effect, introduces unbounded delay. Therefore, we also design a buffer-aided protocol which constrains the average delay, but at the expense of decrease of rate. Our numerical results show that the maximum average rate achieved with the developed buffer-aided protocol is larger than that of existing protocols for the considered network. Moreover, given a sufficiently large permissible average delay, the average rate achieved with the buffer-aided protocol with a delay constraint approaches the maximum average rate achieved without a delay constraint.<br
Keywords: Protocols; Delays; Fading; Relay networks (telecommunications); Spread spectrum communication; Switches

ACM NANOCOM 2018: 5th ACM international conference on nanoscale computing and communication: Reykjavik, Iceland, September 5-7, 2018 - Benediktsson, Jon Atli; Dressler, Falko; Payne, Gregory F.; Juntti, Markku; Schober, Robert; Tentzeris, Emmanouil M.; Kokkoniemi, Joonas; Balasingham, Ilangko; Jornet, Josep M.; Han, Chong; Feng, Liang; Barros, Michael; et al. (Proceedings of the 5th ACM International Conference on Nanoscale Computing and Communication, NANOCOM 2018, 2018)
CRIS-Team Scopus Importer:2022-06-05

A Comprehensive Overview on 5G-and-Beyond Networks with UAVs: From Communications to Sensing and Intelligence - Wu, Qingqing; Xu, Jie; Zeng, Yong; Ng, Derrick Wing Kwan; Al-Dhahir, Naofal; Schober, Robert; Swindlehurst, A. Lee (IEEE Journal on Selected Areas in Communications, 2021)
Due to the advancements in cellular technologies and the dense deployment of cellular infrastructure, integrating unmanned aerial vehicles (UAVs) into the fifth-generation (5G) and beyond cellular networks is a promising solution to achieve safe UAV operation as well as enabling diversified applications with mission-specific payload data delivery. In particular, 5G networks need to support three typical usage scenarios, namely, enhanced mobile broadband (eMBB), ultra-reliable low-latency communications (URLLC), and massive machine-type communications (mMTC). On the one hand, UAVs can be leveraged as cost-effective aerial platforms to provide ground users with enhanced communication services by exploiting their high cruising altitude and controllable maneuverability in three-dimensional (3D) space. On the other hand, providing such communication services simultaneously for both UAV and ground users poses new challenges due to the need for ubiquitous 3D signal coverage as well as the strong air-ground network interference. Besides the requirement of high-performance wireless communications, the ability to support effective and efficient sensing as well as network intelligence is also essential for 5G-and-beyond 3D heterogeneous wireless networks with coexisting aerial and ground users. In this paper, we provide a comprehensive overview of the latest research efforts on integrating UAVs into cellular networks, with an emphasis on how to exploit advanced techniques (e.g., intelligent reflecting surface, short packet transmission, energy harvesting, joint communication and radar sensing, and edge intelligence) to meet the diversified service requirements of next-generation wireless systems. Moreover, we highlight important directions for further investigation in future work.
CRIS-Team Scopus Importer:2021-08-20
Keywords: 5G-and-beyond 3D cellular networks; aerial-terrestrial integration; Cellular networks; communication; Drones; Interference; network intelligence; sensing; Sensors; Three-dimensional displays; Unmanned aerial vehicle (UAV); Wireless fidelity; Wireless sensor networks

Active IRS Design for RSMA-based Downlink URLLC Transmission - Darabi, Mostafa; Ghanem, Walid; Jamali, Vahid; Lampe, Lutz; Schober, Robert (IEEE Wireless Communications and Networking Conference, WCNC, 2023)
Rate-splitting multiple access (RSMA) has been proposed as a flexible multiple access scheme for improving interference management in sixth-generation (6G) networks. In particular, the low latency facilitated by RSMA and its robustness against user mobility and imperfect channel state information make it an ideal candidate for the ultra-reliable and low-latency (URLLC) use case in 6G networks. However, since the common message in RSMA needs to be decoded by all the users, the achievable rate of the common message is determined by the user with the poorest channel quality. To overcome this bottleneck, an active intelligent reflecting surface (IRS) can be deployed to enhance the achievable rate of the common stream. However, this comes at the expense of additional power consumption due to the active IRS. In this paper, we consider an active IRS-aided RSMA-based downlink URLLC system and study the resource allocation design for minimization of the power consumption of the base station and the active IRS under quality-of-service constraints for the URLLC users. Our simulation results reveal that active IRSs yield a lower overall power consumption and require a smaller surface size compared to passive IRSs in RSMA-based URLLC systems. Moreover, we show that active IRS-aided RSMA systems consume less power than active IRS-aided space division multiple access (SDMA) systems.
CRIS-Team Scopus Importer:2023-06-02
Keywords: 6G cellular networks; Active IRS; power consumption minimization; RSMA; URLLC

Active RISs: Signal Modeling, Asymptotic Analysis, and Beamforming Design - Zhang, Zijian; Dai, Linglong; Chen, Xibi; Liu, Changhao; Yang, Fan; Schober, Robert; Poor, H. Vincent (2022 IEEE Global Communications Conference, GLOBECOM 2022 - Proceedings, 2022)
Reconfigurable intelligent surfaces (RISs) have emerged as a candidate technology for future 6G networks. However, due to the 'multiplicative fading' effect, the existing passive RISs only achieve a negligible capacity gain in environments with strong direct links. In this paper, the concept of active RISs is studied to overcome this fundamental limitation. Unlike the existing passive RISs that reflect signals without amplification, active RISs can amplify the reflected signals via amplifiers integrated into their elements. To characterize the signal amplification and incorporate the noise introduced by the active components, we verify the signal model of active RISs through the experimental measurements on a fabricated active RIS element. Based on the verified signal model, we formulate the sum-rate maximization problem for an active RIS aided multi-user multiple-input single-output (MU-MISO) system and a joint transmit precoding and reflect beamforming algorithm is proposed to solve this problem. Simulation results show that, in a typical wireless system, the existing passive RISs can realize only a negligible sum-rate gain of 3%, while the active RISs can achieve a significant sum-rate gain of 62%, thus over coming the 'multiplicative fading' effect. Finally, we develop a 64-element active RIS aided wireless communication prototype, and the significant gain of active RISs is validated by field test.
CRIS-Team Scopus Importer:2023-03-07

Active RIS vs. Passive RIS: Which Will Prevail in 6G? - Zhang, Zijian; Dai, Linglong; Chen, Xibi; Liu, Changhao; Yang, Fan; Schober, Robert; Vincent Poor, H. (IEEE Transactions on Communications, 2022)
As a revolutionary paradigm for controlling wireless channels, reconfigurable intelligent surfaces (RISs) have emerged as a candidate technology for future 6G networks. However, due to the “multiplicative fading” effect, the existing passive RISs only achieve limited capacity gains in many scenarios with strong direct links. In this paper, the concept of active RISs is proposed to overcome this fundamental limitation. Unlike passive RISs that reflect signals without amplification, active RISs can amplify the reflected signals via amplifiers integrated into their elements. To characterize the signal amplification and incorporate the noise introduced by the active components, we develop and verify the signal model of active RISs through the experimental measurements based on a fabricated active RIS element. Based on the verified signal model, we further analyze the asymptotic performance of active RISs to reveal the substantial capacity gain they provide for wireless communications. Finally, we formulate the sum-rate maximization problem for an active RIS aided multi-user multiple-input single-output (MU-MISO) system and a joint transmit beamforming and reflect precoding scheme is proposed to solve this problem. Simulation results show that, in a typical wireless system, passive RISs can realize only a limited sum-rate gain of 22%, while active RISs can achieve a significant sum-rate gain of 130%, thus overcoming the “multiplicative fading” effect.
CRIS-Team Scopus Importer:2023-03-07
Keywords: active RIS; Array signal processing; beamforming; Fading channels; Propagation losses; Receivers; Reconfigurable intelligent surface (RIS); signal model; Signal to noise ratio; Transmitters; Wireless communication

Adaptive coherent Lp-norm combining - Nasri, Amir; Nezampour, Ali; Schober, Robert (IEEE International Conference on Communications, 2009)
In this paper, we introduce an adaptive Lp-norm metric for robust coherent diversity combining in non-Gaussian noise and interference. We derive a general closed-form expression for the asymptotic bit error rate (BER) for Lp-norm combining in independent non-identically distributed Ricean fading and non-Gaussian noise and interference with finite moments. Based on this asymptotic BER expression, the metric parameters can be adapted to the underlying type of noise and interference using a finite difference stochastic approximation (FDSA) algorithm. Simulation results confirm the validity of the derived asymptotic BER expression and the excellent performance of the proposed adaptive Lp-norm metric. ©2009 Crown.
CRIS-Team Scopus Importer:2020-02-03

Adaptive energy consumption scheduling with load uncertainty for the smart grid - Samadi, Pedram; Mohsenian-Rad, Hamed; Wong, Vincent W.S.; Schober, Robert (IEEE International Conference on Communications, 2013)
In this paper, we propose a novel real-time energy consumption scheduling algorithm that takes into account load uncertainty to minimize the energy payment for each user. We formulate the problem of load scheduling as an optimization problem. To reduce the computational complexity, we devise an approximate dynamic programming approach to schedule the operation of appliances. In our problem formulation, we consider different sets of appliances including must-run and controllable. Unlike most of the existing demand side management algorithms that assume perfect knowledge of users' energy needs, our design only requires knowledge of some estimates of the future demand. Simulation results confirm that the proposed energy scheduling algorithm can benefit both the users by reducing their energy expenses and the utility companies by improving the peak-to-average ratio in load demand. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Adaptive Joint Interference Cancellation and Space-Time Block Decoding for IEEE 802.11b WLAN Systems - Jonietz, Christof; Gerstacker, Wolfgang; Rohde, Christian; Koch, Wolfgang; Schober, Robert (Conference Proceedings, 2006)
Digital transmission in wireless local area networks (WLANs) according to the IEEE 802.11b standard suffers from fading, intersymbol interference (ISI), and co-channel interference (CCI). In this paper, receivers with joint interference cancellation and time-reversal space-time block decoding (JICSTD) are proposed for an enhanced version of the IEEE 802.11b WLAN standard with space-time coded transmission. In IEEE 802.11b, complementary code keying (CCK) with a maximum data rate of 11 Mbit/s is employed as modulation format. The proposed receivers perform JICSTD in a first stage and equalization in a second stage. Minimum mean-squared error (MMSE-)JICSTD presuming perfect channel knowledge for all users and a training based least-squares (LS-)JICSTD for asynchronous interference are investigated, respectively. For subsequent equalization block-based reduced-state sequence estimation (RSSE) tailored for CCK transmission is used.<br
UnivIS-Import:2015-04-16:Pub.2006.tech.IE.mobilk.adapti
Keywords: Silicon; Adaptation model

Adaptive Lp-norm diversity combining in non-gaussian noise and interference - Nasri, Amir; Nezampour, Ali; Schober, Robert (IEEE Transactions on Wireless Communications, 2009)
In this paper, we introduce an adaptive Lp-norm metric for robust coherent, differential, and noncoherent diversity combining in non-Gaussian noise and interference. We consider the general case where all diversity branches may use different combining weights and different L p-norms. We derive a general closed-form expression for the asymptotic bit error rate (BER) for Lp-norm combining in independent non-identically distributed Ricean fading and non-Gaussian noise and interference with finite moments. The asymptotic BER expression reveals that the diversity gain of Lp-norm combining is independent of the type of noise and the metric parameters. In contrast, the combining gain depends on both the type of noise and the metric parameters. Thus, the asymptotic BER can be minimized by optimizing the Lp-norm metric parameters for the underlying type of noise. For this purpose finite difference stochastic approximation (FDSA) and localized random search (LRS) algorithms are developed. Both adaptive algorithms do not require any a priori knowledge about the underlying noise and are able to track changes in the noise statistics. Simulation results confirm the validity of the derived asymptotic BER expressions, the effectiveness of the proposed adaptive algorithms, and the excellent performance of the proposed adaptive Lp-norm metric compared to other popular metrics. © 2006 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Adaptive stochastic optimization; Asymptotic performance analysis; Diversity combining; L; Metric optimization; Non-Gaussian noise and interference

Adaptive Lp-norm metric for secondary BICM-OFDM systems - Nasri, Amir; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2009)
The frequency bands used by secondary systems such as cognitive radio (CR) and ultra-wideband (UWB) systems are subject to various forms of non-Gaussian noise and interference including co-channel interference caused by the primary user and other secondary systems and man-made impulsive noise. For secondary systems employing the popular combination of bit-interleaved coded modulation (BICM) and orthogonal frequency division multiplexing (OFDM) it has been recently shown that robustness against the negative effects of non-Gaussian impairments can be achieved by replacing the conventional L2-norm metric for Viterbi decoding with an Lp-norm metric. However, in order to achieve high performance, the metric parameter p has to be optimized for the underlying type of noise. In this paper, we propose two adaptive algorithms for online optimization of p. The first algorithm is based on a maximum-likelihood parameter estimation framework. The second algorithm is based on the direct minimization of the asymptotic bit error rate of Lp-norm decoding. Simulation results show that both algorithms have excellent performance and that the resulting adaptive Lp-norm metric outperforms other popular metrics in non-Gaussian noise channels.
CRIS-Team Scopus Importer:2020-02-03

Adaptive Lp-Norm spectrum sensing for cognitive radio networks - Moghimi, Farzad; Nasri, Amir; Schober, Robert (IEEE Transactions on Communications, 2011)
In cognitive radio (CR) systems, reliable spectrum sensing techniques are required in order to avoid interference to the primary users of the spectrum. Whereas most of the existing literature on spectrum sensing considers impairment by additive white Gaussian noise (AWGN) only, in practice, CRs also have to cope with various types of nonGaussian noise such as manmade impulsive noise, cochannel interference, and ultrawideband interference. In this paper, we propose an adaptive Lp-norm detector which does not require any a priori knowledge about the primary user signal and performs well for a wide range of circularly symmetric nonGaussian noises with finite moments. We analyze the probabilities of false alarm and missed detection of the proposed detector in Rayleigh fading in the low signaltonoise ratio regime and investigate its asymptotic performance if the number of samples available for spectrum sensing is large. Furthermore, we consider the deflection coefficient for optimization of the Lp-norm parameters and discuss its connection to the probabilities of false alarm and missed detection. Based on the deflection coefficient an adaptive algorithm for online optimization of the L p-norm parameters is developed. Analytical and simulation results show that the proposed Lp-norm detector yields significant performance gains compared to conventional energy detection in nonGaussian noise and approaches the performance of the locally optimal detector which requires knowledge of the noise distribution. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: asymptotic analysis; Cognitive radio; energy detection; locally optimal detection; nonGaussian noise; spectrum sensing

Adaptive mode selection for bidirectional relay networks - Fixed rate transmission - Jamali, Vahid; Zlatanov, Nikola; Schober, Robert (2014 IEEE International Conference on Communications, ICC 2014, 2014)
In this paper, we consider the problem of sum throughput maximization for bidirectional relay networks with block fading. Thereby, user 1 and user 2 exchange information only via a relay node, i.e., a direct link between both users is not present. We assume that channel state information at the transmitter (CSIT) is not available and/or only one coding and modulation scheme is used at the transmitters due to complexity constraints. Thus, the nodes transmit with a fixed predefined rate regardless of the channel state information (CSI). In general, the nodes in the network can assume one of three possible states in each time slot, namely the transmit, receive, and silent state. Most of the existing protocols assume a fixed schedule for the sequence of the states of the nodes. In this paper, we abandon the restriction of having a fixed and predefined schedule and propose a new protocol which, based on the CSI at the receiver (CSIR), selects the optimal states of the nodes in each time slot such that the sum throughput is maximized. To this end, the relay has to be equipped with two buffers for storage of the information received from the two users. Numerical results show that the proposed protocol significantly outperforms the existing protocols. © 2014 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Adaptive mode selection in bidirectional buffer-aided relay networks with fixed transmit powers - Jamali, Vahid; Zlatanov, Nikola; Ikhlef, Aissa; Schober, Robert (European Signal Processing Conference, 2013)
We consider a bidirectional network in which two users exchange information with the help of a buffer-aided relay. In such a network without direct link between user 1 and user 2, there exist six possible transmission modes, i.e., four point-to-point modes (user 1-to-relay, user 2-to-relay, relay-to-user 1, relay-to-user 2), a multiple access mode (both users to the relay), and a broadcast mode (the relay to both users). Because of the buffering capability at the relay, the transmissions in the network are not restricted to adhere to a predefined schedule, and therefore, all the transmission modes in the bidirectional relay network can be used adaptively based on the instantaneous channel state information (CSI) of the involved links. For the considered network, assuming fixed transmit powers for both the users and the relay, we derive the optimal transmission mode selection policy which maximizes the sum rate. The proposed policy selects one out of the six possible transmission modes in each time slot based on the instantaneous CSI. Simulation results confirm the effectiveness of the proposed protocol compared to existing protocols. © 2013 EURASIP.
CRIS-Team Scopus Importer:2020-02-03

Adaptive relay selection protocol for the parallel hybrid RF/FSO relay channel - Najafi Kalyani, Marzieh; Jamali Kooshkghazi, Vahid; Schober, Robert (2016 IEEE International Conference on Communications (ICC), 2016)
Hybrid radio frequency (RF)/free space optical (FSO) systems are among the candidate enabling technologies for the next generation of wireless networks since they benefit from the advantages of both the FSO subsystem, e.g. high data rates, and the RF subsystem, e.g. high reliability in terms of link connectivity. In this paper, we focus on the problem of throughput maximization in the parallel hybrid RF/FSO relay channel. In the parallel hybrid RF/FSO relay channel, a source node sends its data to a destination node with the help of multiple relay nodes. Thereby, the source-relay and the relay-destination FSO links are orthogonal with respect to each other due to the narrow beam employed for FSO transmission whereas the RF links are half duplex with respect to each other due to the broadcast nature of RF signals. We derive the optimal relay selection policies for transmission and reception for the RF and FSO links and the optimal time allocation policy to the RF relay reception and transmission links. Simulation results demonstrate that a considerable gain can be achieved by the proposed adaptive protocol in comparison with benchmark schemes from the literature.<br
Keywords: Radio frequency; Relays; Optical Transmitters; Protocols; Throughput; RF Signals; Receivers

Adaptive resource allocation for the fading interference channel with source cooperation - Najafi Kalyani, Marzieh; Jamah, Vahid; Schober, Robert (2015 Iran Workshop on Communication and Information Theory (IWCIT), 2015)
In this paper, we consider the Gaussian interference channel consisting of two source-destination pairs where the sources cooperate to transmit their messages to their respective destination. We assume block fading and that the nodes are constrained to half-duplex operation. For this channel, assuming availability of channel state information (CSI), we determine the optimal adaptive scheduling of reception and transmission at the source nodes. Thereby, the proposed protocol chooses one of the information flows, decides whether to transmit directly or cooperatively to the corresponding destination, and specifies the required transmission strategy such that the achievable ergodic rate region is maximized. Numerical results reveal that the proposed protocol can effectively realize the diversity offered by the fading processes of the different links in the interference channel.<br

A delay-constrained protocol with adaptive mode selection for bidirectional relay networks - Jamali Kooshkghazi, Vahid; Zlatanov, Nikola; Schober, Robert (2014 IEEE Global Communications Conference, 2014)
In this paper, we consider a bidirectional relay network with half-duplex nodes and block fading where the nodes transmit with a fixed transmission rate. Thereby, user 1 and user 2 exchange information only via a relay node, i.e., a direct link between both users is not present. Recently in [1], it was shown that a considerable gain in terms of sum throughput can be obtained in bidirectional relaying by optimally selecting the transmission modes or, equivalently, the states of the nodes, i.e., the transmit, the receive, and the silent states, in each time slot based on the qualities of the involved links. To enable adaptive transmission mode selection, the relay has to be equipped with two buffers for storage of the data received from the two users. However, the protocol proposed in [1] was delay-unconstrained and provides an upper bound for the performance of practical delay-constrained protocols. In this paper, we propose a heuristic but efficient delay-constrained protocol which can approach the performance upper bound reported in [1]. Moreover, the average throughput and delay of the protocol are evaluated by analyzing the Markov chain of the states of the queues.<br
Keywords: Protocols; Delays; Relays; Signal to noise ratio; Throughput; Fading; Markov processes

A distributed market framework for mobile data offloading - Wang, Kehao; Lau, Francis C. M.; Chen, Lin; Schober, Robert (2015 IEEE International Conference on Communications (ICC), 2015)
We develop a distributed market framework to price the offloading service, and conduct a detailed analysis of the incentives for offloading service providers and conflicts arising from the interactions of different participators. Specifically, we formulate a multi-leader multi-follower Stackelberg game (MLMF-SG) to model the interactions between the offloading service providers and the offloading service consumers in the considered market framework, and investigate the cases where the offloading capacity of APs is unlimited and limited, respectively. For the case without capacity limit, we decompose the followers' game of the MLMF-SG (FG-MLMF-SG) into a number of simple follower games (FGs), and prove the existence and uniqueness of the equilibrium of the FGs from which the existence and uniqueness of the FG-MLMF-SG also follows. For the leaders' game of the MLMF-SG, we also prove the existence and uniqueness of the equilibrium. For the case with capacity limit, by considering a symmetric strategy profile, we establish the existence and uniqueness of the equilibrium of the corresponding MLMF-SG, and present a distributed algorithm that allows the leaders to achieve the equilibrium. Finally, extensive numerical experiments demonstrate that the Stackelberg equilibrium is very close to the corresponding social optimum for both considered cases.<br
Keywords: Games; Radio frequency; Mobile communication; Mobile computing; Pricing; Wireless communication; IEEE 802.11 Standard

Advanced demand side management for the future smart grid using mechanism design - Samadi, Pedram; Mohsenian-Rad, Hamed; Schober, Robert; Wong, Vincent W. S. (IEEE Transactions on Smart Grid, 2012)
In the future smart grid, both users and power companies can potentially benefit from the economical and environmental advantages of smart pricing methods to more effectively reflect the fluctuations of the wholesale price into the customer side. In addition, smart pricing can be used to seek social benefits and to implement social objectives. To achieve social objectives, the utility company may need to collect various information about users and their energy consumption behavior, which can be challenging. In this paper, we propose an efficient pricing method to tackle this problem. We assume that each user is equipped with an energy consumption controller (ECC) as part of its smart meter. All smart meters are connected to not only the power grid but also a communication infrastructure. This allows two-way communication among smart meters and the utility company. We analytically model each user's preferences and energy consumption patterns in form of a utility function. Based on this model, we propose a Vickrey-Clarke-Groves (VCG) mechanism which aims to maximize the social welfare, i.e., the aggregate utility functions of all users minus the total energy cost. Our design requires that each user provides some information about its energy demand. In return, the energy provider will determine each user's electricity bill payment. Finally, we verify some important properties of our proposed VCG mechanism for demand side management such as efficiency, user truthfulness, and nonnegative transfer. Simulation results confirm that the proposed pricing method can benefit both users and utility companies. © 2010-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Demand side management; energy consumption control; smart grid; VCG mechanism design

Advanced optical wireless communication systems - Arnon, Shlomi; Barry, John R.; Karagiannidis, George K.; Schober, Robert; Uysal, Murat (Cambridge University Press, 2012)
Optical wireless communications is a dynamic area of research and development. Combining fundamental theory with a broad overview, this book is an ideal reference for anyone working in the field, as well as a valuable guide for self-study. It begins by describing important issues in optical wireless theory, including coding and modulation techniques for optical wireless, wireless optical CDMA communication systems, equalization and Markov chains in cloud channels and optical MIMO systems, as well as explaining key issues in information theory for optical wireless channels. The next section describes unique channels that could be found in optical wireless applications, such as NLOS UV atmospheric scattering channels, underwater communication links and a combination of hybrid RF/optical wireless systems. The final section describes applications of optical wireless technology, such as quantum encryption, visible light communication, IR links and sensor networks, with step-by-step guidelines to help reduce design time and cost.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Communications and Signal Processing; Engineering; Electronic; Optoelectronic Devices; Nanotechnology

Advanced target detection via molecular communication - Mosayebi, Reza; Wicke, Wayan; Jamali Kooshkghazi, Vahid; Ahmadzadeh, Arman; Schober, Robert; Nasiri-Kenari, Masouhmeh (IEEE GlobeCom 2018, 2018)

A Framework for Transmission Design for Active RIS-Aided Communication with Partial CSI - Zhou, Gui; Pan, Cunhua; Ren, Hong; Xu, Dongfang; Zhang, Zaichen; Wang, Jiangzhou; Schober, Robert (IEEE Transactions on Wireless Communications, 2023)
Active reconfigurable intelligent surfaces (RISs) have recently been proposed to compensate for the severe multiplicative fading effect of conventional passive RIS-aided systems. Each reflecting element of active RISs is assisted by an amplifier such that the incident signal can be reflected and amplified instead of only being reflected as in passive RIS-aided systems. This work addresses the practical challenge that, on the one hand, in active RIS-aided systems the perfect individual channel state information (CSI) of the RIS-aided channels cannot be acquired due to the lack of signal processing power at the active RISs, but, on the other hand, this CSI is required to calculate the expected system data rate and RIS transmit power needed for transceiver design. To address this issue, we first derive closed-form expressions for the average achievable rate and the average RIS transmit power based on partial CSI of the RIS-aided channels. Then, we formulate an average achievable rate maximization problem for jointly optimizing the active beamforming at both the base station (BS) and the RIS. This problem is then tackled using the majorization–minimization (MM) algorithm framework, and, in each iteration low-complexity solutions for the BS and RIS beamforming are found based on the Karush-Kuhn-Tucker (KKT) conditions. To ensure the quality of service (QoS) of each user, we further formulate a rate outage constrained beamforming problem, which is solved using the Bernstein-Type inequality (BTI) and semidefinite relaxation (SDR) techniques. Numerical results show that the proposed algorithms can efficiently overcome the challenges imposed by imperfect CSI in active RIS-aided wireless systems.
CRIS-Team Scopus Importer:2023-06-16
Keywords: active RIS; beamforming; intelligent reflecting surface (IRS); partial channel state information (CSI); Reconfigurable intelligent surface (RIS)

A game-theoretic analysis of inter-session network coding - Mohsenian-Rad, A. Hamed; Huang, Jianwei; Wong, Vincent W.S.; Jaggi, Sidharth; Schober, Robert (IEEE International Conference on Communications, 2009)
A common assumption in the network coding literature is that the users are cooperative and will not pursue their own interests. However, this assumption can be violated in practice. In this paper, we analyze inter-session network coding in a wired network, assuming that the users are selfish and act as strategic players to maximize their own utility. We prove the existence of Nash equilibria for a wide range of utility functions. The number of Nash equilibria can be large (even infinite) under certain conditions, which is in sharp contrast to a similar game setting with traditional packet forwarding. We then characterize the worst-case efficiency bounds, i.e., the price-of-anarchy (PoA), compared to an optimal and cooperative network design. We show that by using a novel discriminatory pricing scheme that charges encoded and forwarded packets differently, we can improve PoA in comparison with the case where a single pricing scheme is being used. However, PoA is still worse than the case when network coding is not applied. This implies that intersession network coding is more sensitive to strategic behavior. For example, for the case where only two network coding flows share a single bottleneck link, the efficiency at certain Nash equilibria can be as low as 48%. These results generalize the well-known result of guaranteed 67% efficiency bounds shown by Johari and Tsitsiklis for traditional packet forwarding networks. ©2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03

A General MIMO Framework for NOMA Downlink and Uplink Transmission Based on Signal Alignment - Ding, Zhiguo; Schober, Robert; Poor, H. Vincent (IEEE Transactions on Wireless Communications, 2016)
The application of multiple-input multiple-output (MIMO) techniques to nonorthogonal multiple access (NOMA) systems is important to enhance the performance gains of NOMA. In this paper, a novel MIMO-NOMA framework for downlink and uplink transmission is proposed by applying the concept of signal alignment. By using stochastic geometry, closed-form analytical results are developed to facilitate the performance evaluation of the proposed framework for randomly deployed users and interferers. The impact of different power allocation strategies, namely fixed power allocation and cognitive radio inspired power allocation, on the performance of MIMO-NOMA is also investigated. Computer simulation results are provided to demonstrate the performance of the proposed framework and the accuracy of the developed analytical results.<br
Keywords: Base stations; Interference; Resource management; Downlink; MIMO; Antennas; Uplink

Age of Information: Can CR-NOMA Help? - Ding, Zhiguo; Schober, Robert; Vincent Poor, H. (IEEE Transactions on Communications, 2023)
The aim of this paper is to exploit cognitive-radio inspired NOMA (CR-NOMA) transmission to reduce the age of information in wireless networks. In particular, two CR-NOMA transmission protocols are developed by utilizing the key features of different data generation models and applying CR-NOMA as an add-on to a legacy orthogonal multiple access (OMA) based network. The fact that the implementation of CR-NOMA causes little disruption to the legacy OMA network means that the proposed CR-NOMA protocols can be practically implemented in various communication systems which are based on OMA. Closed-form expressions for the AoI achieved by the proposed NOMA protocols are developed to facilitate performance evaluation, and asymptotic studies are carried out to identify two benefits of using NOMA to reduce the AoI in wireless networks. One is that the use of NOMA provides users more opportunities to transmit, which means that the users can update their base station more frequently. The other is that the use of NOMA can reduce access delay, i.e., the users are scheduled to transmit earlier than in the OMA case, which is useful to improve the freshness of the data available in the wireless network.
CRIS-Team Scopus Importer:2023-09-29
Keywords: Base stations; Data models; NOMA; Protocols; Signal to noise ratio; Time division multiple access; Wireless networks

Aggregate Preamble Sequence Design and Detection for Massive IoT with Deep Learning - Mostafa, Ahmed Elhamy; Wong, Vincent W.S.; Zhou, Yong; Schober, Robert; Luo, Zhe; Liao, Shuri; Ding, Mengying (IEEE Transactions on Vehicular Technology, 2021)
Massive Internet of Things (mIoT) is a major use case of the fifth generation (5G) wireless systems. mIoT aims to support a large number of connection requests from the IoT devices. However, the conventional Long Term Evolution (LTE) random access procedure hinders the support of mIoT due to the limited number of available preambles. In this paper, we propose to aggregate two Zadoff-Chu preamble sequences from two different roots to obtain a larger set of preambles by considering all possible combinations of preamble sequence pairs. Decoding the aggregate preambles is challenging because the receiver needs to decode two preamble sequences where each one is allocated half of the transmit power. We propose two receiver architectures for preamble decoding. The first one is a threshold-based receiver which only requires minor changes to the LTE preamble receiver architecture. The second proposed preamble decoder architecture exploits a deep neural network. Simulations show that the proposed aggregate preamble design results in a lower service time for backlogged IoT devices compared to existing collision avoidance techniques. Moreover, the proposed receiver architectures can decode the aggregate preambles with low probabilities of misdetection and false alarms (less than 11%), especially in the high signal-to-noise ratio (SNR) regime.
CRIS-Team Scopus Importer:2021-03-26
Keywords: 5G mobile communication; Aggregates; deep neural networks; Internet of Things; Long Term Evolution; Massive Internet of Things (mIoT); preamble sequence design; Radio transmitters; random access; Receivers; Signal to noise ratio

Aggregate Preamble Sequence Design for Massive Machine-Type Communications in 5G Networks - Mostafa, Ahmed Elhamy; Wong, Vincent W.S.; Liao, Shuri; Schober, Robert; Ding, Mengying; Wang, Fan (2018 IEEE Global Communications Conference, GLOBECOM 2018 - Proceedings, 2019)
Massive machine-type communications (mMTC) is a major use case in the fifth generation (5G) wireless networks. mMTC aims at supporting a large number of Internet of Things (IoT) connections within a coverage area. The current random access procedure in the Long Term Evolution (LTE) networks may not be able to handle a large number of simultaneous connection requests due to the limited number of random access preambles. Hence, it is essential to modify the random access procedure to support mMTC. In this paper, we propose a new preamble sequence design in which two Zadoff-Chu preamble sequences are aggregated together. This design enables us to have a larger set of random access preambles consisting of all combinations of pairing two Zadoff-Chu preamble sequences. Moreover, we consider a subset of all combinations that satisfy a certain maximum peak-to-average-power-ratio (PAPR) threshold criterion to reduce the energy consumption of the IoT devices. The proposed design requires only minor changes in the conventional transmitter and receiver design for generating and decoding the aggregated preamble sequences, respectively. Results show that the proposed design reduces the probability of preamble collision to less than 10--4, which is lower than LTE. Furthermore, it outperforms other collision avoidance techniques such as access class barring (ACB) in terms of a lower average total service time. The modified receiver detects the aggregated preambles successfully and avoids detecting false preambles. Both the probabilities of misdetection and false alarm are less than 10--3 when the signal-to-noise ratio (SNR) is larger than-7 dB.
CRIS-Team Scopus Importer:2019-05-02

A low-complexity linear precoding and power allocation scheme for downlink massive MIMO systems - Zarei, Shahram; Gerstacker, Wolfgang; Schober, Robert (2013 Asilomar Conference on Signals, Systems and Computers, 2014)
In this paper, we present a low-complexity linear precoding and power allocation scheme for downlink massive multiple-input multiple-output (MIMO) systems. The optimization criteria adopted for the proposed precoding and power allocation scheme are maximization of the sum rate and maximization of the minimum user rate, respectively. The presented precoder is based on a matrix polynomial and can closely approach the sum rate and the minimum user rate of the optimal regularized zero forcing (RZF) precoder, which requires a matrix inversion, and performs substantially better than the simple conjugate beamforming (BF) precoder. Our simulation results show that the proposed precoding scheme with a low order matrix polynomial can approach the sum rate and the minimum user rate of the optimal RZF precoder. We also present analytical results for the asymptotic sum rate and the asymptotic minimum user rat

A Minimum Error Probability NOMA Design - Wang, Yuan; Wang, Jiaheng; Ng, Derrick Wing Kwan; Schober, Robert; Gao, Xiqi (IEEE Transactions on Wireless Communications, 2021)
Non-orthogonal multiple access (NOMA) enables massive connectivity and achieves high spectral efficiency. The vast majority of the NOMA literature has adopted the ideal information rate as performance metric assuming perfect successive interference cancellation (SIC) without any error propagation, which, however, may lead to NOMA designs adverse to SIC. In this paper, we take into account imperfect SIC and practical modulation schemes for power-domain NOMA design. To characterize the error propagation, we derive the bit error rates (BERs) of the users for arbitrary-order quadrature amplitude modulation (QAM) schemes. Then, we propose a minimum error probability NOMA (MEP-NOMA) design, minimizing the average BER of the users via power allocation. Considering the complicated error probability expressions of the MEP-NOMA design, we derive lower and upper bounds on the average BER, based on which a simple closed-form power allocation is obtained. We show that the proposed power allocation minimizes both the lower and upper bounds on the average BER for a sufficiently large power budget and provides near-optimal error performance. On this basis, we theoretically prove the superiority of MEP-NOMA over existing OMA and NOMA schemes in terms of error performance. Comprehensive numerical results are provided to verify the accuracy of the error probability analysis of the considered practical NOMA scheme with imperfect SIC and to demonstrate the efficacy of the proposed MEP-NOMA design.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Error propagation; imperfect successive interference cancellation; minimum error probability; non-orthogonal multiple access; power allocation; quadrature amplitude modulation

A Molecular Communication Testbed Based on Proton Pumping Bacteria: Methods and Data - Grebenstein, Laura; Kirchner, Jens; Wicke, Wayan; Ahmadzadeh, Arman; Jamali Kooshkghazi, Vahid; Fischer, Georg; Weigel, Robert; Burkovski, Andreas; Schober, Robert (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2019)
This paper presents a detailed description of a recent biological molecular communication (MC) testbed and provides a set of experimental measurement data. In particular, the MC testbed is realized using Escherichia coli (E. coli) bacteria that express the light-driven proton pump gloeorhodopsin (GR) from Gloeobacter violaceus (G. violaceus). Upon an external light stimulus, these bacteria (as the transmitter) export protons (as the signaling molecules) into the channel. This changes the pH level of the environment, which can be detected with a pH sensor (as the receiver). To facilitate future advancement in the experimentation of MC systems, in this paper, we explain the methodology used for the development of our testbed and discuss the reasoning behind the choices made throughout its evolution. Moreover, we provide different categories of measurement data obtained with the testbed. The data set is expected to facilitate and promote the experimental evaluation of communication schemes developed by the MC community.
CRIS-Team Scopus Importer:2021-04-20

Amplify-and-forward cooperative diversity for BICM-OFDM systems - Islam, Toufiqul; Schober, Robert; Mallik, Ranjan K.; Bhargava, Vijay K. (GLOBECOM - IEEE Global Telecommunications Conference, 2010)
In this paper, we propose a novel amplify-and-forward cooperative diversity scheme for wireless systems using the combination of bit-interleaved coded modulation (BICM) and orthogonal frequency division multiplexing (OFDM). In the proposed scheme, multiple relays transmit concurrently over disjoint sets of sub-carriers. A careful joint design of the sub-carrier allocation at the relays and the interleaver at the source ensures that the proposed scheme can exploit the maximum spatial and frequency diversity offered by the wireless channel. An upper bound on the asymptotic worst-case pairwise error probability of the proposed cooperative diversity scheme is developed which provides insight into to the influence of various code and channel parameters on performance. Simulation results corroborate the analytical results regarding the diversity gain of the system and confirm the effectiveness of a newly developed relay selection criterion. ©2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Amplify-and-forward multi-antenna beamforming with joint source-relay power constraint - Liang, Yang Wen; Schober, Robert (IEEE Vehicular Technology Conference, 2010)
In this paper, we consider beamforming (BF) for cooperative networks with one multi-antenna source, multiple multi-antenna amplify-and-forward (AF) relays, and one single-antenna destination. The source BF vector and the AF-BF matrices at the relays are optimized for maximization of the signal-to-noise ratio at the destination under a joint power constraint for the source and the relays. We solve the associated optimization problem in two stages. In the first stage, we find the optimal AF-BF matrices for a given BF vector at the source. In particular, the direction of the AF-BF matrices is derived in closed form and an efficient numerical algorithm for the convex power allocation problem between the source and the relays is provided. In the second stage, the optimal source BF vectors are computed. Thereby, we show that the resulting problem can be transformed into a non-convex polynomial programming problem which allows for an exact solution for small-scale networks. For large-scale networks, we propose efficient suboptimal optimization methods for the source BF vector. ©2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Amplify-and-Forward Relaying in Two-Hop Diffusion-Based Molecular Communication Networks - Ahmadzadeh, Arman; Noel, Adam; Burkovski, Andreas; Schober, Robert (2015 IEEE Global Communications Conference (GLOBECOM), 2015)
This paper studies a three-node network in which an intermediate nano-transceiver, acting as a relay, is placed between a nano-transmitter and a nano-receiver to improve the range of diffusion- based molecular communication. Motivated by the relaying protocols used in traditional wireless communication systems, we study amplify-and- forward (AF) relaying with fixed and variable amplification factor for use in molecular communication systems. To this end, we derive a closed-form expression for the expected end-to-end error probability. Furthermore, we derive a closed-form expression for the optimal amplification factor at the relay node for minimization of an approximation of the expected error probability of the network. Our analytical and simulation results show the potential of AF relaying to improve the overall performance of nano-networks.<br
Keywords: Relays; Error probability; Protocols; Molecular communication; Closed-form solutions; Numerical models; Microorganisms

Amplify-and-forward relay selection with outdated channel estimates - Michalopoulos, Diomidis S.; Suraweera, Himal A.; Karagiannidis, George K.; Schober, Robert (IEEE Transactions on Communications, 2012)
We study the effect of outdated channel state information on the outage and error rate performance of amplify-and-forward (AF) relay selection, where only one out of the set of available relays is activated. We consider two variations of AF relay selection, namely best relay selection and partial relay selection, when the selection is based upon outdated channel estimates. For both these variations, closed-form expressions for the outage probability are obtained, along with approximate expressions for the symbol error rate in the medium to high signal-to-noise-ratio (SNR) regime. The diversity gain and coding gain of the above schemes are also explicitly derived. Numerical results manifest that the outage performance of AF relay selection is highly dependent on the level of correlation between the actual channel conditions and their corresponding (outdated) estimates. This result has a significant impact on the deployment of relay selection in practical applications, implying that a high feedback rate may be required in practice in order to attain the full benefits of relay selection. It is further shown that it may be preferable, in terms of outage and symbol error probability, not to include links in the relay selection process that experience a sufficiently high maximum Doppler shift, since in those cases partial relay selection outperforms best relay selection. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Amplify-and-forward; Outdated channel state information; Relay selection

Amplify-and-forward relay selection with outdated channel state information - Michalopoulos, Diomidis S.; Suraweera, Himal A.; Karagiannidis, George K.; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2010)
We study the effect of outdated channel estimation on the outage performance of amplify-and-forward (AF) relay selection, where only one out of the set of available relays is activated. In particular, we derive closed-form expressions for the outage probability of two variations of AF relay selection, namely best relay selection and partial relay selection, when the selection is based upon outdated channel estimates. Numerical results manifest that the outage performance of both schemes under consideration is highly dependent on the level of imperfection of the channel estimates. It is further shown that it may be preferable, in terms of outage probability, not to include links in the relay selection process that experience high maximum Doppler shifts. ©2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Analysis and design of cooperative BICM-OFDM systems - Islam, Toufiqul; Schober, Robert; Mallik, Ranjan K.; Bhargava, Vijay K. (IEEE Transactions on Communications, 2011)
In this paper, we propose a novel cooperative diversity scheme for wireless systems employing the combination of bitinterleaved coded modulation (BICM) and orthogonal frequency division multiplexing (OFDM). The proposed scheme utilizes an amplifyandforward protocol where relays are assigned to multiple groups. Relays in the same group transmit concurrently over disjoint sets of sub-carriers and relays in different groups transmit in different time slots. We derive closed-form expressions for the asymptotic worstcase pairwise error probability and the diversity gain of the proposed cooperative BICMOFDM scheme. Based on the derived analytical results we develop design guidelines for sub-carrier allocation, relay grouping, and relay selection. Simulation results corroborate the derived analytical results and confirm the effectiveness of the developed optimization framework. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: BICM; cooperative diversity; OFDM

Analysis and Design of Secure Massive MIMO Systems in the Presence of Hardware Impairments - Zhu, Jun; Wing Kwan Ng, Derrick; Wang, Ning; Schober, Robert; Bhargava, Vijay Kishore (IEEE Transactions on Wireless Communications, 2017)
To keep the hardware costs of future communications systems manageable, the use of low-cost hardware components is desirable. This is particularly true for the emerging massive multiple-input multiple-output (MIMO) systems which equip base stations (BSs) with a large number of antenna elements. However, low-cost transceiver designs will further accentuate the hardware impairments, which are present in any practical communication system. In this paper, we investigate the impact of hardware impairments on the secrecy performance of downlink massive MIMO systems in the presence of a passive multiple-antenna eavesdropper. Thereby, for the BS and the legitimate users, the joint effects of multiplicative phase noise, additive distortion noise, and amplified receiver noise are taken into account, whereas the eavesdropper is assumed to employ ideal hardware. We derive a lower bound for the ergodic secrecy rate of a given user when matched filter data precoding and artificial noise (AN) transmission are employed at the BS. Based on the derived analytical expression, we investigate the impact of the various system parameters on the secrecy rate and optimize both the pilot sets used for uplink training and the AN precoding. Our analytical and simulation results reveal that: 1) the additive distortion noise at the BS may be beneficial for the secrecy performance, especially if the power assigned for AN emission is not sufficient; 2) all other hardware impairments have a negative impact on the secrecy performance; 3) despite their susceptibility to pilot interference in the presence of phase noise, so-called spatially orthogonal pilot sequences are preferable unless the phase noise is very strong; and 4) the proposed generalized null-space AN precoding method can efficiently mitigate the negative effects of phase noise.<br
Keywords: MIMO; Phase noise; Hardware; Distortion; Precoding; Additives; Physical layer

Analysis and design of two-hop diffusion-based molecular communication networks - Ahmadzadeh, Arman; Noel, Adam; Schober, Robert (2014 IEEE Global Communications Conference, 2014)
In this paper, we consider a two-hop molecular communication network consisting of one nanotransmitter, one nanoreceiver, and one nanotransceiver acting as a relay. We consider two different schemes for relaying to improve the range of diffusion-based molecular communication. In the first scheme, two different types of messenger molecules are utilized at the relay node for transmission and detection. In the second scheme, we assume that there is only one type of molecule available to be used as an information carrier. We identify self-interference as the performance-limiting effect for the second relaying scheme. Self-interference occurs when the relay must detect the same type of molecule that it also emits. Furthermore, we consider two relaying modes analogous to those used in wireless communication systems, i.e., full-duplex and half-duplex. In particular, while our main focus is on full-duplex relaying, half-duplex relaying is employed as a means to mitigate self-interference. In addition, we propose the adaptation of the decision threshold as an effective mechanism to mitigate self-interference at the relay for full-duplex transmission. We derive closed-form expressions for the expected error probability of the network for both considered relaying schemes.<br
Keywords: Relays; Error probability; Nanobioscience; Random variables; Protocols; Numerical models

Analysis and Optimization of RIS-Aided Massive MIMO with ZF Detectors and Imperfect CSI - Zhi, Kangda; Pan, Cunhua; Zhou, Gui; Ren, Hong; Elkashlan, Maged; Schober, Robert (IEEE International Conference on Communications, 2022)
This paper analyzes and optimizes the reconfigurable intelligent surface (RIS)-aided massive multiple-input multiple-output (MIMO) systems with zero-forcing (ZF) detectors under imperfect channel state information (CSI). We first propose a low-overhead minimum mean square error (MMSE) channel estimator, and then derive and analyze closed-form expressions for the uplink achievable rate. Our analytical results prove that: 1) regardless of the RIS phase shift design, the rate of all users scales at least on the order of mathcalOleft( log _2(MN) right), where M and N are the numbers of antennas and reflecting elements, respectively; 2) by aligning the RIS phase shifts to one user, the rate of this user can at most scale on the order of mathcalOleft( log _2(MN) right). Furthermore, we propose a low-complexity majorization-minimization (MM)-based algorithm to optimize the sum user rate, where closed-form solutions are obtained in each iteration. Finally, simulation results validate all derived analytical results. Our simulation results also show that the maximum sum rate can be closely approached by simply aligning the RIS phase shifts to an arbitrary user.
CRIS-Team Scopus Importer:2022-09-16
Keywords: imperfect CSI; intelligent reflecting surface (IRS); majorization-minimization (MM); massive MIMO; Reconfigurable intelligent surface (RIS); ZF

Analysis and relay placement for DF cooperative BICM-OFDM systems - Islam, Toufiqul; Nasri, Amir; Schober, Robert; Mallik, Ranjan K. (2011 IEEE Wireless Communications and Networking Conference, WCNC 2011, 2011)
In this paper, we study a decodeandforward cooperative diversity scheme for wireless systems using the combination of bitinterleaved coded modulation (BICM) and orthogonal frequency division multiplexing (OFDM). We propose a simple cooperative maximumratio combining scheme for the destination which can successfully exploit the full spatial and frequency diversity offered by the channel. Taking possible decision errors at the relay into account, we develop a closed form upper bound on the asymptotic worstcase pairwise error probability (PEP) of the considered cooperative diversity system which provides insight into the influence of various code and channel parameters on performance. The PEP expression is then exploited for optimal relay placement. Simulation results corroborate the derived analytical results regarding the diversity gain of the system and confirm the effectiveness of the proposed relay placement scheme. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Analysis of Coverage in Heterogeneous Cellular Networks - Lee, Woongsup; Schober, Robert (IEEE Communications Letters, 2016)
In this letter, we study the coverage of base stations (BSs) in heterogeneous cellular networks, where BSs with different transmit powers are randomly deployed. Specifically, the boundary of coverage is formulated analytically as the intersection of circles when a multiplicative bias is applied for BS association. Moreover, the effect of the transmit power and the path loss exponent on the coverage is investigated. Furthermore, for femto BSs with low transmit powers which are deployed to offload the traffic of the cellular system, it is shown that the expected number of offloaded users is concave with respect to the transmit power. Finally, the coverage of BSs is evaluated through simulations, which verify the accuracy of the presented analysis.<br
Keywords: Mobile communication; Analytical models; MIMO; Base stations; Received signal strength indicator; Propagation losses; Indexes

Analysis of MC Systems Employing Receivers Covered by Heterogeneous Receptors - Huang, Xinyu; Fang, Yuting; Johnston, Stuart T.; Faria, Matthew; Yang, Nan; Schober, Robert (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2023)
This paper investigates the channel impulse response (CIR), i.e., the molecule hitting rate, of a molecular communication (MC) system employing an absorbing receiver (RX) covered by multiple non-overlapping receptors. In this system, receptors are heterogeneous, i.e., they may have different sizes and arbitrary locations. Furthermore, we consider two types of transmitter (TX), namely a point TX and a membrane fusion (MF)-based spherical TX. We assume the point TX or the center of the MF-based TX has a fixed distance to the center of the RX. Given this fixed distance, the TX can be at different locations and the CIR of the RX depends on the exact location of the TX. By averaging over all possible TX locations, we analyze the expected molecule hitting rate at the RX as a function of the sizes and locations of the receptors, where we assume molecule degradation may occur during the propagation of the signaling molecules. Notably, our analysis is valid for different numbers, a wide range of sizes, and arbitrary locations of the receptors, and its accuracy is confirmed via particle-based simulations. Exploiting our numerical results, we show that the expected number of absorbed molecules at the RX increases with the number of receptors, when the total area on the RX surface covered by receptors is fixed. Based on the derived analytical expressions, we compare different geometric receptor distributions by examining the expected number of absorbed molecules at the RX. We show that evenly distributed receptors result in a larger number of absorbed molecules than other distributions. We further compare three models that combine different types of TXs and RXs. Compared to the ideal model with a point TX and a fully absorbing RX, the practical model with an MF-based TX and an RX with heterogeneous receptors yields a lower peak CIR, suffers from more severe inter-symbol interference, and gives rise to a higher average bit error rate (BER). This underlines the importance of our analysis of practical TX-RX models since the existing CIR and BER analyses based on the ideal model do not reflect the performance achievable in practice. Numerical results show that different vesicle generation rate results in the same number of molecules harvested by the TX, but a different peak received signal at the RX.
CRIS-Team Scopus Importer:2023-02-10
Keywords: Analytical models; Bit error rate; Cells (biology); channel impulse response; Error probability; heterogeneous receptors; Molecular communications; Numerical models; Receivers; spherical transmitter; Transmitters

Analysis of Receiver Covered by Heterogeneous Receptors in Molecular Communications - Huang, Xinyu; Fang, Yuting; Johnston, Stuart T.; Faria, Matthew; Yang, Nan; Schober, Robert (IEEE International Conference on Communications, 2022)
This paper analyzes the channel impulse response of an absorbing receiver (RX) covered by multiple non-overlapping heterogeneous receptors with different sizes and arbitrary locations in a molecular communication system. In this system, a point transmitter (TX) is assumed to be uniformly located on a virtual sphere at a fixed distance from the RX. Considering molecule degradation during the propagation from the TX to the RX, the expected molecule hitting rate at the RX over varying locations of the TX is analyzed as a function of the size and location of each receptor. Notably, this analytical result is applicable for different numbers, sizes, and locations of receptors, and its accuracy is demonstrated via particle-based simulations. Numerical results show that (i) the expected number of absorbed molecules at the RX increases with an increasing number of receptors, when the total area of receptors on the RX surface is fixed, and (ii) evenly distributed receptors lead to the largest expected number of absorbed molecules.
CRIS-Team Scopus Importer:2022-09-16
Keywords: channel modeling; location of receptors; Molecular communication; size of receptors

Analysis of the behavior of electric vehicle charging stations with renewable generations - Lee, William; Xiang, Lin; Schober, Robert; Wong, Vincent W.S. (2013 IEEE International Conference on Smart Grid Communications, SmartGridComm 2013, 2013)
In this paper, we study the competitive interactions between electric vehicle charging stations (EVCSs) with renewable electricity generation facilities (REGFs). As electric vehicles (EVs) become more popular, there will be a competition between neighboring EVCSs to attract more EVs. Therefore, an EVCS is likely to set its electricity price by taking into account the competition with neighboring EVCSs, such that its revenue is maximized. We model the competitive interactions between EVCSs by using game theory. In this paper, we show that the game played by EVCSs is a supermodular game and there exists a unique pure Nash equilibrium for best response algorithms with arbitrary initial policy. Simulation results confirm the convergence of the game between EVCSs. The results also verify that it is beneficial for both EVs and EVCSs to have REGFs and all EVCSs will have REGFs in the long run. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Analytical Models for Particle Diffusion and Flow in a Horizontal Cylinder with a Vertical Force - Schäfer, Maximilian; Wicke, Wayan; Rabenstein, Rudolf; Schober, Robert (IEEE International Conference on Communications (ICC), 2019)
This paper considers particle propagation in a cylindrical molecular communication channel, e.g. a simplified model of a blood vessel. Emitted particles are influenced by diffusion, flow, and a vertical force induced e.g. by gravity or magnetism. The dynamics of the diffusion process are modeled by multi-dimensional transfer functions in a spatio-temporal frequency domain. Realistic boundary conditions are incorporated by the design of a feedback loop. The result is a discrete-time semi-analytical model for the particle concentration in the channel. The model is validated by comparison to particle-based simulations. These numerical experiments reveal that the particle concentration of the proposed semi-analytical model and the particle-based model are in excellent agreement. The analytical form of the proposed solution provides several benefits over purely numerical models, e.g. high variability, existence of low run-time algorithms, extendability to several kinds of boundary conditions, and analytical connection to parameters from communication theor
Keywords: Numerical models; Eigenvalues and eigenfunctions; Boundary conditions; Diffusion processes; Receivers; Transfer functions; Magnetic forces

An Analysis of Price Competition in Heterogeneous Electric Vehicle Charging Stations - Lee, Woongsup; Schober, Robert; Wong, Vincent W.S. (IEEE Transactions on Smart Grid, 2019)
In this paper, we investigate the price competition among electric vehicle charging stations (EVCSs) with renewable power generators (RPGs). Both a large-sized EVCS (L-EVCS) and small-sized EVCSs (S-EVCSs), which have different capacities, are considered. Moreover, the price elasticity of electric vehicles (EVs), the effect of the distance between an EV and the EVCSs, and the impact of the number and type of charging outlets at the EVCSs on the behavior of EVs are taken into account. The electricity demand of the EVCSs is modeled and analyzed using a multiplicatively weighted Voronoi diagram. The price competition between EVCSs is studied by using a Stackelberg game and the electricity price is determined. Through simulations, the correctness of our analysis is validated and the payoff of the EVCSs is examined for various environments. Our results reveal that although the payoff of the EVCSs is generally small, it is higher than when the electricity from the RPGs is directly sold to the power grid. We also find that the payoff of the EVCSs is significantly affected by the elasticity of the electricity demand of the EVs. Furthermore, the payoff of the L-EVCS is inversely proportional to that of the S-EVCSs.
CRIS-Team Scopus Importer:2019-07-02
Keywords: electric vehicle; Electric vehicle charging station; pricing; renewable power generation; Voronoi diagram

An Analysis of Price Competition in Heterogeneous Electric Vehicle Charging Stations - Lee, Woongsup; Schober, Robert; Wong, Vincent W. S. (IEEE Transactions on Smart Grid, 2018)
In this paper, we investigate the price competition among electric vehicle charging stations (EVCSs) with renewable power generators (RPGs). Both a large-sized EVCS (L-EVCS) and small-sized EVCSs (S-EVCSs), which have different capacities, are considered. Moreover, the price elasticity of electric vehicles (EVs), the effect of the distance between an EV and the EVCSs, and the impact of the number and type of charging outlets at the EVCSs on the behavior of EVs are taken into account. The electricity demand of the EVCSs is modeled and analyzed using a multiplicatively weighted Voronoi diagram. The price competition between EVCSs is studied by using a Stackelberg game and the electricity price is determined. Through simulations, the correctness of our analysis is validated and the payoff of the EVCSs is examined for various environments. Our results reveal that although the payoff of the EVCSs is generally small, it is higher than when the electricity from the RPGs is directly sold to the power grid. We also find that the payoff of the EVCSs is significantly affected by the elasticity of the electricity demand of the EVs. Furthermore, the payoff of the L-EVCS is inversely proportional to that of the S-EVCSs.<br
Keywords: Elasticity; Games; Electric vehicle charging; Plugs; Analytical models; Power grids; Pricing

A new class of distributed space-time trellis codes - Yiu, S.; Schober, Robert (2006 International Waveform Diversity and Design Conference, WDD 2006 - Proceedings, 2018)
In this paper, we develop a new class of distributed space-time trellis codes (DSTTCs). These DSTTCs are designed for wireless networks which have a large set of nodes N but at any given time only a small, a priori unknown subset of nodes S -N can be active. Each node is equipped with a unique signature vector but all active nodes use the same STTC for encoding. Efficient methods for the optimization of the set of signature vectors are provided and it is shown that existing full-rank STTCs designed for Nc ≥ 2 co-located antennas are favorable choices for the trellis encoding. If properly designed, the proposed DSTTCs achieve a diversity order of d = minNc, NS if NS nodes are active. Furthermore, the decoding complexity of the proposed DSTTCs is independent of the number of nodes and identical to that of the underlying STTC. Simulation results show the superior performance of the novel DSTTC compared to distributed space-time filtering.
CRIS-Team Scopus Importer:2020-01-31

A New QoS-Guarantee Strategy for NOMA Assisted Semi-Grant-Free Transmission - Ding, Zhiguo; Schober, Robert; Poor, H. Vincent (IEEE Transactions on Communications, 2021)
Semi-grant-free (SGF) transmission has recently received significant attention due to its capability to accommodate massive connectivity and reduce access delay by admitting grant-free users to channels that would otherwise be solely occupied by grant-based users. In this paper, a new SGF transmission scheme that exploits the flexibility in choosing the decoding order in non-orthogonal multiple access (NOMA) is proposed. Compared to existing SGF schemes, this new scheme can ensure that admitting the grant-free users is completely transparent to the grant-based users, i.e., the grant-based users’ quality-of-service experience is guaranteed to be the same as for orthogonal multiple access. In addition, compared to existing SGF schemes, the proposed SGF scheme can significantly improve the robustness of the grant-free users’ transmissions and effectively avoid outage probability error floors. To facilitate the performance evaluation of the proposed SGF transmission scheme, an exact expression for the outage probability is obtained and an asymptotic analysis is conducted to show that the achievable multi-user diversity gain is proportional to the number of participating grant-free users. Computer simulation results demonstrate the performance of the proposed SGF transmission scheme and verify the accuracy of the developed analytical results.
CRIS-Team Scopus Importer:2021-11-19
Keywords: Base stations; Interference; machine-type communications; NOMA; Non-orthogonal multiple access; Power system reliability; Probability; Quality of service; semi grant free transmission; Silicon carbide; successive interference cancellation (SIC) decoding order

An nD Model for a Cylindrical Diffusion-Advection Problem with an Orthogonal Force Component - Schäfer, Maximilian; Wicke, Wayan; Rabenstein, Rudolf; Schober, Robert (23rd International Conference on Digital Signal Processing (DSP), 2018)
This paper presents a physical and algorithmic model for a complex propagation problem in a long cylinder, resembling a blood vessel or a pipeline. Particles are diffusing in the cylinder driven by a plug flow, in addition the particles are attracted by an orthogonal force, e.g. due to magnetism or gravity. The dynamics of this propagation problem are modeled by multidimensional (nD) transfer functions. They are established by suitable functional transformations in a spatio-temporal frequency domain by exploiting eigenfunctions of partial differential operators. Nontrivial boundary conditions are incorporated by the design of a feedback loop. The result is a discrete-time semianalytical model for the particle concentration.<br

A Novel Wireless Communication Paradigm for Intelligent Reflecting Surface Based Symbiotic Radio Systems - Hua, Meng; Wu, Qingqing; Yang, Luxi; Schober, Robert; Poor, H. Vincent (IEEE Transactions on Signal Processing, 2022)
This paper investigates a novel intelligent reflecting surface (IRS)-based symbiotic radio (SR) system architecture consisting of a transmitter, an IRS, and an information receiver (IR). The primary transmitter communicates with the IR and at the same time assists the IRS in forwarding information to the IR. Based on the IRS's symbol period, we distinguish two scenarios, namely, commensal SR (CSR) and parasitic SR (PSR), where two different techniques for decoding the IRS signals at the IR are employed. We formulate bit error rate (BER) minimization problems for both scenarios by jointly optimizing the active beamformer at the base station and the phase shifts at the IRS, subject to a minimum primary rate requirement. Specifically, for the CSR scenario, a penalty-based algorithm is proposed to obtain a high-quality solution, where semi-closed-form solutions for the active beamformer and the IRS phase shifts are derived based on Lagrange duality and Majorization-Minimization methods, respectively. For the PSR scenario, we apply a bisection search-based method, successive convex approximation, and difference of convex programming to develop a computationally efficient algorithm, which converges to a locally optimal solution. Simulation results demonstrate the effectiveness of the proposed algorithms and show that the proposed SR techniques are able to achieve a lower BER than benchmark schemes.
CRIS-Team WoS Importer:2022-02-04

An Overview of Sustainable Green 5G Networks - Wu, Qingqing; Geoffrey Ye Li, Geoffrey Ye Li; Chen, Wen; Wing Kwan Ng, Derrick; Schober, Robert (IEEE Wireless Communications, 2017)
The stringent requirements of a 1000x increase in data traffic and 1 ms round-trip latency have made limiting the potentially tremendous ensuing energy consumption one of the most challenging problems for the design of the upcoming 5G networks. To enable sustainable 5G networks, new technologies have been proposed to improve the system energy efficiency, and alternative energy sources are introduced to reduce our dependence on traditional fossil fuels. In particular, various 5G techniques target the reduction of the energy consumption without sacrificing the quality of service. Meanwhile, energy harvesting technologies, which enable communication transceivers to harvest energy from various renewable resources and ambient radio frequency signals for communication, have drawn significant interest from both academia and industry. In this article, we provide an overview of the latest research on both green 5G techniques and energy harvesting for communication. In addition, some technical challenges and potential research topics for realizing sustainable green 5G networks are also identified.<br
Keywords: 5G mobile communication; Power demand; Antennas; Wireless networks; Wireless fidelity; Green products; Energy harvesting; Green communication; Sustainable development; Telecommunication traffic

An Ultra-Versatile Massive MIMO Transceiver Testbed for Multi-Gb/s Communication - Gröschel, Patrick; Hehn, Markus; Sippel, Erik; Schober, Robert; Weigel, Robert; Vossiek, Martin; Carlowitz, Christian (2019 IEEE 2nd 5G World Forum (5GWF), 2019)
Massive multiple-input multiple-output (MIMO) communication has gained huge attention throughout the last years as a key technology for fifth generation mobile communication systems, because they enable wide area coverage along with ultra-high data rates and low bit energy. Furthermore, for a high number of antennas, communication theory predicts nearly optimal performance using basic linear detection and precoding schemes. However, realizing such large-scale arrays (say 100 elements or more) is non-trivial and costly and hence, only few of them are available for public research. Most often, existing solutions are limited to the current mobile communication standards. We therefore propose the design and implementation of a low-cost ultra-versatile 120-antenna massive MIMO testbed applicable both in communication and localization research. An instantaneous bandwidth of 150 MHz at a center frequency of 5.8 GHz is covered. An indoor verification measurement with 24 parallel transmissions and a bandwidth of 125 MHz achieved a sum-rate of 22.8 Gb/s with only 1.02 % bit error rate resulting in an outstanding equivalent error-free spectral efficiency of 167.2 bit/s/Hz.<br
Keywords: Radio frequency; Antenna arrays; Antenna measurements; OFDM; Transceivers

AoI-Driven Client Scheduling for Federated Learning: A Lagrangian Index Approach - Ma, Manyou; Wong, Vincent W.S.; Schober, Robert (IEEE International Conference on Communications, 2023)
Federated learning (FL) is a distributed learning framework where clients jointly train a global model without sharing their local datasets. In randomized client sampling, a subset of clients are uniformly chosen to participate in training in each communication round of FL. Recent research has shown that by jointly considering the age of information (AoI) and channel state information (CSI) of each client, the convergence of FL can be improved. In this paper, we formulate a joint AoI and CSI-based client scheduling problem as a constrained Markov decision process. We propose a low-complexity and scalable algorithm based on the Lagrangian index approach. Simulation results show that the proposed Lagrangian index-based approach achieves near-optimal performance. For FL tasks with the CIFAR-10 dataset, our results show that the proposed algorithm can speed up the convergence of FL by 40%, by reducing the duration of uplink transmission, when compared with two state-of-the-art FL algorithms.
CRIS-Team Scopus Importer:2023-12-15
Keywords: Training; Simulation; Markov processes; Linear programming; Indexes; Uplink; Task analysis

Application of smart antenna technologies in simultaneous wireless information and power transfer - Ding, Zhiguo; Zhong, Caijun; Wing Kwan Ng, Derrick; Peng, Mugen; Suraweera, Himal A.; Schober, Robert; Poor, H. Vincent (IEEE Communications Magazine, 2015)
Simultaneous wireless information and power transfer (SWIPT) is a promising solution to increase the lifetime of wireless nodes and hence alleviate the energy bottleneck of energy constrained wireless networks. As an alternative to conventional energy harvesting techniques, SWIPT relies on the use of radio frequency signals, and is expected to bring some fundamental changes to the design of wireless communication networks. This article focuses on the application of advanced smart antenna technologies to SWIPT, including multiple-input multiple-output and relaying techniques. These smart antenna technologies have the potential to significantly improve the energy efficiency and also the spectral efficiency of SWIPT. Different network topologies with single and multiple users are investigated, along with some promising solutions to achieve a favorable trade-off between system performance and complexity. A detailed discussion of future research challenges for the design of SWIPT systems is also provided.<br
Keywords: Relays; MIMO; Receiving antennas; Wireless communication; Energy harvesting; Power transfer; Smart antennas

A Probabilistic Approach to Modeling Users' Network Selection in the Presence of Heterogeneous Wireless Networks - Kumar, Abhinav; Mallik, Ranjan K.; Schober, Robert (IEEE Transactions on Vehicular Technology, 2014)
In the presence of heterogeneous service provider (SP) networks such as wireless local area networks and cellular networks, users have to make a choice. The quality of service provided and the price charged by an SP play a crucial role in this decision process. In this paper, we study the network selection behavior of mobile users. A novel probabilistic framework is presented, with explicit analytical expressions for the transition and steady state network selection probabilities of the users. The proposed framework utilizes the price charged and the utility obtained at the SPs in obtaining the transition probabilities, even in the presence of multi-homing users. Furthermore, network-level parameters such as call blocking probabilities and throughput are obtained in terms of the steady state probabilities. Numerical results indicate that the prices and utilities at the heterogeneous SPs have considerable impact on the overall network performance.<br
Keywords: Wireless LAN; Quality of service; Probabilistic logic; Multiaccess communication; Steady-state; Wireless networks

Area Rate Efficiency in Molecular Communications - Brand, Lukas; Lotter, Sebastian; Jamali, Vahid; Schober, Robert (PROCEEDINGS OF THE 8TH ACM INTERNATIONAL CONFERENCE ON NANOSCALE COMPUTING AND COMMUNICATION (ACM NANOCOM 2021), 2021)
We consider a multiuser diffusion-based molecular communication (MC) system where multiple spatially distributed transmitter (TX)-receiver (RX) pairs establish point-to-point communication links employing the same type of signaling molecules. To realize the full potential of such a system, an in-depth understanding of the interplay between the spatial user density and inter-user interference (IUI) and its impact on system performance in an asymptotic regime with large numbers of users is needed. In this paper, we adopt a three-dimensional (3-D) system model with multiple independent and spatially distributed point-to-point transmission links, where both the TXs and RXs are positioned according to a regular hexagonal grid, respectively. Based on this model, we first derive an expression for the channel impulse responses (CIRs) of all TX-RX links in the system. Then, we provide the maximum likelihood (ML) decision rule for the RXs and show that it reduces to a threshold-based detector. We derive an analytical expression for the corresponding detection threshold which depends on the statistics of the MC channel and the statistics of the IUI. Furthermore, we derive an analytical expression for the bit error rate (BER) and the achievable rate of a single transmission link. Finally, we propose a new performance metric, which we refer to as area rate efficiency (ARE), that captures the tradeoff between the user density and IUI. The ARE characterizes how efficiently given TX and RX areas are used for information transmission and is given in terms of bits per area unit. We show that there exists an optimal user density for maximization of the ARE. Results from particle-based and Monte Carlo simulations validate the accuracy of the expressions derived for the CIR, optimal detection threshold, BER, and ARE.<br
CRIS-Team WoS Importer:2022-03-25

Area Rate Efficiency in Multi-Link Molecular Communications - Brand, Lukas; Lotter, Sebastian; Jamali, Vahid; Schober, Robert; Schäfer, Maximilian (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2023)
We consider a multi-link diffusion-based molecular communication (MC) system where multiple spatially distributed transmitter (TX)-receiver (RX) pairs establish point-to-point communication links employing the same type of signaling molecules. To exploit the full potential of such a system, an in-depth understanding of the interplay between the spatial link density and inter-link interference (ILI) and its impact on system performance is needed. In this paper, we consider a three-dimensional unbounded domain with multiple spatially distributed point-to-point non-cooperative transmission links, where both the TXs and RXs are positioned on a regular fixed grid. For this setup, we first derive an analytical expression for the channel impulse responses (CIRs) between the TXs and RXs in the system. Then, we derive the maximum likelihood (ML) detector for the RXs and show that it reduces to a thresholdbased detector. Moreover, we derive an analytical expression for the corresponding detection threshold which depends on the statistics of the desired signal from the dedicated TX, the statistics of the MC channel, and the statistics of the ILI. We also provide a low-complexity suboptimal decision threshold. Furthermore, we derive an analytical expression for the bit error rate (BER) and the achievable rate of a single transmission link. Finally, we propose two new performance metrics, namely area rate efficiency (ARE) and area and time rate efficiency (ARTE), suitable for holistically evaluating spatially distributed multi-link MC systems. In particular, ARE and ARTE capture the tradeoff between transmission link density and achievable rate per link and the tradeoff between transmission link density, achievable rate per link, and inter-symbol interference (ISI), respectively. Hence, ARE and ARTE can be exploited to determine the optimal transmission link density for maximizing the throughput of the entire system.
Created from Fastlane, Scopus look-up
Keywords: Detectors; Interference; Measurement; MIMO communication; Sensors; Signal to noise ratio; Wireless communication

A robust design of electric vehicle frequency regulation service - Yao, Enxin; Wong, Vincent W. S.; Schober, Robert (2014 IEEE International Conference on Smart Grid Communications (SmartGridComm), 2014)
Electric vehicles (EVs) have the potential to provide frequency regulation service to an independent system operator (ISO) by changing their real-time charging or discharging power according to an automatic generation control (AGC) signal. Recently, the Federal Energy Regulatory Commission has issued an order to ISOs to introduce a performance-based compensation paradigm. In this new compensation scheme, the ISOs make payments to the EVs for providing the frequency regulation capacity and the real-time dispatch when following the AGC signal. In this paper, we propose a robust EV frequency regulation (REF) algorithm to determine the hourly regulation capacity for each EV considering the randomness of the AGC signal. The proposed REF algorithm is based on a robust optimization problem formulation. It enables EVs to follow the random AGC signal reliably and to improve the EV frequency regulation revenue. Simulation results show that the proposed REF algorithm obtains a higher revenue compared with a benchmark algorithm from the literature under a performance-based compensation paradigm.<br
Keywords: Frequency control; Automatic generation control; ISO; Robustness; Bismuth; Real-time systems

A Single Antenna Interference Cancellation Algorithm for GSM - Meyer, Raimund; Gerstacker, Wolfgang; Schober, Robert; Huber, Johannes (Conference Proceedings, 2005)
In mobile communication networks, system capacity is often limited by cochannel interference. Therefore, receiver algorithms for cancellation of cochannel interference have recently attracted much interest At the mobile terminal, algorithms can usually rely only on one received signal delivered by a single receive antenna. In this paper, a novel low-complexity single antenna interference cancellation (SAIC) algorithm for real-valued modulation formats referred to as mono interference cancellation (MIC) is introduced which is well suited for practical applications. By using this algorithm in the mobile terminals, capacity of GSM networks can be improved by up to 40-60 %. © 2005 IEEE.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.mobilk.asingl
Keywords: Cochannel interference; Equalization; GSM; Mobile communications

A Single Antenna Interference Cancellation Algorithm for Increased GSM Capacity - Meyer, Raimund; Gerstacker, Wolfgang; Schober, Robert; Huber, Johannes (IEEE Transactions on Wireless Communications, 2006)
In mobile communications networks, system capacity is often limited by cochannel interference. Therefore, receiver algorithms for cancellation of cochannel interference have recently attracted much interest. At the mobile terminal, algorithms can usually rely only on one received signal delivered by a single receive antenna. In this letter, a low-complexity single antenna interference cancellation (SAIC) algorithm for real-valued modulation formats referred to as mono interference cancellation (MIC) is introduced which is well suited for practical applications. Field trials in commercial GSM networks using prototype terminals with the proposed MIC algorithm have demonstrated that the novel concept may yield capacity improvements of up to 80%. The underlying principle is also beneficial for adjacent channel interference and receivers with multiple antennas. Furthermore, in coverage-limited scenarios, there is no performance degradation compared with conventional receivers. © 2006 IEEE.
UnivIS-Import:2015-03-09:Pub.2006.tech.IE.mobilk.asingl
Keywords: Cochannel interference; Equalization; GSM; Mobile communications

A Single-RF Architecture for Multiuser Massive MIMO Via Reflecting Surfaces - Bereyhi, Ali; Jamali, Vahid; Müller, Ralf; Tulino, Antonia M.; Fischer, Georg; Schober, Robert (ICASSP, IEEE International Conference on Acoustics, Speech and Signal Processing - Proceedings, 2020)
In this work, we propose a new single-RF MIMO architecture which enjoys high scalability and energy-efficiency. The transmitter in this proposal consists of a single RF illuminator radiating towards a reflecting surface. Each element on the reflecting surface re-transmits its received signal after applying a phase-shift, such that a desired beamforming pattern is obtained. For this architecture, the problem of beamforming is interpreted as linear regression and a solution is derived via the method of least-squares. Using this formulation, a fast iterative algorithm for tuning of the reflecting surface is developed. Numerical results demonstrate that the proposed architecture is fully compatible with current designs of reflecting surfaces.
CRIS-Team Scopus Importer:2020-09-18
Keywords: least-squares; massive MIMO; reflecting surfaces; Single-RF transmitter

A State-of-the-Art Survey on Reconfigurable Intelligent Surface-Assisted Non-Orthogonal Multiple Access Networks - Ding, Zhiguo; Lv, Lu; Fang, Fang; Dobre, Octavia A.; Karagiannidis, George K.; Al-Dhahir, Naofal; Schober, Robert; Poor, H. Vincent (Proceedings of the IEEE, 2022)
Reconfigurable intelligent surfaces (RISs) and nonorthogonal multiple access (NOMA) have been recognized as key enabling techniques for the envisioned sixth generation (6G) of mobile communication networks. The key feature of RISs is to intelligently reconfigure the wireless propagation environment, which was once considered to be fixed and untunable. The key idea of NOMA is to utilize users' dynamic channel conditions to improve spectral efficiency and user fairness. Naturally, the two communication techniques are complementary to each other and can be integrated to cope with the challenging requirements envisioned for 6G mobile networks. This survey provides a comprehensive overview of the recent progress on the synergistic integration of RISs and NOMA. In particular, the basics of both techniques are introduced first, and then, the fundamentals of RIS-NOMA are discussed for two communication scenarios with different transceiver capabilities. Resource allocation is of paramount importance for the success of RIS-assisted NOMA networks, and various approaches, including artificial intelligence (AI)-empowered designs, are introduced. Security provisioning in RIS-NOMA networks is also discussed as wireless networks are prone to security attacks due to the nature of the shared wireless medium. Finally, the survey is concluded with detailed discussions of the challenges arising in the practical implementation of RIS-NOMA, future research directions, and emerging applications.
CRIS-Team Scopus Importer:2022-06-03
Keywords: 5G mobile communication; 6G mobile communication; Artificial intelligence (AI); Gain; multi-input multi-output (MIMO); NOMA; nonorthogonal multiple access (NOMA); Performance gain; reconfigurable intelligent surface (RIS); resource allocation; Resource management; Security; wireless security.

A Survey of Biological Building Blocks for Synthetic Molecular Communication Systems - Söldner, Christian; Socher, Eileen; Jamali, Vahid; Wicke, Wayan; Ahmadzadeh, Arman; Breitinger, Hans Georg; Burkovski, Andreas; Castiglione, Kathrin; Schober, Robert; Sticht, Heinrich (IEEE Communications Surveys & Tutorials, 2020)
Synthetic molecular communication (MC) is a new communication engineering paradigm which is expected to enable revolutionary applications such as smart drug delivery and real-time health monitoring. The design and implementation of synthetic MC systems (MCSs) at nano- and microscale is very challenging. This is particularly true for synthetic MCSs employing biological components as transmitters and receivers or as interfaces with natural biological MCSs. Nevertheless, since such biological components have been optimized by nature over billions of years, using them in synthetic MCSs is highly promising. This paper provides a survey of biological components that can potentially serve as the main building blocks, i.e., transmitter, receiver, and signaling particles, for the design and implementation of synthetic MCSs. Nature uses a large variety of signaling particles of different sizes and with vastly different properties for communication among biological entities. Here, we focus on three important classes of signaling particles: cations (specifically protons and calcium ions), neurotransmitters (specifically acetylcholine, dopamine, and serotonin), and phosphopeptides. These three classes have unique and distinct features such as their large diffusion coefficients, their specificity, and/or their uniqueness of signaling that make them suitable candidates for signaling particles in synthetic MCSs. For each of these candidate signaling particles, we present several specific transmitter and receiver structures mainly built upon proteins that are capable of performing the distinct physiological functionalities required from the transmitters and receivers of MCSs. Moreover, we present options for both microscale implementation of MCSs as well as the micro-to-macroscale interfaces needed for experimental evaluation of MCSs. One of the main advantages of employing proteins for signal emission and detection is that they can be modified with tools from synthetic biology and be tailored to a wide range of application needs. We discuss the properties, limitations, and applications of the proposed biological building blocks for synthetic MCSs in detail. Furthermore, we outline new research directions for the implementation and the theoretical design and analysis of the proposed transmitter and receiver architectures.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Molecular communications; signaling particles; synthetic biology; test-bed implementation; transmitter and receiver architecture

A Survey of Molecular Communication in Cell Biology: Establishing a New Hierarchy for Interdisciplinary Applications - Bi, Dadi; Almpanis, Apostolos; Noel, Adam; Deng, Yansha; Schober, Robert (IEEE Communications Surveys & Tutorials, 2021)
Molecular communication (MC) engineering is inspired by the use of chemical signals as information carriers in cell biology. The biological nature of chemical signaling makes MC a promising methodology for interdisciplinary applications requiring communication between cells and other microscale devices. However, since the life sciences and communications engineering fields have distinct approaches to formulating and solving research problems, the mismatch between them can hinder the translation of research results and impede the development and implementation of interdisciplinary solutions. To bridge this gap, this survey proposes a novel communication hierarchy for MC signaling in cell biology and maps phenomena, contributions, and problems to the hierarchy. The hierarchy includes: 1) the physical propagation of cell signaling at the Physical Signal Propagation level; 2) the generation, reception, and biochemical pathways of molecular signals at the Physical and Chemical Signal Interaction level; 3) the quantification of physical signals, including macroscale observation and control methods, and conversion of signals to information at the Signal-Data Interface level; 4) the interpretation of information in cell signals and the realization of synthetic systems to store, process, and communicate molecular signals at the Local Data Abstraction level; and 5) applications relying on communication with MC signals at the Application level. To further demonstrate the proposed hierarchy, it is applied to case studies on quorum sensing, neuronal signaling, and communication via DNA. Finally, several open problems are identified for each level and the integration of multiple levels. The proposed hierarchy provides language for communication engineers to study and interface with biological systems, and also helps biologists to understand how communications engineering concepts can be exploited to interpret, control, and manipulate signaling in cell biology.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Biology; Cell biology; chemical reactions; Chemicals; Computer architecture; diffusion; hierarchy; interdisciplinary applications; level; microfluidics; molecular communication; Protocols; Sensors; signaling pathways; Synthetic biology; synthetic biology.; Tools

A Survey on Millimeter-Wave Beamforming Enabled UAV Communications and Networking - Xiao, Zhenyu; Zhu, Lipeng; Liu, Yanming; Yi, Pengfei; Zhang, Rui; Xia, Xiang Gen; Schober, Robert (IEEE Communications Surveys & Tutorials, 2022)
Unmanned aerial vehicles (UAVs) have found widespread commercial, civilian, and military applications. Wireless communication has always been one of the core technologies for UAV. However, the communication capacity is becoming a bottleneck for UAV to support more challenging application scenarios. The heavily-occupied sub-6 GHz frequency band is not sufficient to meet the ultra high-data-traffic requirements. The utilization of the millimeter-wave (mmWave) frequency bands is a promising direction for UAV communications, where large antenna arrays can be packed in a small area on the UAV to perform three-dimensional (3D) beamforming. On the other hand, UAVs serving as aerial access points or relays can significantly enhance the coverage and quality of service of the terrestrial mmWave cellular networks. In this paper, we provide a comprehensive survey on mmWave beamforming enabled UAV communications and networking. The technical potential of and challenges for mmWave-UAV communications are presented first. Then, we provide an overview on relevant mmWave antenna structures and channel modeling. Subsequently, the technologies and solutions for UAV-connected mmWave cellular networks and mmWave-UAV ad hoc networks are reviewed, respectively. Finally, we present open issues and promising directions for future research in mmWave beamforming enabled UAV communications and networking.
CRIS-Team Scopus Importer:2022-03-11
Keywords: ad hoc network; antenna structure; beamforming; channel modeling; mmWave communications; UAV; UAV-connected mmWave cellular

A Survey on Non-Orthogonal Multiple Access for 5G Networks: Research Challenges and Future Trends - Ding, Zhiguo; Lei, Xianfu; Karagiannidis, George K.; Schober, Robert; Yuan, Jinhong; Bhargava, Vijay Kishore (IEEE Journal on Selected Areas in Communications, 2017)
Non-orthogonal multiple access (NOMA) is an essential enabling technology for the fifth-generation (5G) wireless networks to meet the heterogeneous demands on low latency, high reliability, massive connectivity, improved fairness, and high throughput. The key idea behind NOMA is to serve multiple users in the same resource block, such as a time slot, subcarrier, or spreading code. The NOMA principle is a general framework, and several recently proposed 5G multiple access schemes can be viewed as special cases. This survey provides an overview of the latest NOMA research and innovations as well as their applications. Thereby, the papers published in this special issue are put into the context of the existing literature. Future research challenges regarding NOMA in 5G and beyond are also discussed.<br
Keywords: NOMA; 5G mobile communication; Quality of service; Resource management; Millimeter wave communication; MIMO; Cognitive radio

Asymptotically Optimal Power Allocation for Energy Harvesting Communication Networks - Zlatanov, Nikola; Schober, Robert; Hadzi-Velkov, Zoran (IEEE Transactions on Vehicular Technology, 2017)
For a general energy harvesting (EH) communication network, i.e., a network where the nodes generate their transmit power through EH, we derive the asymptotically optimal online power allocation solution that optimizes a general utility function when the number of transmit time slots, N, and the battery capacities of the EH nodes, B max , satisfy N → ∞ and B max → ∞. The considered family of utility functions is general enough to include the most important performance measures in communication theory, such as the average data rate, outage probability, average bit-error probability, and average signal-to-noise ratio. The proposed power allocation solution is very simple. Namely, the asymptotically optimal power allocation for the EH network is identical to the optimal power allocation for an equivalent nonEH network whose nodes have infinite energy available but their average transmit power is constrained to be equal to the average harvested power and/or the maximum average transmit power of the corresponding nodes in the EH network. Moreover, the maximum average performance of a general EH network converges to the maximum average performance of the corresponding equivalent non-EH network, when N → ∞ and B max → ∞. Although the proposed solution is asymptotic in nature, it is applicable to EH systems transmitting in a large but finite number of time slots and having a battery capacity much larger than the average harvested power and/or the maximuma average transmit power.<br
Keywords: Batteries; Resource management; Transmitters; Energy harvesting; Battery charge measurement; Measurement uncertainty; Error probability

Asymptotically optimal power allocation for point-to-point energy harvesting communication systems - Zlatanov, Nikola; Hadzi-Velkov, Zoran; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2013)
For a point-to-point communication system generating its power via energy harvesting (EH), we derive the asymptotically optimal power allocation which optimizes a general utility function when the number of transmitted codewords N and the battery capacity Bmax satisfy N → ∞ and B max → ∞. The considered family of utility functions is general enough to include the most important performance measurements in communication theory such as ergodic rate, outage probability, average signal-to-noise ratio, etc. The discovered solution is very simple. Namely, the optimal power allocation for the EH system is identical to the optimal power allocation of an equivalent non-EH communication system with infinite available energy, under the constraint that both systems use identical average transmit powers. Although the proposed solution is asymptotic, it is applicable to EH systems transmitting a large but finite number of codewords and having a battery capacity much larger than the average harvested power and/or the maximum average transmit power. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Asymptotically tight error rate bounds for EGC in correlated generalized Rician fading - Schlenker, Josh; Cheng, Julian; Schober, Robert (IEEE International Conference on Communications, 2013)
Exact error rate analysis for pre-detection equal gain combining over arbitrarily correlated fading branches has proven elusive. Even specialized correlation models result in complex error rate expressions with multiple nested infinite series or integrals. For this reason, asymptotic analysis is a useful tool due to the simplicity of the error rate expressions it produces. However, one major shortcoming of this approach is that the asymptotic technique can not predict at what signal-to-noise ratio the asymptotic approximation is accurate. In this paper, we derive asymptotically tight single-integral lower and upper bounds on the error probability for a correlated generalized Rician fading model. These lower and upper bounds help determine when the asymptotic solutions approach the exact results. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Asymptotic analysis of coherent and differential space-time codes in non-Gaussian noise and interference - Nezampour, Ali; Schober, Robert; Ma, Yao (IEEE Transactions on Communications, 2009)
In this paper, we provide a unified framework for the asymptotic performance analysis of space-time codes (STCs) in correlated Ricean fading and non-Gaussian noise and interference. In particular, we derive simple and asymptotically tight expressions for the pairwise error probability (PEP) of coherent and differential STCs which are valid for any type of noise and interference with finite moments and detection with general Mahalonobis distance (MD) metrics including Euclidean distance (ED) and noise decorrelating (ND) metrics. These PEP expressions can be combined with truncated union bounds to obtain accurate asymptotic approximations for the bit, symbol, and frame error probabilities of STCs. We show that while the diversity gain of an STC is independent of the type of noise and the type of MD metric used, the coding gain is not and depends on certain moments of the noise and interference. We provide closed-form expressions for these moments for several practically relevant types of noise and interference. We show that for correlated noise significant performance gains can be achieved with the ND metric compared to the ED metric. While noise correlations are beneficial at high signal-to-noise ratios if they can be exploited by the metric, they are harmful if this is not the case and the simple ED metric is employed. All our analytical findings are confirmed by simulations for various popular STCs and several different types of noise and interference. © 2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Asymptotic analysis; Coherent; Differential; Fading channels; Non-Gaussian noise and interference; Space-time code

Asymptotic analysis of space-time codes in generalized keyhole fading channels - Nezampour, Ali; Nasri, Amir; Schober, Robert (IEEE Wireless Communications and Networking Conference, WCNC, 2010)
The keyhole phenomenon, i.e., uncorrelated but rank-deficient fading, can lead to significant performance degradations in multiple-input multiple-output (MIMO) systems and has to be carefully taken into account for system design. In this paper, considering the practically important case of two transmit and an arbitrary number of receive antennas, we provide a simple closed-form expression for the asymptotic pairwise error probability (PEP) of space-time codes (STCs) in generalized keyhole fading channels including Rayleigh, Ricean, Nakagami-q, Nakagami-m, andWeibull fading.We show how the number of transmit and receive antennas as well as the fading parameters affect the diversity gain. The presented analysis provides new insights into STC design and can be used to obtain tight asymptotic upper bounds for the bit, symbol, and frame error probabilities of arbitrary STCs in keyhole fading. ©2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Asymptotic analysis of space-time codes in generalized keyhole fading channels - Nezampour, Ali; Nasri, Amir; Schober, Robert (IEEE Transactions on Wireless Communications, 2011)
The keyhole phenomenon, i.e., non-fully correlated but rank-deficient fading, can lead to significant performance degradations in multiple-input multiple-output (MIMO) systems and has to be carefully taken into account for system design. In this paper, we consider generalized keyhole fading including Rayleigh, Ricean, Nakagami-q, Nakagami-m, and Weibull fading. We derive simple and elegant closed-form expressions for the asymptotic pairwise error probability (PEP) of both single-antenna transmission and space-time coded transmission with two transmit antennas. The obtained PEP expressions provide significant insight into the impact of various system and channel parameters such as the types of fading at the transmitter and receiver side, the numbers of transmit and receive antennas, and the space-time code design on performance. This insight can be exploited for system design and to explain the differences in the performance of space-time codes in non-keyhole and keyhole fading channels. Furthermore, the presented asymptotic PEP expressions can be utilized to obtain tight asymptotic approximations for the bit, symbol, and frame error probabilities of arbitrary, not necessarily orthogonal, space-time codes. Simulation results confirm the accuracy and usefulness of the derived results. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Asymptotic analysis; generalized fading; keyhole fading channels; space-time codes

Asymptotic analysis of space-time codes in non-gaussian noise and interference - Nezampour, Ali; Schober, Robert; Ma, Yao (IEEE Vehicular Technology Conference, 2008)
In this paper, we provide a framework for the asymptotic performance analysis of space-time codes (STCs) in correlated Ricean fading and non-Gaussian noise and interference. In particular, we derive a simple, asymptotically tight expression for the pairwise error probability (PEP) of coherent STCs which is valid for any type of noise and interference with finite moments. This PEP expression can be used to obtain accurate asymptotic approximations for the bit and symbol error probabilities of STCs. Our results show that while the diversity gain of an STC is independent of the type of noise, the coding gain is not and depends on certain moments of the noise and interference. We provide closed-form expressions for these moments for several practically relevant types of noise and interference. Our analytical findings are confirmed by simulations for Alamouti's ST block code and Tarokh's ST trellis code and several different types of noise and interference. © 2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Asymptotic analysis of space-time codes with mahalonobis distance decoding in non-gaussian noise and interference - Nezampour, Ali; Schober, Robert; Yao, Ma (EW2008 - 14th European Wireless Conference 2008, Electronic Proceedings, 2008)
In this paper, we derive simple and asymptotically tight expressions for the pairwise error probability (PEP) of coherent space-time codes (STCs) which are valid for any type of noise and interference with finite moments and detection with general Mahalonobis distance (MD) metrics including Euclidean distance (ED) and noise decorrelating (ND) metric. We show that while the diversity gain of an STC is independent of the type of noise and the type of MD metric used, the coding gain depends on both the noise distribution and the MD metric. We show that in the case of correlated noise, significant performance gains can be achieved with the ND metric compared to the ED metric. While noise correlations are beneficial at high signal-to-noise ratios if they can be exploited by the metric, they are harmful if this is not the case and the simple ED metric is employed.
CRIS-Team Scopus Importer:2020-02-03

Asymptotic BEP and SEP of quadratic diversity combining receivers in correlated ricean fading, non-gaussian noise, and interference - Nezampour, Ali; Nasri, Amir; Schober, Robert; Ma, Yao (IEEE Transactions on Communications, 2009)
In this paper, we study the asymptotic behavior of the bit-rror probability (BEP) and the symbol-error probability (SEP) of quadratic diversity combining schemes such as coherent maximum-atio combining (MRC), differential equal-gain combining (EGC), and noncoherent combining (NC) in correlated Ricean fading and non-Gaussian noise, which in our definition also includes interference.We provide simple and easy- to-evaluate asymptotic BEP and SEP expressions which show that at high signal-to-noise ratios (SNRs) the performance of the considered combining schemes depends on certain moments of the noise and interference impairing the transmission. We derive general rules for calculation of these moments and we provide closed-form expressions for the moments of several practically important types of noise such as spatially dependent and spatially independent Gaussian mixture noise, correlated synchronous and asynchronous co-channel interference, and correlated Gaussian interference. From our asymptotic results we conclude that (a) the asymptotic performance loss of binary frequency-shift keying (BFSK) with NC compared to binary phase-shift keying (BPSK) withMRC is always 6 dB independent of the type of noise and the number of diversity branches, (b) the asymptotic performance loss of differential EGC compared to MRC is always 3 dB for additive white Gaussian noise but depends on the number of diversity branches and may be larger or smaller than 3 dB for other types of noise, and (c) not only fading correlation but also noise correlation negatively affects the performance of quadratic diversity combiners. © 2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Asymptotic analysis; Coherent maximum ratio combining; Differential equal gain combining; Fading channels; Non-Gaussian noise and interference; Noncoherent combining

Asymptotic Performance Analysis of GSVD-NOMA Systems With a Large-Scale Antenna Array - Chen, Zhuo; Ding, Zhiguo; Dai, Xuchu; Schober, Robert (IEEE Transactions on Wireless Communications, 2018)
This paper considers a multiple-input multipleoutput (MIMO) downlink communication scenario with one base station and two users, where each user is equipped with m antennas and the base station is equipped with n antennas. To efficiently exploit the spectrum resources, we propose a transmission protocol which combines generalized singular value decomposition (GSVD) and non-orthogonal multiple access (NOMA). The expected data rates achieved by the two users are adopted as performance metrics for the evaluation of the proposed GSVD-NOMA scheme. In particular, we first characterize the limiting distribution of the squared generalized singular values of the two users' channel matrices for the asymptotic case, where the numbers of transmit and receive antennas approach infinity. Then, we calculate the expected normalized individual rates of the users in the considered asymptotic regime. Furthermore, we extend the proposed GSVD-NOMA scheme to the general MIMO downlink communication scenario with more than two users. To this end, we propose a hybrid multiple access approach, where the base station divides the users into different groups, the proposed GSVD-NOMA scheme is implemented within each group, and different groups are allocated orthogonal bandwidth resources. Finally, numerical results are provided to validate the effectiveness of the proposed GSVD-NOMA protocol and the accuracy of the developed analytical results.<br
Keywords: NOMA; MIMO communication; Downlink; Base stations; Matrix decomposition; Receiving antennas

Asymptotic Performance Analysis of GSVD-NOMA Systems with a Large-Scale Antenna Array - Chen, Zhuo; Ding, Zhiguo; Dai, Xuchu; Schober, Robert (IEEE Transactions on Wireless Communications, 2019)
This paper considers a multiple-input multiple-output (MIMO) downlink communication scenario with one base station and two users, where each user is equipped with m antennas and the base station is equipped with n antennas. To efficiently exploit the spectrum resources, we propose a transmission protocol which combines generalized singular value decomposition (GSVD) and non-orthogonal multiple access (NOMA). The expected data rates achieved by the two users are adopted as performance metrics for the evaluation of the proposed GSVD-NOMA scheme. In particular, we first characterize the limiting distribution of the squared generalized singular values of the two users' channel matrices for the asymptotic case, where the numbers of transmit and receive antennas approach infinity. Then, we calculate the expected normalized individual rates of the users in the considered asymptotic regime. Furthermore, we extend the proposed GSVD-NOMA scheme to the general MIMO downlink communication scenario with more than two users. To this end, we propose a hybrid multiple access approach, where the base station divides the users into different groups, the proposed GSVD-NOMA scheme is implemented within each group, and different groups are allocated orthogonal bandwidth resources. Finally, numerical results are provided to validate the effectiveness of the proposed GSVD-NOMA protocol and the accuracy of the developed analytical results.
CRIS-Team Scopus Importer:2019-07-23
Keywords: Generalized singular value decomposition (GSVD); multiple-input multiple-output (MIMO); non-orthogonal multiple access (NOMA)

Asymptotic performance of generalized selection combining in generic noise and fading - Ahmed, Imtiaz; Nasri, Amir; Schober, Robert; Mallik, Ranjan K. (IEEE Transactions on Communications, 2012)
In this letter, we investigate the performance of generalized selection combining in channels impaired by generalized fading and generic noise with finite moments. In particular, we derive accurate high signal-to-noise ratio approximations for the bit and symbol error rates of linear modulation schemes, which offer significant insight into the impact of the number of selected diversity branches, the type of fading, and the type of noise. Our analysis is applicable to all practically relevant types of fading including Rayleigh, Rician, Nakagami-q, and Nakagami-m fading, all types of noise with finite moments including Gaussian noise, Gaussian mixture noise, generalized Gaussian noise, and co-channel interference, and non-identically distributed fading and noise across the diversity branches. Our results reveal that while performance always improves with increasing number of selected branches for identically distributed noise, this is not necessarily true for non-identically distributed noise. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Diversity methods; fading channels; interference; noise

Asymptotic performance of Lp-norm MIMO detection - Ahmed, Imtiaz; Schober, Robert; Mallik, Ranjan K. (IEEE Vehicular Technology Conference, 2010)
Full search L1-norm (FS-L1) and sphere decoding L∞-norm (SD-L∞) detectors have been previously proposed for multiple-input multiple-output (MIMO) systems as they entail a lower receiver complexity than the optimal L2-norm detector. However, the performance loss caused by application of these suboptimal detectors in additive white Gaussian noise (AWGN) has not been well investigated yet. In this paper, we analyze the asymptotic bit error rate of general FS-Lp and SD-Lp detectors in independent identically distributed Rayleigh fading channels. Our results are valid for all types of noise with finite moments including AWGN. We show that both FS-Lp and SD-Lp detectors achieve a diversity gain equal to the number of receive antennas independent of the metric parameter p and the type of noise. However, except for the conventional L2 case, the performances of FS-Lp and SD-Lp detectors are not identical and the performance differences may be several dB for large numbers of receive antennas. Also, our results show that p = 2 is not optimal in non-Gaussian noise and L1 and L ∞ detectors may result in large performance gains or degradations compared to L2 detectors depending on the type of noise. ©2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03

A System Concept for Online Calibration of Massive MIMO Transceiver Arrays for Communication and Localization - Gröschel, Patrick; Zarei, Shahram; Carlowitz, Christian; Lipka, Melanie; Sippel, Erik; Ali, Arslan; Weigel, Robert; Schober, Robert; Vossiek, Martin (IEEE Transactions on Microwave Theory and Techniques, 2017)
Massive multiple-input multiple-output (MIMO) techniques are being considered for the fifth generation (5G) mobile communication systems in order to deliver high multiplexing gain. However, hardware impairments like quadrature imbalance in mixers violate the requirement for channel reciprocity and may change, e.g., with temperature or while aging. In addition, advanced wireless localization techniques and the generation of predefined beam patterns require knowledge about all antenna phase center positions and the time and phase delay of all transmit and receive channels. Thus, an efficient online compensation method is needed that scales well for very large numbers of transceiver modules. We propose to extend the transmitter with a small measurement feature at the transmitter output based on one uncalibrated power detector per module as well as a single, external four-element backscatter array for the entire matrix. These enhancements facilitate a fast and efficient iterative calibration, which recognizes and mitigates all major error sources. Beside optimal communication throughput and energy efficiency, it thereby brings localization capabilities to mobile networks as an additional major benefit. For verification, a system of multiple cost-efficient 5.8-GHz massive MIMO transceivers with 150-MHz bandwidth and a backscatter array has been implemented. Measurement results demonstrate the capability of the proposed concept to efficiently compensate major error sources as well as its robustness.
elib2cris::1512001600,groeschel2017
Keywords: Backscatter transponder (BT); calibration; fifth generation (5G) mobile communication; massive multiple-input multiple-output (MIMO); wireless localization

A Tractable Framework for Coverage Analysis of Cellular-Connected UAV Networks - Yu, Xianghao; Zhang, Jun; Schober, Robert; Letaief, Khaled B. (2019 IEEE International Conference on Communications Workshops (ICC Workshops), 2019)
Unmanned aerial vehicles (UAVs) have recently found abundant applications in the public and civil domains. To ensure reliable control and navigation, connecting UAVs to controllers via existing cellular network infrastructure, i.e., ground base stations (GBSs), has been proposed as a promising solution. Nevertheless, it is highly challenging to characterize the communication performance of cellular-connected UAVs, due to their unique propagation conditions. This paper proposes a tractable framework for the coverage analysis of cellular-connected UAV networks, which consists of a new blockage model and an effective approach to handle general fading channels. In particular, a line-of-sight (LoS) ball model is proposed to capture the probabilistic propagation in UAV communication systems, and a tractable expression is derived for the Laplace transform of the aggregate interference with general Nakagami fading. This framework leads to a tractable expression for the coverage probability, which in turn helps to investigate the impact of the GBS density. Specifically, a tight lower bound on the optimal density that maximizes the coverage probability is derived. Numerical results show that the proposed LoS ball model is accurate, and the optimal GBS density decreases when the UAV altitude increases.<br

A unified performance analysis framework for differential detection in MIMO Rayleigh fading channels - Pauli, Volker; Schober, Robert; Lampe, Lutz (IEEE Transactions on Communications, 2008)
In this paper, a unified framework for the analysis of differential detection (DD) schemes in time-variant multiple-input multiple-utput Rayleigh fading channels is provided. The present results are very general in that they apply to transmission with differential phase-shift keying, unitary differential space-time modulation (DSTM), and block DSTM and reception with conventional DD (CDD), multiple-symbol DD (MSDD), decision-feedback DD (DFDD), and (differentially) coherent detection (CD). New result for general quadratic forms of Gaussian random variables are derived which allows us to obtain elegant closed-form expressions for the pairwise error probabilities (PEPs) of the dominant error events of the considered detectors. Furthermore, it is shown that a unified treatment of all considered detectors is possible with a properly defined effective signal-to-noise ratio (ESNR) and a useful connection between MSDD and minimum-mean-quared-error (MMSE) interpolation is established. Interesting novel results obtained from this analysis include: (i) DSTM constellations designed for CDD and CD are also optimum for MSDD and DFDD; (ii) the error floor entailed by MSDD and DFDD in time-variant fading decreases exponentially with the observation window size N; and (iii) in time-variant fading with effective normalized fading bandwidth Bh,effT MSDD with N → ∞ suffers only from an SNR loss of (1 - 2Bh,eff T) compared to CD, whereas DFDD suffers from a diversity loss of (1 - 2Bh,effT). © 2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Differential space time modulation; MIMO fading channels; Performance analysis

A Unifying Model for External Noise Sources and ISI in Diffusive Molecular Communication - Noel, Adam; Cheung, Karen C.; Schober, Robert (IEEE Journal on Selected Areas in Communications, 2014)
This paper considers the impact of external noise sources, including interfering transmitters, on a diffusive molecular communication system, where the impact is measured as the number of noise molecules expected to be observed at a passive receiver. A unifying model for noise, multiuser interference, and intersymbol interference is presented, where, under certain circumstances, interference can be approximated as a noise source that is emitting continuously. The model includes the presence of advection and molecule degradation. The time-varying and asymptotic impact is derived for a series of special cases, some of which facilitate closed-form solutions. Simulation results show the accuracy of the expressions derived for the impact of a continuously-emitting noise source, and show how approximating old intersymbol interference as a noise source can simplify the calculation of the expected bit error probability of a weighted sum detector.<br
Keywords: Noise measurement; Receivers; Transmitters; Interference; Degradation; Detectors; Molecular communication

Autonomous demand-side management based on game-theoretic energy consumption scheduling for the future smart grid - Mohsenian-Rad, Amir-Hamed; Wong, Vincent W. S.; Jatskevich, Juri; Schober, Robert; Leon-Garcia, Alberto (IEEE Transactions on Smart Grid, 2010)
Most of the existing demand-side management programs focus primarily on the interactions between a utility company and its customers/users. In this paper, we present an autonomous and distributed demand-side energy management system among users that takes advantage of a two-way digital communication infrastructure which is envisioned in the future smart grid. We use game theory and formulate an energy consumption scheduling game, where the players are the users and their strategies are the daily schedules of their household appliances and loads. It is assumed that the utility company can adopt adequate pricing tariffs that differentiate the energy usage in time and level. We show that for a common scenario, with a single utility company serving multiple customers, the global optimal performance in terms of minimizing the energy costs is achieved at the Nash equilibrium of the formulated energy consumption scheduling game. The proposed distributed demand-side energy management strategy requires each user to simply apply its best response strategy to the current total load and tariffs in the power distribution system. The users can maintain privacy and do not need to reveal the details on their energy consumption schedules to other users. We also show that users will have the incentives to participate in the energy consumption scheduling game and subscribing to such services. Simulation results confirm that the proposed approach can reduce the peak-to-average ratio of the total energy demand, the total energy costs, as well as each user's individual daily electricity charges. © 2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Demand-side management; distributed algorithms; energy consumption scheduling; energy pricing; game theory; market incentives; smart grid; smart meter

Average Harvested Power in THz WPT Systems Employing Resonant-Tunnelling Diodes - Shanin, Nikita; Clochiatti, Simone; Mayer, Kenneth; Cottatellucci, Laura; Weimann, Nils; Schober, Robert (2023 6th International Workshop on Mobile Terahertz Systems, IWMTS 2023, 2023)
In this paper, we study terahertz (THz) wireless power transfer (WPT) systems, where a single-antenna transmitter sends an energy signal to a single-antenna receiver. Since Schottky diodes, which are utilized in GHz energy harvesting (EH) circuits, are not usable for THz EH, we adopt an EH circuit employing a resonant tunnelling diode (RTD) at the receiver. However, the electrical properties of Schottky diodes and RTDs are different, and unlike EH receivers based on a single Schottky diode, an accurate EH model for RTD-based EH receivers is not available. Therefore, we model the dependency between the instantaneous harvested power at the EH device and the instantaneous received power by a piecewise non-linear function, whose parameters are adjusted to fit circuit simulation data. We formulate an optimization problem for the maximization of the average power harvested at the EH receiver subject to constraints imposed on the average and peak transmit powers. Then, for the solution of the formulated problem, we propose an equivalent monotonic EH model and we show that the optimal transmit signal distribution for WPT employs at most two mass points, which can be obtained as the solution of a min-max optimization problem. Our simulation results reveal that RTDs with low leakage currents and high breakdown voltages are preferable for WPT when the received signal power is low and high, respectively. Furthermore, we demonstrate that the proposed optimal input distribution yields significantly higher average harvested powers compared to a baseline scheme employing Gaussian transmit signals.
CRIS-Team Scopus Importer:2023-09-08
Keywords: Schottky diodes; Simulation; Circuit simulation; RLC circuits; Receivers; Wireless power transfer; Resonant tunneling devices

Average outage and non-outage duration of selective decode-and-forward relaying - Zlatanov, Nikola; Schober, Robert; Hadzi-Velkov, Zoran; Karagiannidis, George (12th Canadian Workshop on Information Theory, CWIT 2011, 2011)
In this paper, assuming transmission with fixed rate and fixed power, we derive the average duration of capacity outage and non-outage events of selective decode-and-forward relaying with repetition coding over slow Rayleigh fading channels. Furthermore, we develop high signal-to-noise ratio (SNR) approximations for both durations which provide significant insight into the impact of various system and channel parameters. For high SNR, on a double logarithmic scale, both the average outage duration (AOD) and the average non-outage duration (ANOD) become straight lines when plotted as functions of the SNR. However, while the slope of the ANOD improves with increasing diversity order, the slope of the AOD is 1/2 independent of the diversity order. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

A Widely Linear DF-MMSE Receiver for DS-CDMA with BPSK Modulation - Schober, Robert; Gerstacker, Wolfgang; Lampe, Lutz (Conference Proceedings, 2003)
In this paper, we propose a widely linear (WL) decision-feedback (DF) minimum mean-squared error (MMSE) receiver for direct-sequence code-division multiple access (DS-CDMA) with binary phase-shift keying (BPSK) modulation. Both theoretical considerations and simulations show that the novel receiver yields significant performance gains over both WL receivers without feedback and conventional DF receivers. In particular, the proposed WL DF-MMSE receiver achieves a high performance even in overloaded systems. For efficient adaptation of the filter coefficients a WL least-mean-square (LMS) algorithm and a WL recursive least-squares (RLS) algorithm are devised.
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.mobilk.awidel
Keywords: Binary phase shift keying; Direct-sequence code-division multiple Access; Multiaccess communication; Phase shift keying; Phase Modulation; Modulation coding; Performance gain; Feedback; Filters; Least squares approximation

A Widely Linear LMS Algorithm for MAI Suppression for DS-CDMA - Schober, Robert; Gerstacker, Wolfgang; Lampe, Lutz (Conference Proceedings, 2003)
In this paper, a novel data-aided stochastic gradient algorithm for adjustment of the widely linear (WL) minimum mean-squared error (MMSE) filter for multiple access interference (MAI) suppression for direct-sequence code-division multiple access (DS-CDMA) is introduced and analyzed. We give analytical expressions for the steady-state signal-to-interference-plus-noise ratio (SINR) of the proposed WL least-mean-square (LMS) algorithm, and we also investigate its speed of convergence. Both analytical considerations and simulations show in good agreement the superiority of the novel WL adaptive algorithm. Nevertheless, the computational complexity of the proposed algorithm is lower than that of the linear LMS algorithm.
UnivIS-Import:2015-04-16:Pub.2003.tech.IE.mobilk.awidel_3
Keywords: Least squares Approximation; Multiaccess communication; Multiple access interference; Algorithm design and Analysis; Stochastic processes; Nonlinear filters; Direct-sequence code-division multiple Access; Signal Analysis; Steady-state; Signal to noise ratio

A Wireless Joint Communication and Localization EMG-Sensing Concept for Movement Disorder Assessment - Brückner, Stefan; Weber, Jasmin; Michler, Fabian; Shanin, Nikita; Schober, Robert; Hagelauer, Amelie; Weigel, Robert; Gaßner, Heiko; Winkler, Jürgen; Eskofier, Björn; Vossiek, Martin (IEEE Journal of Electromagnetics, RF and Microwaves in Medicine and Biology, 2023)
Real-time sensory recording of the musculoskeletal system function is an important tool for the diagnosis, treatment planning, and optimal treatment execution of diseases, such as Parkinson's disease and osteoarthritis. This article presents a new wireless joint communication and localization electromyography (EMG)-sensing concept. An on-body sensor beacon measures EMG signals and wirelessly transmits them. At the same time, the spatial position and movement of the beacon is determined with high precision in real time using these transmitted radio signals. The seamless integration of multiple sensors avoids the need to synchronize and individually set up multiple independently operating sensors. An outstanding feature of the radio localization approach is that it does not require proprietary ultra-wideband signals or complicated time synchronization protocols, allowing for small and energy-efficient implementation. To demonstrate this novel concept, a wireless 3D-localizable EMG sensor was developed and experimentally evaluated. This new type of sensing concept allows, for the first time, the time-synchronous measurement of muscle activity and the underlying movement of the associated body part. URL: https://ieeexplore.ieee.org/stamp/stamp.jsp?tp=&arnumber=10286030&isnumber=8000303<br
Keywords: Array signal processing; EMG; localization; radar tracking; radio communication

Bargaining and price-of-anarchy in repeated inter-session network coding games - Mohsenian-Rad, Amir Hamed; Huang, Jianwei; Wong, Vincent W.S.; Schober, Robert (Proceedings - IEEE INFOCOM, 2010)
Most of the previous work on network coding has assumed that the users are not selfish and always follow the designed coding schemes. However, recent results have shown that selfish users do not have the incentive to participate in inter-session network coding in a static non-cooperative game setting. As a result, the worst-case network efficiency (i.e., the price-of-anarchy) can be as low as 22%. In this paper, we show that if the same game is played repeatedly, then the price-of-anarchy can be significantly improved to 48%. We propose a grim-trigger strategy that encourages users to cooperate and participate in the inter-session network coding. A key challenge is to determine a common cooperative coding rate that the users should mutually agree on. We propose to resolve the conflict of interest among the users through a bargaining process. We derive a tight upper bound for the price-of-anarchy which is valid for any bargaining scheme. Moreover, we propose a simple and efficient min-max bargaining solution that can achieve this upper bound. Our results represent one of the first steps towards designing practical inter-session network coding schemes that can achieve reasonable performance for selfish users. ©2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Beamforming and combining based on estimated channels in cooperative relay networks - Arti, M. K.; Mallik, Ranjan K.; Schober, Robert (2012 National Conference on Communications, NCC 2012, 2012)
In this paper, we study an amplify-and-forward (AF) based multiple-input multiple-output (MIMO) cooperative relay network in which beamforming is done by using estimated channels in a Rayleigh fading environment. A protocol for training of the source, relay and destination is described and methods of channel estimation are proposed. Simulation results show that the trained MIMO relay system based on beamforming outperforms the trained MIMO relay system without beamforming. It is also shown that the performance of the beamforming based MIMO relay system improves with increase in the number of receive antennas at the destination. We analyze the symbol error rate (SER) versus signal-to-noise ratio (SNR) performance of beamforming based AF relaying with perfect channel knowledge at the source, relay, and destination. An expression of the moment generating function (m.g.f.) of the received instantenous SNR at the destination is derived. By using this m.g.f., an exact expression for the SER of M-ary phase-shift keying is obtained. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Beamforming and combining in two-way AF MIMO relay networks - Arti, M. K.; Mallik, Ranjan K.; Schober, Robert (IEEE Communications Letters, 2013)
In this letter, we propose a beamforming and combining scheme for a two-way amplify-and-forward (AF) multiple-input multiple-output (MIMO) relay network. An approximate expression for the symbol error rate of the scheme in Rayleigh fading for M-ary phase-shift keying is obtained based on the moment generating function of the instantaneous received signal-to-noise ratio. The diversity order is also analytically derived. It is shown by simulations that the proposed scheme outperforms existing schemes for beamforming and combining in two-way AF MIMO relay systems. We also discuss beamforming and combining in a two-way AF MIMO relay system with estimated channel gains. © 1997-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Amplify-and-forward (AF) protocol; channel estimation; cooperative diversity; multiple-input multiple-output (MIMO) system

Beamforming design for secure SWIPT systems under a non-linear energy harvesting model - Boshkovska, Elena; Zlatanov, Nikola; Chen, Xiaoming; Ng, Derrick Wing Kwan; Schober, Robert (Energy Harvesting for Wireless Sensor Networks: Technology, Components and System Design, 2018)
Simultaneous wireless information and power transfer (SWIPT) is an appealing solution to extend the lifetime of wireless nodes and, hence, alleviate the energy bottleneck of energy-constrained wireless communication networks. SWIPT advocates the dual use of radio frequency signals for conveying information and energy concurrently, which introduces a paradigm shift in system design. This chapter focuses on the use of multiple antennas to improve the efficiency of wireless power transfer (WPT) and secure information transmission. In particular, our objective is to maximize the secrecy rate of a SWIPT system via beamforming. To this end, we formulate a non-convex optimization problem based on a practical nonlinear energy harvesting model. The problem formulation allows for the use of an energy signal to improve WPT efficiency and to provide communication security. The globally optimal solution of the design problem is obtained via a one-dimensional search and semidefinite programming (SDP) relaxation. Numerical results demonstrate that the proposed design can achieve a significant gain in secrecy rate compared to two baseline schemes.
CRIS-Team Scopus Importer:2020-01-31
Keywords: Beamforming; Nonlinear energy harvesting; Secure communication; Wireless information and power transfer

Beamforming for Cooperative Retransmission via User Relaying in Multiple-Antenna Cellular Systems - Ryu, Jong Yeol; Choi, Wan; Kim, Dong In; Schober, Robert (IEEE Transactions on Wireless Communications, 2014)
We propose a novel cooperative user relaying scheme for a two-user multiple-antenna downlink cellular system where each user has to receive a certain required amount of information. A user who successfully receives its required amount of information is supposed to help the other user in receiving its required amount of information through cooperative user relaying. For the proposed cooperative user relaying scheme, we jointly design linear beamformers at the base station over three transmission phases to minimize the total transmission time required for both users to receive their respective required amounts of information, which turn out to be approximated equivalent to the maximization of the sum throughput. In addition, considering a practical hybrid automatic repeat request (HARQ) protocol with user relaying, we modify the proposed scheme to minimize the required number of retransmissions. Our numerical results show that the proposed cooperative user relaying scheme achieves substantial gains over conventional transmission without user relaying in terms of both the average sum throughput and the transmission failure probability.<br
Keywords: Antennas; Throughput; Array signal processing; Silicon carbide; Downlink; Relays; Wireless communication

Beamforming for SC-FDMA transmission over MIMO ISI channels with decision-feedback equalization - Dang, Thi Uyen Ly; Ruder, Michael; Gerstacker, Wolfgang; Schober, Robert (2010 International ITG Workshop on Smart Antennas (WSA), 2010)
We consider transmit beamforming algorithms for single-carrier frequency-division multiple access (SC-FDMA) transmission over frequency-selective multiple-input multiple-output (MIMO) channels. The beamforming filters are designed for optimum performance of MIMO minimum mean-squared error decision-feedback equalization (MMSE-DFE). It turns out that eigenbeamforming diagonalizing the overall channel is optimum, and in addition an optimum power allocation has to be performed which is similar in spirit to classical results for the optimum continuous-time transmit filter for linear modulation formats obtained by Yang and Roy. Simulation results indicate that the proposed solution is beneficial for the block error rate performance of an SC-FDMA transmission scheme with strong channel coding and error-free decisions in the feedback path of MMSE-DFE, which can be guaranteed e.g. by equivalent Tomlinson-Harashima precoding at the transmitter sid

Bidirectional Buffer-Aided Relay Networks With Fixed Rate Transmission—Part II: Delay-Constrained Case - Jamali Kooshkghazi, Vahid; Zlatanov, Nikola; Schober, Robert (IEEE Transactions on Wireless Communications, 2014)
This is the second part of a two-part paper considering bidirectional relay networks with half-duplex nodes and block fading where the nodes transmit with a fixed transmission rate. In Part I, it was shown that a considerable gain in terms of sum throughput can be obtained by optimally selecting the transmission modes or, equivalently, the states of the nodes, i.e., the transmit, the receive, and the silent states, based on the qualities of the involved links. To enable adaptive transmission mode selection, the relay has to be equipped with two buffers for storage of the data received from the two users. The protocol proposed in Part I was delay unconstrained and provides an upper bound for the performance of practical delay-constrained protocols. In this paper, we propose two heuristic but efficient delay-constrained protocols, which can approach the performance upper bound reported in Part I, even in cases where only a small delay is permitted. The proposed protocols not only consider the instantaneous qualities of the involved links for adaptive mode selection but also take the states of the queues at the buffers into account, i.e., the number of packets in the queues. The average throughput and the average delay of the proposed delay-constrained protocols are evaluated by analyzing the Markov chain of the states of the queues. Numerical results show that the proposed protocols outperform existing bidirectional relaying protocols for delay-constrained transmission. <br
Keywords: Protocols; Delays; Throughput; Markov processes; Signal to noise ratio; Relay networks (telecommunications)

Biological Optical-to-Chemical Signal Conversion Interface: A Small-scale Modulator for Molecular Communications - Grebenstein, Laura; Kirchner, Jens; Stavracakis Peixoto, Renata; Zimmermann, Wiebke; Wicke, Wayan; Ahmadzadeh, Arman; Jamali, Vahid; Fischer, Georg; Weigel, Robert; Burkovski, Andreas; Schober, Robert (ACM NANOCOM 2018: 5TH ACM INTERNATIONAL CONFERENCE ON NANOSCALE COMPUTING AND COMMUNICATION, 2018)
CRIS-Team WoS Importer:2019-02-22

Biological Optical-to-Chemical Signal Conversion Interface: A Small-scale Modulator for Molecular Communications - Grebenstein, Laura; Kirchner, Jens; Stavracakis Peixoto, Renata; Zimmermann, Wiebke; Irnstorfer, Florian; Wicke, Wayan; Ahmadzadeh, Arman; Jamali Kooshkghazi, Vahid; Fischer, Georg; Weigel, Robert; Burkovski, Andreas; Schober, Robert (IEEE Transactions on Nanobioscience, 2018)
Although many exciting applications of molecular communication (MC) systems are envisioned to be at microscale, the MC testbeds reported in the literature so far are mostly at macroscale. This may partially be due to the fact that controlling an MC system at microscale is challenging. To link the macroworld to the microworld, we propose and demonstrate a biological signal conversion interface that can also be seen as a microscale modulator. In particular, the proposed interface transduces an optical signal, which is controlled using a light-emitting diode (LED), into a chemical signal by changing the pH of the environment. The modulator is realized using Escherichia coli bacteria as microscale entity expressing the light-driven proton pump gloeorhodopsin from Gloeobacter violaceus. Upon inducing external light stimuli, these bacteria locally change their surrounding pH level by exporting protons into the environment. To verify the effectiveness of the proposed optical-to-chemical signal converter, we analyze the pH signal measured by a pH sensor, which serves as receiver. We develop an analytical parametric model for the induced chemical signal as a function of the applied optical signal. Using this model, we derive a training-based channel estimator which estimates the parameters of the proposed model to fit the measurement data based on a least square error approach. We further derive the optimal maximum likelihood detector and a suboptimal low-complexity detector to recover the transmitted data from the measured received signal. It is shown that the proposed parametric model is in good agreement with the measurement data. Moreover, for an example scenario, we show that the proposed setup is able to successfully convert an optical signal representing a sequence of binary symbols into a chemical signal with a bit rate of 1 bit/min and recover the transmitted data from the chemical signal using the proposed estimation and detection schemes. The proposed modulator may form the basis for future MC testbeds and applications at microscale.
Keywords: Microorganisms; Protons; Biomedical optical Imaging; Optical pumping; Optical Receivers; Optical sensors; Chemicals

Bit-interleaved coded modulation for hybrid RF/FSO systems - He, Ben; Schober, Robert (IEEE International Conference on Communications, 2009)
In this paper, we propose a novel architecture for hybrid radio frequency (RF)/free-space optics (FSO) wireless systems. In particular, we show that a hybrid system robust to all weather conditions is obtained by joint bit-interleaved coded modulation (BICM) of the bit steams transmitted over the RF and FSO sub-channels. An asymptotic performance analysis reveals that a properly designed convolutional code can exploit the diversity offered by the independent sub-channels. Furthermore, we develop a code design criterion and provide an efficient code search procedure. Simulation results show that hybrid RF/FSO systems with BICM outperform previously proposed hybrid systems employing a simple repetition code and selection diversity. ©2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Bit-interleaved coded modulation for hybrid RF/FSO systems - He, Ben; Schober, Robert (IEEE Transactions on Communications, 2009)
In this paper, we propose a novel architecture for hybrid radio frequency (RF)/free-space optics (FSO) wireless systems. Hybrid RF/FSO systems are attractive since the RF and FSO sub-systems are affected differently by weather and fading phenomena. For example, while 60-GHz RF systems are susceptible to rain, fog is detrimental to FSO systems. We show that a hybrid system robust to these impairments is obtained by joint bit-interleaved coded modulation (BICM) of the bit steams transmitted over the RF and FSO sub-channels. An asymptotic performance analysis reveals that a properly designed convolutional code can exploit the diversity offered by the independent sub-channels. Furthermore, we develop code design and power assignment criteria and provide an efficient code search procedure. The cut-off rate of the proposed hybrid system is also derived and compared to that of hybrid systems with perfect channel state information at the transmitter. Simulation results show that hybrid RF/FSO systems with BICM outperform previously proposed hybrid systems employing a simple repetition code and selection diversity. Copyright © 2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Bounds on distance estimation via diffusive molecular communication - Noel, Adam; Cheung, Karen C.; Schober, Robert (2014 IEEE Global Communications Conference, 2014)
This paper studies distance estimation for diffusive molecular communication. The strength of the channel impulse response generally decreases with distance, so it is measured to estimate the distance. The Cramer-Rao lower bound on the variance of the distance estimation error is derived. The lower bound is derived for a physically unbounded environment with molecule degradation and steady uniform flow. The maximum likelihood distance estimator is derived and its accuracy is shown via simulation to perform very close to the Cramer-Rao lower bound. An existing protocol is shown to be equivalent to the maximum likelihood distance estimator if only one observation is made. Simulation results also show the accuracy of existing protocols with respect to the Cramer-Rao lower bound.<br
Keywords: Protocols; Maximum likelihood estimation; Degradation; Accuracy; Estimation error; Nanotechnology

Buffer-aided BICM-OFDM relaying - Islam, Toufiqul; Ikhlef, Aissa; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2012)
In this paper, we study a cooperative diversity scheme for wireless systems where the relay is equipped with a buffer. We consider practical frequency-selective channels and adopt the combination of bit interleaved coded modulation and orthogonal frequency division multiplexing (BICM-OFDM). We propose a novel link selection protocol for BICM-OFDM systems where the relay either transmits or receives in a given time slot depending on the quality of the links. We derive closed-form upper bounds for the asymptotic worst-case pairwise error probability and the diversity gain of the considered buffer-aided relaying scheme for infinite buffer size. We show that impressive diversity gains can be achieved with buffer-aided relaying compared to conventional relaying at the expense of packet delay. In fact, for buffers of infinite (or very large) size, the diversity gain is doubled for links with identical frequency diversity, and even a higher diversity gain advantage is possible for non-identical diversity links. The derived analytical results and performance gains are corroborated by simulation results, where we also show that for buffers of moderate size, a significant coding gain can be achieved, if not any diversity gain. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Buffer-aided cooperative communications: Opportunities and challenges - Zlatanov, Nikola; Ikhlef, Aissa; Islam, Toufiqul; Schober, Robert (IEEE Communications Magazine, 2014)
Cooperative communication can increase the throughput and/or extend the coverage of wireless networks. However, in conventional cooperative networks, half-duplex relays transmit and receive under a prefixed schedule, which does not allow them to exploit the best receiving and transmitting channels, thus limiting performance. Recently, new protocols have been proposed that circumvent this problem by making use of the additional flexibility offered by relays with buffers. Compared to conventional relaying protocols, these buffer-aided protocols provide significant gains in terms of throughput, diversity, and signal-to-noise ratio. This article outlines several buffer-aided relaying protocols for different network topologies, including one-way single- and multi-relay networks as well as two-way single-relay networks. Moreover, some practical challenges inherent to buffer-aided relaying, such as increased delay and complexity, and topics for future research are discussed. Copyright © 2014 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Buffer-Aided Diamond Relay Network With Block Fading and Inter-Relay Interference - Simoni, Renato; Jamali Kooshkghazi, Vahid; Zlatanov, Nikola; Schober, Robert; Pierucci, Laura; Fantacci, Romano (IEEE Transactions on Wireless Communications, 2016)
A simple diamond half-duplex relay network composed of a source, two decode-and-forward half-duplex relays, and a destination is considered, where a direct link between the source and the destination does not exist. For this network, we study the case of buffer-aided relays, where the relays are equipped with buffers. Each relay can receive data from the source, store it in the buffer, and forward it to the destination, when the channel conditions are advantageous. Thereby, buffering enables adaptive scheduling of the transmissions and receptions over time, which allows the network to exploit the diversity offered by the fading channels. For the considered half-duplex network, four transmission modes are defined based on whether the relay nodes receive or transmit. In this paper, we derive the locally optimal scheduling of the transmission modes over time and investigate the achievable average rate, when the relays are affected by inter-relay interference. Since the proposed buffer-aided transmission policies introduce unbounded delay, we provide a sub-optimal buffer-aided transmission policy with limited delay. Moreover, for inter-relay interference cancellation, we consider two coding schemes with different complexities. In the first scheme, we employ dirty paper coding, which entails a high complexity, whereas in the second scheme, we adopt a low-complexity technique based on successive interference cancellation at the receiving relay nodes and optimal power allocation at the transmitting nodes. Our numerical results show that the proposed protocols, with and without delay constraints, outperform existing protocols for the considered network from the literature.<br
Keywords: Relays; Protocols; Interference; Diamond; Delays; Fading channels; Encoding

Buffer-Aided diamond relay network with block fading - Simoni, Renato; Jamali Kooshkghazi, Vahid; Zlatanov, Nikola; Schober, Robert; Pierucci, Laura; Fantacci, Romano (2015 IEEE International Conference on Communications (ICC), 2015)
A simple diamond half-duplex relay network composed of a source, two half-duplex relays, and a destination is considered, where no direct link between the source and the destination is exists. For this network, we investigate the achievable rate when the relays are equipped with buffers. Buffer-aided relays can receive data from the source, store it in their buffers, and forward it to the destination when the channel conditions are more advantageous. Thereby, buffering enables adaptive scheduling of the transmissions and receptions over time, which allows the network to better exploit the diversity offered by the fading channel. For the considered network, because of the half-duplex relays, four transmission modes are employed based on whether the relay nodes receive or transmit. Considering these four transmission modes, in this paper, we derive the optimal transmission mode selection policy such that the received data rate at the destination is maximized. Furthermore, based on numerical examples, we show that the proposed protocol outperforms the existing protocols for the considered network in the literature.<br
Keywords: Protocols; Delays; Fading; Diamonds; Relay networks (telecommunications); Signal to noise ratio

Buffer-aided half-duplex relaying can outperform ideal full-duplex relaying - Zlatanov, Nikola; Schober, Robert (IEEE Communications Letters, 2013)
We consider a three-node relay network comprised of a source, a relay, and a destination, and compare the throughputs of ideal full-duplex (FD) and half-duplex (HD) relaying. For FD relaying, we assume that the relay uses half of its antennas for reception and the other half for transmission. In contrast, for HD relaying, the relay uses all of its antennas for either reception or transmission and a buffer for data storage. Our results show that if the numbers of antennas at source and destination are equal to or larger than the number of antennas at the relay, HD relaying may achieve a similar, and in some cases even higher, throughput compared to ideal FD relaying. © 1997-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: buffer-aided; full-duplex; Half-duplex; relaying

Buffer-aided relaying in a three node network - Zlatanov, Nikola; Schober, Robert; Lampe, Lutz (IEEE International Symposium on Information Theory - Proceedings, 2012)
We propose a buffer-aided relaying protocol for a three node relay network comprised of a source, a half-duplex relay with buffer, and a destination. We assume a direct source-destination link is available and all links undergo fading. The proposed protocol enables the half-duplex relay to choose its reception and transmission time slots adaptively and based on the quality of the involved links. We derive the achievable ergodic rate of the considered three-node network for the proposed protocol. Our results show that this achievable ergodic rate exceeds existing unachievable ergodic capacity upper bounds for the three-node half-duplex relay channel with the relay always alternating between reception and transmission in successive time slots. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Buffer-aided relaying with adaptive link selection - Zlatanov, Nikola; Schober, Robert; Popovski, Petar (IEEE Journal on Selected Areas in Communications, 2013)
In this paper, we consider a simple network consisting of a source, a half-duplex decode-and-forward relay, and a destination. We propose a new relaying protocol employing adaptive link selection, i.e., in any given time slot, based on the channel state information of the source-relay and the relay-destination link a decision is made whether the source or the relay transmits. In order to avoid data loss at the relay, adaptive link selection requires the relay to be equipped with a buffer such that data can be queued until the relay-destination link is selected for transmission. We study both delay-constrained and delay-unconstrained transmission. For the delay-unconstrained case, we characterize the optimal link selection policy, derive the corresponding throughput, and develop an optimal power allocation scheme. For the delay-constrained case, we propose to starve the buffer of the relay by choosing the decision threshold of the link selection policy smaller than the optimal one and derive a corresponding upper bound on the average delay. Furthermore, we propose a modified link selection protocol which avoids buffer overflow by limiting the queue size. Our analytical and numerical results show that buffer-aided relaying with adaptive link selection achieves significant throughput gains compared to conventional relaying protocols with and without buffers where the relay employs a fixed schedule for reception and transmission. © 1983-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: adaptive link selection; buffer-aided; delay; relaying; throughput; Wireless relay network

Buffer-aided relaying with adaptive link selection-fixed and mixed rate transmission - Zlatanov, Nikola; Schober, Robert (IEEE Transactions on Information Theory, 2013)
We consider a simple network consisting of a source, a half-duplex decode-and-forward relay with a buffer, and a destination. We assume that the direct source-destination link is not available and all links undergo fading. We propose two new buffer-aided relaying schemes with different requirements regarding the availability of channel state information at the transmitter (CSIT). In the first scheme, neither the source nor the relay has full CSIT, and consequently, both nodes are forced to transmit with fixed rates. In contrast, in the second scheme, the source does not have full CSIT and transmits with fixed rate but the relay has full CSIT and adapts its transmission rate accordingly. In the absence of delay constraints, for both fixed rate and mixed rate transmission, we derive the throughput-optimal buffer-aided relaying protocols which select either the source or the relay for transmission based on the instantaneous signal-to-noise ratios (SNRs) of the source-relay and relay-destination links. In addition, for the delay constrained case, we develop buffer-aided relaying protocols that achieve a predefined average delay. Compared to conventional relaying protocols, which select the transmitting node according to a predefined schedule independent of the instantaneous link SNRs, the proposed buffer-aided protocols with adaptive link selection achieve large performance gains. In particular, for fixed rate transmission, we show that the proposed protocol achieves a diversity gain of two as long as an average delay of more than three time slots can be afforded. Furthermore, for mixed rate transmission with an average delay of E{T} time slots, a multiplexing gain of r=1-1/(2E{T}) is achieved. As a by-product of the considered link-adaptive protocols, we also develop a novel conventional relaying protocol for mixed rate transmission, which yields the same multiplexing gain as the protocol with adaptive link selection. Hence, for mixed rate transmission, for sufficiently large average delays, buffer-aided half-duplex relaying with and without adaptive link selection does not suffer from a multiplexing gain loss compared to full-duplex relaying. © 1963-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Adaptive link selection; buffer-aided; delay; diversity gain; multiplexing gain; outage probability; relaying; throughput

Buffer-aided relaying with discrete transmission rates. - Wicke, Wayan; Zlatanov, Nikola; Jamali Kooshkghazi, Vahid; Schober, Robert (Proc. CWIT, 2015)

Buffer-aided relaying with discrete transmission rates for the two-hop half-duplex relay network - Wicke, Wayan; Zlatanov, Nikola; Jamali Kooshkghazi, Vahid; Schober, Robert (IEEE Transactions on Wireless Communications, 2017)

Buffer-aided relaying with mixed rate transmission - Zlatanov, Nikola; Schober, Robert (IWCMC 2012 - 8th International Wireless Communications and Mobile Computing Conference, 2012)
We investigate a simple three-node network consisting of a source, a half-duplex decode-and-forward relay with a buffer, and a destination. We assume that a direct source-destination link is not available and all links undergo fading. We consider the case where the source has no channel state information (CSI) and thus is forced to transmit with a fixed rate. On the other hand, the relay has full CSI and thus is able to adapt its rate to the underlaying channel. We propose a buffer-aided relaying protocol which allows the relay to choose its transmission and reception time slots adaptively and based on the quality of the source-relay and relay-destination links. For this system, we derive the maximum achievable throughput and the fraction of throughput lost due to outages. Our results reveal that compared to the conventional case when the relay always alternates between reception and transmission, a throughput gain of up to 100% is possible. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: adaptive link selection; Buffer-aided; delay; relaying; throughput

Buffers improve the performance of relay selection - Ikhlef, Aissa; Michalopoulos, Diomidis S.; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2011)
We show that the performance of relay selection can be improved by employing relays with buffers. Under the idealized assumption that no buffer is full or empty, the best source-relay and the best relay-destination channels can be simultaneously exploited by selecting the corresponding relays for reception and transmission, respectively. The resulting relay selection scheme is referred to as max-max relay selection (MMRS). Since for finite buffer sizes, empty and full buffers are practically unavoidable if MMRS is employed, we propose a hybrid relay selection (HRS) scheme, which is a combination of conventional best relay selection (BRS) and MMRS. We analyze the outage probabilities of MMRS and HRS and show that both schemes achieve the same diversity gain as conventional BRS and a superior coding gain. Furthermore, our results show that for moderate buffer sizes (e.g. 30 packets) HRS closely approaches the performance of idealized MMRS and the performance gain compared to BRS approaches 3 dB as the number of relays increases. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Cache-Aided Massive MIMO: Linear Precoding Design and Performance Analysis - Wei, Xiao; Xiang, Lin; Cottatellucci, Laura; Jiang, Tao; Schober, Robert (ICC 2019 - 2019 IEEE International Conference on Communications (ICC), 2019)
In this paper, we propose a novel joint caching and massive multiple-input multiple-output (MIMO) transmission scheme, referred to as cache-aided massive MIMO, for advanced downlink cellular communications. In addition to reaping the conventional advantages of caching and massive MIMO, the proposed scheme also exploits the side information provided by cached files for interference cancellation at the receivers. This interference cancellation increases the degrees of freedom available for precoding design. In addition, the power freed by the cache-enabled offloading can benefit the transmissions to the users requesting non-cached files. The resulting performance gains are not possible if caching and massive MIMO are designed separately. We analyze the performance of cache-aided massive MIMO for cache-dependent maximum-ratio transmission (MRT), zero-forcing (ZF) precoding, and regularized zero-forcing (RZF) precoding. Lower bounds on the ergodic achievable rates are derived in closed form for MRT and ZF precoding. The ergodic achievable rate of RZF precoding is obtained for the case when the numbers of transmit antennas and users are large but their ratio is fixed. Compared to conventional massive MIMO, the proposed cache-aided massive MIMO scheme achieves a significantly higher ergodic rate especially when the number of users approaches the number of transmit antennas.<br
Keywords: MIMO communication; Precoding; Interference cancellation; Antennas; NOMA; Performance gain

Cache-aided non-orthogonal multiple access - Xiang, Lin; Ng, Derrick Wing Kwan; Ge, Xiaohu; Ding, Zhiguo; Wong, Vincent W.S.; Schober, Robert (IEEE International Conference on Communications, 2018)
In this paper, we propose a novel joint caching and non-orthogonal multiple access (NOMA) scheme to facilitate advanced downlink transmission for next generation cellular networks. In addition to reaping the conventional advantages of caching and NOMA transmission, the proposed cache-aided NOMA scheme also exploits cached data for interference cancellation which is not possible with separate caching and NOMA transmission designs. Furthermore, as caching can help to reduce the residual interference power, several decoding orders are feasible at the receivers, and these decoding orders can be flexibly selected for performance optimization. We characterize the achievable rate region of cache-aided NOMA and investigate its benefits for minimizing the time required to complete video file delivery. Our simulation results reveal that, compared to several baseline schemes, the proposed cache-aided NOMA scheme significantly expands the achievable rate region for downlink transmission, which translates into substantially reduced file delivery times.
CRIS-Team Scopus Importer:2020-01-31

Cache-Aided Non-Orthogonal Multiple Access: The Two-User Case - Xiang, Lin; Ng, Derrick Wing Kwan; Ge, Xiaohu; Ding, Zhiguo; Wong, Vincent W.S.; Schober, Robert (IEEE Journal of Selected Topics in Signal Processing, 2019)
In this paper, we propose a cache-aided non-orthogonal multiple access (NOMA) scheme for spectrally efficient downlink transmission. The proposed scheme not only reaps the benefits associated with NOMA and caching, but also exploits the data cached at the users for interference cancelation. As a consequence, caching can help to reduce the residual interference power, making multiple decoding orders at the users feasible. The resulting flexibility in decoding can be exploited for improved NOMA detection. We characterize the achievable rate region of cache-aided NOMA and derive the Pareto optimal rate tuples forming the boundary of the rate region. Moreover, we optimize cache-aided NOMA for minimization of the time required for completing file delivery. The optimal decoding order and the optimal transmit power and rate allocation are derived as functions of the cache status, the file sizes, and the channel conditions. Simulation results confirm that, compared to several baseline schemes, the proposed cache-aided NOMA scheme significantly expands the achievable rate region and increases the sum rate for downlink transmission, which translates into substantially reduced file delivery times.<br
Keywords: NOMA; Decoding; Streaming media; Interference; Resource Management; Performance gain; Downlink

Cache-Aided Non-Orthogonal Multiple Access: The Two-User Case - Xiang, Lin; Ng, Derrick Wing Kwan; Ge, Xiaohu; Ding, Zhiguo; Wong, Vincent W. S.; Schober, Robert (IEEE Journal of Selected Topics in Signal Processing, 2019)
In this paper, we propose a cache-aided non-orthogonal multiple access (NOMA) scheme for spectrally efficient downlink transmission. The proposed scheme not only reaps the benefits associated with NOMA and caching, but also exploits the data cached at the users for interference cancelation. As a consequence, caching can help to reduce the residual interference power, making multiple decoding orders at the users feasible. The resulting flexibility in decoding can be exploited for improved NOMA detection. We characterize the achievable rate region of cache-aided NOMA and derive the Pareto optimal rate tuples forming the boundary of the rate region. Moreover, we optimize cacheaided NOMA for minimization of the time required for completing file delivery. The optimal decoding order and the optimal transmit power and rate allocation are derived as functions of the cache status, the file sizes, and the channel conditions. Simulation results confirm that, compared to several baseline schemes, the proposed cache-aided NOMA scheme significantly expands the achievable rate region and increases the sum rate for downlink transmission, which translates into substantially reduced file delivery times.
CRIS-Team WoS Importer:2019-06-18

Cache-Enabled Physical Layer Security for Video Streaming in Backhaul-Limited Cellular Networks - Xiang, Lin; Ng, Derrick Wing Kwan; Schober, Robert; Wong, Vincent W. S. (IEEE Transactions on Wireless Communications, 2017)
In this paper, we propose a novel wireless caching scheme to enhance the physical layer security of video streaming in cellular networks with limited backhaul capacity. By proactively sharing video data across a subset of base stations (BSs) through both caching and backhaul loading, secure cooperative joint transmission of several BSs can be dynamically enabled in accordance with the cache status, the channel conditions, and the backhaul capacity. Assuming imperfect channel state information (CSI) at the transmitters, we formulate a two-stage non-convex mixed-integer robust optimization problem for minimizing the total transmit power while providing the quality of service and guaranteeing communication secrecy during video delivery, where the caching and the cooperative transmission policy are optimized in an offline video caching stage and an online video delivery stage, respectively. Although the formulated optimization problem turns out to be NP-hard, low-complexity polynomial-time algorithms, whose solutions are globally optimal under certain conditions, are proposed for cache training and video delivery control. Caching is shown to be beneficial as it reduces the data sharing overhead imposed on the capacity-constrained backhaul links, introduces additional secure degrees of freedom, and enables a power-efficient communication system design. Simulation results confirm that the proposed caching scheme achieves simultaneously a low secrecy outage probability and a high power efficiency. Furthermore, due to the proposed robust optimization, the performance loss caused by imperfect CSI knowledge can be significantly reduced when the cache capacity becomes large.<br
Keywords: Streaming media; Wireless communication; Cellular networks; Communication system security; Quality of service; Robustness; Optimization

Can cooperation reduce the average transmitted power per participating user? - Michalopoulos, Diomidis S.; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2013)
The answer is (in general) affirmative: For a given target bit error rate (BER), cooperation reduces the average transmitted power per user when partners are appropriately selected. The more cooperating users are available and the larger the propagation exponent, the larger the reduction on transmitted power per user. This conclusion is drawn from a preliminary study which considers a community of users located randomly along a straight line. The users communicate with a Base Station (BS) located at the end of this line, and the transmission is subject to path loss. The communication is established either directly (Direct Mode), or via another member of the community (Relaying Mode). We show that the total power needed to achieve a certain BER at the BS is on average lower for the Relaying Mode than for the Direct Mode, even without exploiting any receive diversity benefit. There exist cases, however, where the Relaying Mode is not beneficial. This is true for environments with a propagation exponent smaller than two (δ < 2). For δ = 2, the Relaying Mode performs identical to the Direct Mode. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Capacity of the Gaussian Two-Hop Full-Duplex Relay Channel With Residual Self-Interference - Zlatanov, Nikola; Sippel, Erik; Jamali Kooshkghazi, Vahid; Schober, Robert (IEEE Transactions on Communications, 2017)
In this paper, we investigate the capacity of the Gaussian two-hop full-duplex (FD) relay channel with residual self-interference. This channel is comprised of a source, an FD relay, and a destination, where a direct source-destination link does not exist and the FD relay is impaired by residual self-interference. We adopt the worst case linear self-interference model with respect to the channel capacity, and model the residual self-interference as a Gaussian random variable whose variance depends on the amplitude of the transmit symbol of the relay. For this channel, we derive the capacity and propose an explicit capacity-achieving coding scheme. Thereby, we show that the optimal input distribution at the source is Gaussian and its variance depends on the amplitude of the transmit symbol of the relay. On the other hand, the optimal input distribution at the relay is discrete or Gaussian, where the latter case occurs only when the relay-destination link is the bottleneck link. The derived capacity converges to the capacity of the two-hop ideal FD relay channel without self-interference and to the capacity of the two-hop half-duplex (HD) relay channel in the limiting cases when the residual self-interference is zero and infinite, respectively. Our numerical results show that significant performance gains are achieved with the proposed capacity-achieving coding scheme compared with the achievable rates of conventional HD relaying and/or conventional FD relaying.

Capacity of the Gaussian Two-Hop Full-Duplex Relay Channel with Self-Interference - Zlatanov, Nikola; Sippel, Erik; Jamali, Vahid; Schober, Robert (2016 IEEE Global Communications Conference (GLOBECOM), 2016)
In this paper, we investigate the capacity of the Gaussian two-hop full-duplex (FD) relay channel with self-interference. This channel is comprised of a source, an FD relay, and a destination, where a direct source-destination link does not exist and the FD relay is impaired by self- interference. We model the self-interference as an additive Gaussian random variable whose variance is proportional to the amplitude of the transmit symbol at the relay. For this channel, we derive the capacity and propose an explicit capacity- achieving coding scheme. Thereby, we show that the optimal input distribution at the source is Gaussian and its variance depends on the amplitude of the transmit symbol at the relay. On the other hand, the optimal input distribution at the relay is discrete or Gaussian, where the latter case occurs only when the relay- destination link is the bottleneck link. The derived capacity converges to the capacity of the two-hop ideal FD relay channel without self- interference and to the capacity of the two-hop half-duplex (HD) relay channel in the limiting cases when the self-interference is zero and infinite, respectively. Our numerical results show that significant performance gains are achieved using the proposed capacity-achieving coding scheme compared to the achievable rates of conventional FD relaying and HD relayin
lhft_intern.bib::SipplE2016a

Capacity of the two-hop full-duplex relay channel with wireless power transfer from relay to battery-less source - Zlatanov, Nikola; Wing Kwan Ng, Derrick; Schober, Robert (2016 IEEE International Conference on Communications (ICC), 2016)
In this paper, we investigate a communication system comprised of a wireless sensor which harvests radio frequency (RF) energy from a full-duplex relay node and exploits this energy to transmit data to a destination node via the relay node. Thereby, the relay has two functions. Namely, it transfers RF energy to the sensor via wireless power transfer and relays the information received from the sensor to the destination. Moreover, we assume that the sensor is too small to be equipped with a battery. As a result, the energy of each symbol transmitted by the sensor is limited by the energy harvested during the previous symbol interval. For this system model, we derive the capacity for an average power constraint at the relay. Thereby, we show that in order to achieve the capacity, the sensor has to harvest the RF energy that reaches the sensor when the relay transmits information to the destination. As a result, the relay does not need to dedicate energy strictly for energy harvesting since the energy spent by the relay for information transfer can also be used by the sensor to harvest energy. In a numerical example, we compare the derived capacity to the rates of two benchmark schemes. Our results show that using the optimal input distributions at both the sensor and the relay is essential for high performance.<br
Keywords: Relays; Radio frequency; Wireless communication; Wireless sensor Networks; Batteries; AWGN channels; Sensors

Capacity of the Two-Hop Relay Channel With Wireless Energy Transfer From Relay to Source and Energy Transmission Cost - Zlatanov, Nikola; Wing Kwan Ng, Derrick; Schober, Robert (IEEE Transactions on Wireless Communications, 2016)
In this paper, we investigate a communication system comprised of an energy harvesting (EH) source, which harvests radio frequency (RF) energy from an out-of-band full-duplex relay node and exploits this energy to transmit data to a destination node via the relay node. We assume two scenarios for the battery of the EH source. In the first scenario, we assume that the EH source is not equipped with a battery and thereby cannot store energy. As a result, the RF energy harvested during one symbol interval can only be used in the following symbol interval. In the second scenario, we assume that the EH source is equipped with a battery having unlimited storage capacity in which it can store the harvested RF energy. As a result, the RF energy harvested during one symbol interval can be used in any of the following symbol intervals. For both system models, we derive the channel capacity subject to an average power constraint at the relay and an additional energy transmission cost at the EH source. We compare the derived capacities to the achievable rates of several benchmark schemes. Our results show that using the optimal input distributions at both the EH source and the relay is essential for high performance. Moreover, we demonstrate that neglecting the energy transmission cost at the source can result in a severe overestimation of the achievable performance.<br
Keywords: Relays; Batteries; Wireless communication; Radio frequency; AWGN channels; Channel models; Energy exchange

Censored distributed space-time coding for wireless sensor networks - Yiu, S.; Schober, Robert (EURASIP Journal on Advances in Signal Processing, 2008)
We consider the application of distributed space-time coding in wireless sensor networks (WSNs). In particular, sensors use a common noncoherent distributed space-time block code (DSTBC) to forward their local decisions to the fusion center (FC) which makes the final decision. We show that the performance of distributed space-time coding is negatively affected by erroneous sensor decisions caused by observation noise. To overcome this problem of error propagation, we introduce censored distributed space-time coding where only reliable decisions are forwarded to the FC. The optimum noncoherent maximum-likelihood and a low-complexity, suboptimum generalized likelihood ratio test (GLRT) FC decision rules are derived and the performance of the GLRT decision rule is analyzed. Based on this performance analysis we derive a gradient algorithm for optimization of the local decision/censoring threshold. Numerical and simulation results show the effectiveness of the proposed censoring scheme making distributed space-time coding a prime candidate for signaling in WSNs.
CRIS-Team Scopus Importer:2020-02-03

Channel Capacity of Magnetic Induction Based Wireless Underground Sensor Networks under Practical Constraints - Kisseleff, Steven; Gerstacker, Wolfgang; Schober, Robert; Sun, Zhi; Akyildiz, Ian F. (IEEE Wireless Communications and Networking Conference (WCNC), 2013)

Channel Coding Rate for Finite Blocklength Faster-Than-Nyquist Signaling - Mohammadkarimi, Mostafa; Schober, Robert; Wong, Vincent W.S. (IEEE Communications Letters, 2021)
The fundamental tradeoff between low latency and high reliability makes the design of ultra-reliable low-latency communications (URLLC) wireless systems challenging. To support URLLC for a fixed bandwidth, faster-than-Nyquist (FTN) signaling is a promising approach since it increases the degrees of freedom (i.e., channel uses) per time interval, which can be exploited to improve reliability. In this letter, we derive analytical expressions for the approximate maximum channel coding rate (MCCR) for finite blocklength FTN signaling for water-filling and equal power allocations. We show that for practical non-sinc square-root Nyquist pulses, the penalty on the rate incurred due to the finite blocklength can be significantly reduced by non-orthogonal FTN transmission. Our results reveal that the MCCR for finite blocklength FTN signaling exceeds the Shannon capacity achieved for infinite blocklength and orthogonal transmission.
CRIS-Team Scopus Importer:2021-01-22
Keywords: channel dispersion; constrained channel capacity; Faster-than-Nyquist (FTN) signaling; finite blocklength

Channel estimation and decoding of OSTBC in two-way AF MIMO relay networks - Arti, M. K.; Mallik, Ranjan K.; Schober, Robert (IEEE Vehicular Technology Conference, 2013)
This paper investigates the problem of channel estimation and decoding of orthogonal space time block codes (OSTBCs) in a two-way amplify-and-forward (AF) multiple-input multiple-output (MIMO) relay network. We propose a joint decoder for a pilot symbol-aided two-way AF based MIMO cooperative system. The proposed decoder jointly processes the received OSTBC data and pilot matrix by using vector derivative over the two-way MIMO relay channel. We derive a closed-form expression in Rayleigh fading for the moment generating function of the received signal-to-noise ratio at both cooperating users for the proposed decoder; and then investigate the system performance based on analytical expressions for the symbol error rate, diversity order, and array gain. Copyright © 2013 by the Institute of Electrical and Electronic Engineers, Inc.
CRIS-Team Scopus Importer:2020-02-03

Channel Estimation for Diffusive Molecular Communications - Jamali Kooshkghazi, Vahid; Ahmadzadeh, Arman; Jardin, Christophe; Sticht, Heinrich; Schober, Robert (IEEE Transactions on Communications, 2016)
In molecular communication (MC) systems, the expected number of molecules observed at the receiver over time after the instantaneous release of molecules by the transmitter is referred to as the channel impulse response (CIR). Knowledge of the CIR is needed for the design of detection and equalization schemes. In this paper, we present a training-based CIR estimation framework for MC systems, which aims at estimating the CIR based on the observed number of molecules at the receiver due to emission of a sequence of known numbers of molecules by the transmitter. Thereby, we distinguish two scenarios depending on whether or not statistical channel knowledge is available. In particular, we derive maximum likelihood and least sum of square errors estimators, which do not require any knowledge of the channel statistics. For the case, when statistical channel knowledge is available, the corresponding maximum a posteriori and linear minimum mean square error estimators are provided. As performance bound, we derive the classical Cramer Rao (CR) lower bound, valid for any unbiased estimator, which does not exploit statistical channel knowledge, and the Bayesian CR lower bound, valid for any unbiased estimator, which exploits statistical channel knowledge. Finally, we propose the optimal and suboptimal training sequence designs for the considered MC system. Simulation results confirm the analysis and compare the performance of the proposed estimation techniques with the respective CR lower bounds.<br
Keywords: Channel estimation; Receivers; Transmitters; Channel models; Maximum likelihood estimation; Training

Channel Estimation for Intelligent Reflecting Surface-Assisted Millimeter Wave MIMO Systems - Lin, Tian; Yu, Xianghao; Zhu, Yu; Schober, Robert (2020 IEEE Global Communications Conference, GLOBECOM 2020 - Proceedings, 2020)
Intelligent reflecting surfaces (IRSs) are regarded as promising enablers for future millimeter wave (mmWave) wireless communication, due to their ability to create favorable line-of-sight (LoS) propagation environments. In this paper, we investigate channel estimation in downlink IRS-assisted mmWave multiple-input multiple-output (MIMO) systems. By leveraging the sparsity of mmWave channels, we formulate the channel estimation problem as a fixed-rank constrained non-convex optimization problem. To tackle the non-convexity, an efficient algorithm is proposed by capitalizing on alternating minimization and manifold optimization (MO), which yields a locally optimal solution. Simulation results show that the proposed MObased estimation (MO-EST) algorithm significantly outperforms two benchmark schemes and demonstrate the robustness of the MO-EST algorithm with respect to imperfect knowledge of the sparsity level of the channels in practical implementations.
CRIS-Team Scopus Importer:2021-04-19

Channel Estimation for IRS-Assisted Millimeter-Wave MIMO Systems: Sparsity-Inspired Approaches - Lin, Tian; Yu, Xianghao; Zhu, Yu; Schober, Robert (IEEE Transactions on Communications, 2022)
Due to their ability to create favorable line-of-sight (LoS) propagation environments, intelligent reflecting surfaces (IRSs) are regarded as promising enablers for future millimeter-wave (mm-wave) wireless communication. In this paper, we investigate channel estimation for IRS-assisted mm-wave multiple-input multiple-output (MIMO) wireless systems. By leveraging the sparsity of mm-wave channels in the angular domain, we formulate the channel estimation problem as an ℓ1-norm regularized optimization problem with fixed-rank constraints. To tackle the non-convexity of the formulated problem, an efficient algorithm is proposed by capitalizing on alternating minimization and manifold optimization (MO), which yields a locally optimal solution. To further reduce the computational complexity of the estimation algorithm, we propose a compressive sensing- (CS-) based channel estimation approach. In particular, a three-stage estimation protocol is put forward where the subproblem in each stage can be solved via low-complexity CS methods. Furthermore, based on the acquired channel state information (CSI) of the cascaded channel, we design a passive beamforming algorithm for maximization of the spectral efficiency. Simulation results reveal that the proposed MO-based estimation (MO-EST) and beamforming algorithms significantly outperform two benchmark schemes while the CS-based estimation (CS-EST) algorithm strikes a balance between performance and complexity.
CRIS-Team Scopus Importer:2022-05-06
Keywords: Array signal processing; Channel estimation; Channel estimation; compressive sensing; Estimation; fixed-rank manifold optimization; intelligent reflecting surface; MIMO; MIMO communication; Radio frequency; Receiving antennas; Wireless communication

Channel estimation techniques for diffusion-based molecular communications - Jamali Kooshkghazi, Vahid; Ahmadzadeh, Arman; Jardin, Christophe; Sticht, Heinrich; Schober, Robert (2016 IEEE International Conference on Communications (ICC), 2016)
In molecular communication (MC) systems, the expected number of molecules observed at the receiver over time after the instantaneous release of molecules by the transmitter is referred to as the channel impulse response (CIR). Knowledge of the CIR is needed for the design of detection and equalization schemes. In this paper, we present a training-based CIR estimation framework for MC systems which aims at estimating the CIR based on the observed number of molecules at the receiver due to emission of a sequence of known numbers of molecules by the transmitter. In particular, we derive maximum likelihood (ML) and least sum of square errors (LSSE) estimators. We also study the Cramer Rao (CR) lower bound and training sequence design for the considered system. Simulation results confirm the analysis and compare the performance of the proposed estimation techniques with the CR lower bound.<br
Keywords: Receivers; Transmitters; Channel estimation; Channel models; Maximum likelihood estimation; Training

Channeling partitioning policies for multi-class traffic in LEO-MSS - Wang, Zhipeng; Mathiopoulos, P. Takis; Schober, Robert (IEEE Transactions on Aerospace and Electronic Systems, 2009)
This paper studies channel partitioning policies and channel resource prioritization techniques for handovers, which efficiently support multi-class traffic in low Earth orbit mobile satellite systems (LEO-MSS). Analytical methods are developed for evaluating the performance of complete partitioning (CP) and complete sharing (CS) with and without fixed channel reservation (FCR) for multi-class traffic in LEO-MSS. Furthermore, a novel threshold call admission (TCA) scheme which achieves better channel utilization and fair channel access is introduced and analyzed. © 2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Channel level crossing-based security for communications over fading channels - Karas, Dimitrios S.; Karagiannidis, George K.; Schober, Robert (IET Information Security, 2013)
Several key exchange methods for wireless channels have been proposed in the literature. They are referred to as physical-layer security techniques and are usually based on the channel's fading characteristics and the principle of channel reciprocity. In this study, the authors present key exchange algorithms for wireless fading channels whose operation is based on channel estimation. Specifically, the authors present a complete key exchange scheme that includes channel sampling, thresholding and error reconciliation. Two error reconciliation methods are proposed. The first one is based on neural networks and the second one is based on linear block coding. Simulations of the proposed methods' performances and levels of security are presented and conclusions are drawn regarding their overall utility. © The Institution of Engineering and Technology 2013.
CRIS-Team Scopus Importer:2020-02-03

Channel Modeling for Diffusive Molecular Communication - A Tutorial Review - Jamali Kooshkghazi, Vahid; Ahmadzadeh, Arman; Wicke, Wayan; Noel, Adam; Schober, Robert (Proceedings of the IEEE, 2019)
Molecular communication (MC) is a new communication engineering paradigm where molecules are employed as information carriers. MC systems are expected to enable new revolutionary applications, such as sensing of target substances in biotechnology, smart drug delivery in medicine, and monitoring of oil pipelines or chemical reactors in industrial settings. As for any other kind of communication, simple yet sufficiently accurate channel models are needed for the design, analysis, and efficient operation of MC systems. In this paper, we provide a tutorial review on mathematical channel modeling for diffusive MC systems. The considered end-to-end MC channel models incorporate the effects of the release mechanism, the MC environment, and the reception mechanism on the observed information molecules. Thereby, the various existing models for the different components of an MC system are presented under a common framework and the underlying biological, chemical, and physical phenomena are discussed. Deterministic models characterizing the expected number of molecules observed at the receiver and statistical models characterizing the actual number of observed molecules are developed. In addition, we provide the channel models for time-varying MC systems with moving transmitters and receivers, which are relevant for advanced applications such as smart drug delivery with mobile nanomachines. For complex scenarios, where simple MC channel models cannot be obtained from first principles, we investigate the simulation- and experiment-driven channel models. Finally, we provide a detailed discussion of potential challenges, open research problems, and future directions in channel modeling for diffusive MC systems.
CRIS-Team Scopus Importer:2019-07-09
Keywords: Diffusion; end-to-end channel impulse response (CIR); experiment-driven models; flow; molecular communications (MCs); reaction; simulation-driven models; statistical model

Channel Modeling for Drug Carrier Matrices - Schäfer, Maximilian; Salinas, Yolanda; Ruderer, Alexander; Enzenhofer, Franz; Brueggemann, Oliver; Schober, Robert; Haselmayr, Werner (2021 IEEE GLOBAL COMMUNICATIONS CONFERENCE (GLOBECOM), 2021)
CRIS-Team WoS Importer:2022-05-27

Channel Modeling for IRS -Assisted FSO Systems - Ajam, Hedieh; Najafi Kalyani, Marzieh; Jamali Kooshkghazi, Vahid; Schober, Robert (2021 IEEE WIRELESS COMMUNICATIONS AND NETWORKING CONFERENCE (WCNC), 2021)
CRIS-Team WoS Importer:2021-10-29

Channel Modeling for Synaptic Molecular Communication With Re-uptake and Reversible Receptor Binding - Lotter, Sebastian; Ahmadzadeh, Arman; Schober, Robert (ICC 2020 - 2020 IEEE International Conference on Communications (ICC), 2020)
In Diffusive Molecular Communication (DMC), information is transmitted by diffusing molecules. Synaptic signaling is a natural implementation of this paradigm. It is responsible for relaying information from one neuron to another, but also provides support for complex functionalities, such as learning and memory. Many of its features are not yet understood, some are, however, known to be critical for robust, reliable neural communication. In particular, some synapses feature a re-uptake mechanism at the presynaptic neuron, which provides a means for removing neurotransmitters from the synaptic cleft and for recycling them for future reuse. In this paper, we develop a comprehensive channel model for synaptic DMC encompassing a spatial model of the synaptic cleft, molecule re-uptake at the presynaptic neuron, and reversible binding to individual receptors at the postsynaptic neuron. Based on this model, we derive an analytical time domain expression for the channel impulse response (CIR) of the synaptic DMC system. Our model explicitly incorporates macroscopic physical channel parameters and can be used to evaluate the impact of re-uptake, receptor density, and channel width on the CIR of the synaptic DMC system. Furthermore, we provide results from particlebased computer simulation, which validate the analytical model. The proposed comprehensive channel model for synaptic DMC systems can be exploited for the investigation of challenging problems, like the quantification of the inter-symbol interference between successive synaptic signals and the design of synthetic neural communication systems.<br
Keywords: Molecular Communications; Neurons; Monte Carlo methods; Adsorption; Neurotransmitters; Analytical models; Biomembranes; Synapses

Channel Responses for the Molecule Release from Spherical Homogeneous Matrix Carriers - Schäfer, Maximilian; Salinas, Yolanda; Enzenhofer, Franz; Bruggemann, Oliver; Martinez-Manez, Ramon; Rabenstein, Rudolf; Schober, Robert; Haselmayr, Werner; Ruderer, Alexander (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2022)
Molecular communications is a promising framework for the design of controlled-release drug delivery systems. Under this framework, drug carriers, diseased cells, and the channel in between are modeled as transmitters, absorbing receivers, and diffusive channel, respectively. However, existing works on drug delivery systems consider only simple drug carrier models, which limits their practical applicability. In this paper, we investigate diffusion-based spherical matrix-type drug carriers, which are employed in medical applications. In a matrix carrier, the drug molecules are dispersed in the matrix core and diffuse from the inner to the outer layers of the carrier once immersed in a dissolution medium. We derive the channel response of the matrix carrier transmitter for an absorbing receiver. The results are validated by particle-based simulations and compared with commonly used point and transparent spherical transmitters to highlight the necessity of considering practical models. Moreover, we show that a transparent spherical transmitter, with the drug molecules uniformly distributed over the entire volume, is a special case of the considered matrix system. For this case, we provide an analytical expression for the channel response. Furthermore, we derive a criterion for evaluating whether the release process or the channel dynamics are more important for the overall characteristics of the channel response of a drug delivery system. For the limiting regimes, where only the release process or only the channel determine the behavior of the end-to-end system, we propose closed-form approximations for the channel response. Finally, as a scenario of practical relevance, we investigate the channel responses for the release of common therapeutic drugs, e.g., doxorubicin, from a diblock copolymer micelle acting as drug carrier.
Created from Fastlane, Scopus look-up
Keywords: Analytical models; Biological system modeling; Biology; Diseases; Drugs; Polymers; Transmitters

Characterization of an Inductance-based Detector in Molecular Communication Testbed Based on Superparamagnetic Iron Oxide Nanoparticles - Ahmed, Doaa; Unterweger, Harald; Fischer, Georg; Schober, Robert; Kirchner, Jens (IEEE SENSORS 2019, 2019)
Molecular communication (MC), using chemicals or particles, is a promising approach to bridge the gaps of conventional communication systems, e.g. in nano-scale or in pipelines. Our testbed depends on superparamagnetic iron oxide nanoparticles (SPIONs) as information carriers, which are detected using a susceptometer. In this paper, we study how the position and distribution of particles near the susceptometer, i.e., coil, affect its detected signal. When the particles move axially through the coil, an increment in the signal is detected. In addition, we observed a nonlinear additive behaviour of inductance in the same axial direction, i.e., changes in inductance due to partial volumes are not additive. An exponentially-like signal is detected when the particles move radially through the coil. Moreover, a linear additive behaviour of inductance is observed in this direction. Increasing the magnetic susceptibility has a significant effect on the detected signal. However, the susceptibility of SPIONs is relatively small in order to keep superparamagnetic properties. The coil inductance depends not only on the volume, or permeability of magnetic particles in its core, but also on how they are distributed inside. <br
Keywords: molecular communication; superparamagnetic nanoparticles; simulation; MC testbed; coils; magnetic fields

Chemical Reactions-based Detection Mechanism for Molecular Communications - Cao, Trang Ngoc; Jamali, Vahid; Wicke, Wayan; Yeoh, Phee Lep; Zlatanov, Nikola; Evans, Jamie; Schober, Robert (IEEE Wireless Communications and Networking Conference, WCNC, 2020)
In molecular communications, the direct detection of signaling molecules may be challenging due to the lack of suitable sensors and interference from co-existing substances in the environment. Motivated by examples in nature, we investigate an indirect detection mechanism using chemical reactions between the signaling molecules and a molecular probe to produce an easy-to-measure product at the receiver. The underlying reaction-diffusion equations that describe the concentrations of the reactant and product molecules in the system are non-linear and coupled, and cannot be solved in closed-form. To analyze these molecule concentrations, we develop an efficient iterative algorithm by discretizing the time variable and solving for the space variables in each time step. We also derive insightful closed-form solutions for a special case. The accuracy of the proposed algorithm is verified by particle-based simulations. Our results show that the concentration of the product molecules has a similar characteristic over time as the concentration of the signaling molecules. We analyze the bit error rate (BER) for a threshold detector and highlight that significant improvements in the BER can be achieved by carefully choosing the molecular probe and optimizing the detection threshold.
CRIS-Team Scopus Importer:2020-07-10

Chemical Reactions-based Detection Mechanism for Molecular Communications - Cao, Trang Ngoc; Jamali, Vahid; Wicke, Wayan; Zlatanov, Nikola; Yeoh, Phee Lep; Evans, Jamie; Schober, Robert (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2023)
In molecular communications, the direct detection of signaling molecules may be challenging due to a lack of suitable sensors and interference from co-existing substances in the environment. Motivated by research in molecular biology, we investigate an indirect detection mechanism using chemical reactions between the signaling molecules and a molecular probe to produce an easy-to-measure product at the receiver. We consider two implementations of the proposed detection mechanism, i.e., unrestricted probe movement and probes restricted to a volume around the receiver. In general, the resulting reaction-diffusion equations that describe the concentrations of the reactant and product molecules in the system are non-linear and coupled, and cannot be solved in closed form. To evaluate these molecule concentrations, we develop an efficient iterative algorithm by discretizing the time variable and solving for the space variables of the concentration equations in each time step. In the special case when the concentration of the unrestricted probes is high and not significantly changed by the chemical reaction, we obtain insightful closed-form solutions. Our results show that the concentrations of the product molecules and the signalling molecules have a similar characteristic over time, i.e., a single peak and a long tail. We highlight that by carefully choosing the molecular probe and optimizing the decision threshold, the BER can be improved significantly such that a direct detection system is outperformed. Moreover, when the molecular probes are kept in a small volume around the receiver, fewer resources are needed to achieve a lower BER and/or a higher data rate compared to the case of unrestricted molecular probes.
CRIS-Team Scopus Importer:2023-03-17
Keywords: Calcium; Chemical and biological sensors; Chemical reactions; Chemicals; Mathematical models; Probes; Receivers

Codebook Based Two-Time Scale Resource Allocation Design for IRS-Assisted eMBB-URLLC Systems - Ghanem, Walid; Jamali, Vahid; Schellmann, Malte; Cao, Hanwen; Eichinger, Joseph; Schober, Robert (2022 IEEE GLOBECOM Workshops, GC Wkshps 2022 - Proceedings, 2022)
This paper investigates the resource allocation algorithm design for wireless systems assisted by large intelligent reflecting surfaces (IRSs) with coexisting enhanced mobile broadband (eMBB) and ultra reliable low-latency communication (URLLC) users. We consider a two-time scale resource allocation scheme, whereby the base station's precoders are optimized in each mini-slot to adapt to newly arriving URLLC traffic, whereas the IRS phase shifts are reconfigured only in each time slot to avoid excessive base station-IRS signaling. To facilitate efficient resource allocation design for large IRSs, we employ a codebook-based optimization framework, where the IRS is divided into several tiles and the phase-shift elements of each tile are selected from a pre-defined codebook. The resource allocation algorithm design is formulated as an optimization problem for the maximization of the average sum data rate of the eMBB users over a time slot while guaranteeing the quality-of-service (QoS) of each URLLC user in each mini-slot. An iterative algorithm based on alternating optimization (AO) is proposed to find a high-quality suboptimal solution. As a case study, the proposed algorithm is applied in an industrial indoor environment modelled via the Quadriga channel simulator. Our simulation results show that the proposed algorithm design enables the coexistence of eMBB and URLLC users and yields large performance gains compared to three baseline schemes. Furthermore, our simulation results reveal that the proposed two-time scale resource allocation design incurs only a small performance loss compared to the case when the IRSs are optimized in each mini-slot.
CRIS-Team Scopus Importer:2023-03-07

Codebook-Based User Tracking in IRS-Assisted mmWave Communication Networks - Garkisch, Moritz; Jamali, Vahid; Schober, Robert (ICASSP 2023 - 2023 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2023)
In this paper, we present a novel mobile user tracking (UT) scheme for codebook-based intelligent reflecting surface (IRS)-aided millimeter wave (mmWave) systems. The proposed UT scheme exploits the temporal correlation of the direction from the IRS to the mobile user for selecting IRS phase shifts that provide reflection towards the user. To this end, the user’s direction is periodically estimated based on a generalized likelihood ratio test (GLRT) and the user’s movement trajectory is extrapolated from several past direction estimates. The efficiency of the proposed UT scheme is evaluated in terms of the average effective rate, which accounts for both the required signaling overhead and the achieved signal-to-noise ratio (SNR). Our results show that for medium-to-high SNR, the proposed codebook-based UT scheme achieves a higher effective rate than two reference approaches based on full codebook search and optimization of the individual IRS unit cells, respectively.<br

Coded cooperation for BICM-OFDM - Islam, Toufiqul; Schober, Robert; Mallik, Ranjan K. (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC, 2012)
Coded cooperation is an attractive user cooperation scheme for wireless systems, where different parts of a coded packet are transmitted over different channels. In this paper, we propose a new approach to improve the performance of coded cooperation. We present cooperative maximum-ratio combining (C-MRC) based coded cooperation to guarantee full diversity even if the inter-user link is not ideal. Moreover, we combine bit-interleaved coded modulation (BICM) with orthogonal frequency division multiplexing (OFDM) to overcome frequency-selective fading. Taking possible decision errors at the cooperating sources into account, we develop a closed-form upper bound on the asymptotic worst-case pairwise error probability (PEP) of the considered C-MRC based coded cooperation scheme and obtain the diversity gain as function of free distance of the code and frequency diversity of the links. Furthermore, we discuss the optimization of the puncturing pattern based on the frequency diversity of the involved links. Simulation results corroborate the derived analytical results. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Coherent max-log decision fusion in wireless sensor networks - Lei, Andre; Schober, Robert (IEEE Transactions on Communications, 2010)
In this letter, we revisit the problem of distributed coherent decision fusion for wireless sensor networks where the sensors make independent decisions on the hypothesis under test and forward their decisions over noisy fading channels to the fusion center. We propose a novel fusion rule which is obtained by applying the max-log approximation to the optimal fusion rule. Furthermore, we provide a unified performance analysis of binary decision fusion which is applicable to the optimal fusion rule and various suboptimal fusion rules such as the max-log, maximal ratio combining, equal gain combining, and Chair' Varshney fusion rules. Our results show that the proposed max log fusion rule outperforms all previously proposed suboptimal fusion rules and has a close-to-optimal performance. © 2006 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Data fusion; Fading channels; Multiple hypothesis testing; Wireless sensor networks

Coherent wireless optical communications with predetection and postdetection EGC over Gamma-Gamma atmospheric turbulence channels - Niu, Mingbo; Schlenker, Josh; Cheng, Julian; Holzman, Jonathan F.; Schober, Robert (Journal of Optical Communications and Networking, 2011)
Wireless optical communication systems with coherent detection are analyzed for GammaGamma distributed turbulence channels. In addition to the shot noise, we consider the impacts of both turbulence amplitude fluctuations and phase fluctuations on the error performance. Error rate analyses of predetection and postdetection equal gain combining (EGC) are carried out. We derive the exact error rate expressions for predetection and postdetection EGC using a characteristic function method. In the case of predetection EGC, we also study the impact of phase noise compensation error on the error rate performance. It is shown that the error rate performance of predetection EGC is sensitive to phase noise compensation errors for both weak and strong turbulence conditions. In order to alleviate the impact of phase noise, postdetection EGC with differential phase-shift keying is introduced and analyzed. In addition, postdetection EGC is compared with predetection EGC in the presence of phase noise compensation errors, and it is found to be an effective alternative to predetection EGC with low complexity implementation. © 2009 OSA.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Atmospheric turbulence; Coherent detection; Diversity; Optical communications; Phase noise

Colocated and Distributed Switch-and-Stay Combining: Optimality Under Switching Rate Constraints - Jataprolu, Manjunath Kashyap; Michalopoulos, Diomidis S.; Schober, Robert (IEEE Transactions on Vehicular Technology, 2013)
Switch-and-stay combining (SSC) is a low-complexity alternative to selection combining (SC) in dual diversity systems. These diversity systems can either be the conventional colocated diversity setups, where two antennas are available at the receiver, or the cooperative diversity systems, where two relays assist one transmitter-receiver pair. In SSC, a single diversity branch (i.e., a single antenna or a single relay) is activated and remains active as long as the corresponding channel is sufficiently strong, regardless of the quality of the other branch. Thereby, the switching threshold determines both the bit error rate (BER) and the switching rate, which are defined as the number of times per second a branch switching occurs. Since high switching rates are not preferred in practice, in this paper, we optimize the switching threshold of SSC to minimize the BER under a constraint on the switching rate. To this end, we derive approximate closed-form solutions for the optimization problem for both the colocated and the distributed antenna case. These solutions are shown to achieve close-to-optimal performance through computer simulations.<br
Keywords: cooperative communication; diversity reception; error statistics; optimisation; relay networks (telecommunication); telecommunication switching

Combined Relay Selection and Cooperative Beamforming for Physical Layer Security - Kim, Junsu; Ikhlef, Aissa; Schober, Robert (Journal of Communications and Networks, 2012)
In this paper, we propose combined relay selection and cooperative beamforming schemes for physical layer security. Generally, high operational complexity is required for cooperative beamforming with multiple relays because of the required information exchange and synchronization among the relays. On the other hand, while it is desirable to reduce the number of relays participating in cooperative beamforming because of the associated complexity problem, doing so may degrade the coding gain of cooperative beamforming. Hence, we propose combined relay selection and cooperative beamforming schemes, where only two of the available relays are selected for beamforming and data transmission. The proposed schemes introduce a selection gain which partially compensates for the decrease in coding gain due to limiting the number of participating relays to two. Both the cases where full and only partial channel state information are available for relay selection and cooperative beamforming are considered. Analytical and simulation results for the proposed schemes show improved secrecy capacities compared to existing physical layer security schemes employing cooperative relays. © 2012 KICS
CRIS-Team Scopus Importer:2020-02-03
Keywords: Cooperative beamforming; optimal beamforming; physical layer security; relay selection

Combined time-reversal space-time block coding and transmit beamforming for frequency-selective fading channels - Jonietz, Christof; Gerstacker, Wolfgang; Schober, Robert (IEEE International Conference on Communications, 2008)
Transmit beamforming (BF) with reliable channel state information at the transmitter (CSIT) can improve the system performance significantly. On the other hand, for unreliable CSIT pure space-time coding outperforms transmit BF. In this paper, the combination of time-reversal space-time block codes (TR-STBCs) and transmit BF for transmission over frequency-selective fading channels is considered. The proposed scheme takes the reliability of the CSIT into account in an optimum way. For unreliable CSIT, the proposed scheme yields the same diversity gains as a TR-STBC, whereas for reliable CSIT significant BF gains can be obtained in addition to the diversity gain of the TR-STBC. ©2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Communication theory: Improved OFDMA uplink transmission via cooperative relaying in the presence of frequency offsets-Part II: Outage information rate analysis - Zhang, Zhongshan; Tellambura, Chintha; Schober, Robert (European Transactions on Telecommunications, 2010)
In Part I of this paper, the ergodic information rate is derived for an orthogonal frequency-division multiplexing access (OFDMA) uplink with cooperative relaying in the presence of frequency offsets. In this part, the outage information rate of the system is analysed. Both amplify-and-forward (AF) and decodeand-forward (DF) relays are considered. Each node can play the roles of the source node and the relay, simultaneously, at different subcarriers. Both the outage information rate and the diversity gain are derived for the interference-limited environment. Numerical results illustrate the superior performance of the proposed cooperative scheme over conventional transmission (without relaying) with regard to outage information rate. Copyright © 2009 John Wiley & Sons, Ltd.
CRIS-Team Scopus Importer:2020-02-03

Comparative Evaluation of a New Sensor for Superparamagnetic Iron Oxide Nanoparticles in a Molecular Communication Setting - Bartunik, Max; Unterweger, Harald; Alexiou, Christoph; Schober, Robert; Lübke, Maximilian; Fischer, Georg; Kirchner, Jens (EAI BICT 2020 - 12th EAI International Conference on Bio-inspired Information and Communications Technologies, 2020)
Testbeds are required to assess concepts and devices in the context of molecular communication. These allow the observation of real-life phenomena in a controlled environment and therefore present the basis of future work. A testbed using superparamagnetic iron oxide nanoparticles (SPIONs) as information carriers was constructed with regard to this context and requires a sensitive receiver for the detection of SPIONs. This paper focusses on the comparison between a newly presented device (inductance sensor), a previously constructed SPION sensor (resonance bridge), and a commercial susceptometer as reference. The new inductance sensor is intended to improve on a low sensitivity achieved with the previous device and restrictions with respect to sample rate and measurement aperture encountered with the susceptometer. The signal-to-noise ratio (SNR) for each device is assessed at a variety of SPION concentrations. Furthermore, the sensors bit error rates (BER) for a random bit sequence are determined. The results show the device based on an inductance sensor to be the most promising for further investigation as values both for BER and SNR exceed those of the resonance bridge while providing a suciently high sample rate. On average the SNR of the new device is 13 dB higher while the BER for the worst transmission scenario is 9% lower. The commercial susceptometer, although returning the highest SNR, lacks adaptability for the given use case.<br
Keywords: Molecular Communication; Superparamagnetic Iron Oxide; Nanoparticles; SPION; Testbed; Susceptometer; Resonance Bridge; Inductance Sensor; SNR; BER

Comparison of MOE and Blind LMS - Schober, Robert; Gerstacker, Wolfgang; Lampe, Lutz (IEEE Communications Letters, 2003)
In this letter, we provide a rigorous analytical comparison of two blind adaptive algorithms for adjustment of the minimum mean-squared error (MMSE) filter for multiple access interference (MAI) suppression for direct-square code-division multiple access (DS-CDMA). In particular, we compare the popular minimum-output-energy (MOE) algorithm and the blind least-mean-square algorithm (BLMS) in terms of complexity, transient behavior, convergence, stability, and steady-state performance. We show analytically that the MOE algorithm enjoys a faster speed of convergence and has a superior steady-state performance, while the BLMS algorithm is computationally less complex.
UnivIS-Import:2015-03-09:Pub.2003.tech.IE.mobilk.compar
Keywords: Blind adaptive algorithms; DS-CDMA; Multiuser interference suppression

Comprehensive reactive receiver modeling for diffusive molecular communication systems: Reversible binding, molecule degradation, and finite number of receptors - Ahmadzadeh, Arman; Arjmandi, Hamidreza; Burkovski, Andreas; Schober, Robert (IEEE Transactions on Nanobioscience, 2016)

Compressive Sensing Based Adaptive Active User Detection and Channel Estimation: Massive Access Meets Massive MIMO - Ke, Malong; Gao, Zhen; Wu, Yongpeng; Gao, Xiqi; Schober, Robert (IEEE Transactions on Signal Processing, 2020)
This paper considers massive access in massive multiple-input multiple-output (MIMO) systems and proposes an adaptive active user detection and channel estimation scheme based on compressive sensing. By exploiting the sporadic traffic of massive connected user equipments and the virtual angular domain sparsity of massive MIMO channels, the proposed scheme can support massive access with dramatically reduced access latency. Specifically, we design non-orthogonal pseudo-random pilots for uplink broadband massive access, and formulate the active user detection and channel estimation as a generalized multiple measurement vector compressive sensing problem. Furthermore, by leveraging the structured sparsity of the uplink channel matrix, we propose an efficient generalized multiple measurement vector approximate message passing (GMMV-AMP) algorithm to realize joint active user detection and channel estimation based on a spatial domain or an angular domain channel model. To jointly exploit the channel sparsity present in both the spatial and the angular domains for enhanced performance, a Turbo-GMMV-AMP algorithm is developed for detecting the active users and estimating their channels in an alternating manner. Finally, an adaptive access scheme is proposed, which adapts the access latency to guarantee reliable massive access for practical systems with unknown channel sparsity level. Additionally, the state evolution of the proposed GMMV-AMP algorithm is derived to predict its performance. Simulation results demonstrate the superiority of the proposed active user detection and channel estimation schemes compared to several baseline schemes.
CRIS-Team Scopus Importer:2020-02-04
Keywords: active user detection; approximate message passing; channel estimation; compressive sensing; Massive access; massive multiple-input multiple-output; structured sparsity

Conditional Capacity and Transmit Signal Design for SWIPT Systems with Multiple Nonlinear Energy Harvesting Receivers - Morsi, Rania; Jamali, Vahid; Hagelauer, Amelie Marietta; Ng, Derrick Wing Kwan; Schober, Robert (IEEE Transactions on Communications, 2020)
In this paper, we study information-theoretic limits for simultaneous wireless information and power transfer (SWIPT) systems employing practical nonlinear radio frequency (RF) energy harvesting (EH) receivers (Rxs). In particular, we consider a SWIPT system with one transmitter that broadcasts a common signal to an information decoding (ID) Rx and multiple EH Rxs. Owing to the nonlinearity of the EH Rxs' circuitry, the efficiency of wireless power transfer depends on the waveform of the transmitted signal. We aim to answer the following fundamental question: What is the optimal input distribution of the transmit signal waveform that maximizes the information transfer rate at the ID Rx conditioned on individual minimum required direct-current (DC) powers to be harvested at the EH Rxs? Specifically, we study the conditional capacity problem of a SWIPT system impaired by additive white Gaussian noise subject to average-power (AP) and peak-power (PP) constraints at the transmitter and nonlinear EH constraints at the EH Rxs. To this end, we develop a novel nonlinear EH model that captures the saturation of the harvested DC power by taking into account not only the forward current of the rectifying diode but also the reverse breakdown current. Then, we derive a novel semi-closed-form expression for the harvested DC power, which simplifies to closed form for low input RF powers. The derived analytical expressions are shown to closely match circuit simulation results. We solve the conditional capacity problem for real- and complex-valued signalling and prove that the optimal input distribution that maximizes the rate-energy (R-E) region is unique and discrete with a finite number of mass points. Furthermore, we show that, for the considered nonlinear EH model and a given AP constraint, the boundary of the R-E region saturates for high PP constraints due to the saturation of the harvested DC power for high input RF powers. In addition, we devise a suboptimal input distribution whose R-E tradeoff performance is close to optimal. All theoretical findings are verified by numerical evaluations.
CRIS-Team Scopus Importer:2020-02-04
Keywords: channel capacity; energy harvesting (EH); matched filters; nonlinear circuit analysis; rectennas; rectifiers; Schottky diodes; semiconductor detectors; signal design; Wireless power transmission

Conference Report: IEEE BlackSeaCom 2017 - Ulema, Mehmet; Panayirci, Erdal; Erkucuk, Serhat; Schober, Robert (IEEE Communications Magazine, 2017)
CRIS-Team Scopus Importer:2020-01-31

Constant-Composition Codes for Maximum Likelihood Detection Without CSI in Diffusive Molecular Communications - Jamali, Vahid; Ahmadzadeh, Arman; Farsad, Nariman; Schober, Robert (IEEE Transactions on Communications, 2018)
Instantaneous or statistical channel state information (CSI) is needed for most detection schemes developed for molecular communication (MC) systems. Since the MC channel changes over time, e.g., due to variations in the velocity of flow, the temperature, or the distance between transmitter and receiver, CSI acquisition has to be conducted repeatedly to keep track of CSI variations. Frequent CSI acquisition may entail a large overhead whereas infrequent CSI acquisition may result in a low CSI estimation accuracy. To overcome these challenges, we design codes which enable maximum likelihood sequence detection at the receiver without instantaneous or statistical CSI. In particular, assuming concentration shift keying modulation, we show that a class of codes, known as constant-composition (CC) codes, enables optimal CSI-free sequence detection at the expense of a decrease in data rate. We analyze the code rate, the error rate, and the average number of released molecules for the adopted CC codes. In addition, we study the properties of binary CC codes and balanced CC codes in further detail. Simulation results verify our analytical derivations and reveal that CC codes with CSI-free detection outperform uncoded transmission with optimal coherent and noncoherent detection.<br
Keywords: Receivers; Transmitters; Modulation; Interference; Detectors; Maximum likelihood detection; Molecular communication

Controlled Signaling and Transmitter Replenishment for MC with Functionalized Nanoparticles - Schäfer, Maximilian; Brand, Lukas; Lotter, Sebastian; Büyükoglu, Atakan; Enzenhofer, Franz; Haselmayr, Werner; Castiglione, Kathrin; Appelhans, Dietmar; Schober, Robert (9th ACM International Conference on Nanoscale Computing and Communication, 2022)
In this paper, we propose novel Transmitter (Tx) models for Molecular Communication (MC) systems based on functionalized Nanoparticles (NPs). Current Tx models often rely on simplifying assumptions for the molecule release and replenishment mechanisms. In contrast, we propose a Tx model where the signaling molecule release is controlled by a switchable membrane driven by an external trigger. Moreover, we propose a reloading mechanism, where signaling molecules are harvested based on an enzymatic reaction. Hence, no repeated injection of signaling molecules is required. For the proposed Tx model, we develop a general mathematical description in terms of a discrete-time transfer function model. Furthermore, we investigate two realizations of the proposed Tx model, i.e., an idealized Tx relying on simplifying assumptions, and a realistic Tx employing practical components for the reloading and release mechanisms. Finally, we numerically evaluate the proposed model and compare our results to stochastic Particle Based Simulations (PBSs).<br

Convexity Analysis of Nonlinear Wireless Power Transfer with Multiple RF Sources - Yuan, Xiaopeng; Hu, Yulin; Schober, Robert; Schmeink, Anke (IEEE Transactions on Vehicular Technology, 2022)
In this paper, the performance of nonlinear wireless power transfer (WPT) enabled by multiple radio-frequency (RF) sources is characterized. The harvested power is modelled as a function of the RF powers received from multiple RF sources. Following the characterization, we prove the joint convexity of the harvested power under different sufficient conditions. In particular, based on these conditions, the joint convexity of the harvested power with respect to the reciprocals of the received powers is proved. Moreover, by providing an example design, we illustrate the benefits of exploiting the joint convexity for cooperative WPT enhancement.
CRIS-Team Scopus Importer:2022-09-16
Keywords: Energy harvesting; energy harvesting; Integrated circuit modeling; jointly convex property; multiple RF sources; Nonlinear wireless power transfer; Radio frequency; RF signals; Synchronization; Wireless communication; Wireless power transfer

Convex sensing-reporting optimization for cooperative spectrum sensing - Noel, Adam; Schober, Robert (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC, 2011)
We consider the cooperative spectrum sensing problem in cognitive radio with energy detection. Secondary users with non-identical, independent sensing channels make 1-bit sensing decisions and report their decisions to the secondary base station over orthogonal fading channels. The base station acts as a fusion center by combining the decisions with OR-rule. We allow the secondary users to trade sensing time slots for additional reporting time slots. We derive the corresponding false alarm and missed detection probabilities, which are functions of the secondary sensor decision thresholds and the durations for sensing and reporting. Furthermore, we bound these probabilities and impose a practical convex region that enables convex optimization to minimize the false alarm probability for a target missed detection probability. Allowing secondary users to trade sensing time slots for additional reporting time slots is shown to significantly improve sensing performance, even with poor sensing channels and a small number of secondary users. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Convex sensing-reporting optimization for cooperative spectrum sensing - Noel, Adam; Schober, Robert (IEEE Transactions on Wireless Communications, 2012)
We consider the cooperative spectrum sensing problem in cognitive radio with energy detection. Secondary users with non-identical sensing channels make 1-bit sensing decisions that are reported to the secondary base station over non-identical noisy fading channels. The base station has reporting channel knowledge and combines the decisions with an M-out-of-K rule. We allow the secondary users to trade sensing time samples for additional reporting time slots to increase the reporting signal-to-noise ratios. We derive the false alarm and missed detection probabilities as functions of the secondary sensor decision thresholds and the durations for sensing and reporting. Furthermore, we bound these probabilities and impose practical constraints that enable convex optimization to minimize the false alarm probability for a target missed detection probability. We compare knowing the instantaneous reporting channels for optimization with knowing the average channels. Allowing secondary users to trade sensing time samples for additional reporting time slots is shown to significantly improve sensing performance, even with poor sensing and reporting channels and a small number of secondary users. © 2002-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Cognitive radio; convex optimization; energy detection; spectrum sensing

Cooperative Abnormality Detection via Diffusive Molecular Communications - Mosayebi, Reza; Jamali Kooshkghazi, Vahid; Ghoroghchian, Nafiseh; Schober, Robert; Nasiri-Kenari, Masoumeh; Mehrabi, Mahdieh (IEEE Transactions on Nanobioscience, 2017)
In this paper, we consider abnormality detection via diffusive molecular communications (MCs) for a network consisting of several sensors and a fusion center (FC). If a sensor detects an abnormality, it injects a number of molecules into the medium which is proportional to its sensing output. Two transmission schemes for releasing molecules into the medium are considered. In the first scheme, each sensor releases a different type of molecule (DTM), whereas in the second scheme, all sensors release the same type of molecule (STM). The molecules released by the sensors propagate through the MC channel and some may reach the FC where the final decision regarding whether or not an abnormality has occurred is made. We derive the optimal decision rules for both DTM and STM. However, the optimal detectors entail high computational complexity as log-likelihood ratios (LLRs) have to be computed. To overcome this issue, we show that the optimal decision rule for STM can be transformed into an equivalent low-complexity decision rule. Since a similar transformation is not possible for DTM, we propose simple low-complexity sub-optimal detectors based on different approximations of the LLR. The proposed low-complexity detectors are more suitable for practical MC systems than the original complex optimal decision rule, particularly when the FC is a nano-machine with limited computational capabilities. Furthermore, we analyze the performance of the proposed detectors in terms of their false alarm and missed detection probabilities. Simulation results verify our analytical derivations and reveal interesting insights regarding the tradeoff between complexity and performance of the proposed detectors and the considered DTM and STM schemes.<br
Keywords: Detectors; Molecular communication; Computational complexity; Sensor fusion

Cooperative amplify-and-forward beamforming for OFDM systems with multiple relays - Liang, Yang Wen; Schober, Robert (IEEE International Conference on Communications, 2009)
In this paper, we propose frequency-domain (FD) and time-domain (TD) beamforming (BF) schemes for cooperative orthogonal frequency division multiplexing (OFDM) networks with multiple amplify-and-forward relays. Whereas for FD-BF the BF weights are applied in the FD, for TD-BF cyclic BF filters (C-BFFs) are used on the TD signal avoiding discrete-time Fourier transform operations at the relays and drastically reducing the required amount of feedback from the receiver to the relays. Adopting the average mutual information (AMI) per sub-carrier as optimality criterion, we show that the direction of the optimal FD-BF weights can be obtained in closed-form and that the optimal sub-carrier power allocation (PA) problem is convex. For solution of the PA problem an interior point method and a bisectional search dual method are provide. Furthermore, for solution of the C-BFF optimization problem an efficient gradient algorithm is proposed. Simulation results for IEEE 802.11n channels show that TD-BF with short C-BFFs closely approaches the performance of FD-BF and outperforms direct transmission without relaying. ©2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Cooperative amplify-and-forward beamforming with multi-antenna source and relays - Liang, Yang Wen; Schober, Robert (CAMSAP 2009 - 2009 3rd IEEE International Workshop on Computational Advances in Multi-Sensor Adaptive Processing, 2009)
In this paper, we propose a beamforming (BF) scheme for cooperative networks with multiple antennas at the source node and the amplify-and-forward (AF) relay nodes. Adopting the instantaneous signal-to-noise ratio (SNR) as optimality criterion, we obtain closed-form expressions for the maximum SNR and the optimal AF-BF matrices at the relays for a given BF vector at the source. Furthermore, we propose a numerical algorithm to find a locally optimal BF vector at the source. Simulation results for Rayleigh fading show that AF-BF with multi-antenna relays can achieve significant performance gains compared to direct transmission without relaying. © 2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Cooperative amplify-and-forward beamforming with multiple multi-antenna relays - Liang, Yang-Wen; Schober, Robert (IEEE Transactions on Communications, 2011)
In this paper, we consider beamforming (BF) for cooperative networks with one multiantenna source, multiple multiantenna amplifyandforward (AF) relays, and one singleantenna destination. The source BF vector and the AFBF matrices at the relays are optimized for maximization of the signaltonoise ratio (SNR) at the destination under three different power constraints. In particular, we consider individual relay power constraints, a joint relay power constraint, and a joint power constraint for the source and the relays. We solve the associated optimization problems in two stages. In the first stage, we find the optimal AFBF matrices for a given BF vector at the source. For the cases of individual and joint relay power constraints, closedform solutions for the AFBF matrices are provided, respectively. Furthermore, for the case of a joint sourcerelay power constraint, the AFBF matrices are obtained in closed form up to a scalar power allocation factor and an efficient numerical algorithm for the power allocation between the source and the relays is given. In the second stage, the optimal source BF vectors are computed. Thereby, we show that for the joint relay and the joint sourcerelay power constraints, the resulting problem can be transformed into a nonconvex polynomial programming problem which allows for an exact solution for smallscale networks. For largescale networks and networks with individual relay power constraints, we propose efficient suboptimal optimization methods for the source BF vector. Simulation results show the benefits of having multiple antennas at the source and/or multiple multiantenna relays and illustrate the performance differences introduced by the three different power constraints. © 2006 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: beamforming; Cooperative network; multiple antennas; multiple relays

Cooperative beamforming for single-carrier frequency-domain equalization systems with multiple relays - Wu, Peiran; Schober, Robert (IEEE Transactions on Wireless Communications, 2012)
We consider cooperative beamforming (BF) for block-based single-carrier frequency-domain equalization (SC-FDE) in a wireless network consisting of one single-antenna source, one single-antenna destination, and multiple multi-antenna relays. Adopting the minimum mean squared error as optimality criterion, the optimal frequency-domain linear equalization (LE) and decision-feedback equalization (DFE) receivers are derived and corresponding objective functions for relay BF matrix optimization are specified. For a sum relay power constraint, we obtain the structure of the optimal relay BF matrices in closed form. While the structure of the optimal relay BF matrices is identical for LE and DFE as well as for an idealized matched filter receiver, the solution of the remaining power allocation problem depends on the adopted receiver. The power allocation problem is shown to be convex for all considered receivers and an efficient numerical algorithm for finding the optimal power allocation is provided. Furthermore, to reduce complexity, two suboptimal power allocation schemes assigning identical powers to all relays and/or frequencies are proposed and shown to lead to only a small loss in performance and a remarkable robustness against imperfect channel state information. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: cooperative beamforming; Multiple-relay networks; single-carrier frequency-domain equalization

Cooperative BICM-OFDM: Sub-carrier and power allocation - Islam, Toufiqul; Schober, Robert; Mallik, Ranjan K.; Bhargava, Vijay K. (2010 International Conference on Signal Processing and Communications, SPCOM 2010, 2010)
In this paper, we consider amplify-and-forward cooperative diversity for wireless systems employing bit-interleaved coded modulation (BICM) and orthogonal frequency division multiplexing (OFDM). In the second hop, multiple relays transmit concurrently over disjoint sets of sub-carriers. We propose uniform and non-uniform sub-carrier allocation schemes, which guarantee full diversity if all involved channels have identical lengths. The non-uniform allocation scheme also guarantees full diversity if the involved channels have different lengths. In addition, we formulate a power allocation problem for minimization of an upper bound on the worst-case pairwise error probability of the considered cooperative diversity scheme and provide an efficient solution using geometric programming. Simulation results confirm the effectiveness of the proposed sub-carrier and power allocation schemes. © 2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Cooperative diversity with mobile nodes: Capacity outage rate and duration - Zlatanov, Nikola; Hadzi-Velkov, Zoran; Karagiannidis, George K.; Schober, Robert (IEEE Transactions on Information Theory, 2011)
The outage probability is an important performance measure for cooperative diversity schemes. However, in mobile environments, the outage probability does not completely describe the behavior of cooperative diversity schemes since the mobility of the involved nodes introduces variations in the channel gains. As a result, the capacity outage events are correlated in time and second-order statistical parameters of the achievable information-theoretic capacity such as the average capacity outage rate (AOR) and the average capacity outage duration (AOD) are required to obtain a more complete description of the properties of cooperative diversity protocols. In this paper, assuming slow Rayleigh fading, we derive exact expressions for the AOR and the AOD of three well-known cooperative diversity protocols: variable-gain amplify-and-forward, decode-and-forward, and selection decode-and-forward relaying. Furthermore, we develop asymptotically tight high signal-to-noise ratio (SNR) approximations, which offer important insights into the influence of various system and channel parameters on the AOR and the AOD. In particular, we show that on a double-logarithmic scale, similar to the outage probability, the AOR asymptotically decays with the SNR with a slope that depends on the diversity gain of the cooperative protocol, whereas the AOD asymptotically decays with a slope of -1/2 independent of the diversity gain. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Average outage duration (AOD); average outage rate (AOR); cooperative diversity; Doppler effect; Rayleigh fading

Cooperative frequency-domain beamforming for broadband SC-FDE systems - Wu, Peiran; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2011)
In this work, we investigate cooperative frequency-domain beamforming (FD-BF) for single-carrier frequency-domain equalization (SC-FDE) systems. In particular, we propose optimal and suboptimal FD-BF schemes for frequency-domain linear equalization (FD-LE) and an idealized matched filter receiver. For both receiver structures, we derive the optimal processing at the destination and develop corresponding expressions for the signal-to-interference-plus-noise ratio (SINR). For a given power allocation, the optimal FD-BF filters maximizing the SINR are obtained in closed form and the power allocation problem is shown to be convex. For computation of the optimal power allocation a numerical method is developed and two low-complexity suboptimal power allocations are provided. Simulation results confirm the excellent performance of all proposed FD-BF schemes. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Cooperative Internet of UAVs: Distributed Trajectory Design by Multi-Agent Deep Reinforcement Learning - Hu, Jingzhi; Zhang, Hongliang; Song, Lingyang; Schober, Robert; Poor, H. Vincent (IEEE Transactions on Communications, 2020)
Due to the advantages of flexible deployment and extensive coverage, unmanned aerial vehicles (UAVs) have significant potential for sensing applications in the next generation of cellular networks, which will give rise to a cellular Internet of UAVs. In this article, we consider a cellular Internet of UAVs, where the UAVs execute sensing tasks through cooperative sensing and transmission to minimize the age of information (AoI). However, the cooperative sensing and transmission is tightly coupled with the UAVs' trajectories, which makes the trajectory design challenging. To tackle this challenge, we propose a distributed sense-and-send protocol, where the UAVs determine the trajectories by selecting from a discrete set of tasks and a continuous set of locations for sensing and transmission. Based on this protocol, we formulate the trajectory design problem for AoI minimization and propose a compound-action actor-critic (CA2C) algorithm to solve it based on deep reinforcement learning. The CA2C algorithm can learn the optimal policies for actions involving both continuous and discrete variables and is suited for the trajectory design. Our simulation results show that the CA2C algorithm outperforms four baseline algorithms. Also, we show that by dividing the tasks, cooperative UAVs can achieve a lower AoI compared to non-cooperative UAVs.
CRIS-Team Scopus Importer:2020-12-04
Keywords: Cooperative Internet of UAVs; deep reinforcement learning; distributed trajectory design

Cooperative MIMO multicell networks - Verde, Francesco; Peter Hong, Yao-Win; Samardzija, Dragan; Schober, Robert; Tao, Zhifeng (EURASIP Journal on Advances in Signal Processing, 2012)
CRIS-Team Scopus Importer:2020-02-03

Cooperative wireless backhauling - Jamali, Vahid; Zlatanov, Nikola; Schober, Robert (SCC 2017 - 11th International ITG Conference on Systems, Communications and Coding, 2019)
We consider wireless backhauling for a scenario where two small-cell base stations (SC-BSs) employ the same time and frequency resources for offloading their data to a common macro-cell base station (MC-BS). The two SC-BSs allocate a part of the shared resource to exchange data in order to be able to cooperate to boost the backhaul capacity. For this scenario, we develop the optimal transmission strategy which, based on the channel state information, determines whether the SC-BSs should exchange data and cooperate or transmit their data independently to the MC-BS. Our numerical results demonstrate the superiority of the proposed cooperative wireless backhauling protocol compared to existing protocols in the literature.
CRIS-Team Scopus Importer:2019-10-22

Coupled Phase-Shift STAR-RISs: A General Optimization Framework - Wang, Zhaolin; Mu, Xidong; Liu, Yuanwei; Schober, Robert (IEEE Wireless Communications Letters, 2022)
A general optimization framework is proposed for simultaneously transmitting and reflecting reconfigurable intelligent surfaces (STAR-RISs) with coupled phase shifts, which converges to the Karush– Kuhn–Tucker (KKT) optimal solution under some mild conditions. More particularly, the amplitude and phase-shift coefficients of STAR-RISs are optimized alternately in closed form. To demonstrate the effectiveness of the proposed optimization framework, the throughput maximization problem is considered in a case study. It is rigorously proved that the KKT optimal solution is obtained. Numerical results confirm the effectiveness of the proposed optimization framework compared to baseline schemes.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Coupled phase shifts; Karush–Kuhn–Tucker (KKT); Linear programming; Optimization; Reflection; Reflection coefficient; simultaneous transmission and reflection (STAR); Three-dimensional displays; Throughput; Upper bound

C-RAN with Hybrid RF/FSO Fronthaul Links: Joint Optimization of Fronthaul Compression and RF Time Allocation - Najafi, Marzieh; Jamali, Vahid; Ng, Derrick Wing Kwan; Schober, Robert (IEEE Transactions on Communications, 2019)
This paper considers the uplink of a cloud radio access network (C-RAN) comprised of several multi-antenna remote radio units (RUs) which compress the signals that they receive from multiple mobile users (MUs) and forward them to a CU via wireless fronthaul links. To enable reliable high rate fronthaul links, we employ a hybrid radio frequency (RF)/free space optical (FSO) system for fronthauling. Moreover, to strike a balance between complexity and performance, we consider three different quantization schemes at the RUs, namely per-antenna vector quantization (AVQ), per-RU vector quantization (RVQ), and distributed source coding (DSC), two different RF fronthaul transmission modes, namely orthogonal transmission and non-orthogonal transmission, and two different detectors at the CU, namely the linear minimum mean square error detector and the optimal successive interference cancellation detector. For this network architecture, we investigate the joint optimization of the quantization noise covariance matrices at the RUs and the RF time allocation to the multiple-access and fronthaul links for rate region maximization. To this end, we formulate a unified weighted sum rate maximization problem valid for each possible combination of the considered quantization, RF fronthaul transmission, and detection schemes. To handle the non-convexity of the unified problem, we transform it into a bi-convex problem which facilitates the derivation of an efficient suboptimal solution using alternating convex optimization and golden section search. Moreover, by introducing a backoff parameter to reduce the probability of infeasibility, we generalize the proposed optimization framework to account for imperfect channel estimation. Our simulation results show that for each combination of the considered quantization, RF fronthaul transmission, and detection schemes, C-RAN with hybrid RF/FSO fronthauling can achieve a considerable sum rate gain compared to conventional systems employing pure FSO fronthauling, especially under unfavorable atmospheric conditions. In addition, employing a more sophisticated quantization scheme can significantly improve the system performance under adverse atmospheric conditions. In contrast, in clear weather conditions, when the FSO link capacity is high, the simple AVQ scheme performs close to the optimal DSC scheme. Furthermore, our simulation results suggest that the proposed algorithm can be adapted to the quality of the channel estimates by tuning the backoff parameter.
CRIS-Team Scopus Importer:2020-01-31
Keywords: C-RAN; complexity analysis; compression; hybrid RF/FSO; multi-user detection; optical wireless fronthauling

C-RAN with Hybrid RF/FSO Fronthaul Links: Joint Optimization of RF Time Allocation and Fronthaul Compression - Najafi Kalyani, Marzieh; Jamali, Vahid; Wing Kwan Ng, Derrick; Schober, Robert (GLOBECOM 2017 - 2017 IEEE Global Communications Conference, 2017)
This paper considers the uplink of a cloud radio access network (C-RAN) comprised of several multi-antenna remote radio units (RUs) which send the data that they received from multiple mobile users (MUs) to a central unit (CU) via a wireless fronthaul link. One of the fundamental challenges in implementing C-RAN is the huge data rate required for fronthauling. To address this issue, we employ hybrid radio frequency (RF)/free space optical (FSO) systems for the fronthaul links as they benefit from both the large data rates of FSO links and the reliability of RF links. To efficiently exploit the fronthaul capacity, the RUs employ vector quantization to jointly compress the signals received at their antennas. Moreover, due to the limited available RF spectrum, we assume that the RF multiple-access and fronthaul links employ the same RF resources. Thereby, we propose an adaptive protocol which allocates transmission time to the RF multiple-access and fronthaul links in a time division duplex (TDD) manner and optimizes the quantization noise covariance matrix at each RU such that the sum rate is maximized. Our simulation results reveal that a considerable gain in terms of sum rate can be achieved by the proposed protocol in comparison with benchmark schemes from the literature, especially when the FSO links experience unfavorable atmospheric conditions.<br
Keywords: Radio frequency; Protocols; Fading channels; Optical fiber communication; Bandwidth; Photodetectors; Uplink

Cross-Layer Optimization of Fast Video Delivery in Cache-Enabled Relaying Networks - Xiang, Lin; Wing Kwan Ng, Derrick; Islam, Toufiqul; Schober, Robert; Wong, Vincent W. S. (2015 IEEE Global Communications Conference (GLOBECOM), 2015)
This paper investigates the cross-layer optimization of fast video delivery and caching for minimization of the overall video delivery time in a two-hop relaying network. The half-duplex relay nodes are equipped with both a cache and a buffer which facilitate joint scheduling of fetching and delivery to exploit the channel diversity for improving the overall delivery performance. The fast delivery control is formulated as a two-stage functional non-convex optimization problem. By exploiting the underlying convex and quasi-convex structures, the problem can be solved exactly and efficiently by the developed algorithm. Simulation results show that significant caching and buffering gains can be achieved with the proposed framework, which translates into a reduction of the overall video delivery time. Besides, a trade-off between caching and buffering gains is unveiled.<br
Keywords: Streaming media; Wireless communication; Resource management; Relays; Servers; Random access memory; Optimization

Cross-layer scheduling design for cooperative wireless two-way relay networks - Kwan Ng, Derrick Wing; Schober, Robert (Cooperative Cellular Wireless Networks, 2011)
Introduction Background. The degrees of freedom introduced by multiple antennas at the transmitters and receivers of wireless communication systems facilitate multiplexing gains and diversity gains. A wireless point-to-point link with M transmit and N receive antennas constitutes an M-by-N multiple-input multiple-output (MIMO) communication system. The ergodic capacity of an M-by-N MIMO fading channel increases almost linearly with minM, N provided that the fading meets certain mild conditions. Hence, it is not surprising that MIMO has attracted a lot of research interest since it enables significant performance and throughput gains without requiring extra transmit power and bandwidth. However, limitations on the number of antennas that a wireless device is able to support as well as the significant signal processing power and complexity required in MIMO tranceivers limit the gains that can be achieved in practice. To overcome the limitations of traditional MIMO, the concept of cooperative communication has been proposed for wireless networks such as fixed infrastructure cellular networks and wireless ad-hoc networks. The basic idea of cooperative communication is that the single-antenna terminals of a multiuser system can share their antennas and create a virtual MIMO communication system. Thereby, three different types of cooperation may be distinguished, namely, user cooperation, base station (BS) cooperation, and relaying. Theoretically, user cooperation and BS cooperation are able to provide huge performance gains, when compared with noncooperative networks. However, the required information exchange between users and BSs may make these options less attractive in practice.
CRIS-Team Scopus Importer:2020-02-03

Cross-layer scheduling design for OFDMA two-way amplify-and-forward relay networks - Ng, Derrick Wing Kwan; Schober, Robert (IEEE Wireless Communications and Networking Conference, WCNC, 2010)
In this paper, cross-layer scheduling for orthogonal frequency division multiple access (OFDMA) two-way half-duplex amplify-and-forward (AF) relay assisted networks is studied. Assuming slow fading channels, cross-layer scheduling design with imperfect channel state information at the transmitter (CSIT) and heterogeneous data rate requirements for the users is modeled as an optimization problem, where the rate, power, and subcarrier allocation policies are optimized to maximize the system good-put (bit/s/Hz successfully received). The optimization problem is solved by using dual decomposition and a distributed resource allocation algorithm is derived. Simulation results illustrate that our proposed distributed cross-layer scheduler achieves practically the same performance as the optimal centralized scheduler after a small number of iterations. ©2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Cross-layer scheduling for OFDMA amplify-and-forward relay networks - Ng, Derrick Wing Kwan; Schober, Robert (IEEE Vehicular Technology Conference, 2009)
In this paper, we consider cross-layer scheduling for the downlink of amplify-and-forward (AF) relay assisted orthogonal frequency division multiple access (OFDMA) networks. The proposed cross-layer design takes into account the effects of imperfect channel state information at transmitter (CSIT) in slow fading. The rate adaptation, power adaptation, and subcarrier allocation policies are optimized to maximize the system goodput (bits/s/Hz successfully received by the mobiles). The optimization problem is solved by using dual decomposition resulting in a highly scalable distributed resource allocation algorithm. Simulation results illustrate that the proposed distributed cross-layer scheduler requires only a small number of iterations to achieves practically the same performance as the optimal centralized scheduler. © 2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Cross-layer scheduling for OFDMA amplify-and-forward relay networks - Ng, Derrick Wing Kwan; Schober, Robert (IEEE Transactions on Vehicular Technology, 2010)
In this paper, we consider cross-layer scheduling for the downlink of amplify-and-forward (AF) relay-assisted orthogonal frequency-division multiple-access (OFDMA) networks. The proposed cross-layer design takes into account the effects of imperfect channel-state information (CSI) at the transmitter (CSIT) in slow fading. The rate, power, and subcarrier allocation policies are optimized to maximize the system goodput (in bits per second per hertz successfully received by the users). The optimization problem is solved by using dual decomposition, resulting in a highly scalable distributed iterative resource-allocation algorithm. We also investigate the asymptotic performance of the proposed scheduler with respect to (w.r.t.) the numbers of users and relays. We find that the number of relays should grow faster than the number of users to fully exploit the multiuser diversity (MUD) gain. On the other hand, diversity from multiple relays can be exploited to enhance system performance when the MUD gain is saturated due to noise amplification at the AF relays. Furthermore, we introduce a feedback-reduction scheme to reduce the computational burden and the required amount of CSI feedback from the users to the relays. Simulation results confirm the derived analytical results for the growth of the system goodput and illustrate that the proposed distributed cross-layer scheduler only requires a small number of iterations to achieve practically the same performance as the optimal centralized scheduler, even if the information exchanged between the base station (BS) and the relays in each iteration is quantized, and the proposed CSI feedback reduction scheme is employed. © 2006 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Amplify-and-forward (AF) relaying; Cross-layer scheduling; Distributed resource allocation; Dual decomposition; Imperfect channel-state information (CSI); Multiuser diversity (MUD)

Cyclic space-frequency filtering for BICM-OFDM systems with multiple co-located or distributed transmit antennas - Chen, Harry Z. B.; Schober, Robert (IEEE Transactions on Wireless Communications, 2009)
In this paper, we introduce cyclic space-frequency (CSF) filtering for orthogonal frequency division multiplexing (OFDM) systems using bit-interleaved coded modulation (BICM) and multiple transmit antennas for fading mitigation, and discuss the extension to orthogonal frequency division multiple access (OFDMA) systems. CSF filtering is a simple form of space-frequency coding (SFC) and may be viewed as a generalization of cyclic delay diversity (CDD) where the cyclic delays are replaced by CSF filters. CSF is applicable to both traditional multiple-input multiple-output systems with co-located transmit antennas and cooperative diversity systems with decode-and-forward relaying and distributed transmit antennas. Similar to CDD and in contrast to other SFC schemes, CSF filtering does not require any changes to the receiver compared to single-antenna transmission. Based on the asymptotic pairwise error probability of the overall system we derive an optimization criterion for the CSF filters for co-located and distributed transmit antennas, respectively. We show that the optimum CSF filters are independent of the interleaver if they do not exceed a certain length. If this length is exceeded, the adopted interleaver has to be carefully taken into account in the CSF filter design. For several special cases we derive closed-form solutions for the optimum CSF filters and for the general case we provide various CSF filter design methods. Our simulation results show that CSF filtering can achieve significant performance gains over existing CDD schemes. © 2006 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: BICM-OFDM; Co-located and distributed transmit antennas; Cyclic space-frequency (CSF) filtering; Space-frequency coding (SFC)

Data-Aided Secure Massive MIMO Transmission Under the Pilot Contamination Attack - Wu, Yongpeng; Wen, Chao-Kai; Chen, Wen; Jin, Shi; Schober, Robert; Caire, Giuseppe (IEEE Transactions on Communications, 2019)
In this paper, we study the design of secure communication for time-division duplex multi-cell multi-user massive multiple-input-multiple-output (MIMO) systems with active eavesdropping. We assume that the eavesdropper actively attacks the uplink pilot transmission and the uplink data transmission before eavesdropping the downlink data transmission of the users. We exploit both the received pilot’s and the received data signals for uplink channel estimation. We show analytically that when both the number of transmit antennas and the length of the data vector tend to infinity, the signals of the desired user and the eavesdropper lie in different eigenspaces of the received signal matrix at the base station, provided their signal powers are different. This finding reveals that decreasing (instead of increasing) the desired user’s signal power might be an effective approach to combat a strong active attack from an eavesdropper. Inspired by this observation, we propose a data-aided secure downlink transmission scheme and derive an asymptotic achievable secrecy sum-rate expression for the proposed design. For the special case of a single-cell single-user system with independent and identically distributed fading, the obtained expression reveals that the secrecy rate scales logarithmically with the number of transmit antennas. This is the same scaling law as for the achievable rate of a single-user massive MIMO system in the absence of eavesdroppers. The numerical results indicate that the proposed scheme achieves significant secrecy rate gains compared with alternative approaches based on matched filter precoding with artificial noise generation and null space transmission.<br
Keywords: Contamination; Uplink; MIMO communication; Downlink; Transmitting antennas; Channel estimation; Fading channels

Data-Aided Secure Massive MIMO Transmission with Active Eavesdropping - Wu, Yongpeng; Wen, Chao-Kai; Chen, Wen; Jin, Shi; Schober, Robert; Caire, Giuseppe (2018 IEEE International Conference on Communications (ICC), 2018)
In this paper, we study the design of secure communication for time division duplexing multi-cell multi-user massive multiple-input multiple-output (MIMO) systems with active eavesdropping. We assume that the eavesdropper actively attacks the uplink pilot transmission and the uplink data transmission before eavesdropping the downlink data transmission phase of the desired users. We exploit both the received pilots and data signals for uplink channel estimation. We show analytically that when the number of transmit antennas and the length of the data vector both tend to infinity, the signals of the desired user and the eavesdropper lie in different eigenspaces of the received signal matrix at the base station if their signal powers are different. This finding reveals that decreasing (instead of increasing) the desire user's signal power might be an effective approach to combat a strong active attack from an eavesdropper. Inspired by this result, we propose a data-aided secure downlink transmission scheme and derive an asymptotic achievable secrecy sum-rate expression for the proposed design. Numerical results indicate that under strong active attacks, the proposed design achieves significant secrecy rate gains compared to the conventional design employing matched filter precoding and artificial noise generation.<br
Keywords: Uplink; MIMO communication; Downlink; Data communication; Channel estimation; Contamination; Transmitting antennas

Decision-Feedback Sequence Estimation for Time-Reversal Space-Time Block Coded Transmission - Schober, Robert; Chen, Harry; Gerstacker, Wolfgang (IEEE Transactions on Vehicular Technology, 2004)
In this paper, we present three different decision-feedback sequence estimation (DFSE) schemes for time-reversal space-time block coding (TR-STBC). The first scheme is called unwhitened DFSE (U-DFSE) and performs reduced-state sequence estimation based on the output of the spatio-temporal matched filter (MF) typically employed in TR-STBC. The second approach improves upon U-DFSE by subtracting a bias term caused by anti-causal interference from the U-DFSE metric. In the third scheme, the noise component in the output of the spatio-temporal MF is first whitened using a prediction-error filter that can be efficiently computed using the Levinson-Durbin algorithm, and subsequently whitened DFSE (W-DFSE) is performed. As relevant example, all three DFSE schemes are compared for the GSM/EDGE system and typical channel profiles such as typical urban (TU) and hilly terrain (HT). Our results show that for binary modulation (as used in GSM) U-DFSE and its improved version can approach the performance of W-DFSE for the full range of delay spreads relevant for GSM and EDGE. On the other hand, for high-level modulation (as used in EDGE) only W-DFSE gives a satisfactory performance, if a low trellis complexity is desired.
UnivIS-Import:2015-03-09:Pub.2004.tech.IE.mobilk.decisi
Keywords: GSM; Interference; Additive white noise; Block codes; Matched filters; Filtering; Gaussian noise; Noise cancellation; Maximum likelihood estimation; Decision feedback equalizers

Deep Learning-based Resource Allocation For Device-to-Device Communication - Lee, Woongsup; Schober, Robert (IEEE Transactions on Wireless Communications, 2022)
In this paper, a deep learning (DL) framework for the optimization of the resource allocation in multi-channel cellular systems with device-to-device (D2D) communication is proposed. Thereby, the channel assignment and discrete transmit power levels of the D2D users, which are both integer variables, are optimized for maximization of the overall spectral efficiency whilst maintaining the quality-of-service (QoS) of the cellular users. Depending on the availability of channel state information (CSI), two different configurations are considered, namely 1) centralized operation with full CSI and 2) distributed operation with partial CSI, where in the latter case, the CSI is encoded according to the capacity of the feedback channel. Instead of solving the resulting resource allocation problem for each channel realization, a DL framework is proposed, where the optimal resource allocation strategy for arbitrary channel conditions is approximated by deep neural network (DNN) models. Furthermore, we propose a new training strategy that combines supervised and unsupervised learning methods and a local CSI sharing strategy to achieve near-optimal performance while enforcing the QoS constraints of the cellular users and efficiently handling the integer optimization variables based on a few ground-truth labels. Our simulation results confirm that near-optimal performance can be attained with low computation time, which underlines the real-time capability of the proposed scheme. Moreover, our results show that not only the resource allocation strategy but also the CSI encoding strategy can be efficiently determined using a DNN. Furthermore, we show that the proposed DL framework can be easily extended to communication systems with different design objectives.
CRIS-Team Scopus Importer:2022-04-01
Keywords: Communication systems; CSI sharing; D2D transmission; deep learning; Device-to-device communication; distributed operation; interference channel; Multi-channel wireless communication systems; Optimization; Quality of service; resource allocation; Resource management; Training; Wireless communication

Degrees of Freedom of the K-User Interference Channel Assisted by Active and Passive IRSs - Abdollahi Bafghi, Ali H.; Jamali, Vahid; Nasiri-Kenari, Masoumeh; Schober, Robert (IEEE Transactions on Communications, 2022)
In this paper, we study the degrees of freedom (DoF) region and sum DoF of the time-selective K-user interference channel in the presence of intelligent reflecting surfaces (IRSs). We consider both active and passive IRSs. While both types of IRS can attenuate the amplitude and change the phase of a reflected electromagnetic wave, active IRSs are also capable of amplifying the wave. We derive inner and outer bounds for the DoF region and lower and upper bounds for the sum DoF of the K-user interference channel in the presence of an active IRS and prove that the maximum value of K for the sum DoF can be achieved if the number of IRS elements exceeds a certain finite value. The analysis framework developed for active IRSs forms the basis for our analysis of passive IRS-assisted systems. In particular, we present probabilistic inner and outer bounds for the DoF region and probabilistic lower and upper bounds for the sum DoF of the K-user interference channel in the presence of a passive IRS and prove that the lower bound for the sum DoF asymptotically approaches K as the number of IRS elements grows large.
CRIS-Team Scopus Importer:2022-03-25
Keywords: active and passive intelligent reflecting surface; DoF region; Electromagnetic scattering; Interference; Interference channels; MIMO communication; Probabilistic logic; Relays; sum DoF; Time-selective K-user interference channel; Upper bound

Delay constrained buffer-aided relaying with outdated CSI - Islam, Toufiqul; Michalopoulos, Diomidis S.; Schober, Robert; Bhargava, Vijay K. (2014 IEEE Wireless Communications and Networking Conference (WCNC), 2014)
Recent studies have shown that buffer-aided relaying with adaptive link selection can provide significant performance gains compared to conventional relaying using a fixed transmission schedule. In this paper, we focus on error rate analysis of adaptive link selection for a three node decode-and-forward (DF) relay network with fixed-rate transmission. As in practice link selection may be performed based on outdated channel state information (CSI) because of a delay in the feedback link, we study the error rate performance for both perfect and outdated CSI. Since a packet transmission delay is unavoidable with opportunistic link selection, we provide a unified error-rate analysis in terms of a decision threshold β which can be adjusted to achieve buffer stability and a desired average system delay. We show that a diversity gain of two can be achieved for perfect CSI and the optimum BER can be approached even if only a small delay is tolerated.<br
Keywords: Delays; Relays; Bit error rate; Diversity methods; Throughput; Protocols

Delay Minimization for NOMA-MEC Offloading - Ding, Zhiguo; Wing Kwan Ng, Derrick; Schober, Robert; Poor, H. Vincent (IEEE Signal Processing Letters, 2018)
This letter considers the minimization of the offloading delay for nonorthogonal multiple access assisted mobile edge computing (NOMA-MEC). By transforming the delay minimization problem into a form of fractional programming, two iterative algorithms based on, respectively, Dinkelbach's method and Newton's method are proposed. The optimality of both methods is proved and their convergence is compared. Furthermore, criteria for choosing between three possible modes, namely orthogonal multiple access, pure NOMA, and hybrid NOMA, for MEC offloading are established.<br
Keywords: NOMA; Delays; Signal processing algorithms; Iterative Methods; Newton method

Delay-throughput enhancement in wireless networks with multipath routing and channel coding - Ronasi, Keivan; Mohsenian-Rad, Amir-Hamed; Wong, Vincent W. S.; Gopalakrishnan, Sathish; Schober, Robert (IEEE Transactions on Vehicular Technology, 2011)
Multipath routing and adaptive channel coding are two well-known approaches that have been separately applied to wireless networks to improve the effective throughput. However, it is usually expected that achieving a high throughput would be at a noticeable cost of increasing the average end-to-end delay and causes major degradation in the overall network performance. In this paper, we show that a combination of multipath routing and adaptive channel coding can improve throughput and reduce delay and that it is possible to trade off delay for throughput and vice versa. This is in contrast to the general expectation that higher throughput can only be achieved with noticeable degradations in the end-to-end network delay. In this regard, we jointly formulate the end-to-end data rate allocation and adaptive channel coding (at the physical layer) within the general framework of network utility maximization (NUM). Depending on the choice of the objective function, we formulate two NUM problems: one aiming to maximize the aggregate network utility and another one aiming to maximize the minimum utility among the end-to-end flows to achieve fairness, which is of interest in certain vehicular network applications. Simulation results confirm that we can significantly decrease the average delay at the cost of a small decrease in throughput. This is achieved by maximizing the aggregate utility in the network when fairness is not the dominant concern. Furthermore, we also show that, even when resource allocation is performed to provide fairness, we can still decrease the maximum end-to-end delay of the network at the cost of a slight decrease in the minimum throughput. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Adaptive channel coding; delay-throughput tradeoff; fairness; link reliability; multipath routing; nonconvex optimization; signomial programming; utility maximization

Demand-side management for smart grid: Opportunities and challenges - Samadi, Pedram; Mohsenian-Rad, Hamed; Wong, Vincent W.S.; Schober, Robert (Smart Grid Communications and Networking, 2010)
Introduction Demand-side management (DSM) is one of the key components of the future smart grid to enable more efficient and reliable grid operation [1]. To achieve a high level of reliability and robustness in power systems, the grid is usually designed for peak demand rather than for average demand. This usually results in an under-utilized system. To remedy this problem, different programs have been proposed to shape the daily energy consumption pattern of the users in order to reduce the peak-to-average ratio in load demand and use the available generating capacity more efficiently, avoiding the installation of new generation and transmission infrastructures. However, the increasing expectations of the customers both in quantity and quality [2], emerging new types of demand such as plug-in hybrid electric vehicles (PHEVs), which can potentially double the average household energy consumption [3], the limited energy resources, and the lengthy and expensive process of exploiting new resources give rise to the need for developing some more advanced methods for DSM. Since electricity cannot be stored economically, wholesale prices (i.e., prices set by competing generators to regional electricity retailers) vary drastically between the low-demand times of day and the high-demand periods. However, these changes are usually hidden from retail users. That is, end users are usually charged with some average price. To alleviate this problem, various time-differentiated pricing methods have been proposed in the literature. Some examples include day-ahead pricing, time-of-use pricing, critical-peak-load pricing, and adaptive pricing [4–7]. By equipping users with two-way communication capabilities in smart grid systems and by adopting real-time pricing (RTP) methods, it is possible to reflect the fluctuations of wholesale prices to retail prices.
CRIS-Team Scopus Importer:2020-02-03

Detection of multiple primary systems using DAA UWB-IRs - Erkucuk, Serhat; Lampe, Lutz; Schober, Robert (Proceedings - 2009 IEEE International Conference on Ultra-Wideband, ICUWB 2009, 2009)
Underlay ultra wideband (UWB) systems have to be able to detect the presence of primary systems operating in the same band for detect-and-avoid (DAA) operation. In this paper, the performances of joint and independent detection of multiple primary systems are investigated assuming that the primary systems are potentially dependent (e.g., frequency division duplex uplink-downlink communications). Joint detection is performed based on generating the maximum a posteriori (MAP) decision variables at the receiver, where some bias terms are used with these variables in order to achieve a desired trade-off between the detection and false alarm probabilities. Independent detection is performed based on the Neyman-Pearson (NP) test, which optimizes system threshold values individually in order to achieve the best detection probability for a given false alarm probability value. When the two detection schemes are compared, it is shown that the gain of joint detection depends on the joint system activity values and the considered receiver operating characteristic (ROC) region, where the complementary ROC curves illustrate the trade-off between missdetection and false alarm probabilities. © 2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Detection Schemes and Model Mismatch Analysis for 5G Configured-Grant Access for URLLC - Laue, Friedemann; Karunakaran, Prasanth; Schober, Robert (2019 IEEE GLOBECOM WORKSHOPS (GC WKSHPS), 2019)
CRIS-Team WoS Importer:2020-08-21

Detector Nonlinearity in Six-Port Radar - Linz, Sarah; Will, Christoph; Lurz, Fabian; Lindner, Stefan; Mann, Sebastian; Schober, Robert; Weigel, Robert; Kölpin, Alexander (IEEE Topical Conference on Wireless Sensors and Sensor Networks, 2017)
This paper presents an in-situ detector characterization and calibration method for differential I/Q Sixport radar systems. A separate calibration of the nonlinear detectors and the linear Six-port front-end enables an independent analysis of errors caused by detector nonlinearity and by the measurement scenario. A linearity analysis of various detectors in Six-port radar systems shows the necessity of a detector calibration for accurate displacement measurements. The calibration is evaluated with three different Six-port front-ends at 24 GHz in divers measurement scenarios. An error reduction of up to 50% has been achieved.
elib2cris::1512001600,linz2017

Deterministic Identification for MC Binomial Channel - Salariseddigh, Mohammad Javad; Jamali, Vahid; Boche, Holger; Deppe, Christian; Schober, Robert (IEEE International Symposium on Information Theory - Proceedings, 2023)
The Binomial channel serves as a fundamental model for molecular communication (MC) systems employing molecule-counting receivers. Here, deterministic identification (DI) is addressed for the discrete-time Binomial channels (DTBC), subject to an average and a peak constraint on the molecule release rate. We establish that the number of different messages that can be reliably identified for the DTBC scales as 2(n log n)R, where n and R are the codeword length and coding rate, respectively. Lower and upper bounds on the DI capacity of the DTBC are developed.
CRIS-Team Scopus Importer:2023-09-29
Keywords: and Molecule-Counting Receivers; Binomial Channel; Deterministic Identification; Molecular Communications

Deterministic Identification for Molecular Communications Over the Poisson Channel - Salariseddigh, Mohammad Javad; Jamali, Vahid; Pereg, Uzi; Boche, Holger; Deppe, Christian; Schober, Robert (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2023)
Various applications of molecular communications (MC) are event-triggered, and, as a consequence, the prevalent Shannon capacity may not be the right measure for performance assessment. Thus, in this paper, we motivate and establish the identification capacity as an alternative metric. In particular, we study deterministic identification (DI) for the discrete-time Poisson channel (DTPC), subject to an average and a peak molecule release rate constraint, which serves as a model for MC systems employing molecule counting receivers. It is established that the number of different messages that can be reliably identified for this channel scales as 2(nlogn)R, where n and R are the codeword length and coding rate, respectively. Lower and upper bounds on the DI capacity of the DTPC are developed. The obtained large capacity of the DI channel sheds light on the performance of natural DI systems such as natural olfaction, which are known for their extremely large chemical discriminatory power in biology. Furthermore, numerical results for the empirical miss-identification and false identification error rates are provided for finite length codes. This allows us to characterize the behaviour of the error rate for increasing codeword lengths, which complements our theoretically-derived scale for asymptotically large codeword lengths.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Channel Capacity; Channel coding; Codes; Deterministic Identification; Molecular Communication; Nanobioscience; Olfactory; Poisson Channel; Receivers; Task analysis; Upper bound

Deterministic Identification over Poisson Channels - Salariseddigh, Mohammad J.; Pereg, Uzi; Boche, Holger; Deppe, Christian; Schober, Robert (2021 IEEE Globecom Workshops, GC Wkshps 2021 - Proceedings, 2021)
Deterministic identification (DI) for the discrete-time Poisson channel, subject to an average and a peak power constraint, is considered. It is established that the code size scales as 2(nlogn)R, where n and R are the block length and coding rate, respectively. The authors have recently shown a similar property for Gaussian channels [1]. Lower and upper bounds on the DI capacity of the Poisson channel are developed in this scale. Those imply that the DI capacity is infinite in the exponential scale, regardless of the dark current, i.e., the channel noise parameter.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Channel capacity; deterministic codes; identification; Poisson channel

Deterministic K-Identification for MC Poisson Channel With Inter-Symbol Interference - Salariseddigh, Mohammad Javad; Jamali, Vahid; Pereg, Uzi; Boche, Holger; Deppe, Christian; Schober, Robert (IEEE Open Journal of the Communications Society, 2024)
Various applications of molecular communications (MCs) feature an alarm-prompt behavior for which the prevalent Shannon capacity may not be the appropriate performance metric. The identification capacity as an alternative measure for such systems has been motivated and established in the literature. In this paper, we study deterministic K-identification (DKI) for the discrete-time Poisson channel (DTPC) with inter-symbol interference (ISI), where the transmitter is restricted to an average and a peak molecule release rate constraint. Such a channel serves as a model for diffusive MC systems featuring long channel impulse responses and employing molecule-counting receivers. We derive lower and upper bounds on the DKI capacity of the DTPC with ISI when the size of the target message set K and the number of ISI channel taps L may grow with the codeword length n. As a key finding, we establish that for deterministic encoding, assuming that K and L both grow sub-linearly in n, i.e., K = 2κlogn and L = 2llogn with κ + 4l ϵ 0,1), where κ ϵ 0,1) is the identification target rate and l ϵ 0,1/4) is the ISI rate, then the number of different messages that can be reliably identified scales super-exponentially in n, i.e., 2(nlogn)R, where R is the DKI coding rate. Moreover, since l and κ must fulfill κ + 4l ϵ 0,1), we show that optimizing l (or equivalently the symbol rate) leads to an effective identification rate bits/s that scales sub-linearly with n. This result is in contrast to the typical transmission rate bits/s which is independent of n.
CRIS-Team Scopus Importer:2024-02-16
Keywords: Channel capacity; deterministic identification; inter-symbol interference; Interference; molecular communication; Poisson channel; Receivers; Reliability; Symbols; Task analysis; Transmitters; Upper bound

Diffusive Mobile MC for Controlled-Release Drug Delivery with Absorbing Receiver - Cao, Trang Ngoc; Ahmadzadeh, Arman; Jamali Kooshkghazi, Vahid; Wicke, Wayan; Yeoh, Phee Lep; Evans, Jamie; Schober, Robert (ICC 2019 - 2019 IEEE International Conference on Communications (ICC), 2019)
Nanoparticle drug carriers play an important role in facilitating efficient targeted drug delivery, i.e., improving treatment success and reducing drug costs and side effects. However, the mobility of nanoparticle drug carriers poses a challenge in designing drug delivery systems. Moreover, healing results critically depend on the rate and time duration of drug absorption. Therefore, in this paper, we aim to design a controlled-release drug delivery system with a mobile drug carrier that minimizes the total amount of released drugs while ensuring a desired rate of drug absorption during a prescribed time period. We model the mobile drug carrier as a mobile transmitter, the targeted diseased cells as an absorbing receiver, and the channel between the transceivers as a time-variant channel since the carrier mobility results in a time-variant absorption rate of the drug molecules. Based on this, we develop a molecular communication (MC) framework to design the controlled-release drug delivery system. In particular, we develop new analytical expressions for the mean, variance, probability density function, and cumulative distribution function of the channel impulse response (CIR). Equipped with the statistical analysis of the CIR, we design and evaluate the performance of the controlled-release drug delivery system. Numerical results show significant savings in the amount of released drugs compared to a constant-release rate design and reveal the necessity of accounting for drug carrier mobility for reliable drug delivery.<br
Keywords: Drugs; Drug delivery; Absorption; Receivers; Diseases; Transmitters; Control systems

Diffusive Mobile MC With Absorbing Receivers: Stochastic Analysis and Applications - Cao, Trang Ngoc; Ahmadzadeh, Arman; Jamali Kooshkghazi, Vahid; Wicke, Wayan; Yeoh, Phee Lep; Evans, Jamie; Schober, Robert (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2019)
This paper presents a stochastic analysis of the time-variant channel impulse response (CIR) of a three dimensional diffusive mobile molecular communication (MC) system where the transmitter, the absorbing receiver, and the molecules can freely diffuse. In our analysis, we derive the mean, variance, probability density function (PDF), and cumulative distribution function (CDF) of the CIR. We also derive the PDF and CDF of the probability p that a released molecule is absorbed at the receiver during a given time period. The obtained analytical results are employed for the design of drug delivery and MC systems with imperfect channel state information. For the first application, we exploit the mean and variance of the CIR to optimize a controlled-release drug delivery system employing a mobile drug carrier. We evaluate the performance of the proposed release design based on the PDF and CDF of the CIR. We demonstrate significant savings in the amount of released drugs compared to a constant-release scheme and reveal the necessity of accounting for the drug-carrier's mobility to ensure reliable drug delivery. For the second application, we exploit the PDF of the distance between the mobile transceivers and the CDF of p to optimize three design parameters of an MC system employing on-off keying modulation and threshold detection. Specifically, we optimize the detection threshold at the receiver, the release profile at the transmitter, and the time duration of a bit frame. We show that the proposed optimal designs can significantly improve the system performance in terms of the bit error rate and the efficiency of molecule usage.
CRIS-Team Scopus Importer:2021-04-20
Keywords: Absorbing receivers; drug delivery; mobile molecular communications; stochastic channel modeling; time-varying channels

Diffusive Mobile Molecular Communications over Time-Variant Channels - Ahmadzadeh, Arman; Jamali, Vahid; Noel, Adam; Schober, Robert (IEEE Communications Letters, 2017)
This letter introduces a formalism for modeling time-variant channels for diffusive molecular communication systems. In particular, we consider a fluid environment where one transmitter nano-machine and one receiver nano-machine are subjected to Brownian motion in addition to the diffusive motion of the information molecules used for communication. Due to the stochastic movements of the transmitter and receiver nano-machines, the statistics of the channel impulse response change over time. We show that the time-variant behavior of the channel can be accurately captured by appropriately modifying the diffusion coefficient of the information molecules. Furthermore, we derive an analytical expression for evaluation of the expected error probability of a simple detector for the considered system. The accuracy of the proposed analytical expression is verified via particle-based simulation of the Brownian motion.
CRIS-Team Scopus Importer:2020-01-31
Keywords: mobile nano-machines; Molecular communication; time-variant channels

Diffusive Molecular Communications with Reactive Molecules: Channel Modeling and Signal Design - Jamali Kooshkghazi, Vahid; Farsad, Nariman; Schober, Robert; Goldsmith, Andrea (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2018)
This paper focuses on molecular communication (MC) systems using two types of signaling molecules which may participate in a reversible bimolecular reaction in the channel. The motivation for studying these MC systems is that they can realize the concept of constructive and destructive signal superposition, which leads to favorable properties, such as inter-symbol interference (ISI) reduction and avoiding environmental contamination due to continuous release of signaling molecules into the channel. This paper first presents a general formulation for binary modulation schemes that employ two types of signaling molecules and proposes several modulation schemes as special cases. Moreover, two types of receivers are considered: 1) a receiver that is able to observe both types of signaling molecules (2TM) and 2) a simpler receiver that can observe only one type of signaling molecules (1TM). For both of these receivers, the maximum likelihood (ML) detector for general binary modulation is derived under the assumption that the detector has perfect knowledge of the ISI-causing sequence. The performance of this genie-aided ML detector yields an upper bound on the performance of any practical detector. In addition, two suboptimal detectors of different complexity are proposed, namely, an ML-based detector that employs an estimate of the ISI-causing sequence and a detector that neglects the effect of ISI. The proposed detectors, except for the detector that neglects ISI for the 2TM receiver, require knowledge of the channel response (CR) of the considered MC system. Moreover, the CR is needed for performance evaluation of all proposed detectors. However, deriving the CR of MC systems with reactive signaling molecules is challenging since the underlying partial differential equations that describe the reaction-diffusion mechanism are coupled and non-linear. Therefore, we develop an algorithm for efficient computation of the CR and validate its accuracy via particle-based simulation. Simulation results obtained using this CR computation algorithm confirm the effectiveness of the proposed modulation and detection schemes. Moreover, these results show that MC systems with reactive signaling have superior performance relative to those with non-reactive signaling due to the reduction of ISI enabled by the chemical reactions.
CRIS-Team Scopus Importer:2022-06-05
Keywords: and inter-symbol interference; channel modeling; detector design; Diffusive molecular communications; particle-based simulation; reactive signaling

Diffusive Molecular Communications with Reactive Signaling - Jamali Kooshkghazi, Vahid; Farsad, Nariman; Schober, Robert; Goldsmith, Andrea J. (2018 IEEE International Conference on Communications (ICC), 2018)
This paper focuses on molecular communication (MC) systems where the signaling molecules may participate in a reversible bimolecular reaction in the channel. The motivation for studying these MC systems is that they can realize the concept of constructive and destructive signal superposition, which leads to favorable properties such as inter-symbol interference (ISI) reduction and avoiding environmental contamination due to continuous release of molecules into the channel. This work first derives the maximum likelihood (ML) detector for a binary MC system with reactive signaling molecules under the assumption that the detector has perfect knowledge of the ISI. The performance of this genie-aided ML detector yields an upper bound on the performance of any practical detector. In addition, two suboptimal detectors of different complexity are proposed. The proposed ML detector as well as one of the suboptimal detectors require the channel response (CR) of the considered MC system. Moreover, the CR is needed for the performance evaluation of all proposed detectors. However, analyzing MC with reactive signaling is challenging since the underlying partial differential equations that describe the reaction-diffusion mechanism are coupled and non-linear. Therefore, an algorithm is developed in this paper for efficient computation of the CR to any arbitrary transmit symbol sequence. The accuracy of this algorithm is validated via particle-based simulation. Simulation results using the developed CR algorithm show that the performance of the proposed suboptimal detectors can approach that of the genie-aided ML detector. Moreover, these results show that MC systems with reactive signaling have superior performance relative to those with non-reactive signaling due to the reduction of ISI enabled by the chemical reactions.<br
Keywords: Detectors; Transmitters; Receivers; Biochemistry; Modulation; Computational modeling; Molecular communication

Diffusive molecular communication with disruptive flows - Noel, Adam; Cheung, Karen C.; Schober, Robert (2014 IEEE International Conference on Communications (ICC), 2014)
In this paper, we study the performance of detectors in a diffusive molecular communication environment where steady uniform flow is present. We derive the expected number of information molecules to be observed in a passive spherical receiver, and determine the impact of flow on the assumption that the concentration of molecules throughout the receiver is uniform. Simulation results show the impact of advection on detector performance as a function of the flow's magnitude and direction. We highlight that there are disruptive flows, i.e., flows that are not in the direction of information transmission, that lead to an improvement in detector performance as long as the disruptive flow does not dominate diffusion and sufficient samples are taken.<br
Keywords: Receivers; Detectors; Transmitters; Noise; Error probability; Accuracy; Molecular communication

Direct electricity trading in smart grid: A coalitional game analysis - Lee, Woongsup; Xiang, Lin; Schober, Robert; Wong, Vincent W. S. (IEEE Journal on Selected Areas in Communications, 2014)
Integration of distributed generation based on renewable energy sources into the power system has gained popularity in recent years. Many small-scale electricity suppliers (SESs) have recently entered the electricity market, which has been traditionally dominated by a few large-scale electricity suppliers. The emergence of SESs enables direct trading (DT) of electricity between SESs and end-users (EUs), without going through retailers, and promotes the possibility of improving the benefits to both parties. In this paper, the cooperation between SESs and EUs in DT is analyzed based on coalitional game theory. In particular, an electricity pricing scheme that achieves a fair division of revenue between SESs and EUs is analytically derived by using the asymptotic Shapley value. The asymptotic Shapley value is shown to be in the core of the coalitional game such that no group of SESs and EUs has an incentive to abandon the coalition, which implies the stable operation of DT for the proposed pricing scheme. Unlike the existing pricing schemes that typically require multiple stages of calculations and real time information about each participant, the electricity price for the proposed scheme can be determined instantaneously based on the number of participants in DT and statistical information about electricity supply and demand. Therefore, the proposed pricing scheme is suitable for practical implementation. Using computer simulations, the price of electricity for the proposed DT scheme is examined in various environments, and the numerical results validate the asymptotic analysis. Moreover, the revenues of the SESs and EUs are evaluated for various types of SESs and different numbers of participants in DT. The optimal ratio of different types of SESs is also investigated. © 2014 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: coalitional game; direct trading; electricity market; renewable energy; Shapley value; Smart grid

Distributed channel selection and randomized interrogation algorithms for large-scale and dense RFID systems - Mohsenian-Rad, Amir-Hamed; Shah-Mansouri, Vahid; Wong, Vincent W. S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2010)
Radio frequency identification (RFID) is an emerging wireless communication technology which allows objects to be identified automatically. An RFID system consists of a set of readers and several objects, equipped with small and inexpensive computer chips, called tags. In a dense RFID system, where several readers are placed together to improve the read rate and correctness, readers and tags can frequently experience packet collision. High probability of collision impairs the benefit of multiple reader deployment and results in misreading. A common approach to avoid collision is to use a distinct frequency channel for interrogation for each reader. Various multi-channel anti-collision protocols have been proposed for RFID readers. However, due to their heuristic nature, most algorithms may not achieve optimal system performance. In this paper, we systematically design two optimization-based distributed channel selection and randomized interrogation algorithms for dense RFID systems. For this purpose, we develop elaborate models for the reader-to-tag and reader-to-reader collision problems. The first algorithm is fully distributed and is guaranteed to find a local optimum of a max-min fair resource allocation problem for RFID systems. The second algorithm is semi-distributed and achieves the global optimal system performance. Max-min fair optimality balances the performance and the processing load among readers. Simulation results show that our algorithms have significantly better performance than the previous heuristic algorithms. © 2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Max-min fairness; Optimization; Radio frequency identification; Randomized multi-channel interrogation

Distributed generalized cyclic delay diversity for cooperative OFDM systems - Chen, Harry Z. B.; Schober, Robert; Lampe, Lutz (IEEE Vehicular Technology Conference, 2008)
In this paper, we introduce distributed generalized cyclic delay diversity (DGCDD) for cooperative signaling in orthogonal frequency division multiplexing (OFDM) wireless relay networks. We assume that the set of cooperating nodes is a priori unknown and assign each node in the network a fixed cyclic filter (CF). Assuming bit-interleaved coded modulation (BICM) for forward error correction, we derive an optimization criterion for the CFs and show that DGCDD can exploit the full diversity of the wireless channel. A numerical method for CF design is provided and compared with randomly generated Alters. Simulation results confirm the excellent performance of the proposed scheme and show that the performance loss of DGCDD compared to GCDD with co-located antennas is small for sufficiently long CFs. © 2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Distributed Multi-Antenna Frequency-Selective Energy Beamforming with Joint Total and Individual Power Constraints - Luo, Bing; Yeoh, Phee Lep; Schober, Robert; Krongold, Brian S. (IEEE Transactions on Green Communications and Networking, 2022)
We analyze distributed multi-antenna energy beamforming over frequency selective fading channels in wireless power transfer (WPT) systems with joint total and individual transmit power constraints. The constraints allow the WPT system to limit energy consumption for cost or environmental factors, and prevent individual coordinated energy transmitters (CETs) from overdriving their high-powered amplifiers due to hardware limitations. The harvested power at the energy receiver is modeled as an arbitrary non-linear, continuous, and non-decreasing function of the received radio frequency (RF) power. We show that the optimal frequency selective energy beamforming solution for K CETs with M antennas each is equivalent to maximizing the total RF power coherently combined at the energy receiver over N shared subchannels. We obtained the optimal frequency selective energy beamforming strategy with the following insightful properties: First, for any subchannel, either all antennas of all K CETs allocate zero power to this subchannel (i.e., inactive), or all antennas of all K CETs allocate non-zero power to this subchannel (i.e., active). Second, for the active subchannels, we show that the optimal power allocation obeys a proportionality principle for the powers from all antennas of all K CETs, which reveals that higher powers are not necessarily allocated to subchannels with higher channel gains. Third, we prove that optimally no more than T+1 subchannels are selected for energy beamforming, where T (less than K) is the number of CETs transmitting at their maximum individual powers due to the total power constraint. Based on the above properties, we show that the energy beamforming solution can be efficiently achieved via solving a low-complexity dual problem in simpler form with only K+1 variables compared to the original primal problem with NMK variables. Numerical examples verify our theoretical findings and show the impact of the joint total and individual power constraints on the average harvested power.
CRIS-Team Scopus Importer:2022-05-20
Keywords: Antennas; Array signal processing; distributed energy beamforming; frequency-selective channels; KKT conditions.; optimal power allocation; Radio frequency; Radio transmitters; Receiving antennas; Resource management; total and individual power constraints; Transmitting antennas; Wireless power transfer

Distributed Optimization of Hierarchical Small Cell Networks: A GNEP Framework - Wang, Jiaheng; Guan, Wei; Huang, Yongming; Schober, Robert; You, Xiaohu (IEEE Journal on Selected Areas in Communications, 2017)
Deployment of small cell base stations (SBSs) overlaying the coverage area of a macrocell BS (MBS) results in a two-tier hierarchical small cell network. Cross-tier and inter-tier interference not only jeopardize primary macrocell communication but also limit the spectral efficiency of small cell communication. This paper focuses on distributed interference management for downlink small cell networks. We address the optimization of transmit strategies from both the game theoretical and the network utility maximization (NUM) perspectives and show that they can be unified in a generalized Nash equilibrium problem (GNEP) framework. Specifically, the small cell network design is first formulated as a GNEP, where the SBSs and MBS compete for the spectral resources by maximizing their own rates while satisfying global quality of service (QoS) constraints. We analyze the GNEP via variational inequality theory and propose distributed algorithms, which only require the broadcasting of some pricing information, to achieve a generalized Nash equilibrium (GNE). Then, we also consider a nonconvex NUM problem that aims to maximize the sum rate of all BSs subject to global QoS constraints. We establish the connection between the NUM problem and a penalized GNEP and show that its stationary solution can be obtained via a fixed point iteration of the GNE. We propose GNEP-based distributed algorithms that achieve a stationary solution of the NUM problem at the expense of additional signaling overhead and complexity. The convergence of the proposed algorithms is proved and guaranteed for properly chosen algorithm parameters. The proposed GNEP framework can scale from a QoS constrained game to an NUM design for small cell networks by trading off signaling overhead and complexity.<br
Keywords: Macrocell Networks; Interference; Computer Architecture; Microprocessors; Quality of Service; Games; Optimization

Distributed space-time continuous phase modulation code design - Silvester, Anna-Marie; Lampe, Lutz; Schober, Robert (IEEE Transactions on Wireless Communications, 2008)
In this paper, distributed space-time (ST) codes for continuous-phase modulation (CPM) are introduced. The distributed ST codes are designed to operate in wireless networks containing a large set of nodes N, of which only a small a priori unknown subset S ⊂ N will be active at any time. Under the proposed scheme, a relay node transmits a signal which is the product of a diagonal block-based ST code (optimized specifically for ST-CPM transmission) and a signature vector of length Nc uniquely assigned to each node in the network. An efficient method is presented for the design and optimization of appropriate signature vector sets, assuming a quasi-static, frequency non-selective fading channel model. If a properly designed signature vector set is employed it is shown that a diversity order of d = minNs, N c can be achieved, where Ns is the number of active relay nodes. The decoding complexity of the proposed scheme is shown to be independent of the number of active relay nodes, and non-coherent receiver implementations, which do not require channel estimation, are applicable. Compared to distributed ST transmission with linear modulation, distributed ST-CPM can considerably reduce the energy consumption at the transmitter due to the constant envelope of the transmit signal. At the same time, the additional energy consumption due to more complex receiver processing can be kept low. Therefore, the proposed distributed ST-CPM scheme is particularly apt for energy-efficient cooperative transmission in wireless networks. © 2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: ad hoc and sensor networks; Co-operative diversity; Continuous-phase modulation; Distributed space-time coding; Relaying; Wireless networks

Distributed transmit power allocation for multihop cognitive-radio systems - Mietzner, Jan; Lampe, Lutz; Schober, Robert (IEEE Transactions on Wireless Communications, 2009)
In this paper, we consider a relay-assisted wideband cognitive-radio (CR) system under the assumption that the frequency band chosen by the CR relay network for unlicensed spectrum usage overlaps with one or more bands dedicated to primary (e.g., licensed) narrowband links. Our objective is to optimize the performance of the CR system while limiting the interference in direction of the primary receivers, without requiring any adaptation of the transmitted signal spectra at the cognitive nodes. To this end, we study appropriate transmit power allocation (TPA) strategies among the cognitive relays. We first investigate the optimal centralized (OC) TPA solution and show that it can be formulated as a linear program. Since the OC-TPA solution requires a considerable amount of information exchange between the cognitive nodes, we develop two distributed TPA schemes, namely (i) a fully decentralized (FD) TPA scheme and (ii) a distributed feedback-assisted (DFA) TPA scheme. The FD-TPA scheme aims at maximizing the output signal-tointerference- plus-noise ratio (SINR) at the destination node of the CR network according to a best-effort strategy. It requires neither feedback information from the destination node nor an exchange of channel state information between the cognitive relays. The DFA-TPA scheme, on the other hand, utilizes feedback information from the destination node, in order to achieve a predefined target output SINR value, while minimizing the overall transmit power spent by the relays. Analytical and simulationbased performance results illustrate that notable performance improvements compared to non-cooperative transmission (i.e., without relay assistance) are achieved by the proposed schemes, especially when more than two hops are considered. In particular, the proposed distributed TPA schemes typically perform close to the OC-TPA solution. © 2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Cognitive radio; Performance analysis; Relaying; Transmit power allocation

Distributed user-centric scheduling for visible light communication networks - Chen, Lingjiao; Wang, Jiaheng; Zhou, Jiantao; Ng, Derrick Wing Kwan; Schober, Robert; Zhao, Chunming (Optics Express, 2016)
Visible light communication (VLC) networks, consisting of multiple light-emitting diodes (LEDs) acting as optical access points (APs), can provide low-cost high-rate data transmission to multiple users simultaneously in indoor environments. However, the performance of VLC networks is severely limited by the interference between different users. In this paper, we establish a distributed user-centric scheduling framework based on stable marriage theory, and propose a novel decentralized scheduling method to manage interference by forming flexible amorphous cells for all users. The proposed scheduling method has provable low computational complexity and requires only the exchange of a few 1-bit messages between the APs and the users but not the feedback of the channel state information of the entire network. We further show that the proposed method can achieve both user-wise and system-wise optimality as well as a certain level of fairness. Simulation results indicate that our decentralized user-centric scheduling method outperforms existing centralized approaches in terms of throughput, fairness, and computational complexity.
CRIS-Team Scopus Importer:2020-01-31

Diversity analysis of multi-user multi-relay networks - Kim, Junsu; Michalopoulos, Diomidis S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2011)
In this paper, we analyze the diversity order of opportunistic scheduling networks with arbitrary numbers of relays and users. We show that the opportunistic selection of the relay-user pair with the best end-to-end signal-to-noise ratio (SNR) among M relays and N users achieves a diversity order in the range of [M + N, MN + N] for amplify-and-forward (AF) relays and in the range of [N, MN + N] for decode-and-forward (DF) relays. Our analysis reveals that the achievable diversity order with AF relays depends on the relative strength of the source-relay (SR) and relay-destination (RD) links, while the achievable diversity order with DF relays depends on the SR link SNR. Based on our analysis, which is verified by simulation results, we show that, for AF relays, the maximum diversity order of MN + N is achieved if the SR link quality is better than the RD link quality, and, for DF relays, if the SR link is sufficiently strong such that the relays always succeed in decoding. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Cooperative relaying; diversity order; outage analysis; relay selection; scheduling

Diversity and delay analysis of buffer-aided BICM-OFDM relaying - Islam, Toufiqul; Ikhlef, Aissa; Schober, Robert; Bhargava, Vijay K. (IEEE Transactions on Wireless Communications, 2013)
In this paper, we study a cooperative diversity scheme for wireless systems where the relay is equipped with a buffer. We consider practical frequency-selective channels and adopt the combination of bit interleaved coded modulation and orthogonal frequency division multiplexing (BICM-OFDM). We propose a novel link selection protocol for BICM-OFDM systems where the relay either transmits or receives in a given time slot depending on the quality of the links. We derive a closed-form upper bound for the asymptotic worst-case pairwise error probability (PEP) and the diversity gain of the considered buffer-aided relaying scheme for both infinite and finite buffer size. We show that significant diversity gains can be achieved with buffer-aided relaying compared to conventional relaying at the expense of larger packet delays. In fact, for buffers of infinite (or very large) size, the diversity gain is doubled for links with identical frequency diversity, and an even higher diversity gain advantage is possible for links with non-identical frequency diversities. Furthermore, we perform an exact closed-form average delay analysis for buffers of both finite and infinite size which provides important insight into the achieved delay-performance tradeoff. The derived analytical results and performance gains are corroborated by extensive simulation results. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: BICM; Buffer-aided relaying; Cooperative diversity; OFDM

Diversity combining in FSO systems in presence of non-Gaussian noise - Kamboj, Anisha; Mallik, Ranjan K.; Agrawal, Monika; Schober, Robert (2012 International Conference on Signal Processing and Communications, SPCOM 2012, 2012)
Free-space optics (FSO) communication has received much attention in recent years as a cost-effective, license-free, and wide-bandwidth access technique for high data rate applications. The performance of FSO communication, however, severely suffers from turbulence caused by atmospheric conditions. Multiple photodetectors can be placed at the receiver to mitigate the turbulence and exploit the advantages of spatial diversity combining. In this paper, we analyze the bit error rate (BER) performance of an FSO communication system employing binary phase-shift keying with additive non-Gaussian noise over negative exponential distributed atmospheric turbulence and spatial diversity at the receiver. The Laplace distribution is used to model the non-Gaussian impulsive noise. We consider the case when perfect channel state information is available at the receiver for implementation of coherent detection. Analytical expressions for the BER of a single channel receiver as well as that of a diversity combining receiver using selection combining, dual-diversity equal-gain combining, and maximalratio combining are derived. The derived analytical expressions are verified by simulation results. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Bit error rate (BER); equal-gain combining (EGC); free-space optics (FSO); maximalratio combining (MRC); negative exponential fading; non-Gaussian noise; selection combining (SC)

Diversity loss due to suboptimal relay selection - Michalopoulos, Diomidis S.; Chatzidiamantis, Nestor D.; Schober, Robert; Karagiannidis, George K. (GLOBECOM - IEEE Global Telecommunications Conference, 2011)
The performance of relay selection is degraded when the channel estimates used for relay selection are imperfect. Considering that the channel estimates are obtained via practical channel estimation techniques, we quantify the effects of imperfect channel state information (CSI) on the diversity order of relay selection. The analysis involves combining the effects of noise, time-varying channels, and feedback delays on the CSI used for relay selection into a unified model. Based on this model, the correlation between the actual and the estimated channel values, ρ, is expressed as a function of the signal-to-noise ratio (SNR), providing interesting insight into the behavior of the outage probability in high SNR. The resulting expression for the diversity order reveals that the behavior of the correlation in high SNR crucially affects the asymptotic performance of relay selection. In summary, based upon expressing ρ as a function of the SNR, we answer the following question: How fast should ρ tend to one, as the SNR tends to infinity, so that relay selection does not experience any diversity loss? © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Diversity-multiplexing trade-off of the hybrid non-orthogonal amplify-decode and forward protocol - Lusina, Paul; Schober, Robert; Lampe, Lutz (IEEE International Symposium on Information Theory - Proceedings, 2008)
We propose a hybrid non-orthogonal amplify-decode and forward (NADF) transmission protocol for two halfduplex relay nodes. This strategy allows simple amplify and forward (AF) nodes and more complex decode and forward (DF) nodes to participate jointly in the transmission of information. Such a strategy is useful in networks with heterogeneous devices. Analysis of the diversity-multiplexing trade-off (DMT) shows our protocol to be better than the dynamic decode and forward (DDF) protocol for rates between 1/2 and 2/3. Our technique demonstrates that the DDF protocol is not an upper bound and that protocols exist which perform closer to the DMT limit. The NADF protocol has equal performance to the DDF protocol for rates between 2/3 and one. It has a DMT performance below the DDF protocol and identical to or better than the slotted amplify and forward (SAF) protocol and non-orthogonal amplify and forward (NAF) schemes for rates from zero to 1/2. © 2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Double-differential encoding for dual-hop amplify-and-forward relaying in IR-UWB systems - Hamdi, Maziyar; Mietzner, Jan; Schober, Robert (IEEE Vehicular Technology Conference, 2010)
In this paper, we propose to improve the performance of impulse-radio ultra-wideband (IR-UWB) systems by means of cooperative relaying. With regard to a simple practical realization, we focus on a non-coherent system setup in conjunction with amplify-and-forward (A&F) relaying. In particular, considering a two-hop scenario we propose to employ a double-differential encoding scheme at the source node and single differential decoding at the relay and the destination node, respectively, so as to efficiently limit intersymbol-interference (ISI) effects. A thorough performance analysis of the proposed scheme is provided, along with a closed-form optimization of the transmit power allocation between source and relay. Simulation results illustrate the excellent performance of the proposed scheme, which is compared to alternative coherent and noncoherent schemes based on A&F relaying and decode-andforward (D&F) relaying. © 2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Downlink Massive MU-MIMO with Successively-Regularized Zero Forcing Precoding - Krishnamoorthy, Aravindh; Schober, Robert (IEEE Wireless Communications Letters, 2022)
In this letter, we consider linear precoding for downlink massive multi-user (MU) multiple-input multiple-output (MIMO) systems. We propose the novel successively-regularized zero forcing (SRZF) precoding, which exploits successive null spaces of the MIMO channels of the users, along with regularization, to control the inter-user interference (IUI) and to enhance performance and robustness to imperfect channel state information (CSI) at the base station (BS). We study the IUI characteristics of the proposed SRZF precoding for perfect and imperfect CSI at the BS. Furthermore, via computer simulations, we compare the sum rate of SRZF precoding with those of several baseline schemes including conventional and regularized zero forcing (ZF) precoding. Our simulation results reveal that, for massive MIMO systems with inter-user channel correlations, the proposed SRZF precoding significantly outperforms the considered baseline schemes for both perfect and imperfect CSI at the BS.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Decoding; Downlink; MIMO communication; Null space; Precoding; Robustness; Symmetric matrices

Downlink MIMO-RSMA with Successive Null-Space Precoding - Krishnamoorthy, Aravindh; Schober, Robert (IEEE Transactions on Wireless Communications, 2022)
In this paper, we consider the precoder design for an underloaded or critically loaded downlink multi-user multiple-input multiple-output (MIMO) communication system. We propose novel precoding and decoding schemes which enhance system performance based on rate splitting at the transmitter and single-stage successive interference cancellation at the receivers. The proposed successive null-space (SNS) precoding utilizes linear combinations of the null-space basis vectors of the successively augmented MIMO channel matrices of the users as precoding vectors to adjust the inter-user-interference experienced by the receivers. We formulate a non-convex weighted sum rate optimization problem for the precoding vectors and the associated power allocation for the proposed SNS-based MIMO-rate-splitting multiple access (RSMA) scheme. We obtain a suboptimal solution for this problem via successive convex approximation. Moreover, we study the robustness of the proposed precoding scheme to imperfect channel state information (CSI) at the base station via derivative-based sensitivity analysis. Our analysis and simulation results reveal the enhanced performance and robustness of the proposed SNS-based MIMO-RSMA scheme over several baseline multi-user MIMO schemes, especially for imperfect CSI.
CRIS-Team Scopus Importer:2022-10-28
Keywords: Communication systems; Downlink; MIMO communication; Optimization; Precoding; Robustness; Symbols

Downlink Precoder Design for Two-User Power-Domain MIMO-NOMA with Excess Degrees of Freedom - Krishnamoorthy, Aravindh; Schober, Robert; Ding, Zhiguo (2019 IEEE International Conference on Communications Workshops (ICC Workshops), 2019)
In this paper, we consider downlink precoder design for two-user power-domain multiple-input multiple-output (MIMO) non-orthogonal multiple access (NOMA) for the scenario where the receivers have fewer antennas than the transmitter. We propose a novel precoding scheme which takes advantage of the excess degrees of freedom (DoFs) at the transmitter to enhance MIMO-NOMA performance. The proposed precoder achieves simultaneous diagonalization of the MIMO channels of both users, assuming self-interference cancellation at one of the receivers, thereby lowering the overall decoding complexity. The performance of the proposed scheme is analyzed in terms of the ergodic rate using results from non-asymptotic random matrix theory. Our results show that the proposed scheme significantly outperforms orthogonal multiple access (OMA) and a benchmark precoder performing simultaneous diagonalization via generalized singular value decomposition (GSVD).<br

Downlink scheduling with transmission strategy selection for multi-cell MIMO systems - Niu, Binglai; Wong, Vincent W. S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2013)
In this paper, we study downlink scheduling with transmission strategy selection in multi-cell multiple-input multiple-output (MIMO) systems. Depending on the level of inter-cell interference experienced by a user, the scheduler can choose between two MIMO transmission strategies, namely, spatial multiplexing and interference alignment. We formulate an optimization problem which aims to jointly select a user and the corresponding transmission strategy for each base station in order to maximize the overall system utility while stabilizing all transmission queues. We first develop a centralized dynamic scheduling scheme with transmission strategy selection by using a stochastic network optimization approach. To reduce the communication overhead, we then propose a distributed scheduling algorithm which only requires limited message exchange between the base stations. We also consider the impact of imperfect channel state information on the scheduling schemes and propose an efficient rate adjustment method to improve the performance for this case. Simulation results show that the performance of the proposed distributed scheduling scheme is close to that of the centralized scheduling scheme, and both schemes achieve a better performance than schemes employing a single transmission strategy. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: interference alignment; Scheduling; spatial multiplexing; stochastic network optimization

Downlink scheduling with transmission strategy selection for two-cell MIMO networks - Niu, Binglai; Wong, Vincent W.S.; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2011)
Multiple-input multiple-output (MIMO) processing is a promising technique to achieve high speed data service in next generation cellular networks. However, the performance of multi-cell MIMO networks is limited by the cell-edge users who experience significant inter-cell interference. In this paper, we propose to use interference alignment to mitigate interference experienced by these cell-edge users, and spatial multiplexing for users with less interference. To achieve the optimal performance in a two- cell MIMO network, we formulate a joint scheduling problem to select a pair of users and the corresponding transmission strategies for both cells. We design an efficient dynamic scheduling scheme based on a stochastic network optimization framework. Numerical results show that the proposed scheme achieves a superior performance compared to scheduling schemes with a single transmission strategy. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Dual-hop amplify-and-forward transmission with imperfect channel estimates at the relay - Hadzi-Velkov, Zoran; Michalopoulos, Diomidis S.; Karagiannidis, George K.; Schober, Robert (IEEE International Conference on Communications, 2012)
With reference to the typical three-node amplify-and-forward (AF) relaying setup, where a single relay assists the communication between a source terminal and a destination terminal, we investigate the effect of outdated channel state information (CSI) at the relay on the overall performance. In particular, we consider CSI-assisted (i.e., variable-gain) AF relaying and derive expressions for the outage and the error probability for the case where the relay gain is adapted based on outdated estimates of the source-relay channel, when operating over Nakagami-m fading. The obtained expressions are functions of the scale and shape fading parameters, as well as the correlation coefficient between the actual source-relay channel and its corresponding estimate. Numerical results reveal a considerable degradation of the overall performance, when CSI acquisition is not perfect. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Duopoly price competition of WLAN service providers in presence of heterogeneous user demand - Kumar, Abhinav; Mallik, Ranjan K.; Schober, Robert (IEEE Wireless Communications and Networking Conference, WCNC, 2012)
In the presence of several wireless local area network (WLAN) service providers, the users have to make a choice. The price charged and the congestion experienced by the users play an important role in making this choice. In this paper, we analyze the duopoly price competition between two WLAN service providers in the presence of four types of users. We prove that the distribution of heterogeneous user demand is governed by the Wardrop equilibrium. We also show the existence of the Nash equilibrium between competing WLAN service providers. It is further shown through analysis that the social welfare in Nash equilibrium is close to its maximal value. We find that compared to a strictly regulated monopoly, an unregulated WLAN duopoly market results in significant transfer of the surplus from service providers to users with negligible losses in efficiency. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Duopoly price competition; heterogeneous users; Nash equilibrium (NE); price of anarchy (PoA); social welfare (SW); Wardrop equilibrium (WE); wireless local area network (WLAN)

Dynamic resource allocation in MIMO-OFDMA systems with full-duplex and hybrid relaying - Ng, Derrick Wing Kwan; Lo, Ernest S.; Schober, Robert (IEEE Transactions on Communications, 2012)
In this paper, we formulate a joint optimization problem for resource allocation and scheduling in full-duplex multiple-input multiple-output orthogonal frequency division multiple access (MIMO-OFDMA) relaying systems with amplify-and-forward (AF) and decode-and-forward (DF) relaying protocols. Our problem formulation takes into account heterogeneous data rate requirements for delay sensitive and non-delay sensitive users. We also consider a theoretically optimal hybrid relaying scheme as a performance benchmark, which allows a dynamic selection between AF relaying and DF relaying protocols with full-duplex and half-duplex relays. We show that under some mild conditions the optimal transmitter precoding and receiver post-processing matrices jointly diagonalize the MIMO-OFDMA relay channels for all considered relaying protocols transforming the resource allocation and scheduling problem into a scalar optimization problem. Dual decomposition is employed to solve this optimization problem and a distributed iterative resource allocation and scheduling algorithm with closed-form power and subcarrier allocation is derived. Simulation results not only illustrate that the proposed distributed algorithm converges to the optimal solution in a small number of iterations, but also demonstrate the potential performance gains achievable with full-duplex relaying protocols. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Amplify-and-forward relays; Decode-and-forward relays; Distributed resource allocation; Dual decomposition; Full-duplex relaying; Loop interference; MIMO-OFDMA; Multiuser diversity

Dynamic resource allocation in OFDMA systems with full-duplex and hybrid relaying - Ng, Derrick Wing Kwan; Schober, Robert (IEEE International Conference on Communications, 2011)
In this paper, we formulate a joint optimization problem for resource allocation and scheduling in full-duplex orthogonal frequency division multiple access (OFDMA) relaying systems with amplify-and-forward (AF) and decode-and-forward (DF) relaying protocols. Our problem formulation takes into account heterogeneous data rate requirements for delay sensitive users. Besides, a theoretically optimal hybrid relaying, which allows a dynamic selection between AF relaying and DF relaying protocols with full-duplex relays or half-duplex relays, is also considered in the problem formulation and serves as a performance benchmark. A dual decomposition method is employed to solve the resulting optimization problem and a novel distributed iterative resource allocation and scheduling algorithm with closed-form power and subcarrier allocation is derived. Simulation results illustrate that the proposed distributed algorithm requires only a small number of iterations to achieves practically the same performance as the optimal centralized algorithm. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Early cancer detection in blood vessels using mobile nanosensors - Mosayebi, Reza; Ahmadzadeh, Arman; Wicke, Wayan; Jamali, Vahid; Schober, Robert; Nasiri-Kenari, Masouhmeh (IEEE Transactions on Nanobioscience, 2019)
In this paper, we propose using mobile nanosensors (MNSs) for early stage anomaly detection. For concreteness, we focus on the detection of cancer cells located in a particular region of a blood vessel. These cancer cells produce and emit special molecules, so-called biomarkers, which are symptomatic for the presence of anomaly, into the cardiovascular system. Detection of cancer biomarkers with conventional blood tests is difficult in the early stages of a cancer due to the very low concentration of the biomarkers in the samples taken. However, close to the cancer cells, the concentration of the cancer biomarkers is high. Hence, detection is possible if a sensor with the ability to detect these biomarkers is placed in the vicinity of the cancer cells. Therefore, in this paper, we study the use of MNSs that are injected at a suitable injection site and can move through the blood vessels of the cardiovascular system, which potentially contain cancer cells. These MNSs can be activated by the biomarkers close to the cancer cells, where the biomarker concentration is sufficiently high. Eventually, the MNSs are collected by a fusion center (FC), where their activation levels are read and exploited to declare the presence of anomaly. We analytically derive the biomarker concentration in a network of interconnected blood vessels as well as the probability mass function of the MNSs' activation levels and validate the obtained results via particle-based simulations. Then, we derive the optimal decision rule for the FC regarding the presence of anomaly assuming that the entire network is known at the FC. Finally, for the FC, we propose a simple sum detector that does not require knowledge of the network topology. Our simulations reveal that while the optimal detector achieves a higher performance than the sum detector, both proposed detectors significantly outperform a benchmark scheme that uses fixed nanosensors at the FC.
CRIS-Team Scopus Importer:2019-05-14
Keywords: advection-diffusion; anomaly detection; cardiovascular system; mobile nanosensor; Molecular communication; optimal and suboptimal detectors

EDFA-based all-optical relaying in free-space optical systems - Bayaki, Ehsan; Michalopoulos, Diomidis S.; Schober, Robert (IEEE Vehicular Technology Conference, 2011)
Free-space optical (FSO) communications has recently received considerable attention for last-mile terrestrial applications and wireless backhaul in mobile communication systems. The performance of these systems is mainly impaired by weather-dependent attenuation and the intensity variations of the channel known as scintillation. The distance-dependence of both attenuation and scintillation motivates the use of relays as a means of improving system performance and extending the communication link. In this paper, we propose an exact and practical model for all-optical relays employing erbium-doped fiber amplifiers (EDFAs), which avoid the optical-to-electrical and electrical-to-optical conversions required in conventional FSO relays employing electrical amplification. The proposed model is shown to be more accurate than existing simplified models and an outage probability analysis for all-optical EDFA-based relaying in the presence of lognormal fading is presented. Our results show that FSO systems with simple all-optical relays achieve a better performance compared to systems with relays employing electrical amplification. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

EDFA-based all-optical relaying in free-space optical systems - Bayaki, Ehsan; Michalopoulos, Diomidis S.; Schober, Robert (IEEE Transactions on Communications, 2012)
Free-space optical (FSO) communication has recently gained a lot of interest for last-mile terrestrial applications. Some of its advantages include high data rates, ease of deployment, license-free operation, and high security. However, the weather-dependent optical wireless channel introduces attenuation and intensity variations known as scintillation which impose severe challenges for reliable data transmission. The distance dependence of both attenuation and scintillation motivates the use of relays as a means of improving the system performance and extending the range of communication. In this paper, we advocate the use of all-optical relays equipped with erbium-doped fiber amplifiers (EDFAs), which, in contrast to conventional FSO relays with electrical amplification, avoid optical-to-electrical and electrical-to-optical conversions. We develop accurate signal and noise models for fixed and variable gain all-optical and electrical relaying which include the effects of all relevant system parameters and types of noise. For performance evaluation, we analyze the outage probability of all-optical relaying in lognormal fading for dual-hop and multi-hop transmission. Our results show that all-optical relays, while simpler from an implementation point of view, outperform electrical relays unless the number of relays is very large. Moreover, for a fixed source-destination distance, performance improves as the number of hops (relays) increases up to a certain point beyond which adding more hops deteriorates performance. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: All-optical relaying; erbium-doped fiber amplifiers; multihop free-space optical communications

Effect of spectrum sensing reliability on the capacity of multiuser uplink cognitive radio systems - Kim, Junsu; Shin, Yoan; Ban, Tae Won; Schober, Robert (IEEE Transactions on Vehicular Technology, 2011)
In this paper, we investigate the performance of opportunistic scheduling in uplink cognitive radio (CR) systems by taking into account the CR users' spectrum sensing reliability. In uplink CR systems, each secondary transmitter (CR user) has a spectrum sensing responsibility to protect the primary system, and the secondary receiver (base station) schedules the transmission opportunities for the CR users. We propose novel optimal and suboptimal scheduling schemes by simultaneously taking into account the spectrum sensing reliability and the data channel quality. Analytical performance results for the proposed suboptimal scheduling schemes show that the spectrum sensing reliability should be considered for scheduling to maximize the capacity of the secondary system. Moreover, we also analyze the achievable multiuser diversity (MUD) gain of one of the proposed suboptimal scheduling schemes, which is based on the linear combination of the sensing channel and the data channel qualities. We show that the MUD gain of uplink CR systems grows significantly slower than that of conventional multiuser systems, particularly if the quality of the sensing channel is poor. Analytical and simulation results confirm that the proposed optimal and suboptimal scheduling schemes taking into account the spectrum sensing reliability and the data channel quality yield significant performance gains compared with conventional opportunistic scheduling. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Cognitive radio (CR); multiuser CR systems; multiuser diversity (MUD) gain; uplink scheduling

Efficient receivers for GSM MUROS downlink transmission - Meyer, Raimund; Gerstacker, Wolfgang; Obernosterer, Frank; Ruder, Michael; Schober, Robert (2009 IEEE 20th International Symposium on Personal, Indoor and Mobile Radio Communications, 2010)
Currently, Multiple Users Reusing One Slot (MUROS) is discussed in 3GPP GERAN as an extension of the GSM standard. In MUROS, two overlaid GMSK signals are transmitted in the same time slot and at the same frequency resource. By this, capacity of existing GSM networks in principle can be doubled and up to four half rate voice users can share one time slot. In this paper, channel estimation and detection is investigated for the MUROS downlink. Two novel channel estimation algorithms are presented, taking into account the specifics of the MUROS downlink. For detection, a joint MLSE of both user signals can be applied in case of noise limited scenarios. For interference limited environments, it turns out that approaches based on the mono interference cancellation (MIC) algorithm for single antenna interference cancellation (SAIC) are more favorable. It is shown that the standard MIC algorithm performs sufficiently well and could be used for a fast introduction of MUROS in existing GSM networks. For enhanced performance, a novel algorithm based on MIC along with successive interference cancellation is proposed. The presented results demonstrate that an even better performance as the GSM reference performance before introduction of SAIC can be obtained for MUROS if well-designed receivers are use

Electric vehicle charging stations with renewable power generators: A game theoretical analysis - Lee, Woongsup; Xiang, Lin; Schober, Robert; Wong, Vincent W. S. (IEEE Transactions on Smart Grid, 2015)
In this paper, we study the price competition among electric vehicle charging stations (EVCSs) with renewable power generators (RPGs). As electric vehicles (EVs) become more popular, a competition among EVCSs to attract EVs is inevitable. Thereby, each EVCS sets its electricity price to maximize its revenue by taking into account the competition with neighboring EVCSs. We analyze the competitive interactions between EVCSs using game theory, where relevant physical constraints such as the transmission line capacity, the distance between EV and EVCS, and the number of charging outlets at the EVCSs are taken into account. We show that the game played by EVCSs is a supermodular game and there exists a unique pure Nash equilibrium for best response algorithms with arbitrary initial policy. The electricity price and the revenue of EVCSs are evaluated via simulations, which reveal the benefits of having RPGs at the EVCSs.
CRIS-Team Scopus Importer:2020-01-31
Keywords: Electric vehicle (EV); electric vehicle charging station (EVCS); game theory; pricing; renewable power generation

Electric vehicle charging stations with renewable power generators: A game theoretical analysis - Lee, Woongsup; Xiang, Lin; Schober, Robert; Wong, Vincent W. S. (2015 IEEE Power & Energy Society General Meeting, 2015)
Summary form only given. In this paper, we study the price competition among electric vehicle charging stations (EVCSs) with renewable power generators (RPGs). As electric vehicles (EVs) become more popular, a competition among EVCSs to attract EVs is inevitable. Thereby, each EVCS sets its electricity price to maximize its revenue by taking into account the competition with neighboring EVCSs. We analyze the competitive interactions between EVCSs using game theory, where relevant physical constraints such as the transmission line capacity, the distance between EV and EVCS, and the number of charging outlets at the EVCSs are taken into account. We show that the game played by EVCSs is a supermodular game and there exists a unique pure Nash equilibrium for best response algorithms with arbitrary initial policy. The electricity price and the revenue of EVCSs are evaluated via simulations, which reveal the benefits of having RPGs at the EVCS

Enabling Secure Wireless Communications via Intelligent Reflecting Surfaces - Yu, Xianghao; Xu, Dongfang; Schober, Robert (2019 IEEE GLOBAL COMMUNICATIONS CONFERENCE (GLOBECOM), 2019)
CRIS-Team WoS Importer:2020-08-14

Energy-aware revenue optimization for cellular networks via device-to-device communication - Wu, Yuan; Wang, Jiaheng; Qian, Liping; Schober, Robert (2015 IEEE International Conference on Communications (ICC), 2015)
In this paper, we investigate the revenue optimization of a cellular system, which intelligently provides access services to device-to-device users (DUs) by reusing the resource-blocks (RBs) of cellular users (CUs). While charging the DUs for services, the cellular system compensates for the additional power consumption costs of the CUs to meet their required quality of service (QoS), and hence aims at achieving the best tradeoff between charging the DUs and affording the CUs' costs to maximize its own revenue. We formulate this energy-aware revenue optimization problem as a joint RB-reuse and power control problem, which we further decompose into a power control problem for each individual CU-DU pair and a DU-selection problem for selecting appropriate DUs to reuse the CUs' RBs. For each CU-DU pair, we derive the optimal power allocation in closed form and the maximum gain of the cellular system from this pair. Based on the gains of all CU-DU pairs, we then consider the DU-selection problem as maximum weighted matching on a bipartite graph and solve it by using linear relaxation. Numerical results validate our analysis regarding the optimal power allocation for each CU-DU pair and the BS's optimal selection of the DUs to reuse the CUs' RBs such that the BS's revenue is maximized.<br
Keywords: Throughput; Resource management; Power demand; Optimization; Wireless communication; Power control; Copper

Energy-Efficient 5G Outdoor-to-Indoor Communication: SUDAS Over Licensed and Unlicensed Spectrum - Wing Kwan Ng, Derrick; Breiling, Marco; Rohde, Christian; Burkhardt, Frank; Schober, Robert (IEEE Transactions on Wireless Communications, 2016)
In this paper, we study the design of the user selection, the time allocation to uplink and downlink, and the transceiver processing matrix for uplink and downlink multicarrier transmission employing a shared user equipment (UE)-side distributed antenna system (SUDAS). The proposed SUDAS simultaneously utilizes licensed frequency bands and unlicensed frequency bands with large available bandwidths (e.g. the millimeter wave bands) to enable a spatial multiplexing gain for single-antenna UEs to improve the energy efficiency and throughput of 5th generation (5G) outdoor-to-indoor communication. The resource allocation algorithm design is formulated as a nonconvex optimization problem for the maximization of the end-to-end system energy efficiency (bits/Joule). The nonconvex matrix optimization problem is converted to an equivalent nonconvex scalar optimization problem for multiple parallel channels, which is solved by an asymptotically globally optimal iterative algorithm. Besides, we propose a suboptimal algorithm, which finds a locally optimal solution of the nonconvex optimization problem. Simulation results illustrate that the proposed resource allocation algorithms for SUDAS achieve a significant performance gain in terms of system energy efficiency and spectral efficiency compared to conventional baseline systems by offering multiple parallel data streams for single-antenna UEs.<br
Keywords: Resource management; OFDM; Wireless communication; Bandwidth; MIMO; Uplink; Downlink

Energy-efficient power allocation for M2M communications with energy harvesting transmitter - Ng, Derrick Wing Kwan; Schober, Robert (2012 IEEE Globecom Workshops, GC Wkshps 2012, 2012)
In this paper, power allocation for energy-efficient point-to-point machine-to-machine (M2M) communication systems with multiple energy harvesting sources is studied. Under a deterministic system setting, we formulate the power allocation problem as a non-convex optimization problem over a finite horizon taking into account the circuit energy consumption, finite battery storage capacities, and a minimum required data rate. The considered non-convex optimization problem is transformed into a convex optimization problem by exploiting the properties of fractional programming which results in an efficient optimal off-line iterative power allocation algorithm. In each iteration, the transformed problem is solved by using dual decomposition and a recursive power allocation solution is obtained for maximization of the energy efficiency of data transmission (bit/Joule delivered to the receiver). © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Energy-efficient resource allocation for secure OFDMA systems - Ng, Derrick Wing Kwan; Lo, Ernest S.; Schober, Robert (IEEE Transactions on Vehicular Technology, 2012)
In this paper, resource allocation for energy-efficient secure communication in an orthogonal frequency-division multiple-access (OFDMA) downlink network is studied. The considered problem is modeled as a nonconvex optimization problem that takes into account the sum-rate-dependent circuit power consumption, multiple-antenna eavesdropper, artificial noise generation, and different quality-of-service (QoS) requirements, including a minimum required secrecy sum rate and a maximum tolerable secrecy outage probability. The power, secrecy data rate, and subcarrier allocation policies are optimized for maximization of the energy efficiency of secure data transmission (bit/joule securely delivered to the users). The considered nonconvex optimization problem is transformed into a convex optimization problem by exploiting the properties of fractional programming, which results in an efficient iterative resource allocation algorithm. In each iteration, the transformed problem is solved by using dual decomposition. Simulation results illustrate that the proposed iterative resource allocation algorithm not only converges in a small number of iterations but maximizes the system energy efficiency and guarantees a nonzero secrecy data rate for the desired users as well. In addition, the obtained results unveil a tradeoff between energy efficiency and secure communication. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Artificial noise generation; energy efficiency; green communications; multiple-input-multiple-output (MIMO) beamforming; passive eavesdropper; physical (PHY) layer security

Energy-Efficient Resource Allocation for Wireless Powered Communication Networks - Wu, Qingqing; Tao, Meixia; Ng, Derrick Wing Kwan; Chen, Wen; Schober, Robert (IEEE Transactions on Wireless Communications, 2016)
This paper considers a wireless powered communication network (WPCN), where multiple users harvest energy from a dedicated power station and then communicate with an information receiving station. Our goal is to investigate the maximum achievable energy efficiency (EE) of the network via joint time allocation and power control while taking into account the initial battery energy of each user. We first study the EE maximization problem in the WPCN without any system throughput requirement. We show that the EE maximization problem for the WPCN can be cast into EE maximization problems for two simplified networks via exploiting its special structure. For each problem, we derive the optimal solution and provide the corresponding physical interpretation, despite the nonconvexity of the problems. Subsequently, we study the EE maximization problem under a minimum system throughput constraint. Exploiting fractional programming theory, we transform the resulting nonconvex problem into a standard convex optimization problem. This allows us to characterize the optimal solution structure of joint time allocation and power control and to derive an efficient iterative algorithm for obtaining the optimal solution. Simulation results verify our theoretical findings and demonstrate the effectiveness of the proposed joint time and power optimization.
CRIS-Team Scopus Importer:2020-01-31
Keywords: Energy efficiency; power control; time allocation; wireless powered networks

Energy-efficient resource allocation in multi-cell OFDMA systems with limited backhaul capacity - Ng, Derrick Wing Kwan; Lo, Ernest S.; Schober, Robert (IEEE Wireless Communications and Networking Conference, WCNC, 2012)
In this paper, resource allocation for energy efficient communication in multi-cell orthogonal frequency division multiple access (OFDMA) downlink networks with cooperative base stations (BSs) is studied. The considered problem is formulated as a non-convex optimization problem which takes into account the circuit power consumption, the limited backhaul capacity, and the minimum required data rate for joint BS zero-forcing beamforming (ZFBF) transmission. By exploiting the properties of fractional programming, the considered non-convex optimization problem in fractional form is transformed into an equivalent optimization problem in subtractive form, which enables the derivation of an efficient iterative resource allocation algorithm. For each iteration, the optimal power allocation solution is derived with a low complexity suboptimal subcarrier allocation policy for maximization of the energy efficiency of data transmission (bit/Joule delivered to the users). Simulation results illustrate that the proposed iterative resource allocation algorithm converges in a small number of iterations, and unveil the trade-off between energy efficiency and network capacity. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Energy-efficient resource allocation in multi-cell OFDMA systems with limited backhaul capacity - Ng, Derrick Wing Kwan; Lo, Ernest S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2012)
We study resource allocation for energy-efficient communication in multi-cell orthogonal frequency division multiple access (OFDMA) downlink networks with cooperative base stations (BSs). We formulate the resource allocation problem for joint BS zero-forcing beamforming (ZFBF) transmission as a non-convex optimization problem which takes into account the circuit power consumption, the limited backhaul capacity, and the minimum required data rate. We transform the considered problem in fractional form into an equivalent optimization problem in subtractive form, which enables the derivation of an efficient iterative resource allocation algorithm. In each iteration, a low-complexity suboptimal semi-orthogonal user selection policy is computed. Besides, by using the concept of perturbation function, we show that in the considered systems under some general conditions, the duality gap with respect to the power optimization variables is zero despite the non-convexity of the primal problem. Thus, dual decomposition can be used in each iteration to derive an efficient closed-form power allocation solution for maximization of the energy efficiency of data transmission (bit/Joule delivered to the users). Simulation results illustrate that the proposed iterative resource allocation algorithm converges in a small number of iterations, and unveil the trade-off between energy efficiency, network capacity, and backhaul capacity: (1) In the low transmit power regime, an algorithm which achieves the maximum spectral efficiency may also achieve the maximum energy efficiency; (2) a high spectral efficiency does not necessarily result in a high energy efficiency; (3) spectral efficiency is always limited by the backhaul capacity; (4) energy efficiency increases with the backhaul capacity only until the maximum energy efficiency is achieved. © 2002-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Energy efficiency; green communication; limited backhaul; network MIMO; non-convex optimization; resource allocation

Energy-efficient resource allocation in multiuser OFDM systems with wireless information and power transfer - Ng, Derrick Wing Kwan; Lo, Ernest S.; Schober, Robert (IEEE Wireless Communications and Networking Conference, WCNC, 2013)
In this paper, we study the resource allocation algorithm design for multiuser orthogonal frequency division multiplexing (OFDM) downlink systems with simultaneous wireless information and power transfer. The algorithm design is formulated as a non-convex optimization problem for maximizing the energy efficiency of data transmission (bit/Joule delivered to the users). In particular, the problem formulation takes into account the minimum required system data rate, heterogeneous minimum required power transfers to the users, and the circuit power consumption. Subsequently, by exploiting the method of timesharing and the properties of nonlinear fractional programming, the considered non-convex optimization problem is solved using an efficient iterative resource allocation algorithm. For each iteration, the optimal power allocation and user selection solution are derived based on Lagrange dual decomposition. Simulation results illustrate that the proposed iterative resource allocation algorithm achieves the maximum energy efficiency of the system and reveal how energy efficiency, system capacity, and wireless power transfer benefit from the presence of multiple users in the system. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Energy-efficient resource allocation in OFDMA systems with hybrid energy harvesting base station - Ng, Derrick Wing Kwan; Lo, Ernest S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2013)
We study resource allocation algorithm design for energy-efficient communication in an orthogonal frequency division multiple access (OFDMA) downlink network with hybrid energy harvesting base station (BS). Specifically, an energy harvester and a constant energy source driven by a non-renewable resource are used for supplying the energy required for system operation. We first consider a deterministic offline system setting. In particular, assuming availability of non-causal knowledge about energy arrivals and channel gains, an offline resource allocation problem is formulated as a non-convex optimization problem over a finite horizon taking into account the circuit energy consumption, a finite energy storage capacity, and a minimum required data rate. We transform this non-convex optimization problem into a convex optimization problem by applying time-sharing and exploiting the properties of non-linear fractional programming which results in an efficient asymptotically optimal offline iterative resource allocation algorithm for a sufficiently large number of subcarriers. In each iteration, the transformed problem is solved by using Lagrange dual decomposition. The obtained resource allocation policy maximizes the weighted energy efficiency of data transmission (weighted bit/Joule delivered to the receiver). Subsequently, we focus on online algorithm design. A conventional stochastic dynamic programming approach is employed to obtain the optimal online resource allocation algorithm which entails a prohibitively high complexity. To strike a balance between system performance and computational complexity, we propose a low complexity suboptimal online iterative algorithm which is motivated by the offline algorithm. Simulation results illustrate that the proposed suboptimal online iterative resource allocation algorithm does not only converge in a small number of iterations, but also achieves a close-to-optimal system energy efficiency by utilizing only causal channel state and energy arrival information. © 2002-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Energy harvesting; green communication; non-convex optimization; resource allocation

Energy-efficient resource allocation in OFDMA systems with large numbers of base station antennas - Ng, Derrick Wing Kwan; Lo, Ernest S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2012)
In this paper, resource allocation for energy-efficient communication in an orthogonal frequency division multiple access (OFDMA) downlink network with a large number of transmit antennas is studied. The considered problem is modeled as a non-convex optimization problem which takes into account the circuit power consumption, imperfect channel state information at the transmitter (CSIT), and different quality of service (QoS) requirements including a minimum required data rate and a maximum tolerable channel outage probability. The power allocation, data rate adaptation, antenna allocation, and subcarrier allocation policies are optimized for maximization of the energy efficiency of data transmission (bit/Joule delivered to the users). By exploiting the properties of fractional programming, the resulting non-convex optimization problem in fractional form is transformed into an equivalent optimization problem in subtractive form, which leads to an efficient iterative resource allocation algorithm. In each iteration, the objective function is lower bounded by a concave function which can be maximized by using dual decomposition. Simulation results illustrate that the proposed iterative resource allocation algorithm converges in a small number of iterations and demonstrate the trade-off between energy efficiency and the number of transmit antennas. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Energy efficiency; green communication; large numbers of antennas; multiuser MIMO; resource allocation

Energy-efficient resource allocation in OFDMA systems with large numbers of base station antennas - Ng, Derrick Wing Kwan; Schober, Robert (IEEE International Conference on Communications, 2012)
In this paper, resource allocation for energy efficient communication in orthogonal frequency division multiple access (OFDMA) downlink networks with large numbers of base station (BS) antennas is studied. Assuming perfect channel state information at the transmitter (CSIT), the resource allocation algorithm design is modeled as a non-convex optimization problem for maximizing the energy efficiency of data transmission (bit/Joule delivered to the users), where the circuit power consumption and a minimum required data rate are taken into consideration. Subsequently, by exploiting the properties of fractional programming, an efficient iterative resource allocation algorithm is proposed to solve the problem. In particular, the power allocation, subcarrier allocation, and antenna allocation policies for each iteration are derived. Simulation results illustrate that the proposed iterative resource allocation algorithm converges in a small number of iterations and unveil the trade-off between energy efficiency and the number of antennas. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Energy-efficient transmission for wireless powered multiuser communication networks - Wu, Qingqing; Tao, Meixia; Ng, Derrick Wing Kwan; Chen, Wen; Schober, Robert (IEEE International Conference on Communications, 2015)
This paper considers wireless powered communication networks (WPCN). Our goal is to investigate the maximum network energy efficiency (EE) by joint time allocation and power control while taking account the initial battery energy level of each user. It is shown that the EE maximization problem for the WPCN can be cast into the EE maximization problems for two independent networks, i.e., purely wireless powered communication networks (PWPCN) or initial energy limited communication networks (IELCN). For the PWPCN, we find that: 1) in the wireless energy transfer (WET) stage, the power station always transmits with its maximum power; 2) it is not necessary for all users to transmit signals in the wireless information transmission (WIT) stage, but all scheduled users will deplete all of their energy; 3) the maximum system EE can always be achieved by exhausting all the available time. Based on these observations, we derive a closed-form expression for the system EE based on the user EE, which transforms the original problem into a user scheduling problem that can be solved efficiently. While for the IELCN, we reveal that the most energy-efficient transmission strategy is to only schedule the user who has the highest user EE. Simulation results validate our theoretical findings and demonstrate the effectiveness of the proposed scheme.
CRIS-Team Scopus Importer:2020-01-31

Enhanced MRC for decode-and-forward cooperative diversity systems - Nasri, Amir; Schober, Robert; Uysal, Murat (IEEE Transactions on Wireless Communications, 2012)
In this letter, we propose a novel enhanced maximalratio combining (EMRC) scheme for multibranch decodeandforward (DF) cooperative diversity systems consisting of a source, a destination, and multiple relays. This scheme employs adjustable parameters at the relays and the destination which enable this scheme to appropriately adapt to variations in the sourcerelay and relaydestination channel gains. For the proposed EMRC scheme, we analyze the asymptotic error rate performance for high signaltonoise ratios and Rayleigh fading. Based on the obtained analytical expressions, we find the optimal parameters that lead to minimization of the asymptotic error rate. Furthermore, we compare the error rate performance as well as the feedback overhead of EMRC with those of important DF schemes, namely, cooperative MRC (CMRC) and two DF schemes based on the link adaptive regeneration (LAR) concept, namely, LARα inst and LAR. We show that although the feedback requirements of EMRC are similar to those of LAR, EMRC achieves a performance similar to that of LARα inst, which has a substantially higher feedback overhead. © 2002-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Cooperative diversity; cooperative maximal - ratio combining; decode - and - forward; link adaptive regeneration; performance analysis and optimization

Enhancement of the ECMA-368 UWB system by means of compatible relaying techniques - Kan, Jimmy; Mietzner, Jan; Snow, Chris; Schober, Robert (Proceeedings of The 2008 IEEE International Conference on Ultra-Wideband, ICUWB 2008, 2008)
We assess the benefits of relaying techniques with regard to the performance of ECMA-368 ultra wideband radio systems. To this end, we closely follow the current ECMA-368 standard and adopt the IEEE 802.15.3a channel models. Focus is on compatible relaying techniques that require a minimum of change to the current system specifications. In particular, we consider decode-and-forward (D&F) and amplify-and-forward (A&F) relaying and combine these techniques with a distributed version of cyclic delay diversity (CDD) performed across relays. Our results show that, as long as the relays are located sufficiently close to the source node, both D&F and A&F relaying achieve significant performance gains over direct transmission, even in the case of correlated shadowing. Furthermore, we find that the distributed CDD scheme yields little improvements compared to simple A&F and D&F relaying, since the employed channel coding scheme already picks up a large amount microscopic diversity. ©2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Equalization Concepts for EDGE - Gerstacker, Wolfgang; Schober, Robert (IEEE Transactions on Wireless Communications, 2002)
In this paper, an equalization concept for the novel radio access scheme Enhanced Data rates for GSM Evolution (EDGE) is proposed by which high performance can be obtained at moderate computational complexity. Because high-level modulation is employed in EDGE, optimum equalization as usually performed in Global System for Mobile Communications (GSM) receivers is too complex and suboptimum schemes have to be considered. It is shown that delayed decision-feedback sequence estimation (DDFSE) and reduced-state sequence estimation (RSSE) are promising candidates. For various channel profiles, approximations for the bit error rate of these suboptimum equalization techniques are given and compared with simulation results for DDFSE. It turns out that a discrete-time prefilter creating a minimum-phase overall impulse response is indispensible for a favorable tradeoff between performance and complexity. Additionally, the influence of channel estimation and of the receiver input filter is investigated and the reasons for performance degradation compared to the additive white Gaussian noise channel are indicated. Finally, the overall system performance attainable with the proposed equalization concept is determined for transmission with channel coding. © 2002 IEEE.
UnivIS-Import:2015-03-09:Pub.2002.tech.IE.mobilk.equali
Keywords: EDGE; Equalization; Mobile communications; Reduced-state trellis-based equalizers

Equalization for WLAN IEEE 802.11b - Gerstacker, Wolfgang; Jonietz, Christof; Schober, Robert (Conference Proceedings, 2004)
In this paper, complementary code keying (CCK) transmission over frequency-selective fading channels is investigated. Since CCK can be interpreted as a block code, an appropriate vector signal model is introduced. Based on pairwise error probabilities, we derive a performance approximation for optimum detection in general frequency-selective Ricean fading channels and compare the theoretical results with simulations. Because optimum maximum-likelihood sequence estimation (MLSE) is not practical for large channel delay spreads, minimum mean-squared error decision-feedback equalization (MMSE-DFE) is employed. Two different DFE approaches are considered here: (a) the conventional scalar DFE and (b) a block-based DFE optimized for the underlying vector signal model. Furthermore, a reduced-state sequence estimation (RSSE) algorithm is designed for CCK. Numerical results are given for fixed channels and common indoor fading channel profiles.
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.mobilk.equali
Keywords: Wireless LAN; Decision feedback Equalizers; Maximum likelihood estimation; Delay estimation; Frequency-selective fading channels; Block codes; Pairwise error probability; Frequency; Maximum likelihood detection; Algorithm design and analysis

Ergodic Sum Rate Analysis of UAV-Based Relay Networks With Mixed RF-FSO Channels - Ajam, Hedieh; Najafi, Marzieh; Jamali, Vahid; Schober, Robert (IEEE Open Journal of the Communications Society, 2020)
Unmanned aerial vehicle (UAV)-based communications is a promising new technology that can add a wide range of new capabilities to the current network infrastructure. Given the flexibility, cost-efficiency, and convenient use of UAVs, they can be deployed as temporary base stations (BSs) for on-demand situations like BS overloading or natural disasters. In this work, a UAV-based communication system with radio frequency (RF) access links to the mobile users (MUs) and a free-space optical (FSO) backhaul link to the ground station (GS) is considered. In particular, the RF and FSO channels in this network depend on the UAV's positioning and (in)stability. The relative position of the UAV with respect to the MUs impacts the likelihood of a line-of-sight (LOS) connection in the RF link and the instability of the hovering UAV affects the quality of the FSO channel. Thus, taking these effects into account, we analyze the end-to-end system performance of networks employing UAVs as buffer-aided (BA) and non-buffer-aided (non-BA) relays in terms of the ergodic sum rate. Simulation results validate the accuracy of the proposed analytical derivations and reveal the benefits of buffering for compensation of the random fluctuations caused by the UAV's instability. Our simulations also show that the ergodic sum rate of both BA and non-BA UAV-based relays can be enhanced considerably by optimizing the positioning of the UAV. We further study the impact of the MU density and the weather conditions on the end-to-end system performance.
CRIS-Team WoS Importer:2021-12-24

Error rate performance of network-coded cooperative diversity systems - Nasri, Amir; Schober, Robert; Uysal, Murat (GLOBECOM - IEEE Global Telecommunications Conference, 2010)
In this paper, we study network-coded cooperative diversity (NCCD) systems comprising multiple sources, one relay, and one destination. The relay detects the packets received from all sources and performs Galois field network coding. We propose a simple cooperative maximum-ratio combining scheme for the destination which is shown to achieve the maximum diversity gain of the system. Furthermore, we provide a mathematical framework for the asymptotic analysis of NCCD systems with M-ary modulation for high signal-to-noise ratios. Based on this framework, we derive simple and elegant closed-form expressions for the asymptotic symbol and bit error rates which provide significant insight into the impact of various system and channel parameters on performance and can be exploited for performance optimization. Simulation results confirm the accuracy of the presented analysis and show that large performance gains are possible by optimizing the power allocation in NCCD systems based on the developed analytical results. ©2010 Crown.
CRIS-Team Scopus Importer:2020-02-03

Evolution of NOMA Toward Next Generation Multiple Access (NGMA) for 6G - Liu, Yuanwei; Zhang, Shuowen; Mu, Xidong; Ding, Zhiguo; Schober, Robert; Al-Dhahir, Naofal; Hossain, Ekram; Shen, Xuemin (IEEE Journal on Selected Areas in Communications, 2022)
Due to the explosive growth in the number of wireless devices and diverse wireless services, such as virtual/augmented reality and Internet-of-Everything, next generation wireless networks face unprecedented challenges caused by heterogeneous data traffic, massive connectivity, and ultra-high bandwidth efficiency and ultra-low latency requirements. To address these challenges, advanced multiple access schemes are expected to be developed, namely next generation multiple access (NGMA), which are capable of supporting massive numbers of users in a more resource- and complexity-efficient manner than existing multiple access schemes. As the research on NGMA is in a very early stage, in this paper, we explore the evolution of NGMA with a particular focus on non-orthogonal multiple access (NOMA), i.e., the transition from NOMA to NGMA. In particular, we first review the fundamental capacity limits of NOMA, elaborate on the new requirements for NGMA, and discuss several possible candidate techniques. Moreover, given the high compatibility and flexibility of NOMA, we provide an overview of current research efforts on multi-antenna techniques for NOMA, promising future application scenarios of NOMA, and the interplay between NOMA and other emerging physical layer techniques. Furthermore, we discuss advanced mathematical tools for facilitating the design of NOMA communication systems, including conventional optimization approaches and new machine learning techniques. Next, we propose a unified framework for NGMA based on multiple antennas and NOMA, where both downlink and uplink transmissions are considered, thus setting the foundation for this emerging research area. Finally, several practical implementation challenges for NGMA are highlighted as motivation for future work.
CRIS-Team Scopus Importer:2022-03-25
Keywords: 6G; 6G mobile communication; Interference; machine learning; mathematical optimization; MIMO communication; multi-antenna techniques; next generation multiple access (NGMA); Next generation networking; NOMA; non-orthogonal multiple access (NOMA); Silicon carbide; Time division multiple access

Experimental Molecular Communication Testbed Based on Magnetic Nanoparticles in Duct Flow - Unterweger, Harald; Kirchner, Jens; Wicke, Wayan; Ahmadzadeh, Arman; Ahmed, Doaa; Jamali Kooshkghazi, Vahid; Alexiou, Christoph; Fischer, Georg; Weigel, Robert; Schober, Robert (19th IEEE International Workshop on Signal Processing Advances in Wireless Communications, 2018)
Simple and easy to implement testbeds are needed to further advance molecular communication research. To this end, this paper presents an in-vessel molecular communication testbed using magnetic nanoparticles dispersed in an aqueous suspension as they are also used for drug targeting in biotechnology. The transmitter is realized by an electronic pump for injection via a Yconnector. A second pump provides a background flow for signal propagation. For signal reception, we employ a susceptometer, an electronic device including a coil, where the magnetic particles move through and generate an electrical signal. We present experimental results for the transmission of a binary sequence and the system response following a single injection. For this flowdriven particle transport, we propose a simple parameterized mathematical model for evaluating the system response. <br
Keywords: Molecular communication; magnetic nanoparticles

Experimental Molecular Communication Testbed Based on Magnetic Nanoparticles in Duct Flow - Unterweger, Harald; Kirchner, Jens; Wicke, Wayan; Ahmadzadeh, Arman; Ahmed, Doaa; Jamali, Vahid; Alexiou, Christoph; Fischer, Georg; Schober, Robert (2018 IEEE 19th International Workshop on Signal Processing Advances in Wireless Communications (SPAWC), 2018)
Simple and easy to implement testbeds are needed to further advance molecular communication research. To this end, this paper presents an in-vessel molecular communication testbed using magnetic nanoparticles dispersed in an aqueous suspension as they are also used for drug targeting in biotechnology. The transmitter is realized by an electronic pump for injection via a Y-connector. A second pump provides a background flow for signal propagation. For signal reception, we employ a susceptometer, an electronic device including a coil, where the magnetic particles move through and generate an electrical signal. We present experimental results for the transmission of a binary sequence and the system response following a single injection. For this flow-driven particle transport, we propose a simple parameterized mathematical model for evaluating the system Response.<br
Keywords: Electron tubes; Magnetic nanoparticles; Receivers; Molecular communication; Suspensions; Magnetic susceptibility; Transmitters

Experimental Research in Synthetic Molecular Communications - Part I - Lotter, Sebastian; Brand, Lukas; Jamali, Vahid; Schäfer, Maximilian; Loos, Helene; Unterweger, Harald; Greiner, Sandra; Kirchner, Jens; Alexiou, Christoph; Drummer, Dietmar; Fischer, Georg; Büttner, Andrea; et al. (IEEE Nanotechnology Magazine, 2023)
Since its emergence from the communication engineering community around one and a half decades ago, the field of Synthetic Molecular Communication (SMC) has experienced continued growth, both in the number of technical contributions from a vibrant community and in terms of research funding. Throughout this process, the vision of SMC as a novel, revolutionary communication paradigm has constantly evolved, driven by feedback from theoretical and experimental studies, respectively. It is believed that especially the latter ones will be crucial for the transition of SMC towards a higher technology readiness level in the near future. In this spirit, we present here a comprehensive survey of experimental research in SMC. In particular, this survey focuses on highlighting the major drivers behind different lines of experimental research in terms of the respective envisioned applications. This approach allows us to categorize existing works and identify current research gaps that still hinder the development of practical SMC-based applications. Our survey consists of two parts: this paper and a companion paper. While the companion paper focuses on SMC with relatively long communication ranges, this paper covers SMC over short distances of typically not more than a few millimeters.<br

Experimental Research in Synthetic Molecular Communications - Part II - Lotter, Sebastian; Brand, Lukas; Jamali, Vahid; Schäfer, Maximilian; Loos, Helene M.; Unterweger, Harald; Greiner, Sandra; Kirchner, Jens; Alexiou, Christoph; Drummer, Dietmar; Fischer, Georg; Buettner, Andrea; et al. (IEEE Nanotechnology Magazine, 2023)
In this second part of our survey on experimental research in Synthetic Molecular Communication (SMC), we review works on long-range SMC systems, i.e., systems with communication ranges of more than a few millimeters. Despite the importance of experimental research for the evolution of SMC towards a mature communication paradigm that will eventually support revolutionary applications beyond the reach of today’s prevalent communication paradigms, the existing body of literature is still comparatively sparse. Long-range SMC systems have been proposed in the literature for information transmission in two types of fluid media, liquid and air. While both types of SMC systems, i.e., liquid-based and air-based systems, rely on encoding and transmitting information using molecules, they differ substantially in terms of the physical system designs and in the type of applications they are intended for. In this article, we present a systematic characterization of experimental works on long-range SMC that reveals the major drivers of these works in terms of the respective target applications. Furthermore, the physical designs for long-range SMC proposed in the literature are comprehensively reviewed. In this way, our survey will contribute to making experimental research in this field more accessible and identifying novel directions for future research.
CRIS-Team Scopus Importer:2023-05-05
Keywords: Copper; Detectors; Fluorescence; Ions; Liquids; Pipelines; Prototypes

Experimental System for Molecular Communication in Pipe Flow With Magnetic Nanoparticles - Wicke, Wayan; Unterweger, Harald; Kirchner, Jens; Brand, Lukas; Ahmadzadeh, Arman; Ahmed, Doaa; Jamali, Vahid; Alexiou, Christoph; Fischer, Georg; Schober, Robert (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2021)
In the emerging field of molecular communication (MC), testbeds are needed to validate theoretical concepts, motivate applications, and guide further modeling efforts. To this end, this paper presents a flexible and extendable in-vessel testbed for flow-based macroscopic MC, abstractly modeling, e.g., a part of a chemical reactor or a blood vessel. Signaling is based on injecting non-reactive superparamagnetic iron oxide nanoparticles (SPIONs) dispersed in an aqueous suspension into a tube with background flow. A commercial magnetic susceptometer is used for non-intrusive downstream signal reception. To shed light on the operation of the testbed, we identify the physical mechanisms governing the transmission, propagation, and reception of the information-carrying SPIONs. Moreover, to facilitate system design, we propose a closed-form parametric expression for the end-to-end channel impulse response (CIR). The proposed CIR model is shown to consistently capture the experimentally observed distance-dependent impulse response peak heights and peak decays for transmission distances from 540. Moreover, to validate our testbed, reliable communication is demonstrated based on experimental data for model-agnostic and model-based detection methods.
Created from Fastlane, Scopus look-up
Keywords: Biology; Chemicals; Coatings; Electron tubes; Experimental system; fluid flow; injection; Iron; magnetic nanoparticles; Magnetic nanoparticles; Magnetic susceptibility; molecular communication; SPIONs; testbed.

Fast multiple-symbol detection for free-space optical communications - Riediger, Michael L. B.; Schober, Robert; Lampe, Lutz (IEEE Transactions on Communications, 2009)
In this paper, we investigate noncoherent detection, i.e. detection assuming the absence of channel state information at the receiver, of on-ff keying in an intensity modulation and direct detection (IM/DD) free-space optical (FSO) system. To partially recover the performance loss associated with symbol- by-symbol noncoherent detection, we consider the application of multiple-symbol detection (MSD), in which block-wise decisions are made using an observation window of several bit intervals. Specifically, we develop a fast search algorithm for optimal MSD and propose a reduced-complexity decision metric suitable for suboptimal MSD; performance results confirm that the optimal and suboptimal metrics perform comparably well. Significantly, the complexity of our receiver, on a per bit-decision basis, is only logarithmically dependent on the observation window size. We also present the framework for a decision-feedback receiver and obtain performance expressions for the ideal case of error-free feedback; these expressions serve as an upper bound to the performance of MSD. Analytical and simulation results indicate that as the observation window size increases, the performance of the MSD receiver approaches that of detection with channel state information. The conclusion is reached that the proposed implementation provides an attractive low-complexity mechanism for performing noncoherent MSD in FSO systems. © 2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Atmospheric turbulence; Decision-feedback; Free-space optical communication; Multiple-symbol detection; Noncoherent detection

Feedback-Aware Precoding for Millimeter Wave Massive MIMO Systems - Ghanaatian, Reza; Jamali, Vahid; Burg, Andreas; Schober, Robert (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC, 2019)
Millimeter wave (mmWave) communication is a promising solution for coping with the ever-increasing mobile data traffic because of its large bandwidth. To enable a suffi-cient link margin, a large antenna array employing directional beamforming, which is enabled by the availability of channel state information at the transmitter (CSIT), is required. However, CSIT acquisition for mmWave channels introduces a huge feedback overhead due to the typically large number of transmit and receive antennas. Leveraging properties of mmWave channels, this paper proposes a precoding strategy which enables a flexible adjustment of the feedback overhead. In particular, the optimal unconstrained precoder is approximated by selecting a variable number of elements from a basis that is constructed as a function of the transmitter array response, where the number of selected basis elements can be chosen according to the feedback constraint. Simulation results show that the proposed precoding scheme can provide a near-optimal solution if a higher feedback overhead can be afforded. For a low overhead, it can still provide a good approximation of the optimal precoder.
CRIS-Team Scopus Importer:2020-01-31

Finite-SNR diversity-multiplexing tradeoff in bidirectional cooperative networks - Yi, Zhihang; Kim, Il Min; Schober, Robert (IEEE International Conference on Communications, 2010)
Analog network coding (ANC) and time division broadcasting (TDBC) are two major protocols used in bidirectional cooperative networks with half-duplex terminals. Most previous work on those two protocols was based on the assumption that there was no direct channel between the two sources. In this paper, we remove this limitation and investigate both protocols in a general bidirectional cooperative network with a direct channel between the two sources. Lower bounds on the outage probabilities of the two protocols are derived first. These lower bounds are very close to the exact outage probabilities in the whole signal-to-noise ratio (SNR) range irrespective of the values of channel variances. Based on the lower bounds, the finite-SNR diversity-multiplexing tradeoffs (DMTs) of the ANC and TDBC protocols are obtained. These tradeoffs establish a framework which enables us to make a comprehensive comparison between both protocols. ©2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Firefly Ultra Dense Networks with mmWave Fronthaul Links - Ackermann, Katharina; Jamali, Vahid; Gerstacker, Wolfgang; Wartenberg, Fredrik; Aulin, Jocelyn; Krishnan, Rajet; Schober, Robert (2018 IEEE GLOBECOM WORKSHOPS (GC WKSHPS), 2018)
CRIS-Team WoS Importer:2019-04-16

Fixed gain amplify-and-forward relaying with co-channel interference - Suraweera, Himal A.; Michalopoulos, Diomidis S.; Schober, Robert; Karagiannidis, George K.; Nallanathan, Arumugam (IEEE International Conference on Communications, 2011)
We investigate the outage probability and the average bit error rate (BER) of a dual-hop fixed gain relaying system in the presence of co-channel interference and thermal noise at the relay and the destination. Our analysis assumes Rayleigh fading for the source-relay and relay-destination channels and Rician fading for the interfering channels. We present new closed-form/series expressions for the outage probability and the average BER. The achievable diversity order is also studied. It is further shown through numerical results that the Rician K-factor of the interfering channel has a negative effect on the overall outage probability and BER, yet this effect is very small. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Fractionally Spaced Equalization and Decision Feedback Sequence Detection for Diffusive MC - Cao, Trang Ngoc; Jamali, Vahid; Zlatanov, Nikola; Yeoh, Phee Lep; Evans, Jamie; Schober, Robert (IEEE Communications Letters, 2021)
In this letter, we consider diffusive molecular communication (MC) systems affected by signal-dependent diffusive noise, inter-symbol interference, and external noise. We design linear and nonlinear fractionally-spaced equalization schemes and a detection scheme which combines decision feedback and sequence detection (DFSD). In contrast to the symbol-rate equalization schemes in the MC literature, the proposed equalization and detection schemes exploit multiple samples of the received signal per symbol interval to achieve lower bit error rates (BERs) than existing schemes. The proposed DFSD scheme achieves a BER which is very close to that achieved by maximum likelihood sequence detection, but with lower computational complexity.
CRIS-Team Scopus Importer:2021-01-22
Keywords: equalization; sequence detection; Signal-dependent noise

Fundamentals of Signal Design for WPT and SWIPT - Wing Kwan Ng, Derrick; Duong, Trung Q.; Zhong, Caijun; Schober, Robert (Wireless Information and Power Transfer: Theory and Practice, 2019)
Standardized wireless communication systems based on radio frequency (RF) radiation are one of the important technologies in the modern societies. The emergence of low‐power autonomous wireless devices, such as ubiquitous sensing through wireless sensor networks (WSN) or an Internet‐of‐Things (IoT), has made the powering of such devices another challenge for the next generation 5G mobile networks. This chapter provides an overview of a wireless power transfer (WPT) architecture and the latest advances in the field of signal design for WPT and sequence wireless information power transfer (SWIPT). In order to demonstrate the feasibility of the proposed signal and system designs for WPT, prototyping and experimentation are required. Utilizing the WPT waveform designs shows that the rectifier nonlinearity has a significant impact on the performance of a SWIPT system.<br
Keywords: Wireless communication; Radio frequency; Rectennas; Wireless sensor Networks; Transmitters; Receivers; Signal design

Fundamentals of Wireless Information and Power Transfer: From RF Energy Harvester Models to Signal and System Designs - Clerckx, Bruno; Zhang, Rui; Schober, Robert; Wing Kwan Ng, Derrick; Kim, Dong In; Poor, H. Vincent (IEEE Journal on Selected Areas in Communications, 2018)
Radio waves carry both energy and information simultaneously. Nevertheless, radio-frequency (RF) transmissions of these quantities have traditionally been treated separately. Currently, the community is experiencing a paradigm shift in wireless network design, namely, unifying wireless transmission of information and power so as to make the best use of the RF spectrum and radiation as well as the network infrastructure for the dual purpose of communicating and energizing. In this paper, we review and discuss recent progress in laying the foundations of the envisioned dual purpose networks by establishing a signal theory and design for wireless information and power transmission (WIPT) and identifying the fundamental tradeoff between conveying information and power wirelessly. We start with an overview of WIPT challenges and technologies, namely, simultaneous WIPT (SWIPT), wirelessly powered communication networks (WPCNs), and wirelessly powered backscatter communication (WPBC). We then characterize energy harvesters and show how WIPT signal and system designs crucially revolve around the underlying energy harvester model. To that end, we highlight three different energy harvester models, namely, one linear model and two nonlinear models, and show how WIPT designs differ for each of them in single-user and multi-user deployments. Topics discussed include rate-energy region characterization, transmitter and receiver architectures, waveform design, modulation, beamforming and input distribution optimizations, resource allocation, and RF spectrum use. We discuss and check the validity of the different energy harvester models and the resulting signal theory and design based on circuit simulations, prototyping, and experimentation. We also point out numerous directions that are promising for future research.<br
Keywords: Radio frequency; System analysis and design; Receivers; Wireless Networks; Electronic mail; Backscatter

Generalized Wireless-Powered Communications: When to Activate Wireless Power Transfer? - Wu, Qingqing; Zhang, Guangchi; Ng, Denick Wing Kwan; Chen, Wen; Schober, Robert (IEEE Transactions on Vehicular Technology, 2019)
Wireless-powered communication network (WPCN) is a key technology to power energy limited massive devices, such as on-board wireless sensors in autonomous vehicles, for Internet-of-Things applications. Conventional WPCNs rely only on dedicated downlink wireless power transfer (WPT), which is practically inefficient due to the significant energy loss in wireless signal propagation. Meanwhile, ambient energy harvesting is highly appealing as devices can scavenge energy from various existing energy sources (e.g., solar energy and cellular signals). Unfortunately, the randomness of the availability of these energy sources cannot guarantee stable communication services. Motivated by the above statements, we consider a generalized WPCN where the devices can not only harvest energy from a dedicated multiple-antenna power station (PS), but can also exploit stored energy stemming from ambient energy harvesting. Since the dedicated WPT consumes system resources, if the stored energy is sufficient, WPT may not be needed to maximize the weighted sum rate. To analytically characterize this phenomenon, we derive the condition for WPT activation and reveal how it is affected by the different system parameters. Subsequently, we further derive the optimal resource allocation policy for the cases that WPT is activated and deactivated, respectively. In particular, it is found that when WPT is activated, the optimal energy beamforming at the PS does not depend on the devices' stored energy, which is shown to lead to a new unfairness issue. Simulation results verify our theoretical findings and demonstrate the effectiveness of the proposed optimal resource allocation.
CRIS-Team WoS Importer:2019-09-10

Geometric aspects of efficient cooperation - Michalopoulos, Diomidis S.; Schober, Robert (2015 IEEE International Conference on Communication Workshop (ICCW), 2015)
By appropriately selecting their relaying partners, wireless users are able to reduce their average transmit power without any performance cost. This important feature of cooperation is captured by the notion of relaying efficiency: A relaying partner is considered efficient for a given user if it can decrease the overall transmit power for achieving a certain signal-to-noise ratio (SNR) associated with that user. In this work, a two-dimensional geometric investigation of efficient cooperation is conducted. It is shown that the locus of efficient partner locations can be approximated by an ellipse, which is centred at the midpoint of the user and the base station, and has an eccentricity which depends on the path loss exponent. Moreover, the efficiency of the relaying partners is illustrated via contour graphs, which provide a graphical assessment of the energy efficiency potential of cooperation based on partner location. The cases of fading-free transmissions and transmission over Rayleigh fading channels are examined.<br
Keywords: Wireless communication; Integrated circuits

Globally Optimal Resource Allocation Design for IRS-Assisted Multiuser Networks with Discrete Phase Shifts - Wu, Yifei; Xu, Dongfang; Ng, Derrick Wing Kwan; Schober, Robert; Gerstacker, Wolfgang (2023 IEEE International Conference on Communications Workshops: Sustainable Communications for Renaissance, ICC Workshops 2023, 2023)
Intelligent reflecting surfaces (IRSs) are envisioned as a low-cost solution to achieve high spectral and energy efficiency in future communication systems due to their ability to customize wireless propagation environments. Although resource allocation design for IRS-assisted multiuser wireless communication systems has been exhaustively investigated in the literature, the optimal design and performance of such systems are still not well understood. To fill this gap, in this paper, we study optimal resource allocation for IRS-assisted multiuser multiple-input single-output (MISO) systems. In particular, we jointly optimize the beamforming at the base station (BS) and the discrete IRS phase shifts to minimize the total transmit power. For attaining the globally optimal solution of the formulated non-convex combinatorial optimization problem, we develop a resource allocation algorithm with guaranteed convergence based on Schur's complement and the generalized Bender's decomposition. Our numerical results reveal that the proposed algorithm can significantly reduce the BS transmit power compared to the state-of-the-art suboptimal alternating optimization-based approach, especially for moderate-to-large numbers of IRS elements.
CRIS-Team Scopus Importer:2023-12-08

GSM/EDGE: A mobile communications system determined to stay - Gerstacker, Wolfgang; Schober, Robert; Meyer, Raimund; Obernosterer, Frank; Ruder, Michael; Kalveram, Hans (AEÜ - International Journal of Electronics and Communications, 2011)
The Global System for Mobile Communications (GSM) is still the most successful mobile communications system worldwide. During the last decade, major steps have been taken towards an improvement of GSM with respect to performance and spectral efficiency. To serve the increasing demands of more and more users for higher data rates, significant efforts are made towards a further evolution of GSM. The standard extension Voice Services over Adaptive Multi-User Channels (VAMOS) has been specified in 3GPP Release 9. In VAMOS mode, two overlaid Gaussian minimum-shift keying (GMSK) signals are transmitted in the same time slot and frequency channel, potentially doubling the capacity of existing GSM networks in many cases. In this paper, we address channel estimation and detection techniques for the VAMOS downlink. In a new 3GPP work item called TIGHTER, it is also foreseen to tighten all downlink receiver performance requirements for all data and voice services by at least 2 dB through the application of more sophisticated processing techniques at the receiver. Furthermore, a 3GPP study on Signal Precoding Enhancements for EGPRS2 (SPEED) to further modify the modulation and coding for data services by introducing OFDM has been started recently. We present ideas for improved receivers to enable tighter performance requirements and for SPEED transmission concepts, which might merit further investigation. © 2011 Elsevier GmbH. All rights reserved.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Decoding; Equalization; GSM/EDGE; OFDM; SAIC; VAMOS

Guest Editorial - Dai, Linglong; Ding, Zhiguo; Al-Dhahir, Naofal; Chih-Lin, I.; Karagiannidis, George K.; Krikidis, Ioannis; Schober, Robert (IEEE Wireless Communications, 2018)
CRIS-Team Scopus Importer:2020-01-31

Guest editorial: Large-scale multiple antenna wireless systems - Matthaiou, Michail; Karagiannidis, George K.; Larsson, Erik G.; Marzetta, Thomas L.; Schober, Robert (IEEE Journal on Selected Areas in Communications, 2013)
CRIS-Team Scopus Importer:2020-02-03

Guest Editorial Massive Access for 5G and beyond - Part I - Chen, Xiaoming; Ng, Derrick Wing Kwan; Yu, Wei; Larsson, Erik G.; Al-Dhahir, Naofal; Schober, Robert (IEEE Journal on Selected Areas in Communications, 2021)
CRIS-Team Scopus Importer:2021-03-19

Guest editorial optical wireless communications - Karagiannidis, George K.; Arnon, Shlomi; Barry, John R.; Schober, Robert; Uysal, Murat (IEEE Journal on Selected Areas in Communications, 2009)
CRIS-Team Scopus Importer:2020-02-03

Guest editorial special issue on cognitive sensor networks - Mukhopadhyay, Subhas Chandra; Varshney, Pramod Kumar; Leung, Henry; Schober, Robert (IEEE Sensors Journal, 2011)
CRIS-Team Scopus Importer:2020-02-03

Guest Editorial Special Issue on "Edge-Based Wireless Communications Technologies to Counter Communicable Infectious Diseases" - Balasubramaniam, Sasitharan; Schober, Robert; Pierobon, Massimiliano; Misra, Sudip; Thomas, Peter (IEEE Journal on Selected Areas in Communications, 2022)
CRIS-Team WoS Importer:2022-11-25

Guest Editorial Special Issue on Next Generation Multiple Access-Part II - Liu, Yuanwei; Zhang, Shuowen; Ding, Zhiguo; Schober, Robert; Al-Dhahir, Naofal; Hossain, Ekram; Shen, Xuemin (IEEE Journal on Selected Areas in Communications, 2022)
CRIS-Team WoS Importer:2022-04-29

Guest Editorial Special Issue on UAV Communications in 5G and beyond Networks - Part II - Wu, Qingqing; Xu, Jie; Zeng, Yong; Kwan Ng, Derrick Wing; Al-Dhahir, Naofal; Schober, Robert; Swindlehurst, A. Lee (IEEE Journal on Selected Areas in Communications, 2021)
CRIS-Team Scopus Importer:2021-10-29

Guest Editorial Wireless Transmission of Information and Power—Part I - Clerckx, Bruno; Zhang, Rui; Schober, Robert; Ng, Derrick Wing Kwan; Kim, Dong In; Poor, H. Vincent (IEEE Journal on Selected Areas in Communications, 2018)
Wireless transmission of information and power has received growing attention in the research community in the past few years. In two consecutive special issues, a total of thirty papers present state-of-the-art results in the broad area of wireless transmission of information and power.<br
Keywords: Special issues and sections; Wireless communication; Wireless power Transfer; Wireless Networks; Data transfer

Guest editorial wireless transmission of information and power - Part i - Clerckx, Bruno; Zhang, Rui; Schober, Robert; Ng, Derrick Wing Kwan; Kim, Dong In; Poor, H. Vincent (IEEE Journal on Selected Areas in Communications, 2019)
CRIS-Team Scopus Importer:2019-05-28

Guest Editorial Wireless Transmission of Information and Power—Part II - Clerckx, Bruno; Zhang, Rui; Schober, Robert; Ng, Derrick Wing Kwan; Kim, Dong In; Poor, H. Vincent (IEEE Journal on Selected Areas in Communications, 2019)
This second of the two issues on wireless transmission of information and power starts with some works on Simultaneous Wireless Information and Power Transfer (SWIPT), then switches to Wirelessly Powered Communication Networks (WPCNs), and finishes with a few works on Wirelessly Powered Backscatter Communication (WPBC).<br
Keywords: Special issues and sections; Wireless communication; Wireless power Transfer; Wireless sensor networks

Guest Editorial xURLLC in 6G: Next Generation Ultra-Reliable and Low-Latency Communications - She, Changyang; Pan, Cunhua; Duong, Trung Q.; Quek, Tony Q.S.; Schober, Robert; Simsek, Meryem; Zhu, Peiying (IEEE Journal on Selected Areas in Communications, 2023)
AS ONE of the new communication scenarios in 5th-generation (5G) mobile communication systems, ultra-reliable and low-latency communications (URLLC) have stringent requirements on latency (around 1 ms) and reliability (up to 99.99999%). Nevertheless, existing 5G URLLC alone cannot fulfill all the Key Performance Indicators (KPIs) in emerging mission-critical applications like industrial automation, intelligent transportation, telemedicine, Tactile Internet, and Virtual/Augmented Reality (VR/AR). The 6th generation (6G) communication systems need to meet additional requirements on some of the following KPIs in combination with URLLC: high spectrum efficiency (SE)/throughput/energy efficiency (EE)/network availability/security as well as low Age of Information (AoI)/jitter/round-trip delay. These new requirements pose unprecedented challenges in terms of design methodologies and enabling technologies in 6G. To fill the gap between 5G URLLC and the diverse KPI requirements of the neXt generation URLLC (xURLLC), novel methodologies and innovative technologies are much needed.
CRIS-Team Scopus Importer:2023-07-21
Keywords: Special issues and sections; 5G mobile communication; Low latency communication; 6G mobile communication; Performance evaluation; Ultra reliable low latency communication

HoloFed: Environment-Adaptive Positioning via Multi-band Reconfigurable Holographic Surfaces and Federated Learning - Hu, Jingzhi; Chen, Zhe; Zheng, Tianyue; Schober, Robert; Luo, Jun (IEEE Journal on Selected Areas in Communications, 2023)
Positioning is an essential service for various applications and is expected to be integrated with existing communication infrastructures in 5G and 6G. Though current Wi-Fi and cellular base stations (BSs) can be used to support this integration, the resulting precision is unsatisfactory due to the lack of precise control of the wireless signals. Recently, BSs adopting reconfigurable holographic surfaces (RHSs) have been advocated for positioning as RHSs’ large number of antenna elements enable generation of arbitrary and highly-focused signal beam patterns. However, existing designs face two major challenges: i) RHSs only have limited operating bandwidth, and ii) the positioning methods cannot adapt to the diverse environments encountered in practice. To overcome these challenges, we present HoloFed, a system providing high-precision environment-adaptive user positioning services by exploiting multi-band (MB)-RHS and federated learning (FL). For improving the positioning performance, a lower bound on the error variance is obtained and utilized for guiding MB-RHS’s digital and analog beamforming design. For better adaptability while preserving privacy, an FL framework is proposed for users to collaboratively train a position estimator, where we exploit the transfer learning technique to handle the lack of position labels of the users. Moreover, a scheduling algorithm for the BS to select which users train the position estimator is designed, jointly considering the convergence and efficiency of FL. Our performance evaluation based on simulations confirms that HoloFed achieves a 57%lower positioning error variance compared to a beam-scanning baseline and can effectively adapt to diverse environments.
CRIS-Team Scopus Importer:2023-11-03
Keywords: Array signal processing; Bandwidth; beamforming; federated learning; Federated learning; Global Positioning System; Optimization; Positioning; Privacy; Protocols; reconfigurable holographic surfaces

How sensitive is compute-and-forward to channel estimation errors? - Pappi, Koralia N.; Karagiannidis, George K.; Schober, Robert (IEEE International Symposium on Information Theory - Proceedings, 2013)
We investigate the sensitivity of Compute-and-Forward (C&F) to channel estimation errors. More specifically, a general formula for the computation rate region of a C&F relay, suffering from imperfect channel estimation, is derived, which is then tightly approximated for Gaussian distributed channel estimation errors. Furthermore, a closed-form expression for the distribution of the C&F rate loss is presented, which can be efficiently used to compute relevant statistical parameters, such as the mean rate loss. Numerical and simulation results highlight the high sensitivity of the overall network performance to channel estimation errors. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Hybrid coherent/energy detection for cognitive radio networks - Moghimi, Farzad; Schober, Robert; Mallik, Ranjan K. (GLOBECOM - IEEE Global Telecommunications Conference, 2010)
Cognitive radio (CR) networks require reliable spectrum sensing techniques in order to avoid interference to the primary users of the spectrum. Most existing spectrum sensing techniques are based on simple energy detection. However, in practice, the signals transmitted by primary users usually also contain known symbol such as pilots and preambles for synchronization and channel estimation purposes. Coherent, correlation based spectrum sensing techniques can exploit these known symbols but waste the energy contained in the data symbols. In this paper, we propose a hybrid spectrum sensing scheme which exploits both the pilot and the data symbols transmitted by the primary user. For the practically relevant low signal-to-noise ratio regime, we derive a locally optimal hybrid detection metric, which turns out to be a linear combination of an energy detection metric and a correlation metric. Simulation and analytical results confirm that the hybrid metric outperforms both energy detection and coherent detection even if the pilot positions are not known a priori and have to be estimated by the CR receiver. ©2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Hybrid coherent/energy detection for cognitive radio networks - Moghimi, Farzad; Schober, Robert; Mallik, Ranjan K. (IEEE Transactions on Wireless Communications, 2011)
Cognitive radio (CR) networks require reliable spectrum sensing in order to avoid interference to the primary users of the spectrum. Most existing spectrum sensing techniques are based on simple energy detection. However, in practice, the signals transmitted by primary users often also contain known pilot symbols for synchronization and channel estimation purposes. Coherent correlation based spectrum sensing techniques can exploit these known symbols but fail to utilize the energy contained in the data symbols. In this paper, we propose a hybrid coherent/energy detection scheme for spectrum sensing which exploits both the pilot and the data symbols transmitted by the primary user. Since the complexity of the globally optimal hybrid detection metric is very high, we develop a simple locally optimal hybrid metric, which turns out to be a linear combination of an energy detection metric and a correlation metric. We derive the probabilities of false alarm and missed detection of the proposed hybrid detector, and investigate the asymptotic behavior of both quantities for low signaltonoise ratio and large sample size assuming that the CR network is optimized using a NeymanPearson framework. Simulation and analytical results confirm that the hybrid metric outperforms both energy detection and coherent detection even if the positions of the pilot symbols are not known a priori. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: asymptotic analysis; Cognitive radio; coherent detection; energy detection; locally optimal detection; spectrum sensing

Hybrid NOMA Offloading in Multi-User MEC Networks - Ding, Zhiguo; Xu, Dongfang; Schober, Robert; Vincent Poor, H. (IEEE Transactions on Wireless Communications, 2022)
Non-orthogonal multiple access (NOMA) assisted mobile edge computing (MEC) has recently attracted significant attention due to its superior capability to reduce the energy consumption and the latency of MEC offloading. In this paper, a general hybrid NOMA-MEC offloading strategy is proposed, which includes conventional orthogonal multiple access (OMA) and pure NOMA based offloading as special cases. A multi-objective optimization problem is formulated to minimize the energy consumption for MEC offloading, and a low-complexity resource allocation solution is derived and shown to be Pareto-optimal. Furthermore, by analyzing the properties of the obtained resource allocation solution, important insights regarding NOMA-MEC offloading are obtained. For example, it is proved that pure NOMA-MEC offloading cannot outperform hybrid NOMA-MEC. In addition, a precise condition under which NOMA-MEC outperforms OMA-MEC is established, and shown to match the one previously developed for the two-user special case. Furthermore, the developed analytical results also establish an interesting analogy between the proposed hybrid NOMA-MEC power allocation scheme and the well-known water-filling strategy.
CRIS-Team Scopus Importer:2022-02-04
Keywords: mobile edge computing (MEC); multi-objective optimization; Non-orthogonal multiple access (NOMA); Pareto optimality

Hybrid Precoder Design for Cache-Enabled Millimeter-Wave Radio Access Networks - He, Shiwen; Wu, Yongpeng; Ren, Ju; Huang, Yongming; Schober, Robert; Zhang, Yaoxue (IEEE Transactions on Wireless Communications, 2019)
In this paper, we study the design of a hybrid precoder, consisting of an analog and a digital precoder, for the delivery phase of downlink cache-enabled millimeter-wave (mm-wave) radio access networks (CeMm-RANs). In CeMm-RANs, enhanced remote radio heads (eRRHs), which are equipped with local cache and baseband signal processing capabilities in addition to the basic functionalities of conventional RRHs, are connected to the baseband processing unit via fronthaul links. Two different fronthaul information transfer strategies are considered, namely, hard fronthaul information transfer, where hard information of uncached requested files is transmitted via the fronthaul links to a subset of eRRHs, and soft fronthaul information transfer, where the fronthaul links are used to transmit quantized baseband signals of uncached requested files. The hybrid precoder is optimized for maximization of the minimum user rate under a fronthaul capacity constraint, an eRRH transmit power constraint, and a constant-modulus constraint on the analog precoder. The resulting optimization problem is non-convex, and hence, the global optimal solution is difficult to obtain. Therefore, convex approximation methods are employed to tackle the non-convexity of the achievable user rate, the fronthaul capacity constraint, and the constant modulus constraint on the analog precoder. Then, an effective algorithm with provable convergence is developed to solve the approximated optimization problem. The simulation results are provided to evaluate the performance of the proposed algorithms, where fully digital precoding is used as the benchmark. The results reveal that except for the case of a large fronthaul link capacity, soft fronthaul information transfer is preferable for CeMm-RANs. Furthermore, surprisingly, hybrid precoding outperforms fully digital precoding with soft fronthaul information transfer for medium-to-large file sizes and fronthaul capacity limited mm-wave cloud RANs<br
Keywords: Precoding; Optimization; Downlink; Wireless communication; Radio frequency; Radio access Networks; Baseband

Hybrid Precoder Design for Cache-Enabled Millimeter-Wave Radio Access Networks - He, Shiwen; Wu, Yongpeng; Ren, Ju; Huang, Yongming; Schober, Robert; Zhang, Yaoxue (IEEE Transactions on Wireless Communications, 2019)
In this paper, we study the design of a hybrid precoder, consisting of an analog and a digital precoder, for the delivery phase of downlink cache-enabled millimeter-wave (mm-wave) radio access networks (CeMm-RANs). In CeMm-RANs, enhanced remote radio heads (eRRHs), which are equipped with local cache and baseband signal processing capabilities in addition to the basic functionalities of conventional RRHs, are connected to the baseband processing unit via fronthaul links. Two different fronthaul information transfer strategies are considered, namely, hard fronthaul information transfer, where hard information of uncached requested files is transmitted via the fronthaul links to a subset of eRRHs, and soft fronthaul information transfer, where the fronthaul links are used to transmit quantized baseband signals of uncached requested files. The hybrid precoder is optimized for maximization of the minimum user rate under a fronthaul capacity constraint, an eRRH transmit power constraint, and a constant-modulus constraint on the analog precoder. The resulting optimization problem is non-convex, and hence, the global optimal solution is difficult to obtain. Therefore, convex approximation methods are employed to tackle the non-convexity of the achievable user rate, the fronthaul capacity constraint, and the constant modulus constraint on the analog precoder. Then, an effective algorithm with provable convergence is developed to solve the approximated optimization problem. The simulation results are provided to evaluate the performance of the proposed algorithms, where fully digital precoding is used as the benchmark. The results reveal that except for the case of a large fronthaul link capacity, soft fronthaul information transfer is preferable for CeMm-RANs. Furthermore, surprisingly, hybrid precoding outperforms fully digital precoding with soft fronthaul information transfer for medium-to-large file sizes and fronthaul capacity limited mm-wave cloud RANs.
CRIS-Team WoS Importer:2019-03-29

Hybrid Puncturing and Superposition Scheme for Joint Scheduling of URLLC and eMBB Traffic - Darabi, Mostafa; Jamali, Vahid; Lampe, Lutz; Schober, Robert (IEEE Communications Letters, 2022)
Recent modifications to the air interface of 5G and beyond networks have improved the support for mixed enhanced mobile broadband (eMBB) and ultra-reliable and low-latency (URLLC) traffic. In particular, the concept of mini-slots has been introduced, and URLLC traffic is served at the mini-slot boundaries using superposition or puncturing of eMBB resources. This approach enables low latency for URLLC traffic, but it can incur a rate loss for eMBB traffic. To alleviate the latter, we propose a novel hybrid puncturing and superposition policy that jointly maximizes the minimum average throughput of eMBB traffic and the number of admitted URLLC users. Using sequential convex programming, a joint access technology selection, resource block, and power allocation problem is solved, where eMBB and URLLC user pairing and the decoding order in case of superposition are optimized based on channel state information. Our numerical results confirm that our proposed policy achieves a better trade-off between eMBB throughput and the number of admissible URLLC users when compared with existing solutions.
CRIS-Team Scopus Importer:2022-04-01
Keywords: 5G and beyond cellular networks; Decoding; Downlink; eMBB; hybrid puncturing and superposition; NOMA; Quality of service; Reliability; Resource management; Ultra reliable low latency communication; URLLC

IEEE fellow elevation for ComSoc members - Letaief, Khaled B.; Schober, Robert; Galli, Stefano (IEEE Communications Magazine, 2019)
CRIS-Team Scopus Importer:2020-01-31

Impact of Channel Models on Performance Characterization of RIS-Assisted Wireless Systems - Jamali, Vahid; Ghanem, Walid; Schober, Robert; Poor, H. Vincent (17th European Conference on Antennas and Propagation, EuCAP 2023, 2023)
The performance characterization of communication systems assisted by large reconfigurable intelligent surfaces (RISs) significantly depends on the adopted models for the underlying channels. Under unrealistic channel models, the system performance may be over- or under-estimated which yields inaccurate conclusions for the system design. In this paper, we review five channel models that are chosen to progressively improve the modeling accuracy for large RISs. For each channel model, we highlight the underlying assumptions, its advantages, and its limitations. We compare the system performance under the aforementioned channel models using RIS configuration algorithms from the literature and a new scalable algorithm proposed in this paper specifically for the configuration of extremely large RISs.
CRIS-Team Scopus Importer:2023-06-30

Impact of NOMA on Age of Information: A Grant-Free Transmission Perspective - Ding, Zhiguo; Schober, Robert; Poor, H. Vincent (IEEE Transactions on Wireless Communications, 2023)
The aim of this paper is to characterize the impact of non-orthogonal multiple access (NOMA) on the age of information (AoI) of grant-free transmission. In particular, a low-complexity form of NOMA, termed NOMA-assisted random access, is applied to grant-free transmission in order to illustrate the two benefits of NOMA for AoI reduction, namely increasing channel access and reducing user collisions. Closed-form analytical expressions for the time average AoI achieved by NOMA assisted grant-free transmission are obtained, and asymptotic studies are carried out to demonstrate that the use of the simplest form of NOMA is already sufficient to reduce the AoI of orthogonal multiple access (OMA) by more than 40%. In addition, the developed analytical expressions are also shown to be useful for optimizing the users’ transmission attempt probabilities, which are key parameters for grant-free transmission.
CRIS-Team Scopus Importer:2023-10-13
Keywords: age of information (AoI); Base stations; Complexity theory; grant-free transmission; Internet of Things; Markov processes; NOMA; Non-orthogonal multiple access (NOMA); Signal to noise ratio; Wireless communication

Impact of WiMAX interference on MB-OFDM UWB systems: Analysis and mitigation - Snow, Chris; Lampe, Lutz; Schober, Robert (IEEE Transactions on Communications, 2009)
This paper presents an analysis of the performance of the Multiband Orthogonal Frequency Division Multiplexing (MB-OFDM) system for Ultra Wideband (UWB) communication in the presence of interference from IEEE 802.16 WiMAX systems operating in the 3.5 GHz band. We present an exact analysis of the uncoded bit error rate (BER) of the MB-OFDM system, based on Laplace transform techniques. We also present a simple Gaussian approximation for the WiMAX interference, and establish its relative accuracy and usefulness by means of comparison with the exact analysis and simulations. Such a Gaussian approximation is especially useful for simplified performance analysis, as well as for the design of interference mitigation techniques. Motivated by the Gaussian approximation, we propose a simple two-stage interference mitigation technique for coded MB-OFDM transmissions, consisting of interference spectrum estimation during silent periods followed by appropriate bit metric weighting during Viterbi decoding. We compare parametric and non-parametric spectrum estimation techniques for various scenarios of interest. In the presence of WiMAX interference, the two-stage interference mitigation provides substantial gains in performance in return for modest increases in complexity and without requiring any modifications to the MB-OFDM transmitter or signal structure. © 2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Interference mitigation; Interference suppression; Multiband orthogonal frequency division multiplexing (OFDM); Narrowband interference; Spectral estimation; Ultra wideband (UWB); WiMAX

Improved OFDMA uplink transmission via cooperation in the presence of frequency offsets - Zhang, Zhongshan; Tellambura, Chintha; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2008)
In this paper, we evaluate the performance improvement in an Orthogonal Frequency-Division Multiple Access (OFDMA) uplink achievable with cooperative relaying in the presence of frequency offsets. We consider both the amplify-and-forward (AF) and decode-and-forward (DF) relays. In each transmission, each node plays two roles i.e., the source node and relay, simultaneously, but at different subcarriers. The proposed scheme improves performance without sacrificing the transmission rate and power of the cooperative relays, and the total power used to transmit each symbol, including the power consumed in node the source node and the relays, is kept constant. The outage information rates of the proposed cooperative transmission scheme are derived, and the diversity gain of each forwarding mode in an interference-limited environment is analyzed in this paper. Numerical results illustrate the superior performance of the proposed scheme over the conventional transmission with regard to outage information rate. © 2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Improving and Bounding Asymptotic Approximations for Diversity Combiners in Correlated Generalized Rician Fading - Schlenker, Josh; Chen, Julian; Schober, Robert (IEEE Transactions on Wireless Communications, 2014)
Although relatively simple exact error rate expressions are available for selection combining (SC) and equal gain combining (EGC) with independent fading channels, results for correlated channels are highly complex, requiring multiple levels of integration when more than two branches are considered. Asymptotic analysis has been used to derive simple error expressions valid in the high signal-to-noise ratio (SNR) region. However, it is not clear at what SNR value the asymptotic results are an accurate approximation of the exact solution. In this paper, we derive asymptotic results for SC and EGC in correlated generalized Rician fading channels. Furthermore, the asymptotic results for SC are expanded into an exact infinite series. Although this series grows quickly in complexity as more terms are included, truncation to even two or three terms has much greater accuracy than the first (asymptotic) term alone. Finally, we derive asymptotically tight lower and upper bounds on the error rate for EGC. Using these bounds, we are able to show at what SNR value the asymptotic results are valid. <br
Keywords: Rician channels; Correlation; Signal to noise ratio; Fading; Error analysis; Diversity reception; Joints

Improving bandwidth efficiency in E-band communication systems - Mehrpouyan, Hani; Khanzadi, M. Reza; Matthaiou, Michail; Sayeed, Akbar M.; Schober, Robert; Hua, Yingbo (IEEE Communications Magazine, 2014)
The allocation of a large amount of bandwidth by regulating bodies in the 70/80 GHz band, that is, the E-band, has opened up new potentials and challenges for providing affordable and reliable gigabit-per-second wireless point-to-point links. This article first reviews the available bandwidth and licensing regulations in the E-band. Subsequently, different propagation models (e.g., the ITU-R and Cane models) are compared against measurement results, and it is concluded that to meet specific availability requirements, E-band wireless systems may need to be designed with larger fade margins compared to microwave systems. A similar comparison is carried out between measurements and models for oscillator phase noise. It is confirmed that phase noise characteristics, which are neglected by the models used for narrowband systems, need to be taken into account for the wideband systems deployed in the E-band. Next, a new MIMO transceiver design, termed continuous aperture phased (CAP)-MIMO, is presented. Simulations show that CAP-MIMO enables E-band systems to achieve fiber-optic-like throughputs. Finally, it is argued that full-duplex relaying can be used to greatly enhance the coverage of E-band systems without sacrificing throughput, thus facilitating their application in establishing the backhaul of heterogeneous Networks.<br
Keywords: Phase noise; MIMO; Wireless communicationtten; Attenuation; Bandwidth allocation; Transceivers

Improving diffusion-based molecular communication with unanchored enzymes - Noel, Adam; Cheung, Karen; Schober, Robert (Lecture Notes of the Institute for Computer Sciences, Social-Informatics and Telecommunications Engineering, LNICST, 2014)
In this paper, we propose adding enzymes to the propagation environment of a diffusive molecular communication system as a strategy for mitigating intersymbol interference. The enzymes form reaction intermediates with information molecules and then degrade them so that they have a smaller chance of interfering with future transmissions. We present the reaction-diffusion dynamics of this proposed system and derive a lower bound expression for the expected number of molecules observed at the receiver. We justify a particle-based simulation framework, and present simulation results that show both the accuracy of our expression and the potential for enzymes to improve communication performance.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Intersymbol interference; Molecular communication; Nanonetwork; Reaction-diffusion system

Improving Receiver Performance of Diffusive Molecular Communication With Enzymes - Noel, Adam; Cheung, Karen; Schober, Robert (IEEE Transactions on Nanobioscience, 2014)
This paper studies the mitigation of intersymbol interference in a diffusive molecular communication system using enzymes that freely diffuse in the propagation environment. The enzymes form reaction intermediates with information molecules and then degrade them so that they cannot interfere with future transmissions. A lower bound expression on the expected number of molecules measured at the receiver is derived. A simple binary receiver detection scheme is proposed where the number of observed molecules is sampled at the time when the maximum number of molecules is expected. Insight is also provided into the selection of an appropriate bit interval. The expected bit error probability is derived as a function of the current and all previously transmitted bits. Simulation results show the accuracy of the bit error probability expression and the improvement in communication performance by having active enzymes present. <br
Keywords: Biochemistry; Receivers; Transmitters; Degradation; Nanobioscience; Molecular communication; Kinetic theory

Integrated Sensing and Communication in Distributed Antenna Networks - Xu, Dongfang; Khalili, Ata; Yu, Xianghao; Kwan Ng, Derrick Wing; Schober, Robert (2023 IEEE International Conference on Communications Workshops: Sustainable Communications for Renaissance, ICC Workshops 2023, 2023)
In this paper, we investigate the resource allocation design for integrated sensing and communication (ISAC) in distributed antenna networks (DANs). In particular, coordinated by a central processor (CP), a set of remote radio heads (RRHs) provide communication services to multiple users and sense several target locations within an ISAC frame. To avoid severe interference between the information transmission and the radar echo, we propose to divide the ISAC frame into a communication phase and a sensing phase. During the communication phase, the data signal is generated at the CP and then conveyed to the RRHs via fronthaul links. As for the sensing phase, based on pre-determined RRH-target pairings, each RRH senses a dedicated target location with a synthesized highly-directional beam and then transfers the samples of the received echo to the CP via its fronthaul link for further processing of the sensing information. Taking into account the limited fronthaul capacity and the quality-of-service requirements of both communication and sensing, we jointly optimize the durations of the two phases, the information beamforming, and the covariance matrix of the sensing signal for minimization of the total energy consumption over a given finite time horizon. To solve the formulated non-convex design problem, we develop a low-complexity alternating optimization algorithm which converges to a suboptimal solution. Simulation results show that the proposed scheme achieves significant energy savings compared to the two baseline schemes. Moreover, our results reveal that for efficient ISAC in wireless networks, energy-focused short-duration pulses are favorable for sensing while low-power long-duration signals are preferable for communication.
CRIS-Team Scopus Importer:2023-12-08

Integration of Molecular Communications into Future Generation Wireless Networks - Haselmayr, Werner; Springer, Andreas; Fischer, Georg; Alexiou, Christoph; Boche, Holger; Höher, Peter Adam; Dressler, Falko; Schober, Robert (6G Wireless Summit, 2019)

Intelligent Reflecting Surface Assisted Free-Space Optical Communications - Jamali, Vahid; Ajam, Hedieh; Najafi, Marzieh; Schmauß, Bernhard; Schober, Robert; Poor, H. Vincent (IEEE Communications Magazine, 2021)
Free-space optical (FSO) systems are able to offer the high data-rate, secure, and cost-efficient communication links required for applications such as wireless front- and backhauling for 5G and 6G communication networks. Despite the substantial advancement of FSO systems over the past decades, the requirement of a line-of-sight connection between transmitter and receiver remains a key limiting factor for their deployment. In this article, we discuss the potential role of intelligent reflecting surfaces (IRSs) as a solution to relax this requirement. We present an overview of existing optical IRS technologies; compare optical IRSs with radio frequency IRSs and optical relays; and identify various open problems for future research on IRS-assisted FSO communications.
CRIS-Team WoS Importer:2021-12-10

Intelligent Reflecting Surface Enabled Multi-Target Sensing - Meng, Kaitao; Wu, Qingqing; Schober, Robert; Chen, Wen (IEEE Transactions on Communications, 2022)
Besides improving communication performance, intelligent reflecting surfaces (IRSs) are also promising enablers for achieving larger sensing coverage and enhanced sensing quality. Nevertheless, in the absence of a direct path between the base station (BS) and the targets, multi-target sensing is generally very difficult, since IRSs are incapable of proactively transmitting sensing beams or analyzing target information. Moreover, the echoes of different targets reflected via the IRS-assisted virtual links arrive at the BS from the same direction. In this paper, we study a wireless system comprising a multi-antenna BS and an IRS for multi-target sensing, where the beamforming vector and the IRS phase shifts are jointly optimized to improve the sensing performance. To meet the different sensing requirements, such as a minimum received power and a minimum sensing frequency, we propose three novel IRS-assisted sensing schemes: Time division (TD) sensing, signature sequence (SS) sensing, and hybrid TD-SS sensing. For TD sensing, the sensing tasks are performed in sequence over time. In contrast, the novel SS sensing scheme senses all targets simultaneously and establishes a relationship between the target directions and SSs. To strike a flexible balance between the beam pattern gain and sensing efficiency, we also propose a general hybrid TD-SS sensing scheme with target grouping, where targets belonging to the same group are sensed simultaneously via SS sensing, while the targets in different groups are assigned to orthogonal time slots. By controlling the number of groups, hybrid TD-SS sensing can provide a more flexible balance between beam pattern gain and sensing frequency. Moreover, we propose a two-layer penalty-based algorithm to solve the challenging non-convex optimization problem for the joint design of the BS beamformers, IRS phase shifts, and target grouping. Simulation results demonstrate the effectiveness of the proposed hybrid scheme in achieving a flexible trade-off between beam pattern gain and sensing frequency. Our results also reveal that the power leakage in unintended directions is larger for tighter interference constraints.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Array signal processing; beamforming; Intelligent reflecting surface; multi-target sensing; non-line-of-sight (NLoS); Object detection; Optimization; Radar; Sensors; signature sequence; Task analysis; time division; Time-frequency analysis

Intelligent Reflecting Surface Enhanced Indoor Robot Path Planning: A Radio Map based Approach - Mu, Xidong; Liu, Yuanwei; Guo, Li; Lin, Jiaru; Schober, Robert (IEEE Transactions on Wireless Communications, 2021)
Integrating robots into cellular networks creating connected robotic users has emerged as a promising technology for future smart cities and smart factories due to their low cost and high maneuverability. However, the requirement of establishing stable and high-quality communication links to the robotic users greatly restricts their applicability, especially in indoor environments where obstacles may block the wireless link. To tackle this challenge, in this paper, an indoor robot navigation system is investigated, where an intelligent reflecting surface (IRS) is employed to enhance the connectivity between the access point (AP) and robotic users. Both single-user and multiple-user scenarios are considered. In the single-user scenario, one mobile robotic user (MRU) communicates with the AP. In the multiple-user scenario, the AP serves one MRU and one static robotic user (SRU) employing either non-orthogonal multiple access (NOMA) or orthogonal multiple access (OMA) transmission. The considered system is optimized for minimization of the travelling time/distance of the MRU from a given starting point to a predefined final location, while satisfying constraints on the communication quality of the robotic users. To this end, a radio map based approach is proposed to exploit location-dependent channel propagation knowledge. For the single-user scenario, a channel power gain map is constructed, which characterizes the spatial distribution of the maximum expected effective channel power gain of the MRU for the optimal IRS phase shifts. Based on the obtained channel power gain map, the communication-aware robot path planing problem is solved by exploiting graph theory. For the multiple-user scenario, a communication rate map is constructed, which characterizes the spatial distribution of the maximum expected rate of the MRU for the optimal power allocation at the AP and the optimal IRS phase shifts subject to a minimum rate requirement for the SRU. The joint optimization problem is efficiently solved by invoking bisection search and successive convex approximation methods. Then, a graph theory based solution for the robot path planning problem is derived by exploiting the obtained communication rate map. Our numerical results show that: 1) the required travelling distance of the MRU can be significantly reduced by deploying an IRS; 2) NOMA yields a higher communication rate for the MRU than OMA; 3) the IRS performance gain is significantly more pronounced for NOMA than for OMA.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Intelligent reflecting surfaces; non-orthogonal multiple access; radio maps; robot path planning

Intelligent Reflecting Surfaces for Free Space Optical Communications - Najafi, Marzieh; Schober, Robert (2019 IEEE GLOBAL COMMUNICATIONS CONFERENCE (GLOBECOM), 2019)
CRIS-Team WoS Importer:2020-08-14

Intelligent Reflecting Surfaces for Free Space Optical Communication Systems - Najafi, Marzieh; Schmauß, Bernhard; Schober, Robert (IEEE Transactions on Communications, 2021)
In this paper, we investigate the use of intelligent reflecting surfaces (IRSs) to relax the line-of-sight requirement of free space optical (FSO) systems. Considering a Gaussian laser beam, we first design a phase-shift distribution across the IRS that enables the reflection of the incident beam in any desired direction, i.e., realizing the generalized law of reflection. Moreover, for the designed phase-shift profile, we show that there exists an equivalent mirror-assisted FSO system that generates a reflected electric field on a mirror that is identical to that on the IRS in the original system. However, the location of the laser source and the properties of the emitted Gaussian laser beam are different in the original and the equivalent systems. This equivalence allows us to study the mirror-assisted system, employing the image method from geometric optics, instead of directly analyzing the original IRS-assisted system. Based on this analysis, we model the geometric and misalignment losses (GML) and characterize the impact of the physical parameters of the IRS, such as its size, position, and orientation, on the end-to-end FSO channel. Moreover, we develop a statistical model for the GML which accounts for the random movements of IRS, transmitter (Tx), and receiver (Rx) due to building sway. Furthermore, we analyze the outage probability of an IRS-assisted FSO link based on the derived channel model. Our simulation results validate the accuracy of the developed channel model and offer various insights for system design. For instance, both our simulations and theoretical analysis reveal that even if the variances of the fluctuations of the Tx, IRS, and Rx positions caused by building sway are identical, their impact on the end-to-end channel is not necessarily the same and depends on the relative positioning of these three nodes.
CRIS-Team Scopus Importer:2021-06-11
Keywords: anomalous reflection; Buildings; Channel models; free space optical systems; geometric and misalignment losses; Intelligent reflecting surfaces; Laser beams; Lenses; line-of-sight link; Mirrors; Optical surface waves; Optical transmitters; pointing error

Intelligent surface-Aided transmitter architectures for millimeter-wave ultra massive mimo systems - Jamali Kooshkghazi, Vahid; Tulino, Antonia M.; Fischer, Georg; Müller, Ralf; Schober, Robert (IEEE Open Journal of the Communications Society, 2021)
In this article, we study two novel massive multiple-input multiple-output (MIMO) transmitter architectures for millimeter wave (mmWave) communications which comprise few active antennas, each equipped with a dedicated radio frequency (RF) chain, that illuminate a nearby large intelligent reflecting/transmitting surface (IRS/ITS). The IRS (ITS) consists of a large number of low-cost and energy-efficient passive antenna elements which are able to reflect (transmit) a phase-shifted version of the incident electromagnetic field. Similar to lens array (LA) antennas, IRS/ITS-Aided antenna architectures are energy efficient due to the almost lossless over-The-Air connection between the active antennas and the intelligent surface. However, unlike for LA antennas, for which the number of active antennas has to linearly grow with the number of passive elements (i.e., the lens aperture) due to the non-reconfigurablility (i.e., non-intelligence) of the lens, for IRS/ITS-Aided antennas, the reconfigurablility of the IRS/ITS facilitates scaling up the number of radiating passive elements without increasing the number of costly and bulky active antennas. We show that the constraints that the precoders for IRS/ITS-Aided antennas have to meet differ from those of conventional MIMO architectures. Taking these constraints into account and exploiting the sparsity of mmWave channels, we design two efficient precoders; one based on maximizing the mutual information and one based on approximating the optimal unconstrained fully digital (FD) precoder via the orthogonal matching pursuit algorithm. Furthermore, we develop a power consumption model for IRS/ITS-Aided antennas that takes into account the impacts of the IRS/ITS imperfections, namely the spillover loss, taper loss, aperture loss, and phase shifter loss. Moreover, we study the effect that the various system parameters have on the achievable rate and show that a proper positioning of the active antennas with respect to the IRS/ITS leads to a considerable performance improvement. Our simulation results reveal that unlike conventional MIMO architectures, IRS/ITS-Aided antennas are both highly energy efficient and fully scalable in terms of the number of transmitting (passive) antennas. Therefore, IRS/ITS-Aided antennas are promising candidates for realizing the potential of mmWave ultra massive MIMO communications in practice.
CRIS-Team Scopus Importer:2022-06-05
Keywords: and energy efficiency; hybrid MIMO; Intelligent reflecting/transmitting surfaces; lens array; mmWave communications; reflect/transmit array; scalability

Interference mitigation for coded MB-OFDM UWB - Snow, Chris; Lampe, Lutz; Schober, Robert (2008 IEEE Radio and Wireless Symposium, RWS, 2008)
We consider the ECMA-368 Multiband Orthogonal Frequency Division Multiplexing (MB-OFDM) standard for high rate Ultra Wideband (UWB) wireless communication in the 3.1-10.6 GHz band. The performance of MB-OFDM is impacted by interference from IEEE 802.16 WiMAX systems operating in the licensed 3.5 GHz band. Motivated by recent work showing the approximately Gaussian nature of the WiMAX interference to MB-OFDM, we propose a simple two-stage interference mitigation technique for coded MB-OFDM transmissions according to the ECMA-368 standard, consisting of interference spectrum estimation during silent periods followed by appropriate bit metric weighting during Viterbi decoding. We compare parametric and non-parametric spectrum estimation techniques for coded MB-OFDM transmissions and WiMAX interference for various scenarios of interest. The proposed two-stage interference mitigation technique is shown to be highly effective at mitigating the impact of WiMAX interference. © 2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Inter-session network coding with strategic users: A game-theoretic analysis of the butterfly network - Mohsenian-Rad, Hamed; Huang, Jianwei; Wong, Vincent W. S.; Jaggi, Sidharth; Schober, Robert (IEEE Transactions on Communications, 2013)
We analyze inter-session network coding in a wired network using game theory. We assume that users are selfish and act as strategic players to maximize their own utility, which leads to a resource allocation game among users. In particular, we study a butterfly network, where a bottleneck link is shared by network coding and routing flows. We assume that network coding is performed using pairwise XOR operations. We prove the existence of Nash equilibrium for a wide range of utility functions. We also show that the number of Nash equilibria can be large (even infinite) for certain choices of parameters. This is in sharp contrast to a similar game setting with traditional packet forwarding, where the Nash equilibrium is always unique. We characterize the worst-case efficiency bound, i.e., the Price-of-Anarchy (PoA), compared to an optimal and cooperative network design. We show that by using a discriminatory pricing scheme which charges encoded and forwarded packets differently, we can improve the PoA in comparison with the case where a single pricing scheme is used. However, even when a discriminatory pricing scheme is used, the PoA is still worse than for the case when network coding is not applied. This implies that, although inter-session network coding can improve performance compared to routing, it is much more sensitive to users' strategic behavior. © 1972-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: butterfly network; efficiency bound; game theory; Inter-session network coding; Nash equilibrium; price-of-anarchy

Introduction to the Issue on Signal Processing Advances for Non-Orthogonal Multiple Access in Next Generation Wireless Networks - Liu, Yuanwei; Ding, Zhiguo; Al-Dhahir, Naofal; Schober, Robert; Dobre, Octavia A.; Karagiannidis, George K.; Fan, Pingzhi (IEEE Journal of Selected Topics in Signal Processing, 2019)
CRIS-Team WoS Importer:2019-06-18

Introduction to the Issue on Signal Processing Advances for Non-Orthogonal Multiple Access in Next Generation Wireless Networks - Liu, Yuanwei; Ding, Zhiguo; Al-Dhahir, Naofal; Schober, Robert; Dobre, Octavia A.; Karagiannidis, George K.; Fan, Pingzhi (IEEE Journal of Selected Topics in Signal Processing, 2019)
The papers in this special section focus on signal processing advances in non-orthogonal multiple access (NOMA) and network generation wireless networks. Recent years have witnessed the explosive growth ofmobile data traffic, which has led to ever-increasing demand for high system throughput, massive user access, heterogeneous data traffic, high bandwidth efficiency, and ultra-low latency. Non-orthogonal multiple access (NOMA) has received considerable attention in both industry and academia as an efficient multiple access scheme to meet this demand. The concept of NOMA is to encourage spectrum sharing and to accommodate multiple users in the same orthogonal resource block, such as a time slot, a frequency band, and a spatial direction. By doing so, high bandwidth efficiency and massive connectivity can be attained. Because of its superior performance, NOMA has already been included in the 3rd generation partnership project long-term evolution advanced (3GPP-LTE-A) standard and the next generation digital TV standard (ATSC 3.0), while new proposals for including NOMA in the 5G New Radio (NR) have been put forward. While the principle of NOMA has been wellaccepted by both academia and industry, there are still many open issues related to the required signal processing. The aim of this special issue is to present solutions for signal processing and practical implementation problems related to NOMA, in order to close the gap between theory and practice. In fact, this special issue presents innovative solutions to advanced signal processing designs for of NOMA systems.<br

Introduction to the Issue on Signal Processing for Exploiting Interference Toward Energy Efficient and Secure Wireless Communications - Krikidis, Ioannis; Masouros, Christos; Zheng, Gan; Zhang, Rui; Schober, Robert (IEEE Journal of Selected Topics in Signal Processing, 2016)
INTERFERENCE has been the central focus for meeting the ever increasing requirements on quality of service in modern and future wireless communication systems, and has long been considered as a deleterious factor that limits the system capacity. In conventional communications systems, the design objective is to allow users to share a medium with minimum or no interference. Thus, great efforts are made to avoid, mitigate, and cancel interference. For instance, to support multiple users, orthogonal access methods in time, frequency, code well as spatial domains have been used in different generations of cellular systems. In future-generation heterogeneous cellular networks, due to the increasing number of uncoordinated lowpower nodes such as femtocells to improve the coverage and pacity, interferences need to be mitigated in multiple domains, rendering their management a challenge. Interference mitigation/avoidance techniques provide convenient mechanisms allow multiple users to share the wireless medium. However, they lead to inefficient use of wireless resources.<br
Keywords: Special issues and sections; Interference; Energy efficiency; Wireless communication; Physical layer; Array signal processing; MIMO; Jamming

Introduction to the special section on energy-harvesting cognitive radio networks - Da Costa, Daniel Benevides; Karagiannidis, George K.; Dobre, Octavia A.; Upadhyay, Prabhat K.; Xia, Minghua; Ding, Haiyang; Schober, Robert (IEEE Transactions on Cognitive Communications and Networking, 2019)
We are delighted to introduce the readers to this special section of the IEEE Transactions on Cognitive Communications and Networking (TCCN), which has the purpose of addressing fundamental and practical challenges in the analysis and design of energy-harvesting cognitive radio networks (EH-CRNs). We received a total of 19 submissions, and after a rigorous review process, 9 articles have been selected for publication, which are briefly discussed next.<br
CRIS-Team Scopus Importer:2019-06-21

Invited papers and timeliness of review process - Schober, Robert (IEEE Transactions on Communications, 2014)
CRIS-Team Scopus Importer:2020-02-03

Ion Channel Based Bio-Synthetic Modulator for Diffusive Molecular Communication - Arjmandi, Hamidreza; Ahmadzadeh, Arman; Schober, Robert; Nasiri-Kenari, Masoumeh (IEEE Transactions on Nanobioscience, 2016)
In diffusion-based molecular communication (DMC), a transmitter nanomachine is responsible for signal modulation. Thereby, the transmitter has to be able to control the release of the signaling molecules employed for representing the transmitted information. In nature, an important class of control mechanisms for releasing molecules from cells utilizes ion channels which are pore-forming proteins across the cell membrane. The opening and closing of the ion channels is controlled by a gating parameter. In this paper, an ion channel based modulator for DMC is proposed which controls the rate of molecule release from the transmitter by modulating a gating parameter signal. Exploiting the capabilities of the proposed modulator, an on-off keying modulation technique is introduced and the corresponding average modulated signal, i.e., the average release rate of the molecules from the transmitter, is analyzed. However, since the modulated signal is random in nature, it may deviate from its average. Therefore, the concept of modulator noise is introduced and the statistics of the modulated signal are investigated. Finally, by assuming a simple transparent receiver, the performance of the proposed on-off keying modulation format is studied. The derived analytical expressions for the average modulated signal are confirmed with particle based simulations. Our numerical results reveal that performance estimates of DMC systems obtained based on the assumption of instantaneous molecule release at the transmitter may substantially deviate from the performance achieved with practical modulators.<br
Keywords: Modulation; Logic gates; Biomembranes; Cells (biology); Nanobioscience; Optical transmitters

Ion pump based bio-synthetic modulator model for diffusive molecular communications - Arjmandi, Hamidreza; Jamali Kooshkghazi, Vahid; Ahmadzadeh, Arman; Burkovski, Andreas; Schober, Robert; Nasiri-Kenari, Masoumeh (2016 IEEE 17th International Workshop on Signal Processing Advances in Wireless Communications (SPAWC), 2016)
In diffusive molecular communication (DMC), the transmitter has to be able to control the release of signaling molecules for modulation of the information bits. In natural cells, pumping ions is an important control mechanism for releasing molecules which is carried out by ion pumps embedded in the membrane. The activity of the ion pumps is controlled by a driving parameter. In particular, light driven pumps are controlled by light intensity and enable a high degree of spatial and temporal control for modulation functionality. In this paper, a modulator based on ion pumps is proposed for DMC which controls the release rate of the molecules from the transmitter by modulating a light intensity signal. The pumping process of the ion pump is modeled by a Markov model based on which the stochastic nature of the modulated signal, i.e., the release rate of the ions from the transmitter is analyzed. A simple on-off keying modulation scheme is realized based on the proposed modulator. Our numerical results show that a realistic transmitter based on ion pumps can not release ions instantaneously nor deterministically.<br
Keywords: Ions; Photonics; Modulation; Absorption; Optical Transmitters; Proteins; Biomembranes

I/Q imbalance aware widely-linear channel estimation and detection for uplink massive MIMO systems - Zarei, Shahram; Gerstacker, Wolfgang; Schober, Robert (2015 International Symposium on Wireless Communication Systems (ISWCS), 2016)
In this paper, we propose an in-phase/quadrature-phase imbalance (IQI) aware widely-linear minimum mean square error (IQA-WLMMSE) receiver for uplink single-cell massive multiple-input multiple-output (MIMO) systems with imperfect channel state information (CSI). In our system model, IQI is present at the base station and user terminals and affects both channel estimation and data detection. The proposed IQA-WLMMSE receiver processes the real and imaginary parts of the received signal separately and mitigates both multiple-access interference (MAI) and IQI. Our analytical and simulation results show that the proposed IQA-WLMMSE receiver performs significantly better than the conventional IQI unaware MMSE (IQU-MMSE) receiver, and its sum rate closely approaches the sum rate of the ideal system with no IQ

I/Q imbalance aware widely-linear precoding for downlink massive MIMO systems - Zarei, Shahram; Gerstacker, Wolfgang; Schober, Robert (2014 IEEE Globecom Workshops (GC Wkshps), 2014)
In-phase/quadrature-phase (I/Q) imbalance is one of the most important hardware impairments in communication systems. It arises in the analog parts of direct conversion radio frequency (RF) transceivers and can cause large performance losses. In this paper, the impact of I/Q imbalance on the sum rate performance of downlink massive multiple-input multiple-output (MIMO) systems is analyzed and I/Q imbalance aware widely-linear precoding is considered. The proposed precoder is a widely-linear (WL) extension of the regularized zero-forcing (RZF) precoder and jointly mitigates multi-user interference and I/Q imbalance by processing the real and the imaginary parts of the transmit signal separately. Results from random matrix theory are used to derive analytical expressions for the achievable sum rate of the proposed precoder. Our analytical results show that if the number of base station antennas is much larger than the number of users, the proposed I/Q imbalance aware WL-RZF precoder achieves the same sum rate as the RZF precoder in an ideal system without I/Q imbalance. We also provide an analytical expression for the sum rate loss of the I/Q imbalance unaware RZF precoder compared to the ideal case without I/Q imbalance.<br
Keywords: MIMO; Base stations; Interference; Signal to noise ratio; Vectors; Downlink; Antennas

I/Q Imbalance Aware Widely-Linear Receiver for Uplink Multi-Cell Massive MIMO Systems: Design and Sum Rate Analysis - Zarei, Shahram; Gerstacker, Wolfgang; Aulin, Jocelyn; Schober, Robert (IEEE Transactions on Wireless Communications, 2016)
In-phase/quadrature-phase imbalance (IQI) is one of the most important hardware impairments in communication systems. It arises in the analogue parts of direct conversion transceivers and can cause severe performance losses. In this paper, IQI aware widely-linear (WL) channel estimation and data detection schemes for uplink multicell massive multiple-input multiple-output (MIMO) systems are proposed. The resulting receiver is a WL extension of the minimum mean-square-error (MMSE) receiver and jointly mitigates multiuser interference and IQI by processing the real and the imaginary parts of the received signal separately. Thereby, the IQI arising at both the base station and the user terminals is taken into account. The considered channel state information acquisition model includes the effect of pilot contamination, which is caused by the reuse of the same training sequences in neighbouring cells. We apply results from random matrix theory to derive analytical expressions for the asymptotic achievable sum rates of the proposed IQI aware and conventional IQI unaware (IQU) receivers in the large system limit. Our simulation and analytical results show that the performance of the proposed IQI aware WLMMSE (IQA-WLMMSE) receiver in a system with IQI is close to that of the MMSE receiver in an ideal system without IQI.<br
Keywords: MIMO; Receivers; Uplink; Channel estimation; OFDM; Wireless communication; Interference

I/Q-Imbalance Self-Interference Coordination - Boulogeorgos, Alexandros-Apostolos A.; Kapinas, Vasileios M.; Schober, Robert; Karagiannidis, George K. (IEEE Transactions on Wireless Communications, 2016)
In this paper, we present a novel low-complexity technique, which improves the performance of single-antenna multi-carrier communication systems, suffering from in-phase and quadrature (I/Q)-imbalance (IQI) at the receiver. We refer to the proposed scheme as I/Q-imbalance self-interference coordination (IQSC). This technique not only mitigates the detrimental effects of IQI, but, through appropriate signal processing, also coordinates the self-interference terms produced by IQI in order to achieve second-order frequency diversity. However, these benefits come at the expense of a reduction in transmission rate. More specifically, IQSC is a simple transmit diversity scheme that improves the signal quality at the receiver by elementary signal processing operations across symmetric (mirror) pairs of subcarriers. Thereby, the proposed transmission protocol has a similar complexity as Alamouti's space-time block coding scheme and does not require extra transmit power nor any feedback. To evaluate the performance of IQSC, we derive closed-form expressions for the resulting outage probability and symbol-error rate. Interestingly, IQSC outperforms not only existing IQI compensation schemes but also the ideal system without IQI for the same spectral efficiency and practical target error rates, while it achieves almost the same performance as ideal (i.e., IQI-free) equal-rate repetition coding. Our findings reveal that IQSC is a promising low-complexity technique for significantly increasing the reliability of low-cost devices that suffer from high levels of IQI.<br
Keywords: Radio frequency; OFDM; Wireless communication; Interference; Receivers; Diversity reception

IRS-Assisted Active Device Detection - Laue, Friedemann; Jamali Kooshkghazi, Vahid; Schober, Robert (IEEE Workshop on Signal Processing Advances in Wireless Communications, SPAWC, 2021)
This paper studies intelligent reflecting surface (IRS) assisted active device detection. Since the locations of the devices are a priori unknown, optimal IRS beam alignment is not possible and a worst-case design for a given coverage area is developed. To this end, we propose a generalized likelihood ratio test (GLRT) detection scheme and an IRS phase-shift design that minimizes the worst-case probability of misdetection. In addition to the proposed optimization-based phase-shift design, we consider two alternative suboptimal designs based on closed-form expressions for the IRS phase shifts. Our performance analysis establishes the superiority of the optimization-based design, especially for large coverage areas. Furthermore, we investigate the impact of scatterers on the proposed line-of-sight based design using simulations.
CRIS-Team Scopus Importer:2022-06-05

IRS-Assisted Green Communication Systems: Provable Convergence and Robust Optimization - Yu, Xianghao; Xu, Dongfang; Ng, Derrick Wing Kwan; Schober, Robert (IEEE Transactions on Communications, 2021)
In this paper, we investigate resource allocation for IRS-assisted green multiuser multiple-input single-output (MISO) systems. To minimize the total transmit power, both the beamforming vectors at the access point (AP) and the phase shifts at multiple IRSs are jointly optimized, while taking into account the minimum required quality-of-service (QoS) of multiple users. First, two novel algorithms, namely a penalty-based alternating minimization (AltMin) algorithm and an inner approximation (IA) algorithm, are developed to tackle the non-convexity of the formulated optimization problem when perfect channel state information (CSI) is available. Existing designs employ semidefinite relaxation in AltMin-based algorithms, which, however, cannot ensure convergence. In contrast, the proposed penalty-based AltMin and IA algorithms are guaranteed to converge to a stationary point and a Karush-Kuhn-Tucker (KKT) solution of the design problem, respectively. Second, the impact of imperfect knowledge of the CSI of the channels between the AP and the users is investigated. To this end, a non-convex robust optimization problem is formulated and the penalty-based AltMin algorithm is extended to obtain a stationary solution. Simulation results reveal a key trade-off between the speed of convergence and the achievable total transmit power for the two proposed algorithms. In addition, we show that the proposed algorithms can significantly reduce the total transmit power at the AP compared to various baseline schemes and that the optimal numbers of transmit antennas and IRS reflecting elements, which maximize the system energy efficiency of the considered system, are finite.
CRIS-Team Scopus Importer:2021-08-06
Keywords: Approximation algorithms; Array signal processing; Channel estimation; Convergence; Convergence; green communications; intelligent reflecting surface; MISO communication; Optimization; robust optimization; Wireless communication

IRS-Assisted Wireless Powered NOMA: Do We Really Need Different Phase Shifts in DL and UL? - Wu, Qingqing; Zhou, Xiaobo; Schober, Robert (IEEE Wireless Communications Letters, 2021)
Intelligent reflecting surface (IRS) is a promising technology to improve the performance of wireless powered communication networks (WPCNs) due to its capability to reconfigure signal propagation environments via smart reflection. In particular, the high passive beamforming gain promised by IRS can significantly enhance the efficiency of both downlink wireless power transfer (DL WPT) and uplink wireless information transmission (UL WIT) in WPCNs. Although adopting different IRS phase shifts for DL WPT and UL WIT, i.e., dynamic IRS beamforming, is in principle possible but incurs additional signaling overhead and computational complexity, it is an open problem whether it is actually beneficial. To answer this question, we consider an IRS-assisted WPCN where multiple devices employ a hybrid access point (HAP) to first harvest energy and then transmit information using non-orthogonal multiple access (NOMA). Specifically, we aim to maximize the sum throughput of all devices by jointly optimizing the IRS phase shifts and the resource allocation. To this end, we first prove that dynamic IRS beamforming is not needed for the considered system, which helps reduce the number of IRS phase shifts to be optimized. Then, we propose both joint and alternating optimization based algorithms to solve the resulting problem. Simulation results demonstrate the effectiveness of our proposed designs over benchmark schemes and also provide useful insights into the importance of IRS for realizing spectrum and energy efficient WPCNs.
CRIS-Team Scopus Importer:2021-04-30
Keywords: Array signal processing; dynamic beamforming; Heuristic algorithms; IRS; NOMA; NOMA; Optimization; Throughput; time allocation.; Wireless communication; Wireless power transfer; wireless powered networks

Is NOMA Efficient in Multi-Antenna Networks? A Critical Look at Next Generation Multiple Access Techniques - Clerckx, Bruno; Mao, Yijie; Schober, Robert; Jorswieck, Eduard A.; Love, David J.; Yuan, Jinhong; Hanzo, Lajos; Li, Geoffrey Ye; Larsson, Erik G.; Caire, Giuseppe (IEEE Open Journal of the Communications Society, 2021)
In the past few years, a large body of literature has been created on downlink Non-Orthogonal Multiple Access (NOMA), employing superposition coding and Successive Interference Cancellation (SIC), in multi-antenna wireless networks. Furthermore, the benefits of NOMA over Orthogonal Multiple Access (OMA) have been highlighted. In this paper, we take a critical and fresh look at the downlink Next Generation Multiple Access (NGMA) literature. Instead of contrasting NOMA with OMA, we contrast NOMA with two other multiple access baselines. The first is conventional Multi-User Linear Precoding (MU-LP), as used in Space-Division Multiple Access (SDMA) and multi-user Multiple-Input Multiple-Output (MIMO) in 4G and 5G. The second, called Rate-Splitting Multiple Access (RSMA), is based on multi-antenna Rate-Splitting (RS). It is also a non-orthogonal transmission strategy relying on SIC developed in the past few years in parallel and independently from NOMA. We show that there is some confusion about the benefits of NOMA, and we dispel the associated misconceptions. First, we highlight why NOMA is inefficient in multi-antenna settings based on basic multiplexing gain analysis. We stress that the issue lies in how the NOMA literature, originally developed for single-antenna setups, has been hastily applied to multi-antenna setups, resulting in a misuse of spatial dimensions and therefore loss in multiplexing gains and rate. Second, we show that NOMA incurs a severe multiplexing gain loss despite an increased receiver complexity due to an inefficient use of SIC receivers. Third, we emphasize that much of the merits of NOMA are due to the constant comparison to OMA instead of comparing it to MU-LP and RS baselines. We then expose the pivotal design constraint that multi-antenna NOMA requires one user to fully decode the messages of the other users. This design constraint is responsible for the multiplexing gain erosion, rate and spectral efficiency loss, ineffectiveness to serve a large number of users, and inefficient use of SIC receivers in multi-antenna settings. Our analysis and simulation results confirm that NOMA should not be applied blindly to multi-antenna settings, highlight the scenarios where MU-LP outperforms NOMA and vice versa, and demonstrate the inefficiency, performance loss, and complexity disadvantages of NOMA compared to RSMA. The first takeaway message is that, while NOMA is suited for single-antenna settings (as originally intended), it is not efficient in most multi-antenna deployments. The second takeaway message is that another non-orthogonal transmission framework, based on RSMA, exists which fully exploits the multiplexing gain and the benefits of SIC to boost the rate and the number of users to serve in multi-antenna settings and outperforms both NOMA and MU-LP. Indeed, RSMA achieves higher multiplexing gains and rates, serves a larger number of users, is more robust to user deployments, network loads and inaccurate channel state information and has a lower receiver complexity than NOMA. Consequently, RSMA is a promising technology for NGMA and future networks such as 6G and beyond.
CRIS-Team WoS Importer:2021-07-16

Is RIS-Aided Massive MIMO Promising with ZF Detectors and Imperfect CSI? - Zhi, Kangda; Pan, Cunhua; Zhou, Gui; Ren, Hong; Elkashlan, Maged; Schober, Robert (IEEE Journal on Selected Areas in Communications, 2022)
This paper provides a theoretical framework for understanding the performance of reconfigurable intelligent surface (RIS)-aided massive multiple-input multiple-output (MIMO) with zero-forcing (ZF) detectors under imperfect channel state information (CSI). We first introduce a low-overhead minimum mean square error (MMSE) channel estimator, and then derive and analyze closed-form expressions for the uplink achievable rate. Our analytical results demonstrate that: 1) regardless of the RIS phase shift design, the rate of all users scales at least on the order of O(log2 (MN)), where M and N are the numbers of antennas and reflecting elements, respectively; 2) by aligning the RIS phase shifts to one user, the rate of this user can at most scale on the order of O (log2 (MN2)); 3) either M or the transmit power can be reduced inversely proportional to N, while maintaining a given rate. Furthermore, we propose two low-complexity majorization-minimization (MM)-based algorithms to optimize the sum user rate and the minimum user rate, respectively, where closed-form solutions are obtained in each iteration. Finally, simulation results validate the accuracy of all derived analytical results. Our simulation results also show that the maximum sum rate can be closely approached by simply aligning the RIS phase shifts to an arbitrary user.
CRIS-Team Scopus Importer:2022-08-19
Keywords: Channel estimation; Detectors; imperfect CSI; intelligent reflecting surface (IRS); majorization-minimization (MM); Manganese; massive MIMO; Massive MIMO; Optimization; Radio frequency; Reconfigurable intelligent surface (RIS); Signal to noise ratio; ZF

Joint Beamforming and Phase Shift Optimization for Multicell IRS-aided OFDMA-URLLC Systems - Ghanem, Walid; Jamali Kooshkghazi, Vahid; Schober, Robert (2021 IEEE WIRELESS COMMUNICATIONS AND NETWORKING CONFERENCE (WCNC), 2021)
CRIS-Team WoS Importer:2021-10-29

Joint beamforming, resource allocation, and scheduling for multi-cell multi-user MIMO-OFDMA systems - Zhu, Jun; Schober, Robert; Bhargava, Vijay (GLOBECOM - IEEE Global Telecommunications Conference, 2012)
In this paper, we formulate an optimization problem for joint transmit beamforming, resource allocation, and user scheduling for multi-cell multi-user multiple-input multiple-output (MIMO) orthogonal frequency division multiple access (OFDMA) networks aiming at total average weighted system throughput maximization. Despite the non-convex and combinatorial characteristics of the resulting problem, we transform it into a standard convex optimization problem by introducing an extra sum interference constraint and certain relaxations, which leads to a lower bound for the original problem. Applying Lagrange dual decomposition, we successfully solve the transformed problem in a distributed manner with closed-form expressions for the optimal beamformers, power adaptation, and subcarrier allocation. Numerical results show that our proposed scheme provides a considerable performance gain compared to other existing strategies in terms of weighted system throughput. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Joint channel estimation and decoding of space-time block codes in AF MIMO relay networks - Arti, M. K.; Mallik, Ranjan K.; Schober, Robert (2012 International Conference on Signal Processing and Communications, SPCOM 2012, 2012)
In this paper, we discuss methods of channel estimation and decoding in amplify-and-forward (AF) based multiple-input multiple-output (MIMO) relay networks. We derive three different decoders, namely decoder-I, decoder-II, and decoder-III, for orthogonal space-time block codes using pilot symbol-aided channel estimation over Rayleigh fading MIMO channels in an AF based cooperative communication system. Decoder-I is a decoupled decoder which uses estimated channel gains in decoding. The other two decoders jointly process the received pilot signals and data samples through vector derivative (decoder-II) and probability density function marginalization (decoder-III). Simulation results show that decoder-II and decoder-III have almost the same performance. However, decoder-II is computationally less complex as compared to decoder-III. We also derive an expression for the moment generating function (m.g.f.) of the received signal-to-noise ratio at the destination for decoder-I and by using this m.g.f. the analytical symbol error rate is obtained. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Joint Data Compression and Computation Offloading in Hierarchical Fog-Cloud Systems - Ti Ti Nguyen,; Vu Nguyen Ha,; Long Bao Le,; Schober, Robert (IEEE Transactions on Wireless Communications, 2020)
Data compression (DC) has the potential to significantly improve the computation offloading performance in hierarchical fog-cloud systems. However, it remains unknown how to optimally determine the compression ratio jointly with the computation offloading decisions and the resource allocation. This optimization problem is studied in this paper where we aim to minimize the maximum weighted energy and service delay cost (WEDC) of all users. First, we consider a scenario where DC is performed only at the mobile users. We prove that the optimal offloading decisions have a threshold structure. Moreover, a novel three-step approach employing convexification techniques is developed to optimize the compression ratios and the resource allocation. Then, we address the more general design where DC is performed at both the mobile users and the fog server. We propose three algorithms to overcome the strong coupling between the offloading decisions and the resource allocation. Numerical results show that the proposed optimal algorithm for DC at only the mobile users can reduce the WEDC by up to 65% compared to computation offloading strategies that do not leverage DC or use sub-optimal optimization approaches. The proposed algorithms with additional DC at the fog server lead to a further reduction of the WEDC.
CRIS-Team Scopus Importer:2020-02-04
Keywords: computation offloading; data compression; energy saving; Fog computing; hierarchical fog/cloud; latency; mixed integer non-linear programming; resource allocation

Joint Deployment and Multiple Access Design for Intelligent Reflecting Surface Assisted Networks - Mu, Xidong; Liu, Yuanwei; Guo, Li; Lin, Jiaru; Schober, Robert (IEEE Transactions on Wireless Communications, 2021)
The fundamental intelligent reflecting surface (IRS) deployment problem is investigated for IRS-assisted networks, where one IRS is arranged to be deployed in a specific region for assisting the communication between an access point (AP) and multiple users. Specifically, three multiple access schemes are considered, namely non-orthogonal multiple access (NOMA), frequency division multiple access (FDMA), and time division multiple access (TDMA). The weighted sum rate maximization problem for joint optimization of the deployment location and the reflection coefficients of the IRS as well as the power allocation at the AP is formulated. The non-convex optimization problems obtained for NOMA and FDMA are solved by employing monotonic optimization and semidefinite relaxation to find a performance upper bound. The problem obtained for TDMA is optimally solved by leveraging the time-selective nature of the IRS. Furthermore, for all three multiple access schemes, low-complexity suboptimal algorithms are developed by exploiting alternating optimization and successive convex approximation techniques, where a local region optimization method is applied for optimizing the IRS deployment location. Numerical results are provided to show that: 1) near-optimal performance can be achieved by the proposed suboptimal algorithms; 2) asymmetric and symmetric IRS deployment strategies are preferable for NOMA and FDMA/TDMA, respectively; 3) the performance gain achieved with IRS can be significantly improved by optimizing the deployment location.
CRIS-Team Scopus Importer:2021-06-04
Keywords: Channel estimation; Deployment design; Downlink; intelligent reflecting surface; MISO communication; monotonic optimization; NOMA; non-orthogonal multiple access; Resource management; Transmission line matrix methods; Wireless communication

Joint detection of primary systems using uwb impulse radios - Erkucuk, Serhat; Lampe, Lutz; Schober, Robert (IEEE Transactions on Wireless Communications, 2011)
Regulation in Europe and Japan requires the implementation of detect-and-avoid (DAA) techniques in some bands for the coexistence of licensed primary systems and secondary ultra wideband (UWB) systems. In a typical coexistence scenario, a primary system may have potentially interdependent uplink-downlink communication channels (e.g., simultaneous uplink-downlink communications in a frequency division duplex system) overlapping with the frequency band of a UWB system. If such interdependencies of primary systems' activities are known, the UWB system's ability to detect primary systems can be improved. In this study, we are interested in determining the possible gains in the detection performance when taking interdependencies into account for practically implementable detection methods. Contrary to selecting the detection thresholds individually for each band as in a conventional detection approach, the bands are jointly processed. To this end, maximum a posteriori (MAP) decision variables are generated at the receiver, and bias terms are introduced to achieve a desired trade-off between the probabilities of detection and false alarm. In addition to finding the optimal detection results based on the Neyman-Pearson (NP) test, a suboptimal but practically implementable approach is also considered, and the gain compared to conventional independent detection is quantified for various practical scenarios. The results obtained from this study can be used for improving the primary system detection performance of UWB systems, as well as for cognitive radios that perform spectrum sensing in multiple bands. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: coexistence; cognitive radios; detect-and-avoid (DAA); joint detection; spectrum sensing; Ultra wideband (UWB) systems

Joint Estimation of Channel Parameters in Massive MIMO Systems via PARAFAC Analysis - Wei, Xiao; Peng, Wei; Wing Kwan Ng, Derrick; Schober, Robert; Jiang, Tao (2018 International Conference on Computing, Networking and Communications (ICNC), 2018)
In this paper, we investigate channel parameter estimation for massive multiple-input multiple-output (MIMO) systems, where a large base station (BS) antenna array is used to provide multiplexing and diversity gains. We propose a Parallel Factor (PARAFAC)-based joint estimation scheme, which exploits the low-rank property of massive MIMO channels caused by the physical finite scattering environment. Specifically, we first parameterize the channel in terms of fading coefficients, directions of arrival (DOAs), and delays, thereby the channel is characterized via three equivalent PARAFAC models. Subsequently, we certify the identifiability of the three parameters of the PARAFAC models by exploiting the low-rank property. Then, we develop the proposed PARAFAC-based estimation scheme, which jointly estimates the three channel parameters using an alternating least squares (ALS) algorithm. Moreover, we analyze the computational complexity of the proposed scheme in terms of the required number of floating-point operations (FLOPs). Simulation results show that the proposed scheme achieves both a high performance and a low computational complexity.<br
Keywords: MIMO communication; Estimation; Channel estimation; Direction-of-arrival estimation; Delays; Fading channels; Computational modeling

Joint Optimal Pricing and Task Scheduling in Mobile Cloud Computing Systems - Shah-Mansouri, Hamed; Wong, Vincent W. S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2017)
The evolving mobile cloud computing (MCC) paradigm enables mobile users to offload their computing tasks to cloud servers. In this paper, we study the following problems in MCC systems: 1) which tasks should be offloaded to cloud servers? 2) and what is the optimal price of cloud services? We jointly address these issues by formulating two levels of optimization problems. On the mobile users side, we formulate a utility maximization problem that takes the energy consumption, delay, and price of cloud services into account and obtain the optimal scheduling for both delay-sensitive and delay-tolerant applications. On the cloud service provider (CSP) side, we determine the optimal pricing strategy by formulating a profit maximization problem, which is non-convex in general. We further propose an algorithm using convexification and primal-dual methods to mitigate the non-convexity. Through numerical studies, we investigate the mobile users' behavior and the CSP's pricing strategy. Our results reveal that the proposed scheduler effectively balances the tradeoff between the energy consumption and delay in comparison with different schedulers proposed in the literature. Furthermore, we show that with the proposed pricing algorithm, the CSP can improve its profit by up to 25% compared with static and dynamic pricing strategies.<br
Keywords: Cloud computing; Mobile communication; Pricing; Energy consumption; Mobile handsets; Servers; 5218 - 5232 Delays

Joint power allocation and relay selection in energy harvesting AF relay systems - Ahmed, Imtiaz; Ikhlef, Aissa; Schober, Robert; Mallik, Ranjan K. (IEEE Wireless Communications Letters, 2013)
In this letter, we propose joint relay selection and power allocation schemes for maximization of the throughput of an amplify-and-forward (AF) cooperative communication system where the source and the relays are energy harvesting (EH) nodes. We formulate an offline optimization problem which can be solved optimally by the generalized Bender's decomposition. For real-time implementation with low computational complexity, we propose two suboptimal online power allocation schemes. The performance of the proposed schemes is evaluated via simulations. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Energy harvesting; generalized Bender's decomposition; power allocation; relay selection

Joint Power and Rate Control for Device-to-Device Communications in Cellular Systems - Song, Hojin; Ryu, Jong Yeol; Choi, Wan; Schober, Robert (IEEE Transactions on Wireless Communications, 2015)
This paper investigates device-to-device (D2D) communication nested in a cellular network, where a pair of D2D users directly exchanges their information using the uplink frequency band of the cellular network. When the D2D user treats the interference from the cellular user as noise, power control at the cellular user is optimal for maximizing the rate of the cellular user while controlling the interference to the D2D user. However, if the D2D user can perform successive interference cancelation (SIC), the cellular user needs to adjust both transmit power and rate to maximize its rate, because the decodability of the interfering signals at the D2D user depends not only on the signal power but also on the rate of the cellular user. To control the interference from the cellular user, we propose a joint transmit power and rate control scheme at the cellular user. Forcing the cellular user to transmit with a reduced data rate compared with the maximum possible rate, given its transmit power, the proposed joint power and rate control scheme efficiently enables SIC at the D2D user. To reduce the computational complexity, we also propose a near-optimal scheme that employs either power control or rate control depending on the channel conditions.<br
Keywords: Interference; Receivers; Silicon carbide; Power control; Quality of service; Transmitters; Uplink

JOINT POWER AND SUBCARRIER ALLOCATION FOR MULTI CARRIER FULL-DUPLEX SYSTEMS - Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (2017)
In this paper, we investigate resource allocation for multicarrier communication systems employing a full-duplex base station for serving multiple half-duplex downlink and uplink users simultaneously. We study the joint power and subcarrier allocation design for the maximization of the weighted sum throughput of the system. The algorithm design is formulated as a mixed combinatorial non-convex optimization problem and obtaining the globally optimal solution may require prohibitively high computational complexity. Therefore, a low computational complexity suboptimal iterative algorithm exploiting successive convex approximation is proposed to obtain a locally optimal solution. Simulation results confirm that the proposed suboptimal algorithm obtains a substantial improvement in system throughput compared to various existing baseline schemes.

Joint source-relay design in multi-antenna multi-relay networks with prefixed receivers - Ikhlef, Aissa; Schober, Robert (IEEE International Conference on Communications, 2013)
In this paper, we consider the problem of joint source and relay precoder design for multi-antenna multi-relay networks with a prefixed receiver. Prefixed receivers are of practical interest since they enable low complexity at the end-user's receiver as well as backward compatibility. To compute the source and relay precoders, we propose to maximize the worst stream signal-to- interference-plus-noise ratio (SINR) at the output of the receiver subject to source and relay transmit power constraints. The problem is a non-convex optimization problem. To solve it, we propose an iterative alternating algorithm, where, in each iteration, we compute the precoders alternately. We formulate the resulting optimization problems for the computation of the source and relay precoders as second order cone programming (SOCP) and semidefinite relaxation (SDR) problems, respectively. Moreover, we provide sufficient conditions for the convergence of the proposed iterative alternating algorithm to a fixed point. Simulation results show that the performance of the proposed algorithm is close to the performance achieved if the source, relay, and receiver filters are jointly optimized. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Joint Source-Relay Optimization for Fixed Receivers in Multi-Antenna Multi-Relay Networks - Ikhlef, Aissa; Schober, Robert (IEEE Transactions on Wireless Communications, 2013)
We jointly optimize the source and relay precoders for multi-antenna multi-relay networks employing a prefixed receiver. Prefixed receivers are of practical interest since they enable low complexity at the end-user's receiver as well as backward compatibility. To compute the source and relay precoders, we consider two different criteria. The objective of the first criterion is to maximize the worst stream signal-to-interference-plus-noise ratio (SINR) at the output of the receiver subject to source and relay transmit power constraints. Under the second criterion, we minimize the source and relay transmit powers subject to a certain quality-of-service constraint. Both optimization problems are non-convex. To solve them, we propose iterative alternating algorithms, where, in each iteration, we compute the precoders alternately, i.e., for each precoder optimization, we fix all the precoders except the one which is optimized. For both criteria, we formulate the optimization problem for the computation of the source precoder as a second order cone programming (SOCP) problem, for which the optimal solution can be found using interior point algorithms. For each relay precoder, we formulate the optimization problem as a semidefinite relaxation (SDR) problem for which ready-to-use solvers exist. If the solution to the SDR problem is not of rank one, matrix rank-one decomposition or randomization is applied. We also provide sufficient conditions for the convergence of the proposed iterative alternating algorithms to a fixed point. Simulation results show that the performance of the proposed algorithms is close to the performance achieved if the source, relay, and receiver filters are jointly optimized.<br
Keywords: Relays; Optimization; Receivers; Equalizers; Frequency modulation; Joints; Signal to noise ratio

Joint transceiver design for MIMO relay systems employing SC-FDE - Wu, Peiran; Schober, Robert; Bhargava, Vijay (GLOBECOM - IEEE Global Telecommunications Conference, 2012)
In this paper, we propose a joint transceiver design for multiple-input multiple-output (MIMO) relay systems employing single-carrier frequency-domain equalization (SC-FDE). We first derive the optimal minimum mean-squared error (MMSE) frequency-domain linear equalization filter at the destination and the associated stream-wise MSEs at the output of the equalizer. Subsequently, we optimize the source and relay precoding matrices for various optimality criteria by minimizing a general function of the MSEs subject to separate source and relay power constraints. The structures of the optimal source and relay precoding matrices are obtained in closed form and the remaining power allocation problems are solved using an alternating optimization algorithm. Simulation results show that the proposed SC-FDE designs outperform orthogonal frequency-division multiplexing based MIMO relay systems in terms of both uncoded and coded bit error rate. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Joint Uplink-Downlink Resource Allocation for OFDMA-URLLC MEC Systems - Ghanem, Walid; Jamali, Vahid; Zhang, Qiuyu; Schober, Robert (2020 IEEE Global Communications Conference, GLOBECOM 2020 - Proceedings, 2020)
In this paper, we study resource allocation algorithm design for multiuser orthogonal frequency division multiple access (OFDMA) ultra-reliable low latency communication (URLLC) in mobile edge computing (MEC) systems. To achieve the stringent end-to-end delay and reliability requirements of URLLC MEC systems, we propose joint uplink-downlink resource allocation and finite blocklength transmission. Furthermore, we propose a partial time overlap between the uplink and downlink frames to minimize the end-to-end delay, which introduces new time causality constraints. Then, the proposed resource allocation algorithm is formulated as an optimization problem for minimization of the total weighted transmit power of the network under constraints on the minimum quality-of-service regarding the number of computed URLLC user bits within the maximum allowable computing time, i.e., the end-to-end delay of a computation task. Due to the non-convexity of the optimization problem, finding the globally optimal solution entails a high computational complexity which is not tolerable for real-time applications. Therefore, a low-complexity algorithm based on successive convex approximation is proposed to find a high-quality sub-optimal solution. Our simulation results show that the proposed resource allocation algorithm design facilitates the application of URLLC in MEC systems, and yields significant power savings compared to a benchmark scheme.
CRIS-Team Scopus Importer:2021-04-19

Large-scale analysis of linear massive MIMO Precoders in the Presence of Phase Noise - Krishnan, R.; Khanzadi, M. R.; Krishnan, N.; Wu, Yongpeng; Graell I Amat, A.; Eriksson, T.; Schober, Robert (2015 IEEE International Conference on Communication Workshop, ICCW 2015, 2015)
We study the impact of phase noise on the downlink performance of a multi-user multiple-input multiple-output system, where the base station (BS) employs a large number of transmit antennas M. We consider a setup where the BS employs Mosc free-running oscillators, and M/Mosc antennas are connected to each oscillator. For this configuration, we analyze the impact of phase noise on the performance of regularized zero-forcing (RZF) precoding, when M and the number of users K are asymptotically large, while the ratio M/K = β is fixed. We analytically show that the impact of phase noise on the signal-to-interference-plus-noise ratio (SINR) can be quantified as an effective reduction in the quality of the channel state information available at the BS when compared to a system without phase noise. As a consequence, we observe that as Mosc increases, the SINR of the RZF precoder degrades as the interference power increases, and the desired signal power decreases. On the other hand, the variance of the random phase variations caused by the BS oscillators reduces with increasing Mosc. Through simulations, we verify our analytical results, and study the performance of the RZF precoder for different phase noise and channel noise variances.
CRIS-Team Scopus Importer:2020-01-31

Large-Scale MIMO Secure Transmission with Finite Alphabet Inputs - Wu, Yongpeng; Wang, Jun-Bo; Wang, Jue; Schober, Robert; Xiao, Chengshan (2017)
In this paper, we investigate secure transmission over the large-scale multiple-antenna wiretap channel with finite alphabet inputs. First, we show analytically that a generalized singular value decomposition (GSVD) based design, which is optimal for Gaussian inputs, may exhibit a severe performance loss for finite alphabet inputs in the high signal-to-noise ratio (SNR) regime. In light of this, we propose a novel Per-Group-GSVD (PG-GSVD) design which can effectively compensate the performance loss caused by the GSVD design. More importantly, the computational complexity of the PG-GSVD design is by orders of magnitude lower than that of the existing design for finite alphabet inputs in Wu2012TVT while the resulting performance loss is minimal. Numerical results indicate that the proposed PG-GSVD design can be efficiently implemented in large-scale multiple-antenna systems and achieves significant performance gains compared to the GSVD design.<br
Keywords: antenna arrays; computational complexity; MIMO communication; singular value decomposition; telecommunication security; wireless channels

Leader-Follower Dynamics for Diffusion-based Molecular Communication - Gomez, Jorge Torres; Wicke, Wayan; Toledo, Karel; Schober, Robert; Dressler, Falko (2021 IEEE GLOBAL COMMUNICATIONS CONFERENCE (GLOBECOM), 2021)
CRIS-Team WoS Importer:2022-05-27

Linear Massive MIMO Precoders in the Presence of Phase Noise - A Large-Scale Analysis - Krishnan, Rajet; Khanzadi, M. R.; Krishnan, N.; Wu, Yongpeng; Graell I Amat, Alexandre; Eriksson, Thomas; Schober, Robert (IEEE Transactions on Vehicular Technology, 2016)
We study the impact of phase noise on the downlink performance of a multiuser multiple-input-multiple-output (MIMO) system, where the base station (BS) employs a large number of transmit antennas M. We consider a setup where the BS employs Mosc free-running oscillators, and M/Mosc antennas are connected to each oscillator. For this configuration, we analyze the impact of phase noise on the performance of zero forcing (ZF), regularized ZF, and matched filter precoders when M and the number of users K are asymptotically large, whereas the ratio M/K = β is fixed. We analytically show that the impact of phase noise on the signal-to-interference-plus-noise ratio (SINR) can be quantified as an effective reduction in the quality of the channel state information (CSI) available at the BS when compared with a system without phase noise. As a consequence, we observe that as Mosc increases, the SINR performance of all considered precoders degrades. On the other hand, the variance of the random phase variations caused by the BS oscillators reduces with increasing Mosc. Through Monte Carlo simulations, we verify our analytical results and compare the performance of the precoders for different phase noise and channel noise variances. For all considered precoders, we show that when β is small, the performance of the setup where all BS antennas are connected to a single oscillator is superior to that of the setup where each BS antenna has its own oscillator. However, the opposite is true when β is large and the signal-to-noise ratio (SNR) at the users is low.
CRIS-Team Scopus Importer:2020-01-31
Keywords: Broadcast channel (BC); linear precoding; massive multiple-input multiple-output (MIMO); multiuser (MU) MIMO; phase noise; random matrix theory (RMT)

Linear MIMO precoding in jointly-correlated fading multiple access channels with finite alphabet signaling - Wu, Yongpeng; Wen, Chao-Kai; Xiao, Chengshan; Gao, Xiqi; Schober, Robert (2014 IEEE International Conference on Communications (ICC), 2014)
In this paper, we investigate the design of linear precoders for multiple-input multiple-output (MIMO) multiple access channels (MAC). We assume that statistical channel state information (CSI) is available at the transmitters and consider the problem under the practical finite alphabet input assumption. First, we derive an asymptotic (in the large-system limit) weighted sum rate (WSR) expression for the MIMO MAC with finite alphabet inputs and general jointly-correlated fading. Subsequently, we obtain necessary conditions for linear precoders maximizing the asymptotic WSR and propose an iterative algorithm for determining the precoders of all users. In the proposed algorithm, the search space of each user for designing the precoding matrices is its own modulation set. This significantly reduces the dimension of the search space for finding the precoding matrices of all users compared to the conventional precoding design for the MIMO MAC with finite alphabet inputs, where the search space is the combination of the modulation sets of all users. As a result, the proposed algorithm decreases the computational complexity for MIMO MAC precoding design with finite alphabet inputs by several orders of magnitude. Simulation results for finite alphabet signalling indicate that the proposed iterative algorithm achieves significant performance gains over existing precoder designs, including the precoder design based on the Gaussian input assumption, in terms of both the sum rate and the coded bit error rate.<br
Keywords: MIMO; Algorithm design and analysis; Vectors; Transmitters; Fading; Mutual information; Modulation

Linear Precoding for the MIMO Multiple Access Channel With Finite Alphabet Inputs and Statistical CSI - Wu, Yongpeng; Wen, Chao-Kai; Xiao, Chengshan; Gao, Xiqi; Schober, Robert (IEEE Transactions on Wireless Communications, 2015)
In this paper, we investigate the design of linear precoders for the multiple-input-multiple-output (MIMO) multiple access channel (MAC). We assume that statistical channel state information (CSI) is available at the transmitters and consider the problem under the practical finite alphabet input assumption. First, we derive an asymptotic (in the large system limit) expression for the weighted sum rate (WSR) of the MIMO MAC with finite alphabet inputs and Weichselberger's MIMO channel model. Subsequently, we obtain the optimal structures of the linear precoders of the users maximizing the asymptotic WSR and an iterative algorithm for determining the precoders. We show that the complexity of the proposed precoder design is significantly lower than that of MIMO MAC precoders designed for finite alphabet inputs and instantaneous CSI. Simulation results for finite alphabet signaling indicate that the proposed precoder achieves significant performance gains over existing precoder designs.<br
Keywords: MIMO; Transmitters; Vectors; Channel models; Fading; Mutual information; Iterative methods

Linear Precoding of Data and Artificial Noise in Secure Massive MIMO Systems - Zhu, Jun; Schober, Robert; Bhargava, Vijay K. (IEEE Transactions on Wireless Communications, 2015)
n this paper, we consider secure downlink transmission in a multicell massive multiple-input multiple-output (MIMO) system where the numbers of base station (BS) antennas, mobile terminals, and eavesdropper antennas are asymptotically large. The channel state information of the eavesdropper is assumed to be unavailable at the BS and hence, linear precoding of data and artificial noise (AN) are employed for secrecy enhancement. Four different data precoders (i.e., selfish zero-forcing (ZF)/regularized channel inversion (RCI) and collaborative ZF/RCI precoders) and three different AN precoders (i.e., random, selfish/collaborative null-space-based precoders) are investigated and the corresponding achievable ergodic secrecy rates are analyzed. Our analysis includes the effects of uplink channel estimation, pilot contamination, multicell interference, and path-loss. Furthermore, to strike a balance between complexity and performance, linear precoders that are based on matrix polynomials are proposed for both data and AN precoding. The polynomial coefficients of the data and AN precoders are optimized, respectively, for minimization of the sum-mean-squared-error of and the AN leakage to the mobile terminals in the cell of interest using tools from free probability and random matrix theory. Our analytical and simulation results provide interesting insights for the design of secure multicell massive MIMO systems and reveal that the proposed polynomial data and AN precoders closely approach the performance of selfish RCI data and null-space-based AN precoders, respectively.<br
Keywords: MIMO; Interference; Polynomials; Collaboration; Contamination; Complexity theory; Downlink

Link Allocation for Multiuser Systems With Hybrid RF/FSO Backhaul: Delay-Limited and Delay-Tolerant Designs - Jamali Kooshkghazi, Vahid; Michalopoulos, Diomidis; Uysal, Murat; Schober, Robert (IEEE Transactions on Wireless Communications, 2016)
In this paper, we consider a cascaded radio frequency (RF) and hybrid RF/free space optical (FSO) system where several mobile users transmit their data over an RF link to a decode-and-forward relay node (e.g., a small cell base station) and the relay forwards the information to a destination (e.g., a macro-cell base station) over a hybrid RF/FSO backhaul link. The relay and the destination employ multiple antennas for transmission and reception over the RF links while each mobile user has a single antenna. The RF links are orthogonal to the FSO link but half-duplex with respect to each other, i.e., either the user-relay RF link or the relay-destination RF link is active. For this communication setup, we derive the optimal fixed and adaptive link allocation policies for sharing the transmission time between the RF links based on the statistical and instantaneous channel state information (CSI) of the RF and FSO links, respectively. Thereby, we consider the following two scenarios depending on the delay requirements: 1) delay-limited transmission where the relay has to immediately forward the packets received from the users to the destination, and 2) delay-tolerant transmission where the relay is allowed to store the packets received from the users in its buffer and forward them to the destination when the quality of the relay-destination RF link is favorable. Our numerical results illustrate the effectiveness of the proposed communication architecture and link allocation policies, and their superiority compared to existing schemes, which employ only one type of backhaul link.<br
Keywords: Radio frequency; Relays; Resource management; Delays; Antennas; Wireless communication; Mobile nodes

Load Scheduling and Power Trading in Systems With High Penetration of Renewable Energy Resources - Samadi, Pedram; Wong, Vincent W. S.; Schober, Robert (IEEE Transactions on Smart Grid, 2015)
In this paper, we focus on the problems of load scheduling and power trading in systems with high penetration of renewable energy resources (RERs). We adopt approximate dynamic programming to schedule the operation of different types of appliances including must-run and controllable appliances. We assume that users can sell their excess power generation to other users or to the utility company. Since it is more profitable for users to trade energy with other users locally, users with excess generation compete with each other to sell their respective extra power to their neighbors. A game theoretic approach is adopted to model the interaction between users with excess generation. In our system model, each user aims to obtain a larger share of the market and to maximize its revenue by appropriately selecting its offered price and generation. In addition to yielding a higher revenue, consuming the excess generation locally reduces the reverse power flow, which impacts the stability of the system. Simulation results show that our proposed algorithm reduces the energy expenses of the users. The proposed algorithm also facilitates the utilization of RERs by encouraging users to consume excess generation locally rather than injecting it back into the power grid.<br
Keywords: Home appliances; Demand-side management; Power markets; Scheduling; Dynamic programming

Low-Complexity Hybrid Linear/Tomlinson-Harashima Precoding for Downlink Large-Scale MU-MIMO Systems - Zarei, Shahram; Gerstacker, Wolfgang; Schober, Robert (2016 IEEE Globecom Workshops (GC Wkshps), 2016)
In this paper, we propose a novel low-complexity hybrid linear/Tomlinson-Harashima precoder (HL-THP) for downlink large-scale multiuser multiple-input multiple-output (MU-MIMO) systems. The proposed precoder comprises an inner linear precoder which is designed based on only the second order statistics of the channel state information (CSI) and outer THPs which exploit the instantaneous overall CSI of the cascade of the actual channel and the inner precoder. Thereby, the user terminals (UTs) are divided into groups, where for each group a THP successively mitigates the intra-group interference, whereas the inter-group interference is canceled by the inner linear precoder. Our analytical and simulation results show that the proposed HL-THP achieves a substantially higher average rate per UT and a considerably lower bit error rate (BER) than the linear regularized zero-forcing (RZF) precoder. Moreover, both the average achievable rate per UT and the BER of the proposed HL-THP are close to those of the conventional THP. In addition, we analyze the computational complexity of the proposed HL-THP in terms of the required number of floating-point operations. These results reveal that the proposed HL-THP has a much lower computational complexity than the conventional THP and RZF precoders, respectively. This and its high performance make the HL-THP an excellent candidate for practical systems.<br
Keywords: Computational complexity; Precoding; MIMO; Interference; Antennas; Benchmark testing; Downlink

Low-Complexity Linear Precoding for Downlink Large-Scale MIMO Systems - Zarei, Shahram; Gerstacker, Wolfgang; Müller, Ralf; Schober, Robert (2013)
In this work, we present a low-complexity linear precoding scheme for downlink large-scale multiple-input multiple-output (MIMO) systems. The proposed scheme can achieve near minimum mean square error (MMSE) precoding performance in terms of the sum rate and is based on a matrix polynomial instead of matrix inversion. Simulation results show that matrix polynomials consisting of only a few terms are sufficient to closely approach the sum rate of the classical MMSE precoder and to perform orders of magnitude better than the simple conjugate beamforming (BF) precoder. We derive exact expressions for the computational complexity of the proposed scheme in terms of the number of additions and multiplications and compare it to the complexity of the BF and MMSE precoders. Our complexity analysis shows that for large number of base station antennas N compared to the number of generated transmit symbols tau per channel estimate and large number of users K, the proposed polynomial precoder has a lower complexity than the classical MMSE precoder.

Low-Complexity MIMO Precoding for Finite-Alphabet Signals - Wu, Yongpeng; Wing Kwan Ng, Derrick; Wen, Chao-Kai; Schober, Robert; Lozano, Angel (IEEE Transactions on Wireless Communications, 2017)
This paper investigates the design of precoders for single-user multiple-input multiple-output (MIMO) channels, and, in particular, for finite-alphabet signals. Based on an asymptotic expression for the mutual information of channels exhibiting line-of-sight components and rather general antenna correlations, precoding structures that decompose the general channel into a set of parallel subchannel pairs are proposed. Then, a low-complexity iterative algorithm is devised to maximize the sum mutual information of all pairs. The proposed algorithm significantly reduces the computational load of existing approaches with only minimal loss in performance. The complexity savings increase with the number of transmit antennas and with the cardinality of the signal alphabet, making it possible to support values thereof that were unmanageable with existing solutions. Most importantly, the proposed solution does not require instantaneous channel state information (CSI) at the transmitter, but only statistical CSI.<br
Keywords: MIMO; Mutual information; Channel models; Precoding; Complexity theory; Transmitting antennas

Low-complexity MIMO precoding with discrete signals and statistical CSI - Wu, Yongpeng; Wen, Chao-Kai; Wing Kwan Ng, Derrick; Schober, Robert; Lozano, Angel (2016 IEEE International Conference on Communications (ICC), 2016)
In this paper, we investigate the design of multiple-input multiple-output single-user precoders for finite-alphabet signals under the premise of statistical channel-state information at the transmitter. Based on an asymptotic expression for the mutual information of channels exhibiting antenna correlations, we propose a low-complexity iterative algorithm that radically reduces the computational load of existing approaches by orders of magnitude with only minimal losses in performance. The complexity savings increase with the number of transmit antennas and with the cardinality of the signal alphabet, making it possible to support values thereof that were unwieldy in existing solutions.<br
Keywords: Transmitters; MIMO; Mutual information; Channel models; Precoding; Receivers; Constellation diagram

Low-Complexity Widely-Linear Precoding for Downlink Large-Scale MU-MISO Systems - Zarei, Shahram; Gerstacker, Wolfgang; Schober, Robert (IEEE Communications Letters, 2015)
In this letter, we present a widely-linear minimum mean square error (WL-MMSE) precoding scheme employing real-valued transmit symbols for downlink large-scale multi-user multiple-input single-output (MU-MISO) systems. In contrast to the existing WL-MMSE transceivers for single-user multiple-input multiple-output (SU-MIMO) systems, which use both WL precoders and WL detectors, the proposed scheme uses WL precoding only and simple conventional detection at the user terminals (UTs). Moreover, to avoid the computational complexity associated with inversion of large matrices, we modify the WL-MMSE precoder using polynomial expansion (PE). Our simulation results show that in overloaded systems, where the number of UTs is larger than the number of base station antennas, the proposed PE WL-MMSE precoder with only a few terms in the matrix polynomial achieves a substantially higher sum rate than systems employing conventional MMSE precoding. Hence, more UTs sharing the same time/frequency resources can be served in a cell. We validate our simulation results with an analytical expression for the asymptotic sum rate which is obtained by using results from random matrix theory.<br
Keywords: Uplink; Downlink; Signal to noise ratio; Interference; Vectors; Detectors; MIMO

Low-to-Zero-Overhead IRS Reconfiguration: Decoupling Illumination and Channel Estimation - Jamali, Vahid; Alexandropoulos, George C.; Schober, Robert; Vincent Poor, H. (IEEE Communications Letters, 2022)
Most algorithms developed for the optimization of Intelligent Reflecting Surfaces (IRSs) so far require knowledge of full Channel State Information (CSI). However, the resulting acquisition overhead constitutes a major bottleneck for the realization of IRS-assisted wireless systems in practice. In contrast, in this paper, focusing on downlink transmissions from a Base Station (BS) to a Mobile User (MU) that is located in a blockage region, we propose to optimize the IRS for illumination of the area centered around the MU. Hence, the proposed design requires the estimation of the MU’s position and not the full CSI. For a given IRS phase-shift configuration, the end-to-end BS-IRS-MU channel can then be estimated using conventional channel estimation techniques. The IRS reconfiguration overhead for the proposed scheme depends on the MU mobility as well as on how wide the coverage of the IRS illumination is. Therefore, we develop a general IRS phase-shift design, which is valid for both the near- and far-field regimes and features a parameter for tuning the size of the illumination area. Moreover, we study a special case where the IRS illuminates the entire blockage area, which implies that the IRS phase shifts do not change over time leading to zero overhead for IRS reconfiguration.
CRIS-Team Scopus Importer:2022-03-18
Keywords: blockage area; channel estimation; Channel estimation; Downlink; Estimation; illumination area; Intelligent reflecting surfaces; Lighting; Location awareness; low-overhead design; Signal to noise ratio; Wireless communication

Lp - Norm spectrum sensing for cognitive radio networks impaired by non-Gaussian noise - Moghimi, Farzad; Nasri, Amir; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2009)
In cognitive radio (CR) systems reliable spectrum sensing techniques are required in order to avoid interference to the primary users of the spectrum. Whereas most of the existing literature on spectrum sensing considers impairment by additive white Gaussian noise (AWGN) only, in practice, CRs also have to cope with various types of non - Gaussian noise such as man - made impulsive noise, co - channel interference, and ultra - wideband interference. In this paper, we propose robust Lp - norm detectors which do not require any a priori knowledge about the primary user signal and perform well for a wide range of non - Gaussian noises. Furthermore, we analyze the probabilities of false alarm and missed detection of the proposed detectors in the low signal - to - noise ratio regime. For optimization of Lp - norm detection we propose a direct approach based on minimization of the probability of false alarm for a given probability of missed detection and a simpler approach based on maximization of the deflection coefficient of the detector. Analytical and simulation results show that the proposed Lp - norm detectors achieve significant performance gains over conventional energy detection in non-Gaussian noise.
CRIS-Team Scopus Importer:2020-02-03

Magnetic Nanoparticle Based Interface for Molecular Communication Systems - Kisseleff, Steven; Schober, Robert; Gerstacker, Wolfgang (IEEE Communications Letters, 2017)

Magnetic nanoparticle based molecular communication in microfluidic environments - Wicke, Wayan; Ahmadzadeh, Arman; Jamali Kooshkghazi, Vahid; Unterweger, Harald; Alexiou, Christoph; Schober, Robert (IEEE Transactions on Nanobioscience, 2019)
The possibility to guide and control magnetic nanoparticles in a non-invasive manner has spawned various applications in biotechnology, such as targeted drug deliveryandsensingofbiologicalsubstances.Theseapplications are facilitated by the engineering of the size, selective chemical reactivity, and general chemical composition of the employed particles. Motivated by their widespread useandfavorableproperties,inthispaper,weprovideatheoreticalstudyofthepotentialbeneﬁtsofmagneticnanoparticles for the design of molecular communication systems. In particular, we consider a magnetic nanoparticle-based communication in a microﬂuidic channel where an external magnetic ﬁeld is employed to attract the informationcarrying particles to the receiver. We show that the particle transport affected by the Brownian motion, ﬂuid ﬂow, and an external magnetic ﬁeld can be mathematically modeled as diffusion with drift. Thereby, we reveal that the key parameters determining the magnetic force are the particle size and the magnetic ﬁeld gradient. Moreover, we derive an analyticalexpressionfor the channel impulse response, which is used to evaluatethe potentialgain in the expected number of observed nanoparticles due to the magnetic ﬁeld.Furthermore,adoptingthesymbolerrorrateasperformance metric, we show that using magnetic nanoparticles can enable a reliable communication in the presence of disruptive ﬂuid ﬂow. The numerical results obtained by the particle-based simulation validate the accuracy of the derived analyticalexpressions.<br

Magnetic nanoparticle-based molecular communication in microfluidic environments - Wicke, Wayan; Ahmadzadeh, Arman; Jamali, Vahid; Unterweger, Harald; Alexiou, Christoph; Schober, Robert (IEEE Transactions on Nanobioscience, 2019)
The possibility to guide and control magnetic nanoparticles in a non-invasive manner has spawned various applications in biotechnology, such as targeted drug delivery and sensing of biological substances. These applications are facilitated by the engineering of the size, selective chemical reactivity, and general chemical composition of the employed particles. Motivated by their widespread use and favorable properties, in this paper, we provide a theoretical study of the potential benefits of magnetic nanoparticles for the design of molecular communication systems. In particular, we consider a magnetic nanoparticle-based communication in a microfluidic channel where an external magnetic field is employed to attract the information-carrying particles to the receiver. We show that the particle transport affected by the Brownian motion, fluid flow, and an external magnetic field can be mathematically modeled as diffusion with drift. Thereby, we reveal that the key parameters determining the magnetic force are the particle size and the magnetic field gradient. Moreover, we derive an analytical expression for the channel impulse response, which is used to evaluate the potential gain in the expected number of observed nanoparticles due to the magnetic field. Furthermore, adopting the symbol error rate as performance metric, we show that using magnetic nanoparticles can enable a reliable communication in the presence of disruptive fluid flow. The numerical results obtained by the particle-based simulation validate the accuracy of the derived analytical expressions.
CRIS-Team Scopus Importer:2019-05-14
Keywords: Analytical solution; diffusion; fluid flow; magnetic nanoparticles; microfluidic channel; molecular communication

Magnetic Steering of Superparamagnetic Nanoparticles in Duct Flow for Molecular Communication: A Feasibility Study - Schlechtweg, Niklas; Meyer, Sebastian; Unterweger, Harald; Bartunik, Max; Ahmed, Doaa; Wicke, Wayan; Jamali, Vahid; Alexiou, Christoph; Fischer, Georg; Weigel, Robert; Schober, Robert; Kirchner, Jens (Lecture Notes of the Institute for Computer Sciences, Social-Informatics and Telecommunications Engineering, LNICST, 2019)
Molecular communication (MC) denotes information transmission by use of molecules and nanosized particles. For the realization of testbeds, superparamagnetic iron oxide nanoparticles (SPIONs) in duct flow have recently been proposed. Here, an experimental setup is provided to direct these particles at a branching of a tube into a specific direction by use of magnetic fields. For that purpose, gold-coated SPIONs suspended in water at constant flow rate are considered at a Y-shaped connector of tubes. The particles are attracted by use of a custom-made electromagnet, while change of particle concentration in either of the branches is measured by a commercial susceptometer. The approach is evaluated for different flow rates and with the electromagnet both at a fixed position and moving along the tube. Exemplary measurements show that an information transmission is feasible in both approaches and with all tested flow rates. The feasibility study hence shows that particle steering by use of magnetic fields is a viable approach, which is even robust against flow rate variations. It can thus be used in MC to address different transmission channels as well as to realize differential signal transmission. Furthermore, it might help to improve magnetic drug targeting in future applications.
CRIS-Team Scopus Importer:2019-12-27
Keywords: Duct flow; Magnetic field; Molecular communication; Particle steering; Superparamagnetic nanoparticles

Markov Decision Process Based Design of SWIPT Systems: Non-Linear EH Circuits, Memory, and Impedance Mismatch - Shanin, Nikita; Cottatellucci, Laura; Schober, Robert (IEEE Transactions on Communications, 2021)
In this paper, we study simultaneous wireless information and power transfer (SWIPT) systems employing practical non-linear energy harvester (EH) circuits. Since the voltage across the reactive elements of realistic EH circuits cannot drop or rise instantaneously, EHs have memory which we model with a Markov decision process (MDP). Moreover, since an analytical model that accurately models all non-linear effects and the unavoidable impedance mismatch of EHs is not tractable, we propose a learning based model for the EH circuit. We optimize the input signal distribution for maximization of the harvested power under a constraint on the minimum mutual information between transmitter (TX) and information receiver (IR). We distinguish the cases where the MDP state is known and not known at TX and IR. When the MDP state is known, the formulated optimization problem for the harvested power is convex. In contrast, if TX and IR do not know the MDP state, the resulting optimization problem is non-convex and solved via alternating optimization, which is shown to yield a limit point of the problem. Our simulation results reveal that the rate-power region of the considered SWIPT system depends on the symbol duration, the EH input power level, the EH impedance mismatch, and the type of EH circuit. In particular, a shorter symbol duration enables higher bit rates at the expense of a significant decrease in the average harvested power. Furthermore, whereas half-wave rectifiers outperform full-wave rectifiers in the low and medium input power regimes, full-wave rectifiers are preferable if the input power at the EH is high.
CRIS-Team Scopus Importer:2021-03-05
Keywords: energy harvesting; impedance matching; low-pass filters (LPF); Markov processes; non-linear circuits; rectennas; rectifiers; signal design; Wireless power transmission

Massive Access for 5G and Beyond - Chen, Xiaoming; Ng, Derrick Wing Kwan; Yu, Wei; Larsson, Erik G.; Al-Dhahir, Naofal; Schober, Robert (IEEE Journal on Selected Areas in Communications, 2021)
Massive access, also known as massive connectivity or massive machine-type communication (mMTC), is one of the main use cases of the fifth-generation (5G) and beyond 5G (B5G) wireless networks. A typical application of massive access is the cellular Internet of Things (IoT). Different from conventional human-type communication, massive access aims at realizing efficient and reliable communications for a massive number of IoT devices. Hence, the main characteristics of massive access include low power, massive connectivity, and broad coverage, which require new concepts, theories, and paradigms for the design of next-generation cellular networks. This paper presents a comprehensive survey of massive access design for B5G wireless networks. Specifically, we provide a detailed review of massive access from the perspectives of theory, protocols, techniques, coverage, energy, and security. Furthermore, several future research directions and challenges are identified.
CRIS-Team WoS Importer:2021-03-26

Massive Access in Extra Large-Scale MIMO With Mixed-ADC Over Near-Field Channels - Mei, Yikun; Gao, Zhen; Mi, De; Zhou, Mingyu; Zheng, Dezhi; Matthaiou, Michail; Xiao, Pei; Schober, Robert (IEEE Transactions on Vehicular Technology, 2023)
Massive connectivity for extra large-scale multi-input multi-output (XL-MIMO) systems is a challenging issue due to the near-field access channels and the prohibitive cost. In this paper, we propose an uplink grant-free massive access scheme for XL-MIMO systems, in which a mixed-analog-to-digital converters (ADC) architecture is adopted to strike the right balance between access performance and power consumption. By exploiting the spatial-domain structured sparsity and the piecewise angular-domain cluster sparsity of massive access channels, a compressive sensing (CS)-based two-stage orthogonal approximate message passing algorithm is proposed to efficiently solve the joint activity detection and channel estimation problem. Particularly, high-precision quantized measurements are leveraged to perform accurate hyper-parameter estimation, thereby facilitating the activity detection. Moreover, we adopt a subarray-wise estimation strategy to overcome the severe angular-domain energy dispersion problem which is caused by the near-field effect in XL-MIMO channels. Simulation results verify the superiority of our proposed algorithm over state-of-the-art CS algorithms for massive access based on XL-MIMO with mixed-ADC architectures.
CRIS-Team Scopus Importer:2023-07-07
Keywords: Channel estimation; Compressive sensing; massive access; Massive MIMO; Message passing; MIMO communication; mixed-ADC; orthogonal approximate message passing; Quantization (signal); Receiving antennas; Signal processing algorithms; XL-MIMO system

Maximum SNR Transmit Filtering for Decision-Feedback Equalization in Physical Layer Network Coding - Schmidt, Armin Christian; Gerstacker, Wolfgang; Schober, Robert (SCC 2013; 9th International ITG Conference on Systems, Communication and Coding, 2013)
We consider a two-way relaying system employing physical layer network coding (PNC) in channels suffering from frequency-selective fading. In order to mitigate the distortions introduced by the channel, decision-feedback equalization (DFE) is used at the relay node. We introduce transmit filters that generate identical overall channel impulse responses for the links from both source nodes to the relay node, while achieving the maximum signal-to-noise ratio (SNR) for zero-forcing DFE and minimum mean-squared error DFE at the relay node. The performance gain of our novel approach is compared against a benchmark filtering scheme which also creates identical channel impulse responses to enable decision-feedback equalization at the rela

Maximum SNR transmit filtering for linear equalization in physical layer network coding - Schmidt, Armin Christian; Gerstacker, Wolfgang; Schober, Robert (2012 IEEE Globecom Workshops, 2013)
We consider a two-way relaying system employing physical layer network coding (PNC) in channels suffering from frequency-selective fading. In order to mitigate the distortions introduced by the channel, a linear equalizer is used at the relay node. We introduce transmit filters that generate identical overall channel impulse responses for both source nodes, while achieving the maximum signal-to-noise ratio (SNR) for linear zero-forcing (ZF) and minimum mean-squared error (MMSE) equalization at the relay node. The performance gain of our novel approach is compared against a benchmark filtering scheme which also creates identical channel impulse responses to enable linear equalization at the rela

Max-max relay selection for relays with buffers - Ikhlef, Aissa; Michalopoulos, Diomidis S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2012)
In this paper, we propose a new relay selection scheme for half-duplex relays with buffers. The proposed scheme is referred to as max-max relay selection (MMRS) since the relays with the best source-relay and the best relay-destination channels are selected for reception and transmission, respectively, which is only possible without data loss if the relays have buffers of infinite size. To relax this idealized assumption, we propose hybrid relay selection (HRS) for relays with buffers of finite size. HRS is a combination of conventional best relay selection (BRS) and MMRS and takes into account both the channel state and the buffer state for relay selection. We provide a comprehensive analysis of the outage and symbol error probabilities of both MMRS and HRS for a decode-and-forward protocol in Rayleigh fading. This analysis reveals that BRS, HRS, and MMRS achieve the same diversity gain. However, for N relays, MMRS achieves a signal-to-noise ratio (SNR) gain of 3(1-1/N) dB compared to BRS, and HRS closely approaches the SNR gain of MMRS for moderate buffer sizes (e.g. 30 transmission intervals). © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Cooperative relaying; error rate analysis; outage analysis; relay selection; relays with buffers

Max-Min Fair Beamforming for SWIPT Systems with Non-Linear EH Model - Boshkovska, Elena; Chen, Xiaoming; Dai, Linglong; Wing Kwan Ng, Derrick; Schober, Robert (2017 IEEE 86th Vehicular Technology Conference (VTC-Fall), 2017)
We study the beamforming design for multiuser systems with simultaneous wireless information and power transfer (SWIPT). Employing a practical non-linear energy harvesting (EH) model, the design is formulated as a non-convex optimization problem for the maximization of the minimum harvested power across several energy harvesting receivers. The proposed problem formulation takes into account imperfect channel state information (CSI) and a minimum required signal-to-interference-plus-noise ratio (SINR). The globally optimal solution of the design problem is obtained via the semidefinite programming (SDP) relaxation approach. Interestingly, we can show that at most one dedicated energy beam is needed to achieve optimality. Numerical results demonstrate that with the proposed design a significant performance gain and improved fairness can be provided to the users compared to two baseline schemes.<br
Keywords: Erbium; Integrated circuit modeling; Receivers; Array signal processing; Wireless communication; Radio frequency; Mathematical model

Max-min fair wireless energy transfer for secure multiuser communication systems - Wing Kwan Ng, Derrick; Schober, Robert (2014 IEEE Information Theory Workshop (ITW 2014), 2014)
This paper considers max-min fairness for wireless energy transfer in a downlink multiuser communication system. Our resource allocation design maximizes the minimum harvested energy among multiple multiple-antenna energy harvesting receivers (potential eavesdroppers) while providing quality of service (QoS) for secure communication to multiple single-antenna information receivers. In particular, the algorithm design is formulated as a non-convex optimization problem which takes into account a minimum required signal-to-interference-plus-noise ratio (SINR) constraint at the information receivers and a constraint on the maximum tolerable channel capacity achieved by the energy harvesting receivers for a given transmit power budget. The proposed problem formulation exploits the dual use of artificial noise generation for facilitating efficient wireless energy transfer and secure communication. A semidefinite programming (SDP) relaxation approach is exploited to obtain a global optimal solution of the considered problem. Simulation results demonstrate the significant performance gain in harvested energy that is achieved by the proposed optimal scheme compared to two simple baseline schemes.<br
Keywords: Receivers; Energy harvesting; Resource management; Noise; Wireless communication; Interference; Optimization

Max–Min Multicell-Aware Precoding and Power Allocation for Downlink Massive MIMO Systems - Zarei, Shahram; Aulin, Jocelyn; Gerstacker, Wolfgang; Schober, Robert (IEEE Signal Processing Letters, 2017)
We propose a max-min multicell-aware regularized zero-forcing (MCA-RZF) precoding and power allocation scheme for downlink multicell massive multiple-input multiple-output systems. A general correlated channel model is considered, and the adopted channel state information (CSI) acquisition model includes the effects of estimation errors and pilot contamination. We use results from random matrix theory to derive deterministic equivalents for the proposed max-min power allocation in the large system limit, which solely depend on statistical CSI, but not on individual channel realizations. Our numerical results show that the proposed max-min MCA-RZF precoder achieves a substantially higher network-wide minimum rate than the MCA-RZF and the conventional RZF precoders with uniform power allocation, respectively, as well as the conventional RZF precoder with max-min power allocation.<br
Keywords: Resource management; Precoding; MIMO; Interference; Signal to noise ratio; Optimization; Channel estimation

Media Modulation based Molecular Communication - Brand, Lukas; Garkisch, Moritz; Lotter, Sebastian; Schäfer, Maximilian; Burkovski, Andreas; Sticht, Heinrich; Castiglione, Kathrin; Schober, Robert (IEEE Transactions on Communications, 2022)
In conventional molecular communication (MC) systems, the signaling molecules used for information transmission are stored, released, and then replenished by a transmitter (TX). However, the replenishment of signaling molecules at the TX is challenging in practice. Furthermore, in most envisioned MC applications, e.g., in the medical field, it is not desirable to insert the TX into the MC system, as this might impair natural biological processes. In this paper, we propose the concept of media modulation based MC where the TX is placed outside the channel and utilizes signaling molecules already present inside the system. The signaling molecules can assume different states which can be switched by external stimuli. Hence, in media modulation based MC, the TX modulates information into the state of the signaling molecules. In particular, we exploit the group of photochromic molecules, which undergo light-induced reversible state transitions, for media modulation. We study the usage of these molecules for information transmission in a three-dimensional duct system, which contains an eraser, a TX, and a receiver for erasing, writing, and reading of information via external light, respectively. We develop a statistical model for the received signal which accounts for the distribution of the signaling molecules in the system, the initial states of the signaling molecules, the reliability of the state control mechanism, the randomness of irrepressible, spontaneous state switching, and the randomness of molecule propagation. We adopt a maximum likelihood detector and show that it can be reduced to a threshold based detector. Furthermore, we derive analytical expressions for the optimal threshold value and the resulting bit error rate (BER), respectively. Both the statistical model and BER results are verified by computer simulations. Our results reveal that media modulation enables reliable information transmission, validating it as a promising alternative to MC based on molecule emitting TXs.<br

Media Modulation in Molecular Communications - Brand, Lukas; Garkisch, Moritz; Lotter, Sebastian; Schäfer, Maximilian; Castiglione, Kathrin; Schober, Robert (IEEE International Conference on Communications, 2022)
In conventional molecular communication (MC) systems, the signaling molecules used for information transmission are stored, released, and then replenished by a transmitter (TX). However, the replenishment of signaling molecules at the TX is challenging in practice. Furthermore, in most envisioned MC applications, e.g., in the medical field, it is not desirable to insert the TX into the MC system, as this might impair natural biological processes. In this paper, we propose the concept of media modulation based MC where the TX is placed outside the channel and utilizes signaling molecules already existing inside the system. We consider signaling molecules that can be in different states which can be switched by external stimuli. Hence, in media modulation based MC, for information transmission, the TX stimulates the signaling molecules to encode information into their state. In particular, we elaborate media modulation for the group of photochromic molecules, which undergo light-induced reversible transformations, and study the usage of these molecules for information transmission in a three-dimensional duct system. We develop a statistical model for the received signal which depends on the distribution of the signaling molecules in the system, the reliability of the state control mechanism, and the randomness of molecule propagation. Furthermore, we analyze the performance of media modulation based MC in terms of the bit error rate (BER). We show that media modulation enables reliable information transmission, which renders a TX inside the channel unnecessary.
CRIS-Team Scopus Importer:2022-09-16

Millimeter-Wave Full-Duplex UAV Relay: Joint Positioning, Beamforming, and Power Control - Zhu, Lipeng; Zhang, Jun; Xiao, Zhenyu; Cao, Xianbin; Xia, Xiang Gen; Schober, Robert (IEEE Journal on Selected Areas in Communications, 2020)
In this paper, a full-duplex unmanned aerial vehicle (FD-UAV) relay is employed to increase the communication capacity of millimeter-wave (mmWave) networks. Large antenna arrays are equipped at the source node (SN), destination node (DN), and FD-UAV relay to overcome the high path loss of mmWave channels and to help mitigate the self-interference at the FD-UAV relay. Specifically, we formulate a problem for maximization of the achievable rate from the SN to the DN, where the UAV position, analog beamforming, and power control are jointly optimized. Since the problem is highly non-convex and involves high-dimensional, highly coupled variable vectors, we first obtain the conditional optimal position of the FDUAV relay for maximization of an approximate upper bound on the achievable rate in closed form, under the assumption of a line-of-sight (LoS) environment and ideal beamforming. Then, the UAV is deployed to the position which is closest to the conditional optimal position and yields LoS paths for both air-to-ground links. Subsequently, we propose an alternating interference suppression (AIS) algorithm for the joint design of the beamforming vectors and the power control variables. In each iteration, the beamforming vectors are optimized for maximization of the beamforming gains of the target signals and the successive reduction of the interference, where the optimal power control variables are obtained in closed form. Our simulation results confirm the superiority of the proposed positioning, beamforming, and power control method compared to three benchmark schemes. Furthermore, our results show that the proposed solution closely approaches a performance upper bound for mmWave FD-UAV systems.
CRIS-Team Scopus Importer:2020-06-30
Keywords: Antenna arrays; Array signal processing; beamforming; full-duplex relay; Interference; Millimeter wave communication; mmWave communications; positioning; power control; Power control; Relays; UAV communications; Unmanned aerial vehicles

Mimicking full-duplex relaying using half-duplex relays with buffers - Ikhlef, Aissa; Kim, Junsu; Schober, Robert (IEEE Transactions on Vehicular Technology, 2012)
We propose a new relaying scheme referred to as space full-duplex max-max relay selection (SFD-MMRS), which uses relay selection and half-duplex (HD) relays with buffers to mimic full-duplex (FD) relaying. SFD-MMRS allows the selection of different relays for reception and transmission, which, in turn, enables the relays selected for reception and transmission to simultaneously receive and transmit. With SFD-MMRS, the prelog factor 1/2 is removed from the capacity expression, and better performance in terms of both throughput and outage probability is achieved. We provide a comprehensive analysis of the capacity and outage probability of the proposed scheme for a decode-and-forward (DF) protocol in Rayleigh fading. This analysis reveals that the proposed scheme provides better performance, compared with HD MMRS and HD best relay selection (BRS). Moreover, our simulation results show that the capacity of the proposed scheme with HD relays exceeds twice the capacity of BRS with HD relays for any number of relays. Furthermore, the proposed scheme provides full diversity and large signal-to-noise ratio (SNR) gains, compared with competing schemes in the literature. © 1967-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Capacity analysis; cooperative relaying; fixed relays with buffers; outage analysis; relay selection; space full-duplex (SFD)

MIMO wiretap channels: Secure transmission using Transmit antenna selection and receive generalized selection combining - Yang, Nan; Yeoh, Phee Lep; Elkashlan, Maged; Schober, Robert; Yuan, Jinhong (IEEE Communications Letters, 2013)
We propose and analyze transmit antenna selection with receive generalized selection combining (TAS/GSC) for physical layer security enhancement in multiple-input multiple-output wiretap channels. In this protocol, a single antenna out of NA antennas is selected at the transmitter and L B antennas out of NB antennas are combined at the legitimate receiver. We characterize the physical layer secrecy of TAS/GSC via our new closed-form expressions for the exact and the asymptotic secrecy outage probability. We demonstrate that the maximum secrecy outage diversity gain of NA NB is achieved. © 1997-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: generalized selection combining; Multiple-input multiple-output wiretap channel; transmit antenna selection

Minimum BER transmit beamforming for MIMO-OFDM systems with finite rate feedback - Liang, Yang-Wen; Schober, Robert; Gerstacker, Wolfgang (IEEE International Conference on Communications, 2008)
In this paper, we consider minimum bit error rate (BER) beamforming (BF) for multiple-input multiple-output orthogonal frequency division multiplexing (MIMO-OFDM) systems. In particular, assuming perfect channel state information (CSI) at the transmitter we optimize cyclic BF filters (C-BFFs) for minimization of the average BER and the maximum sub-carrier BER, respectively. If the C-BFF length Lg is equal to the number of sub-carriers Nc, closed-form solutions to both optimization problems exist. For the practically relevant case L g < Nc we present numerical methods for calculation of the optimum C-BFFs. For finite-rate feedback channels we provide a global vector quantization (GVQ) scheme for codebook design. Simulation results for typical IEEE 802.11n channels confirm the excellent performance of the proposed minimum BER BF schemes for both uncoded and coded MIMO-OFDM systems. ©2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03

MISO wireless communication systems via intelligent reflecting surfaces - Yu, Xianghao; Xu, Dongfang; Schober, Robert (2019 IEEE/CIC International Conference on Communications in China, ICCC 2019, 2019)
Intelligent reflecting surfaces (IRSs) have received considerable attention from the wireless communications research community recently. In particular, as low-cost passive devices, IRSs enable the control of the wireless propagation environment, which is not possible in conventional wireless networks. To take full advantage of such IRS-assisted communication systems, both the beamformer at the access point (AP) and the phase shifts at the IRS need to be optimally designed. However, thus far, the optimal design is not well understood. In this paper, a point-to-point IRS-assisted multiple-input single-output (MISO) communication system is investigated. The beamformer at the AP and the IRS phase shifts are jointly optimized to maximize the spectral efficiency. Two efficient algorithms exploiting fixed point iteration and manifold optimization techniques, respectively, are developed for solving the resulting non-convex optimization problem. The proposed algorithms not only achieve a higher spectral efficiency but also lead to a lower computational complexity than the state-of-the-art approach. Simulation results reveal that deploying large-scale IRSs in wireless systems is more efficient than increasing the antenna array size at the AP for enhancing both the spectral and the energy efficiency.
CRIS-Team Scopus Importer:2019-11-05

Mixed RF and Hybrid RF/FSO Relaying - Jamali Kooshkghazi, Vahid; Michalopoulos, Diomidis S.; Uysal, Murat; Schober, Robert (2015 IEEE Globecom Workshops (GC Wkshps), 2015)
In this paper, we consider a mixed RF and hybrid RF/FSO system where several mobile users transmit their data over an RF link to a relay node (e.g. a small cell base station) and the relay forwards the information to a destination (e.g. a macro cell base station) over a hybrid RF/FSO backhaul link. The relay and the destination employ multiple antennas for transmission and reception over the RF links while each mobile user has a single antenna. The RF links are orthogonal with respect to the FSO link and half-duplex with respect to each other, i.e., either the user-relay RF link or the relay-destination RF link is active. For this communication setup, we derive the optimal policy for sharing the RF transmission time between the RF links. Our numerical results show the effectiveness of the proposed communication architecture and link allocation policy, and their superiority compared to existing schemes which employ only one type of backhaul link.<br
Keywords: Radio frequency; Relays; Antennas; Bandwidth; Mobile nodes; Receivers

ML Detection without CSI for Constant-Weight Codes in THz Communications with Strong Phase Noise - Wu, Yifei; Koch, Johannes; Vossiek, Martin; Schober, Robert; Gerstacker, Wolfgang (2022 IEEE Global Communications Conference, GLOBECOM 2022 - Proceedings, 2022)
To meet the ever-increasing requirements of high-rate data transmission, the significant amount of spectrum available in the TeraHertz (THz) band is considered for future wireless communications. However, the performance of THz communications is limited by strong phase noise (PN) introduced by oscillators and the complexity added by channel state information (CSI) acquisition. To overcome such impediments, we propose a new transmission concept based on constant-weight (CW) codes which enable low-complexity maximum-likelihood (ML) sequence detection at the receiver side in the presence of strong PN without requiring statistical or instantaneous CSI knowledge. In addition, the error rate of the ML receiver for the proposed CW codes is analyzed. Simulation results verify the analytical derivations and illustrate that the proposed transmission scheme outperforms transmission with on-off keying modulation and coherent detection.
CRIS-Team Scopus Importer:2023-03-07

MMSE beamforming for SC-FDMA transmission over MIMO ISI channels - Dang, Uyen Ly; Ruder, Michael; Schober, Robert; Gerstacker, Wolfgang (EURASIP Journal on Advances in Signal Processing, 2011)
We consider transmit beamforming for single-carrier frequency-division multiple access (SC-FDMA) transmission over frequency-selective multiple-input multiple-output (MIMO) channels. The beamforming filters are optimized for minimization of the sum of the mean-squared errors (MSEs) of the transmitted data streams after MIMO minimum mean-squared error linear equalization (MMSE-LE), and for minimization of the product of the MSEs after MIMO MMSE decision-feedback equalization (MMSE-DFE), respectively. We prove that for SC-FDMA transmission in both cases eigenbeamforming, diagonalizing the overall channel, together with a nonuniform power distribution is the optimum beamforming strategy. The optimum power allocation derived for MMSE-LE is similar in spirit to classical results for the optimum continuous-time transmit filter for linear modulation formats obtained by Berger/Tufts and Yang/Roy, whereas for MMSE-DFE the capacity achieving waterfilling strategy well known from conventional single-carrier transmission schemes is obtained. Moreover, we present a modification of the beamformer design to mitigate an increase of the peak-to-average power ratio (PAPR) which is in general associated with beamforming. Simulation results demonstrate the high performance of the proposed beamforming algorithms. Copyright © 2011 Uyen Ly Dang et al.
CRIS-Team Scopus Importer:2020-02-03

MMSE Beamforming for SC-FDMA Transmission over MIMO ISI Channels with Linear Equalization - Dang, Thi Uyen Ly; Ruder, Michael; Gerstacker, Wolfgang; Schober, Robert (2010 IEEE Global Telecommunications Conference GLOBECOM 2010, 2011)
We consider transmit beamforming for single-carrier frequency-division multiple access (SC-FDMA) transmission over frequency-selective multiple-input multiple-output (MIMO) channels. The beamforming filter is optimized for minimization of the sum of the mean-squared errors (MMSEs) of the transmitted data streams after equalization. Here, MIMO minimum mean-squared error linear equalization (MMSE-LE) is considered. We prove that for SC-FDMA transmission eigen-beamforming diagonalizing the overall channel together with a nonuniform power distribution is the optimum beamforming strategy in the MMSE sense. The derived optimum power allocation is similar in spirit to classical results for the optimum continuous-time transmit filter for linear modulation formats obtained by Berger/Tufts and Yang/Roy. Moreover, we present a modification of the beamformer design to mitigate an increase of the peak-to-average power ratio (PAPR) which is in general associated with beamforming. Simulation results demonstrate the excellent performance of the proposed beamforming algorith

Modeling and Design of IRS-Assisted Multi-Link FSO Systems - Ajam, Hedieh; Najafi, Marzieh; Jamali Kooshkghazi, Vahid; Schmauß, Bernhard; Schober, Robert (IEEE Transactions on Communications, 2022)
In this paper, we investigate the modeling and design of intelligent reflecting surface (IRS)-assisted optical communication systems, which can circumvent the line-of-sight (LOS) requirement in multi-link free space optical (FSO) systems. The FSO laser beams incident on the optical IRSs have a Gaussian power intensity profile and a nonlinear phase profile, whereas the plane waves in radio frequency (RF) systems have a uniform power intensity profile and a linear phase profile. Given these substantial differences, the results available for IRS-assisted RF systems are not applicable to IRS-assisted FSO systems. Therefore, we develop a new analytical channel model for point-to-point IRS-assisted FSO systems based on the Huygens-Fresnel principle. Our analytical model captures the impact of the size, position, and orientation of the IRS as well as its phase shift profile on the end-to-end channel. To allow the sharing of the optical IRS by multiple FSO links, we propose three different protocols, namely the time division (TD), IRS-division (IRSD), and IRS homogenization (IRSH) protocols. The proposed protocols address the specific characteristics of FSO systems including the non-uniformity and possible misalignment of the laser beams. Furthermore, to compare the proposed IRS sharing protocols, we analyze the bit error rate (BER) and the outage probability of IRS-assisted multi-link FSO systems in the presence of inter-link interference. Our simulation results validate the accuracy of the proposed analytical channel model for IRS-assisted FSO systems and confirm that this model is applicable for both large and intermediate IRS-receiver lens distances. Furthermore, we show that for the proposed IRSD and IRSH protocols, inter-link interference becomes negligible if the laser beams are properly centered on the IRS and the transceivers are carefully positioned, respectively. Moreover, in the absence of misalignment errors, the IRSD protocol outperforms the other protocols, whereas in the presence of misalignment errors, the IRSH protocol performs significantly better than the IRSD protocol.
CRIS-Team Scopus Importer:2022-04-15
Keywords: Analytical models

Modeling an Experimental Biological Modulator for Molecular Communications by Electrical Circuits - Schäfer, Maximilian; Wicke, Wayan; Grebenstein, Laura; Strobl, Christian; Stavracakis Peixoto, Renata; Kirchner, Jens; Burkovski, Andreas; Fischer, Georg; Weigel, Robert; Rabenstein, Rudolf; Schober, Robert (4th Workshop on Molecular Communications, 2019)
Experimental systems are necessary to validate and improve theoretical molecular communication models. We propose an analytical model for a biological modulator based on genetically modified Escherichia coli (E. coli) bacteria which convert an electrically-controlled light signal into a chemical response. Techniques from system identification and electrical networks synthesis are used to model the complex biological system. Compared to a simple reference model, a better fit to the observed dynamics in the experimental data is obtaine

Modeling Duct Flow for Molecular Communication - Wicke, Wayan; Schwering, Tobias; Ahmadzadeh, Arman; Jamali Kooshkghazi, Vahid; Noel, Adam; Schober, Robert (2018 IEEE Global Communications Conference (GLOBECOM), 2018)
Active transport such as fluid flow is sought in molecular communication to extend coverage, improve reliability, and mitigate interference. Flow models are often over-simplified, assuming one-dimensional diffusion with constant drift. However, diffusion and flow are usually encountered in three-dimensional bounded environments where the flow is highly non-uniform such as in blood vessels or microfluidic channels. For a qualitative understanding of the relevant physical effects inherent to these channels, based on the Peclet number and the transmitter-receiver distance, we study when simplified models of uniform flow and advection-only transport are applicable. For these two regimes, analytical expressions for the channel impulse response are derived and validated by particle-based simulation. Furthermore, as advection-only transport is typically overlooked and hence not analyzed in the molecular communication literature, we evaluate the symbol error rate for exemplary on-off keying as performance metri

Modeling Duct Flow for Molecular Communication - Wicke, Wayan; Schwering, Tobias; Ahmadzadeh, Arman; Jamali, Vahid; Noel, Adam; Schober, Robert (2018 IEEE Global Communications Conference, GLOBECOM 2018 - Proceedings, 2019)
Active transport such as fluid flow is sought in molecular communication to extend coverage, improve reliability, and mitigate interference. Flow models are often over-simplified, assuming one-dimensional diffusion with constant drift. However, diffusion and flow are usually encountered in three-dimensional bounded environments where the flow is highly non-uniform such as in blood vessels or microfluidic channels. For a qualitative understanding of the relevant physical effects inherent to these channels, based on the Péclet number and the transmitter-receiver distance, we study when simplified models of uniform flow and advection-only transport are applicable. For these two regimes, analytical expressions for the channel impulse response are derived and validated by particle-based simulation. Furthermore, as advection-only transport is typically overlooked and hence not analyzed in the molecular communication literature, we evaluate the symbol error rate for exemplary on-off keying as performance metric.
CRIS-Team Scopus Importer:2019-05-02

Molecular communication using magnetic nanoparticles - Wang, Jiaheng; Huang, Yongming; Jin, Shi; Schober, Robert; You, Xiaohu; Zhao, Chunming (IEEE Journal on Selected Areas in Communications, 2018)
As a promising technology for 5G networks, device-to-device (D2D) communication can improve spectrum utilization by sharing the resources of cellular users (CUs). However, this is at the cost of generating interference to the CUs. While most existing works focused on eliminating or suppressing the interference between the D2D links and the CUs, such interference could in fact be beneficial for improving the security of cellular communication. Specifically, D2D links may, in return for reusing cellular resources to achieve high spectral efficiency, act as friendly jammers and help the CUs against malicious wiretapping. To reach this win-win situation, D2D resource management has to be designed from a physical layer security perspective. In this paper, we consider the joint optimization of power allocation and channel assignment of the D2D links and the CUs with the aim to provide security to the CUs and improve the spectral efficiency of the D2D links simultaneously. We focus on the challenging downlink resource sharing problem and investigate both single-channel and multi-channel D2D communications. The resulting resource management design problems turn out to be difficult nonlinear mixed integer problems. Nevertheless, by exploiting the inherent properties of the formulated optimization problems, we are able to analytically characterize the optimal power allocation of the CUs and D2D links, and develop efficient methods for joint optimization of their channel assignments. Simulation results show that the proposed resource management policies outperform several baseline schemes and can indeed achieve the desired twofold objective.<br
Keywords: Device-to-device communication; Resource Management; Copper; Security; Interference; Channel allocation; Downlink

Molecular communication using magnetic nanoparticles - Wicke, Wayan; Ahmadzadeh, Arman; Jamali Kooshkghazi, Vahid; Unterweger, Harald; Alexiou, Christoph; Schober, Robert (Proceedings of IEEE Wireless Communications and Networking Conference (WCNC), 2018)

Molecular Noise In Synaptic Communication - Lotter, Sebastian; Schäfer, Maximilian; Schober, Robert (IEEE Transactions on Nanobioscience, 2022)
In synaptic molecular communication (MC), the activation of postsynaptic receptors by neurotransmitters (NTs) is governed by a stochastic reaction-diffusion process. This randomness of synaptic MC contributes to the randomness of the electrochemical downstream signal in the postsynaptic cell, called postsynaptic membrane potential (PSP). Since the randomness of the PSP is relevant for neural computation and learning, characterizing the statistics of the PSP is critical. However, the statistical characterization of the synaptic reaction-diffusion process is difficult because the reversible bi-molecular reaction of NTs with receptors renders the system nonlinear. Consequently, there is currently no model available which characterizes the impact of the statistics of postsynaptic receptor activation on the PSP. In this work, we propose a novel statistical model for the synaptic reaction-diffusion process in terms of the chemical master equation (CME). We further propose a novel numerical method which allows to compute the CME efficiently and we use this method to characterize the statistics of the PSP. Finally, we present results from stochastic particle-based computer simulations which validate the proposed models. We show that the biophysical parameters governing synaptic transmission shape the autocovariance of the receptor activation and, ultimately, the statistics of the PSP. Our results suggest that the processing of the synaptic signal by the postsynaptic cell effectively mitigates synaptic noise while the statistical characteristics of the synaptic signal are preserved. The results presented in this paper contribute to a better understanding of the impact of the randomness of synaptic signal transmission on neuronal information processing.
Created from Fastlane, Scopus look-up
Keywords: Adaptation models; Biological system modeling; Computational modeling; Degradation; Ions; Monte Carlo methods; Synapses

Molecule Harvesting Transmitter Model for Molecular Communication Systems - Ahmadzadeh, Arman; Jamali, Vahid; Schober, Robert (IEEE Open Journal of the Communications Society, 2022)
This paper develops mathematical models for molecule harvesting transmitters in diffusive molecular communication (MC) systems. In particular, we consider a communication link consisting of a spherical transmitter nano-machine and a spherical receiver nano-machine suspended in a fluid environment. The transmitter and the receiver exchange information via signaling molecules. The transmitter is equipped with molecule harvesting units on its surface. Signaling molecules which come into contact with the harvesting units may be re-captured by the transmitter. For this system, we derive closed-form expressions for the channel impulse response and harvesting impulse response. Furthermore, we extend the harvesting transmitter model to the case of continuous signaling molecule release. In particular, we derive closed-form expressions for the average received signal at the receiver and the average harvested signal at the transmitter for different temporal release rates namely, constant, linearly increasing, and linearly decreasing release rates. Finally, we validate the accuracy of the derived mathematical expressions via particle-based simulations.
CRIS-Team WoS Importer:2022-03-25

Multi‐antenna Energy Beamforming for SWIPT - Wing Kwan Ng, Derrick; Duong, Trung Q.; Zhong, Caijun; Schober, Robert (Wireless Information and Power Transfer: Theory and Practice, 2019)
Energy‐constrained wireless networks, such as sensor networks, are typically powered by batteries that have limited operation time. This chapter focuses on the downlink case with simultaneous wireless information and power transfer (SWIPT) from the access point (AP) to user terminals (UTs). It considers simplified scenarios with only one or two active UTs in the network. The chapter analyzes the multi‐antenna design for rate‐energy region characterization in a two‐user SWIPT system with separated information decoding (ID) receiver and energy harvesting (EH) receivers, by assuming perfect channel state information (CSI) at the transmitter. It reveals fundamental trade‐offs in designing wireless MIMO systems for maximizing the efficiency of simultaneous information and energy transmission and discusses some extensions of such a SWIPT design to different setups by considering various practical considerations.<br
Keywords: Receivers; Wireless communication; Transmitters; Covariance matrices; Wireless sensor networks; Baseband; Radio frequency

Multi-Cell Massive MIMO Systems With Hardware Impairments: Uplink-Downlink Duality and Downlink Precoding - Zarei, Shahram; Gerstacker, Wolfgang; Aulin, Jocelyn; Schober, Robert (IEEE Transactions on Wireless Communications, 2017)
In this paper, we propose a new framework for uplink-downlink duality in multi-cell multi-user multiple-input multiple-output systems suffering from residual hardware impairments (HWIs) at the base stations and the user terminals. We apply the proposed uplink-downlink duality framework to derive a multi-cell interference and HWI aware minimum mean square error (MCHA-MMSE) precoder which also takes channel state information estimation errors into account. We use results from random matrix theory to derive an analytical expression for the downlink power allocation for the proposed MCHA-MMSE precoder in the large system limit, which only depends on the channel's second order statistics. In contrast to the conventional MMSE precoder, the proposed MCHA-MMSE precoder takes inter-cell interference, pilot contamination, and residual HWIs into account and therefore achieves substantially higher sum rates. The proposed MCHA-MMSE precoder exploits statistical channel knowledge, but does not require data exchange between base stations via backhaul links. In order to reduce the computational complexity, the matrix inversion required for the computation of the MCHA-MMSE precoder is approximated by a matrix polynomial leading to a new polynomial-expansion MCHA-MMSE precoder. Using results from the random matrix theory, we derive closed-form expressions for the asymptotically optimal coefficients of the matrix polynomial, which only depend on the channel's second order statistics.<br
Keywords: MIMO; Training; Interference; Resource Management; Signal to noise Ratio; Covariance Matrices; Wireless communication

Multi-objective beamforming for energy-efficient SWIPT systems - Leng, Shiyang; Wing Kwan Ng, Derrick; Zlatanov, Nikola; Schober, Robert (2016 International Conference on Computing, Networking and Communications (ICNC), 2016)
In this paper, we study the resource allocation algorithm design for energy-efficient simultaneous wireless information and power transfer (SWIPT) systems. The considered system comprises a transmitter, an information receiver, and multiple energy harvesting receivers equipped with multiple antennas. We propose a multi-objective optimization framework to study the trade-off between the maximization of the energy efficiency of information transmission and the maximization of wireless power transfer efficiency. The proposed problem formulation takes into account the per antenna circuit power consumption of the transmitter and the imperfect channel state information of the energy harvesting receivers. The adopted non-convex multi-objective optimization problem is transformed into an equivalent rank-constrained semidefinite program (SDP) and optimally solved by SDP relaxation. Numerical results unveil an interesting trade-off between the considered conflicting system design objectives and reveal the benefits of multiple transmit antennas for improving system energy efficiency.<br
Keywords: Receivers; Transmitters; System analysis and design; Resource Management; Energy harvesting; Optimization; Erbium

Multi-objective beamforming for secure communication in systems with wireless information and power transfer - Ng, Derrick Wing Kwan; Xiang, Lin; Schober, Robert (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC, 2013)
In this paper, we study power allocation for secure communication in a multiuser multiple-input single-output (MIS-O) downlink system with simultaneous wireless information and power transfer. The receivers are able to harvest energy from the radio frequency when they are idle. We propose a multi-objective optimization problem for power allocation algorithm design which incorporates two conflicting system objectives: total transmit power minimization and energy harvesting efficiency maximization. The proposed problem formulation takes into account a quality of service (QoS) requirement for the system secrecy capacity. Our designs advocate the dual use of artificial noise in providing secure communication and facilitating efficient energy harvesting. The multi-objective optimization problem is non-convex and is solved by a semidefinite programming (SDP) relaxation approach which results in an approximate of solution. A sufficient condition for the global optimal solution is revealed and the accuracy of the approximation is examined. To strike a balance between computational complexity and system performance, we propose two suboptimal power allocation schemes. Numerical results not only demonstrate the excellent performance of the proposed suboptimal schemes compared to baseline schemes, but also unveil an interesting trade-off between energy harvesting efficiency and total transmit power. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Multi-Objective Optimization for Active IRS-Assisted Communication Systems - Xu, Dongfang; Yu, Xianghao; Song, Shenghui; Kwan Ng, Derrick Wing; Schober, Robert (2023 IEEE International Mediterranean Conference on Communications and Networking, MeditCom 2023, 2023)
In this paper, we study the resource allocation algorithm design for a multiuser communication system assisted by an active intelligent reflecting surface (IRS). In particular, supported by a power source, each active IRS element can adjust the phase and amplify the magnitude of the incident signal. To realize power-efficient communication, the proposed design incorporates two conflicting yet desirable objectives, i.e., access point (AP) transmit power minimization and active IRS amplification power minimization, via a multi-objective optimization problem (MOOP). In the literature, systematic algorithms that can efficiently tackle such a non-convex MOOP while preserving joint optimality are not available. To this end, we propose a state-of-the-art optimization framework by capitalizing on bilinear transformation, ϵ-constraint, and inner approximation methods. Simulation results not only reveal the power consumption tradeoff between the AP and the active IRS, but also confirm that the proposed scheme is more power-efficient than four baseline schemes.
CRIS-Team Scopus Importer:2023-11-10

Multi-Objective Optimization for Power Efficient Full-Duplex Wireless Communication Systems - Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (Global Communications Conference (GLOBECOM), 2015)
In this paper, we investigate power efficient resource allocation algorithm design for multiuser wireless communication systems employing a full-duplex (FD) radio base station for serving multiple half-duplex (HD) downlink and uplink users simultaneously. We propose a multi-objective optimization framework for achieving two conflicting yet desirable system design objectives, i.e., total downlink transmit power minimization and total uplink transmit power minimization, while guaranteeing the quality-of-service of all users. To this end, the weighted Tchebycheff method is adopted to formulate a multi-objective optimization problem (MOOP). Although the considered MOOP is non-convex, we solve it optimally by semidefinite programming relaxation. Simulation results not only unveil the trade-off between the total downlink and the total uplink transmit power, but also confirm that the proposed FD system provides substantial power savings over traditional HD systems.
Keywords: Downlink; Uplink; Optimization; Resource Management; MIMO; Wireless communication; High definition video

Multi-Objective Optimization for Robust Power Efficient and Secure Full-Duplex Wireless Communication Systems - Sun, Yan; Ng, Derrick Wing Kwan; Zhu, Jun; Schober, Robert (IEEE Transactions on Wireless Communications, 2016)
In this paper, we investigate the power efficient resource allocation algorithm design for secure multiuser wireless communication systems employing a full-duplex (FD) base station (BS) for serving multiple half-duplex (HD) downlink (DL) and uplink (UL) users simultaneously. We propose a multi-objective optimization framework to study two conflicting yet desirable design objectives, i.e., total DL transmit power minimization and total UL transmit power minimization. To this end, the weighed Tchebycheff method is adopted to formulate the resource allocation algorithm design as a multi-objective optimization problem (MOOP). The considered MOOP takes into account the quality-of-service requirements of all legitimate users for guaranteeing secure DL and UL transmission in the presence of potential eavesdroppers. Thereby, secure UL transmission is enabled by the FD BS and would not be possible with an HD BS. The imperfectness of the channel state information of the eavesdropping channels and the inter-user interference channels is incorporated for robust resource allocation algorithm design. Although the considered MOOP is non-convex, we solve it optimally by semidefinite programming relaxation. Simulation results not only unveil the trade-off between the total DL transmit power and the total UL transmit power, but also confirm the robustness of the proposed algorithm against potential eavesdroppers.
Keywords: Full-duplex radio; physical layer security; multi-objective optimization; non-convex optimization

Multi-objective optimization for secure full-duplex wireless communication systems - Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (Full-Duplex Communications for Future Wireless Networks, 2020)
In traditional half-duplex (HD) communication systems, the HD base station (BS) can transmit artificial noise (AN) to jam the eavesdroppers for securing the downlink (DL) communication. However, guaranteeing uplink (UL) transmission is not possible with an HD BS because HD BSs cannot jam the eavesdroppers during UL transmission. In this chapter, we investigate the resource allocation algorithm design for secure multiuser systems employing a full-duplex (FD) BS for serving multiple HD DL and UL users simultaneously. In particular, the FD BS transmits AN to guarantee the concurrent DL and UL communication security. We propose a multi-objective optimization framework to study two conflicting yet desirable design objectives, namely total DL transmit power minimization and total UL transmit power minimization. To this end, the weighted Tchebycheff method is adopted to formulate the resource allocation algorithm design as a multi-objective optimization problem (MOOP). The considered MOOP takes into account the quality-of-service (QoS) requirements of all legitimate users for guaranteeing secure DL and UL transmission in the presence of potential eavesdroppers. Thereby, secure UL transmission is enabled by the FD BS, which would not be possible with an HD BS. Although the considered MOOP is non-convex, we solve it optimally by semidefinite programming (SDP) relaxation. Simulation results not only unveil the trade-off between the total DL transmit power and the total UL transmit power, but also confirm that the proposed secure FD system can guarantee concurrent secure DL and UL transmission and provide substantial power savings over a baseline system.
CRIS-Team Scopus Importer:2020-08-07

Multiobjective Resource Allocation for Secure Communication in Cognitive Radio Networks With Wireless Information and Power Transfer - Wing Kwan Ng, Derrick; Lo, Ernest S.; Schober, Robert (IEEE Transactions on Vehicular Technology, 2015)
In this paper, we study resource allocation for multiuser multiple-input-single-output secondary communication systems with multiple system design objectives. We consider cognitive radio (CR) networks where the secondary receivers are able to harvest energy from the radio frequency when they are idle. The secondary system provides simultaneous wireless power and secure information transfer to the secondary receivers. We propose a multiobjective optimization framework for the design of a Pareto-optimal resource allocation algorithm based on the weighted Tchebycheff approach. In particular, the algorithm design incorporates three important system design objectives: total transmit power minimization, energy harvesting efficiency maximization, and interference-power-leakage-to-transmit-power ratio minimization. The proposed framework takes into account a quality-of-service (QoS) requirement regarding communication secrecy in the secondary system and the imperfection of the channel state information (CSI) of potential eavesdroppers (idle secondary receivers and primary receivers) at the secondary transmitter. The proposed framework includes total harvested power maximization and interference power leakage minimization as special cases. The adopted multiobjective optimization problem is nonconvex and is recast as a convex optimization problem via semidefinite programming (SDP) relaxation. It is shown that the global optimal solution of the original problem can be constructed by exploiting both the primal and the dual optimal solutions of the SDP-relaxed problem. Moreover, two suboptimal resource allocation schemes for the case when the solution of the dual problem is unavailable for constructing the optimal solution are proposed. Numerical results not only demonstrate the close-to-optimal performance of the proposed suboptimal schemes but unveil an interesting tradeoff among the considered conflicting system design objectives as well.<br
Keywords: Receivers; Resource management; Energy harvesting; Interference; Wireless communication; Radio transmitters

Multiple-Access Fading Channel With Wireless Power Transfer and Energy Harvesting - Hadzi-Velkov, Zoran; Zlatanov, Nikola; Schober, Robert (IEEE Communications Letters, 2014)
We consider the achievable average rates of a multiple-access system, which consists of N energy-harvesting users (EHUs) that transmit information over a block fading multiple-access channel (MAC) and a base station (BS) that broadcasts radio frequency (RF) energy to the EHUs for wireless power transfer. The information (over the uplink) and power (over the downlink) can be transmitted either in time division duplex or frequency division duplex. For the case when the EHUs' battery capacities and the number of transmission slots are both infinite, we determine the optimal power allocation for the BS and the optimal rates and power allocations for the EHUs that maximize the achievable rate region of the MAC. The resulting online solution is asymptotically optimal and also applicable for a finite number of transmission slots and finite battery capacities.<br
Keywords: Wireless communication; Fading; Uplink; Downlink; Batteries; Resource management; Energy harvesting

Multiple-antenna techniques for wireless communications - a comprehensive literature survey - Mietzner, Jan; Schober, Robert; Lampe, Lutz; Gerstacker, Wolfgang; Höher, Peter (IEEE Communications Surveys & Tutorials, 2009)
The use of multiple antennas for wireless communication systems has gained overwhelming interest during the last decade - both in academia and industry. Multiple antennas can be utilized in order to accomplish a multiplexing gain, a diversity gain, or an antenna gain, thus enhancing the bit rate, the error performance, or the signal-to-noise-plus-interference ratio of wireless systems, respectively. With an enormous amount of yearly publications, the field of multiple-antenna systems, often called multiple-input multiple-output (MIMO) systems, has evolved rapidly. To date, there are numerous papers on the performance limits of MIMO systems, and an abundance of transmitter and receiver concepts has been proposed. The objective of this literature survey is to provide non-specialists working in the general area of digital communications with a comprehensive overview of this exciting research field. To this end, the last ten years of research efforts are recapitulated, with focus on spatial multiplexing and spatial diversity techniques. In particular, topics such as transmitter and receiver structures, channel coding, MIMO techniques for frequency-selective fading channels, diversity reception and space-time coding techniques, differential and non-coherent schemes, beamforming techniques and closed-loop MIMO techniques, cooperative diversity schemes, as well as practical aspects influencing the performance of multiple-antenna systems are addressed. Although the list of references is certainly not intended to be exhaustive, the publications cited will serve as a good starting point for further readin

Multiple-differential encoding for multi-hop amplify-and-forward IR-UWB systems - Hamdi, Maziyar; Mietzner, Jan; Schober, Robert (IEEE Transactions on Wireless Communications, 2011)
In this paper, we propose a novel multi-hop relaying scheme to improve the performance and coverage of impulse-radio-based ultra-wideband (IR-UWB) systems. With regard to a simple practical realization, we focus on a non-coherent system setup in conjunction with amplify-and-forward (A&F) relaying. In particular, we propose to employ a multiple-differential encoding scheme at the source node and single differential decoding at each relay and at the destination node, respectively, so as to efficiently limit intersymbol- interference effects at the destination node. For a dual-hop system we derive a closedform expression for the signal-to-noise ratio (SNR) at the destination node, and for the general multi-hop case we provide a simple recursive formula for SNR calculation. Based on these SNR results, we obtain a closed-form expression for the optimal transmit power allocation to the source node and the relay for a dual-hop system and a simple recursive suboptimal power allocation scheme for the multi-hop case, which permits a semi-distributed implementation with limited feedback between nodes. Simulation results illustrate the excellent performance of the proposed multiple-differential encoding scheme with A&F relaying for both uncoded and coded transmission compared to various alternative coherent and non-coherent schemes based on A&F relaying and decode-and-forward (D&F) relaying. Furthermore, our simulations confirm the (near-)optimal performance of the proposed power allocation solutions. © 2006 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: amplify and forward (A&F) relaying; differential encoding; impulse radio (IR); multiple hops; performance analysis; power allocation; Ultra-wideband (UWB) communications

Multiple-symbol detection for photon-counting MIMO free-space optical communications - Riediger, Michael L. B.; Schober, Robert; Lampe, Lutz (IEEE Transactions on Wireless Communications, 2008)
We employ a photon-counting signal model of a multiple-input multiple-output (MIMO) free-space optical (FSO) system and investigate detection assuming the absence of channel state information (CSI) at the receiver, in moderate to strong atmospheric turbulence. The considered modulation format is on-off keying with repetition coding across the transmitters. To partially recover the performance loss associated with symbol- by-symbol detection without CSI, we consider the application of multiple-symbol detection (MSD) to equal gain combined (EGC) statistics. We develop a fast search algorithm for EGC- MSD and propose a suboptimal closed-form decision metric suitable for reduced-complexity implementation; performance results confirm that the true and suboptimal metrics perform comparably well. Significantly, the complexity of our receiver, on a per bit-decision basis, is only logarithmically dependent on the observation window length N, and is effectively independent of the size of the MIMO array. We also present the framework for a decision-feedback receiver and obtain performance expressions for the ideal case of error-free feedback; these expressions serve as an upper bound to the performance of EGC-MSD. Analytical and simulation results indicate that the system effectively realizes the diversity gains expected from a MIMO configuration and that the performance of the EGC-MSD receiver approaches the EGC with CSI lower bound with increasing N. © 2006 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Decision-feedback; Detection without channel.; Free-space optical communication; Multiple-input multiple-output (MIMO) system; Multiple-symbol detection; Photon-counting signal model; State information (CSI)

Multiple-symbol differential decision fusion for mobile wireless sensor networks - Lei, Andre; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2009)
We consider the problem of decision fusion in mobile wireless sensor networks where the channels between the sensors and the fusion center are time-variant. We assume that the sensors make independent local decisions on the M hypotheses under test and report these decisions to the fusion center using differential phase-shift keying (DPSK), so as to avoid the channel estimation overhead entailed by coherent decision fusion. For this setup we derive the optimal and three low-complexity, suboptimal fusion rules which do not require knowledge of the instantaneous fading gains. Since all these fusion rules exploit an observation window of at least two symbol intervals, we refer to them collectively as multiple-symbol differential (MSD) fusion rules. Simulation and analytical results confirm the excellent performance of the proposed MSD fusion rules and show that in fast fading channels significant performance gains can be achieved by increasing the observation window to more than two symbol intervals.
CRIS-Team Scopus Importer:2020-02-03

Multiple-symbol differential decision fusion for mobile wireless sensor networks - Lei, Andre; Schober, Robert (IEEE Transactions on Wireless Communications, 2010)
We consider the problem of decision fusion in mobile wireless sensor networks where the channels between the sensors and the fusion center are time-varying. We assume that the sensors make independent local decisions on the hypotheses under test and report these decisions to the fusion center using differential phase-shift keying (DPSK), so as to avoid the channel estimation overhead entailed by coherent decision fusion. For this setup we derive the optimal and three low-complexity, suboptimal fusion rules which do not require knowledge of the instantaneous fading gains. The suboptimal fusion rules are obtained by applying certain approximations to the optimal fusion rule and are referred to as Chair-Varshney (CV), ideal local sensors (ILS), and max-log fusion rules. Since all proposed fusion rules exploit an observation window of at least two symbol intervals, we refer to them collectively as multiple- symbol differential (MSD) fusion rules. For binary hypothesis testing, we derive performance bounds for the optimal fusion rule and exact or approximate analytical expressions for the probabilities of false alarm and detection for all three suboptimal fusion rules. Simulation and analytical results show that whereas the CV and ILS fusion rules approach the performance of the optimal fusion rule for high and low channel signal-to-noise ratios (SNRs), respectively, the max-log fusion rule performs close-to-optimal for the entire range of SNRs. Furthermore, in fast fading channels significant performance gains can be achieved for the considered MSD fusion rules by increasing the observation window to more than two symbol intervals. © 2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Data fusion; Fading channels; Multiple hypothesis testing; Multiple symbol differential detection (MSDD); Sphere decoding; Wireless sensor networks

Multiple-symbol differential detection based on combinatorial geometry - Pauli, Volker; Lampe, Lutz; Schober, Robert; Fukuda, Komei (IEEE Transactions on Communications, 2008)
In this paper, the application of combinatorial geometry to noncoherent multiple-symbol differential detection (MSDD) is considered. The resulting algorithm is referred to as CG-MSDD. Analytical expressions for the complexity of CG-MSDD are derived and it is shown that it is polynomial in the length N of the MSDD observation window if the rank of the N × N channel autocorrelation matrix is fixed, but in fact exponential in N if standard fading models are considered. Compared to popular sphere-decoder based MSDD, CG-MSDD is superior (i) in low-signal-to-noise power ratio (SNR) slow-fading channels as its complexity is independent of the SNR, (ii) as its complexity is constant, i.e., independent of the particular channel and noise realization, and (iii) asymptotically, as its complexity exponent only scales linearly with the bandwidth of the fading process. © 2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Combinatorial geometry; Fading channels; Multiple-symbol differential detection (MSDD); Sphere decoding

Multiplexing precoding scheme for STC-CPM with parametric phase discriminator IWM receiver - Sykora, Jan; Schober, Robert (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC, 2008)
A constant envelope Continuous Phase Modulation (CPM) class of Multi-Channel (MC) modulations for multiantenna transmitters is considered. Each receive antenna receives a superposition of CPM waveforms. The useful signal at the receiver spans a curved space - the Information Waveform Manifold (IWM). Particularly it has the form of a cylinder on a cylinder for 2-component CPM signals. At the receiver, we use a nonlinear preprocessor consisting of a nonlinear projector on the IWM, optional processing on the curved space, and a decoding isomorphism. A particular form of the preprocessor, the 2-component IWM phase discriminator, is analyzed. We show that the discriminator can separate individual instantaneous phases of the component CPM modulations and therefore has multiplexing capabilities with respect to the individual transmitted components. Two parallel channels are created without the need for a time domain processing since the procedure fully relies on the curved space properties of the IWM, and thus can be combined with arbitrary outer space-time coding of MC-CPM. An information theoretic analysis of the multiplexing properties based on the mutual information regions is presented. The discriminator solution has a two-fold ambiguity. We show that the discriminator provides good separation of component phases conditioned on a perfect ambiguity resolution. We propose a transmit spatial-differential precoding scheme that allows the ambiguity resolution. © 2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Multi-scale stochastic simulation for diffusive molecular communication - Noel, Adam; Cheung, Karen; Schober, Robert (2015 IEEE International Conference on Communications (ICC), 2015)
Recently, hybrid models have emerged that combine microscopic and mesoscopic regimes in a single stochastic reaction-diffusion simulation. Microscopic simulations track every individual molecule and are generally more accurate. Mesoscopic simulations partition the environment into subvolumes, track when molecules move between adjacent subvolumes, and are generally more computationally efficient. In this paper, we present the foundation of a multi-scale stochastic simulator from the perspective of molecular communication, for both mesoscopic and hybrid models, where we emphasize simulation accuracy at the receiver and efficiency in regions that are far from the communication link. Our multi-scale models use subvolumes of different sizes, between which we derive the diffusion event transition rate. Simulation results compare the accuracy and efficiency of traditional approaches with that of a regular hybrid method and with those of our proposed multi-scale methods.<br
Keywords: Computational modeling; Microscopy; Silicon; Accuracy; Receivers; Stochastic processes; Nanoscale devices

Multisource buffer-aided relay networks: Adaptive rate transmission - Islam, Toufiqul; Ikhlef, Aissa; Schober, Robert; Bhargava, Vijay (GLOBECOM - IEEE Global Telecommunications Conference, 2013)
In this paper, we consider a multisource multirelay network where relays employ buffers to store the received user data packets before forwarding them to a common destination. The transmission schedule, i.e., when each source and each relay transmit, is not a priori fixed, but rather depends on the link qualities. In particular, we consider adaptive link selection and adaptive rate transmission for the considered network. For simple three node relay networks, it was shown before that buffer-aided relaying with adaptive link selection yields significant throughput gains compared to conventional relaying protocols using a fixed transmission schedule. In this work, we consider a general multisource multirelay framework where operations are more complex and analysis is more involved. First, we consider average sum rate maximization for adaptive rate transmission and derive an adaptive link selection policy which exploits the channel state information. As fairness is an important issue in multisource networks, we also consider max-min fairness constrained throughput optimization and derive the corresponding link selection policy. Numerical results show that the proposed link selection policies yield significantly higher throughputs compared to conventional relaying schemes where source and relay transmission schedules are a-priori fixed. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Multi-user diversity gain in uplink cognitive radio systems with spectrum sensing reliability - Kim, Junsu; Shin, Yoan; Schober, Robert (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC, 2010)
In this paper, we investigate the performance of opportunistic scheduling in uplink cognitive radio (CR) systems taking into account the spectrum sensing reliability of each CR user. In uplink CR systems, each secondary transmitter (CR user) has a spectrum sensing responsibility to protect the primary system, and the secondary receiver (base station) schedules the transmission opportunity for each CR user. Unlike non-CR multi-user systems, the spectrum sensing reliability may degrade the achievable multi-user diversity (MUD) gain. We propose novel scheduling schemes taking into account the spectrum sensing reliability and data channel quality simultaneously to improve the MUD gain in uplink CR systems. ©2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Multiuser MISO UAV Communications in Uncertain Environments with No-Fly Zones: Robust Trajectory and Resource Allocation Design - Xu, Dongfang; Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (IEEE Transactions on Communications, 2020)
In this paper, we investigate robust resource allocation algorithm design for multiuser downlink multiple-input single-output (MISO) unmanned aerial vehicle (UAV) communication systems, where we account for the various uncertainties that are unavoidable in such systems and, if left unattended, may severely degrade system performance. We jointly optimize the two-dimensional (2-D) trajectory and the transmit beamforming vector of the UAV for minimization of the total power consumption. The algorithm design is formulated as a non-convex optimization problem taking into account the imperfect knowledge of the angle of departure (AoD) caused by UAV jittering, user location uncertainty, wind speed uncertainty, and polygonal no-fly zones (NFZs). Despite the non-convexity of the optimization problem, we solve it optimally by employing monotonic optimization theory and semidefinite programming relaxation which yields the optimal 2-D trajectory and beamforming policy. Since the developed optimal resource allocation algorithm entails a high computational complexity, we also propose a suboptimal iterative low-complexity scheme based on successive convex approximation to strike a balance between optimality and computational complexity. Our simulation results reveal not only the significant power savings enabled by the proposed algorithms compared to two baseline schemes, but also confirm their robustness with respect to UAV jittering, wind speed uncertainty, and user location uncertainty. Moreover, our results unveil that the joint presence of wind speed uncertainty and NFZs has a considerable impact on the UAV trajectory. Nevertheless, by counteracting the wind speed uncertainty with the proposed robust design, we can simultaneously minimize the total UAV power consumption and ensure a secure trajectory that does not trespass any NFZ.
CRIS-Team Scopus Importer:2020-06-02
Keywords: aerodynamic power consumption; disjunctive programming; monotonic optimization; multi-antenna UAV; no-fly zones; Robust trajectory design; UAV communication systems

Multi-user Scheduling Schemes for Simultaneous Wireless Information and Power Transfer - Morsi, Rania; Michalopoulos, Diomidis; Schober, Robert (International Conference on Communications (ICC), 2014)
In this paper, the downlink multi-user scheduling problem is studied for a time-slotted system with simultaneous wireless information and power transfer. In particular, in each time slot, a single user is scheduled to receive information, while the remaining users opportunistically harvest the ambient radio frequency (RF) energy. We devise novel scheduling schemes in which the tradeoff between the users' ergodic capacities and their average amount of harvested energy can be controlled. To this end, two fair scheduling schemes used in information-only transfer systems are modified. First, proportionally fair maximum normalized signal-to-noise ratio (N-SNR) scheduling is modified by scheduling the user having the jth ascendingly ordered (rather than the maximum) N-SNR. We refer to this scheme as order-based N-SNR scheduling. Second, conventional equal-throughput (ET) fair scheduling is modified by scheduling the user having the minimum moving average throughput among the set of users whose N-SNR orders fall into a certain set of allowed orders Sa (rather than the set of all users). We refer to this scheme as order-based ET scheduling. The feasibility conditions required for the users to achieve ET with this scheme are also derived. It is shown that the smaller the selection order j for the order-based N-SNR scheme, and the lower the orders in Sa for the order-based ET scheme, the higher the average amount of energy harvested by the users at the expense of a reduction in their ergodic capacities. The performance of the considered scheduling schemes is analyzed for independent and non-identically distributed (i.n.d.) Ricean fading channels, and closed-form results for the special case of i.n.d. Rayleigh fading are provided.

Multiuser Scheduling Schemes for Simultaneous Wireless Information and Power Transfer Over Fading Channels - Morsi, Rania; Michalopoulos, Diomidis; Schober, Robert (IEEE Transactions on Wireless Communications, 2015)
Radio-frequency (RF) energy harvesting presents a viable solution to prolong the lifetime of wireless communication devices. In this paper, we study downlink multiuser scheduling for a time-slotted system with simultaneous wireless information and power transfer. In particular, in each time slot, a single user is scheduled to receive information, whereas the remaining users opportunistically harvest the ambient RF energy. We devise novel online scheduling schemes in which the tradeoff between the users' ergodic rates and their average amount of harvested energy can be controlled. In particular, we modify the well-known maximum signal-to-noise ratio (SNR) and maximum normalized-SNR (N-SNR) schedulers by scheduling the user whose SNR/N-SNR has a certain ascending order (selection order) rather than the maximum one. We refer to these new schemes as order-based SNR/N-SNR scheduling and show that the lower the selection order, the higher the average amount of harvested energy in the system at the expense of a reduced ergodic sum rate. The order-based N-SNR scheduling scheme provides proportional fairness among the users in terms of both the ergodic achievable rate and the average harvested energy. Furthermore, we propose an order-based equal throughput (ET) fair scheduler, which schedules the user having the minimum moving average throughput out of the users whose N-SNR orders fall into a given set of allowed orders. We show that this scheme provides the users with proportionally fair average harvested energy values. In this context, we also derive feasibility conditions for achieving ET with the order-based ET scheduler. Using the theory of order statistics, the average per-user harvested energy and ergodic achievable rate of all proposed scheduling schemes are analyzed and obtained in closed form for independent and nonidentically distributed Rayleigh, Rician, Nakagami-m, and Weibull fading channels. Our closed-form analytical results are corroborated by simulations.
Keywords: Wireless information and power transfer; RF energy harvesting; multi-user scheduling; fairness

NANO-NETWORKING FOR NANO-, MICRO-, MACRO-SCALE APPLICATIONS - Demirkol, Ilker; Mitra, Urbashi; Schober, Robert; Yilmaz, H. Birkan (IEEE Communications Magazine, 2021)
CRIS-Team WoS Importer:2021-06-18

Near-Field Communications: A Tutorial Review - Liu, Yuanwei; Wang, Zhaolin; Xu, Jiaqi; Ouyang, Chongjun; Mu, Xidong; Schober, Robert (IEEE Open Journal of the Communications Society, 2023)
Extremely large-scale antenna arrays, tremendously high frequencies, and new types of antennas are three clear trends in multi-antenna technology for supporting the sixth-generation (6G) networks. To properly account for the new characteristics introduced by these three trends in communication system design, the near-field spherical-wave propagation model needs to be used, which differs from the classical far-field planar-wave one. As such, near-field communication (NFC) will become essential in 6G networks. In this tutorial, we cover three key aspects of NFC. 1) Channel Modelling: We commence by reviewing near-field spherical-wave-based channel models for spatially-discrete (SPD) antennas. Then, uniform spherical wave (USW) and non-uniform spherical wave (NUSW) models are discussed. Subsequently, we introduce a general near-field channel model for SPD antennas and a Green’s function-based channel model for continuous-aperture (CAP) antennas. 2) Beamfocusing and Antenna Architectures: We highlight the properties of near-field beamfocusing and discuss NFC antenna architectures for both SPD and CAP antennas. Moreover, the basic principles of near-field beam training are introduced. 3) Performance Analysis: Finally, we provide a comprehensive performance analysis framework for NFC. For near-field line-of-sight channels, the received signal-to-noise ratio and power-scaling law are derived. For statistical near-field multipath channels, a general analytical framework is proposed, based on which analytical expressions for the outage probability, ergodic channel capacity, and ergodic mutual information are obtained. Finally, for each aspect, topics for future research are discussed.
CRIS-Team Scopus Importer:2023-09-08
Keywords: 6G mobile communication; Antenna architecture; Antenna arrays; Antennas; beamforcusing; channel modelling; Channel models; near-field communications; performance analysis; Transmitting antennas; Tutorials; Wireless networks

Near-Field Hierarchical Beam Management for RIS-Enabled Millimeter Wave Multi-Antenna Systems - Alexandropoulos, George C.; Jamali, Vahid; Schober, Robert; Vincent Poor, H. (Proceedings of the IEEE Sensor Array and Multichannel Signal Processing Workshop, 2022)
In this paper, we present a low overhead beam management approach for near-field millimeter-wave multi-antenna communication systems enabled by Reconfigurable Intelligent Surfaces (RISs). We devise a novel variable-width hierarchical phase-shift codebook suitable for both the near- and far-field of the RIS, and present a fast alignment algorithm for the RIS phase shifts and the transceiver beamformers. Indicative performance evaluation results are shown, verifying the effectiveness of the proposed approach in comparison with various benchmark schemes.
CRIS-Team Scopus Importer:2022-08-12
Keywords: beam management; hierarchical codebook; millimeter wave; near-field regime; Reconfigurable intelligent surfaces

Network coded cooperative BICM-OFDM - Islam, Toufiqul; Nasri, Amir; Schober, Robert; Mallik, Ranjan K.; Bhargava, Vijay K. (GLOBECOM - IEEE Global Telecommunications Conference, 2011)
In this paper, we study a cooperative diversity scheme for wireless systems employing network coding and the combination of bit-interleaved coded modulation (BICM) and orthogonal frequency division multiplexing (OFDM). The considered system comprises multiple sources, one relay, and one destination. The relay decodes the signal received from all sources and performs network coding before forwarding the signal to the destination. We propose a simple cooperative maximum-ratio combining scheme for decoding at the destination which can successfully exploit the full spatial and frequency diversity offered by the channel for arbitrary number of sources and arbitrary modulation schemes. We derive a closed-form upper bound for the asymptotic worst-case pairwise error probability and the diversity gain of the considered network coded cooperative BICM-OFDM scheme. Simulation results corroborate the derived diversity gain and show the effectiveness of a low complexity decoding scheme. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Network coded multi-source cooperative communication in BICM-OFDM networks - Islam, Toufiqul; Nasri, Amir; Schober, Robert; Mallik, Ranjan K.; Bhargava, Vijay K. (IEEE Transactions on Wireless Communications, 2012)
In this paper, we study a cooperative diversity scheme for wireless systems employing network coding and the combination of bit-interleaved coded modulation (BICM) and orthogonal frequency division multiplexing (OFDM). The considered system comprises multiple sources, one relay, and one destination. The relay decodes the signal received from all sources and performs network coding before forwarding the signal to the destination. We propose a simple cooperative maximum-ratio combining scheme for the destination which can successfully exploit the full spatial and frequency diversity offered by the channel for arbitrary numbers of sources and arbitrary linear modulation schemes. Furthermore, we propose techniques to reduce the signaling overhead and the decoding complexity at the destination. To gain insight for system design, we derive a closed-form upper bound for the asymptotic worst-case pairwise error probability and the diversity gain of the considered network coded cooperative BICM-OFDM system. These analytical results reveal the influence of various system parameters, including the number of sources, the free distance of the code, and the frequency diversity of the involved links, on performance. Based on the derived analytical results, we develop schemes for optimal relay placement and power allocation. Simulation results corroborate the derived analytical results and confirm the effectiveness of the developed optimization framework. © 2002-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: BICM; cooperative diversity; network coding; OFDM

Neural network based PHY-layer key exchange for wireless communications - Karas, Dimitrios S.; Karagiannidis, George K.; Schober, Robert (IEEE International Symposium on Personal, Indoor and Mobile Radio Communications, PIMRC, 2011)
Several key exchange methods for wireless channels have been proposed in the literature. They are referred to as PHY-layer security techniques and are usually based on the channel's fading characteristics and the principle of reciprocity. In this paper, we present a novel PHY-layer security algorithm whose function is based on neural networks. Specifically, we present a full key exchange scheme which includes channel sampling and thresholding and neural network based error reconciliation. The proposed method's performance and offered security are studied through simulations and interesting conclusions are drawn about its overall utility. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

NOMA Assisted Wireless Caching: Strategies and Performance Analysis - Ding, Zhiguo; Fan, Pingzhi; Karagiannidis, George K.; Schober, Robert; Poor, H. Vincent (IEEE Transactions on Communications, 2018)
Conventional wireless caching assumes that content can be pushed to local caching infrastructure during off-peak hours in an error-free manner; however, this assumption is not applicable if local caches need to be frequently updated via wireless transmission. This paper investigates a new approach to wireless caching for situations in which the cache content has to be updated during on-peak hours. Two non-orthogonal multiple access (NOMA)-assisted caching strategies are developed, namely, the push-then-deliver strategy and the push-and-deliver strategy. In the push-then-deliver strategy, the NOMA principle is applied to push more content files to the content servers during a short time interval reserved for content pushing during on-peak hours and to provide more connectivity for content delivery, compared with the conventional orthogonal multiple access (OMA) strategy. The push-and-deliver strategy is motivated by the fact that some users' requests cannot be accommodated locally and the base station has to serve them directly. These events during the content delivery phase are exploited as opportunities for content pushing, which further facilitates the frequent update of the files cached at the content servers. It is also shown that this strategy can be straightforwardly extended to device-to-device caching, and various analytical results are developed to illustrate the superiority of the proposed caching strategies compared with OMA based schemes.<br
Keywords: NOMA; Servers; Device-to-device communication; Bandwidth; Wireless networks; Electronic mail

NOMA-Based Coexistence of Near-Field and Far-Field Massive MIMO Communications - Ding, Zhiguo; Schober, Robert; Poor, H. Vincent (IEEE Wireless Communications Letters, 2023)
This letter considers a legacy massive multiple-input multiple-output (MIMO) network, in which spatial beams have been preconfigured for near-field users, and proposes to use the non-orthogonal multiple access (NOMA) principle to serve additional far-field users by exploiting the spatial beams preconfigured for the legacy near-field users. Our results reveal that the coexistence between near-field and far-field communications can be effectively supported via NOMA, and that the performance of NOMA-assisted massive MIMO can be efficiently improved by increasing the number of antennas at the base station.
CRIS-Team Scopus Importer:2023-06-30
Keywords: Antenna arrays; Array signal processing; Base stations; beamforming; Multiaccess communication; near-field communications; Noise measurement; NOMA; Non-orthogonal multiple access (NOMA); Resource management

NOMA Meets Finite Resolution Analog Beamforming in Massive MIMO and Millimeter-Wave Networks - Ding, Zhiguo; Dai, Linglong; Schober, Robert; Poor, H. Vincent (IEEE Communications Letters, 2017)
Finite resolution analog beamforming (FRAB) has been recognized as an effective approach to reduce hardware costs in massive multiple-input multiple-output and millimeter-wave networks. However, the use of FRAB means that the beamformers are not perfectly aligned with the users' channels and multiple users may be assigned similar or even identifical beamformers. This letter shows how non-orthogonal multiple access (NOMA) can be used to exploit this feature of FRAB, in which a single FRAB-based beamformer is shared by multiple users. Both analytical and simulation results are provided to demonstrate the excellent performance achieved by this new NOMA transmission scheme.<br
Keywords: NOMA; Array signal processing; MIMO; Diversity Methods; Base stations; Fading channels; Signal to noise ratio

Non-Coherent Detection for Diffusive Molecular Communication Systems - Jamali Kooshkghazi, Vahid; Farsad, Nariman; Schober, Robert; Goldsmith, Andrea J. (IEEE Transactions on Communications, 2018)
We study non-coherent detection schemes for molecular communication (MC) systems with negligible inter-symbol interference that do not require knowledge of the channel state information (CSI). In particular, we first derive the optimal maximum likelihood (ML) multiple-symbol (MS) detector for MC systems. As a special case of the optimal MS detector, we show that the optimal ML symbol-by-symbol (SS) detector can be equivalently written in the form of a threshold-based detector, where the optimal decision threshold is constant and depends only on the statistics of the MC channel. The main challenge of the MS detector is the complexity associated with the calculation of the optimal detection metric. To overcome this issue, we propose an approximate MS detection metric that can be expressed in closed form. In addition, we develop a non-coherent decision-feedback detector, which introduces a lower detection delay compared with the optimal MS detector, and a suboptimal blind detector, which has a significantly lower complexity than the optimal MS detector. Finally, we derive analytical expressions for the bit error rate (BER) of the optimal SS detector, as well as upper and lower bounds for the BER of the optimal MS detector. Simulation results confirm the analysis and reveal the effectiveness of the proposed optimal and suboptimal detection schemes compared with the benchmark scheme that assumes perfect CSI knowledge, particularly, when the number of observations used for detection is sufficiently large. Simulation results are also presented that show the performance of the proposed detectors, when inter-symbol interference is non-negligible.<br
Keywords: Detectors; Receivers; Transmitters; Channel models; Bit error rate; Interference; Measurement

Non-coherent multiple-symbol detection for diffusive molecular communications - Jamali, Vahid; Farsad, Nariman; Schober, Robert; Goldsmith, Andrea (Proceedings of the 3rd ACM International Conference on Nanoscale Computing and Communication, ACM NANOCOM 2016, 2016)
Most of the available works on molecular communication (MC) assume that the channel state information (CSI) is perfectly known at the receiver for data detection. In contrast, in this paper, we study non-coherent multiple-symbol detection schemes which do not require knowledge of the CSI. In particular, we derive the optimal maximum likelihood (ML) multiple-symbol (MLMS) detector. Moreover, we propose an approximated detection metric and a suboptimal detector to cope with the high complexity of the optimal MLMS detector. Numerical results reveal the effectiveness of the proposed optimal and suboptimal detection schemes with respect to a baseline scheme which assumes perfect CSI knowledge, particularly when the number of observations used for detection is sufficiently large.
CRIS-Team Scopus Importer:2020-01-31

Nonlinear Equalization Approaches for Physical Layer Network Coding - Schmidt, Armin; Schober, Robert; Gerstacker, Wolfgang (IEEE Transactions on Wireless Communications, 2016)
We consider a two-way relaying system employing physical layer network coding in channels suffering from frequency-selective fading. We study decision-feedback equalization (DFE), a technique based on delayed decision-feedback sequence estimation (DDFSE), and Tomlinson-Harashima precoding (THP) approaches for mitigating the distortions introduced by the channel. For DFE, we introduce transmit filtering schemes that generate identical overall source-to-relay channel impulse responses for both source nodes, while achieving the maximum signal-to-noise ratio after equalization for the zero-forcing and the minimum mean-squared error criterion, respectively. The advocated DDFSE approach also relies on transmit filtering at the source nodes. For the THP scheme, we derive the optimal precoding filters that guarantee an intersymbol interference free source-to-relay transmission. In order to obtain a two-way relaying system, which uses the same equalization techniques in both transmission directions, we design a THP-based compromise precoding scheme for the relay-to-destination transmission. The performance of the proposed techniques is compared with that of benchmark schemes with simpler filtering/precoding, where identical overall source-to-relay channel impulse responses are enforced by straightforward but suboptimum choices for the transmit filters. Our results reveal that the developed schemes enable significant gains compared with the benchmark schemes.<br
Keywords: Relays; Decision feedback equalizers; Uplink; OFDM; Fading channels; Precoding; Wireless communication

Nonlinear Forwarding Strategy for Firefly Ultra Dense Networks with mmWave Fronthaul Links - Ackermann, Katharina; Jamali Kooshkghazi, Vahid; Gerstacker, Wolfgang; Aulin, Jocelyn; Schober, Robert (IEEE Access, 2021)
We consider the uplink of firefly ultra dense networks which combine the promising features of ultra dense deployment and centralized processing. In these networks, a large number of remote radio units which we denote as firefly nodes (FNs) are spatially distributed over an area. The mobile devices (MDs) in the coverage area are simultaneously connected via sub-6 GHz radio frequency links to all FNs. Unlike the cloud radio access network (C-RAN) architecture, in firefly ultra dense networks, the FNs forward the MDs’ data through multi-hop millimeter-wave (mmWave) links to one or multiple root nodes since the coverage radius of each mmWave link is limited. These root nodes then forward the data via optical fiber links further to a central unit (CU), where the MDs’ signals are decoded. The amount of data that is received at each FN is potentially huge, and hence, efficient signal processing is needed at each FN before the received signals can be forwarded to other FNs. Therefore, we propose a nonlinear processing strategy, which quantizes the received signals at each FN. In particular, we formulate an optimization problem for a local design strategy for the nonlinear forwarding at the FNs, and present an optimal solution by exploiting strong duality and using the Lagrangian method to convert the optimization problem into an unconstrained problem via its dual formulation. A closed-form solution for the primal variables and a bisection algorithm for finding the optimal dual variables are presented. Moreover, based on the cut-set bound, we develop an upper bound on the achievable sum rate of the considered firefly network. The proposed nonlinear forwarding strategy is shown to outperform a benchmark linear forwarding strategy and to approach the performance upper bound in relevant transmit power regimes at the expense of a higher computational complexity. Our results reveal that having more root nodes in the topology improves the performance of linear and nonlinear forwarding but requires additional optical fiber links to the CU.
CRIS-Team Scopus Importer:2021-10-01
Keywords: Cloud radio access network (C-RAN); millimeter wave (mmWave); multi-hop system; nonlinear forwarding; Optical fiber communication; Optical network units; Optimization; Radio frequency; Receiving antennas; Topology; ultra dense network (UDN); Upper bound

Non-orthogonal multiple access: Common myths and critical questions - Vaezi, Mojtaba; Schober, Robert; Ding, Zhiguo; Vincent Poor, H. (IEEE Wireless Communications, 2019)
Non-orthogonal multiple access (NOMA) has received tremendous attention for the design of radio access techniques for fifth generation (5G) wireless networks and beyond. The basic concept behind NOMA is to serve more than one user in the same resource block, for example, a time slot, subcarrier, spreading code, or space. With this, NOMA promotes massive connectivity, lowers latency, improves user fairness and spectral efficiency, and increases reliability compared to orthogonal multiple access (OMA) techniques. While NOMA has gained significant attention from the communications community, it has also been subject to several widespread misunderstandings, such as "NOMA is based on allocating higher power to users with worse channel conditions. As such, cell-edge users receive more power in NOMA and due to this biased power allocation toward celledge users inter-cell interference is more severe in NOMA compared to OMA. NOMA also compromises security for spectral efficiency." The above statements are actually false, and this article aims at identifying such common myths about NOMA and clarifying why they are not true. We also pose critical questions that are important for the effective adoption of NOMA in 5G and beyond and identify promising research directions for NOMA, which will require intense investigation in the future.
CRIS-Team Scopus Importer:2019-11-12

Nonorthogonal transmission and noncoherent fusion of censored decisions - Yiu, Simon; Schober, Robert (IEEE Transactions on Vehicular Technology, 2009)
In this paper, we consider the binary-distributed hypothesis testing problem, where a wireless sensor network (WSN) is used to determine the true state of nature. We propose a novel signaling scheme where signature vectors (SVs) are used to transmit censored sensor decisions to the fusion center (FC). In particular, the length of the SVs is chosen to be smaller than the number of sensors, resulting in nonorthogonal sensor channels and allowing a desirable tradeoff between bandwidth and power efficiency in WSNs. We consider deterministic SVs that are assumed to be known to the FC and random SVs that are unknown to the FC. For both cases, the optimum noncoherent fusion rules are derived, assuming independent Ricean fading sensor-FC channels. Since the complexity of these optimum fusion rules is prohibitively large, even for WSNs of moderate size, we also consider a low-complexity suboptimum energy-based fusion rule and show that it is equivalent to the optimum fusion rules under certain conditions. Furthermore, we calculate the system probabilities of detection and false alarm for the energy-based fusion rule for both deterministic and random SVs. Numerical and simulation results show that with the proposed nonorthogonal signaling scheme, significant improvements in bandwidth efficiency are possible at the expense of only a small loss in power efficiency. © 2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Data fusion; Fading channels; Nonorthogonal signaling; Wireless sensor networks (WSNs)

No-Pain No-Gain: DRL Assisted Optimization in Energy-Constrained CR-NOMA Networks - Ding, Zhiguo; Schober, Robert; Vincent Poor, H. (IEEE Transactions on Communications, 2021)
This paper applies machine learning to optimize the transmission policy of cognitive radio inspired non-orthogonal multiple access (CR-NOMA) networks, where time-division multiple access (TDMA) is used to serve multiple primary users and an energy-constrained secondary user is admitted to the primary users’ time slots via NOMA. During each time slot, the secondary user performs the two tasks: data transmission and energy harvesting based on the signals received from the primary users. The goal of the paper is to maximize the secondary user’s long-term throughput, by optimizing its transmit power and the time-sharing coefficient for its two tasks. The long-term throughput maximization problem is challenging due to the need for making decisions that yield long-term gains but might result in short-term losses. For example, when in a given time slot, a primary user with large channel gains transmits, intuition suggests that the secondary user should not carry out data transmission due to the strong interference from the primary user but perform energy harvesting only, which results in zero data rate for this time slot but yields potential long-term benefits. In this paper, a deep reinforcement learning (DRL) approach is applied to emulate this intuition, where the deep deterministic policy gradient (DDPG) algorithm is employed together with convex optimization. Our simulation results demonstrate that the proposed DRL assisted NOMA transmission scheme can yield significant performance gains over two benchmark schemes.
CRIS-Team Scopus Importer:2021-08-06
Keywords: and energy harvesting; cognitive radio communications; deep reinforcement learning; Non-orthogonal multiple access

Novel protocol with improved outage probability performance for the fading two-hop half-duplex relay channel - Zlatanov, Nikola; Jamali Kooshkghazi, Vahid; Wing Kwan Ng, Derrick; Schober, Robert (2016 IEEE International Conference on Communications (ICC), 2016)
Based on the coding scheme recently introduced in [1], we propose new communication protocols with improved outage probability performance for the fading two-hop half-duplex (HD) relay channel. This channel is comprised of a source, a HD relay, and a destination, where a direct source-destination link does not exist. For this channel, we assume that the transmitting nodes do not have transmitter-side channel state information and therefore have to transmit with fixed rate. As a result, outages may occur. We propose protocols for the cases when feedback from receiving to transmitting nodes is not possible and restricted to one bit of feedback information per time slot, respectively. In the proposed protocols, the relay's silent symbol intervals, when the relay receives, carry information which improves the reliability of both the source-relay and relay-destination links. In contrast, in existing protocols, the relay's silent symbol intervals, when the relay receives, are a priori known to the destination and thereby cannot carry information. Our numerical results show that the proposed protocols achieve significant performance gains in terms of outage probability compared to existing protocols in the literature. These gains are only the result of using a different coding scheme and not of utilizing more resources than existing protocols.<br
Keywords: Relays; Protocols; High definition Video; Fading channels; Encoding; Time-frequency Analysis; Buffer storage

Novel Radar-based Calibration Techniques for Massive MIMO Arrays - Carlowitz, Christian; Gröschel, Patrick; Schober, Robert; Vossiek, Martin (IMS 2017 Workshop on Massive MIMO and its 5G Related Applications, 2017)

Novel Receiver for Superparamagnetic Iron Oxide Nanoparticles in a Molecular Communication Setting - Bartunik, Max; Lübke, Maximilian; Unterweger, Harald; Alexiou, Christoph; Meyer, Sebastian; Ahmed, Doaa; Fischer, Georg; Wicke, Wayan; Jamali Kooshkghazi, Vahid; Schober, Robert; Kirchner, Jens (Proceedings of the 6th ACM International Conference on Nanoscale Computing and Communication, NANOCOM 2019, 2019)
Superparamagnetic iron oxide nanoparticles (SPIONs) have recently been introduced as information carriers in a testbed for molecular communication (MC) in duct flow. Here, a new receiver for this testbed is presented, based on the concept of a Wheatstone bridge. The capability for a reliable transmission using the testbed and detection of the proposed receiver was evaluated by sending a text message and a 80 bit random sequence at a bit rate of 1/s, which resulted in a bit error rate of 0 %. Furthermore, the sensitivity of the device was assessed by a dilution series, which gave a limit of detectability of peaks between 0:1 to 0:5 mg/mL. Compared to the commercial susceptometer that was previously used as receiver, the new detector provides an increased sampling rate of 100 samples/s and flexibility in the dimensions of the propagation channel. Furthermore, it allows to implement both single-ended and differential signaling in SPION-bases MC testbeds <br
CRIS-Team Scopus Importer:2019-10-29
Keywords: Molecular communication; superparamagnetic iron oxide nanoparticles; SPION; differtial signaling; receiver

Olfaction-inspired MCs: Molecule Mixture Shift Keying and Cross-Reactive Receptor Arrays - Jamali, Vahid; Loos, Helene; Büttner, Andrea; Schober, Robert; Vincent Poor, H. (IEEE Transactions on Communications, 2023)
In this paper, we propose a novel concept for engineered molecular communication (MC) systems inspired by animal olfaction. We focus on a multi-user scenario where several transmitters wish to communicate with a central receiver. We assume that each transmitter employs a unique mixture of different types of signaling molecules to represent its message and the receiver is equipped with an array comprising R different types of receptors in order to detect the emitted molecule mixtures. The design of an MC system based on orthogonal molecule-receptor pairs implies that the hardware complexity of the receiver linearly scales with the number of signaling molecule types Q (i.e., R = Q). Natural olfaction systems avoid such high complexity by employing arrays of cross-reactive receptors, where each type of molecule activates multiple types of receptors and each type of receptor is predominantly activated by multiple types of molecules albeit with different activation strengths. For instance, the human olfactory system is believed to discriminate several thousands of chemicals using only a few hundred receptor types, i.e., Q ≫ R. Motivated by this observation, we first develop an end-to-end MC channel model that accounts for the key properties of olfaction. Subsequently, we present the proposed transmitter and receiver designs. In particular, given a set of signaling molecules, we develop algorithms that allocate molecules to different transmitters and optimize the mixture alphabet for communication. Moreover, we formulate the molecule mixture recovery as a convex compressive sensing problem which can be efficiently solved via available numerical solvers. Finally, we present a comprehensive set of simulation results to evaluate the performance of the proposed MC designs revealing interesting insights regarding the design parameters. For instance, we show that mixtures comprising few types of molecules are best suited for communication since they can be more reliably detected by the cross-reactive array than one type of molecule or mixtures of many molecule types.
CRIS-Team Scopus Importer:2023-03-03
Keywords: compressive sensing; Engineered molecular communication; generalist receptors; molecule mixture modulation; odor; pheromone; transmitter and receiver design

Online resource allocation for energy harvesting downlink MIMO systems with finite-alphabet inputs - Zeng, Weiliang; Zheng, Yahong Rosa; Schober, Robert (2015 IEEE International Conference on Communications (ICC), 2015)
This paper proposes an online resource allocation algorithm for weighted sum rate maximization in energy harvesting downlink multiuser multiple-input multiple-output (MIMO) systems. Taking into account the discrete nature of the modulation and coding rates (MCRs) used in practice, we formulate a stochastic dynamic programming (SDP) problem to jointly design the MIMO precoders, select the MCRs, assign the subchannels, and optimize the energy consumption over multiple time slots with causal and statistical energy arrival information and statistical channel state information. Solving this high-dimensional SDP entails several difficulties: the SDP has a nonconcave objective function, the optimization variables are of mixed binary and continuous types, and the number of optimization variables is on the order of thousands. We propose a new method to solve this NP-hard SDP by decomposing the high-dimensional SDP into an equivalent three-layer optimization problem and show that efficient algorithms can be used to solve each layer separately. The decomposition reduces the computational burden and breaks the curse of dimensionality.<br
Keywords: MIMO; Energy consumption; Transmitters; Optimization; Wireless communication; Downlink; Joints

Online Resource Allocation for Energy Harvesting Downlink Multiuser Systems: Precoding With Modulation, Coding Rate, and Subchannel Selection - Zeng, Weiliang; Zheng, Yahong Rosa; Schober, Robert (IEEE Transactions on Wireless Communications, 2015)
This paper proposes an online resource allocation algorithm for weighted sum rate maximization in energy harvesting downlink multiuser multiple-input-multiple-output (MIMO) systems, where the base station transmitter is powered by both a regular energy source and an energy buffer that is connected to an energy harvester. Taking into account the discrete nature of the modulation and coding rates (MCRs) used in practice, we formulate a stochastic dynamic programming (SDP) problem to jointly design the MIMO precoders, select the MCRs, assign the subchannels, and optimize the energy consumption over multiple time slots with causal and statistical energy arrival information and statistical channel state information. Solving this high-dimensional SDP entails several difficulties: the SDP has a nonconcave objective function, the optimization variables are of mixed binary and continuous types, and the number of optimization variables is on the order of thousands. We propose a new method to solve this NP-hard SDP by decomposing the high-dimensional SDP into an equivalent three-layer optimization problem and develop efficient algorithms to solve each layer separately. The decomposition reduces the computational burden and breaks the curse of dimensionality successfully. We analyze the complexity of the proposed algorithm and demonstrate the performance gains based on numerical examples.<br
Keywords: MIMO; Resource management; Energy consumption; Wireless communication; Transmitters; Joints; Optimization

On MIMO-OFDM with coding and loading - Chen, Harry Z. B.; Lampe, Lutz; Schober, Robert (EURASIP Journal on Wireless Communications and Networking, 2008)
Orthogonal frequency-division multiplexing (OFDM) with multiple transmit and multiple receive antennas (MIMO-OFDM) is considered a candidate for high-data rate communication in various existing and forthcoming system standards. To achieve the usually desired low frame and bit error rates, MIMO-OFDM should be combined with adaptive bit loading (ABL) and forward error correction (FEC) coding, where the former is particularly apt for moderate mobility as considered in, for example, IEEE 802.16e OFDM systems. In this paper, we investigate "simple" coding schemes and their combination with ABL for MIMO-OFDM. In particular, we consider wrapped space-frequency coding (WSFC) and coded V-BLAST with ABL and optimize both schemes to mitigate error propagation inherent in the detection process. Simulation results show that bit-loaded WSFC and V-BLAST optimized for coded MIMO-OFDM achieve excellent error rate performances, close to that of quasioptimal MIMO-OFDM based on singular value decomposition of the channel, while their feedback requirements for loading are low. Copyright © 2008 Harry Z. B. Chen et al.
CRIS-Team Scopus Importer:2020-02-03

On noncoherent receivers for DSTM in spatially correlated fading - Zhu, Cindy; Yiu, Simon; Schober, Robert (IEEE Transactions on Communications, 2009)
In this letter, we derive a multiple-symbol differential detection (MSDD) and a novel MSDD-based decision-feedback differential detection (MS-DFDD) receiver for differential space-time modulation transmitted over spatially correlated multiple-input multiple-output fading channels. We show that MS-DFDD outperforms previously proposed DFDD schemes that are based on scalar and vector prediction (SP-DFDD and VP-DFDD). In addition, we prove that at high signal-to-noise ratio (SNR) VP-DFDD is equivalent to SP-DFDD and thus fails to properly exploit the spatial fading correlations. © 2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Correlated fading channels; Differential phase-shift keying; MIMO; Noncoherent receivers; Space-time coding

On-Off Transmission Policy for Wireless Powered Communication with Energy Storage - Morsi, Rania; Michalopoulos, Diomidis; Schober, Robert (2014)
In this paper, we consider an energy harvesting (EH) node which harvests energy from a radio frequency (RF) signal broadcasted by an access point (AP) in the downlink (DL). The node stores the harvested energy in an energy buffer and uses the stored energy to transmit data to the AP in the uplink (UL). We consider a simple transmission policy, which accounts for the fact that, in practice, the EH node may not have knowledge of the EH profile nor of the UL channel state information. In particular, in each time slot, the EH node transmits with either a constant desired power or remains silent if not enough energy is available in its energy buffer. For this simple policy, we use the theory of discrete-time continuous-state Markov chains to analyze the limiting distribution of the stored energy for finite-and infinitesize energy buffers. Moreover, we take into account imperfections of the energy buffer and the circuit power consumption of the EH node. For a Rayleigh fading DL channel, we provide the limiting distribution of the energy buffer content in closed form. In addition, we analyze the average error rate and the outage probability of a Rayleigh faded UL channel and show that the diversity order is not affected by the finite capacity of the energy buffer. Our results reveal that, for medium to high signal-to-noise ratio (SNRs), the optimal target transmit power of the EH node is less than the average harvested power and increases with the capacity of the energy buffer.
Keywords: data communication; energy harvesting; energy storage; Markov processes; probability; radio networks; Rayleigh channels; telecommunication network reliability; telecommunication power management; on-off transmission policy; wireless powered communication; energy storage; energy harvesting; EH; radio frequency signal; RF signal; access point; AP; downlink; data transmission; uplink; UL channel state information; discrete-time continuous-state Markov chain; circuit power consumption; Rayleigh fading DL channel; energy buffer distribution; average error rate; outage probability; Rayleigh fading UL channel; signal-to-noise ratio; SNR; Limiting; Buffer storage; Energy storage; Rayleigh channels; Probability density function; Approximation methods

On-off transmission policy for wireless powered communication with energy storage - Morsi, Rania; Michalopoulos, Diomidis; Schober, Robert (Conference Record - Asilomar Conference on Signals, Systems and Computers, 2015)
In this paper, we consider an energy harvesting (EH) node which harvests energy from a radio frequency (RF) signal broadcasted by an access point (AP) in the downlink (DL). The node stores the harvested energy in an energy buffer and uses the stored energy to transmit data to the AP in the uplink (UL). We consider a simple transmission policy, which accounts for the fact that, in practice, the EH node may not have knowledge of the EH profile nor of the UL channel state information. In particular, in each time slot, the EH node transmits with either a constant desired power or remains silent if not enough energy is available in its energy buffer. For this simple policy, we use the theory of discrete-time continuous-state Markov chains to analyze the limiting distribution of the stored energy for finite- and infinite-size energy buffers. Moreover, we take into account imperfections of the energy buffer and the circuit power consumption of the EH node. For a Rayleigh fading DL channel, we provide the limiting distribution of the energy buffer content in closed form. In addition, we analyze the average error rate and the outage probability of a Rayleigh faded UL channel and show that the diversity order is not affected by the finite capacity of the energy buffer. Our results reveal that, for medium to high signal-to-noise ratio (SNRs), the optimal target transmit power of the EH node is less than the average harvested power and increases with the capacity of the energy buffer.
CRIS-Team Scopus Importer:2020-01-31

On space-time coding for free-space optical systems - Bayaki, Ehsan; Schober, Robert (IEEE Transactions on Communications, 2010)
Atmospheric turbulence-induced fading is one of the main impairments affecting free-space optics (FSO) communications. In this paper, we consider FSO systems with intensity modulation and direct detection (IM/DD) and derive a closed- form expression for the asymptotic pairwise error probability of general FSO space-time codes (STCs) for two lasers and an arbitrary number of photodetectors for channels suffering from Gamma-Gamma fading. Furthermore, we provide a simple design criterion for FSO STCs which is used to establish the quasi-optimality of previously proposed FSO repetition codes. We also show that STCs optimized for RF systems achieve full diversity in FSO systems but are suboptimal as far as the coding gain is concerned. Simulation results confirm the analytical findings of this paper. © 2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Intensity modulation and direct detection; gamma-gamma fading; Repetition coding; Space-time coding; free-space optical systems

On the Application of NOMA to Wireless Caching - Ding, Zhiguo; Fan, Pingzhi; Karagiannidis, George K.; Schober, Robert; Poor, H. Vincent (2018 IEEE International Conference on Communications (ICC), 2018)
This paper investigates the impact of non-orthogonal multiple access (NOMA) on wireless caching. Two NOMA caching strategies are developed, namely the push-then- deliver strategy and the push-and-deliver strategy, with the objective to improve the spectral efficiency of the two caching phases, content pushing and content delivery, compared to the conventional orthogonal multiple-access (OMA) based strategy. Both analytical and computer simulation results are provided to demonstrate the performance of the proposed caching strategies and verify the accuracy of the developed analytical results.<br
Keywords: NOMA; Servers; Wireless communication; Resource management; Reliability; Power system reliability; Probability

On the Capacity of SWIPT Systems with a Nonlinear Energy Harvesting Circuit - Morsi, Rania; Jamali Kooshkghazi, Vahid; Ng, Derrick Wing Kwan; Schober, Robert (IEEE International Conference on Communications (ICC), 2018)
In this paper, we study information-theoretic limits for simultaneous wireless information and power transfer (SWIPT) systems employing a practical nonlinear radio frequency (RF) energy harvesting (EH) receiver. In particular, we consider a three-node system with one transmitter that broadcasts a common signal to separated information decoding (ID) and EH receivers. Owing to the nonlinearity of the EH receiver circuit, the efficiency of wireless power transfer depends significantly on the waveform of the transmitted signal. In this paper, we aim to answer the following fundamental question: What is the optimal input distribution of the transmit waveform that maximizes the rate of the ID receiver for a given required harvested power at the EH receiver? In particular, we study the capacity of a SWIPT system impaired by additive white Gaussian noise (AWGN) under average-power (AP) and peak-power (PP) constraints at the transmitter and an EH constraint at the EH receiver. Using Hermite polynomial bases, we prove that the optimal capacity-achieving input distribution that maximizes the rate-energy region is unique and discrete with a finite number of mass points. Our numerical results show that the rate-energy region is enlarged for a larger PP constraint and that the rate loss of the considered SWIPT system compared to the AWGN channel without EH receiver is reduced by increasing the AP budge
Keywords: AWGN channels; channel capacity; decoding; energy harvesting; optimisation; polynomials; radio receivers; radiofrequency power transmission; telecommunication power supplies; rate-energy region; nonlinear energy harvesting circuit; information-theoretic limits; wireless power transfer; SWIPT system; nonlinear radio frequency energy harvesting receiver; information decoding; additive white Gaussian noise; average-power constraint; peak-power constraint; Hermite polynomial; simultaneous wireless information and power transfer; Receivers; Radio frequency; Integrated circuit modeling; Rectennas; Transmitters; RF signals; AWGN channels

On the Capacity of the Two-Hop Half-Duplex Relay Channel - Zlatanov, Nikola; Jamali Kooshkghazi, Vahid; Schober, Robert (2015 IEEE Global Communications Conference (GLOBECOM), 2015)
Although extensively investigated, the capacity of the two-hop half-duplex (HD) relay channel is not fully understood. In particular, a capacity expression which can be evaluated straightforwardly is not available and an explicit coding scheme which achieves the capacity is not known either. In this paper, we derive a new expression for the capacity of the two-hop HD relay channel based on a simplified converse. Compared to previous results, this capacity expression can be easily evaluated. Moreover, we propose an explicit coding scheme which achieves the capacity. To achieve the capacity, the relay does not only send information to the destination by transmitting information-carrying symbols but also with the zero symbols resulting from the relay's silence during reception. As examples, we compute the capacities of the two-hop HD relay channel for the cases when the source-relay and relay-destination links are both binary-symmetric channels (BSCs) and additive white Gaussian noise (AWGN) channels, respectively, and numerically compare the capacities with the rates achieved by conventional relaying where the relay receives and transmits in a codeword-by-codeword fashion and switches between reception and transmission in a strictly alternating manner. Our numerical results show that the capacities of the two-hop HD relay channel for BSC and AWGN links are significantly larger than the rates achieved with conventional relaying.<br
Keywords: Relays; High definition video; Encoding; Entropy; AWGN channels; Mutual information; Switches

On the Design of Matched Filters for Molecule Counting Receivers - Jamali Kooshkghazi, Vahid; Ahmadzadeh, Arman; Schober, Robert (IEEE Communications Letters, 2017)
In this letter, we design matched filters for diffusive molecular communication systems taking into account the following impairments: signal-dependent diffusion noise, inter-symbol interference (ISI), and external interfering molecules. The receiver counts the number of observed molecules several times within one symbol interval and employs linear filtering to detect the transmitted data. We derive the optimal matched filter by maximizing the expected signal-to-interference-plus-noise ratio of the decision variable. Moreover, we show that for the special case of an ISI-free channel, the matched filter reduces to a simple sum detector and a correlator for the channel impulse response for the diffusion noise-limited and (external) interference-limited regimes, respectively. Our simulation results reveal that the proposed matched filter considerably outperforms the benchmark schemes available in literature, especially when ISI is severe.<br
Keywords: Interference; Receivers; Signal to noise ratio; Optimal matching; Correlators; Transmitters; Detectors

On the design of MIMO-NOMA downlink and uplink transmission - Ding, Zhiguo; Schober, Robert; Poor, H. Vincent (2016 IEEE International Conference on Communications (ICC), 2016)
In this paper, a novel MIMO-NOMA framework for downlink and uplink transmission is proposed by applying the concept of signal alignment. By using stochastic geometry, closed-form analytical results are developed to facilitate the performance evaluation of the proposed framework for randomly deployed users and interferers. The impact of different power allocation strategies, such as fixed power allocation and cognitive radio inspired power allocation, on the performance of MIMO-NOMA is also investigated. Computer simulation results are provided to demonstrate the performance of the proposed framework and the accuracy of the developed analytical results.<br
Keywords: Base stations; NOMA; Interference; Uplink; Resource management; Downlink; Signal to noise ratio

On the effect of outdated channel estimation in variable gain relaying: Error performance and PAPR - Hadzi-Velkov, Zoran; Michalopoulos, Diomidis S.; Karagiannidis, George K.; Schober, Robert (IEEE Transactions on Wireless Communications, 2013)
For the conventional three-node amplify-and-forward (AF) relaying setup, we investigate the effect of imperfect channel state information (CSI) at the relay on the overall performance. In particular, we consider variable gain (a.k.a, CSI-assisted) AF relaying and derive expressions for the outage and the error probability for the case where the relay gain is adjusted based on outdated estimates of the source-relay channel, when operating over Nakagami-m fading. For the case of Rayleigh fading in the source-relay link, we show that the results can be extended to the versatile case of imperfect CSI, where the estimation error is caused either by additive white Gaussian noise or by quantization noise. The obtained expressions are functions of the correlation coefficient between the actual source-relay channel and its corresponding estimate. We also optimize the power allocation for minimization of the outage probability under a total transmit power constraint. Numerical results reveal a considerable degradation of the overall performance, when CSI acquisition is not perfect. Moreover, it is shown that the average relay transmit power is affected when the CSI is outdated, a fact which impacts the design of variable gain relaying in practice. Since outdated CSI leads to fluctuations of the relay transmit power, we derive expressions for the complementary cumulative distribution function (CCDF) of the peak-to-average-power ratio (PAPR) at the relay. By comparing the error probability and the CCDF of the PAPR of variable gain relaying with those of fixed gain relaying, we shed some light onto the following question: How reliable has the instantaneous CSI at the relay to be for variable gain relaying to be preferable over fixed gain relaying, which requires only statistical CSI? © 2002-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: imperfect channel estimation; Nakagami-m fading; outage and error probability; peak-to-average power ratio (PAPR); Wireless relaying

On the impact of phase shifting designs on IRS-NOMA - Ding, Zhiguo; Schober, Robert; Poor, H. Vincent (IEEE Wireless Communications Letters, 2020)
In this letter, the impact of two phase shifting designs, namely coherent phase shifting and random discrete phase shifting, on the performance of intelligent reflecting surface (IRS) assisted non-orthogonal multiple access (NOMA) is studied. Analytical and simulation results are provided to show that the two designs achieve different tradeoffs between reliability and complexity. To further improve the reception reliability of the random phase shifting design, a low-complexity phase selection scheme is also proposed in this letter.
CRIS-Team Scopus Importer:2020-10-30
Keywords: intelligent reflecting surface (IRS); Non-orthogonal multiple access (NOMA); phase shifting designs

On the Outage Performance of Non-Orthogonal Multiple Access With 1-bit Feedback - Xu, Peng; Yuan, Yi; Ding, Zhiguo; Dai, Xuchu; Schober, Robert (IEEE Transactions on Wireless Communications, 2016)
In this paper, the outage performance of downlink non-orthogonal multiple access (NOMA) is investigated for the case where each user feeds back only one bit of its channel state information (CSI) to the base station. Conventionally, opportunistic one-bit feedback has been used in fading broadcast channels to select only one user for transmission. In contrast, the considered NOMA scheme adopts superposition coding to serve all users simultaneously in order to improve user fairness. A closed-form expression for the common outage probability (COP) is derived, along with the optimal diversity gains under two types of power constraints. Particularly, it is demonstrated that the diversity gain under a long-term power constraint is twice as large as that under a short-term power constraint. Furthermore, we study dynamic power allocation optimization for minimizing the COP, based on one-bit CSI feedback. This problem is challenging, since the objective function is non-convex; however, under the short-term power constraint, we demonstrate that the original problem can be transformed into a set of convex problems. Under the long-term power constraint, an asymptotically optimal solution is obtained for high signal-to-noise ratio.<br
Keywords: NOMA; Fading channels; Base stations; Resource management; Encoding; Downlink; Transmitters

On the performance of non-coherent transmission schemes with equal-gain combining in correlated generalized K-fading - Zhu, Cindy; Mietzner, Jan; Schober, Robert (IEEE Vehicular Technology Conference, 2009)
The generalized K-fading model, characterized by two parameters, k and m, was recently shown to accurately capture the effects of composite shadowing and multipath fading in wireless communication systems. In this paper, we derive closed-form expressions for the bit error probability of two non-coherent transmission schemes over L diversity branches being subject to generalized K-fading. Specifically, focus is on binary differential phase-shift keying (DPSK) and binary non-coherent frequency-shift keying (FSK) modulation with equal-gain combining at the receiver. We also derive expressions for the asymptotic diversity order, which reveal an interesting interplay between the two fading parameters k and m. Moreover, we show that the diversity order of the considered non-coherent transmission schemes is the same as in the case of coherent transmission. Finally, numerical performance results are presented, and our analytical results are corroborated by means of Monte-Carlo simulations. © 2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03

On the performance of non-coherent transmission schemes with equal-gain combining in generalized Κ-fading - Zhu, Cindy; Mietzner, Jan; Schober, Robert (IEEE Transactions on Wireless Communications, 2010)
The generalized Κ-fading model, characterized by two parameters, κ and m, is a very versatile model and was recently shown to accurately capture the effects of composite shadowing and multipath fading in wireless communication systems. Furthermore, it can be used to model cascade multipath fading, which is relevant in, e.g., mobile-to-mobile communication scenarios. In this paper, we derive closed-form expressions for the bit error probability of two non-coherent transmission schemes over L diversity branches being subject to generalized Κfading. Specifically, focus is on binary differential phase-shift keying (DPSK) and binary non-coherent frequency-shift keying (FSK) modulation with (post-detection) equal-gain combining at the receiver. We also discuss the extension of our results to M-ary modulation schemes. Considering both independent and correlated fading across the L branches, we derive expressions for the asymptotic diversity order, which reveal an interesting interplay between the two fading parameters κ and m. Moreover, we show that the diversity order of the considered non-coherent transmission schemes is the same as in the case of a coherent transmission scheme. Finally, numerical performance results are presented, and our analytical results are corroborated by means of Monte-Carlo simulations. © 2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Κ-fading; Cascade fading; Diversity reception; Fading channels; Non-coherent transmission; Performance analysis; Shadowing

On the Performance of Wireless Powered Communication With Non-linear Energy Harvesting - Morsi, Rania; Boshkovska, Elena; Ramadan, Esmat; Ng, Derrick Wing Kwan; Schober, Robert (International Workshop on Signal Processing Advances in Wireless Communications (SPAWC), 2017)
In this paper, we analyze the performance of a time-slotted multi-antenna wireless powered communication (WPC) system, where a wireless device first harvests radio frequency (RF) energy from a power station (PS) in the downlink to facilitate information transfer to an information receiving station (IRS) in the uplink. The main goal of this paper is to provide insights and guidelines for the design of practical WPC systems. To this end, we adopt a recently proposed parametric non-linear RF energy harvesting (EH) model, which has been shown to accurately model the end-to-end non-linearity of practical RF EH circuits. In order to enhance the RF power transfer efficiency, maximum ratio transmission is adopted at the PS to focus the energy signals on the wireless device. Furthermore, at the IRS, maximum ratio combining is used. We analyze the outage probability and the average throughput of information transfer, assuming Nakagamim fading uplink and downlink channels. Moreover, we study the system performance as a function of the number of PS transmit antennas, the number of IRS receive antennas, the transmit power of the PS, the fading severity, the transmission rate of the wireless device, and the EH time duration. In addition, we obtain a fixed point equation for the optimal transmission rate and the optimal EH time duration that maximize the asymptotic throughput for high PS transmit powers. All analytical results are corroborated by simulations.

On the statistics of reaction-diffusion simulations for molecular communication - Noel, Adam; Cheung, Karen C.; Schober, Robert (Proceedings of the 2nd ACM International Conference on Nanoscale Computing and Communication, ACM NANOCOM 2015, 2015)
A molecule traveling in a realistic propagation environment can experience stochastic interactions with other molecules and the environment boundary. The statistical behavior of some isolated phenomena, such as dilute unbounded molecular diffusion, are well understood. However, the coupling of multiple interactions can impede closed-form analysis, such that simulations are required to determine the statistics. This paper compares the statistics of molecular reactiondiff usion simulation models from the perspective of molecular communication systems. Microscopic methods track the location and state of every molecule, whereas mesoscopic methods partition the environment into virtual containers that hold molecules. The properties of each model are described and compared with a hybrid of both models. Simulation results also assess the accuracy of Poisson and Gaussian approximations of the underlying Binomial statistics.
CRIS-Team Scopus Importer:2020-01-31

Optical IRSs: Power Scaling Law, Optimal Deployment, and Comparison with Relays - Ajam, Hedieh; Najafi, Marzieh; Jamali, Vahid; Schober, Robert (IEEE Transactions on Communications, 2023)
The line-of-sight (LOS) requirement of free-space optical (FSO) systems can be relaxed by employing optical relays or optical intelligent reflecting surfaces (IRSs). In this paper, we show that the power reflected from FSO IRSs and collected at the receiver (Rx) lens may scale quadratically or linearly with the IRS size or may saturate at a constant value. We analyze the power scaling law for optical IRSs and unveil its dependence on the wavelength, transmitter (Tx)-to-IRS and IRS-to-Rx distances, beam waist, and Rx lens size. We also consider the impact of linear, quadratic, and focusing phase shift profiles across the IRS on the power collected at the Rx lens for different IRS sizes. Our results reveal that surprisingly the powers received for the different phase shift profiles are identical, unless the IRS operates in the saturation regime. Moreover, IRSs employing the focusing (linear) phase shift profile require the largest (smallest) size to reach the saturation regime. We also compare optical IRSs in different power scaling regimes with optical relays in terms of the outage probability, diversity and coding gains, and optimal placement. Our results show that, at the expense of a higher hardware complexity, relay-assisted FSO links yield a better outage performance at high signal-to-noise-ratios (SNRs), but optical IRSs can achieve a higher performance at low SNRs. Moreover, while it is optimal to place relays equidistant from Tx and Rx, the optimal location of optical IRSs depends on the phase shift profile and the power scaling regime they operate in.
CRIS-Team Scopus Importer:2023-11-24
Keywords: Laser beams; Lenses; Optical network units; Optical receivers; Optical saturation; Optical transmitters; Relays

Optimal 3D-Trajectory Design and Resource Allocation for Solar-Powered UAV Communication Systems - Sun, Yan; Xu, Dongfang; Ng, Derrick Wing Kwan; Dai, Linglong; Schober, Robert (IEEE Transactions on Communications, 2019)
n this paper, we investigate the resource allocation algorithm design for multicarrier solar-powered unmanned aerial vehicle (UAV) communication systems. In particular, the UAV is powered by the solar energy enabling sustainable communication services to multiple ground users. We study the joint design of the 3D aerial trajectory and the wireless resource allocation for maximization of the system sum throughput over a given time period. As a performance benchmark, we first consider an off-line resource allocation design assuming non-causal knowledge of the channel gains. The algorithm design is formulated as a mixed-integer non-convex optimization problem taking into account the aerodynamic power consumption, solar energy harvesting, a finite energy storage capacity, and the quality-of-service requirements of the users. Despite the non-convexity of the optimization problem, we solve it optimally by applying monotonic optimization to obtain the optimal 3D-trajectory and the optimal power and subcarrier allocation policy. Subsequently, we focus on the online algorithm design that only requires real-time and statistical knowledge of the channel gains. The optimal online resource allocation algorithm is motivated by the off-line scheme and entails a high computational complexity. Hence, we also propose a low-complexity iterative suboptimal online scheme based on the successive convex approximation. Our simulation results reveal that both the proposed online schemes closely approach the performance of the benchmark off-line scheme and substantially outperform two baseline schemes. Furthermore, our results unveil the tradeoff between solar energy harvesting and power-efficient communication. In particular, the solar-powered UAV first climbs up to a high altitude to harvest a sufficient amount of solar energy and then descends again to a lower altitude to reduce the path loss of the communication links to the users it serves.<br
Keywords: Resource management; Communication systems; Trajectory; Solar energy; Unmanned aerial vehicles; Optimization; Aerodynamics

Optimal 3D-Trajectory Design and Resource Allocation for Solar-Powered UAV Communication Systems - Sun, Yan; Xu, Dongfang; Ng, Derrick Wing Kwan; Dai, Linglong; Schober, Robert (IEEE Transactions on Communications, 2019)
In this paper, we investigate the resource allocation algorithm design for multicarrier solar-powered unmanned aerial vehicle (UAV) communication systems. In particular, the UAV is powered by the solar energy enabling sustainable communication services to multiple ground users. We study the joint design of the 3D aerial trajectory and the wireless resource allocation for maximization of the system sum throughput over a given time period. As a performance benchmark, we first consider an off-line resource allocation design assuming non-causal knowledge of the channel gains. The algorithm design is formulated as a mixed-integer non-convex optimization problem taking into account the aerodynamic power consumption, solar energy harvesting, a finite energy storage capacity, and the quality-of-service requirements of the users. Despite the non-convexity of the optimization problem, we solve it optimally by applying monotonic optimization to obtain the optimal 3D-trajectory and the optimal power and subcarrier allocation policy. Subsequently, we focus on the online algorithm design that only requires real-time and statistical knowledge of the channel gains. The optimal online resource allocation algorithm is motivated by the off-line scheme and entails a high computational complexity. Hence, we also propose a low-complexity iterative suboptimal online scheme based on the successive convex approximation. Our simulation results reveal that both the proposed online schemes closely approach the performance of the benchmark off-line scheme and substantially outperform two baseline schemes. Furthermore, our results unveil the tradeoff between solar energy harvesting and power-efficient communication. In particular, the solar-powered UAV first climbs up to a high altitude to harvest a sufficient amount of solar energy and then descends again to a lower altitude to reduce the path loss of the communication links to the users it serves.
CRIS-Team Scopus Importer:2019-07-02
Keywords: 3D-trajectory planning; monotonic optimization; power and subcarrier allocation; solar energy harvesting; UAV communication systems

Optimal adaptive modulation and coding with switching costs - Farrokh, Arsalan; Krishnamurthy, Vikram; Schober, Robert (IEEE Transactions on Communications, 2009)
We present an optimal adaptive modulation and coding policy that minimizes the transmission latency and modulation/coding switching cost across a finite-state Markovian fading channel. We formulate the optimal tradeoff between transmission latency and modulation/coding switching cost as a discounted infinite horizon Markov Decision Problem (MDP). By exploiting special structures of the formulated MDP and under certain sufficient conditions, we show that optimal modulation and coding selection policies are monotone in the state variables. These monotone optimal policies are computationally inexpensive to implement and are scalable in terms of channel and switching cost parameters. Numerical results confirm the monotonicity and threshold-based structure of the optimal Modulation and Coding Scheme (MCS) selection policies under the proposed sufficient conditions. © 2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Adaptive modulation and coding; Markov decision problem (MDP); Modulation and coding scheme (MCS); Opportunistic selection; Threshold-based ordering

Optimal and autonomous incentive-based energy consumption scheduling algorithm for smart grid - Mohsenian-Rad, Amir Hamed; Wong, Vincent W.S.; Jatskevich, Juri; Schober, Robert (Innovative Smart Grid Technologies Conference, ISGT 2010, 2010)
In this paper, we consider deployment of energy consumption scheduling (ECS) devices in smart meters for autonomous demand side management within a neighborhood, where several buildings share an energy source. The ECS devices are assumed to be built inside smart meters and to be connected to not only the power grid, but also to a local area network which is essential for handling two-way communications in a smart grid infrastructure. They interact automatically by running a distributed algorithm to find the optimal energy consumption schedule for each subscriber, with an aim at reducing the total energy cost as well as the peak-to-average-ratio (PAR) in load demand in the system. Incentives are also provided for the subscribers to actually use the ECS devices via a novel pricing model, derived from a game-theoretic analysis. Simulation results confirm that our proposed distributed algorithm significantly reduces the PAR and the total cost in the system. ©2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Optimal Antenna Placement for Two-Antenna Near-Field Wireless Power Transfer - Mayer, Kenneth; Cottatellucci, Laura; Schober, Robert (IEEE International Conference on Communications, ICC 2023, 2023)
Current trends in communication system design precipitate a change in the operating regime from the traditional far-field to the radiating near-field (Fresnel) region. We investigate the optimal transmit antenna placement for a multiple-input single-output (MISO) wireless power transfer (WPT) system designed for a three-dimensional cuboid room under line-of-sight (LoS) conditions in the Fresnel region. We formulate an optimisation problem for maximising the received power at the worst possible receiver location by considering the spherical nature of the electromagnetic (EM) wavefronts in the Fresnel region while assuming perfect knowledge of the channel at the transmitter. For the case of two transmit antennas, we derive a closed-form expression for the optimal positioning of the antennas which is purely determined by the geometry of the environment. If the room contains locations where the far-field approximation holds, the proposed positioning is shown to reduce to the far-field solution. The analytical solution is validated through simulation. Furthermore, the maximum received power at the locations yielding the worst performance is quantified and the power gain over the optimal far-field solution is presented. For the considered cuboid environment, we show that a distributed antenna system is optimal in the Fresnel region, whereas a co-located antenna architecture is ideal for the far-field.<br
Keywords: Geometry; Transmitting antennas; Receiving antennas; Wireless power transfer; MISO communication; Pulse width modulation; Market research

Optimal Beamforming for MISO Communications via Intelligent Reflecting Surfaces - Yu, Xianghao; Xu, Dongfang; Schober, Robert (IEEE Workshop on Signal Processing Advances in Wireless Communications, SPAWC, 2020)
Wireless communications via intelligent reflecting surfaces (IRSs) has received considerable attention from both academia and industry. In particular, IRSs are able to create favorable wireless propagation environments with typically low-cost passive devices. While various IRS-Aided wireless communication systems have been investigated in the literature, thus far, the optimal design of such systems is not well understood. In this paper, IRS-Assisted single-user multiple-input single-output (MISO) communication is investigated. To maximize the spectral efficiency, a branch-And-bound (BnB) algorithm is proposed to obtain globally optimal solutions for both the active and passive beamformers at the access point (AP) and the IRS, respectively. Simulation results confirm the effectiveness of deploying IRSs in wireless systems. Furthermore, by taking the proposed optimal BnB algorithm as the performance benchmark, the optimality of existing design algorithms is investigated.
CRIS-Team Scopus Importer:2020-09-18

Optimal Buffer-Aided Relaying With Imperfect CSI - Jamali Kooshkghazi, Vahid; Waly, Noha; Zlatanov, Nikola; Schober, Robert (IEEE Communications Letters, 2016)
In this letter, we consider a two-hop relay channel that consists of a source, a half-duplex decode-and-forward relay, and a destination. We derive the optimal buffer-aided relaying policy based on imperfect channel state information (CSI) and under long-term per-node power constraints for the source and the relay. In particular, the proposed protocol determines the optimal state of the relay node, namely, the transmit, receive, or silent state, based on the imperfect CSI of the involved links, the quality of the CSI, and the required acquisition overhead. Our simulation results verify the analysis and reveal that there is an optimal tradeoff between the required acquisition overhead and the quality of the CSI that maximizes the throughput.<br
Keywords: Relays; Throughput; Protocols; Channel estimation; Fading channels; Simulation; Indexes

Optimal data transmission and channel code rate allocation in multi-path wireless networks - Ronasi, Keivan; Mohsenian-Rad, Amir Hamed; Wong, Vincent W.S.; Gopalakrishnan, Sathish; Schober, Robert (IEEE International Conference on Communications, 2011)
Wireless links are often unreliable and prone to transmission error due to varying channel conditions. These can degrade the performance in wireless networks, particularly for applications with tight quality-of-service requirements. A common remedy is to use channel coding where the transmitter node adds redundant bits to the transmitted packets in order to reduce the error probability at the receiver. However, this per-link solution can compromise the link data rate, leading to undesired end-to-end performance. In this paper, we show that this latter shortcoming can be mitigated if the end-to-end transmission rates and channel code rates are selected properly over multiple routing paths. We formulate the joint channel coding and end-to-end data rate allocation problem in multipath wireless networks as a network throughput maximization problem, which is non-convex. We tackle the non-convexity by using function approximation and iterative techniques from signomial programming. Simulation results confirm that by using channel coding jointly with multi-path routing, the end-to-end network performance can be improved significantly. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Optimal data transmission and channel code rate allocation in multipath wireless networks - Ronasi, Keivan; Mohsenian-Rad, Amir-Hamed; Wong, Vincent W. S.; Gopalakrishnan, Sathish; Schober, Robert (IEEE Transactions on Vehicular Technology, 2011)
Wireless links are often unreliable and prone to transmission error, particularly when network users are mobile. These can degrade the performance in wireless networks, particularly for applications with tight quality-of-service requirements. A common remedy to this problem is channel coding. However, this per-link solution can compromise the link data rate, leading to an undesired end-to-end performance. In this paper, we show that this shortcoming can be mitigated if the end-to-end transmission rates and channel code rates are properly selected over multiple routing paths. We formulate a joint channel coding and end-to-end data rate allocation problem in multipath wireless networks with max-min fairness as the objective function. Our goal is to maximize the minimum throughput available among the network users. To cope with the fast and frequent changes in dynamic environments that are typical for vehicular networks, we address both adaptive and nonadaptive channel coding scenarios. Unlike similar formulations in single-path routing networks, in the multipath routing case, we face an optimization problem that is nonconvex and usually difficult to solve. We tackle the nonconvexity by using function approximation and iterative techniques from signomial programming. Simulation results confirm that by using channel coding jointly with multipath routing, we can significantly improve the end-to-end network performance compared with the case when only one of them is used in the network. Nonadaptive channel coding is also shown to achieve a high degree of optimality with much less complexity. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Adaptive and nonadaptive channel coding; link reliability; max-min fairness; multipath routing; nonconvex optimization; signomial programming; throughput maximization

Optimal Energy Beamforming for Distributed Wireless Power Transfer Over Frequency-Selective Channels - Luo, Bing; Yeoh, Phee Lep; Schober, Robert; Krongold, Brian S. (CC 2019 - 2019 IEEE International Conference on Communications (ICC), 2019)
This paper analyzes the optimal transmission strategy and power allocation for a distributed wireless power transfer (WPT) system operating over frequency-selective fading channels. We consider K coordinated energy transmitters (CETs) coherently transmitting energy to a single user over N > K subchannels with individual power constraints. To maximize the total harvested energy, we derive the optimal co-phasing power allocation rule which has the following properties: 1) For any given subchannel, if the optimal power allocation of one CET is zero, then the power allocated by all the other K − 1 CETs to that subchannel is also zero (i.e., the subchannel is inactive); 2) For the non-zero power subchannels, the optimal power allocation obeys a proportionality principle that establishes a relationship between the powers allocated by all K CETs to all active subchannels. Based on this property, we prove that the optimal distributed WPT strategy is for all CETs to select no more than K subchannels. This is in sharp contrast to wireless information transmission where more than K subchannels may be used for capacity maximization. Numerical examples verify our theoretical results and show the performance gains of our proposed scheme compared to two benchmark schemes.<br
Keywords: Resource Management; Array signal processing; Frequency-selective fading channels; Receivers; Linear programming; Wireless power Transfer; Transmitters

Optimal energy consumption scheduling using mechanism design for the future smart grid - Samadi, Pedram; Schober, Robert; Wong, Vincent W.S. (2011 IEEE International Conference on Smart Grid Communications, SmartGridComm 2011, 2011)
In the future smart grid, both users and power companies can benefit from real-time interactions and pricing methods which can reflect the fluctuations of the wholesale price into the demand side. In addition, smart pricing can be used to seek social benefits and to achieve social objectives. However, the utility company may need to collect various information about users and their energy consumption behavior, which can be challenging. That is, users may not be willing to reveal their local information unless there is an incentive for them to do so. In this paper, we propose an efficient pricing algorithm to tackle this problem. The benefit that each user obtains from each appliance can be modeled in form of a utility function, a concept from microeconomics. We propose a Vickrey-Clarke-Groves (VCG) based mechanism for our problem formulation aiming to maximize the social welfare, i.e., the aggregate utility functions of all users minus the total energy cost. Our design requires that each user provides some information about its energy demand. In return, the energy provider will determine each user's payment for electricity. The payment of each user is structured in such a way that it is in each user's self interest to reveal its local information truthfully. Finally, we present simulation results to show that both the energy provider and the individual users can benefit from the proposed pricing algorithm. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Optimal Energy Signal Design for Multi-user MISO WPCNs with Non-linear Energy Harvesting Circuits - Shanin, Nikita; Hagelauer, Amelie; Cottatellucci, Laura; Schober, Robert (IEEE Transactions on Communications, 2023)
The optimal energy signal design for wireless powered communication networks (WPCNs) enabling energy-sustainable communication for a large number of low-power devices is still an open problem in practical systems. In this work, we study a multi-user WPCN, where a multi-antenna base station (BS) sends an energy signal to multiple single-antenna users, which, in turn, harvest energy from the received signal and utilize it for information transmission in the uplink. In contrast to the existing works on multiple-input single-output (MISO) WPCN design, in this paper, we jointly optimize the energy signal waveform and downlink beamforming at the BS for energy harvesting (EH) devices described by non-linear circuit-based models. To this end, we assume that the BS broadcasts a pulse-modulated signal employing multiple energy signal vectors and we formulate an optimization problem for the joint design of the downlink transmit energy signal vectors, their number, the durations of the transmit pulses, and the time allocation policy for minimization of the average transmit power at the BS. We show that for single-user WPCNs, a single energy signal vector, which is collinear with the maximum ratio transmission (MRT) vector and drives the EH circuit at the user device into saturation, is optimal. Next, for the general multi-user case, we show that the optimal signal design requires a maximum number of energy signal vectors that exceeds the number of users by one and propose an algorithm to obtain the optimal energy signal vectors. Since the complexity of the optimal design is high, we also propose two suboptimal schemes for WPCN design. First, for asymptotic massive WPCNs, where the ratio of the number of users to the number of BS antennas, i.e., the system load, tends to zero, we show that the optimal downlink transmit signal can be obtained in closed-form and comprises a sequence of weighted sums of MRT vectors. Next, based on this result, for general WPCNs with finite system loads, we propose a suboptimal closed-form MRT-based design and a suboptimal semidefinite relaxation (SDR)-based scheme. Our simulation results reveal that the proposed optimal scheme and suboptimal SDR-based design achieve nearly identical performance and outperform two baseline schemes, which are based on linear and sigmoidal EH models. Furthermore, we show that, if the system load of the WPCN is low, the performance gap between the proposed suboptimal solutions is small and becomes negligible as the number of BS antennas tends to infinity.
CRIS-Team Scopus Importer:2023-04-14
Keywords: Downlink; Integrated circuit modeling; MISO communication; Multiple-input multiple-output (MIMO); Non-linear energy harvesting; Radio frequency; Signal design; Signal design; Uplink; Wireless communication; Wireless powered communication

Optimal Frequency-Selective Energy Beamforming with Joint Total and Individual Power Constraints - Luo, Bing; Yeoh, Phee Lep; Schober, Robert; Krongold, Brian S. (2019 IEEE GLOBAL COMMUNICATIONS CONFERENCE (GLOBECOM), 2019)
CRIS-Team WoS Importer:2020-08-14

Optimal joint power and subcarrier allocation for full-duplex multicarrier non-orthogonal multiple access systems - Sun, Yan; Ng, Derrick Wing Kwan; Ding, Zhiguo; Schober, Robert (IEEE Transactions on Communications, 2017)
In this paper, we investigate resource allocation algorithm design for multicarrier non-orthogonal multiple access (MC-NOMA) systems employing a full-duplex (FD) base station for serving multiple half-duplex (HD) downlink and uplink users simultaneously. The proposed algorithm is obtained from the solution of a non-convex optimization problem for the maximization of the weighted sum system throughput. We apply monotonic optimization to develop an optimal joint power and subcarrier allocation policy. The optimal resource allocation policy serves as a system performance benchmark due to its high computational complexity. Furthermore, a suboptimal iterative scheme based on successive convex approximation is proposed to strike a balance between computational complexity and optimality. Our simulation results reveal that the proposed suboptimal algorithm achieves a close-to-optimal performance. In addition, FD MC-NOMA systems employing the proposed resource allocation algorithms provide a substantial system throughput improvement compared with conventional HD multicarrier orthogonal multiple access (MC-OMA) systems and other baseline schemes. In addition, our results unveil that FD MC-NOMA systems enable a fairer resource allocation compared with traditional HD MC-OMA systems.<br
Keywords: monotonic optimization; full-duplex radio; non-convex optimization; multicarrier systems; Non-orthogonal multiple access

Optimal Joint Power and Subcarrier Allocation for MC-NOMA Systems - Sun, Yan; Ng, Derrick Wing Kwan; Ding, Zhiguo; Schober, Robert (2016)
In this paper, we investigate the resource allocation algorithm design for multicarrier non-orthogonal multiple access (MC-NOMA) systems. The proposed algorithm is obtained from the solution of a non-convex optimization problem for the maximization of the weighted system throughput. We employ monotonic optimization to develop the optimal joint power and subcarrier allocation policy. The optimal resource allocation policy serves as a performance benchmark due to its high complexity. Furthermore, to strike a balance between computational complexity and optimality, a suboptimal scheme with low computational complexity is proposed. Our simulation results reveal that the suboptimal algorithm achieves a close-tooptimal performance and MC-NOMA employing the proposed resource allocation algorithm provides a substantial system throughput improvement compared to conventional multicarrier orthogonal multiple access (MC-OMA).

Optimal MISO UWB pre-equalizer design with spectral mask constraints - Mohsenian-Rad, Amir-Hamed; Mietzner, Jan; Schober, Robert; Wong, Vincent W. S. (2010 International ITG Workshop on Smart Antennas, WSA 2010, 2010)
In this paper, we propose a novel optimization-based pre-equalization filter (PEF) design for multiple-input single-output (MISO) direct-sequence ultra-wideband (DS-UWB) systems with pre-Rake combining. The key feature in our design is that we explicitly take into account spectral mask constraints which are usually imposed by telecommunications regulation and standardization bodies. This avoids the need for an inefficient power back-off, which is necessary for existing pre-equalizer and pre-Rake designs that are designed solely based on average transmit power constraints. Simulation results confirm that the proposed PEF design leads to significant performance gains over UWB PEF structures without any explicit spectral mask considerations. Furthermore, the use of multiple transmit antennas is shown to provide substantial combining gains compared to single-antenna transmitter structures. We also investigate the impact of certain system and optimization parameters on the performance of the proposed PEF design. ©2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Multiple antennas; Pre-equalization; Pre-rake combining; Semi-definite programming; Spectral mask constraints; Ultra-wideband communication

OPTIMAL MULTIUSER SCHEDULING SCHEMES FOR SIMULTANEOUS WIRELESS INFORMATION AND POWER TRANSFER - Chynonova, Maryna; Morsi, Rania; Ng, Derrick Wing Kwan; Schober, Robert (EUSIPCO, 2015)
In this paper, we study the downlink multiuser scheduling problem for systems with simultaneous wireless information and power transfer (SWIPT). We design optimal scheduling algorithms that maximize the long-term average system throughput under different fairness requirements, such as proportional fairness and equal throughput fairness. In particular, the algorithm designs are formulated as non-convex optimization problems which take into account the minimum required average sum harvested energy in the system. The problems are solved by using convex optimization techniques and the proposed optimization framework reveals the tradeoff between the long-term average system throughput and the sum harvested energy in multiuser systems with fairness constraints. Simulation results demonstrate that substantial performance gains can be achieved by the proposed optimization framework compared to existing suboptimal scheduling algorithms from the literature.
Keywords: RF energy harvesting; wireless information and power transfer; optimal multiuser scheduling

Optimal power allocation for a hybrid energy harvesting transmitter - Ahmed, Imtiaz; Ikhled, Aissa; Ng, Derrick Wing Kwan; Schober, Robert (IEEE International Conference on Communications, 2013)
In this work, we consider a point-to-point link where the transmitter has a hybrid supply of energy, i.e., the energy is supplied by a constant energy source and an energy harvester, which harvests energy from its surrounding environment. Our goal is to jointly minimize the power consumed by the constant energy source and any possible waste of the harvested energy to ensure their optimum utilization for transmission of a given amount of data in a given number of time intervals. Two scenarios are considered for packet arrival. In the first scenario, we assume that all data packets have arrived before the transmission begins, whereas in the second scenario, we assume that data packets are arriving during the course of data transmission. For both scenarios, we propose optimal offline transmit power allocation schemes which provide insight on how to efficiently consume the energy supplied by the constant energy source and the energy harvester. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Optimal power allocation for three-phase bidirectional DF relaying with fixed rates - Hadzi-Velkov, Zoran; Zlatanov, Nikola; Schober, Robert (Proceedings of the International Symposium on Wireless Communication Systems, 2013)
Wireless systems that carry delay-sensitive information (such as speech and/or video signals) typically transmit with fixed data rates, but may occasionally suffer from transmission outages caused by the random nature of the fading channels. If the transmitter has instantaneous channel state information (CSI) available, it can compensate for a significant portion of these outages by utilizing power allocation. In this paper, we consider optimal power allocation for a conventional dual-hop bidirectional decode-and-forward (DF) relaying system with a threephase transmission protocol. The proposed strategy minimizes the average power consumed by the end nodes and the relay, subject to some maximum allowable system outage probability (OP), or equivalently, minimizes the system OP while meeting average power constraints at the end nodes and the relay. We show that in the proposed power allocation scheme, the end nodes and the relay adjust their output powers to the minimum level required to avoid outages, but will sometimes be silent, in order to conserve power and prolong their lifetimes. For the proposed scheme, the end nodes use the instantaneous CSI of their respective sourcerelay links and the relay uses the instantaneous CSI of both links. © VDE Verlag GMBH.
CRIS-Team Scopus Importer:2020-02-03

Optimal power allocation for wideband cognitive radio networks employing SC-FDMA - Wu, Peiran; Schober, Robert; Bhargava, Vijay K. (IEEE Communications Letters, 2013)
In this paper, we investigate the optimal power allocation (OPA) strategy of secondary user (SU) transmitters in wideband cognitive radio networks employing single-carrier frequency-division multiple access (SC-FDMA). To protect the link of the primary user, we study two types of constraints on the SUs: Individual per-tone interference power constraints (IPCs) for each SU and a joint aggregate IPC across all frequency tones and users. Using tools from convex optimization, we derive the sum rate optimal OPA across frequency tones for the SU transmitters for both types of constraints. Simulation results show that the proposed OPA schemes can considerably improve the achievable sum rate of SC-FDMA based SU systems compared to equal power allocation and conventional power allocation schemes. © 1997-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Cognitive radio; power allocation; SC-FDMA

Optimal power allocation in a multi-hop decode-and-forward communication system - Dhaka, Kalpana; Mallik, Ranjan K.; Schober, Robert (IEEE International Conference on Communications, 2012)
This paper analyzes optimal power allocation schemes for a multi-hop decode-and-forward relay system in a Rayleigh fading environment at high signal-to-noise ratio. Analysis is done for two kinds of modulation schemes: M-ary phase-shift keying with coherent detection and orthogonal M-ary frequency-shift keying with noncoherent detection. An optimal power allocation scheme based on end-to-end symbol error probability is derived for asymmetric relay placement and it is found that for fixed asymmetric relay locations equal power allocation is not optimal. When we have global channel state information at each node, a scheme for optimal power allocation based on relay link quality is also derived. Simulation results for a multi-hop system with optimal power allocation show significant improvement in performance compared to those of a system with equal power allocation. The gap in performance increases further with increase in number of relay nodes. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Decode-and-forward (DF) relaying; M-ary phase-shift keying (MPSK); multi-hop communication; optimal power allocation; orthogonal M-ary frequency-shift keying (OMFSK)

Optimal power and retransmission control policies over fading channels with packet drop penalty costs - Farrokh, Arsalan; Krishnamurthy, Vikram; Schober, Robert (IEEE International Conference on Communications, 2008)
We present a power and retransmission control policy that achieves an optimal tradeoff between transmission power, delay, and packet drop penalty costs over a radio fading channel. We formulate the underlying power and retransmission control as a Markov Decision Problem (MDP). Under certain sufficient conditions, we show that the optimal transmission power monotonically decreases in the channel quality and the number of retransmission slots left. These structural results lead to power allocation policies that are computationally inexpensive for on-line implementation and are scalable in terms of transmission parameters. Numerical examples confirm the monotonicity results and demonstrate the improvement in the transmission cost enabled by the optimal policy. ©2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Optimal Power and Time Allocation for WPCNs With Piece-Wise Linear EH Model - Pejoski, Slavche; Hadzi-Velkov, Zoran; Schober, Robert (IEEE Wireless Communications Letters, 2017)
We propose a novel transmission protocol for harvest-then-transmit wireless powered communication networks, which takes into account the non-linearity of the energy harvesting (EH) process at the EH users and maximizes the sum rate in the uplink. We assume a piece-wise linear EH model and provide expressions for the optimal transmit power of the base station (BS), the duration of the EH phase, and the duration of the uplink information transmission phases of the users. The obtained solution provides insight regarding the significance of the non-linear EH model on the optimal resource allocation. Simulations unveil the growing impact of the saturation effect, which occurs for high received radio frequency powers, as the average and the maximum instantaneous transmit powers of the BS increase.<br
Keywords: Resource management; Integrated circuit modeling; Wireless communication; Uplink; Pins; Batteries; Time division multiple access

Optimal power control for analog bidirectional relaying with long-term relay power constraint - Hadzi-Velkov, Zoran; Zlatanov, Nikola; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2013)
Wireless systems that carry delay-sensitive information (such as speech and/or video signals) typically transmit with fixed data rates, but may occasionally suffer from transmission outages caused by the random nature of the fading channels. If the transmitter has instantaneous channel state information (CSI) available, it can compensate for a significant portion of these outages by utilizing power allocation. In a conventional dual-hop bidirectional amplify-and-forward (AF) relaying system, the relay already has instantaneous CSI of both links available, as this is required for relay gain adjustment. We therefore develop an optimal power allocation strategy for the relay, which adjusts its instantaneous output power to the minimum level required to avoid outages, but only if the required output power is below some cutoff level; otherwise, the relay is silent in order to conserve power and prolong its lifetime. The proposed scheme is proven to minimize the system outage probability, subject to an average power constraint at the relay and fixed output powers at the end nodes. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Optimal Power Control for Energy Efficient D2D Communication and Its Distributed Implementation - Wu, Yuan; Wang, Jiaheng; Qian, Liping; Schober, Robert (IEEE Communications Letters, 2015)
In this letter, we propose an energy efficient power control scheme for resource sharing between cellular and device-to-device (D2D) users in cellular network assisted D2D communication. We take into account the circuit power consumption of the device-to-device user (DU) and aim at maximizing the DU's energy efficiency while guaranteeing the required throughputs of both the DU and the cellular user. Specifically, we define three different regions for the circuit power consumption of the DU and derive the optimal power control scheme for each region. Moreover, a distributed algorithm is proposed for implementation of the optimal power control scheme.<br
Keywords: Power control; Throughput; Power demand; Interference; Educational institutions; Convergence; Distributed algorithms

Optimal receiver design for diffusive molecular communication with flow and additive noise - Noel, Adam; Cheung, Karen C.; Schober, Robert (IEEE Transactions on Nanobioscience, 2014)
In this paper, we perform receiver design for a diffusive molecular communication environment. Our model includes flow in any direction, sources of information molecules in addition to the transmitter, and enzymes in the propagation environment to mitigate intersymbol interference. We characterize the mutual information between receiver observations to show how often independent observations can be made. We derive the maximum likelihood sequence detector to provide a lower bound on the bit error probability. We propose the family of weighted sum detectors for more practical implementation and derive their expected bit error probability. Under certain conditions, the performance of the optimal weighted sum detector is shown to be equivalent to a matched filter. Receiver simulation results show the tradeoff in detector complexity versus achievable bit error probability, and that a slow flow in any direction can improve the performance of a weighted sum detector.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Diffusion; matched filter; molecular communication; sequence detection; weighted sum detector

Optimal Relay Selection for Outdated CSI - Michalopoulos, Diomidis; Ng, Jonathan; Schober, Robert (IEEE Communications Letters, 2013)
Consider the scenario of relay selection in an environment where the channel estimates are outdated, yet their reliability is known. For this scenario, we propose the optimal relay selection policy, in a minimum outage probability sense. We show that, if the reliabilities of the channel estimates are dissimilar across the relays, this policy offers a noteworthy improvement in terms of array gain, when compared to conventional selection policies. Analytical outage probability expressions are provided, which are corroborated by simulation

Optimal Relay Selection for the Parallel Hybrid RF/FSO Relay Channel: Non-Buffer-Aided and Buffer-Aided Designs - Najafi Kalyani, Marzieh; Jamali Kooshkghazi, Vahid; Schober, Robert (IEEE Transactions on Communications, 2017)
Hybrid radio frequency (RF)/free space optical (FSO) systems are among the candidate enabling technologies for the next generation of wireless networks, since they benefit from both the high data rates of the FSO subsystem and the high reliability of the RF subsystem. In this paper, we focus on the problem of throughput maximization in the parallel hybrid RF/FSO relay channel. In the parallel hybrid RF/FSO relay channel, a source node sends its data to a destination node with the help of multiple relay nodes. Thereby, for a given relay, the source-relay and the relay-destination FSO links are orthogonal with respect to each other due to the narrow beam employed for FSO transmission, whereas due to the broadcast nature of the RF channel, half-duplex operation is required for the RF links if self-interference is to be avoided. Moreover, we consider the two cases where the relays are and are not equipped with buffers. For both cases, we derive the optimal relay selection policies for the RF and FSO links and the optimal time allocation policy for transmission and reception for the RF links. The proposed optimal protocols provide important insights for an optimal system design. Since the optimal buffer-aided policy introduces an unbounded delay, we also propose a suboptimal buffer-aided policy, which ensures certain target average delays. Moreover, we present distributed implementations for both the proposed optimal protocols. Simulation results demonstrate that a considerable gain can be achieved by the proposed adaptive protocols in comparison with benchmark schemes from the literature.<br
Keywords: Relays; Radio frequency; Protocols; Throughput; Wireless communication; Optical transmitters; Delays

Optimal Resource Allocation and Beamforming for Two-User MISO WPCNs for a Non-linear Circuit-Based EH Model - Shanin, Nikita; Garkisch, Moritz; Hagelauer, Amelie; Schober, Robert; Cottatellucci, Laura (Proceedings of ICASSP 2022 - 2022 IEEE International Conference on Acoustics, Speech and Signal Processing (ICASSP), 2022)
In this paper, we study multi-user multi-antenna wireless power transfer (WPT) systems, where each antenna at the energy harvesting (EH) nodes is connected to a dedicated non-linear rectifier. We propose optimal transmit strategies which maximize a weighted sum of the average harvested powers at the EH nodes subject to a constraint on the power budget of the transmitter. First, for multiple-input single-output (MISO) WPT systems, we prove that the optimal strategy employs maximum ratio transmission (MRT) beamforming and scalar symbols with arbitrary phases and discrete amplitudes following a probability density function (pdf) with at most two mass points. Then, we prove that for single-input multiple-output (SIMO) WPT systems, the optimal transmit symbol amplitudes are discrete random variables, whose pdf also has no more than two mass points. For general multi-user MIMO WPT, we show that the optimal transmit strategy employs scalar unit-norm symbols with arbitrary phases and at most two beamforming vectors. To determine these vectors, we formulate a non-convex optimization problem and obtain an optimal solution based on monotonic optimization. Since the computational complexity of the optimal solution is high, we propose a low-complexity iterative algorithm to obtain a suboptimal solution, which achieves near-optimal performance. Our simulation results reveal that the proposed transmit strategy for multi-user MIMO WPT systems outperforms baseline schemes based on a linear EH model and a single beamforming vector. For a given transmit power budget, we show that the harvested power saturates when increasing the number of transmit antennas. Finally, we observe that the harvested power region spanned by multiple EH nodes is convex and the power harvested at one EH node can be traded for a higher harvested power at the other node

OPTIMAL RESOURCE ALLOCATION AND BEAMFORMING FOR TWO-USER MISO WPCNs FOR A NON-LINEAR CIRCUIT-BASED EH MODEL (Invited Paper) - Shanin, Nikita; Garkisch, Moritz; Hagelauer, Amelie; Schober, Robert; Cottatellucci, Laura (2022 IEEE INTERNATIONAL CONFERENCE ON ACOUSTICS, SPEECH AND SIGNAL PROCESSING (ICASSP), 2022)
CRIS-Team WoS Importer:2023-01-13

Optimal Resource Allocation Design for Large IRS-Assisted SWIPT Systems: A Scalable Optimization Framework - Xu, Dongfang; Jamali, Vahid; Yu, Xianghao; Ng, Derrick Wing Kwan; Schober, Robert (IEEE Transactions on Communications, 2022)
In this paper, we study the optimal resource allocation algorithm design for large intelligent reflecting surface (IRS)-assisted simultaneous wireless information and power transfer (SWIPT) systems. To facilitate efficient system design for large IRSs, instead of jointly optimizing all the IRS elements, we partition the IRS into several tiles and employ a scalable optimization framework comprising an offline design stage and an online optimization stage. In the offline stage, the IRS elements of each tile are jointly designed to support a set of different phase shift configurations, referred to as transmission modes, while the best transmission mode is selected from the set for each tile in the online stage. Given a transmission mode set, we aim to minimize the total base station (BS) transmit power by jointly optimizing the beamforming and the transmission mode selection policy taking into account the quality-of-service requirements of information decoding and non-linear energy harvesting receivers, respectively. Although the resource allocation algorithm design is formulated as a non-convex combinatorial optimization problem, we solve it optimally by applying the branch-and-bound (BnB) approach which entails a high computational complexity. To strike a balance between optimality and computational complexity, we also develop an efficient suboptimal algorithm capitalizing on the penalty method and successive convex approximation. Our simulation results show that the proposed designs enable considerable power savings compared to several baseline schemes. Moreover, our results reveal that by properly adjusting the numbers of tiles and transmission modes, the proposed scalable optimization framework indeed facilitates online design for large IRSs. Besides, our results confirm that the advocated physics-based model and scalable optimization framework enable a flexible trade-off between performance and complexity, which is vital for realizing the performance gains promised by large IRS-assisted communication systems in practice.
CRIS-Team Scopus Importer:2022-01-21
Keywords: Array signal processing; Branch and bound approach; Computational complexity; intelligent reflecting surface; optimal resource allocation; Optimization; Radio frequency; Receivers; Resource management; scalable optimization; Wireless communication

Optimal resource allocation for energy harvesting two-way relay systems with channel uncertainty - Ahmed, Imtiaz; Ikhlef, Aissa; Ng, Derrick Wing Kwan; Schober, Robert (2013 IEEE Global Conference on Signal and Information Processing, GlobalSIP 2013 - Proceedings, 2013)
In this paper, we consider two-way decode-and-forward (DF) multiple access and time division broadcasting relaying protocols with energy harvesting (EH) nodes. We propose optimal offline joint energy and transmission time allocation schemes for the considered relaying protocols taking into account channel state uncertainty. The proposed joint energy and transmission time allocation schemes are obtained based on convex optimization problems and maximize the aggregate system throughput over a finite number of transmission intervals.We compare the optimal throughputs obtained for the multiple access and time division broadcasting protocols via simulations. Our results reveal that the proposed schemes are robust to imperfect channel state information and that multiple access broadcasting is less affected by low harvesting rate at the relay than time division broadcasting. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Optimal Resource Allocation for Multicarrier MISO-NOMA Systems - Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (2017)
In this paper, we investigate optimal resource allocation for multicarrier (MC) multiple-input single-output non-orthogonal multiple access (MISO-NOMA) downlink systems. The resource allocation design for the maximization of the weighted system throughput is formulated as a non-convex optimization problem taking into account the quality-of-service requirements of the downlink receivers. We employ monotonic optimization to solve the formulated problem and to obtain the optimal joint precoding and subcarrier allocation policy. The optimal resource allocation policy serves as a performance benchmark due to its high computational complexity. Furthermore, a low-complexity suboptimal resource allocation algorithm is developed and shown to find a locally optimal solution. Our simulation results reveal that the suboptimal algorithm closely approaches the optimal performance. Besides, our results show that MC MISO-NOMA significantly improves the system throughput compared to conventional MC MISO orthogonal multiple access.

Optimal Resource Allocation for Multi-User OFDMA-URLLC MEC Systems - Ghanem, Walid; Jamali, Vahid; Schober, Robert (IEEE Open Journal of the Communications Society, 2022)
In this paper, we study resource allocation algorithm design for multi-user orthogonal frequency division multiple access (OFDMA) ultra-reliable low latency communication (URLLC) in mobile edge computing (MEC) systems. To meet the stringent end-to-end delay and reliability requirements of URLLC MEC systems, we employ joint uplink-downlink resource allocation and finite blocklength transmission. Furthermore, we propose a partial time overlap between the uplink and downlink frames to minimize the end-to-end delay, which introduces a new time causality constraint. The proposed resource allocation algorithm is formulated as an optimization problem for minimization of the total weighted power consumption of the network under a constraint on the number of URLLC user bits computed within the maximum allowable computation time, i.e., the end-to-end delay of a computation task of each user. Despite the non-convexity and the complicated structure of the formulated optimization problem, we develop a globally optimal solution using a branch-and-bound approach based on discrete monotonic optimization theory. The branch-and-bound algorithm minimizes an upper bound on the total power consumption until convergence to the globally optimal value. Furthermore, to strike a balance between computational complexity and performance, we propose two efficient suboptimal algorithms. For the first suboptimal scheme, the optimization problem is reformulated in the canonical form of difference of convex programming. Then, successive convex approximation (SCA) is used to determine a locally optimal solution. For the second suboptimal scheme, we use a high signal-to-noise ratio approximation for the channel dispersion. Then, via novel transformations, we convert the non-convex quality-of-service constraints of the original problem into equivalent second-order-cone constraints. Our simulation results reveal that the proposed resource allocation algorithm design facilitates URLLC in MEC systems, and yields significant power savings compared to three baseline schemes. Moreover, our simulation results show that the proposed suboptimal algorithms offer different trade-offs between performance and complexity and attain an excellent performance at comparatively low complexity.
CRIS-Team WoS Importer:2022-11-25

Optimal SINR-based random access - Mohsenian-Rad, Amir Hamed; Wong, Vincent W.S.; Schober, Robert (Proceedings - IEEE INFOCOM, 2010)
Random access protocols, such as Aloha, are commonly modeled in wireless ad-hoc networks by using the protocol model. However, it is well-known that the protocol model is not accurate and particularly it cannot account for aggregate interference from multiple interference sources. In this paper, we use the more accurate physical model, which is based on the signal-to-interference-plus- noise-ratio (SINR), to study optimization-based design in wireless random access systems, where the optimization variables are the transmission probabilities of the users. We focus on throughput maximization, fair resource allocation, and network utility maximization, and show that they entail non-convex optimization problems if the physical model is adopted. We propose two schemes to solve these problems. The first design is centralized and leads to the global optimal solution using a sum-of-squares technique. However, due to its complexity, this approach is only applicable to small-scale networks. The second design is distributed and leads to a close-to-optimal solution using the coordinate ascent method. This approach is applicable to medium-size and large-scale networks. Based on various simulations, we show that it is highly preferable to use the physical model for optimization-based random access design. In this regard, even a sub-optimal design based on the physical model can achieve a significantly better performance than an optimal design based on the inaccurate protocol model. ©2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Optimal storage-aided wind generation integration considering ramping requirements - Xiang, Lin; Ng, Derrick Wing Kwan; Lee, William; Schober, Robert (2013 IEEE International Conference on Smart Grid Communications, SmartGridComm 2013, 2013)
Large-scale integration of intermittent wind energy can put a large burden on the utility company in balancing system demand and supply. As more and more dispersed wind energy suppliers connect to the system for electricity supply, the power system suffers from increased operation cost and risk caused by the discrepant interests of energy suppliers and the utility company. Energy suppliers may only concern about maximizing their own profits by pushing as much energy into the grid as possible, while neglecting the risk of steep ramps in wind generation. In this paper, exploiting the two-way communication capability in smart grid, we propose interactive ramp control of wind energy integration by aligning the individual pursuits of the energy suppliers and the utility company for social welfare maximization. The optimal wind energy integration and generator ramp control are investigated in an offline social welfare optimization problem assuming full knowledge of future wind energy and load demand. Moreover, the benefits of storage are exploited in our proposed storage-aided generation range adaption scheme to reduce the potential risk caused by inaccurate wind energy forecasts and the ramping latency of slow generators. Furthermore, a suboptimal storage-aided generation range adaption scheme with low computational complexity is presented for online control of wind integration when wind energy forecasts are unavailable. Our simulation results show that interactive ramp control is necessary to achieve efficient and secure wind energy integration and with the aid of storage, the power system's ramping capability can be improved at lower operation cost. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Large-scale integration; Ramp control; Smart grid

Optimal switch and stay combining (SSC) under switching rate constraints - Jataprolu, Manjunath Kashyap; Michalopoulos, Diomidis S.; Schober, Robert (2011 IEEE Wireless Communications and Networking Conference, WCNC 2011, 2011)
Switch-and-stay combining (SSC) is a low-complexity alternative of selection combining in diversity schemes with two receiving antennas. Its operation is based upon activating a single diversity branch and maintaining it active for as long as the corresponding channel is sufficiently strong, regardless of the quality of the remaining branch. In this respect, we optimize here the switching threshold of SSC applications in terms of the achievable bit error rate (BER), under certain constraints on the switching rate, defined as the number of times per second a branch-switching takes place. Specifically, an approximate closed-form solution of the optimization problem is presented, which, however, matches closely to the optimal solution obtained via numerical optimization methods. The results apply to practical scenarios where the BER performance is of high importance, yet hardware constraints limit the maximum switching rate between the receiving antennas that the system can tolerate. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Optimal Tomlinson-Harashima precoding for physical layer network coding - Schmidt, Armin Christian; Schober, Robert; Gerstacker, Wolfgang (2013 IEEE Wireless Communications and Networking Conference Workshops (WCNCW), 2013)
We consider a two-way relaying system employing physical layer network coding in channels suffering from frequency-selective fading. In order to mitigate the distortions introduced by the channel, Tomlinson-Harashima precoding is applied at the source nodes. We introduce an optimal precoding scheme that provides intersymbol interference free source-to-relay transmission without requiring identical overall channel impulse responses, which is in contrast to previously proposed equalization approaches. The performance of our novel approach is compared against that of a benchmark precoding scheme, motivated by the optimal decision-feedback equalization for physical layer network coding, which creates identical overall channel impulse responses in order to be able to use identical feedback filters for precoding at both source node

Optimal Transmit Strategy for MIMO WPT Systems with Non-linear Energy Harvesting - Shanin, Nikita; Cottatellucci, Laura; Schober, Robert (Proceedings - 17th Annual International Conference on Distributed Computing in Sensor Systems, DCOS 2021, 2021)
In this paper, we study multiple-input multiple-output (MIMO) wireless power transfer (WPT) systems, where the energy harvesting (EH) node is equipped with multiple nonlinear rectennas. We characterize the optimal transmit strategy by the optimal distribution of the transmit symbol vector that maximizes the average harvested power at the EH node subject to a constraint on the power budget of the transmitter. We show that the optimal transmit strategy employs scalar unit-norm input symbols with arbitrary phase and two beamforming vectors, which are determined as solutions of a non-convex optimization problem. To solve this problem, we propose an iterative algorithm based on a two-dimensional grid search, semi-definite relaxation, and successive convex approximation. Our simulation results reveal that the proposed MIMO WPT design significantly outperforms two baseline schemes based on a linear EH model and a single beamforming vector, respectively. Finally, we show that the average harvested power grows linearly with the number of rectennas at the EH node and saturates for a large number of TX antennas.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Energy harvesting; Information Theory; Power Transfer

Optimal Transmit Strategy for Multi-User MIMO WPT Systems With Non-Linear Energy Harvesters - Shanin, Nikita; Schober, Robert; Cottatellucci, Laura (IEEE Transactions on Communications, 2022)
In this paper, we study multi-user multi-antenna wireless power transfer (WPT) systems, where each antenna at the energy harvesting (EH) nodes is connected to a dedicated non-linear rectifier. We propose optimal transmit strategies which maximize a weighted sum of the average harvested powers at the EH nodes subject to a constraint on the power budget of the transmitter. First, for multiple-input single-output (MISO) WPT systems, we prove that the optimal strategy employs maximum ratio transmission (MRT) beamforming and scalar symbols with arbitrary phases and discrete amplitudes following a probability density function (pdf) with at most two mass points. Then, we prove that for single-input multiple-output (SIMO) WPT systems, the optimal transmit symbol amplitudes are discrete random variables, whose pdf also has no more than two mass points. For general multi-user MIMO WPT, we show that the optimal transmit strategy employs scalar unit-norm symbols with arbitrary phases and at most two beamforming vectors. To determine these vectors, we formulate a non-convex optimization problem and obtain an optimal solution based on monotonic optimization. Since the computational complexity of the optimal solution is high, we propose a low-complexity iterative algorithm to obtain a suboptimal solution, which achieves near-optimal performance. Our simulation results reveal that the proposed transmit strategy for multi-user MIMO WPT systems outperforms baseline schemes based on a linear EH model and a single beamforming vector. For a given transmit power budget, we show that the harvested power saturates when increasing the number of transmit antennas. Finally, we observe that the harvested power region spanned by multiple EH nodes is convex and the power harvested at one EH node can be traded for a higher harvested power at the other node

Optimal Tx-BF for MIMO SC-FDE Systems - Wu, Peiran; Schober, Robert; Bhargava, Vijay Kishore (IEEE Communications Letters, 2013)
Transmit beamforming (Tx-BF) for multiple-input multiple-output (MIMO) channels is an effective means to improve system performance. In frequency-selective channels, Tx-BF can be implemented in combination with single-carrier frequency-domain equalization (SC-FDE) to combat inter-symbol interference. In this paper, we consider the optimal design of the Tx-BF matrix for a MIMO SC-FDE system employing a linear minimum mean square error (MSE) receiver. We formulate the Tx-BF optimization problem as the minimization of a general function of the stream MSEs, subject to a transmit power constraint. The optimal structure of the Tx-BF matrix is obtained in closed form and an efficient algorithm is proposed for computing the optimal power allocation. Our simulation results validate the excellent performance of the proposed scheme in terms of uncoded bit-error rate and achievable bit rat

Optimisation of power allocation for asymmetric relay placement in multi-hop relay systems - Dhaka, Kalpana; Mallik, Ranjan K.; Schober, Robert (IET Communications, 2013)
In this study, schemes for optimisation of power allocation (OPA) for asymmetric relay placement are presented for multi-hop communication in a Rayleigh-fading environment. For a decode-and-forward (DF) multi-hop communication system, expressions are derived for optimised power allocation based on symbol error probability (SEP) and global channel state information (GCSI). The analysis for OPA based on GCSI is extended to a hybrid combination of amplify-and-forward (AF) and DF relays. Analysis is done for two kinds of modulation schemes: M-ary phase-shift keying with coherent detection and orthogonal M-ary frequency-shift keying with non-coherent detection. Simulation results show that for a multi-hop system with asymmetric relay placement, power optimisation schemes perform better than the conventional equal power allocation scheme. In addition, power optimisation based on GCSI shows substantially improved performance compared with power allocation based on end-to-end SEP. Further, performance comparison is shown for increase in number of relay nodes in an AF and DF multi-hop system with and without power allocation. The performance of a DF system improves with increase in number of relay nodes whereas performance of an AF system degrades. Hybrid relaying provides an option to exercise switching between DF and AF so as to extract the maximum advantage of the two relaying schemes. © The Institution of Engineering and Technology 2013.
CRIS-Team Scopus Importer:2020-02-03

Optimization-Based Phase-Shift Codebook Design for Large IRSs - Ghanem, Walid; Jamali, Vahid; Schellmann, Malte; Cao, Hanwen; Eichinger, Joseph; Schober, Robert (IEEE Communications Letters, 2023)
In this letter, we focus on large intelligent reflecting surfaces (IRSs) and propose a new codebook construction method to obtain a set of pre-designed phase-shift configurations for the IRS unit cells. Since the complexity of online optimization and the overhead for channel estimation scale with the size of the phase-shift codebook, the design of small codebooks is of high importance. We consider both continuous and discrete phase-shift designs and formulate the codebook construction as optimization problems. To solve the optimization problems, we propose an optimal algorithm for the discrete phase-shift design and a locally optimal solution for the continuous design. Simulation results show that the proposed algorithms facilitate the construction of codebooks of different sizes and with different beamwidths. Moreover, the performance of the discrete phase-shift design with 2-bit quantization is shown to approach that of the continuous phase-shift design. Finally, our simulation results show that the proposed designs enable large transmit power savings compared to the existing linear and quadratic codebook designs.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Intelligent reflecting surfaces (IRSs); optimization problem; phase-shift codebook

Optimization of Aggregate Capacity of PEVs for Frequency Regulation Service in Day-Ahead Market - Yao, Enxin; Wong, Vincent W.S.; Schober, Robert (IEEE Transactions on Smart Grid, 2016)
An aggregator can coordinate plug-in electric vehicles (PEVs) to provide frequency regulation service to an independent system operator (ISO). The aggregator can participate in the electricity markets of ISOs which provide economic incentives for PEV frequency regulation service. While the ISOs typically use forward market [e.g., day-ahead market (DAM)] to trade frequency regulation service, the available regulation capacity of an aggregator is subject to the random arrival and departure of the PEVs. In the DAM, the aggregator submits a bid to indicate its available capacity on the next day. This motivates us to study the problem of how an aggregator determines its bid in the DAM, given the uncertainty of the available regulation capacity of the PEVs. The DAM is used to trade the frequency regulation capacity in California ISO (CAISO) and New York ISO (NYISO). We consider two types of DAMs based on the market rules of CAISO and NYISO. For the first type, the exact amount of regulation capacity submitted in the DAM needs to be fulfilled on the next day. For the second type, a market participant can settle a shortage of capacity by paying a penalty to the ISO. In both cases, the aggregator can participate in the real-time market to sell extra capacity on the next day. We formulate the problem for determining the bid using stochastic programming. As PEVs have uncertain arrival and departure times, our problem formulation incorporates risk management using the conditional value at risk. Efficient algorithms are proposed for solving the formulated problem. PEV charging data collected in Vancouver, BC, Canada, is used in our simulations. We compare the profit of the aggregator when it participates in the markets of CAISO and NYISO. Our simulation results show that the uncertainty of the PEVs' available capacity has less effect on the profit and financial risk as the number of PEVs increases.<br
Keywords: Frequency control; ISO; Power grids; Uncertainty; Contracts; Batteries; Stochastic processes

Optimization of Delay Diversity for Fading ISI Channels - Schober, Robert; Hehn, Thorsten; Gerstacker, Wolfgang (Conference Proceedings, 2004)
In this paper, we propose an optimized delay diversity (ODD) scheme for fading intersymbol interference (ISI) channels. We derive a cost function for optimization of the ODD transmit filters and we provide a steepest descent algorithm for iterative calculation of the filter coefficients. In addition, an upper bound on the cost function is derived and employed to prove the asymptotic optimality of the generalized DD (ODD) scheme in [1] for very high signal-to-noise (SNR) ratios and transmit filters of maximum length. However, for SNRs of practical interest and reasonable filter lengths the novel ODD scheme significantly outperforms GDD for both optimum and suboptimum equalization.
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.mobilk.optimi

Optimization of Multi-UAV-BS Aided Millimeter-Wave Massive MIMO Networks - Zhu, Lipeng; Zhang, Jun; Xiao, Zhenyu; Schober, Robert (2020 IEEE GLOBAL COMMUNICATIONS CONFERENCE (GLOBECOM), 2020)
CRIS-Team WoS Importer:2021-10-29

Optimization of wireless multicast systems employing hybrid-ARQ with chase combining - Kim, Junsu; Jin, Hu; Sung, Dan Keun; Schober, Robert (IEEE Transactions on Vehicular Technology, 2010)
The throughput of conventional wireless multicast systems is limited by the multicast user with the lowest channel quality, which leads to a low throughput, particularly if the number of multicast users is large. In this paper, we show that hybrid-automatic repeat request with Chase combining (HARQ-CC) is a promising technique to overcome this problem and optimize the corresponding transmission rate. We analyze the throughput of wireless multicast systems with HARQ-CC under various channel conditions and derive a closed-form approximation for the optimal rate. The numerical evaluation of our analytical expressions reveals that HARQ-aided multicast outperforms conventional multicast in most channel environments. To further improve performance, we propose a dynamic rate-allocation scheme that combines the advantages of conventional multicast and HARQ-aided multicast. © 2006 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Chase combining; hybrid-automatic repeat request (HARQ); throughput optimization; wireless multicast

Optimized Delay Diversity for Frequency-Selective Fading Channels - Hehn, Thorsten; Schober, Robert; Gerstacker, Wolfgang (IEEE Transactions on Wireless Communications, 2005)
This paper proposes an optimized delay diversity (ODD) scheme for frequency-selective fading channels. The novel scheme requires knowledge of the channel impulse response (CIR) autocorrelation matrix at the transmitter, but the CIRs themselves have to be available only at the receiver side. A cost function for optimization of the ODD transmit filters is derived and a steepest descent algorithm for iterative calculation of the filter coefficients is provided. In addition, an upper bound on the cost function is derived and employed to prove the asymptotic optimally of the generalized DD (GDD) scheme in [Proc. IEEE Int. Conf. Communications (ICC), (2002) p. 1949] for very high signal-to-noise ratios (SNRs) and transmit filters of maximum length. However, for SNRs of practical interest and reasonable filter lengths, the novel ODD scheme significantly outperforms GDD for both optimum and suboptimum equalizations. It is also shown that, in contrast to the frequency-nonselective case, for frequency-selective channels, transmit diversity schemes designed under the high SNR assumption may perform poorly for practically relevant SNRs. © 2005 IEEE.
UnivIS-Import:2015-03-09:Pub.2005.tech.IE.mobilk.optimi_7
Keywords: Delay diversity (DD); Equalization; Frequency-selective channels; Transmit diversity (TD)

Optimized of Delay Diversity for Linear Equalization - Yiu, Simon; Schober, Robert; Gerstacker, Wolfgang (Conference Proceedings, 2005)
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.mobilk.optimi

Orthogonal Time Frequency Space Modulation – Part I: Fundamentals and Challenges Ahead - Wei, Zhiqiang; Li, Shuangyang; Yuan, Weijie; Schober, Robert; Caire, Giuseppe (IEEE Communications Letters, 2022)
This letter is the first part of a three-part tutorial on orthogonal time frequency space (OTFS) modulation, which is a promising candidate waveform for future wireless networks. This letter introduces and compares two popular implementations of OTFS modulation, namely the symplectic finite Fourier transform (SFFT)-and discrete Zak transform (DZT)-based architectures. Based on these transceiver architectures, fundamental concepts of OTFS modulation, including the delay-Doppler (DD) domain, DD domain information multiplexing, and its potential benefits, are discussed. Finally, the challenges ahead for OTFS modulation are highlighted. Parts II and III of this tutorial on OTFS modulation focus on transceiver designs and integrated sensing and communication (ISAC), respectively.
CRIS-Team Scopus Importer:2022-10-21
Keywords: delay-Doppler domain; Delays; Demodulation; DZT; Indexes; Modulation; OTFS; SFFT; Symbols; Time-frequency analysis; Transceivers

Orthogonal Time Frequency Space Modulation – Part III: ISAC and Potential Applications - Yuan, Weijie; Wei, Zhiqiang; Li, Shuangyang; Schober, Robert; Caire, Giuseppe (IEEE Communications Letters, 2022)
The first two parts of this tutorial on orthogonal time frequency space (OTFS) modulation have discussed the fundamentals of delay-Doppler (DD) domain communications as well as some advanced technologies for transceiver design. In this letter, we will present an OTFS-based integrated sensing and communications (ISAC) system, which is regarded as an enabling technology in next generation wireless communications. In particular, we illustrate the sensing as well as the communication models for OTFS-ISAC systems. Next, we show that benefiting from time-invariant DD channels, the sensing parameters can be used for inferring the communication channels, leading to an efficient transmission scheme. As both functionalities are realized in the same DD domain, we briefly discuss several promising benefits of OTFS-based ISAC systems, which have not been completely unveiled yet. Finally, a range of potential applications of OTFS for the future wireless networks will be highlighted.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Array signal processing; delay-Doppler domain; Delays; Doppler effect; integrated sensing and communications (ISAC); Linear antenna arrays; OTFS; Receiving antennas; Sensors; Time-frequency analysis

Orthogonal Time Frequency Space Modulation – Part II: Transceiver Designs - Li, Shuangyang; Yuan, Weijie; Wei, Zhiqiang; Schober, Robert; Caire, Giuseppe (IEEE Communications Letters, 2022)
The fundamental concepts and challenges of orthogonal time frequency space (OTFS) modulation have been reviewed in Part I of this three-part tutorial. In this second part, we provide an overview of the state-of-the-art transceiver designs for OTFS systems, with a particular focus on the cyclic prefix (CP) design, window design, pulse shaping, channel estimation, and signal detection. Furthermore, we analyze the performance of OTFS modulation, including the diversity gain and the achievable rate. Specifically, comparative simulations are presented to evaluate the error performance of different OTFS detection schemes, and the advantages of coded OTFS systems over coded orthogonal frequency-division multiplexing (OFDM) systems are investigated.
CRIS-Team Scopus Importer:2022-10-21
Keywords: Channel estimation; Delays; Modulation; OFDM; OTFS; performance analysis; Pulse shaping methods; Shape; transceiver designs; Transceivers

OTFS-NOMA: An Efficient Approach for Exploiting Heterogenous User Mobility Profiles - Ding, Zhiguo; Schober, Robert; Fan, Pingzhi; Vincent Poor, H. (IEEE Transactions on Communications, 2019)
This paper considers a challenging communication scenario, in which users have heterogenous mobility profiles, e.g., some users are moving at high speeds and some users are static. A new non-orthogonal multiple-access (NOMA) transmission protocol that incorporates orthogonal time frequency space (OTFS) modulation is proposed. Thereby, users with different mobility profiles are grouped together for the implementation of NOMA. The proposed OTFS-NOMA protocol is shown to be applicable to both uplink and downlink transmission, where sophisticated transmit and receive strategies are developed to remove inter-symbol interference and harvest both multi-path and multi-user diversity. Analytical results demonstrate that both the high-mobility and the low-mobility users benefit from the application of OTFS-NOMA. In particular, the use of NOMA allows the spreading of the high-mobility users' signals over a large amount of time-frequency resources, which enhances the OTFS resolution and improves the detection reliability. In addition, OTFS-NOMA ensures that low-mobility users have access to bandwidth resources which in conventional OTFS-orthogonal multiple access (OTFS-OMA) would be solely occupied by the high-mobility users. Thus, OTFS-NOMA improves the spectral efficiency and reduces latency.
CRIS-Team Scopus Importer:2019-12-10
Keywords: dual plane multiple access; non-orthogonal multiple access (NOMA); Orthogonal time frequency space (OTFS); uplink and downlink transmission

Outage analysis of multihop full duplex relaying - Baranwal, Tarun Kr.; Michalopoulos, Diomidis S.; Schober, Robert (IEEE Communications Letters, 2013)
We consider a multihop full duplex relaying (FDR) system, where multiple full duplex decode-and-forward relays are connected in cascade so as to forward the information from a source terminal to a destination terminal. Since FDR causes additional quotedblleft echoquotedblright interference at the relay, we introduce a parameter that captures the ability of the relays to isolate transmission from reception. This parameter is defined as the ratio of the received desired signal power to the received interference power, when the transmit power is the same for the useful and the interfering signals, and dubbed as quotedblleft path-loss-to-interference ratioquotedblright (PLIR). For given values of the PLIR, we investigate the number of full duplex relays that lead to the minimum outage probability. The performance of multihop half duplex relaying (HDR) is also studied as a benchmark, showing that FDR outperforms HDR, in terms of the outage probability, for sufficiently large values of PLIR. © 1997-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Full-duplex relaying; multihop communications

Outage analysis of q-duplex RF/FSO relaying - Jamali Kooshkghazi, Vahid; Michalopoulos, Diomidis; Uysal, Murat; Schober, Robert (2015 International Symposium on Wireless Communication Systems (ISWCS), 2015)
In this paper, we propose and analyze a novel q-duplex radio frequency/free space optical (RF/FSO) relaying protocol for a mixed RF and hybrid RF/FSO communication system. In our scheme, several mobile users transmit their data over an RF link to a relay node (e.g. a small cell base station) and the relay forwards the information to a destination (e.g. a macro cell base station) over a hybrid RF/FSO backhaul link. The RF links are full-duplex with respect to the FSO link and half-duplex with respect to each other, i.e., either the user-relay RF link or the relay-destination RF link is active. Depending on the channel statistics, the q-duplex relaying protocol may reduce to full-duplex relaying, when the quality of the FSO link is sufficiently high, or to half-duplex relaying, when the FSO link becomes unavailable due to severe atmospheric conditions. We derive an analytical expression for the end-to-end outage probability of the proposed protocol when the fading for the user-relay RF link, the relay-destination RF link, and the relay-destination FSO link are modelled as Rayleigh, Ricean, and Gamma-Gamma distributed, respectively. Our simulation results confirm the analytical derivations and reveal the effectiveness of the proposed q-duplex protocol and its superiority compared to existing schemes.<br
Keywords: Radio frequency; Relays; Mixers; Optical fiber communication; Encoding

Outage rate and outage duration of decode-and-forward cooperative diversity systems - Zlatanov, Nikola; Hadzi-Velkov, Zoran; Karagiannidis, George K.; Schober, Robert (IEEE International Conference on Communications, 2011)
A complete evaluation of the benefits of cooperative diversity schemes should not only include the outage and error rate performance but also the second-order statistics of the achievable information-theoretic capacity. In a non-ergodic fading channel, the system is said to be in outage when the destination cannot decode the fixed-rate transmitted signal with negligible error probability. Because of the Doppler effect, which is induced by the mobility of the wireless nodes, these outage capacity events are correlated. In this paper, we derive the average outage rate (AOR) and the average outage duration (AOD) of two well-known cooperative diversity protocols, decode-and-forward relaying and selection decode-and-forward relaying, operating in slow Rayleigh fading channels. We also analyze the asymptotic behavior of these statistical parameters for high SNRs, where it is shown that the AOR exhibits a similar behavior as the outage probability. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Overcoming noise and multiuser interference in diffusive molecular communication - Noel, Adam; Cheung, Karen C.; Schober, Robert (Proceedings of the 1st ACM International Conference on Nanoscale Computing and Communication, NANOCOM 2014, 2014)
In this paper, weighted sum detectors in Diffusion molecu- lar communication are assessed for their performance in the presence of multiuser interference and continuously-emitting noise sources that release molecules over finite time intervals. Weighted sum decision feedback detectors are proposed to address the limitations imposed by intersymbol and mul- Tiuser interference. Weighted sum detectors with matched filter weights are shown to be more robust to noise and in- Terference than equal weight detectors, and adding decision feedback enables additional improvements in performance.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Diffusion channel; Matched filter; Molecular communication; Multiuser interference; Weighted sum detector

PAPR-Limited Precoding in Massive MIMO Systems with Reflect- and Transmit-Array Antennas - Bereyhi, Ali; Jamali, Vahid; Müller, Ralf; Fischer, Georg; Schober, Robert; Tulino, Antonia M. (CONFERENCE RECORD OF THE 2019 FIFTY-THIRD ASILOMAR CONFERENCE ON SIGNALS, SYSTEMS & COMPUTERS, 2019)
CRIS-Team WoS Importer:2020-07-31

PAPR of Variable-Gain and Fixed-Gain Amplify and Forward Relaying - Michalopoulos, Diomidis; Hadzi-Velkov, Zoran; Karagiannidis, George K.; Schober, Robert (SCC 2013; 9th International ITG Conference on Systems, Communication and Coding, 2013)
Most works on amplify and forward (AF) relaying assume that the relay obtains perfect channel state information (CSI) of the source-relay channel. This renders variable-gain relaying (VGR) an attractive technique, as the relay can ideally invert the channel at its input and thus ensure constant output power. What happens to the output power, however, if the CSI at the input is outdated? As an attempt to answer this question, we introduce a study of AF relaying under a novel perspective. This involves the use of the well-known peak-to-average-powerratio (PAPR) for capturing the negative effects of imperfect channel inversion at the relay. The imperfect channel inversion, caused by imperfect CSI at the relay, results in using the power amplifier in its non-linear region, which induces signal distortion. In this regard, expressions for the complementary cumulative distribution function (CCDF) of the PAPR at the relay's output are derived. The analysis involves VGR with outdated CSI at its input, as well as its simpler counterpart which uses only statistical CSI, namely fixed-gain relaying (FGR). Our results manifest that there exists a threshold on the reliability of the CSI at the relay, below which VGR looses its advantage over FGR in being more efficient in terms of the potential signal distortion at the relay, caused by amplification in the non-linear regio

Performance Analysis and Design of STBC's for Fading ISI Channels - Schober, Robert; Gerstacker, Wolfgang; Lampe, Lutz (Conference Proceedings, 2002)
In this paper, space-time block-coded transmission over fading intersymbol interference (ISI) channels is investigated. A lower bound on the pairwise error probability for optimum detection is given. Also an approximation for the bit error rate is derived and compared with simulation results for maximum-likelihood sequence estimation (MLSE) for the GSM/EDGE (Enhanced Data Rates for GSM Evolution) system. Furthermore, a novel design rule for space-time block codes (STBC's) with arbitrary rate for fading ISI channels is provided. A corresponding full-rate code is designed and shown to yield higher performance than Alamouti's code. It is demonstrated that for fading channels with L independent impulse response coefficients, full-rate STBC's designed for the flat fading channel can achieve at most a diversity order of (NT + L - 1)NR if NT transmit antennas and NR receive antennas are used. On the other hand, the maximum diversity order employing the proposed code design rule is LNT NR.
UnivIS-Import:2015-04-16:Pub.2002.tech.IE.mobilk.perfor
Keywords: Approximation Theory; Bit error rate; Block codes; Computer simulation; Error analysis; Fading (radio); Global system for mobile communication; Intersymbol interference; Maximum likelihood estimation; Receiving antennas; Transceivers

Performance Analysis and Design of STBC's for Frequency-Selective Fading Channels - Schober, Robert; Gerstacker, Wolfgang; Lampe, Lutz (IEEE Transactions on Wireless Communications, 2004)
In this paper, space-time block-coded transmission over frequency-selective fading channels is investigated. A lower bound for the pairwise error probability for optimum detection is given. Also, an approximation for the bit-error rate is derived and compared with simulation results for maximum-likelihood sequence estimation (MLSE) for the GSM/EDGE (Enhanced Data Rates for GSM Evolution) system. Furthermore, a novel design rule for space-time block codes (STBCs) for frequency-selective fading channels is provided. A corresponding code is designed and shown to yield higher performance than Alamouti's code. It is demonstrated that for fading channels with L independent impulse response coefficients, STBCs designed for the flat fading channel can achieve at most a diversity order of (NT + L - 1) NR if NT transmit antennas and NR receive antennas are used. On the other hand, the maximum diversity order employing the proposed code design rule is LNTNR. <br
UnivIS-Import:2015-03-09:Pub.2004.tech.IE.mobilk.perfor
Keywords: Bit-error rate (BER) analysis; Equalization; Frequency-selective fading channels; Space-time codes

Performance analysis and improvement methods for channel resource management strategies of LEO-MSS with multiparty traffic - Wang, Zhipeng; Mathiopoulos, P. Takis; Schober, Robert (IEEE Transactions on Vehicular Technology, 2008)
A novel analytical framework for the accurate and efficient evaluation of the performance of channel resource management strategies for low Earth orbit mobile satellite systems (LEO-MSSs) supporting multiparty traffic is presented. By considering a fixed channel reservation (FCR) scheme as a benchmark, an efficient and accurate analytical approach is developed for obtaining the performance of multiparty traffic under various quality-of-service (QoS) performance measure criteria. The proposed approach is based on a Markovian queuing model, and its correctness and accuracy have been verified by means of computer simulations. To improve the overall performance of LEO-MSS, two novel resource management techniques are introduced and analyzed. The first one is an efficient adaptive channel reservation (ACR) scheme, which allows priority to be given to handover requests that are generated by multiparty traffic. The second one is a new call queuing (NCQ) policy, which efficiently reduces the new call blocking probability with little impact on other system performance measures, such as call dropping probability and unsuccessful call probability. Various performance results show that when ACR is used in conjunction with NCQ, extremely low blocking and handover failure probabilities can be achieved for multiparty traffic. © 2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Channel resource management; Fixed channel reservation (FCR); Handover; Low Earth orbit (LEO); Mobile satellite systems (MSSs); Multiparty

Performance analysis and power allocation of AF best relay selection in generic noise - Ahmed, Imtiaz; Nasri, Amir; Michalopoulos, Diomidis S.; Schober, Robert; Mallik, Ranjan K. (IEEE Wireless Communications and Networking Conference, WCNC, 2012)
In this paper, we provide a high signal-to-noise ratio (SNR) error rate analysis of amplify-and-forward (AF) best relay selection in networks impaired by Rayleigh fading and generic, possibly non-Gaussian noise. The derived closed - form asymptotic error rate expressions are applicable to any type of noise with finite moments. Exploiting these analytical results, we formulate a power allocation problem with energy consumption fairness constraints for the source and the relays, which is solved using monomial fitting and a series of geometric programs. The accuracy of the derived analytical results and the effectiveness of the proposed power allocation scheme are confirmed with computer simulations. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Performance analysis for a fully decentralized transmit power allocation scheme for relay-assisted cognitive-radio systems - Mietzner, Jan; Lampe, Lutz; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2008)
We analyze the performance of a fully decentralized (FD) transmit power allocation (TPA) scheme for relay-assisted cognitive-radio (CR) systems. In particular, we assume that the frequency band chosen by the CR relay network for unlicensed spectrum usage overlaps with an active primary narrowband link. The considered FD-TPA scheme maximizes the signal-to-noise- plus-interference ratio at the destination node of the CR network according to a best-effort strategy, while limiting the interference experienced by the primary receiver. Numerical performance results show substantial improvements compared to non-cooperative transmission. Moreover, the performance of the FD-TPA scheme is close to that of the optimal centralized power allocation solution. © 2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Performance analysis of a multi-hop communication system with decode-and-forward relaying - Dhaka, Kalpana; Mallik, Ranjan K.; Schober, Robert (IEEE International Conference on Communications, 2011)
This paper analyzes the performance of a multi-hop wireless communication system, consisting of a source node, N intermediate nodes or relays, and a destination node in a Rayleigh fading environment with decode-and-forward relaying at each intermediate node. The data is therefore transmitted from source to destination through N+1 hops. Two types of modulation, namely, M-ary phase-shift keying (MPSK) and orthogonal M-ary frequency-shift keying (OMFSK), are considered for the transmitted data. In case of MPSK, each relay performs coherent detection, while in case of OMFSK, each relay performs non-coherent detection. Using a difference equation approach, analytical expressions for the end-to-end symbol error probability are derived in both cases. We find that (1) although the performance degrades with increasing number of hops for fixed average signal-to-noise ratio per hop, the incremental degradation in performance with the addition of each extra hop decreases, (2) when each node transmits with fixed power, multi-hop transmission offers significant performance improvement over direct transmission. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Coherent and non-coherent detection; decode-and-forward (DF) relaying; M-ary phase-shift keying (MPSK); multi-hop communication; orthogonal M-ary frequency-shift keying (OMFSK); symbol error probability (SEP)

Performance analysis of a multi-hop power line communication system over log-normal fading in presence of impulsive noise - Dubey, Ankit; Mallik, Ranjan K.; Schober, Robert (IET Communications, 2015)
The authors present a study on the end-to-end average bit error rate (BER), the average channel capacity and the outage performance of a multi-hop power line communication (PLC) system equipped with decode-and-forward (DF) relays. To combat the issue of distance dependent signal attenuation, multi-hop data transmission has recently been introduced for PLC systems. However, apart from the distance dependent signal attenuation, PLC systems also suffer from (i) the variation in signal amplitude (fading) because of reflections and (ii) impulsive noise. Thus, in this study, the channel for each hop of the multi-hop PLC system is modelled by a log-normal fading amplitude, which is clubbed to a distance dependent signal attenuation factor. To consider the effect of the impulsive noise along with the background noise, the additive noise at each node is modelled by a Bernoulli-Gaussian process. Analytical expressions for the end-to-end average BER for binary phase-shift keying, the average channel capacity and the outage probability are obtained. The merit of the multi-hop PLC system over a conventional direct transmission PLC system for fixed transmission power is shown through numerical results. The authors' results show that with increasing number of DF relays, the end-to-end average BER, the average channel capacity and the outage performance improve.<br

Performance analysis of a power line communication system employing selection combining in correlated log-normal channels and impulsive noise - Dubey, Ankit; Mallik, Ranjan K.; Schober, Robert (IET Communications, 2014)
The authors analyse an L -channel selection combining (SC) scheme for a power line communication (PLC) system with binary phase-shift keying. The focus is on improving the reliability in data transfer of the system instead of improving the data rate. To enhance the reliability in data transfer, multiple PLC channels are used to send the same information-bearing signal to the receiver. The L PLC channels are subject to log-normal fading, which is modelled by a multivariate log-normal distribution with an exponential correlation. The channels are also corrupted by additive impulsive noise as well as thermal noise. To consider the effect of both types of noises, they adopt a Gaussian mixture noise model, in which the additive noise samples are taken from a Bernoulli-Gaussian process. The system performance is evaluated in terms of the average bit error rate and the average channel capacity, for which approximate closed form expressions are derived. Numerical results showing the impact of the number of PLC channels, the amount of correlation, the noise scenarios, and the fading environments on the performance are presented. The authors' results show that the performance improves with increasing number of PLC channels; however, the amount of improvement reduces with increasing channel correlation.<br

Performance Analysis of Cooperative NOMA with Dynamic Decode-and-Forward Relaying - Zhou, Yong; Wong, Vincent W. S.; Schober, Robert (GLOBECOM 2017 - 2017 IEEE Global Communications Conference, 2017)
Non-orthogonal multiple access (NOMA) is a promising multiple access technique, which exploits the power domain to enhance the spectral efficiency of the fifth generation (5G) wireless networks. In this paper, we propose a dynamic decode-and-forward (DDF) based cooperative NOMA scheme for downlink transmission to enhance the reception reliability of spatially random users. In DDF-based cooperative NOMA, the user closer to the base station decodes the superimposed mixture of the users' signals received from the base station based on partial reception, and then forwards the signal intended for the far user. To avoid the need for instantaneous channel state information at the base station, we consider random user pairing, where the users are randomly paired for NOMA transmission. Tools from point process theory are utilized to derive the outage probability of the proposed DDF-based cooperative NOMA scheme. Simulation results validate the performance analysis and demonstrate the performance gains of the proposed DDF-based cooperative NOMA scheme over conventional NOMA and cooperative NOMA.<br
Keywords: NOMA; Base stations; Relays; Downlink; Power system reliability; Probability; Signal to noise ratio

Performance analysis of decode-and-forward multi-hop communication: A difference equation approach - Dhaka, Kalpana; Mallik, Ranjan K.; Schober, Robert (IEEE Transactions on Communications, 2012)
The performance of decode-and-forward multi-hop communication is analyzed in a Rayleigh fading environment. Analytical expressions for the end-to-end symbol error probability are derived in the cases of M-ary phase-shift keying with coherent detection and orthogonal M-ary frequency-shift keying with non-coherent detection using a difference equation approach. When the path loss exponent is greater than one, each node transmits with the same power as that of a direct transmission source, and the relays are equispaced along the line joining the source and the destination, the performance improves with increasing number of hops. Furthermore, for fixed average signal-to-noise ratio per hop, the incremental degradation in performance when adding more hops decreases with each extra hop. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Coherent and non-coherent detection; Decodeand-forward (DF) relaying; Difference equation; M-ary phaseshift keying (MPSK); Multi-hop communication; Orthogonal M-ary frequency-shift keying (OMFSK); Power allocation; Symbol error probability (SEP)

Performance analysis of free-space optical systems in gamma-gamma fading - Bayaki, Ehsan; Schober, Robert; Mallik, Ranjan K. (GLOBECOM - IEEE Global Telecommunications Conference, 2008)
Atmospheric turbulence induced fading is one of the main impairments affecting free-space optics (FSO). In recent years, Gamma-Gamma fading has become the dominant fading model for FSO links because of its excellent agreement with measurement data for a wide range of turbulence conditions. In this paper, we express the bit error rate of intensity modulated FSO with direct detection in single-input single-output and multiple-input multiple-output Gamma-Gamma fading channels as generalized infinite power series with respect to the signal-to- noise ratio. For fast numerical evaluation these power series are truncated to a finite number of terms and an upper bound for the associated approximation error is provided. Another contribution of this paper is the extension of the well-known RF concepts of diversity and combining gain to FSO and Gamma-Gamma fading. © 2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Performance analysis of MIMO free-space optical systems in Gamma-Gamma fading - Bayaki, Ehsan; Schober, Robert; Mallik, Ranjan K. (IEEE Transactions on Communications, 2009)
Atmospheric turbulence induced fading is one of the main impairments affecting free-space optics (FSO) communications. In recent years, Gamma-Gamma fading has become the dominant fading model for FSO links because of its excellent agreement with measurement data for a wide range of turbulence conditions. However, in contrast to RF communications, the analysis techniques for FSO are not well developed and prior work has mostly resorted to simulations and numerical integration for performance evaluation in Gamma-Gamma fading. In this paper, we express the pairwise error probabilities of single-input single-output (SISO) and multiple-input multiple-output (MIMO) FSO systems with intensity modulation and direct detection (IM/DD) as generalized infinite power series with respect to the signal-to-noise ratio. For numerical evaluation these power series are truncated to a finite number of terms and an upper bound for the associated approximation error is provided. The resulting finite power series enables fast and accurate numerical evaluation of the bit error rate of IM/DD FSO with on-off keying and pulse position modulation in SISO and MIMO Gamma-Gamma fading channels. Furthermore, we extend the well-known RF concepts of diversity and combining gain to FSO and Gamma-Gamma fading. In particular, we provide simple closed-form expressions for the diversity gain and the combining gain of MIMO FSO with repetition coding across lasers at the transmitter and equal gain combining or maximal ratio combining at the receiver. © 2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Combining gain; Diversity gain; Free-space optics; Gamma-Gamma fading; Generalized infinite power series; Pairwise error probability

Performance Analysis of Near-Optimal Energy Buffer Aided Wireless Powered Communication - Morsi, Rania; Michalopoulos, Diomidis; Schober, Robert (IEEE Transactions on Wireless Communications, 2017)
In this paper, we consider a wireless powered communication system, where an energy harvesting (EH) node harvests energy from a radio frequency (RF) signal broadcasted by an access point (AP) in the downlink (DL). The node stores the harvested energy in an energy buffer and uses the stored energy to transmit data to the AP in the uplink (UL). We investigate two simple online transmission policies for the EH node, namely a best-effort policy and an on-off policy, which do not require knowledge of the EH profile nor channel knowledge. In particular, for both policies, the EH node transmits in each time slot with a constant desired power if sufficient energy is available in its energy buffer. Otherwise, the node transmits with the maximumpossible power in the best-effort policy and remains silent in the on-off policy. For both policies, we use the theory of discrete-time continuous-state Markov chains to analyze the limiting distribution of the stored energy for finite-and infinite-size energy buffers. We provide this limiting distribution in closed form for a Nakagami-m fading DL channel and analyze the outage probability for a Nakagami-m fading UL channel. All derived analytical results are not limited to EH via RF WPT but are applicable for any independent and identically distributed EH process from e.g. solar and wind energy. Our results reveal that, for low-to-medium outage probabilities, the best-effort policy is superior to the on-off policy and the optimal UL transmit power of the EH node that minimizes the outage probability is always less than the average harvested power. The opposite behaviour is observed for high outage probabilities. Furthermore, we show that the minimum outage probability of the two proposed policies is near-optimal.
Keywords: Energy harvesting; energy storage; Markov processes; wireless power transmission

Performance Analysis of OSTBC Relaying in AF MIMO Relay Systems With Imperfect CSI - Arti, M. K.; Mallik, Ranjan K.; Schober, Robert (IEEE Transactions on Vehicular Technology, 2014)
In this paper, the transmission of orthogonal space-time block codes (OSTBCs) in amplify-and-forward (AF) multiple-input-multiple-output (MIMO) relay networks, with imperfect channel state information (CSI), is considered. Individual channel estimation and time-efficient cascaded (for estimating the product of channel matrices) channel estimation protocols are used for estimating the channel matrices required for decoding of OSTBC data at the destination. We derive tight approximations for the moment-generating function (m.g.f.) of the received signal-to-noise ratio at the destination node with imperfect CSI, by ignoring higher order noise terms, in Rayleigh fading. Using the derived m.g.f. expression, we obtain the analytical symbol error rate (SER) of the AF MIMO relay system for general OSTBCs with M-ary phase-shift keying constellation. The diversity order of the MIMO OSTBC relay system is also derived for some special cases by using the SER expression.<br
Keywords: Relays; MIMO; Channel estimation; Decoding; Noise; Protocols; Approximation methods

Performance Analysis of Wireless Powered Communication with Finite/Infinite Energy Storage - Morsi, Rania; Michalopoulos, Diomidis; Schober, Robert (International Conference on Communications ICC, 2015)
In this paper, we consider an energy harvesting (EH) node which harvests energy from a radio frequency (RF) signal broadcasted by an access point (AP) in the downlink (DL). The node stores the harvested energy in an energy buffer and uses the stored energy to transmit data to the AP in the uplink (UL). We consider a simple transmission policy, which accounts for the fact that in practice the EH node may not have knowledge of the EH profile nor of the UL channel state information. In particular, in each time slot, the EH node transmits with either a constant desired power or a lower power if not enough energy is available in its energy buffer. For this simple policy, we use the theory of discrete-time continuous-state Markov chains to analyze the limiting distribution of the stored energy for finite-and infinitesize energy buffers. Moreover, we take into account imperfections of the energy buffer and the circuit power consumption of the EH node. For a Rayleigh fading DL channel, we provide the limiting distribution of the energy buffer content in closed form. In addition, we analyze the average error rate (AER) and the outage probability of a Rayleigh faded UL channel and show that the diversity order is not affected by the finite capacity of the energy buffer. Our results reveal that, except for high outage probabilities and high AERs, the optimal transmit power by the EH node is less than the average harvested power and increases with the capacity of the energy buffer.
Keywords: Buffer storage; Limiting; Energy storage; Fading; Probability density function; Approximation methods; Wireless communication

Performance and design of coherent and differential space-time coded FSO systems - Bayaki, Ehsan; Schober, Robert (Journal of Lightwave Technology, 2012)
Free-space optical (FSO) communication enables high rate data transmission over the atmospheric channel. However, turbulence-induced fading poses severe challenges for operating these systems. Employing spatial diversity has been proposed as an effective measure to improve system performance. In this paper, we first develop a comprehensive model for multiple-input multiple-output (MIMO) coherent and differential FSO systems with heterodyne detection taking into account all relevant signal and noise terms. For the sake of comparison, a similar model is also developed for direct detection. An asymptotic performance analysis is presented for MIMO FSO systems employing coherent and differential space-time codes (STCs) over Gamma-Gamma fading channels. We consider the practically important case of two transmit and an arbitrary number of receive apertures and provide a simple STC design criterion for coherent and differential FSO systems. Our results reveal that, in contrast to FSO systems with intensity modulation and direct detection (IM/DD), for coherent and differential FSO systems, orthogonal space-time block codes previously introduced in the RF literature, are preferable over repetition STCs, which do not yield full diversity. We quantify the asymptotic performance gain of coherent space-time coded FSO systems compared to IM/DD systems and show that this gain is mainly caused by the superiority of heterodyne detection compared to direct detection rather than the different STC and modulation designs. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Atmospheric turbulence; coherent detection; free-space optical communication; multiple-input multiple-output; space-time code design

Performance and optimization of amplify-and-forward cooperative diversity systems in generic noise and interference - Nasri, Amir; Schober, Robert; Blake, Ian F. (IEEE Transactions on Wireless Communications, 2011)
Cooperative diversity systems have received significant attention recently as a distributed means of exploiting the inherent spatial diversity of wireless networks. In this paper, we consider a cooperative diversity system consisting of a source, a destination, and multiple single-hop amplify-and-forward relays, and provide a mathematical framework for the asymptotic analysis of this system in generic noise and interference for high signal-to-noise ratios. Assuming independent Rayleigh fading for all links in the network and orthogonal relay-destination channels, we obtain simple and elegant closed-form expressions for the asymptotic symbol and bit error rates valid for arbitrary linear modulation formats, arbitrary numbers of relays, and arbitrary types of noise and interference with finite moments including co-channel interference, ultra-wideband interference, impulsive ∈-mixture noise, generalized Gaussian noise, and Gaussian noise. Furthermore, we exploit the derived analytical error rate expressions to develop power allocation, relay selection, and relay placement schemes that are asymptotically optimal in environments with generic noise and interference. In general, the power allocation problem results in a geometric program which can be solved efficiently numerically. For the special case of only one relay, we provide a closed-form result for the optimal power allocation. Simulation results confirm our analysis and illustrate that, in non-Gaussian noise, the proposed power allocation, relay selection, and relay placement schemes lead to large performance gains compared to their conventional counterparts optimized for Gaussian noise. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: amplify-and-forward relaying; Cooperative diversity; generic noise and interference; nonGaussian noise; performance analysis; power allocation; relay placement; relay selection

Performance and optimization of network-coded cooperative diversity systems - Nasri, Amir; Schober, Robert; Uysal, Murat (IEEE Transactions on Communications, 2013)
In this paper, we study network-coded cooperative diversity (NCCD) systems comprising multiple sources, one relay, and one destination, where the relay detects the packets received from all sources and performs Galois field (GF) network coding over rm GF(2m) before forwarding a single packet to the destination. Assuming independent Rayleigh fading for all links of the network, we derive simple and accurate closed-form approximations for the asymptotic symbol and bit error rates of NCCD systems. The derived error rate expressions are valid for arbitrary numbers of sources, arbitrary modulation schemes, and arbitrary constellation mappings and provide significant insight into the impact of various system and channel parameters on performance. Moreover, these expressions can be exploited for optimization of the constellation mapping as well as for formulation of various NCCD system optimization problems including optimal power allocation, relay selection, and relay placement. © 1972-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Cooperative diversity; cooperative maximal-ratio combining; decode-and-forward; link adaptive regeneration; performance analysis and optimization

Performance evaluation of BICM-OFDM systems impaired by UWB interference - Nasri, Amir; Schober, Robert; Lampe, Lutz (IEEE International Conference on Communications, 2008)
In this paper, we propose a theoretical framework for the analysis of the impact of ultra-wideband (UWB) interference on systems that use the popular combination of bit-interleaved coded modulation (BICM) and orthogonal frequency-division multiplexing (OFDM). For the UWB interference we consider multi-band OFDM (MB-OFDM), direct-sequence UWB (DS-UWB), and impulse-radio UWB (IR-UWB) formats following recent IEEE/ECMA standards and standard proposals. Our analysis is applicable to generic BICM-OFDM victim systems including IEEE 802.11 wireless local area networks (WLANs), IEEE 802.16 wireless access systems (WiMAX), and 4th generation mobile communication systems. Besides the exact analysis we also calculate the bit-error rate for the case when the UWB interference is modeled as additional Gaussian noise. Our results show that in general the BER of the BICM-OFDM system strongly depends on the type of the UWB interference and the sub-carrier spacing. While the Gaussian approximation is very accurate for DS-UWB, it may severely over- or underestimate the true BER for MB-OFDM and IR-UWB interference. ©2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Performance evaluation of bluetooth systems with LDI, modified LDI, and NSD receivers - Bayaki, Ehsan; Lampe, Lutz; Schober, Robert (IEEE Transactions on Vehicular Technology, 2008)
Bluetooth is a popular short-range low-power radio standard for wireless personal area networks. Bluetooth transmitters employ Gaussian frequency shift keying (GFSK) and simple block codes for error correction. Recently, two new receiver designs for Bluetooth devices, which are the so-called modified limiter-discriminator detector with integrate-and-dump filtering (LDI) and noncoherent sequence detection (NSD), have been proposed in the literature. While the modified LDI receiver is a concatenation of a conventional LDI detector with an improved error-correction decoder, the NSD receiver fully takes into account the memory introduced by the GFSK. Both receivers have been shown to improve the Bluetooth system performance in terms of physical-layer metrics such as bit-error rate and packet-error rate. In this paper, we present a comprehensive performance evaluation considering practically more relevant metrics such as throughput, delay, and delay jitter at the medium-access control layer. To this end, we develop an evaluation framework, which includes the spatial distribution of Bluetooth devices, path loss, fading, realistic data traffic models, scheduling, automatic repeat request, and baseband packet selection. Our numerical and simulation results verify that the newly introduced Bluetooth receivers, especially NSD, offer a significant performance enhancement for Bluetooth systems in terms of practically relevant measures. © 2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Bluetooth; Delay; Limiter-discriminator detector with integrate-and-dump filtering (LDI) receiver; Noncoherent sequence detection (NSD) receiver; Performance evaluation; Throughput

Performance evaluation of coordinated dual-cell transmission based on random unitary beamforming with user scheduling - Zhu, Jun; Yang, Hong Chuan; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2012)
In this paper, we present and study the performance of a coordinated random beamforming transmission strategy for dual-cell multiple-input single-output (MISO) systems. The strategy under consideration has low complexity as the coordinating base stations need to share only the indices of the qualified beamforming vectors. Focusing on single-user scheduling in each cell, we analyze exact sum-rate of the resulting system. Based on selected numerical examples, we develop important design guidelines for coordinated random beamforming schemes. We also consider an adaptive implementation approach of the proposed strategy where the number of qualified beamforming vectors are determined based on a certain predetermined threshold. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Performance limits of massive MIMO systems based on Bayes-optimal inference - Wen, Chao-Kai; Wu, Yongpeng; Wong, Kai-Kit; Schober, Robert; Ting, Pangan (2015 IEEE International Conference on Communications (ICC), 2015)
This paper gives a replica analysis for the minimum mean square error (MSE) of a massive multiple-input multipleoutput (MIMO) system by using Bayesian inference. The Bayesoptimal estimator is adopted to estimate the data symbols and the channels from a block of received signals in the spatial-temporal domain. We show that using the Bayes-optimal estimator, the interfering signals from adjacent cells can be separated from the received signals without pilot information of the interfering signals. In addition, the MSEs with respect to the data symbols and the channels of the desired users decrease with the number of receive antennas and the number of data symbols, respectively. There are no residual interference terms that remain bounded away from zero as the numbers of receive antennas and data symbols approach infinity.<br
Keywords: Estimation; Channel estimation; MIMO; Interference; Antennas; Wireless communication; Receivers

Performance of a PLC system in impulsive noise with selection combining - Dubey, Ankit; Mallik, Ranjan K.; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2012)
This paper proposes a selection combining (SC) scheme for a power line communication (PLC) system with binary phase-shift keying. The main purpose is to utilize multiple of independent and non-interfering channels to send an information-bearing signal and to use SC at the receiver end to improve the reliability of the PLC system. The fading coefficient of each PLC channel is modeled by a log-normal distribution, and to include the effects of both background noise and impulsive noise, the additive noise samples are taken from a Bernoulli-Gaussian process. We obtain a closed-form approximation of the bit error rate and an expression for the outage probability of the proposed scheme. The merit of the L-channel PLC system with SC when compared with a single channel PLC system over different fading and impulsive noise scenarios is demonstrated through numerical results. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Bernoulli-Gaussian process; binary phase-shift keying (BPSK); bit error rate (BER); Lambert L-function; log-normal fading; power line communication (PLC); selection combining (SC)

Performance of BICM-OFDM systems in non-gaussian noise and interference - Nasri, Amir; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2008)
In this paper, we present a general mathematical framework for performance analysis of systems employing bit- interleaved coded modulation (BICM) and orthogonal frequency division multiplexing (OFDM). The proposed analysis is general enough to include impairment by general types of noise and interference with finite moments such as additive white Gaussian noise (AWGN), Gaussian mixture noise, narrowband interference, and ultra-wideband interference. We present an asymptotically tight upper bound for the bit error rate (BER) and a closed-form expression for the asymptotic BER at high signal-to-noise ratios. Our analysis shows that, if the popular Euclidean distance metric is used for Viterbi decoding, BICM-OFDM systems optimized for AWGN are also optimum for any other type of noise and interference with finite moments. © 2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Performance of BICM-OFDM systems in UWB interference - Nasri, Amir; Schober, Robert; Lampe, Lutz (IEEE Transactions on Wireless Communications, 2009)
In this paper, we develop an analytical framework for performance analysis of generic bit-interleaved coded modulation orthogonal frequency-division multiplexing (BICM-OFDM) systems impaired by ultra-wideband (UWB) interference. For practical relevance we consider multi-band OFDM (MB-OFDM), direct-sequence UWB (DS-UWB), and impulse-radio UWB (IR-UWB) interference formats following recent IEEE/ECMA standards or standard proposals. Besides the exact analysis we calculate the bit error rate (BER) for the case when the UWB interference is modeled as additional Gaussian noise. Our results show that in general the BER of the BICM-OFDM system strongly depends on the UWB format and the OFDM sub-carrier spacing. While the Gaussian approximation is very accurate for DS-UWB, it may severely over- or underestimate the true BER for MB"OFDM and IR-UWB interference. Our analysis is applicable to e.g. IEEE 802.11 wireless local area networks (WLANs), IEEE 802.16 wireless access systems (WiMAX), and 4th generation mobile communication systems. Furthermore, since the ECMA MB-OFDM standard is also based on the BICM-OFDM concept, our analysis can also be used to evaluate the impact of other UWB signals on ECMA MB-OFDM UWB systems. © 2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Direct-sequence UWB (DS-UWB); Impulse-radio UWB (IR-UWB); Multi-band OFDM (MB-OFDM); No-Gaussian interference; Orthogonal frequency division multiplexing (OFDM); Terms-Bit-interleaved coded modulation (BICM); Ultrawideband (UWB)

Performance of BICM-SC and BICM-OFDM systems with diversity reception in non-gaussian noise and interference - Nasri, Amir; Schober, Robert (IEEE Transactions on Communications, 2009)
In this paper, we present a general mathematical framework for performance analysis of single-carrier (SC) and orthogonal frequency division multiplexing (OFDM) systems employing popular bit-interleaved coded modulation (BICM) and multiple receive antennas. The proposed analysis is applicable to BICM systems impaired by general types of fading (including Rayleigh, Ricean, Nakagami-m, Nakagami-q, and Weibull fading) and general types of noise and interference with finite moments such as additive white Gaussian noise (AWGN), additive correlated Gaussian noise, Gaussian mixture noise, co-channel interference, narrowband interference, and ultra-wideband interference. We present an approximate upper bound for the bit error rate (BER) and an accurate closed-form approximation for the asymptotic BER at high signal-to-noise ratios for Viterbi decoding with the standard Euclidean distance branch metric. For the standard rate-1/2 convolutional code the proposed approximate upper bound and the asymptotic approximation become tight at BERs of 10-6-and 10 -12-, respectively. However, if the code is punctured to higher rates (e.g. 2/3 or 3/4), the asymptotic approximation also becomes tight at a BER of 10-6-. Exploiting the asymptotic BER approximation we show that the diversity gain of BICM systems only depends on the free distance of the code, the type of fading, and the number of receive antennas but not on the type of noise. In contrast their coding gain strongly depends on the noise moments. Our asymptotic analysis shows that as long as the standard Euclidean distance branch metric is used for Viterbi decoding, BICM systems optimized for AWGN are also optimum for any other type of noise and interference with finite moments. © 2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Asymptotic analysis; Bit-interleaved coded modulation (BICM); Coding gain; Diversity gain; Fading channels; Non-Gaussian noise and interference; Orthogonal frequency division multiplexing (OFDM) and single-carrier (SC) systems

Performance of cooperative diversity systems in non-Gaussian environments - Nasri, Amir; Schober, Robert (IEEE International Conference on Communications, 2010)
Cooperative diversity (CD) systems have received significant attention recently as a distributed means of exploiting the inherent spatial diversity of wireless networks. In this paper, we consider a CD system where a source transmits to a destination via multiple single-hop amplify and forward (AF) relays. In particular, we provide a mathematical framework for the asymptotic analysis of this system in general non-Gaussian noise and interference for high signal-to-noise ratios (SNRs). Assuming independent Rayleigh fading for all links in the network, we obtain simple and elegant closed-form expressions for the asymptotic symbol error rate (SER) and bit error rate (BER) valid for arbitrary linear modulation formats, arbitrary numbers of relays, and arbitrary non-Gaussian noise and interference with finite moments. Furthermore, exploiting the derived analytical results, we introduce a new relay selection criterion for non-Gaussian environments. Simulation results confirm our analysis and illustrate that, in non-Gaussian noise, the proposed relay selection criterion can lead to large performance gains compared to the conventional relay selection criterion which was optimized for Gaussian noise. ©2010 Crown.
CRIS-Team Scopus Importer:2020-02-03

Phase noise in mimo systems: Bayesian Cramér-Rao bounds and soft-input estimation - Nasir, Ali A.; Mehrpouyan, Hani; Schober, Robert; Hua, Yingbo (IEEE Transactions on Signal Processing, 2013)
This paper addresses the problem of estimating time varying phase noise caused by imperfect oscillators in multiple-input multiple-output (MIMO) systems. The estimation problem is parameterized in detail and based on an equivalent signal model its dimensionality is reduced to minimize the overhead associated with phase noise estimation. New exact and closed-form expressions for the Bayesian Cramér-Rao lower bounds (BCRLBs) and soft-input maximum a posteriori (MAP) estimators for online, i.e., filtering, and offline, i.e., smoothing, estimation of phase noise over the length of a frame are derived. Simulations demonstrate that the proposed MAP estimators' mean-square error (MSE) performances are very close to the derived BCRLBs at moderate-to-high signal-to-noise ratios. To reduce the overhead and complexity associated with tracking the phase noise processes over the length of a frame, a novel soft-input extended Kalman filter (EKF) and extended Kalman smoother (EKS) that use soft statistics of the transmitted symbols given the current observations are proposed. Numerical results indicate that by employing the proposed phase tracking approach, the bit-error rate performance of a MIMO system affected by phase noise can be significantly improved. In addition, simulation results indicate that the proposed phase noise estimation scheme allows for application of higher order modulations and larger numbers of antennas in MIMO systems that employ imperfect oscillators.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Bayesian Cramér Rao lower bound (BCRLB); Extended Kalman smoother (EKS); Maximum-a-posteriori (MAP); Multiple-input multiple-output (MIMO); Soft-decision extended Kalman filter (EKF); WIENER phase noise

Physical layer security for massive MIMO systems - Zhu, Jun; Schober, Robert; Bhargava, Vijay K. (Institution of Engineering and Technology, 2017)
The chapter is organised as follows. In Sections 5.1 and 5.2, we briefly review the fundamentals of massive MIMO and physical layer security, respectively. In Section 5.3, we motivate the chapter by illustrating why we consider physical layer security for massive MIMO systems. The considered model and the performance evaluation metrics for secure massive MIMO systems are introduced in Sections 5.4 and 5.5, respectively. Section 5.6 studies linear precoding for downlink secure massive MIMO transmission. In Section 5.7, we conclude with abrief summary of this chapter.
CRIS-Team Scopus Importer:2022-06-05
Keywords: Alamouti coding; Antenna arrays; Antenna selection strategies; Correlation; Full-duplex wiretap channels; Imperfect feedback; Low feedback overhead; Low hardware complexity; MIMO communication; Multiple-input multiple-output wiretap channels; Physical layer security; Secrecy performance; Secure transmissions; Space-time block codes; TAS; Telecommunication security; Transmit antenna selection; Transmitting antennas

Physical layer security for massive MIMO systems impaired by phase noise - Zhu, Jun; Schober, Robert; Bhargava, Vijay K. (2016 IEEE 17th International Workshop on Signal Processing Advances in Wireless Communications (SPAWC), 2016)
In this paper, we investigate the impact of phase noise on the secrecy performance of downlink massive MIMO systems in the presence of a passive multiple-antenna eavesdropper. Thereby, for the base station (BS) and the legitimate users, the effect of multiplicative phase noise is taken into account, whereas the eavesdropper is assumed to employ ideal hardware. We derive a lower bound for the ergodic secrecy rate of a given user when matched filter data precoding and artificial noise transmission are employed at the BS. Based on the derived analytical expression, we investigate the impact of the various system parameters on the secrecy rate. Our analytical and simulation results reveal that distributively deployed local oscillators (LOs) can achieve a better performance than one common LO for all BS antennas as long as a sufficient amount of power is assigned for data transmission.<br
Keywords: Phase noise; MIMO; Hardware; Downlink; Precoding; Channel estimation; Data communication

Physical layer security in SWIPT systems with nonlinear energy harvesting circuits - Su, Yuqing; Ng, Derrick Wing Kwan; Schober, Robert (wiley, 2018)
The discrepancy between the properties of practical nonlinear harvesting circuits and the linear harvesting model conventionally assumed in the literature may cause a severe mismatch for resource allocation, leading to insecure simultaneous wireless information and power transfer (SWIPT) systems. This chapter presents novel beamforming designs enabling secure SWIPT based on a practical nonlinear energy harvesting model. It introduces the adopted channel model and a practical nonlinear RF-based energy harvesting model. The chapter studies the beamforming design for secure communication in SWIPT systems taking into account the impact of imperfect channel state information (CSI). Simulation results are presented to illustrate the performance of proposed resource allocation algorithm. The chapter aims to maximize the system achievable secrecy rate while guaranteeing a required minimum harvested power at the energy harvesting receivers (ERs).
CRIS-Team Scopus Importer:2022-06-05
Keywords: Energy harvesting receivers; Imperfect channel state information; Resource allocation; RF-based energy harvesting model; Simulation results; SWIPT systems

Physics-based Modeling and Scalable Optimization of Large Intelligent Reflecting Surfaces - Najafi, Marzieh; Jamali, Vahid; Schober, Robert; Vincent Poor, H. (IEEE Transactions on Communications, 2020)
Intelligent reflecting surfaces (IRSs) have the potential to transform wireless communication channels into smart reconfigurable propagation environments. To realize this new paradigm, the passive IRSs have to be large, especially for communication in far-field scenarios, so that they can compensate for the large end-to-end path-loss, which is caused by the multiplication of the individual path-losses of the transmitter-to-IRS and IRS-to-receiver channels. However, optimizing a large number of sub-wavelength IRS elements imposes a significant challenge for online transmission. To address this issue, in this paper, we develop a physics-based model and a scalable optimization framework for large IRSs. The basic idea is to partition the IRS unit cells into several subsets, referred to as tiles, model the impact of each tile on the wireless channel, and then optimize each tile in two stages, namely an offline design stage and an online optimization stage. For physics-based modeling, we borrow concepts from the radar literature, model each tile as an anomalous reflector, and derive its impact on the wireless channel for a given phase shift by solving the corresponding integral equations for the electric and magnetic vector fields. In the offline design stage, the IRS unit cells of each tile are jointly designed for the support of different transmission modes, where each transmission mode effectively corresponds to a given configuration of the phase shifts that the unit cells of the tile apply to an impinging electromagnetic wave. In the online optimization stage, the best transmission mode of each tile is selected such that a desired quality-of-service (QoS) criterion is maximized. We consider an exemplary downlink system and study the minimization of the base station (BS) transmit power subject to QoS constraints for the users. Since the resulting mixed-integer programming problem for joint optimization of the BS beamforming vectors and the tile transmission modes is non-convex, we derive two efficient suboptimal solutions, which are based on alternating optimization and a greedy approach, respectively. We show that the proposed modeling and optimization framework can be used to efficiently optimize large IRSs comprising thousands of unit cells.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Optimization; Quality of service; Radar cross-sections; Receivers; Solid modeling; Surface waves; Wireless communication

Physics-based Modeling of Large Intelligent Reflecting Surfaces for Scalable Optimization - Najafi Kalyani, Marzieh; Jamali, Vahid; Schober, Robert; Poor, H. Vincent (2020 54TH ASILOMAR CONFERENCE ON SIGNALS, SYSTEMS, AND COMPUTERS, 2020)
CRIS-Team WoS Importer:2021-09-03

Pilot Spoofing Attack by Multiple Eavesdroppers - Huang, Ke-Wen; Wang, Hui-Ming; Wu, Yongpeng; Schober, Robert (IEEE Transactions on Wireless Communications, 2018)
In this paper, we investigate the design of a pilot spoofing attack (PSA) carried out by multiple single-antenna eavesdroppers (Eves) in a downlink time-division duplex system, where a multiple antenna base station (BS) transmits confidential information to a single-antenna legitimate user. During the uplink channel training phase, multiple Eves collaboratively impair the channel acquisition of the legitimate link, aimed at maximizing the wiretapping signal-to-noise ratio (SNR) in the subsequent downlink data transmission phase. Two different scenarios are investigated: 1) the BS is unaware of the PSA and 2) the BS attempts to detect the presence of the PSA. For both scenarios, we formulate wiretapping SNR maximization problems. For the second scenario, we also investigate the probability of successful detection and constrain it to remain below a pre-designed threshold. The two resulting optimization problems can be unified into a more general non-convex optimization problem, and we propose an efficient algorithm based on the minorization-maximization (MM) method and the alternating direction method of multipliers (ADMM) to solve it. The proposed MM-ADMM algorithm is shown to converge to a stationary point of the general problem. In addition, we propose a semi-definite relaxation (SDR) method as a benchmark to evaluate the efficiency of the MM-ADMM algorithm. Numerical results show that the MM-ADMM algorithm achieves near-optimal performance and is computationally more efficient than the SDR-based method.<br
Keywords: Training; Channel estimation; Uplink; Signal to noise Ratio; Optimization; Downlink; MIMO communication

Polynomial-Expansion Multi-Cell Aware Detector for Uplink Massive MIMO Systems with Imperfect CSI - Zarei, Shahram; Aulin, Jocelyn; Gerstacker, Wolfgang; Schober, Robert (2015 IEEE Global Communications Conference (GLOBECOM), 2015)
In this paper, we propose a multi-cell aware (MCA) detector for uplink multi-cell massive multiple-input multiple-output (MIMO) systems. The proposed detector exploits knowledge of the channel statistics but data exchange between different base stations over backhaul links is not required. A correlated channel model is considered and the adopted channel state information (CSI) acquisition model includes the effects of estimation errors and pilot contamination. In contrast to the conventional minimum mean square error (MMSE) detector, which mitigates only the multiple-access interference (MAI) in the target cell, the proposed detector takes the interference from neighboring cells and pilot contamination into account and therefore achieves substantially higher sum rates. Moreover, in order to reduce the computational complexity, the matrix inversion required for the MCA detector is approximated by a matrix polynomial leading to a new polynomial-expansion MCA (PEMCA) detector. Using results from random matrix theory, we derive closed-form expressions for the optimal coefficients of the matrix polynomial, which only depend on the channel statistics but not on the channel realizations. Our simulation results show that the PEMCA detector with only a few terms in the matrix polynomial achieves a considerably higher sum rate than the conventional MMSE detector while having a lower computational complexity.<br
Keywords: Detectors; MIMO; Channel estimation; Interference; Uplink; Contamination; Complexity theory

Power Allocation and Scheduling for SWIPT Systems with Non-linear Energy Harvesting Model - Boshkovska, Elena; Morsi, Rania; Ng, Derrick Wing Kwan; Schober, Robert (International Conference on Communications ICC, 2016)
In this paper, we design a resource allocation algorithm for multiuser simultaneous wireless information and power transfer systems for a realistic non-linear energy harvesting (EH) model. In particular, the algorithm design is formulated as a non-convex optimization problem for the maximization of the long-term average total harvested power at EH receivers subject to quality of service requirements for information decoding receivers. To obtain a tractable solution, we transform the corresponding non-convex sum-of-ratios objective function into an equivalent objective function in parametric subtractive form. This leads to a computationally efficient iterative resource allocation algorithm. Numerical results reveal a significant performance gain that can be achieved if the resource allocation algorithm design is based on the non-linear EH model instead of the traditional linear model.

Power allocation for a hybrid energy harvesting relay system with imperfect channel and energy state information - Ahmed, I. Zakir; Ikhlef, Aissa; Wing Kwan Ng, Derrick; Schober, Robert (2014 IEEE Wireless Communications and Networking Conference (WCNC), 2014)
In this paper, we consider both channel state uncertainty and harvested energy state uncertainty for a source-relay-destination communication link where the source and the relay are equipped with hybrid energy sources. Taking into account these uncertainties is of important for practical energy harvesting (EH) communication. While channel state uncertainties also affect conventional communication systems and have been widely studied, harvested energy state uncertainties are specific to energy harvesting systems and have not been considered in the literature before. The considered hybrid energy sources include a constant energy source and an energy harvester. Our objective is to maximize the worst case system throughput over a finite number of transmission intervals. We propose robust optimal offline, optimal online, and suboptimal online power allocation schemes. The offline power allocation design is formulated as an optimization problem which can be solved optimally. For the online case, we propose a dynamic programming (DP) approach to compute the optimal transmit power. To alleviate the prohibitively high complexity inherent to DP, we also propose several suboptimal low-complexity online power allocation schemes. Simulation results confirm the robustness of the proposed power allocation schemes to channel and energy state uncertainties.<br
Keywords: Resource management; Optimized production technology; Uncertainty; Batteries; Channel estimation; Relays

Power allocation for an energy harvesting transmitter with hybrid energy sources - Ahmed, Imtiaz; Ikhlef, Aissa; Ng, Derrick Wing Kwan; Schober, Robert (IEEE Transactions on Wireless Communications, 2013)
In this work, we consider a point - to - point communication link where the transmitter has a hybrid supply of energy. Specifically, the hybrid energy is supplied by a constant energy source and an energy harvester, which harvests energy from its surrounding environment and stores it in a battery which suffers from energy leakage. Our goal is to minimize the power consumed by the constant energy source for transmission of a given amount of data in a given number of time intervals. Two scenarios are considered for packet arrival. In the first scenario, we assume that all data packets have arrived before transmission begins, whereas in the second scenario, we assume that data packets are arriving during the course of data transmission. For both scenarios, we propose an optimal offline transmit power allocation scheme which provides insight into how to efficiently consume the energy supplied by the constant energy source and the energy harvester. For offline power allocation, we assume that causal and non - causal information regarding the channel and the amount of harvested energy is available a priori. For optimal online power allocation, we adopt a stochastic dynamic programming (DP) approach for both considered scenarios. For online power allocation, only causal information regarding the channel and the amount of harvested energy is assumed available. Due to the inherent high complexity of DP, we propose suboptimal online algorithms which are appealing because of their low complexity. Simulation results reveal that the offline scheme performs best among all considered schemes and the suboptimal online scheme provides a good performance - complexity tradeoff. © 2002-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: convex optimization; dynamic programming; Energy harvesting; hybrid energy supply; power allocation

Power Allocation for Conventional and Buffer-Aided Link Adaptive Relaying Systems with Energy Harvesting Nodes - Ahmed, Imtiaz; Ikhlef, Aissa; Schober, Robert; Mallik, Ranjan K. (IEEE Transactions on Wireless Communications, 2014)
In this paper, we consider optimal power allocation for conventional and buffer-aided link adaptive energy harvesting (EH) relay systems, where an EH source communicates with the destination via an EH decode-and-forward relay over fading channels. In conventional relaying, source and relay transmit signals in consecutive time slots whereas in buffer-aided link adaptive relaying, the state of the source-relay and relay-destination channels as well as the amounts of energy available at source and relay determine whether the source or the relay is selected for transmission. Our objective is to maximize the system throughput over a finite number of transmission time slots for both relaying protocols. In case of conventional relaying, we propose an offline and several online joint source and relay transmit power allocation schemes. For offline power allocation, we formulate a convex optimization problem whereas for the online case, we propose a dynamic programming (DP) approach to compute the optimal online transmit power. To alleviate the complexity inherent to DP, we also propose several suboptimal online power allocation schemes. For buffer-aided link adaptive relaying, we show that the joint offline optimization of the source and relay transmit powers along with the link selection results in a mixed integer non-linear program which we solve optimally using the spatial branch-and-bound method. We also propose efficient online power allocation schemes for buffer-aided link adaptive relaying. Simulation results show that buffer-aided link adaptive relaying provides significant performance gains compared to conventional relaying but requires a higher complexity for computation of the power allocation solution. We also show that buffer-aided link adaptive relaying is more robust to changes in the EH rate than conventional relaying.<br
Keywords: Resource management; Relays; Batteries; Protocols; Optimization; Throughput; Fading

Power Allocation for SC-FDE-Based CR Systems Under Explicit Primary User Protection - Wu, Peiran; Schober, Robert; Bhargava, Vijay Kishore (IEEE Communications Letters, 2016)
In this letter, we consider the power allocation for a single-carrier (SC)-based secondary user (SU) transmitter (Tx), which transmits concurrently with an SC or multicarrier (MC) primary user (PU) over the same frequency band. A rate maximization problem for the SU system is formulated subject to an SU-Tx power constraint and an explicit rate loss constraint for the PU system. Due to the nonconvexity of the resulting problem, we propose a successive convex approximation approach to solve the problem where in each iteration closed-form solutions are derived for the power allocation variables of the SU-Tx. We further prove that the proposed algorithm is guaranteed to converge to a local optimum of the original nonconvex problem. Simulation results are provided to show the efficacy of the proposed approach.<br
Keywords: OFDM; Interference; Signal to noise Ratio; Resource Management; Frequency-domain Analysis; Approximation algorithms; Decision support systems

Power allocation in energy harvesting relay systems - Ahmed, Imtiaz; Ikhlef, Aissa; Schober, Robert; Mallik, Ranjan K. (IEEE Vehicular Technology Conference, 2012)
Using energy harvesting nodes can be a viable solution for energy limited cooperative communication systems. In this paper, we consider the optimization of an energy harvesting (EH) relay system, where an EH source communicates with the destination via an EH decode-and-forward (DF) relay. Our objective is to maximize the system throughput over a finite number of transmission intervals. To this end, we propose an offline and several online joint source and relay transmit power allocation schemes. For offline power allocation, we formulate a convex optimization problem which can be solved either in closed form or using standard optimization tools. For the online case, we propose a dynamic programming (DP) approach to compute the optimal online transmit power. To alleviate the complexity inherent to DP, we propose several suboptimal online power allocation schemes. Our simulation results show that the developed suboptimal schemes provide a good complexity-performance tradeoff compared to optimal online power allocation. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Power dispatch and load control with generation uncertainty - Samadi, Pedram; Bahrami, Shahab; Wong, Vincent W.S.; Schober, Robert (2015 IEEE Global Conference on Signal and Information Processing (GlobalSIP), 2015)
In this paper, we focus on the problem of joint load scheduling and generation management to better match supply and demand. We formulate an optimization problem to jointly minimize the generation cost and discomfort cost of the users subject to the voltage and power balance equations for the equivalent circuit of the power system. The optimal power flow (OPF) equations are solved using semidefinite programming (SDP) relaxation technique. In our system model, we assume that users can exploit renewable energy resources (RERs). RERs are random in nature and may cause voltage variations in different nodes of the system. To minimize the risk of having high voltage values, a barrier term is added to the objective function. This term is calculated based on the concept of conditional value-at-risk (CVaR). Simulation results show that compared to the case where there is no control over the load, our proposed algorithm reduces the generation cost by better matching the generation and demand. Moreover, the proposed algorithm reduces the voltage variations at different nodes of the system.<br
Keywords: Reactive power; Power generation; Power demand; Cost function; Supply and demand; Mathematical model; Admittance

Power Efficiency, Overhead, and Complexity Tradeoff of IRS Codebook Design – Quadratic Phase-Shift Profile - Jamali, Vahid; Najafi, Marzieh; Schober, Robert; Vincent Poor, H. (IEEE Communications Letters, 2021)
In this paper, we focus on large intelligent reflecting surfaces (IRSs) and propose a new codebook construction method to obtain a set of predesigned phase-shift configurations for the IRS unit cells. Since the overhead for channel estimation and the complexity of online optimization for IRS-assisted communications scale with the size of the phase-shift codebook, the design of small codebooks is of high importance. We show that there exists a fundamental tradeoff between power efficiency and the size of the codebook. We first analyze this tradeoff for baseline designs that employ a linear phase-shift across the IRS. Subsequently, we show that an efficient design for small codebooks mandates higher-order phase-shift variations across the IRS. Consequently, we propose a quadratic phase-shift design, derive its coefficients as a function of the codebook size, and analyze its performance. Our simulation results show that the proposed design yields a higher power efficiency for small codebooks than the linear baseline designs.
CRIS-Team Scopus Importer:2021-04-09
Keywords: and power efficiency; Channel estimation; channel estimation overhead; complexity; Complexity theory; Discrete Fourier transforms; Downlink; Intelligent reflecting surfaces; Millimeter wave communication; Optimization; phase-shift design; Transmission line matrix methods

Power Efficient and Secure Full-Duplex Wireless Communication Systems - Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (Power Efficient and Secure Full-Duplex Wireless Communication Systems, 2015)
In this paper, we study resource allocation for a full-duplex (FD) radio base station serving multiple half-duplex (HD) downlink and uplink users simultaneously. The considered resource allocation algorithm design is formulated as a non-convex optimization problem taking into account minimum required receive signal-to-interference-plus-noise ratios (SINRs) for downlink and uplink communication and maximum tolerable SINRs at potential eavesdroppers. The proposed optimization framework enables secure downlink and uplink communication via artificial noise generation in the downlink for interfering the potential eavesdroppers. We minimize the weighted sum of the total downlink and uplink transmit power by jointly optimizing the downlink beamformer, the artificial noise covariance matrix, and the uplink transmit power. We adopt a semidefinite programming (SDP) relaxation approach to obtain a tractable solution for the considered problem. The tightness of the SDP relaxation is revealed by examining a sufficient condition for the global optimality of the solution. Simulation results demonstrate the excellent performance achieved by the proposed scheme and the significant transmit power savings enabled optimization of the artificial noise covariance matrix.

Power efficient and secure multiuser communication systems with wireless information and power transfer - Leng, Shiyang; Ng, Derrick Wing Kwan; Schober, Robert (2014 IEEE International Conference on Communications Workshops, ICC 2014, 2014)
In this paper, we study resource allocation algorithm design for power efficient secure communication with simultaneous wireless information and power transfer (WIPT) in multiuser communication systems. In particular, we focus on power splitting receivers which are able to harvest energy and decode information from the received signals. The considered problem is modeled as an optimization problem which takes into account a minimum required signal-to-interference-plus-noise ratio (SINR) at multiple desired receivers, a maximum tolerable data rate at multiple multi-antenna potential eavesdroppers, and a minimum required power delivered to the receivers. The proposed problem formulation facilitates the dual use of artificial noise in providing efficient energy transfer and guaranteeing secure communication. We aim at minimizing the total transmit power by jointly optimizing transmit beamforming vectors, power splitting ratios at the desired receivers, and the covariance of the artificial noise. The resulting non-convex optimization problem is transformed into a semidefinite programming (SDP) and solved by SDP relaxation. We show that the adopted SDP relaxation is tight and achieves the global optimum of the original problem. Simulation results illustrate the significant power saving obtained by the proposed optimal algorithm compared to suboptimal baseline schemes. © 2014 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Power-Efficient and Secure WPCNs With Hardware Impairments and Non-Linear EH Circuit - Boshkovska, Elena; Wing Kwan Ng, Derrick; Dai, Linglong; Schober, Robert (IEEE Transactions on Communications, 2017)
In this paper, we design a robust resource allocation algorithm for a wireless-powered communication network (WPCN) taking into account residual hardware impairments (HWIs) at the transceivers, the imperfectness of the channel state information, and the non-linearity of practical radio frequency energy harvesting circuits. In order to ensure power-efficient secure communication, physical layer security techniques are exploited to deliberately degrade the channel quality of a multiple-antenna eavesdropper. The resource allocation algorithm design is formulated as a non-convex optimization problem for minimization of the total power consumption in the network, while guaranteeing the quality of service of the information receivers in terms of secrecy rate. The globally optimal solution of the optimization problem is obtained via a 2-D search and semidefinite programming relaxation. To strike a balance between computational complexity and system performance, a low-complexity iterative suboptimal resource allocation algorithm is also proposed. Numerical results demonstrate that both the proposed optimal and suboptimal schemes can significantly reduce the total system power consumption required for guaranteeing secure communication, and unveil the impact of HWIs on the system performance: 1) residual HWIs create a system performance bottleneck in WPCN in the high transmit/receive power regimes; 2) increasing the number of transmit antennas can effectively reduce the power consumption of wireless power transfer and alleviate the performance degradation due to residual HWIs; and 3) imperfect CSI exacerbates the impact of residual HWIs, which increases the power consumption of both wireless power and wireless information transfer.<br
Keywords: Wireless communication; Algorithm design and Analysis; Communication system security; Resource Management; Hardware; Energy harvesting; Security

Power-Efficient and Secure WPCNs with Residual Hardware Impairments and a Non-Linear EH Model - Boshkovska, Elena; Ng, Derrick Wing Kwan; Schober, Robert (GLOBECOM 2017 - 2017 IEEE Global Communications Conference, 2017)
In this paper, we design a resource allocation algorithm for a wireless-powered communication network (WPCN) taking into account residual hardware impairments (HWIs) at the transceivers and the non-linearity of radio frequency (RF) energy harvesting (EH) circuits. In order to ensure communication secrecy, physical layer (PHY) security techniques are exploited to deliberately degrade the channel quality of a multiple-antenna eavesdropper. The resource allocation algorithm design is formulated as a non-convex optimization problem for the minimization of the total consumed power in the network, while guaranteeing the quality of service (QoS) of the information receivers (IRs). The globally optimal solution of the optimization problem is obtained via a one-dimensional search and semidefinite programming (SDP) relaxation. Numerical results demonstrate that the proposed scheme can significantly reduce the power consumption of the system compared to a baseline scheme, which assumes ideal hardware.<br
Keywords: Hardware; Wireless communication; Communication system security; Resource management; Algorithm design and analysis; Distortion; Security

Power-Efficient Beam Designs for Millimeter Wave Communication Systems - Zhang, Jianjun; Huang, Yongming; Wang, Jiaheng; Schober, Robert; Yang, Luxi (IEEE Transactions on Wireless Communications, 2020)
The use of the millimeter wave (mmwave) spectrum for next generation mobile communication systems has gained significant attention recently. Large antenna arrays along with beamforming techniques are required to combat the large path-loss at mmwave frequencies. However, the existing beam designs often cause a large peak to average power ratio, and thus require power-inefficient power amplifiers (PAs). In this paper, we propose power-efficient beam design methods that facilitate the use of power-efficient PAs. Specifically, we design digital and hybrid analog-digital mmwave beams that possess a per-antenna constant envelope (PACE) and thus are highly power-efficient. Meanwhile, we also minimize the ripples in the mainlobe and sidelobe of the beams and consider both infinite and finite resolution phase shifters. To this end, we first propose an efficient feasible point search method to provide a feasible solution for the considered difficult beam design problem. Then, a novel hybrid analog-digital mapping algorithm is developed to map a designed digital beam to a hybrid analog-digital beam. To achieve better performance, we propose an improved hybrid analog-digital beam design method employing further optimization based on the feasible point. The proposed method is applicable to both infinite-resolution and finite-resolution phase shifters. Comprehensive simulation results are provided to demonstrate the effectiveness and superiority of the proposed beam designs.
CRIS-Team Scopus Importer:2020-03-06
Keywords: Beam design; beam optimization; low PAPR; millimeter wave communication; power-efficient

Power efficient MISO beamforming for secure layered transmission - Wing Kwan Ng, Derrick; Schober, Robert; Alnuweiri, Hussein (2014 IEEE Wireless Communications and Networking Conference (WCNC), 2014)
This paper studies secure layered video transmission in a multiuser multiple-input single-output (MISO) beamforming downlink communication system. The power allocation algorithm design is formulated as a non-convex optimization problem for minimizing the total transmit power while guaranteeing a minimum received signal-to-interference-plus-noise ratio (SINR) at the desired receiver. In particular, the proposed problem formulation takes into account the self-protecting architecture of layered transmission and artificial noise generation to prevent potential information eavesdropping. A semi-definite programming (SDP) relaxation based power allocation algorithm is proposed to obtain an upper bound solution. A sufficient condition for the global optimal solution is examined to reveal the tightness of the upper bound solution. Subsequently, two suboptimal power allocation schemes with low computational complexity are proposed for enabling secure layered video transmission. Simulation results demonstrate significant transmit power savings achieved by the proposed algorithms and layered transmission compared to the baseline schemes.<br
Keywords: Receivers; Resource management; Transmitters; Noise; Vectors; Streaming media; Optimization

Power Efficient Resource Allocation for Full-Duplex Radio Distributed Antenna Networks - Wing Kwan Ng, Derrick; Wu, Yongpeng; Schober, Robert (IEEE Transactions on Wireless Communications, 2016)
In this paper, we study the resource allocation algorithm design for distributed antenna multiuser networks with full-duplex (FD) radio base stations (BSs), which enable simultaneous uplink and downlink communications. The considered resource allocation algorithm design is formulated as an optimization problem taking into account the antenna circuit power consumption of the BSs and the quality of service (QoS) requirements of both uplink and downlink users. We minimize the total network power consumption by jointly optimizing the downlink beamformer, the uplink transmit power, and the antenna selection. To overcome the intractability of the resulting problem, we reformulate it as an optimization problem with decoupled binary selection variables and nonconvex constraints. The reformulated problem facilitates the design of an iterative resource allocation algorithm, which obtains an optimal solution based on the generalized Bender's decomposition (GBD). For this algorithm, we also propose a simple technique to improve the speed of convergence. Furthermore, to strike a balance between computational complexity and system performance, a suboptimal resource allocation algorithm with polynomial time complexity is proposed. Simulation results illustrate that the proposed GBD-based iterative algorithm converges to the globally optimal solution and the suboptimal algorithm achieves a close-to-optimal performance. Our results also demonstrate the tradeoff between power efficiency and the number of active transmit antennas when the circuit power consumption is taken into account. In particular, activating an exceedingly large number of antennas may not be an efficient approach for reducing the total system power consumption. In addition, our results reveal that FD systems facilitate significant power savings compared to traditional half-duplex systems, despite the nonnegligible self-interference.<br
Keywords: Downlink; Uplink; Resource management; Antenna arrays; Algorithm design and analysis; Power demand

Power-Efficient Resource Allocation for Multiuser MISO Systems via Intelligent Reflecting Surfaces - Yu, Xianghao; Xu, Dongfang; Ng, Derrick Wing Kwan; Schober, Robert (2020 IEEE Global Communications Conference, GLOBECOM 2020 - Proceedings, 2020)
Intelligent reflecting surfaces (IRSs) are regarded as key enablers of next-generation wireless communications, due to their capability of customizing the wireless propagation environment. In this paper, we investigate power-efficient resource allocation for IRS-assisted multiuser multiple-input single-output (MISO) systems. To minimize the transmit power, both the beamforming vectors at the access point (AP) and phase shifts at the IRS are jointly optimized while taking into account the minimum required quality-of-service (QoS) of the users. To tackle the non-convexity of the formulated optimization problem, an inner approximation (IA) algorithm is developed. Unlike existing designs, which cannot guarantee local optimality, the proposed algorithm is guaranteed to converge to a Karush-Kuhn-Tucker (KKT) solution. Our simulation results show the effectiveness of the proposed algorithm compared to baseline schemes and reveal that deploying IRSs is more promising than leveraging multiple antennas at the AP in terms of energy efficiency.
CRIS-Team Scopus Importer:2021-04-19

Power saving potential of cooperative communication: A two-dimensional approach - Korn, Clemens; Michalopoulos, Diomidis; Schober, Robert (SCC 2015 - 10th International ITG Conference on Systems, Communications and Coding, 2019)
We assess the power saving potential of cooperative communication for a two-dimensional user distribution scenario. In particular, we compare the average total transmit power of cooperative transmission (i.e., the sum of the user and the relay transmit power, averaged over the distribution of the users) with the average transmit power of conventional (direct) communication. The comparison is performed on the basis of achieving the same signal-to-noise ratio (SNR) at the base station in both cases. In this regard, a circular shaped radio cell with circularly uniformly distributed users is considered. A theoretical investigation of the savings in transmit power offered by cooperation is conducted for the case where the path-loss exponent equals four. The theoretical analysis is verified by simulations, which also consider a wider range of path loss exponent values for the evaluation of the power savings achieved by cooperation. Our results demonstrate that the power savings per user increase with increasing path loss exponent and with increasing number of users within the circular cell.
CRIS-Team Scopus Importer:2019-10-22

Power Scaling Law for Optical IRSs and Comparison with Optical Relays - Ajam, Hedieh; Najafi Kalyani, Marzieh; Jamali, Vahid; Schober, Robert (2022 IEEE Global Communications Conference, GLOBECOM 2022 - Proceedings, 2022)
The line-of-sight (LOS) requirement of free-space optical (FSO) systems can be relaxed by employing optical relays and optical intelligent reflecting surfaces (IRSs). Unlike radio frequency (RF) IRSs, which typically exhibit a quadratic power scaling law, the power reflected from FSO IRSs and collected at the receiver lens may scale quadratically or linearly with the IRS size or may even saturate at a constant value. We analyze the power scaling law for optical IRSs and unveil its dependence on the wavelength, transmitter (Tx)-to-IRS and IRS-to-receiver (Rx) distances, beam waist, and lens size. We compare optical IRSs in different power scaling regimes with optical relays in terms of the outage probability, diversity and coding gains, and optimal placement. Our results show that, at the expense of a higher hardware complexity, relay-assisted FSO links yield a better outage performance at high signal-to-noise-ratios (SNRs), but optical IRSs can achieve a higher performance at low SNRs. Moreover, while it is optimal to place relays equidistant from Tx and Rx, the optimal location of IRSs depends on the power scaling regime they operate in.
CRIS-Team Scopus Importer:2023-03-07

Practical Non-Linear Energy Harvesting Model and Resource Allocation for SWIPT Systems - Boshkovska, Elena; Wing Kwan Ng, Derrick; Zlatanov, Nikola; Schober, Robert (IEEE Communications Letters, 2015)
In this letter, we propose a practical non-linear energy harvesting model and design a resource allocation algorithm for simultaneous wireless information and power transfer (SWIPT) systems. The algorithm design is formulated as a non-convex optimization problem for the maximization of the total harvested power at energy harvesting receivers subject to minimum required signal-to-interference-plus-noise ratios (SINRs) at multiple information receivers. We transform the considered non-convex objective function from sum-of-ratios form into an equivalent objective function in subtractive form, which enables the derivation of an efficient iterative resource allocation algorithm. In each iteration, a rank-constrained semidefinite program (SDP) is solved optimally by SDP relaxation. Numerical results unveil a substantial performance gain that can be achieved if the resource allocation design is based on the proposed non-linear energy harvesting model instead of the traditional linear model.<br
Keywords: Resource management; Wireless communication; Integrated circuit modeling; Receivers; Optimization; Wireless sensor networks

Precoder Design and Power Allocation for Downlink MIMO-NOMA via Simultaneous Triangularization - Krishnamoorthy, Aravindh; Huang, Meng; Schober, Robert (2021 IEEE Wireless Communications and Networking Conference (WCNC), 2021)

Precoder Design and Statistical Power Allocation for MIMO-NOMA via User-Assisted Simultaneous Diagonalization - Krishnamoorthy, Aravindh; Ding, Zhiguo; Schober, Robert (IEEE Transactions on Communications, 2020)
Keywords: Symmetric matrices; Decoding; Covariance matrices; NOMA; MIMO communication; Resource management; Precoding

Precoder Design for Two-User Uplink MIMO-NOMA with Simultaneous Triangularization - Krishnamoorthy, Aravindh; Schober, Robert (2019 IEEE GLOBAL COMMUNICATIONS CONFERENCE (GLOBECOM), 2019)
In this paper, we consider the uplink precoder design for two-user power-domain multiple-input multiple-output (MIMO) non-orthogonal multiple access (NOMA) systems. We propose a novel precoding scheme which utilizes simultaneous tri-angularization to decompose the MIMO-NOMA channels of the two users into multiple single-input single-output (SISO)-NOMA channels assuming low-complexity self-interference cancellation at the base station, thereby reducing the decoding complexity. The proposed scheme takes advantage of the available excess degrees of freedom at the base station to enhance the ergodic achievable rate. The ergodic achievable rate region of the proposed scheme is characterized using finite-size random matrix theory (RMT). Our results illustrate that the proposed scheme significantly outperforms traditional MIMO-OMA and zero forcing based MIMO-NOMA schemes, and has a small performance gap to the achievable rate region of MIMO-NOMA.
CRIS-Team WoS Importer:2020-08-14

Precoding and Decoding Schemes for Downlink MIMO-RSMA with Simultaneous Diagonalization and User Exclusion - Diab, Rouaa; Krishnamoorthy, Aravindh; Schober, Robert (2022 IEEE International Conference on Communications Workshops, ICC Workshops 2022, 2022)
In this paper, we consider the precoder design for downlink multiple-input multiple-output (MIMO) rate-splitting multiple access (RSMA) systems. The proposed scheme with simultaneous diagonalization (SD) decomposes the MIMO channel matrices of the users into scalar channels via higher-order generalized singular value decomposition for the common message (CM) and block diagonalization (BD) for the private messages, thereby enabling low-complexity element-by-element successive interference cancellation (SIC) and decoding at the receivers. Furthermore, the proposed SD MIMO-RSMA overcomes a critical limitation in RSMA systems, whereby the achievable rate of the CM is restricted by the users with weak effective MIMO channel for the CM, by excluding a subset of users from decoding the CM. We formulate a non-convex weighted sum rate (WSR) optimization problem for SD MIMO-RSMA and solve it via successive convex approximation to obtain a locally optimal solution. Our simulation results reveal that, for both perfect and imperfect CSI, the proposed SD MIMO-RSMA with user exclusion outperforms baseline MIMO-RSMA schemes and linear BD precoding.
CRIS-Team Scopus Importer:2022-08-05

Predictive feedback for transmit beamforming with delayed feedback and channel estimation errors - Ma, Yao; Leith, Alex; Schober, Robert (IEEE International Conference on Communications, 2008)
The effect of limited-rate feedback on the transmit beamforming (TB) channel capacity has been well studied in the literature, but the negative effects of outdated feedback and imperfect channel estimation (ICE) have not been adequately addressed yet. In this paper, we study the joint effects of receiver ICE and delayed and limited feedback on the capacity of transmit beamforming over Rayleigh fading channels. Our results show that with perfect receiver channel state information (CSI) the TB capacity may not monotonically decrease even as the delay increases. However, if the delay is not properly considered in the channel estimation, the TB channel capacity may quickly degrade to zero as the feedback delay increases. As countermeasures, we propose a predictive channel feedback scheme to improve the feedback quality and a pilot symbol assisted channel estimation (PSACE) scheme to improve channel estimation quality. Analytical and numerical results show that the proposed scheme is much more robust against feedback delay than the traditional one, and can provide a capacity performance close to the case with perfect receiver CSI and without feedback delay. Our results provide new insight into the achievable performance of transmit beamforming impaired by limited and delayed feedback and receive ICE. ©2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Pre-equalization for DS-UWB systems with spectral mask constraints - Mohsenian-Rad, Amir Hamed; Mietzner, Jan; Schober, Robert; Wong, Vincent W.S. (IEEE International Conference on Communications, 2010)
In this paper, we propose a novel optimization-based pre-equalization filter (PEF) design for direct - sequence ultra-wideband (DS-UWB) systems with pre-Rake combining. The key feature in our design is that we explicitly take into account the spectral mask constraints that are usually imposed by the telecommunication regulation bodies. This avoids the need for an inefficient power back-off, which is necessary for transmit structures designed solely based on average transmit power constraints. Simulation results confirm that the proposed PEF design leads to significant performance gains over UWB PEF structures without explicit spectral mask considerations. ©2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Pre-equalization for MISO DS-UWB systems with pre-Rake combining - Torabi, Elham; Mietzner, Jan; Schober, Robert (IEEE Transactions on Wireless Communications, 2009)
In this paper, we propose two novel pre-equalization schemes for multiple-input single-output (MISO) direct-sequence ultra-wideband (DS-UWB) systems with pre-Rake combining and symbol-by-symbol detection. The first scheme employs one pre-equalization filter (PEF) per transmit antenna, whereas in the second scheme, the simplified PEF (S-PEF) scheme, all transmit antennas share the same PEF. For both schemes the optimum finite impulse response (FIR) and infinite impulse response (IIR) PEFs are calculated based on the minimum mean squared error (MMSE) criterion. Our approach is sufficiently general to include also reduced-complexity versions of pre-Rake combining that employ a limited number of Rake fingers. We show that under certain conditions the S-PEF scheme achieves the same performance as the more complex PEF scheme. We also demonstrate that a single-input multiple-output (SIMO) DS-UWB system with post-Rake combining and MMSE post-equalization is the dual system to the considered MISO DS-UWB system with pre-Rake combining and MMSE pre-equalization. This uplink-downlink duality can be exploited for efficient calculation of the PEFs and for complexity reduction. Our simulation results show that the proposed PEF schemes achieve significant performance gains over pre-Rake combining without equalization, even if only short PEFs are employed. © 2006 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Equalization; Multipath channels; Multiple-input single-output systems; Pre-filtering; Rake combining; Spread-spectrum communications; Ultra-wideband systems

Pre-equalization for pre-rake DS-UWB systems with spectral mask constraints - Mohsenian-Rad, Amir-Hamed; Mietzner, Jan; Schober, Robert; Wong, Vincent W. S. (IEEE Transactions on Communications, 2011)
In this paper, we propose a novel optimization-based pre-equalization filter (PEF) design framework for direct-sequence ultra-wideband (DS-UWB) systems with pre-Rake combining. The key feature in our design is that we explicitly take into account the spectral mask constraints that are usually imposed in practice by the telecommunications regulation and standardization bodies. This avoids the need for an inefficient power back-off, which is necessary for the existing pre-Rake-based transmitter structures designed solely based on average transmit power constraints. We consider two PEF design structures. In the first structure, the PEF is placed before the up-sampling unit at the transmitter. In the second structure, the PEF is placed after the up-sampling unit. We show that these two structures are significantly different in terms of their capabilities in reducing the residual inter-symbol interference at the receiver and also in following the spectral mask at the transmitter. This introduces a trade-off such that one design structure outperforms the other one, depending on the system parameters. In this regard, we show that if the spreading factor is large enough, the second design structure has a superior performance. Simulation results confirm that both of the proposed PEF structures lead to significant performance gains over PEF designs without explicit spectral mask considerations. In addition, our PEF designs have the capability of adhering to spectral masks with arbitrary shapes. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: inter-symbol interference; optimization; pre-equalization; pre-Rake combining; semi-definite programming; Spectral mask constraints; ultra-wideband communication

Pre-equalization for pre-rake MISO DS-UWB systems - Torabi, Elham; Mietzner, Jan; Schober, Robert (IEEE International Conference on Communications, 2008)
In this paper, we propose two novel pre-equalization schemes for multiple-input single-output (MISO) direct-sequence ultra-wideband (DS-UWB) systems with pre-Rake combining and symbol-by-symbol detection. The first pre-equalization filter (PEF) scheme employs one PEF per transmit antenna, whereas in the second, simplified PEF (S-PEF) scheme all transmit antennas share the same PEF. For both schemes, the optimum finite impulse response (FIR) and infinite impulse response (IIR) PEFs are calculated based on the minimum mean squared error (MMSE) criterion. Our approach is sufficiently general to include also complexity-reduced versions of pre-Rake combining that employ a limited number of Rake fingers. We show that under certain conditions the S-PEF scheme achieves the same performance as the more complex PEF scheme. Moreover, our simulation results show that the proposed PEF schemes achieve significant performance gains over pure pre-Rake combining without equalization, even if only short PEFs are employed. ©2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Pricing Mobile Data Offloading: A Distributed Market Framework - Wang, Kehao; Lau, Francis C. M.; Chen, Lin; Schober, Robert (IEEE Transactions on Wireless Communications, 2015)
Mobile data offloading is an emerging technology to avoid congestion in cellular networks and improve the level of user satisfaction. In this paper, we develop a distributed market framework to price the offloading service, and conduct a detailed analysis of the incentives for offloading service providers and conflicts arising from the interactions of different participators. Specifically, we formulate a multileader multifollower Stackelberg game (MLMF-SG) to model the interactions between the offloading service providers and the offloading service consumers in the considered market framework, and investigate the cases where the offloading capacity of APs is unlimited and limited, respectively. For the case without capacity limit, we decompose the followers' game of the MLMF-SG (FG-MLMF-SG) into a number of simple follower games (FGs), and prove the existence and uniqueness of the equilibrium of the FGs from which the existence and uniqueness of the FG-MLMF-SG also follows. For the leaders' game of the MLMF-SG, we also prove the existence and uniqueness of the equilibrium. For the case with capacity limit, by considering a symmetric strategy profile, we establish the existence and uniqueness of the equilibrium of the corresponding MLMF-SG, and present a distributed algorithm that allows the leaders to achieve the equilibrium. Finally, extensive numerical experiments demonstrate that the Stackelberg equilibrium is very close to the corresponding social optimum for both considered cases.<br
Keywords: Games; Mobile communication; IEEE 802.11 Standard; Radio frequency; Pricing; Mobile computing; Femtocells

Proportional Fairness in ALOHA Networks With RF Energy Harvesting - Hadzi-Velkov, Zoran; Pejoski, Slavche; Zlatanov, Nikola; Schober, Robert (IEEE Wireless Communications Letters, 2018)
In this letter, we study wireless powered communication networks that employ the slotted ALOHA protocol, which is the preferred protocol for simple and uncoordinated networks. In the energy harvesting (EH) phase, the base station broadcasts radio frequency energy to the EH users (EHUs). The EHUs harvest the broadcasted energy and use it to transmit information back to the base station by contending for access to the uplink channel in the random access (RA) phase. In order to ensure fairness among the users, we propose a proportionally fair resource allocation scheme that exploits the RA nature of slotted ALOHA. Specifically, assuming statistical channel state information, we determine the optimal transmit power at the base station, the optimal durations of the EH and RA phases, the channel access probability, and the rate of each EHU.<br
Keywords: Fading channels; Resource Management; Wireless Networks; Batteries; Power Generation; Throughput

Proportional Fairness in ALOHA Networks With RF Energy Harvesting - Hadzi-Velkov, Zoran; Pejoski, Slavche; Zlatanov, Nikola; Schober, Robert (IEEE Wireless Communications Letters, 2019)
In this letter, we study wireless powered communication networks that employ the slotted ALOHA protocol, which is the preferred protocol for simple and uncoordinated networks. In the energy harvesting (EH) phase, the base station broadcasts radio frequency energy to the EH users (EHUs). The EHUs harvest the broadcasted energy and use it to transmit information back to the base station by contending for access to the uplink channel in the random access (RA) phase. In order to ensure fairness among the users, we propose a proportionally fair resource allocation scheme that exploits the RA nature of slotted ALOHA. Specifically, assuming statistical channel state information, we determine the optimal transmit power at the base station, the optimal durations of the EH and RA phases, the channel access probability, and the rate of each EHU.
CRIS-Team WoS Importer:2019-03-06

Pulse Shaping for MC via Particle Size - Wicke, Wayan; Felsheim, Rebecca; Brand, Lukas; Jamali, Vahid; Loos, Helene; Büttner, Andrea; Schober, Robert (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2023)
In molecular communication (MC), combining different types of particles at the transmitter is a degree of freedom which can be utilized to improve performance. In this paper, we address the problem of pulse shaping to simplify time synchronization requirements by exploiting and combining the received signal characteristics of particles of different sizes. In particular, we optimize the mixture of particles of different sizes used for transmission in order to support a prescribed detection time period for on-off keying, guaranteeing on average 1) a sufficiently large received signal if a binary one is transmitted, and 2) a low enough received signal if a binary zero is transmitted even in the presence of inter-symbol interference. For illustration, we consider an optimization problem based on a free space diffusion channel model. It is shown that there is a tradeoff between the maximum feasible detection duration and the for different particle sizes from the smallest particle size enabling the largest detection duration to the largest particle size minimizing the at the expense of a limited detection duration.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Pulse shaping methods; Receivers; Robustness; Shape; Symbols; Synchronization; Transmitters

Quasi-Coherent Phase-Based Localization and Tracking of Incoherently Transmitting Radio Beacons - Sippel, Erik; Hehn, Markus; Kögel, Tobias; Gröschel, Patrick; Hofmann, Andreas; Brückner, Stefan; Geiß, Johanna; Schober, Robert; Vossiek, Martin (IEEE Access, 2021)
The direct measurement of distance-dependent information between wireless units represents a challenge for wireless locating systems, because it requires the exact time synchronization of separate wireless units. To avoid these synchronization efforts, many wireless locating systems only evaluate phase difference of arrival (PDOA) measurements. While simple PDOA localization techniques rely on multiangulation, advanced PDOA concepts like the holographic extended Kalman filter (HEKF) directly evaluate the measured phases without non-linear preprocessing. However, these differential phase measurement approaches are less sensitive than systems that can measure absolute phase variations, which allow the tracking of much smaller position changes than the signal’s carrier wavelength. This paper proposes to extend the HEKF by the evaluation of absolute phases in an incoherent measurement setup, which consists of a continuous wave (CW) beacon and several receivers. The developed quasi-coherent holographic extended Kalman filter (QCHEKF) uses the overdetermined PDOA measurements to estimate the phase–frequency relation between each beacon–receiver pair. Then, the established phase–frequency relations allow the evaluation of absolute phase measurements and, thus, the accurate localization and tracking of a simple, unsynchronized, narrowband CW beacon, even under severe multipath conditions. This novel concept is experimentally validated via 3D localization results in a challenging indoor scenario using a 24 GHz CW measurement setup. Here, the QCHEKF improves the achieved localization accuracy in comparison to the HEKF by 35% from 0.78 cm to 0.51 cm, while the maximum deviation from the trajectory reduces by 68% from 5 cm to 1.6 cm. Furthermore, the QCHEKF enables the exact tracking of fast changes in direction, which is usually a significant challenge for standard wireless target tracking systems.
Keywords: Phase measurement; Location awareness; Antenna measurements; Time-frequency analysis; Receiving antennas; Time measurement; Wireless sensor networks

RACE: QoI-Aware Strategic Resource Allocation for Provisioning Se-aaS - Misra, Sudip; Schober, Robert; Chakraborty, Aishwariya (IEEE Transactions on Services Computing, 2022)
In this paper, the problem of ensuring profitability for multiple sensor-owners in sensor-cloud, while satisfying the service requirements of end-users, is studied. In traditional sensor-cloud, Sensor-Cloud Service Provider (SCSP) solely dictates the service provisioning process. However, the SCSP cannot always ensure high profits for sensor-owners, who incur significant maintenance costs for their sensor-nodes. Contrarily, it is highly essential to meet the Quality-of-Information (QoI) requirements of end-users to ensure their service satisfaction. Existing works proposed a few node allocation schemes which neither consider the cost incurred by sensor-owners nor the QoI of sensed-data in sensor-cloud. To address this problem, a strategic resource allocation scheme, named RACE, is proposed, which introduces the participation of sensor-owners in the node allocation process. First, utility theory is used to calculate the optimum number of nodes to be allocated for a service. Thereafter, single leader multiple followers Stackelberg game is formulated to decide the number of nodes to be contributed by each sensor-owner and the price to be charged. Simulation-based experimental results reveal that, using RACE, the profits of the sensor-owners and those of the SCSP increase by 86.11-89.26 percent and 41.95-80.82 percent, respectively, as compared to the existing benchmark schemes, while considering that each sensor-node is capable of serving multiple applications simultaneously. Moreover, service availability in sensor-cloud increases by 31.70-96.96 percent using RACE.
CRIS-Team WoS Importer:2022-07-08

Random access for elastic and inelastic traffic in WLANs - Cheung, Man Hon; Mohsenian-Rad, Amir-Hamed; Wong, Vincent W. S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2010)
In this paper, we consider the problem of random access in wireless local area networks (WLANs) with each station generating either elastic or inelastic traffic. Elastic traffic is usually non-real-time, while inelastic traffic is usually coming from real-time applications. We formulate a network utility maximization (NUM) problem, where the optimization variables are the persistent probabilities of the stations and the utilities are either concave or sigmoidal functions. Sigmoidal utility functions can better represent inelastic traffic sources compared to concave utility functions commonly used in the existing random access literature. However, they lead to non-convex NUM problems which are not easy to solve in general. By applying the dual decomposition method, we propose a subgradient algorithm to solve the formulated NUM problem. We also develop closed-form solutions for the dual subproblems involving sigmoidal functions that have to be solved in each iteration of the proposed algorithm. Furthermore, we obtain a sufficient condition on the link capacities which guarantees achieving the global optimal solution when our proposed algorithm is being used. If this condition is not satisfied, then we can still guarantee that the optimal value of the objective function is within some lower and upper bounds. We perform various simulations to validate our analytical models when the available link capacities meet or do not meet the sufficient optimality condition. © 2002-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Wireless random access; medium access control; network utility maximization; non-convex optimization; sigmoidal function; elastic and inelastic traffic; real-time applications

Random access protocols for WLANs based on mechanism design - Man, Hon Cheung; Mohsenian-Rad, A. Hamed; Wong, Vincent W.S.; Schober, Robert (IEEE International Conference on Communications, 2009)
In wireless local area networks (WLANs), quality of service (QoS) can be provided by mapping applications with different requirements (e.g., delay and throughput) into one of the available access categories (ACs), as is done in the IEEE 802.11e standard. With the increasing programmability of network adapters, a malicious user can strategically declare a higher AC for its application to gain an unfair share of resources. This can drastically degrade the network performance and avoid adequate service distinction among different ACs. In this paper, we use the technique of mechanism design in game theory to tackle this problem in WLANs with random access. We propose to use the Vickrey-Clarke-Groves (VCG) mechanism in order to motivate each station to inform the access point (AP) truthfully, about the required AC of its application. The AP will then inform each station about its persistent probability and the price it needs to pay for the offered service. The result of the allocation of the persistent probabilities can be used for admission control. Simulation results show that the use of mechanism design can lead to a higher aggregate utility and prevents malicious users from gaining an unfair share of the network bandwidth. ©2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Randomized multi-channel interrogation algorithm for large-scale RFID systems - Mohsenian-Rad, Amir Hamed; Shah-Mansouri, Vahid; Wong, Vincent W.S.; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2009)
A radio frequency identification (RFID) system consists of a set of readers and several objects, equipped with small computer chips, called tags. In a dense RFID system, where several readers are placed together to improve the read rate and correctness, readers and tags can frequently experience packet collision. A common approach to avoid collision is to use a distinct frequency channel for interrogation for each reader. Various multi-channel anti-collision protocols have been proposed for RFID readers. However, due to their heuristic nature, most algorithms may not fully utilize the achievable system performance. In this paper, we develop an optimization-based distributed randomized multi-channel interrogation algorithm, called FDFA, for large-scale RFID systems. For this purpose, we develop elaborate models for reader-to-tag and reader-to-reader collision problems. FDFA algorithm is guaranteed to find a local optimum of a max-min fair resource allocation problem to balance the processing load among readers. Simulation results show that FDFA has a significantly better performance than the existing heuristic algorithms in terms of the number of successful interrogations. It also better utilizes the frequency spectrum.
CRIS-Team Scopus Importer:2020-02-03

Range of achievable diversity order in multiple relay networks with multiple users - Kim, Junsu; Michalopoulos, Diomidis S.; Schober, Robert (IEEE International Conference on Communications, 2011)
In this paper, we investigate the range of the achievable diversity order of opportunistic relay selection with M amplify-and-forward (AF) relays and N users. We show that the opportunistic selection of the relay-user pair with the best end-to-end signal-to-noise ratio (SNR) achieves a diversity order between M+N and MN+N. Our analysis reveals that the achievable diversity order depends on the SNR values of the source-relay (SR) and relay-destination (RD) links. Based on our analysis, which is verified by simulation results, we show that the achievable diversity order converges to the upper bound MN+N when the SR link SNR is greater than the RD link SNR; when the SR link quality is poorer than the RD link quality, the diversity order approaches the lower bound M+N. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Rate Optimization for Hybrid SC-FDE/OFDM Decode-and-Forward MIMO Relay Systems - Wu, Peiran; Schober, Robert; Bhargava, Vijay K. (IEEE Communications Letters, 2014)
In this paper, we consider the rate-optimal transceiver design for a hybrid single-carrier frequency-domain equalization and orthogonal frequency-division multiplexing decode-and-forward (DF) multiple-input-multiple-output (MIMO) relay system. Such hybrid systems can provide a high end-to-end bit rate and a low peak-to-average power ratio at one of the transmitting nodes. Assuming minimum mean-squared-error equalization at the receiving nodes, we optimize the transmit precoding matrices for maximization of the achievable bit rate (ABR) of the system subject to a joint node transmit power constraint. We provide a unified solution for the precoding matrices, which subsumes the solutions for pure single-carrier and pure multicarrier MIMO DF relay systems as special cases. Specifically, the optimal structure of the precoding matrices is obtained by exploiting the relation between our design and conventional point-to-point MIMO transceiver designs. With the optimal precoding structure, the optimization problem reduces to a convex power allocation problem, for which an efficient closed-form solution is derived. Numerical results are provided to confirm the excellent ABR performance of the proposed relaying schemes.<br
Keywords: Relays; OFDM; MIMO; Optimization; Transceivers; Wireless communication; Vectors

Rate-Power Region of SWIPT Systems Employing Nonlinear Energy Harvester Circuits with Memory - Shanin, Nikita; Cottatellucci, Laura; Schober, Robert (IEEE International Conference on Communications, 2020)
In this paper, we study the rate-power region of a simultaneous wireless information and power transfer (SWIPT) system where a transmitter (TX) broadcasts a common signal to an information receiver (IR) and an energy harvester (EH). Since practical EH circuits include a reactive element as part of their signal rectifier and the voltage on this element cannot drop or rise instantaneously, the EH circuit has memory. We model the memory effect of the EH by a Markov reward chain. Furthermore, since an analytical model that includes all nonlinear and memory effects of the EH circuit is not available, we employ a deep neural network (DNN) to model the Markov chain. We formulate an optimization problem to determine the rate-power region of the considered SWIPT system and propose an iterative algorithm based on sequential quadratic programming (SQP) to solve it. Our numerical results show that the optimal input distribution and the rate-power region depend on both the input power level at the EH and the symbol duration.
CRIS-Team Scopus Importer:2020-08-28

Rate-Splitting for Intelligent Reflecting Surface-Aided Multiuser VR Streaming - Huang, Rui; Wong, Vincent W.S.; Schober, Robert (IEEE Journal on Selected Areas in Communications, 2023)
The growing demand for virtual reality (VR) applications requires wireless systems to provide a high transmission rate to support 360-degree video streaming to multiple users simultaneously. In this paper, we propose an intelligent reflecting surface (IRS)-aided rate-splitting (RS) VR streaming system. In the proposed system, RS facilitates the exploitation of the shared interests of the users in VR streaming, and IRS creates additional propagation channels to support the transmission of high-resolution 360-degree videos. IRS also enhances the capability to mitigate the performance bottleneck caused by the requirement that all RS users have to be able to decode the common message. We formulate an optimization problem for maximization of the achievable bitrate of the 360-degree video subject to the quality-of-service (QoS) constraints of the users. We propose a deep deterministic policy gradient with imitation learning (Deep-GRAIL) algorithm, in which we leverage deep reinforcement learning (DRL) and the hidden convexity of the formulated problem to optimize the IRS phase shifts, RS parameters, beamforming vectors, and bitrate selection of the 360-degree video tiles. We also propose RavNet, which is a deep neural network customized for the policy learning in our Deep-GRAIL algorithm. Performance evaluation based on a real-world VR streaming dataset shows that the proposed IRS-aided RS VR streaming system outperforms several baseline schemes in terms of system sum-rate, achievable bitrate of the 360-degree videos, and online execution runtime. Our results also reveal the respective performance gains obtained from RS and IRS for improving the QoS in multiuser VR streaming systems.
CRIS-Team Scopus Importer:2023-03-03
Keywords: Array signal processing; Base stations; Bit rate; deep reinforcement learning; imitation learning; intelligent reflecting surface; Quality of service; Rate-splitting; Signal to noise ratio; Streaming media; virtual reality; Wireless communication

Rate-Splitting for IRS-Aided Multiuser VR Streaming: An Imitation Learning-Based Approach - Huang, Rui; Wong, Vincent W.S.; Schober, Robert (IEEE International Conference on Communications, 2023)
Virtual reality (VR) applications require wireless systems to provide a high transmission rate to support 360-degree video streaming to multiple users simultaneously. In this paper, we propose an intelligent reflecting surface (IRS)-aided rate-splitting (RS) VR streaming system. In the proposed system, RS exploits the shared interests of the users in VR streaming, and the IRS creates reflected channels to facilitate a high transmission rate. The IRS also mitigates the performance bottleneck caused by the requirement that all RS users have to be able to decode the common message. We formulate an optimization problem for maximization of the achievable bitrate of the streamed 360-degree video subject to the quality-of-service (QoS) constraints of the users. We propose a deep reinforcement learning (DRL)-based algorithm, in which we leverage imitation learning and the hidden convexity of the formulated problem to optimize the IRS phase shifts, RS parameters, beamforming vectors, and bitrate selection of the 360-degree video tiles. Simulations based on a real-world dataset show that the proposed IRS-aided RS VR streaming system outperforms two baseline schemes in terms of system sum-rate and average runtime.
CRIS-Team Scopus Importer:2023-12-15

Rate-Splitting Multiple Access: Fundamentals, Survey, and Future Research Trends - Mao, Yijie; Dizdar, Onur; Clerckx, Bruno; Schober, Robert; Popovski, Petar; Poor, H. Vincent (IEEE Communications Surveys & Tutorials, 2022)
Rate-splitting multiple access (RSMA) has emerged as a novel, general, and powerful framework for the design and optimization of non-orthogonal transmission, multiple access (MA), and interference management strategies for future wireless networks. By exploiting splitting of user messages as well as non-orthogonal transmission of common messages decoded by multiple users and private messages decoded by their corresponding users, RSMA can softly bridge and therefore reconcile the two extreme interference management strategies of fully decoding interference and treating interference as noise. RSMA has been shown to generalize and subsume as special cases four existing MA schemes, namely, orthogonal multiple access (OMA), physical-layer multicasting, space division multiple access (SDMA) based on linear precoding (currently used in the fifth generation wireless network–5G), and non-orthogonal multiple access (NOMA) based on linearly precoded superposition coding with successive interference cancellation (SIC). Through information and communication theoretic analysis, RSMA has been shown to be optimal (from a Degrees-of-Freedom region perspective) in several transmission scenarios. Compared to the conventional MA strategies used in 5G, RSMA enables spectral efficiency (SE), energy efficiency (EE), coverage, user fairness, reliability, and quality of service (QoS) enhancements for a wide range of network loads (including both underloaded and overloaded regimes) and user channel conditions. Furthermore, it enjoys a higher robustness against imperfect channel state information at the transmitter (CSIT) and entails lower feedback overhead and complexity. Despite its great potential to fundamentally change the physical (PHY) layer and media access control (MAC) layer of wireless communication networks, RSMA is still confronted with many challenges on the road towards standardization. In this paper, we present the first comprehensive tutorial on RSMA by providing a survey of the pertinent state-of-the-art research, detailing its architecture, taxonomy, and various appealing applications, as well as comparing with existing MA schemes in terms of their overall frameworks, performance, and complexities. An in-depth discussion of future RSMA research challenges is also provided to inspire future research on RSMA-aided wireless communication for beyond 5G systems.
CRIS-Team Scopus Importer:2022-08-12
Keywords: 5G mobile communication; beyond 5G (B5G); Interference; interference management; Multiaccess communication; multiple-input multiple-output (MIMO); next generation multiple access; NOMA; non-orthogonal transmission; Radio transmitters; Rate-splitting (RS); rate-splitting multiple access (RSMA); Time-frequency analysis; Wireless communication

Rate-Splitting Unifying SDMA, OMA, NOMA, and Multicasting in MISO Broadcast Channel: A Simple Two-User Rate Analysis - Clerckx, Bruno; Mao, Yijie; Schober, Robert; Poor, H. Vincent (IEEE Wireless Communications Letters, 2020)
Considering a two-user multi-antenna Broadcast Channel, this letter shows that linearly precoded Rate-Splitting (RS) with Successive Interference Cancellation (SIC) receivers is a flexible framework for non-orthogonal transmission that generalizes, and subsumes as special cases, four seemingly different strategies, namely Space Division Multiple Access (SDMA) based on linear precoding, Orthogonal Multiple Access (OMA), Non-Orthogonal Multiple Access (NOMA) based on linearly precoded superposition coding with SIC, and physical-layer multicasting. This letter studies the sum-rate and shows analytically how RS unifies, outperforms, and specializes to SDMA, OMA, NOMA, and multicasting as a function of the disparity of the channel strengths and the angle between the user channel directions.
CRIS-Team Scopus Importer:2020-03-27
Keywords: multi-antenna broadcast channel; multicasting; NOMA; OMA; rate analysis; Rate-splitting; SDMA

Reactive receiver modeling for diffusive molecular communication systems with molecule degradation - Ahmadzadeh, Arman; Arjmandi, Hamidreza; Burkovski, Andreas; Schober, Robert (2016 IEEE International Conference on Communications, ICC 2016, 2016)
In this paper, we consider the diffusive molecular communication channel between a transmitter nano-machine and a receiver nano-machine in a fluid environment. The information molecules released by the transmitter nano-machine into the environment can degrade in the channel via a first-order degradation reaction and those that reach the receiver nano-machine can participate in a reversible bimolecular-reaction with receiver receptor proteins. We derive a closed-form analytical expression for the expected received signal at the receiver, i.e., the expected number of activated receptors on the surface of the receiver. The accuracy of the derived analytical result is verified with a Brownian motion particle-based simulation of the environment.
CRIS-Team Scopus Importer:2020-01-31

Real-Time Pricing for Demand Response Based on Stochastic Approximation - Samadi, Pedram; Mohsenian-Rad, Hamed; Wong, Vincent W. S.; Schober, Robert (IEEE Transactions on Smart Grid, 2014)
In this paper, we propose a new pricing algorithm to minimize the peak-to-average ratio (PAR) in aggregate load demand. The key challenge that we seek to address is the energy provider's uncertainty about the impact of prices on users' load profiles, in particular when users are equipped with automated energy consumption scheduling (ECS) devices. We use an iterative stochastic approximation approach to design two real-time pricing algorithms based on finite-difference and simultaneous perturbation methods, respectively. We also propose the use of a system simulator unit (SSU) that employs approximate dynamic programming to simulate the operation of the ECS devices and users' price-responsiveness. Simulation results show that our proposed real-time pricing algorithms reduce the PAR in aggregate load and help the users to reduce their energy expenses.<br
Keywords: Approximation algorithms; Pricing; Linear programming; Approximation methods; Home appliances; Vectors; Peak to average power ratio

Receiver Concepts for WLAN IEEE 802.11b - Jonietz, Christof; Gerstacker, Wolfgang; Schober, Robert (Conference Proceedings, 2004)
In this paper, complementary code keying (CCK) transmission over frequency-selective fading channels is investigated. A vector signal model is introduced since CCK can be interpreted as a block code. Based on pairwise error probabilities we derive a performance approximation for optimum detection obtained for given channel statistics, and compare the theoretical results with simulations. Because optimum maximum-likelihood sequence estimation (MLSE) is not practical for large channel delay spreads, minimum mean-squared error decision-feedback equalization (MMSE-DFE) is employed. Two different DFE approaches are considered here: (a) the conventional scalar DFE and (b) a block-based DFE, which is well suited for the underlying vector signal model. For various common indoor channel profiles, numerical results are given for MLSE, scalar DFE and block DFE in terms of bit error rates (BERs) and packet error rates (PERs).
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.mobilk.receiv

Receivers with Widely Linear Processing for Frequency-Selective Channels - Gerstacker, Wolfgang; Schober, Robert; Lampe, Alexander (IEEE Transactions on Communications, 2003)
In this paper, we propose several equalization schemes based on widely linear processing (WLP). The received signal and its complex conjugate are separately filtered and the results are linearly combined. It is shown that WLP yields a gain in performance if the (noiseless) received signal can be interpreted as the convolution of a real-valued data sequence and an equivalent complex-valued intersymbol interference channel impulse response. Such a model applies to, e.g., amplitude-shift keying, offset quadrature amplitude modulation, and binary minimum-shift keying-type modulation. We consider receivers without and with decision feedback. Finite impulse response filters are derived for these structures, which are optimum with respect to the zero-forcing and minimum mean-squared error (MMSE) criterion, respectively. In the MMSE case, adaptive algorithms for filter adjustment are given. Infinite filter orders are investigated in order to obtain analytical performance results. Furthermore, suboptimum trellis-based detection with widely linear preprocessing is briefly discussed. It is demonstrated analytically and by numerical examples that widely linear schemes may outperform conventional schemes significantly, depending on the considered application.
UnivIS-Import:2015-03-09:Pub.2003.tech.IE.mobilk.receiv
Keywords: Equalization; Global system for mobile communication (GSM); Intersymbol interference (ISI); Widely linear processing (WLP)

Receptor Saturation Modeling for Synaptic DMC - Lotter, Sebastian; Schäfer, Maximilian; Zeitler, Johannes; Schober, Robert (ICC 2021 - IEEE International Conference on Communications, 2021)
Synaptic communication is a natural Molecular Communication (MC) system which may serve as a blueprint for the design of synthetic MC systems. In particular, it features highly specialized mechanisms to enable inter-symbol interference (ISI)-free and energy efficient communication. The understanding of synaptic MC is furthermore critical for disruptive innovations in the context of brain-machine interfaces. However, the physical modeling of synaptic MC is complicated by the possible saturation of the molecular receiver arising from the competition of postsynaptic receptors for neurotransmitters. Saturation renders the system behavior nonlinear and is commonly neglected in existing analytical models. In this work, we propose a novel model for receptor saturation in terms of a nonlinear, state-dependent boundary condition for Fick’s diffusion equation. We solve the resulting boundary-value problem using an eigenfunction expansion of the Laplace operator and the incorporation of the receiver memory as feedback system into the corresponding state-space description. The presented solution is numerically stable and computationally efficient. Furthermore, the proposed model is validated with particle-based stochastic computer simulations.
Keywords: Degradation; Neurotransmitters; Computational modeling; Biological system modeling; Stochastic processes; Receivers; Brain modeling

Reconfigurable Intelligent Surface-Aided Multi-User Networks: Interplay Between NOMA and RIS - Liu, Yuanwei; Mu, Xidong; Liu, Xiao; Di Renzo, Marco; Ding, Zhiguo; Schober, Robert (IEEE Wireless Communications, 2022)
This article focuses on the exploitation of reconfigurable intelligent surfaces (RISs) in multiuser networks employing orthogonal multiple access (OMA) or non-orthogonal multiple access (NOMA), with an emphasis on investigating the interplay between NOMA and RIS. Depending on whether the RIS reflection coefficients can be adjusted only once or multiple times during one transmission, we distinguish between static and dynamic RIS configurations. In particular, the capacity region of RIS-aided single-antenna NOMA networks is discussed and compared with the OMA rate region from an information-theoretic perspective, revealing that the dynamic RIS configuration is capacity-achieving. Then, the impact of the RIS deployment location on the performance of different multiple access schemes is investigated, which reveals that asymmetric and symmetric deployment strategies are preferable for NOMA and OMA, respectively. Furthermore, for RIS-aided multiple-antenna NOMA networks, three novel joint active and passive beamformer designs are proposed based on both beamformer-based and cluster-based strategies. Finally, open research problems for RIS-NOMA networks are highlighted.
CRIS-Team WoS Importer:2022-07-08

Reduced-State Sequence Estimation for Complementary Code Keying - Jonietz, Christof; Gerstacker, Wolfgang; Schober, Robert (Conference Proceedings, 2004)
In this paper, reduced-state sequence estimation (RSSE) designed for complementary code keying (CCK) transmission over frequency-selective fading channels is investigated. An Ungerboeck-like set partitioning of the multidimensional CCK symbol constellation is given. For the proposed RSSE algorithm based on this partitioning, numerical results are provided for a typical indoor wireless channel. A comparison is made with optimum detection and suboptimum decision-feedback equalization (DFE), respectively.
UnivIS-Import:2015-04-16:Pub.2004.tech.IE.mobilk.reduce
Keywords: Complementary code keying; Reduced-state sequence estimation; Set partitioning; WLAN IEEE 802.11b

Relay Selection for Simultaneous Information Transmission and Wireless Energy Transfer: A Tradeoff Perspective - Michalopoulos, Diomidis S.; Suraweera, Himal A.; Schober, Robert (IEEE Journal on Selected Areas in Communications, 2014)
In certain applications, relay terminals can be employed to simultaneously deliver information and energy to a designated receiver and a set of radio frequency (RF) energy harvesters, respectively. In such scenarios, the relay that is preferable for information transmission does not necessarily coincide with the relay that is preferable for energy transfer, since the corresponding channels fade independently. Relay selection thus entails a tradeoff between the efficiency of the information transmission to the receiver and the amount of energy transferred to the energy harvesters. The study of this tradeoff is the subject on which this work mainly focuses. Specifically, we investigate the dependence of the ergodic capacity and the outage probability of the information transmission to the receiver on the amount of energy transferred to the RF energy harvesters. We propose a relay selection policy that yields the optimal tradeoff in a maximum capacity/minimum outage probability sense, for a given energy transfer constraint. We also propose two suboptimal relay selection methods that apply to scenarios with limited availability of channel state information. Additionally, we propose a suboptimal scheme which approximates the optimal scheme for the special case of two relays and facilitates performance analysis. Interesting insights on the aforementioned tradeoffs are unveiled.<br
Keywords: Relays; Energy exchange; Information processing; Signal to noise ratio; Radio frequency; Energy harvesting; Measurement

Relay selection in relay-assisted free space optical systems - Chatzidiamantis, Nestor D.; Michalopoulos, Diomidis S.; Kriezis, Emmanouil E.; Karagiannidis, George K.; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2011)
We investigate transmission protocols for relay-assisted free-space optical (FSO) systems, when multiple parallel relays are employed and there is no direct link between the source and the destination. As an alternative to all-active FSO relaying, where all the available relays transmit jointly, we propose a scheme which selects only a single relay to participate in the communication between the source and the destination in each transmission slot, based on the channel state information (CSI) obtained from all FSO links. Thus, the need for synchronizing the relays' transmission is avoided, while the slowly varying nature of the atmospheric channel is exploited. For both relay selection and all-active relaying, novel analytical closed-form expressions for their outage performance are derived, assuming the Gamma-Gamma channel model. Numerical results are provided for equal and non-equal length FSO links, which clearly demonstrate the significant performance gains offered by relay selection compared to all-active relaying. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Relay selection protocols for relay-assisted free-space optical systems - Chatzidiamantis, Nestor D.; Michalopoulos, Diomidis S.; Kriezis, Emmanouil E.; Karagiannidis, George K.; Schober, Robert (Journal of Optical Communications and Networking, 2013)
We investigate transmission protocols for relayassisted free-space optical (FSO) systems, when multiple parallel relays are employed and there is no direct link between the source and the destination. As alternatives to all-active FSO relaying, where all the available relays transmit concurrently, we propose schemes that select only a single relay to participate in the communication between the source and the destination in each transmission slot. The selection is based on the channel state information obtained either from all or from the last used FSO links. Thus, the need for synchronization of the relays' transmissions is avoided, while the slowly varying nature of the atmospheric channel is exploited. For the considered relay selection and all-active relaying schemes, novel closed-form expressions for the outage performance are derived, assuming the versatile Gamma-Gamma channel model. In addition, based on the derived analytical results, the problem of optimizing the optical power resources of the FSO links is addressed. Optimal and more computationally attractive suboptimal solutions are proposed that lead to a power efficient system design. Numerical results for equal and non-equal length FSO links illustrate the merits of the proposed relay selection protocols compared to the all-active scheme and demonstrate the significant power savings offered by the proposed power allocation schemes. © 2009-2012 OSA.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Cooperative diversity; Distributed switch and stay relaying; Free-space optical communications; Powerallocation; Relay selection; Relay-assisted communications

Relay selection with outdated channel estimates in Nakagami-m fading - Michalopoulos, Diomidis S.; Chatzidiamantis, Nestor D.; Schober, Robert; Karagiannidis, George K. (IEEE International Conference on Communications, 2011)
We study the effect of outdated channel estimates on decode-and-forward relay selection, when operating over Nakagami-m fading channels. Closed-form expressions for the exact outage probability are derived, as function of the correlation between the actual and the estimated channel values. The diversity and coding gain are also studied, revealing a high dependence of diversity order on the aforementioned correlation coefficient. It is shown that when the channel estimates are not perfectly updated, the performance of relay selection is equivalent, in terms of diversity order, to the scheme where only a single relay is available. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Relay subset selection and fair power allocation for best and partial relay selection in generic noise and interference - Ahmed, Imtiaz; Nasri, Amir; Michalopoulos, Diomidis S.; Schober, Robert; Mallik, Ranjan K. (IEEE Transactions on Wireless Communications, 2012)
Best relay selection (BRS) has received considerable attention in the literature as it makes efficient use of the system resources and achieves full diversity. Partial relay selection (PRS) is an alternative to BRS and performs relay selection based on local channel state information (CSI) only at the expense of a loss in diversity. Although, in practice, relays may be deployed in unfavorable environments exposing them to non-Gaussian impairments, existing analyses and design guidelines for BRS and PRS are limited to additive white Gaussian noise channels. In this paper, we analyze the error rate of BRS and PRS in the asymptotic regime of high signal-to-noise ratio (SNR) for amplify-and-forward (AF) relays and impairment by generic noise and interference. The derived analytical results are valid for Gaussian and non-Gaussian noises with finite moments, independent and non-identically distributed Rayleigh fading, and arbitrary linear modulation schemes. In order to reduce the signaling overhead required for CSI acquisition, we propose a relay subset selection scheme for BRS and PRS. Furthermore, to guarantee fairness in energy resource usage across the relays, we introduce a fair and flexible power allocation scheme with energy consumption constraints which does not affect the achievable diversity gain. The proposed relay subset selection and power allocation schemes only require knowledge of the average CSI of the links and certain moments of the noises impairing the relays and the destination. © 2002-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Amplify-and-forward; best relay selection; interference; noise; partial relay selection; power allocation

Reliability-based rate allocation in wireless inter-session network coding systems - Ronasi, Keivan; Mohsenian-Rad, A. Hamed; Wong, Vincent W.S.; Gopalakrishnan, Sathish; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2009)
Network coding has recently received increasing attention to improve performance and increase capacity in both wired and wireless communication networks. In this paper, we focus on inter-session network coding, where multiple unicast sessions jointly participate in network coding. Wireless links are often unreliable because of varying channel conditions. We consider multi-hop unicast sessions over unreliable links and propose a distributed end-to-end transmission rate adjustment mechanism to maximize the aggregate network utility by taking into account the wireless link reliability information. This includes an elaborate modeling of end-to-end reliability. Simulation results show that by taking into account the reliability information, we can increase the network throughput by up to 100% for some network topologies. We can also increase the aggregate network utility significantly for various choices of utility functions.
CRIS-Team Scopus Importer:2020-02-03

Repeated Intersession Network Coding Games: Efficiency and Min-Max Bargaining Solution - Mohsenian-Rad, Hamed; Huang, Jianwei; Wong, Vincent W.S.; Schober, Robert (IEEE-ACM Transactions on Networking, 2013)
Recent results have shown that selfish users do not have an incentive to participate in intersession network coding in a static noncooperative game setting. Because of this, the worst-case network efficiency (i.e., the price-of-anarchy) can be as low as 20%. In this paper, we show that if the same game is played repeatedly, then the price-of-anarchy can be improved to 36%. We design a grim-trigger strategy that encourages users to cooperate and participate in the intersession network coding. A key challenge is to determine a common cooperative coding rate that the users should mutually agree on. We resolve the conflict of interest among the users through a bargaining process and obtain tight upper bounds for the price-of-anarchy that are valid for any possible bargaining scheme. Moreover, we propose a simple and efficient min-max bargaining solution that can achieve these upper bounds, as confirmed through simulation studies. The coexistence of multiple selfish network coding sessions as well as the coexistence of selfish network coding and routing sessions are also investigated. Our results represent a first step toward designing practical intersession network coding schemes that achieve reasonable performance for selfish users.<br
Keywords: Network coding; Games; Encoding; Routing; Nash equilibrium; Resource management; History

Residential Demand Side Management Under High Penetration of Rooftop Photovoltaic Units - Yao, Enxin; Samadi, Pedram; Wong, Vincent W. S.; Schober, Robert (IEEE Transactions on Smart Grid, 2015)
In a residential area where many households have installed rooftop photovoltaic (PV) units, there is a reverse power flow from the households to the substation when the power generation from PV units is larger than the aggregate load of the households. This reverse power flow causes the voltage rise problem. In this paper, we study the use of demand side management to mitigate the voltage rise problem. We propose an autonomous energy consumption scheduling algorithm, which schedules the operation of deferrable loads to jointly shave the peak load and reduce the reverse power flow. The proposed algorithm shifts the operation of deferrable loads from peak consumption hours to hours with high-power generation from the PV units. We use stochastic programming to formulate an energy consumption scheduling problem, which takes into account the uncertainty related to the amount of power generation from PV units. The formulated cost function comprises a monetary cost for energy consumption, the revenue from energy export, and an external cost for the voltage rise. Numerical results show that our proposed algorithm can mitigate the voltage rise problem in areas with high penetration of PV units and reduce the peak-to-average ratio of the aggregate load.<br
Keywords: Energy consumption; Cost function; Companies; Pricing; System-on-chip; Solar power generation

Resource allocation and scheduling in multi-cell OFDMA decode-and-forward relaying networks - Ng, Derrick Wing Kwan; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2010)
In this paper, we formulate a joint optimization problem for resource allocation and scheduling in multi-cell orthogonal frequency division multiple access (OFDMA) half-duplex decode-and-forward (DF) relay assisted networks. Our problem formulation takes into account multi-cell interference and heterogeneous data rate requirements. We transform the resulting non-convex and combinatorial optimization problem into a standard convex optimization problem by introducing an additional interference constraint, which constitutes a performance lower bound for the original problem. Subsequently, the transformed optimization problem is solved by using dual decomposition and a centralized iterative resource allocation algorithm with closed-form power and subcarrier allocation policies is derived maximizing the average weighted system throughput (bit/s/Hz/base station). Simulation results illustrate that our proposed algorithm approaches the maximum achievable throughput and provides substantial performance gains compared to single-cell optimization. ©2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Resource allocation and scheduling in multi-cell OFDMA systems with decode-and-forward relaying - Derrick Wing Kwan Ng,; Schober, Robert (IEEE Transactions on Wireless Communications, 2011)
In this paper, we formulate resource allocation and scheduling for multi-cell orthogonal frequency division multiple access (OFDMA) systems with half-duplex decode-and-forward (DF) relaying as a joint optimization problem taking into account multi-cell interference and heterogeneous user data rate requirements. For efficient multi-cell interference mitigation, we incorporate a time slot allocation strategy into the problem formulation. We transform the resulting non-convex and combinatorial optimization problem into a standard convex problem by imposing an interference temperature constraint, which yields a lower bound for the original problem. Subsequently, the transformed optimization problem is solved by dual decomposition and a semi-distributed iterative resource allocation algorithm with closed-form power and subcarrier allocation policies is derived to maximize the average weighted system throughput (bit/s/Hz/base station). Simulation results illustrate that our proposed semi-distributed algorithm achieves practically the same performance as the centralized optimal solution of the original non-convex problem and provides a substantial performance gain compared to single-cell resource allocation and scheduling schemes. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: base station coordination; decode-and-forward relay; Heterogeneous users; multi-cell resource allocation; multiuser diversity

Resource Allocation for Active IRS-Assisted Multiuser Communication Systems - Xu, Dongfang; Yu, Xianghao; Kwan Ng, Derrick Wing; Schober, Robert (Conference Record - Asilomar Conference on Signals, Systems and Computers, 2021)
Intelligent reflecting surfaces (IRSs) are emerging as promising enablers for the next generation of wireless communication systems, because of their ability to customize favorable radio propagation environments. However, with the conventional passive architecture, IRSs can only adjust the phase of the incident signals limiting the achievable beamforming gain. To fully unleash the potential of IRSs, in this paper, we consider a more general IRS architecture, i.e., active IRSs, which can adapt the phase and amplify the magnitude of the reflected incident signal simultaneously with the support of an additional power source. To realize green communication in active IRS-assisted multiuser systems, we jointly optimize the reflection matrix at the IRS and the beamforming vector at the base station (BS) for the minimization of the BS transmit power. The resource allocation algorithm design is formulated as an optimization problem taking into account the maximum power budget of the active IRS and the quality-of-service (QoS) requirements of the users. To handle the non-convex design problem, we develop a novel and computationally efficient algorithm based on the bilinear transformation and inner approximation methods. The proposed algorithm is guaranteed to converge to a locally optimal solution of the considered problem. Simulation results illustrate the effectiveness of the proposed scheme compared to two baseline schemes. Moreover, the results unveil that deploying active IRSs is a promising approach to enhance the system performance compared to conventional passive IRSs, especially when strong direct links exist.
CRIS-Team Scopus Importer:2022-06-05

Resource allocation for coordinated multipoint networks with wireless information and power transfer - Ng, Derrick Wing Kwan; Schober, Robert (2014 IEEE Global Communications Conference, GLOBECOM 2014, 2014)
This paper studies the resource allocation algorithm design for multiuser coordinated multipoint (CoMP) networks with simultaneous wireless information and power transfer (SWIPT). In particular, remote radio heads (RRHs) are connected to a central processor (CP) via capacity-limited backhaul links to facilitate CoMP joint transmission. Besides, the CP transfers energy to the RRHs for more efficient network operation. The considered resource allocation algorithm design is formulated as a non-convex optimization problem with a minimum required signal-to-interference-plus-noise ratio (SINR) constraint at multiple information receivers and a minimum required power transfer constraint at the energy harvesting receivers. By optimizing the transmit beamforming vectors at the CP and energy sharing between the CP and the RRHs, we aim at jointly minimizing the total network transmit power and the maximum capacity consumption per backhaul link. The resulting non-convex optimization problem is NP-hard. In light of the intractability of the problem, we reformulate it by replacing the non-convex objective function with its convex hull, which enables the derivation of an efficient iterative resource allocation algorithm. In each iteration, a non-convex optimization problem is solved by semi-definite programming (SDP) relaxation and the proposed iterative algorithm converges to a local optimal solution of the original problem. Simulation results illustrate that our proposed algorithm achieves a close-to-optimal performance and provides a significant reduction in backhaul capacity consumption compared to full cooperation. Besides, the considered CoMP network is shown to provide superior system performance as far as power consumption is concerned compared to a traditional system with multiple antennas co-located.
CRIS-Team Scopus Importer:2020-02-03

Resource Allocation for Intelligent Reflecting Surface-Assisted Cognitive Radio Networks - Xu, Dongfang; Yu, Xianghao; Schober, Robert (PROCEEDINGS OF THE 21ST IEEE INTERNATIONAL WORKSHOP ON SIGNAL PROCESSING ADVANCES IN WIRELESS COMMUNICATIONS (IEEE SPAWC2020), 2020)
CRIS-Team WoS Importer:2021-03-05

Resource Allocation for Intelligent Reflecting Surface-Assisted Cognitive Radio Networks - Xu, Dongfang; Yu, Xianghao; Schober, Robert (IEEE Workshop on Signal Processing Advances in Wireless Communications, SPAWC, 2020)
In this paper, we investigate resource allocation algorithm design for intelligent reflecting surface (IRS)-Assisted multiuser cognitive radio (CR) systems. In particular, an IRS is deployed to mitigate the interference caused by the secondary network to the primary users. The beamforming vectors at the base station (BS) and the phase shift matrix at the IRS are jointly optimized for maximization of the sum rate of the secondary system. The algorithm design is formulated as a non-convex optimization problem taking into account the maximum interference tolerance of the primary users. To tackle the resulting non-convex optimization problem, we propose an alternating optimization-based suboptimal algorithm exploiting semidefinite relaxation, the penalty method, and successive convex approximation. Our simulation results show that the system sum rate is dramatically improved by our proposed scheme compared to two baseline schemes. Moreover, our results also illustrate the benefits of deploying IRSs in CR networks.
CRIS-Team Scopus Importer:2020-09-18

Resource Allocation for IRS-Assisted Full-Duplex Cognitive Radio Systems - Xu, Dongfang; Yu, Xianghao; Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (IEEE Transactions on Communications, 2020)
In this article, we investigate the resource allocation design for intelligent reflecting surface (IRS)-assisted full-duplex (FD) cognitive radio systems. In particular, a secondary network employs an FD base station (BS) for serving multiple half-duplex downlink (DL) and uplink (UL) users simultaneously. An IRS is deployed to enhance the performance of the secondary network while helping to mitigate the interference caused to the primary users (PUs). The DL transmit beamforming vectors and the UL receive beamforming vectors at the FD BS, the transmit power of the UL users, and the phase shift matrix at the IRS are jointly optimized for maximization of the total spectral efficiency of the secondary system. The design task is formulated as a non-convex optimization problem taking into account the imperfect knowledge of the PUs' channel state information (CSI) and their maximum interference tolerance. Since the maximum interference tolerance constraint is intractable, we apply a safe approximation to transform it into a convex constraint. To efficiently handle the resulting approximated optimization problem, which is still non-convex, we develop an iterative block coordinate descent (BCD)-based algorithm. This algorithm exploits semidefinite relaxation, a penalty method, and successive convex approximation and is guaranteed to converge to a stationary point of the approximated optimization problem. Our simulation results do not only reveal that the proposed scheme yields a substantially higher system spectral efficiency for the secondary system than several baseline schemes, but also confirm its robustness against CSI uncertainty. Besides, our results illustrate the tremendous potential of IRS for managing the various types of interference arising in FD cognitive radio networks.
CRIS-Team WoS Importer:2021-01-08

Resource Allocation for Large IRS-Assisted SWIPT Systems with Non-linear Energy Harvesting Model - Xu, Dongfang; Yu, Xianghao; Jamali Kooshkghazi, Vahid; Ng, Derrick Wing Kwan; Schober, Robert (2021 IEEE WIRELESS COMMUNICATIONS AND NETWORKING CONFERENCE (WCNC), 2021)
CRIS-Team WoS Importer:2021-10-29

Resource Allocation for MC-NOMA Systems with Cognitive Relaying - Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (2017)
In this paper, we investigate the resource allocation algorithm design for cooperative cognitive relaying multicarrier non-orthogonal multiple access (MC-NOMA) systems. In particular, the secondary base station serves multiple secondary users and simultaneously acts as a relay assisting the information transmission in the primary network. The resource allocation aims to maximize the weighted system throughput by jointly optimizing the power and subcarrier allocation for both the primary and the secondary networks while satisfying the quality-of-service requirements of the primary users. The algorithm design is formulated as a mixed combinatorial non-convex optimization problem. We apply monotonic optimization theory to solve the problem leading to an optimal resource allocation policy. Besides, we develop a low-complexity scheme to find a suboptimal solution. Our simulation results reveal that the performance of the proposed suboptimal algorithm closely approaches that of the optimal one. Besides, the combination of MC-NOMA and cognitive relaying improves the system throughput considerably compared to conventional multicarrier cognitive relaying systems.

Resource Allocation for Multi-User Downlink MISO OFDMA-URLLC Systems - Ghanem, Walid; Jamali, Vahid; Sun, Yan; Schober, Robert (IEEE Transactions on Communications, 2020)
This article considers the resource allocation algorithm design for downlink multiple-input single-output (MISO) orthogonal frequency division multiple access (OFDMA) ultra-reliable low latency communication (URLLC) systems. To meet the stringent delay requirements of URLLC, short packet transmission is adopted and taken into account for resource allocation algorithm design. The resource allocation is optimized for maximization of the weighted system sum throughput subject to quality-of-service (QoS) constraints regarding the URLLC users' number of transmitted bits, packet error probability, and delay. Despite the non-convexity of the resulting optimization problem, the optimal solution is found via monotonic optimization. The corresponding optimal resource allocation policy can serve as a performance upper bound for sub-optimal low-complexity solutions. We develop such a low-complexity sub-optimal resource allocation algorithm based on successive convex approximation and difference of convex programming. Our simulation results reveal the importance of using multiple antennas for reducing the latency and improving the reliability of URLLC systems. Moreover, the proposed sub-optimal algorithm is shown to closely approach the performance of the proposed optimal algorithm and outperforms two baseline schemes by a considerable margin, especially when the users have heterogeneous delay requirements. Finally, conventional resource allocation designs based on Shannon's capacity formula are shown to be not applicable in MISO OFDMA-URLLC systems as they are not able to guarantee the users' delay constraints.
CRIS-Team Scopus Importer:2020-12-04
Keywords: monotonic optimization; orthogonal frequency division multiple access (OFDMA); Resource allocation; short packet transmission; ultra-reliable low latency communication (URLLC)

Resource Allocation for Multi-User Downlink URLLC-OFDMA Systems - Ghanem, Walid; Jamali Kooshkghazi, Vahid; Sun, Yan; Schober, Robert (2019 IEEE International Conference on Communications Workshops (ICC Workshops), 2019)
In this paper, we study resource allocation for downlink orthogonal frequency division multiple access (OFDMA) systems with the objective to enable ultra-reliable low latency communication (URLLC). To meet the stringent delay requirements of URLLC, the impact of short packet communication is taken into account for resource allocation algorithm design. In particular, the resource allocation design is formulated as a weighted system sum throughput maximization problem with quality-of-service (QoS) constraints for the URLLC users. The formulated problem is non-convex, and hence, finding the global optimum solution entails a high computational complexity. Thus, an algorithm based on successive convex optimization is proposed to find a sub-optimal solution with polynomial time complexity. Simulation results confirm that the proposed algorithm facilities URLLC and significantly improves the system sum throughput compared to two benchmark schemes.<br

Resource Allocation for Outdoor-to-Indoor Amplify-and-Forward SUDAS with Independent Relay Processing - Goodarzi, Meysam; Krishnamoorthy, Aravindh; Schober, Robert; Breiling, Marco (SCC 2019; 12th International ITG Conference on Systems, Communications and Coding, 2019)
In this work, we study resource allocation for a downlink multicarrier outdoor-to-indoor transmission system employing a shared user equipment (UE)-side distributed antenna system (SUDAS) with independently operating amplifyand-forward (AF) relays which utilize both licensed and unlicensed frequency bands to enhance indoor data throughput and coverage. We formulate a non-convex matrix-valued resource allocation problem for maximization of the sum rate. The nonconvex problem is simplified to a scalar optimization problem using an approximation in order to obtain a low-complexity algorithm based on alternating optimization (AO). Simulation results illustrate that despite the simplification, the proposed algorithm achieves excellent performance in terms of the sum rate and closely approaches the max-flow min-cut upper bound. The proposed SUDAS scheme facilitates low-complexity outdoor-to-indoor communication for next-generation wireless systems.<br

Resource Allocation for Outdoor-to-Indoor Compress-and-Forward SUDAS with Independent Relay Processing - Krishnamoorthy, Aravindh; Schober, Robert; Breiling, Marco (Vehicular Technology Conference (VTC-Fall), 2017)
In this paper, we consider resource allocation for an outdoor-to-indoor shared user-equipment (UE)-side distributed antenna system (SUDAS) employing multiple independently operating compress-and-forward (CF) relays which utilize both licensed and unlicensed frequency bands to enhance indoor data throughput. First, a non-convex matrix-valued resource allocation problem for maximization of the weighted sum rate is formulated. Next, the non-convex problem is simplified to obtain a low-complexity suboptimal resource allocation algorithm based on sequential quadratic programming (SQP). The proposed algorithm is shown to provide excellent performance in practical scenarios. Furthermore, the algorithm has a low channel state information (CSI) feedback requirement and can accommodate arbitrary communication bands and technologies for indoor relaying. Therefore, the proposed CF-SUDAS scheme can help achieve high outdoor-to-indoor data throughput at low complexity, a crucial requirement for next generation wireless communication systems.
Keywords: Relays; Resource Management; MIMO communication; Quantization (signal); Antennas; Covariance matrices; Bandwidth

Resource Allocation for Outdoor-to-Indoor Multicarrier Transmission with Shared UE-Side Distributed Antenna Systems - Breiling, Marco; Ng, Derrick Wing Kwan; Rohde, Christian; Burkhardt, Frank; Schober, Robert (2015 IEEE 81st Vehicular Technology Conference (VTC Spring), 2015)
In this paper, we study the resource allocation algorithm design for downlink multicarrier transmission with a shared user equipment (UE)-side distributed antenna system (SUDAS) which utilizes both licensed and unlicensed frequency bands for improving the system throughput. The joint UE selection and transceiver processing matrix design is formulated as a non-convex optimization problem for the maximization of the end-to-end system throughput (bits/s). In order to obtain a tractable resource allocation algorithm, we first show that the optimal transmitter precoding and receiver post-processing matrices jointly diagonalize the end-to-end communication channel. Subsequently, the optimization problem is converted to a scalar optimization problem for multiple parallel channels, which is solved by using an asymptotically optimal iterative algorithm. Simulation results illustrate that the proposed resource allocation algorithm for the SUDAS achieves an excellent system performance and provides a spatial multiplexing gain for single-antenna UEs.<br
Keywords: Resource management; Optimization; OFDM; MIMO; Downlink; Bandwidth; Algorithm design and analysis

Resource Allocation for Secure Full-Duplex OFDMA Radio Systems - Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (2017)
In this paper, we study the resource allocation for an orthogonal frequency division multiple access (OFDMA) radio system employing a full-duplex base station for serving multiple half-duplex downlink and uplink users simultaneously. The resource allocation design objective is the maximization of the weighted system throughput while limiting the information leakage to guarantee secure simultaneous downlink and uplink transmission in the presence of potential eavesdroppers. The algorithm design leads to a mixed combinatorial non-convex optimization problem and obtaining the globally optimal solution entails a prohibitively high computational complexity. Therefore, an efficient successive convex approximation based suboptimal iterative algorithm is proposed. Our simulation results confirm that the proposed suboptimal algorithm achieves a significant performance gain compared to two baseline schemes.

Resource Allocation for Secure Full-Duplex OFDMA Radio Systems - Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (2017)
In this paper, we study the resource allocation for an orthogonal frequency division multiple access (OFDMA) radio system employing a full-duplex base station for serving multiple half-duplex downlink and uplink users simultaneously. The resource allocation design objective is the maximization of the weighted system throughput while limiting the information leakage to guarantee secure simultaneous downlink and uplink transmission in the presence of potential eavesdroppers. The algorithm design leads to a mixed combinatorial non-convex optimization problem and obtaining the globally optimal solution entails a prohibitively high computational complexity. Therefore, an efficient successive convex approximation based suboptimal iterative algorithm is proposed. Our simulation results confirm that the proposed suboptimal algorithm achieves a significant performance gain compared to two baseline schemes.

Resource allocation for secure full-duplex OFDMA radio systems : (Invited paper) - Sun, Yan; Wing Kwan Ng, Derrick; Schober, Robert (2017 IEEE 18th International Workshop on Signal Processing Advances in Wireless Communications (SPAWC), 2017)
In this paper, we study the resource allocation for an orthogonal frequency division multiple access (OFDMA) radio system employing a full-duplex base station for serving multiple half-duplex downlink and uplink users simultaneously. The resource allocation design objective is the maximization of the weighted system throughput while limiting the information leakage to guarantee secure simultaneous downlink and uplink transmission in the presence of potential eavesdroppers. The algorithm design leads to a mixed combinatorial non-convex optimization problem and obtaining the globally optimal solution entails a prohibitively high computational complexity. Therefore, an efficient successive convex approximation based suboptimal iterative algorithm is proposed. Our simulation results confirm that the proposed suboptimal algorithm achieves a significant performance gain compared to two baseline schemes.<br
Keywords: Resource management; Silicon; Optimization; Wireless communication; Covariance matrices; High definition video; Throughput

Resource Allocation for Secure IRS-assisted Multiuser MISO Systems - Xu, Dongfang; Yu, Xianghao; Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (2019 IEEE GLOBECOM WORKSHOPS (GC WKSHPS), 2019)
CRIS-Team WoS Importer:2020-08-21

Resource Allocation for Secure Multi-User Downlink MISO-URLLC Systems - Ghanem, Walid; Jamali Kooshkghazi, Vahid; Schober, Robert (IEEE International Conference on Communications, 2020)
In this paper, we study resource allocation algorithm design for secure multi-user downlink ultra-reliable low latency communication (URLLC). To enhance physical layer security (PLS), the base station (BS) is equipped with multiple antennas and artificial noise (AN) is injected by the BS to impair the eavesdroppers' channels. To meet the stringent delay requirements in secure URLLC systems, short packet transmission (SPT) is adopted and taken into consideration for resource allocation design. The resource allocation algorithm design is formulated as an optimization problem for minimization of the total transmit power, while guaranteeing qualityof-service (QoS) constraints regarding the URLLC users' number of transmitted bits, packet error probability, information leakage, and delay. Due to the non-convexity of the optimization problem, finding a global solution entails a high computational complexity. Thus, we propose a low-complexity algorithm based successive convex approximation (SCA) to find a sub-optimal solution. Our simulation results show that the proposed resource allocation algorithm design ensures the secrecy of the URLLC users' transmissions, and yields significant power savings compared to a baseline scheme.
CRIS-Team Scopus Importer:2020-08-28

Resource allocation for secure OFDMA communication systems - Wing, Derrick; Ng, Kwan; Schober, Robert (Proceedings of the 2011 Australian Communications Theory Workshop, AusCTW 2011, 2011)
In this paper, resource allocation and scheduling in an orthogonal frequency division multiple access (OFDMA) downlink network is studied. The considered problem is modeled as an optimization problem which takes into account a multiple antenna eavesdropper and artificial noise generation for secure communications. Power, secrecy data rate, and subcarrier allocation are optimized for maximization of the average secrecy outage capacity (bit/s/Hz securely delivered to the users). The optimization problem is solved by using dual decomposition resulting in an efficient iterative resource allocation algorithm. Simulation results illustrate that the proposed iterative resource allocation and scheduling algorithm converges in a small number of iterations and guarantees a non-zero secrecy date rate even if the eavesdropper is closer to the base station than the desired users. ©2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Resource allocation for secure OFDMA decode-and-forward relay networks - Ng, Derrick Wing Kwan; Schober, Robert (12th Canadian Workshop on Information Theory, CWIT 2011, 2011)
In this paper, we formulate an optimization problem for resource allocation and scheduling in orthogonal frequency division multiple access (OFDMA) half-duplex decode-and-forward (DF) relay assisted networks. Our problem formulation takes into account artificial noise generation to combat a multiple antenna eavesdropper. The secrecy data rate, power, and sub-carrier allocation policies are optimized to maximize the average secrecy outage capacity (bit/s/Hz securely delivered to the users via relays). The optimization problem is solved by dual decomposition which results in an efficient iterative algorithm. Simulation results illustrate that the proposed iterative algorithm converges in a small number of iterations and guarantees a non-zero secrecy date rate for a given target secrecy outage probability. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Resource allocation for secure OFDMA networks with imperfect CSIT - Ng, Derrick Wing Kwan; Lo, Ernest S.; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2011)
In this paper, we formulate an optimization problem for resource allocation and scheduling in orthogonal frequency division multiple access (OFDMA) networks. Our problem formulation takes into account artificial noise generation to combat a passive multiple antenna eavesdropper and the effects of imperfect channel state information at the transmitter (CSIT) in slow fading. The optimization problem is solved by dual decomposition which results in an iterative resource allocation algorithm with a fast speed of convergence. The packet data rate, secrecy data rate, power, and subcarrier allocation policies are optimized to maximize the average secrecy outage capacity (bit/s/Hz securely and successfully delivered to the users). Simulation results illustrate that our proposed iterative algorithm converges to the optimal solution in a small number of iterations and guarantees a non-zero secrecy data rate for given target secrecy outage and channel outage probability requirements. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Resource Allocation for Simultaneous Wireless Information and Power Transfer Systems: A Tutorial Overview - Wei, Zhiqiang; Yu, Xianghao; Ng, Derrick Wing Kwan; Schober, Robert (Proceedings of the IEEE, 2021)
Over the last decade, simultaneous wireless information and power transfer (SWIPT) has become a practical and promising solution for connecting and recharging battery-limited devices due to significant advances in low-power electronics technology and wireless communications techniques. To realize the promised potentials, advanced resource allocation design plays a decisive role in revealing, understanding, and exploiting the intrinsic rate-energy tradeoff capitalizing on the dual use of radio frequency (RF) signals for wireless charging and communication. In this article, we provide a comprehensive tutorial overview of SWIPT from the perspective of resource allocation design. The fundamental concepts, system architectures, and RF energy harvesting (EH) models are introduced. In particular, three commonly adopted EH models, namely, the linear EH model, the nonlinear saturation EH model, and the nonlinear circuit-based EH model, are characterized and discussed. Then, for a typical wireless system setup, we establish a generalized resource allocation design framework that subsumes conventional resource allocation design problems as special cases. Subsequently, we elaborate on relevant tools from optimization theory and exploit them for solving representative resource allocation design problems for SWIPT systems with and without perfect channel state information (CSI) available at the transmitter, respectively. The associated technical challenges and insights are also highlighted. Furthermore, we discuss several promising and exciting future research directions for resource allocation design for SWIPT systems intertwined with cutting-edge communication technologies, such as intelligent reflecting surfaces, unmanned aerial vehicles, mobile edge computing, federated learning, and machine learning.
Keywords: Wireless communication; Resource management; Wireless sensor networks; Integrated circuit modeling; Radio frequency; Systems architecture; RF signals; optimization; resource allocation; simultaneous wireless information and power transfer (SWIPT); wireless pwoer transfer (WPT)

Resource Allocation for Solar Powered UAV Communication Systems - Sun, Yan; Wing Kwan Ng, Derrick; Xu, Dongfang; Dai, Linglong; Schober, Robert (IEEE Workshop on Signal Processing Advances in Wireless Communications, SPAWC, 2018)
In this paper, we investigate the resource allocation design for multicarrier (MC) systems employing a solar powered unmanned aerial vehicle (UAV) for providing communication services to multiple downlink users. We study the joint design of the three-dimensional positioning of the UAV and the power and subcarrier allocation for maximization of the system sum throughput. The algorithm design is formulated as a mixed-integer non-convex optimization problem, which requires a prohibitive computational complexity for obtaining the globally optimal solution. Therefore, a low-complexity suboptimal iterative solution based on successive convex approximation is proposed. Simulation results confirm that the proposed suboptimal algorithm achieves a substantially higher system sum throughput compared to several baseline schemes.
CRIS-Team Scopus Importer:2020-01-31

Resource allocation for wireless communication networks with RF energy harvesting - Boshkovska, Elena; Ng, Derrick Wing Kwan; Schober, Robert (From Internet of Things to Smart Cities: Enabling Technologies, 2017)
The successful development of wireless communication networks and technologies has triggered an exponential growth in the number of wireless communication devices worldwide. In the near future, devices embedded with multifunctional sensors and communication chip sets will be able to collect and exchange information via the Internet. Specifically, these smart devices will be connected to computationally powerful central computing systems to provide intelligent services for the daily life such as environmental monitoring, e-health, automated control, energy management, logistics, and safety management. This new concept of interconnecting a massive number of communication and sensing devices is known as the Internet of Things (IoT).
CRIS-Team Scopus Importer:2020-01-31

RIS-Assisted Device Activity Detection with Statistical Channel State Information - Laue, Friedemann; Jamali, Vahid; Schober, Robert (IEEE Transactions on Wireless Communications, 2023)
This paper studies reconfigurable intelligent surface (RIS)-assisted device activity detection for grant-free (GF) uplink transmission in wireless communication networks. In particular, we consider mobile devices located in an area where the direct link to an access point (AP) is blocked. Thus, the devices try to connect to the AP via a reflected link provided by an RIS. Therefore, for the RIS, a phase-shift design is desired that covers the entire blocked area with a wide reflection beam because the exact locations and times of activity of the devices are unknown in GF transmission. In order to study the impact of the phase-shift design on the device activity detection at the AP, we derive a generalized likelihood ratio test (GLRT) based detector and present an analytical expression for the probability of detection, which is a function of the channel statistics and the phase-shift design. Assuming knowledge of statistical channel state information (CSI), we formulate an optimization problem for the phase-shift design for maximization of the guaranteed probability of detection for all locations within a given coverage area. To tackle the non-convexity of the problem, we propose two different approximations of the objective function and an algorithm based on the majorization-minimization (MM) principle. The first approximation leads to a design that aims to reduce the variations of the end-to-end channel while taking system parameters such as transmit power, noise power, and probability of false alarm into account. The second approximation can be adopted for versatile RIS deployments because it only depends on the line-of-sight (LoS) component of the end-to-end channel and is not affected by system parameters. For comparison, we also consider a phase-shift design maximizing the average channel gain and a baseline analytical phase-shift design for large blocked areas. Our performance evaluation shows that the proposed approximations result in phase-shift designs that guarantee a high probability of detection across the coverage area and outperform the baseline designs.
CRIS-Team Scopus Importer:2023-06-02
Keywords: Channel models; coverage extension; Detectors; Device activity detection; grant-free uplink; Mobile handsets; Optimization; Performance evaluation; phase-shift design; Probability; reconfigurable intelligent surface; Reflection; statistical channel state information

Risk-averse forward contract for electric vehicle frequency regulation service - Yao, Enxin; Wong, Vincent W. S.; Schober, Robert (2015 IEEE International Conference on Smart Grid Communications (SmartGridComm, 2015)
Electric vehicles (EVs) can be coordinated by an aggregator to participate in the electricity day-ahead market (DAM) and provide frequency regulation service. In the DAM, a short-term forward contract is made between the aggregator and an independent system operator (ISO). The contract specifies the contract size, which is the amount of regulation capacity provided by the aggregator for each hour of the next day. However, since the capacity of the aggregator is provided by many EVs instead of a single source, the challenge is how to efficiently aggregate the small and uncertain individual capacity and determine the optimal size of the forward contract. We consider two cases for the contract between the aggregator and the ISO. In the first case, the aggregator needs to ensure that the capacity provided by the EVs on the next day will meet the amount specified in the contract. In contrast, in the second case, the ISO allows an update of the contract size. A stochastic program is formulated to determine the contract size for both cases. Our problem formulation incorporates risk management using the conditional value at risk (CVaR). Chance constraints are embedded when the contract size is fixed. We tackle the chance constraints using the Markov inequality and propose an efficient algorithm. The EV charging data collected in the province of British Columbia, Canada, is used to evaluate the performance of the proposed algorithm. Simulation results show that the proposed algorithm improves the revenue of the aggregator compared to an existing algorithm from the literature.<br
Keywords: Forward contracts; ISO; Frequency control; Smart grids; Microgrids; Real-time systems

Robust and Secure Resource Allocation for Full-Duplex MISO Multicarrier NOMA Systems - Sun, Yan; Ng, Derrick Wing Kwan; Zhu, Jun; Schober, Robert (IEEE Transactions on Communications, 2018)
In this paper, we study the resource allocation algorithm design for multiple-input single-output (MISO) multicarrier non-orthogonal multiple access (MC-NOMA) systems, in which a full-duplex base station serves multiple half-duplex uplink and downlink users on the same subcarrier simultaneously. The resource allocation is optimized for maximization of the weighted system throughput while the information leakage is constrained and artificial noise is injected to guarantee secure communication in the presence of multiple potential eavesdroppers. To this end, we formulate a robust non-convex optimization problem taking into account the imperfect channel state information of the eavesdropping channels and the quality-of-service requirements of the legitimate users. Despite the non-convexity of the optimization problem, we solve it optimally by applying monotonic optimization which yields the optimal beamforming, artificial noise design, subcarrier allocation, and power allocation policy. The optimal resource allocation policy serves as a performance benchmark since the corresponding monotonic optimization-based algorithm entails a high computational complexity. Hence, we also develop a low-complexity suboptimal resource allocation algorithm which converges to a locally optimal solution. Our simulation results reveal that the performance of the suboptimal algorithm closely approaches that of the optimal algorithm. Besides, the proposed optimal MISO NOMA system can not only ensure downlink and uplink communication security simultaneously but also provides a significant system secrecy rate improvement compared with the traditional MISO orthogonal multiple access systems and two other baseline schemes.<br
Keywords: physical layer security; full-duplex radio; multicarrier systems; imperfect channel state information; Non-orthogonal multiple access (NOMA); non-convex and combinatorial optimization

Robust and Secure Resource Allocation for ISAC Systems: A Novel Optimization Framework for Variable-Length Snapshots - Xu, Dongfang; Yu, Xianghao; Ng, Derrick Wing Kwan; Schmeink, Anke; Schober, Robert (IEEE Transactions on Communications, 2022)
In this paper, we investigate the robust resource allocation design for secure communication in an integrated sensing and communication (ISAC) system. A multi-antenna dual-functional radar-communication (DFRC) base station (BS) serves multiple single-antenna legitimate users and senses for targets simultaneously, where already identified targets are treated as potential single-antenna eavesdroppers. The DFRC BS scans a sector with a sequence of dedicated beams, and the ISAC system takes a snapshot of the environment during the transmission of each beam. Based on the sensing information, the DFRC BS can acquire the channel state information (CSI) of the potential eavesdroppers. Different from existing works that focused on the resource allocation design for a single snapshot, in this paper, we propose a novel optimization framework that jointly optimizes the communication and sensing resources over a sequence of snapshots with adjustable durations. Besides, artificial noise (AN) is exploited by the BS for joint sensing and physical layer security provisioning. To this end, we jointly optimize the duration of each snapshot, the beamforming vector, and the covariance matrix of the AN for maximization of the system sum secrecy rate over a sequence of snapshots while guaranteeing a minimum required average achievable rate and a maximum information leakage constraint for each legitimate user. The resource allocation algorithm design is formulated as a non-convex optimization problem, where we account for the imperfect CSI of both the legitimate users and the potential eavesdroppers. To make the problem tractable, we derive a bound for the uncertainty region of the potential eavesdroppers’ small-scale fading based on a safe approximation, which facilitates the development of a block coordinate descent-based iterative algorithm for obtaining an efficient suboptimal solution. Simulation results illustrate that the proposed scheme can significantly enhance the physical layer security of ISAC systems compared to three baseline schemes. Moreover, compared to the conventional multi-stage approach for ISAC system design, the proposed approach based on variable-length snapshots not only facilitates a highly-directional offline sensing beam design but also allows us to flexibly prioritize communication or sensing depending on the application scenario.
CRIS-Team Scopus Importer:2022-11-25
Keywords: Array signal processing; beamforming design; imperfect channel state information; Integrated sensing and communication; Optimization; Radar; Resource management; secure communication; Sensors; Uncertainty; Wireless communication

Robust and Secure Wireless Communications via Intelligent Reflecting Surfaces - Yu, Xianghao; Xu, Dongfang; Sun, Ying; Ng, Derrick Wing Kwan; Schober, Robert (IEEE Journal on Selected Areas in Communications, 2020)
In this paper, intelligent reflecting surfaces (IRSs) are employed to enhance the physical layer security in a challenging radio environment. In particular, a multi-antenna access point (AP) has to serve multiple single-antenna legitimate users, which do not have line-of-sight communication links, in the presence of multiple multi-antenna potential eavesdroppers whose channel state information (CSI) is not perfectly known. Artificial noise (AN) is transmitted from the AP to deliberately impair the eavesdropping channels for security provisioning. We investigate the joint design of the beamformers and AN covariance matrix at the AP and the phase shifters at the IRSs for maximization of the system sum-rate while limiting the maximum information leakage to the potential eavesdroppers. To this end, we formulate a robust non-convex optimization problem taking into account the impact of the imperfect CSI of the eavesdropping channels. To address the non-convexity of the optimization problem, an efficient algorithm is developed by capitalizing on alternating optimization, a penalty-based approach, successive convex approximation, and semidefinite relaxation. Simulation results show that IRSs can significantly improve the system secrecy performance compared to conventional architectures without IRS. Furthermore, our results unveil that, for physical layer security, uniformly distributing the reflecting elements among multiple IRSs is preferable over deploying them at a single IRS.
CRIS-Team Scopus Importer:2020-07-17
Keywords: Alternating optimization; imperfect channel state information; intelligent reflecting surface; physical layer security

Robust Beamforming Design in C-RAN With Sigmoidal Utility and Capacity-Limited Backhaul - Wang, Zehua; Wing Kwan Ng, Derrick; Wong, Vincent W. S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2017)
In this paper, we study the robust beamforming design in cloud radio access networks, where remote radio heads (RRHs) are connected to a cloud server that performs signal processing and resource allocation in a centralized manner. Different from traditional approaches adopting a concave increasing function to model the utility of a user, we model the utility by a sigmoidal function of the signal-to-interference-plus-noise ratio (SINR) to capture the diminishing utility returns for very small and very large SINRs in real-time applications (e.g., video streaming). Our objective is to maximize the aggregate utility of the users while considering the imperfection of channel state information (CSI), limited backhaul capacity, and minimum quality of service requirements. Because of the sigmoidal utility function and some of the constraints, the formulated problem is non-convex. To efficiently solve the problem, we introduce a maximum interference constraint, transform the CSI uncertainty constraints into linear matrix inequalities, employ convex relaxation to handle the backhaul capacity constraints, and exploit the sum-of-ratios form of the objective function. This leads to an efficient resource allocation algorithm, which outperforms several baseline schemes, and closely approaches a performance upper bound for large CSI uncertainty or large number of RRHs.<br
Keywords: Array signal processing; Interference; Signal to noise ratio; Servers; Downlink; Data communication; Mobile communication

Robust Beamforming for Secure Communication in Systems With Wireless Information and Power Transfer - Wing Kwan Ng, Derrick; Lo, Ernest S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2014)
This paper considers a multiuser multiple-input single-output (MISO) downlink system with simultaneous wireless information and power transfer. In particular, we focus on secure communication in the presence of passive eavesdroppers and potential eavesdroppers (idle legitimate receivers). We study the design of a resource allocation algorithm minimizing the total transmit power for the case when the legitimate receivers are able to harvest energy from radio frequency signals. Our design advocates the dual use of both artificial noise and energy signals in providing secure communication and facilitating efficient wireless energy transfer. The algorithm design is formulated as a non-convex optimization problem. The problem formulation takes into account artificial noise and energy signal generation for protecting the transmitted information against both considered types of eavesdroppers when imperfect channel state information (CSI) of the potential eavesdroppers and no CSI of the passive eavesdroppers are available at the transmitter. Besides, the problem formulation also takes into account different quality of service (QoS) requirements: a minimum required signal-to-interference-plus-noise ratio (SINR) at the desired receiver; maximum tolerable SINRs at the potential eavesdroppers; a minimum required outage probability at the passive eavesdroppers; and minimum required heterogeneous amounts of power transferred to the idle legitimate receivers. In light of the intractability of the problem, we reformulate the considered problem by replacing a non-convex probabilistic constraint with a convex deterministic constraint. Then, a semi-definite programming (SDP) relaxation approach is adopted to obtain the optimal solution for the reformulated problem. Furthermore, we propose a suboptimal resource allocation scheme with low computational complexity for providing communication secrecy and facilitating efficient energy transfer. Simulation results demonstrate the close-to-optimal performance of the proposed schemes and significant transmit power savings by optimization of the artificial noise and energy signal generation.<br
Keywords: Receivers; Transmitters; Noise; Energy harvesting; Wireless communication; Resource management; Algorithm design and analysis

Robust Beamforming for SWIPT Systems with Non-linear Energy Harvesting Model - Boshkovska, Elena; Kölpin, Alexander; Kwan Ng, Derrick Wing; Zlatanov, Nikola; Schober, Robert (IEEE 17th International Workshop on Signal Processing Advances in Wireless Communications (SPAWC), 2016)
This paper investigates resource allocation for simultaneous wireless information and power transfer (SWIPT) downlink systems based on a non-linear energy harvesting model. The resource allocation algorithm design is formulated as a non-convex optimization problem for the maximization of the total harvested power. The proposed problem formulation not only takes into account imperfect channel state information (CSI) but also guarantees the quality-of-service (QoS) of information transfer. A novel iterative algorithm is proposed to obtain the globally optimal solution of the considered non-convex optimization problem. In each iteration, a rank-constrained semidefinite program (SDP) is solved optimally by SDP relaxation. Simulation results demonstrate the significant gains in harvested power and the robustness against CSI imperfection for the proposed optimal resource allocation, compared to a baseline scheme designed for perfect CSI and the conventional linear energy harvesting model.
elib2cris::1512001600,boshkovska2016
Keywords: Energy Harvesting; Diode Detector

Robust cooperative beamforming for SC-FDMA based multi-relay networks - Wu, Peiran; Schober, Robert; Bhargava, Vijay K. (2014 IEEE International Conference on Communications (ICC), 2014)
In this work, we propose a robust cooperative relay beamforming (rBF) design for single-carrier frequency-division multiple access (SC-FDMA) based multiuser multi-relay systems with imperfect channel state information. We maximize a lower bound on the achievable bit rate (ABR) of the network, subject to an aggregate relay transmit power constraint. Employing the primal decomposition technique, we decompose the problem into two subproblems: the rBF coefficient optimization and the relay power allocation. For a given power allocation across the frequency tones, a closed-form solution for the rBF matrices is obtained first. Subsequently, the convexity of the remaining power allocation problem is then proved, and efficient convex optimization methods are employed to find the global optimum. Simulation results validate the excellent performance of the proposed rBF schemes and show their superiority compared to conventional non-robust designs.<br
Keywords: Relays; Channel estimation; Optimization; Vectors; Resource management; Noise; Matrix decomposition

Robust cyclic space-frequency filtering for BICM-OFDM with outdated CSIT - Chen, Harry Z.B.; Schober, Robert; Gerstacker, Wolfgang (IEEE International Conference on Communications, 2009)
In this paper, we introduce robust cyclic space-frequency (CSF) filtering for systems combining bit-interleaved coded modulation (BICM) and orthogonal frequency division multiplexing (OFDM). The proposed robust CSF filtering scheme exploits outdated channel state information at the transmitter (CSIT) and takes into account the reliability of the CSIT via a Bayesian model. Based on an upper bound on the worst-case pairwise error probability we formulate the optimization problem for the robust CSF filters which can be solved exactly for certain special cases. For the general case, we obtain an approximate solution by solving a related problem with additional constraints. This approximate solution can be further improved with a gradient algorithm for the original problem. Simulation results confirm the excellent performance of BICM-OFDM with robust CSF filtering. ©2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Robust Frequency Regulation Capacity Scheduling Algorithm for Electric Vehicles - Yao, Enxin; Wong, Vincent W. S.; Schober, Robert (IEEE Transactions on Smart Grid, 2016)
Electric vehicles (EVs) have the potential to provide frequency regulation service to an independent system operator (ISO) by changing their real-time charging or discharging power according to an automatic generation control (AGC) signal. Recently, the Federal Energy Regulatory Commission has issued Order 755 to ISOs to introduce a performance-based compensation scheme in the frequency regulation market. The goal is to provide economic incentives for fast ramping resources such as EVs to participate in the market. In this paper, we model the EV frequency regulation service under the performance-based compensation scheme. Thereby, a robust optimization framework is adopted for the formulation of a frequency regulation capacity scheduling problem. Our problem formulation takes into account the performance-based compensation scheme, the random AGC signal, and the dynamic arrival and departure times of the EVs. We propose an efficient algorithm to solve the formulated problem. Simulation results show that the proposed algorithm improves the revenue under the performance-based compensation scheme compared with a benchmark algorithm.<br
Keywords: Frequency control; Automatic generation control; ISO; Robustness; Real-time systems; Optimization; Heuristic algorithms

Robust Lp-norm decoding for BICM-based secondary user systems - Nasri, Amir; Schober, Robert (IEEE Transactions on Communications, 2010)
The frequency bands used by secondary user systems such as cognitive radio and ultrawideband (UWB) systems are subject to various forms of nonGaussian noise and interference including cochannel and narrowband interference caused by the primary user and other secondary users as well as manmade impulsive noise. For secondary user systems employing popular bitinterleaved coded modulation (BICM) we propose a robust Lpnorm metric for Viterbi decoding to overcome the harmful effects of nonGaussian noise and interference. For the resulting system, we derive an approximate upper bound on the bit error rate (BER) and a general analytical expression for the asymptotic BER valid for all practically relevant types of fading, including Rayleigh, Ricean, Nakagami m, Nakagamiq, and Weibull fading, and all types of noise and interference with finite moments. Simulation and analytical results show that, in nonGaussian noise and interference, the proposed Lpnorm metric yields large performance gains over the conventional L2norm metric and outperforms erasure decoding. © 2006 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: asymptotic analysis; bit-interleaved coded modulation (BICM); cognitive radio; fading channels; L; non-Gaussian noise and interference; Primary and secondary users; robust metrics; ultra-wideband (UWB)

Robust L p-norm metric for BICM-OFDM cognitive radio systems - Nasri, Amir; Schober, Robert (Canadian Conference on Electrical and Computer Engineering, 2009)
Cognitive radio (CR) systems make efficient use of the frequency spectrum by opportunistically exploiting unoccupied or under-utilized frequency bands. However, the frequency bands used by CR systems are expected to suffer from various forms of noise and interference with non-Gaussian distributions, such as narrowband and co-channel interference caused by the primary user and other CRs, respectively, and man-made impulsive noise. To mitigate the harmful effects of non-Gaussian noise and interference, we propose a robust L p-norm metric for CR systems that employ the popular combination of bit-interleaved coded modulation (BICM) and orthogonal frequency division multiplexing (OFDM). For the considered CR system we provide an approximate upper bound and an asymptotic closed-form approximation for the bit error rate (BER). Our results show that the proposed L p-norm metric can achieve large performance gains compared to the conventional L 2-norm metric in non-Gaussian noise and interference. ©2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Robust MMSE design for full-duplex decode-and-forward SC-FDE relay Systems - Wu, Peiran; Schober, Robert; Bhargava, Vijay K. (2015 IEEE International Conference on Communications (ICC), 2015)
In this paper, we consider the robust transceiver design for a two-hop full-duplex decode-and-forward relay system employing single-carrier transmission with frequency-domain equalization (SC-FDE). The design problem for the transmit precoding and receive equalization is formulated as an optimization problem with the objective to minimize the sum mean-squared error (MSE) of the two hops subject to separate node transmit power constraints. We show that the equalization filters can be optimized individually at the receiving nodes and take the form of robust Wiener filters. However, due to the loopback interference, the transmissions in the two hops are coupled and the transmit precoding problem boils down to a non-convex power allocation problem in the frequency domain. An alternating optimization approach is proposed to obtain the power allocation where convex programming problems and difference of convex programming problems are solved in an alternating manner. Numerical results are provided to validate the MSE and the achievable rate of the proposed robust schemes, showing that significant performance gains can be achieved compared to conventional half-duplex systems and non-robust full-duplex designs.<br
Keywords: Relays; Channel estimation; Optimization; Resource Management; Robustness; Interference; Linear programming

Robust MSE-Balancing Hierarchical Linear/Tomlinson-Harashima Precoding for Downlink Massive MU-MIMO Systems - Zarei, Shahram; Gerstacker, Wolfgang; Weigel, Robert; Vossiek, Martin; Schober, Robert (IEEE Transactions on Wireless Communications, 2018)
In this paper, we propose a robust minimum maximum mean square error Tomlinson-Harashima precoding (Min-Max-MSE THP) scheme and a low-complexity robust Min-Max-MSE hierarchical linear/THP (HL-THP) scheme for downlink massive multiuser multiple-input-multiple-output (MU-MIMO) systems with imperfect channel state information (CSI) at the transmitter. The proposed robust Min-Max-MSE HL-THP scheme comprises an inner linear beamformer (BF), which is designed based on second-order CSI statistics, and outer THP modules, which exploit the instantaneous overall CSI of the cascade of the actual channel and the inner BF. Thereby, the user terminals are divided into groups, where for each group a THP module successively mitigates the intra-group interference, whereas the inter-group interference is canceled by the inner BF. To ensure fairness, we adopt the maximization of the asymptotic signal-to-leakage-plus-noise ratio in the large system limit and the Min-Max-MSE as an optimization criterion for designing the inner BF and the per-group THP modules, respectively. Our analytical and simulation results show that the proposed robust Min-Max-MSE HL-THP scheme achieves a substantially improved performance in terms of the Max-MSE, maximum bit error rate, and minimum rate compared to linear regularized zero-forcing precoding. Moreover, the performance loss of the proposed robust Min-Max-MSE HL-THP scheme compared to the robust Min-Max-MSE THP scheme is small. In addition, our complexity analysis reveals that the proposed robust Min-Max-MSE HL-THP scheme has a much lower computational complexity than the Min-Max-MSE THP scheme. Hence, the robust Min-Max-MSE HL-THP scheme provides a favorable tradeoff between complexity and performanc
lhft_intern.bib::Zarei2018a
Keywords: Precoding; Robustness; Interference; Computational complexity; Optimization; Wireless communication

Robust Resource Allocation for Full-Duplex Cognitive Radio Systems - Sun, Yan; Ng, Derrick Wing Kwan; Zlatanov, Nikola; Schober, Robert (2016)
In this paper, we investigate resource allocation algorithm design for full-duplex (FD) cognitive radio systems. The secondary network employs a FD base station for serving multiple half-duplex downlink and uplink users simultaneously. We study the resource allocation design for minimizing the maximum interference leakage to primary users while providing quality of service for secondary users. The imperfectness of the channel state information of the primary users is taken into account for robust resource allocation algorithm design. The algorithm design is formulated as a non-convex optimization problem and solved optimally by applying semidefinite programming (SDP) relaxation. Simulation results not only show the significant reduction in interference leakage compared to baseline schemes, but also confirm the robustness of the proposed algorithm.

Robust Resource Allocation for MIMO Wireless Powered Communication Networks Based on a Non-Linear EH Model - Boshkovska, Elena; Wing Kwan Ng, Derrick; Zlatanov, Nikola; Kölpin, Alexander; Schober, Robert (IEEE Transactions on Communications, 2017)
In this paper, we consider a multiple-input multiple-output wireless powered communication network, where multiple users harvest energy from a dedicated power station in order to be able to transmit their information signals to an information receiving station. Employing a practical non-linear energy harvesting (EH) model, we propose a joint time allocation and power control scheme, which takes into account the uncertainty regarding the channel state information (CSI) and provides robustness against imperfect CSI knowledge. In particular, we formulate two non-convex optimization problems for different objectives, namely system sum throughput maximization and the maximization of the minimum individual throughput across all wireless powered users. To overcome the non-convexity, we apply several transformations along with a one-dimensional search to obtain an efficient resource allocation algorithm. Numerical results reveal that a significant performance gain can be achieved when the resource allocation is designed based on the adopted non-linear EH model instead of the conventional linear EH model. Besides, unlike a non-robust baseline scheme designed for perfect CSI, the proposed resource allocation schemes are shown to be robust against imperfect CSI knowledge.<br
Keywords: Resource management; Wireless communication; Algorithm design and analysis; Robustness; Power generation; Throughput; Radio frequency

Robust Resource Allocation for UAV Systems with UAV Jittering and User Location Uncertainty - Xu, Dongfang; Sun, Yan; Ng, Derrick Wing Kwan; Schober, Robert (2018 IEEE GLOBECOM WORKSHOPS (GC WKSHPS), 2018)
CRIS-Team WoS Importer:2019-04-16

Robust Transceiver Design for Broadband Multiuser Multi-Relay Networks - Wu, Peiran; Schober, Robert; Bhargava, Vijay K. (IEEE Transactions on Wireless Communications, 2015)
In this paper, we study the robust design of the relay beamforming (rBF) and destination equalization (dEQ) filters for broadband multiuser multi-relay networks employing single-carrier frequency-division multiple access (SC-FDMA) and orthogonal frequency-division multiple access (OFDMA). Thereby, we consider the realistic case where only imperfect channel state information is available for rBF and dEQ filter optimization. Our goal is to maximize a lower bound for the weighted achievable bit rate (ABR) of the network, subject to either individual relay power constraints (Ind-PCs) or an aggregate relay power constraint (Agg-PC). We first derive the optimal dEQ filters and the phases of the optimal rBF filter coefficients, which are independent of the power constraints. For the Agg-PC, the amplitude optimization of the rBF filter coefficients is decomposed into two subproblems, which correspond to the optimization of the power allocation across the relays and the power allocation across the users and subcarriers, respectively. We obtain a closed-form structural solution for the first subproblem by fixing the powers across users and subcarriers, and the global optimal solution for the second subproblem. For the Ind-PCs, the corresponding optimization problem is formulated as a reverse-convex problem with convex constraints. Subsequently, the constrained convex concave procedure is applied to approximate the original non-convex problem with a sequence of convex problems, which can be efficiently solved using convex optimization techniques. Simulation results validate the excellent performance of the proposed robust rBF and dEQ filter designs and show their superiority compared to conventional non-robust and naive relaying schemes.<br
Keywords: Relays; Optimization; OFDM; Channel estimation; Robustness; Broadband communication; Signal to noise ratio

Robust Transceiver Design for SC-FDE Multi-hop Full-Duplex Decode-and-Forward Relaying Systems - Wu, Peiran; Schober, Robert; Bhargava, Vijay Kishore (IEEE Transactions on Wireless Communications, 2015)
In this paper, we consider the robust transceiver design for a multi-hop full-duplex decode-and-forward (DF) relay system employing single-carrier transmission with frequency-domain equalization (SC-FDE). We take into account the effect of imperfect channel state information (CSI) where the CSI errors are modeled as Gaussian random variables with known statistics. The design of the precoding at the transmitter and the equalization at the receiver is formulated as an optimization problem with the objective to minimize two relevant performance metrics, namely, the sum mean-square error (MSE) and the maximum MSE across the different hops, subject to separate transmit power constraints for the nodes. We show that the equalization filters can be optimized individually at the receiving nodes and take the form of robust Wiener filters. However, due to the loopback/backward interference, the transmit signals in the different hops are coupled and the transmit precoding problem leads to a nonconvex power allocation problem in the frequency domain. To find the optimal power allocation, we first employ a sequential geometric programming (sGP) approach, which uses the condensation technique to transform the objective function into a posynomial and then solves a sequence of standard GP problems. The sGP approach requires global channel knowledge at a central node and the involved subproblems admit only numerical solutions. To gain further insight into the structure of the problem, we also consider an alternating optimization (AO) approach for power allocation where convex programming problems and difference of convex programming problems are solved in an alternating manner. The resulting AO algorithm admits closed-form solutions in each iteration step and requires less signaling overhead compared to the centralized sGP scheme. Numerical results for the MSEs and achievable rates of the proposed robust schemes are provided, showing that the proposed sGP and AO algorithms yield significant performance gains compared to conventional half-duplex relay systems and nonrobust full-duplex designs.<br
Keywords: Relays; Resource Management; Channel estimation; Optimization; Robustness; Interference; Transceivers

Robust transmit processing for frequency-selective fading channels with imperfect channel feedback - Jonietz, Christof; Gerstacker, Wolfgang; Schober, Robert (IEEE Transactions on Wireless Communications, 2008)
Reliable channel state information at the transmitter (CSIT) can improve the throughput of wireless networks significantly. In a realistic scenario, there is a mismatch between the CSIT and the true channel. The CSIT may be outdated due to channel variations or could be erroneous due to quantization effects. In this paper, robust transmit beamforming (rBF) and the combination of time-reversal space-time block codes (TR-STBCs) with rBF, both optimized for transmission over frequency-selective fading channels with decision-feedback equalization (DFE), are considered. The reliability of the CSIT is taken into account for the design of channel state dependent transmit signal processing algorithms to achieve robustness against imperfect CSIT. Noisy (quantized) CSIT, outdated CSIT, and the combination of both cases are considered. We show that the performance of the rBF scheme is upper and lower bounded by that of transmit BF with perfect CSIT and optimized delay diversity (ODD) without instantaneous CSIT, respectively. The combination of a TR-STBC with rBF yields significant BF gains in addition to the diversity gains of the TR-STBC for reliable CSIT, whereas for unreliable CSIT, the performance is identical to that of the TR-STB

SAFEGUARDING UAV NETWORKS THROUGH INTEGRATED SENSING, JAMMING, AND COMMUNICATIONS - Wei, Zhiqiang; Liu, Fan; Ng, Derrick Wing Kwan; Schober, Robert (2022 IEEE INTERNATIONAL CONFERENCE ON ACOUSTICS, SPEECH AND SIGNAL PROCESSING (ICASSP), 2022)
CRIS-Team WoS Importer:2023-01-13

Saturating Receiver and Receptor Competition in Synaptic DMC: Deterministic and Statistical Signal Models - Lotter, Sebastian; Schäfer, Maximilian; Zeitler, Johannes; Schober, Robert (IEEE Transactions on Nanobioscience, 2021)
Synaptic communication is based on a biological Molecular Communication (MC) system which may serve as a blueprint for the design of synthetic MC systems. However, the physical modeling of synaptic MC is complicated by the possible saturation of the molecular receiver caused by the competition of neurotransmitters (NTs) for postsynaptic receptors. Receiver saturation renders the system behavior nonlinear in the number of released NTs and is commonly neglected in existing analytical models. Furthermore, due to the ligands’ competition for receptors (and vice versa), the individual binding events at the molecular receiver are in general not statistically independent and the commonly used binomial model for the statistics of the received signal does not apply. Hence, in this work, we propose a novel deterministic model for receptor saturation in terms of a state-space description based on an eigenfunction expansion of Fick’s diffusion equation. The presented solution is numerically stable and computationally efficient. Employing the proposed deterministic model, we show that saturation at the molecular receiver effectively reduces the peak-value of the expected received signal and accelerates the clearance of NTs as compared to the case when receptor occupancy is neglected. We further derive a statistical model for the received signal in terms of the hypergeometric distribution which accounts for the competition of NTs for receptors and the competition of receptors for NTs. The proposed statistical model reveals how the signal statistics are shaped by the number of released NTs, the number of receptors, and the binding kinetics of the receptors, respectively, in the presence of competition. In particular, we show that the impact of these parameters on the signal variance is qualitatively different depending on the relative numbers of NTs and receptors. Finally, the accuracy of the proposed deterministic and statistical models is verified by particle-based computer simulations.
Keywords: Receivers; Mathematical model; Analytical models; Computational modeling; Numerical models; Monte Carlo methods; Degradation

Scalable and Energy-Efficient Millimeter Massive MIMO Architectures: Reflect-Array and Transmit-Array Antennas - Jamali, Vahid; Tulino, Antonia M.; Fischer, Georg; Muller, Ralf; Schober, Robert (ICC 2019 - 2019 IEEE International Conference on Communications (ICC), 2019)
Hybrid analog-digital architectures are considered as promising candidates for implementing millimeter wave (mmWave) massive multiple-input multiple-output (MIMO) systems since they enable a considerable reduction of the required number of costly radio frequency (RF) chains by moving some of the signal processing operations into the analog domain. However, the analog feed network, comprising RF dividers, combiners, phase shifters, and line connections, of hybrid MIMO architectures is not scalable due to its prohibitively high power consumption for large numbers of transmit antennas. Motivated by this limitation, in this paper, we study novel massive MIMO architectures, namely reflect-array (RA) and transmit-array (TA) antennas. We show that the precoders for RA and TA antennas have to meet different constraints compared to those for conventional MIMO architectures. Taking these constraints into account and exploiting the sparsity of mmWave channels, we design an efficient precoder for RA and TA antennas based on the orthogonal matching pursuit algorithm. Furthermore, in order to fairly compare the performance of RA and TA antennas with conventional fully-digital and hybrid MIMO architectures, we develop a unified power consumption model. Our simulation results show that unlike conventional MIMO architectures, RA and TA antennas are highly energy efficient and fully scalable in terms of the number of transmit antennas.<br
Keywords: Vehicular ad hoc networks; Taxonomy; Vehicle-to-infrastructure; Databases; Real-time systems

SCW codes for optimal CSI-free detection in diffusive molecular communications - Jamali Kooshkghazi, Vahid; Ahmadzadeh, Arman; Farsad, Nariman; Schober, Robert (2017 IEEE International Symposium on Information Theory (ISIT), 2017)
Instantaneous or statistical channel state information (CSI) is needed for most detection schemes developed in the molecular communication (MC) literature. Since the MC channel changes, e.g., due to variations in the velocity of flow, the temperature, or the distance between transmitter and receiver, CSI acquisition has to be conducted repeatedly to keep track of CSI variations. Frequent CSI acquisition may entail a large overhead whereas infrequent CSI acquisition may result in a low CSI estimation quality. To cope with these issues, we design codes which facilitate maximum likelihood sequence detection at the receiver without instantaneous or statistical CSI. In particular, assuming concentration shift keying modulation, we show that a class of codes, referred to as strongly constant-weight (SCW) codes, enables optimal CSI-free sequence detection at the cost of decreasing the data rate. For the proposed SCW codes, we analyze the code rate and the error rate. Simulation results verify our analytical derivations and reveal that the proposed CSI-free detector for SCW codes outperforms the baseline coherent and non-coherent detectors for uncoded transmission.<br
Keywords: Receivers; Transmitters; Modulation; Detectors; Complexity theory; Information theory; Molecular communication

Secrecy analysis of multi-cell massive MIMO systems with RCI precoding and artificial noise transmission - Zhu, Jun; Schober, Robert; Bhargava, Vijay K. (2014 6th International Symposium on Communications, Control and Signal Processing (ISCCSP), 2014)
In this paper, we study linear precoding for a secure multi-cell massive multiple-input multiple-output (MIMO) downlink system employing artificial noise generation. We consider the large system limit where the number of base station antennas, the number of mobile users, and the number of eavesdropper antennas are all growing without bound but with fixed ratio. The proposed precoder is based on regularized channel inversion (RCI) with regularization parameter κ. The optimal κ is derived such that the ergodic secrecy rate is maximized in the case of imperfect channel state information at the transmitter due to pilot contamination. Our analytical results show that the proposed RCI precoder outperforms other linear precoders.<br
Keywords: Antennas

Secrecy outage of TAS/GSC in Nakagami-m fading channels - Wang, Lifeng; Elkashlan, Maged; Huang, Jing; Schober, Robert; Mallik, Ranjan K. (2014 IEEE International Conference on Communications (ICC), 2014)
This paper considers transmit antenna selection (TAS) and receive generalized selection combining (GSC) for secure communication in MIMO wiretap channel, where confidential messages transmitted from an N A -antenna transmitter to an N B -antenna legitimate receiver are overheard by an N E -antenna eavesdropper. We assume that the main channel and the eavesdropper's channel undergo Nakagami-m fading with fading parameters m B and m E , respectively. In an effort to assess the secrecy performance, we present a closed-form expression for the secrecy outage probability. We then derive closed-form expressions for the secrecy outage probability at high signal-to-noise ratio (SNR) for two realistic scenarios: 1) the legitimate receiver is located close to the transmitter, and 2) the legitimate receiver and the eavesdropper are located close to the transmitter. In the first scenario, we confirm that the secrecy diversity order is m B N B N A . In the second scenario, we confirm that the secrecy diversity order collapses to zero. While this may appear discouraging at a first glance, we show that low secrecy outage probability can still be achieved.<br
Keywords: Receiving antennas; Transmitting antennas; Niobium; Signal to noise ratio; Fading

Secure and Green SWIPT in Distributed Antenna Networks With Limited Backhaul Capacity - Wing Kwan Ng, Derrick; Schober, Robert (IEEE Transactions on Wireless Communications, 2015)
This paper studies the resource allocation algorithm design for secure information and renewable green energy transfer to mobile receivers in distributed antenna communication systems. In particular, distributed remote radio heads (RRHs/antennas) are connected to a central processor (CP) via capacity-limited backhaul links to facilitate joint transmission. The RRHs and the CP are equipped with renewable energy harvesters and share their energies via a lossy micropower grid for improving the efficiency in conveying information and green energy to mobile receivers via radio frequency signals. The considered resource allocation algorithm design is formulated as a mixed nonconvex and combinatorial optimization problem taking into account the limited backhaul capacity and the quality-of-service requirements for simultaneous wireless information and power transfer (SWIPT). We aim at minimizing the total network transmit power when only imperfect channel state information of the wireless energy harvesting receivers, which have to be powered by the wireless network, is available at the CP. In light of the intractability of the problem, we reformulate it as an optimization problem with binary selection, which facilitates the design of an iterative resource allocation algorithm to solve the problem optimally using the generalized Bender's decomposition (GBD). Furthermore, a suboptimal algorithm is proposed to strike a balance between computational complexity and system performance. Simulation results illustrate that the proposed GBD-based algorithm obtains the global optimal solution and the suboptimal algorithm achieves a close-to-optimal performance. In addition, the distributed antenna network for SWIPT with renewable energy sharing is shown to require a lower transmit power compared with a traditional system with multiple colocated antennas.<br
Keywords: Receivers; Wireless communication; Antenna arrays; Noise; Resource management; Erbium; Communication system security

Secure Downlink Transmission in Massive MIMO System with Zero-Forcing Precoding - Zhu, Jun; Bhargava, Vijay K.; Schober, Robert (European Wireless 2014; 20th European Wireless Conference, 2014)
We analyze the ergodic secrecy rate of multi-cell downlink systems assuming that the number of base station (BS) antennas per cell, the number of mobile users, and the number of eavesdropper antennas are all growing without bound. Our analysis includes the effect of uplink channel estimation, pilot contamination, and path-loss. The BS employs zero-forcing (ZF) precoding and artificial noise (AN) generation for secrecy enhancement. Our analytical results reveal that in a secure massive multiple-input multiple-output (MIMO) system employing AN, ZF precoding outperforms matched-filter (MF) precoding, unless the signal power is very small, inter-cell interference is severe, or the effect of pilot contamination is dominant.<br

Secure layered transmission in multicast systems with wireless information and power transfer - Wing Kwan Ng, Derrick; Schober, Robert; Alnuweiri, Hussein (2014 IEEE International Conference on Communications (ICC), 2014)
This paper considers downlink multicast transmit beamforming for secure layered transmission systems with wireless simultaneous information and power transfer. We study the power allocation algorithm design for minimizing the total transmit power in the presence of passive eavesdroppers and energy harvesting receivers. The algorithm design is formulated as a non-convex optimization problem. Our problem formulation promotes the dual use of energy signals in providing secure communication and facilitating efficient energy transfer. Besides, we take into account a minimum required power for energy harvesting at the idle receivers and heterogeneous quality of service (QoS) requirements for the multicast video receivers. In light of the intractability of the problem, we reformulate the considered problem by replacing a non-convex probabilistic constraint with a convex deterministic constraint which leads to a smaller feasible solution set. Then, a semidefinite programming relaxation (SDR) approach is adopted to obtain an upper bound solution for the reformulated problem. Subsequently, sufficient conditions for the global optimal solution of the reformulated problem are revealed. Furthermore, we propose two suboptimal power allocation schemes based on the upper bound solution. Simulation results demonstrate the excellent performance and significant transmit power savings achieved by the proposed schemes compared to isotropic energy signal generation.<br
Keywords: Receivers; Resource management; Transmitters; Energy harvesting; Wireless communication; Vectors; Interference

Secure Massive MIMO transmission in the presence of an active eavesdropper - Wu, Yongpeng; Schober, Robert; Wing Kwan Ng, Derrick; Xiao, Chengshan; Caire, Giuseppe (2015 IEEE International Conference on Communications (ICC), 2015)
In this paper, we investigate secure and reliable transmission strategies for multi-cell multi-user massive multipleinput multiple-output (MIMO) systems in the presence of an active eavesdropper. We consider a time-division duplex system where uplink training is required and an active eavesdropper can attack the training phase to cause pilot contamination at the transmitter. This forces the precoder used in the subsequent downlink transmission phase to implicitly beamform towards the eavesdropper, thus increasing its received signal power. We derive an asymptotic achievable secrecy rate for matched filter precoding and artificial noise (AN) generation at the transmitter when the number of transmit antennas goes to infinity. For the achievability scheme at hand, we obtain the optimal power allocation policy for the transmit signal and the AN in closed form. For the case of correlated fading channels, we show that the impact of the active eavesdropper can be completely removed if the transmit correlation matrices of the users and the eavesdropper are orthogonal. Inspired by this result, we propose a precoder null space design exploiting the low rank property of the transmit correlation matrices of massive MIMO channels, which can significantly degrade the eavesdropping capabilities of the active eavesdropper.<br
Keywords: MIMO; Correlation; Training; Transmitters; Null space; Fading; Uplink

Secure MISO cognitive radio system with perfect and imperfect CSI - Kwon, Taesoo; Wong, Vincent W.S.; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2012)
In cognitive radio (CR) systems, harmful interference from the secondary system degrades the data rate of the primary system. However, this interference may be beneficial to the primary system in terms of the secrecy rate, when unauthorized users eavesdrop on the primary link. This paper explores multiple-input single-output (MISO) CR systems where the secondary system secures the primary communication in return for permission to use the spectrum. In this context, the optimal transmission strategy has to be found which provides the best tradeoff between the useful and harmful effects of interference on the secrecy rate of the primary system. Considering the cases of perfect and imperfect channel state information of the eavesdroppers we formulate optimization problems for maximizing the primary secrecy rate under secondary data rate requirements. The resulting non-convex optimization problems are solved through a sequence of convex semidefinite programs. The simulation results reveal that the proposed schemes improve the secrecy level of the primary system while meeting the data rate requirements of the secondary system. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Secure resource allocation and scheduling for OFDMA decode-and-forward relay networks - Ng, Derrick Wing Kwan; Lo, Ernest S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2011)
In this paper, we formulate an optimization problem for secure resource allocation and scheduling in orthogonal frequency division multiple access (OFDMA) half-duplex decode-and-forward (DF) relay assisted networks. Our problem formulation takes into account artificial noise generation to combat a passive multiple antenna eavesdropper and the effects of imperfect channel state information at the transmitter (CSIT) in slow fading. The optimization problem is solved by dual decomposition which results in a highly scalable distributed iterative resource allocation algorithm. The packet data rate, secrecy data rate, power, and subcarrier allocation policies are optimized to maximize the average secrecy outage capacity (bit/s/Hz securely and successfully delivered to the users via relays). Simulation results illustrate that our proposed distributed iterative algorithm converges to the optimal solution in a small number of iterations and guarantees a non-zero secrecy data rate for given target secrecy outage and channel outage probability requirements. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: artificial noise generation; decode-and-forward relay; imperfect CSI; MIMO beamforming; passive eavesdropper; Physical (PHY) layer security

Secure SWIPT Networks Based on a Non-Linear Energy Harvesting Model - Boshkovska, Elena; Zlatanov, Nikola; Dai, Linglong; Wing Kwan Ng, Derrick; Schober, Robert (2017 IEEE Wireless Communications and Networking Conference Workshops (WCNCW), 2017)
We optimize resource allocation to enable com- munication security in simultaneous wireless information and power transfer (SWIPT) for internet-of-things (IoT) networks. The resource allocation algorithm design is formulated as a non-convex optimization problem. We aim at maximizing the total harvested power at energy harvesting (EH) receivers via the joint optimization of transmit beamforming vectors and the covariance matrix of the artificial noise injected to facilitate secrecy provisioning. The proposed problem formulation takes into account the non-linearity of energy harvesting circuits and the quality of service requirements for secure communication. To obtain a globally optimal solution of the resource allocation problem, we first transform the resulting non-convex sum-of- ratios objective function into an equivalent objective function in parametric subtractive form, which facilitates the design of a novel iterative resource allocation algorithm. In each iteration, the semidefinite programming (SDP) relaxation approach is adopted to solve a rank-constrained optimization problem optimally. Nu- merical results reveal that the proposed algorithm can guarantee communication security and provide a significant performance gain in terms of the harvested energy compared to existing designs which are based on the traditional linear EH model.<br
Keywords: Erbium; Wireless communication; Resource management; Receivers; Radio frequency; Energy harvesting; Security

Secure transmission in multi-cell massive MIMO systems - Zhu, Jun; Schober, Robert; Bhargava, Vijay K. (2013 IEEE Globecom Workshops, GC Wkshps 2013, 2013)
In this paper, we consider a multi-cell massive MIMO system with matched-filter precoding and artificial noise (AN) generation at the base station (BS) for secure downlink transmission in the presence of multi-antenna passive eavesdroppers. We derive two tight lower bounds for the achievable ergodic secrecy rate and a tight upper bound on the secrecy outage probability of the considered system. The analytical results are used to optimize the amount of power allocated for AN generation. Our results reveal that AN generation is not required in massive MIMO systems as long as the number of BS antennas is much larger than the number of eavesdropper antennas. However, as the number of eavesdropper antennas increases relative to the number of BS antennas, AN becomes beneficial and the amount of power optimally allocated to AN generation increases with the number of eavesdropper antennas. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Secure Transmission in Multicell Massive MIMO Systems - Zhu, Jun; Schober, Robert; Bhargava, Vijay K. (IEEE Transactions on Wireless Communications, 2014)
In this paper, we consider physical layer security provisioning in multicell massive multiple-input-multiple-output (MIMO) systems. Specifically, we consider secure downlink transmission in a multicell massive MIMO system with matched-filter precoding and artificial noise (AN) generation at the base station (BS) in the presence of a passive multiantenna eavesdropper. We investigate the resulting achievable ergodic secrecy rate and the secrecy outage probability for the cases of perfect training and pilot contamination. Thereby, we consider two different AN shaping matrices, namely, the conventional AN shaping matrix, where the AN is transmitted in the null space of the matrix formed by all user channels, and a random AN shaping matrix, which avoids the complexity associated with finding the null space of a large matrix. Our analytical and numerical results reveal the following, in multicell massive MIMO systems employing matched-filter precoding: 1) AN generation is required to achieve a positive ergodic secrecy rate if the user and the eavesdropper experience the same path loss; 2) even with AN generation, secure transmission may not be possible if the number of eavesdropper antennas is too large and not enough power is allocated to channel estimation; 3) for a given fraction of power allocated to AN and a given number of users, in case of pilot contamination, the ergodic secrecy rate is not a monotonically increasing function of the number of BS antennas; and 4) random AN shaping matrices provide a favorable performance/complexity tradeoff and are an attractive alternative to conventional AN shaping matrices.<br
Keywords: MIMO; Channel estimation; Training; Vectors; Contamination; Transmitting antennas; Interference

Secure transmission via transmit antenna selection in MIMO wiretap channels - Yang, Nan; Yeoh, Phee Lep; Elkashlan, Maged; Schober, Robert; Collings, Iain B. (GLOBECOM - IEEE Global Telecommunications Conference, 2012)
We propose and analyze transmit antenna selection (TAS) to enhance physical layer security in a wiretap channel with multiple antennas at the transmitter, the receiver, and the eavesdropper. We consider the practical scenario of passive eavesdropping, where the transmitter does not have any channel state information (CSI) of the eavesdropper's channel. In the main channel between the transmitter and the receiver, we select a single antenna at the transmitter that maximizes the instantaneous signal-to-noise ratio (SNR) at the receiver. At the receiver and the eavesdropper, we consider two combining techniques: 1) maximal-ratio combining (MRC) and 2) selection combining (SC). For non-identical Rayleigh fading between the main channel and the eavesdropper's channel, we first derive new closed-form expressions for the exact and asymptotic secrecy outage probabilities. The asymptotic results accurately reveal the secrecy diversity order and the secrecy array gain. Next, we derive new closed-form expressions for the probability of positive secrecy and characterize the ε-outage secrecy capacity. We show that, under TAS/MRC and TAS/SC protocols, the secrecy outage probability approaches zero and the ε-outage secrecy capacity increases with increasing number of transmitter antennas. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Secure Transmission With Antenna Selection in MIMO Nakagami- m Fading Channels - Wang, Lifeng; Elkashlan, Maged; Huang, Jing; Schober, Robert; Mallik, Ranjan K. (IEEE Transactions on Wireless Communications, 2014)
This paper considers transmit antenna selection (TAS) and receive generalized selection combining (GSC) for secure communication in the multiple-input-multiple-output wiretap channel, where confidential messages transmitted from an NA-antenna transmitter to an NB-antenna legitimate receiver are overheard by an NE-antenna eavesdropper. We assume that the main channel and the eavesdropper's channel undergo Nakagami-m fading with fading parameters mB and mE, respectively. In order to assess the secrecy performance, we present a new unifying framework for the average secrecy rate and the secrecy outage probability. We first derive expressions for the probability density function and the cumulative distribution function of the signal-to-noise ratio with TAS/GSC, from which we derive exact expressions for the average secrecy rate and the secrecy outage probability. We then derive compact expressions for the asymptotic average secrecy rate and the asymptotic secrecy outage probability for two distinct scenarios: 1) the legitimate receiver is located close to the transmitter, and 2) the legitimate receiver and the eavesdropper are located close to the transmitter. For these scenarios, we present new closed-form expressions for several key performance indicators: 1) the capacity slope and the power offset of the asymptotic average secrecy rate, and 2) the secrecy diversity order and the secrecy array gain of the asymptotic secrecy outage probability. For the first scenario, we confirm that the capacity slope is one and the secrecy diversity order is mBNBNA. For the second scenario, we confirm that the capacity slope and the secrecy diversity order collapse to zero.<br
Keywords: Signal to noise ratio; Receiving antennas; Fading; Transmitting antennas; Niobium

Secure Transmission With Large Numbers of Antennas and Finite Alphabet Inputs - Wu, Yongpeng; Wang, Jun-Bo; Wang, Jue; Schober, Robert; Xiao, Chengshan (IEEE Transactions on Communications, 2017)
In this paper, we investigate secure transmission over the large-scale multiple-antenna wiretap channel with finite alphabet inputs. First, we investigate the case where instantaneous channel state information (CSI) of the eavesdropper is known at the transmitter. We show analytically that a generalized singular value decomposition (GSVD)-based design, which is optimal for Gaussian inputs, may exhibit a severe performance loss for finite alphabet inputs in the high signal-to-noise ratio regime. In light of this, we propose a novel Per-Group-GSVD (PG-GSVD) design, which can effectively compensate the performance loss caused by the GSVD design. More importantly, the computational complexity of the PG-GSVD design is by orders of magnitude lower than that of the existing design for finite alphabet inputs while the resulting performance loss is minimal. Then, we extend the PG-GSVD design to the case where only statistical CSI of the eavesdropper is available at the transmitter. Numerical results indicate that the proposed PG-GSVD design can be efficiently implemented in large-scale multiple-antenna systems and achieves significant performance gains compared with the GSVD design.<br
Keywords: Receivers; Signal to noise Ratio; Transmitting antennas; Covariance Matrices; Precoding; MIMO

Secure Video Streaming in Heterogeneous Small Cell Networks with Untrusted Cache Helpers - Xiang, Lin; Ng, Derrick Wing Kwan; Schober, Robert; Wong, Vincent W.S. (2017 IEEE Global Communications Conference, GLOBECOM 2017 - Proceedings, 2017)
This paper studies secure video streaming in cache-enabled small cell networks, where some of the cache-enabled small cell base stations (BSs) helping in video delivery are untrusted. Unfavorably, caching improves the eavesdropping capability of these untrusted helpers as they may intercept both the cached and the delivered video files. To address this issue, we propose joint caching and scalable video coding (SVC) of video files to enable secure cooperative multiple-input multiple-output (MIMO) transmission and exploit the cache memory of all BSs for improving system performance. The caching and delivery design is formulated as a non-convex mixed-integer optimization problem to minimize the total BS transmit power required for secure video streaming. We develop an algorithm based on the modified generalized Benders decomposition (GBD) to solve the problem optimally. Inspired by the optimal algorithm, a low-complexity suboptimal algorithm is also proposed. Simulation results show that the proposed schemes achieve significant gains in power efficiency and secrecy performance compared to three baseline schemes.
CRIS-Team Scopus Importer:2020-01-31

Secure Video Streaming in Heterogeneous Small Cell Networks With Untrusted Cache Helpers - Xiang, Lin; Wing Kwan Ng, Derrick; Schober, Robert; Wong, Vincent W.S. (IEEE Transactions on Wireless Communications, 2018)
This paper studies secure video streaming in cache-enabled small cell networks, where some of the cache-enabled small cell base stations (BSs) helping in video delivery are untrusted. Unfavorably, caching improves the eavesdropping capability of these untrusted helpers as they may intercept both the cached and the delivered video files. To address this issue, we propose joint caching and scalable video coding of video files to enable secure cooperative multiple-input multiple-output transmission and, at the same time, exploit the cache memory of both the trusted and untrusted BSs for improving the system performance. Considering imperfect channel state information at the transmitters, we formulate a two-timescale non-convex mixed-integer robust optimization problem to minimize the total transmit power required for guaranteeing the quality of service and secrecy during video streaming. We develop an iterative algorithm based on a modified generalized Benders decomposition to solve the problem optimally, where the caching and the cooperative transmission policies are determined via offline (long-timescale) and online (short-timescale) optimization, respectively. Furthermore, inspired by the optimal algorithm, a low-complexity suboptimal algorithm based on a greedy heuristic is proposed. Simulation results show that the proposed schemes achieve significant gains in power efficiency and secrecy performance compared to several baseline schemes.<br
Keywords: Streaming media; Wireless communication; Communication system security; Microcell networks; Eavesdropping; MIMO communication; Computer architecture

Security Enhancement via Device-to-Device Communication in Cellular Networks - Wang, Jiaheng; Tang, Qi; Yang, Chungang; Schober, Robert; Li, Jing (IEEE Signal Processing Letters, 2016)
Device-to-device (D2D) communication underlaying cellular networks improves spectral efficiency but causes interference to cellular users (CUs). Such interference can be utilized to help CUs prevent wiretapping. This paper aims to achieve the twofold goal of security provisioning for CUs and spectral efficiency enhancement for D2D links by optimizing the resource sharing of CUs and D2D links. We first provide the necessary and sufficient conditions for the accessibility of a CU channel by a D2D link. Then, we derive the jointly optimal resource sharing strategy, including the closed-form power control and the optimal channel pairing of CUs and D2D links. Numerical results show that the proposed strategy can improve both the CUs' security and D2D spectral efficiency.<br
Keywords: Device-to-device communication; Copper; Security; Power Control; Quality of Service; Interference; Resource management

Selective cooperative relaying over time-varying channels - Michalopoulos, Diomidis S.; Lioumpas, Athanasios S.; Karagiannidis, George K.; Schober, Robert (IEEE Transactions on Communications, 2010)
In selective cooperative relaying only a single relay out of the set of available relays is activated, hence the available power and bandwidth resources are efficiently utilized. However, implementing selective cooperative relaying in time-varying channels may cause frequent relay switchings that deteriorate the overall performance. In this paper, we study the rate at which a relay switching occurs in selective cooperative relaying applications in time-varying fading channels. In particular, we derive closed-form expressions for the relay switching rate (measured in Hz) for opportunistic relaying (OR) and distributed switch and stay combining (DSSC). Additionally, expressions for the average relay activation time for both of the considered schemes are also provided, reflecting the average time that a selected relay remains active until a switching occurs. Numerical results manifest that DSSC yields considerably lower relay switching rates than OR, along with larger average relay activation times, rendering it a better candidate for implementation of relay selection in fast fading environments. © 2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Relay switching rate; selective cooperative relaying

Semiblind iterative receiver for coded MIMO-OFDM systems - Kim, Kyeong Jin; Tsiftsis, Theodoros A.; Schober, Robert (IEEE Transactions on Vehicular Technology, 2011)
In this paper, a semiblind iterative receiver is proposed for coded multiple-input-multiple-output orthogonal frequency-division multiplexing (MIMO-OFDM) systems. A novel iterative extended soft-recursive least square (IES-RLS) estimator for joint channel and frequency offset estimation is introduced. Extrinsic bit information obtained from the channel decoder and expected symbol decisions obtained from the demodulator are simultaneously exploited by the IES-RLS. The proposed receiver combines the MIMO data demodulator, the proposed channel estimator, and the channel decoder in an iterative manner to yield an improved bit error rate (BER) performance. To arrive at a feasible algorithm, the first-order linearization of the received vector signal with respect to the frequency offset is used in the IES-RLS channel estimator. The BER performance, a constellation-constrained mutual information analysis, and an EXIT chart analysis are used to verify the effectiveness of the proposed receiver. Simulation results show the superiority of the proposed semiblind receiver, compared with conventional semiblind receivers. © 2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: EXIT chart analysis; frequency offset and channel estimation; iterative demodulator; low-density parity-check (LDPC) codes; multiple-input-multiple-output orthogonal frequency-division multiplexing (MIMO-OFDM) system; mutual information; spherical-radial transform (SRT)

Sensing time and power optimization in MIMO cognitive radio networks - Moghimi, Farzad; Mallik, Ranjan K.; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2012)
In this paper, we investigate the sensing-throughput tradeoff in multi-antenna cognitive radio (CR) systems. Specifically, we optimize the sensing threshold, sensing time, and transmit power of a multi-input multi-output (MIMO) CR system for maximization of the opportunistic system throughput under transmit power and probability of false alarm and detection constraints. To this end, we propose a new transmission protocol which allows the CR user to simultaneously perform data transmission and spectrum sensing on different spatial subchannels. We formulate a non-convex optimization problem for the optimal choice of the sensing threshold, sensing times, and transmit powers in the different spatial subchannels of MIMO CR systems. Since finding the global optimal solution entails a very high complexity, we develop an efficient iterative algorithm that is based on the concept of alternating optimization and solves only convex subproblems in each iteration. Simulation results show that the developed algorithm closely approaches the global optimal performance and achieves significant performance gains compared to baseline schemes employing equal powers or equal sensing times in all subcannels. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Sensing time and power optimization in MIMO cognitive radio networks - Moghimi, Farzad; Mallik, Ranjan K.; Schober, Robert (IEEE Transactions on Wireless Communications, 2012)
In this paper, we investigate the sensing-throughput tradeoff in multi-antenna cognitive radio (CR) systems. Specifically, we optimize the sensing threshold, sensing time, and transmit power of a multi-input multi-output (MIMO) CR system for maximization of the opportunistic system throughput under transmit power, probability of false alarm, and probability of missed detection constraints. To this end, we propose a new transmission protocol which allows the CR user to simultaneously perform data transmission and spectrum sensing on different spatial subchannels. We formulate non-convex optimization problems for the optimal choice of the sensing threshold, sensing times, and transmit powers in each spatial subchannel for both single-band and multi-band MIMO CR systems. Since finding the global optimal solution of these problems entails a very high complexity, we develop two iterative algorithms that are based on the concept of alternating optimization and solve only convex subproblems in each iteration. Thus, the complexity of these algorithms is low, and we prove their convergence to a fixed point analytically. Simulation results show that the developed algorithms closely approach the global optimal performance and achieve significant performance gains compared to baseline schemes employing equal powers or equal sensing times in all subchannels. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Cognitive radio; MIMO; multi-band systems; non-convex optimization; spectrum sensing; throughput maximization

Signal Reception With Generic Three-State Receptors in Synaptic MC - Lotter, Sebastian; Barros, Michael Taynnan; Schober, Robert; Schäfer, Maximilian (IEEE Global Communications Conference, 2022)
Synaptic communication is studied by communication engineers for two main reasons. One is to enable novel neuroengineering applications that require interfacing with neurons. The other reason is to draw inspiration for the design of synthetic molecular communication systems. Both of these goals require understanding of how the chemical synaptic signal is sensed and transduced at the synaptic receiver (Rx). While signal reception in synaptic molecular communication (SMC) depends heavily on the kinetics of the receptors employed by the synaptic Rxs, existing channel models for SMC either oversimplify the receptor kinetics or employ complex, high-dimensional kinetic schemes limited to specific types of receptors. Both approaches do not facilitate a comparative analysis of different types of natural synapses. In this paper, we propose a novel deterministic channel model for SMC which employs a generic three-state receptor model that captures the characteristics of the most important receptor types in SMC. The model is based on a transfer function expansion of Fick's diffusion equation and accounts for release, diffusion, and degradation of neurotransmitters as well as their reversible binding to finitely many generic postsynaptic receptors. The proposed SMC model is the first that allows studying the impact of the characteristic dynamics of the main postsynaptic receptor types on synaptic signal transmission. Numerical results indicate that the proposed model indeed exhibits a wide range of biologically plausible dynamics when specialized to specific natural receptor types.<br

Simple Semi-Grant-Free Transmission Strategies Assisted by Non-Orthogonal Multiple Access - Ding, Zhiguo; Schober, Robert; Fan, Pingzhi; Poor, H. Vincent (IEEE Transactions on Communications, 2019)
Grant-free transmission is an important feature to be supported by future wireless networks since it reduces the signaling overhead caused by conventional grant-based schemes. However, for grant-free transmission, the number of users admitted to the same channel is not capped, which can lead to a failure of multi-user detection. This paper proposes non-orthogonal multiple-access (NOMA) assisted semi-grant-free (SGF) transmission, which is a compromise between grant-free and grant-based schemes. In particular, instead of reserving channels either for grant-based users or grant-free users, the focus here is on an SGF communication scenario, where users are admitted to the same channel via a combination of grant-based and grant-free protocols. As a result, a channel reserved by a grant-based user can be shared by grant-free users, which improves both connectivity and spectral efficiency. Two NOMA assisted SGF contention control mechanisms are developed to ensure that, with a small amount of signaling overhead, the number of admitted grant-free users is carefully controlled and the interference from the grant-free users to the grant-based users is effectively suppressed. Analytical results are provided to demonstrate that the two proposed SGF mechanisms employing different successive interference cancelation decoding orders are applicable to different practical network scenarios.<br
Keywords: Base stations; Protocols; NOMA; Silicon Carbide; Decoding; Multiuser detection; Fans

Simple Semi-Grant-Free Transmission Strategies Assisted by Non-Orthogonal Multiple Access - Ding, Zhiguo; Schober, Robert; Fan, Pingzhi; Poor, H. Vincent (IEEE Transactions on Communications, 2019)
Grant-free transmission is an important feature to be supported by future wireless networks since it reduces the signaling overhead caused by conventional grant-based schemes. However, for grant-free transmission, the number of users admitted to the same channel is not capped, which can lead to a failure of multi-user detection. This paper proposes non-orthogonal multiple-access (NOMA) assisted semi-grant-free (SGF) transmission, which is a compromise between grant-free and grant-based schemes. In particular, instead of reserving channels either for grant-based users or grant-free users, the focus here is on an SGF communication scenario, where users are admitted to the same channel via a combination of grant-based and grant-free protocols. As a result, a channel reserved by a grantbased user can be shared by grant-free users, which improves both connectivity and spectral efficiency. Two NOMA assisted SGF contention control mechanisms are developed to ensure that, with a small amount of signaling overhead, the number of admitted grant-free users is carefully controlled and the interference from the grant-free users to the grant-based users is effectively suppressed. Analytical results are provided to demonstrate that the two proposed SGF mechanisms employing different successive interference cancelation decoding orders are applicable to different practical network scenarios.
CRIS-Team WoS Importer:2019-07-09

Simulating with AcCoRD: Actor-based Communication via Reaction–Diffusion - Noel, Adam; Cheung, Karen C.; Schober, Robert; Makrakis, Dimitrios; Hafid, Abdelhakim (Nano Communication Networks, 2017)
This paper introduces AcCoRD (Actor-based Communication via Reaction–Diffusion)version 1.0. AcCoRD is a sandbox reaction–diffusion solver designed for the study of molecular communication systems. It uses a hybrid of microscopic and mesoscopic simulation models that enables scalability via user control of local accuracy. AcCoRD is developed in C as an open source command line tool and includes utilities to process simulation output in MATLAB. The latest code and links to user documentation can be found at https://github.com/adamjgnoel/AcCoRD/. This paper provides an overview of AcCoRD's design, including the motivation for developing a specialized reaction–diffusion solver. The corresponding algorithms are presented in detail, including the computational complexity of the microscopic and mesoscopic models. Other novel derivations include the transition rates between adjacent mesoscopic subvolumes of different sizes. Simulation results demonstrate the use of AcCoRD as both an accurate reaction–diffusion solver and one that is catered to the analysis of molecular communication systems. Videos in the supplementary materials demonstrate many of the simulated scenarios. Additional insights from the simulation results include the selection of suitable hybrid model parameters, the impact of reactive surfaces that are in the proximity of a hybrid interface, and the size of a bounded environment that is necessary to assume that it is unbounded. The development of AcCoRD is ongoing, so its future direction is also discussed in order to highlight improvements that will expand its potential areas of application. New features that are being planned at the time of writing include a fluid flow model and more complex actor behavior.
CRIS-Team Scopus Importer:2020-01-31
Keywords: Mesoscopic simulation; Microscopic simulation; Molecular communication; Reaction–diffusion

Simultaneous information transmission and wireless energy transfer via selecting one out of two relays - Michalopoulos, Diomidis; Suraweera, Himal A.; Schober, Robert (2014 6th International Symposium on Communications, Control and Signal Processing (ISCCSP), 2014)
In certain applications, relay terminals can be employed to simultaneously deliver information and energy to a designated receiver and a radio frequency (RF) energy harvester, respectively. The relays are efficiently deployed when one out of the set of available relays is activated, as multiple relay activation reduces the overall spectral efficiency. In this regard, since the relays that are preferable for information and energy delivery do not necessarily coincide with one another, relay selection entails a tradeoff between information transmission and energy transfer. Assuming that two relays are available, we investigate the behavior of the ergodic capacity of the information transmission to the receiver, for a given amount of energy transferred to the RF energy harvester. We propose the optimal relay selection method for a given energy transfer constraint (in a maximum achievable capacity sense), as well as three suboptimal schemes which apply to scenarios with limited channel state information.<br
Keywords: Relays; Energy exchange; Information processing; Wireless sensor networks; Wireless communication; Radio frequency; Receivers

Simultaneously Transmitting And Reflecting (STAR) RIS Aided Wireless Communications - Mu, Xidong; Liu, Yuanwei; Guo, Li; Lin, Jiaru; Schober, Robert (IEEE Transactions on Wireless Communications, 2021)
The novel concept of simultaneously transmitting and reflecting (STAR) reconfigurable intelligent surfaces (RISs) is investigated, where the incident wireless signal is divided into transmitted and reflected signals passing into both sides of the space surrounding the surface, thus facilitating a full-space manipulation of signal propagation. Based on the introduced basic signal model of ‘STAR’, three practical operating protocols for STAR-RISs are proposed, namely energy splitting (ES), mode switching (MS), and time switching (TS). Moreover, a STAR-RIS aided downlink communication system is considered for both unicast and multicast transmission, where a multi-antenna base station (BS) sends information to two users, i.e., one on each side of the STAR-RIS. A power consumption minimization problem for the joint optimization of the active beamforming at the BS and the passive transmission and reflection beamforming at the STAR-RIS is formulated for each of the proposed operating protocols, subject to communication rate constraints of the users. For ES, the resulting highly-coupled non-convex optimization problem is solved by an iterative algorithm, which exploits the penalty method and successive convex approximation. Then, the proposed penalty-based iterative algorithm is extended to solve the mixed-integer non-convex optimization problem for MS. For TS, the optimization problem is decomposed into two subproblems, which can be consecutively solved using state-of-the-art algorithms and convex optimization techniques. Finally, our numerical results reveal that: 1) the TS and ES operating protocols are generally preferable for unicast and multicast transmission, respectively; and 2) the required power consumption for both scenarios is significantly reduced by employing the proposed STAR-RIS instead of conventional reflecting/transmiting-only RISs.
CRIS-Team Scopus Importer:2021-10-29
Keywords: Array signal processing; Multicast communication; Operating protocols; Optimization; Power demand; Protocols; reconfigurable intelligent surfaces; simultaneous transmission and reflection; Unicast; unicast and multicast communication; Wireless communication

Simultaneously Transmitting and Reflecting (STAR)-RISs: A Coupled Phase-Shift Model - Liu, Yuanwei; Mu, Xidong; Schober, Robert; Poor, H. Vincent (IEEE International Conference on Communications, 2022)
A simultaneously transmitting and reflecting reconfigurable intelligent surface (STAR-RIS) aided communication system is investigated, where an access point sends information to two users located on each side of the STAR-RIS. Different from current works assuming that the phase-shift coefficients for transmission and reflection can be independently adjusted, which is non-trivial to realize for purely passive STAR-RISs, a coupled transmission and reflection phase-shift model is considered. Based on this model, a power consumption minimization problem is formulated for both non-orthogonal multiple access (NOMA) and orthogonal multiple access (OMA). In particular, the amplitude and phase-shift coefficients for transmission and reflection are jointly optimized, subject to the rate constraints of the users. To solve this non-convex problem, an efficient element-wise alternating optimization algorithm is developed to find a high-quality suboptimal solution, whose complexity scales only linearly with the number of STAR elements. Finally, numerical results are provided for both NOMA and OMA to validate the effectiveness of the proposed algorithm by comparing its performance with that of STAR-RISs using the independent phase-shift model and conventional reflecting/transmitting-only RISs.
CRIS-Team Scopus Importer:2022-09-16
Keywords: Coefficient design; coupled phase-shift model; reconfigurable intelligent surfaces; simultaneous transmission and reflection

Simultaneous Wireless Information and Power Transfer in modern communication systems - Krikidis, Ioannis; Timotheou, Stelios; Nikolaou, Symeon; Zheng, Gan; Ng, Derrick Wing Kwan; Schober, Robert (IEEE Communications Magazine, 2014)
Energy harvesting for wireless communication networks is a new paradigm that allows terminals to recharge their batteries from external energy sources in the surrounding environment. A promising energy harvesting technology is wireless power transfer where terminals harvest energy from electromagnetic radiation. Thereby, the energy may be harvested opportunistically from ambient electromagnetic sources or from sources that intentionally transmit electromagnetic energy for energy harvesting purposes. A particularly interesting and challenging scenario arises when sources perform simultaneous wireless information and power transfer (SWIPT), as strong signals not only increase power transfer but also interference. This article provides an overview of SWIPT systems with a particular focus on the hardware realization of rectenna circuits and practical techniques that achieve SWIPT in the domains of time, power, antennas, and space. The article also discusses the benefits of a potential integration of SWIPT technologies in modern communication networks in the context of resource allocation and cooperative cognitive radio networks.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Decoding; Energy harvesting; Green products; Radio frequency; Receiving antennas; Telecommunication services; Wireless communication

Single-antenna interference cancellation for complex-valued signal constellations with applications to GSM/EDGE - Lehmann, Andreas; Ruder, Michael; Gerstacker, Wolfgang; Schober, Robert (2011 IEEE 22nd International Symposium on Personal, Indoor and Mobile Radio Communications, 2012)
Different approaches for single antenna interference cancellation (SAIC) in GSM/EDGE have been proposed. Most of them work best in synchronous interference environments. We propose three different modifications of the conventional EDGE receiver, which target the harmful effects of asynchronous co-channel interference (ACCI). All modifications are applicable to all linear modulation alphabets and do not require any modification of the GSM/EDGE air interface. We model the effect of ACCI as impulsive Generalized Gaussian noise. The proposed methods include a modification of the conventional path metrics for the reduced-state equalizer and the decoder, respectively, as well as a Viterbi algorithm, which performs erasure decoding. Based on simulation results, the performances of the proposed schemes are compared with that of a standard GSM/EDGE receiver. We show that all three proposed schemes outperform the standard receiver in ACCI environments and discuss their complexit

Single Antenna Interference Cancellation for GSM/VAMOS/EDGE Using Lp-Norm Detection and Decoding - Ruder, Michael; Lehmann, Andreas; Schober, Robert; Gerstacker, Wolfgang (IEEE Transactions on Wireless Communications, 2015)
Different schemes for single antenna interference cancellation (SAIC) in the Global System for Mobile Communications (GSM) have been proposed so far. Most of these schemes work best in synchronous interference environments and are limited to Gaussian minimum-shift keying (GMSK) modulation. In this paper, we propose several modifications of the conventional GSM receiver, which target the harmful effects of asynchronous co-channel interference (ACCI). Based on the observation that the impairment caused by ACCI cannot be modeled as additive Gaussian noise, which was assumed for the derivation of the metric used in state-of-the-art receivers, we propose modeling the impairment as Generalized Gaussian noise (GGN). This leads to modifications of the conventional branch metrics of the reduced-state equalizer and the decoder employed at the receiver. Both proposed modifications are applicable to any linear modulation alphabet and do not require any modification of the GSM air interface. Hence, the proposed novel branch metrics are also applicable in Enhanced Data Rates for GSM Evolution (EDGE) systems which employ 8-ary phase-shift keying (8-PSK) modulation and where the SAIC algorithms tailored for GMSK cannot be used. Furthermore, we show that the proposed branch metric modifications also improve the performance of the new Voice Services over Adaptive Multiuser channels on One Slot (VAMOS) extension of GSM in ACCI environments. Based on simulation results, the performance of the proposed schemes is compared with that of an unmodified receiver employing the conventional Gaussian metric. We show that the proposed receivers outperform the unmodified receiver in ACCI environments and discuss the complexity entailed by the proposed branch metric modifications.<br
Keywords: Measurement; GSM; Receivers; Decoding; Equalizers; Interference; Modulation

SINR-based random access for cognitive radio: Distributed algorithm and coalitional game - Cheung, Man Hon; Wong, Vincent W. S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2011)
In this paper, we study the problem of multi-channel medium access control (MAC) in cognitive radio (CR) networks. While most of the previously proposed MAC protocols for CR networks are heuristic and are based on the simplistic protocol model, we design a distributed MAC protocol using the more accurate signal-to-interference-plus-noise-ratio (SINR) model. First, we assume that the secondary users are cooperative and formulate the problem of assigning transmission and listening probabilities for random access as a non-convex network utility maximization problem. We propose a three-phase algorithm that converges to a near-optimal solution after solving a number of convex optimization problems distributively. Simulation results show that our proposed algorithm based on the SINR model achieves a higher aggregate throughput than other schemes which are based on the protocol model. Then, we consider the case that the secondary users are rational. We use coalitional game theory to study the incentive issues of user cooperation in a given channel for the SINR model. In particular, we use the solution concept of the core to analyze the stability of the grand coalition, and the solution concept of the Shapley value to fairly divide the payoff among the users. We show that the Shapley value lies in the core when all the users are one-hop neighbours of each other. We illustrate the Shapley value and the core with a numerical example. © 2006 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: coalitional game theory; Cognitive radio networks; multi-channel medium access control (MAC); network utility maximization; non-convex optimization; random access; SINR model

SLNC for multi-source multi-relay BICM-OFDM systems - Islam, Toufiqul; Schober, Robert; Mallik, Ranjan K.; Bhargava, Vijay (IEEE Transactions on Wireless Communications, 2014)
In this paper, we study the application of bit - interleaved coded modulation (BICM) and orthogonal frequency division multiplexing (OFDM) to reap the benefits of wireless multiuser network coding in practical frequency - selective fading channels. We propose a mapping based symbol level network coding (SLNC) scheme for a cooperative diversity system comprising multiple sources, multiple relays, and one common destination. A simple cooperative maximum - ratio combining scheme is used at the destination and is shown to successfully exploit both the full spatial and the full frequency diversity offered by the channel for arbitrary numbers of sources, arbitrary numbers of relays, and arbitrary linear modulation schemes. To gain analytical insight for system design, we derive a closed - form upper bound for the asymptotic worst - case pairwise error probability (PEP) and obtain the diversity gain of the considered SLNC scheme for BICM - OFDM systems. These analytical results reveal the influence of the various system parameters, such as the number of sources, the free distance of the code, and the frequency diversity of the involved links, on performance. Furthermore, we propose two different relay selection schemes for the considered system: a) bulk selection, i.e., a single best relay is selected to transmit on all sub - carriers, and b) per - subcarrier selection, where a best relay is selected on each sub - carrier. Last but not least, we exploit the derived PEP expression for selecting a subset of sources from the set of active sources when the number of active sources is larger than the number of available orthogonal relay channels. We study the achievable diversity gain for the proposed relay and source subset selection schemes. Numerical results corroborate the derived diversity gain expressions and confirm the performance gains. © 2002-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: BICM - OFDM; Cooperative diversity; network coding; relay selection; source subset selection

Smart and Reconfigurable Wireless Communications: From IRS Modeling to Algorithm Design - Yu, Xianghao; Jamali, Vahid; Xu, Dongfang; Ng, Derrick Wing Kwan; Schober, Robert (IEEE Wireless Communications, 2021)
Intelligent reflecting surfaces (IRSs) have been introduced into wireless communications systems due to their great potential to smartly customize and reconfigure radio propagation environments in a cost-effective manner. Despite the promising advantages of IRSs, academic research on IRSs is still in its infancy. In particular, the design and analysis of IRS-assisted wireless communication systems critically depend on accurate and tractable modeling of the IRS. In this article, we first present and compare three IRS models, namely the conventional independent diffusive scatterer-based model, physics-based model, and impedance network-based model, in terms of their accuracy, tractability, and implementation simplicity. Furthermore, a new framework based on partitioning the IRS into tiles and employing codebooks of transmission modes is introduced to enable scalable IRS optimization. Then we investigate the impact of the three considered IRS models on system design, where several crucial technical challenges for the efficient design of IRS-assisted wireless systems are identified and the corresponding solutions are unraveled. Furthermore, to illustrate the properties of the considered models and the efficiency of the proposed solution concepts, IRS-assisted secure wireless systems and simultaneous wireless information and power transfer systems are studied in more detail. Finally, several promising future research directions for IRS-assisted wireless systems are highlighted.
CRIS-Team WoS Importer:2022-02-04

Space full-duplex max-max relay selection for relays with buffers - Ikhlef, Aissa; Kim, Junsu; Schober, Robert (GLOBECOM - IEEE Global Telecommunications Conference, 2012)
In this paper, a new relaying scheme, referred to as space full-duplex max-max relay selection (SFD-MMRS) is proposed. SFD-MMRS uses relay selection and half-duplex (HD) relays with buffers to mimic full-duplex (FD) relaying. It allows the selection of different relays for reception and transmission, which in turn enables simultaneous reception and transmission. With SFD-MMRS the pre-log factor 1 over 2 is removed from the capacity expression and better performance in terms of throughput is achieved compared to the existing schemes. We provide a comprehensive analysis of the capacity of the proposed scheme for a decode-and-forward (DF) protocol in Rayleigh fading. Our simulation results show that the capacity of the proposed scheme with HD relays exceeds twice the capacity of the best relay selection (BRS) scheme with HD relays. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Space-Time Block Coding and Receive Diversity for WLAN IEEE 802.11b - Jonietz, Christof; Gerstacker, Wolfgang; Schober, Robert (Conference Proceedings, 2005)
In this paper, we investigate time-reversal space-time block codes (TR-STBCs) and receive diversity for complementary code keying (CCK) modulation, which is employed in the wireless local area network (WLAN) standard IEEE 802.11b. The construction of TR-STBCs from orthogonal space-time block codes designed for flat fading channels for an arbitrary number of transmit antennas is discussed. Furthermore, an equivalent single-input single-output (SISO) transmission model for CCK is derived, which combines the effects of space-time coding and multiple receive antennas. For indoor multipath fading channels numerical results are provided for TR-STBCs with two and three transmit antennas, which demonstrate that significant gains can be obtained compared to a SISO transmission. For detection, decision-feedback equalization (DFE) and reduced-state sequence estimation (RSSE) especially tailored for CCK transmission are considered. © 2005 IEEE.
UnivIS-Import:2015-04-16:Pub.2005.tech.IE.mobilk.spacet
Keywords: Block codes; Wireless LAN; Diversity reception; Decision feedback Equalizers; Fading; Diversity methods; Modulation coding; Transmitting antennas; Frequency diversity; Decoding

Space-Time Continuous Phase Modulation for Non-Coherent Detection - Silvester, Anna-Marie; Lampe, Lutz; Schober, Robert (IEEE Transactions on Wireless Communications, 2008)
The combination of space-time (ST) coding and continuous-phase modulation (CPM) is attractive for power-efficient transmission over fading channels. In this paper, we propose a diagonal block-based ST-CPM (DBST-CPM) scheme, which in addition to its high power efficiency facilitates noncoherent detection at the receiver. DBST-CPM can be regarded as a non-trivial extension of well-known differential ST modulation (DSTM) with diagonal signal matrices for linear modulation formats. For optimization of the code parameters of DBST-CPM we derive an upper bound on the frame-error rate of DBST-CPM in the quasi-static fading channel (QSFC) and we present an efficient optimization algorithm. Additionally, we derive decision rules for low-complexity non-coherent detection of DBST-CPM in various fading environments. Numerical and simulation results show that (a) the derived upper bound accurately predicts the performance of DBST-CPM in the QSFC, (b) the proposed code optimization yields highly power-efficient designs, and (c) the non-coherent detectors approach the performances of their coherent counterparts for various fading channel models. © 2008 IEEE
CRIS-Team Scopus Importer:2020-02-03
Keywords: Continuous-phase modulation (CPM); decision-feedback detection; differential space-time modulation (DTSM); non-coherent detection; Space-time transmission; Viterbi detection

Special Issue on "advanced distributed wireless communication techniques - Theory and practice" - Mietzner, Jan; Wuebben, Dirk; Michalopoulos, Diomidis; Schober, Robert; Rost, Peter M.; Mecklenbraeuker, Christoph (EURASIP Journal on Advances in Signal Processing, 2013)
CRIS-Team Scopus Importer:2020-02-03

Special Issue on Intelligent Reflecting Surface for Green Communication, Computing, and Sensing - You, Changsheng; Wu, Qingqing; Liu, Yuanwei; Schober, Robert; Swindlehurst, A. Lee (IEEE Transactions on Green Communications and Networking, 2022)
CRIS-Team WoS Importer:2022-03-11

Special Issue on Next Generation Multiple Access-Part I - Liu, Yuanwei; Zhang, Shuowen; Ding, Zhiguo; Schober, Robert; Al-Dhahir, Naofal; Hossain, Ekram; Shen, Xuemin (IEEE Journal on Selected Areas in Communications, 2022)
As the long-term evolution (LTE) system is reaching maturity and the fifth-generation (5G) systems are being commercially deployed, researchers have turned their attention to the development of next-generation wireless networks. Compared to current wireless networks, on the one hand, next-generation wireless networks are expected to achieve significantly higher capacity, extremely low latency, ultra-high reliability, as well as massive and ubiquitous connectivity for supporting diverse disruptive applications (e.g., virtual reality (VR), augmented reality (AR), and industry 4.0). On the other hand, the evolution toward next-generation wireless networks requires a paradigm shift from the communication-oriented design to a multi-functional design, including communication, sensing, imaging, computing, and localization. Looking back at the history of wireless communication systems, multiple access (MA) techniques have been key enablers. From the first generation (1G) to the fifth generation (5G), orthogonal multiple access (OMA) schemes are mainly employed, where multiple users are allotted in orthogonal frequency/time/code resources, and the uplink transmission of the code code-division multiple-access (CDMA) uses non-orthogonal code resources. However, given the enormous challenges and diverse services of next-generation wireless networks, which significantly differ from that in current and previous wireless networks, existing MA schemes may not be applicable. As a result, a fundamental issue is the design of next-generation multiple access (NGMA) techniques. The key concept of NGMA is to enable a very large number of users/devices to be efficiently, flexibly, and intelligently connected with the network over the given wireless radio resources to not only satisfy stringent communication requirements but also realize heterogeneous functions. The investigation of NGMA is still in the infancy stage, and extensive research efforts have to be devoted to areas, including but not limited to 1) the development of new MA schemes, such as non-orthogonal multiple access (NOMA) and space division multiple access (SDMA), which are capable of achieving higher bandwidth efficiency and higher connectivity compared with conventional MA schemes; 2) the development of innovative techniques, such as reconfigurable metasurfaces, random access, advanced modulation, and channel coding, which are beneficial to the overall design of NGMA; and 3) the exploitation of advanced machine learning (ML) tools and big data techniques for providing effective solutions to address newly emerging NGMA problems.
CRIS-Team WoS Importer:2022-04-01

Special Issue on UAV Communications in 5G and Beyond Networks-Part I - Wu, Qingqing; Xu, Jie; Zeng, Yong; Ng, Derrick Wing Kwan; Al-Dhahir, Naofal; Schober, Robert; Swindlehurst, A. Lee (IEEE Journal on Selected Areas in Communications, 2021)
CRIS-Team WoS Importer:2021-09-24

Special Section on Full-Duplex Transceivers for Future Networks: Theory and Techniques - Tran, Nghi H.; Suraweera, Himal A.; Riihonen, Taneli; Reiskarimian, Negar; Jain, Hardik; Schober, Robert (IEEE Open Journal of the Communications Society, 2021)
Conventional wireless communication systems operate in a half-duplex mode, i.e., current radios cannot transmit and receive at the same time and on the same frequency. Full-duplex wireless operation was generally assumed to be impossible due to the great difference in transmit and receive signal power levels. However, recent advances in antenna, hardware, and signal processing techniques have shown that full-duplex operation is practically feasible. Thanks to novel combinations of antenna, analog, and digital cancellation techniques, self-interference suppression of 80-110 dB can be made possible. The feasibility in building a practical full-duplex radio using off-the-shelf hardware and software-defined radios therefore alleviates many problems in wireless network design.
CRIS-Team WoS Importer:2021-11-26

Spectral and Energy-Efficient Wireless Powered IoT Networks: NOMA or TDMA? - Wu, Qingqing; Chen, Wen; Wing Kwan Ng, Derrick; Schober, Robert (IEEE Transactions on Vehicular Technology, 2018)
Wireless powered communication networks (WPCNs), where multiple energy-limited devices first harvest energy in the downlink and then transmit information in the uplink, have been envisioned as a promising solution for the future Internet-of-Things (IoT). Meanwhile, nonorthogonal multiple access (NOMA) has been proposed to improve the system spectral efficiency (SE) of the fifth-generation (5G) networks by allowing concurrent transmissions of multiple users in the same spectrum. As such, NOMA has been recently considered for the uplink of WPCNs based IoT networks with a massive number of devices. However, simultaneous transmissions in NOMA may also incur more transmit energy consumption as well as circuit energy consumption in practice which is critical for energy constrained IoT devices. As a result, compared to orthogonal multiple access schemes such as time-division multiple access (TDMA), whether the SE can be improved and/or the total energy consumption can be reduced with NOMA in such a scenario still remains unknown. To answer this question, we first derive the optimal time allocations for maximizing the SE of a TDMA-based WPCN (T-WPCN) and a NOMA-based WPCN (N-WPCN), respectively. Subsequently, we analyze the total energy consumption as well as the maximum SE achieved by these two networks. Surprisingly, it is found that N-WPCN not only consumes more energy, but also is less spectral efficient than T-WPCN. Simulation results verify our theoretical findings and unveil the fundamental performance bottleneck, i.e., “worst user bottleneck problem”, in multiuser NOMA systems.<br
Keywords: NOMA; Energy consumption; Wireless communication; Time division multiple Access; Throughput; Resource Management; IEEE transactions

Spectral efficiency in large-scale MIMO-OFDM systems with per-antenna power cost - Ng, Derrick Wing Kwan; Schober, Robert (Conference Record - Asilomar Conference on Signals, Systems and Computers, 2012)
In this paper, resource allocation for multipleinput multiple-output orthogonal frequency division multiplexing (MIMO-OFDM) downlink networks with large numbers of base station antennas is studied. Assuming perfect channel state information at the transmitter, the resource allocation algorithm design is modeled as a non-convex optimization problem which takes into account the joint power consumption of the power amplifiers, antenna unit, and signal processing circuit unit. Subsequently, by exploiting the law of large numbers and dual decomposition, an efficient suboptimal iterative resource allocation algorithm is proposed for maximization of the system capacity (bit/s). In particular, closed-form power allocation and antenna allocation policies are derived in each iteration. Simulation results illustrate that the proposed iterative resource allocation algorithm achieves a close-to-optimal performance in a small number of iterations and unveil a trade-off between system capacity and the number of activated antennas: Activating all antennas may not be a good solution for system capacity maximization when a system with a per antenna power cost is considered. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Spectral efficient optimization in OFDM systems with wireless information and power transfer - Ng, Derrick Wing Kwan; Schober, Robert (European Signal Processing Conference, 2013)
This paper considers an orthogonal frequency division multiplexing (OFDM) point-to-point wireless communication system with simultaneous wireless information and power transfer. We study a receiver which is able to harvest energy from the desired signal, noise, and interference. In particular, we consider a power splitting receiver which dynamically splits the received power into two power streams for information decoding and energy harvesting. We design power allocation algorithms maximizing the spectral efficiency (bit/s/Hz) of data transmission. In particular, the algorithm design is formulated as a nonconvex optimization problem which takes into account the constraint on the minimum power delivered to the receiver. The problem is solved by using convex optimization techniques and a one-dimensional search. The optimal power allocation algorithm serves as a system benchmark scheme due to its high complexity. To strike a balance between system performance and computational complexity, we also propose two suboptimal algorithms which require a low computational complexity. Simulation results demonstrate the excellent performance of the proposed suboptimal algorithms. © 2013 EURASIP.
CRIS-Team Scopus Importer:2020-02-03

Sphere Constrained Block RSSE with Per-Survivor Intra-Block Processing for CCK Transmission - Jonietz, Christof; Gerstacker, Wolfgang; Schober, Robert (2008 IEEE 10th International Symposium on Spread Spectrum Techniques and Applications, 2008)
In the wireless local area network (WLAN) standard IEEE 802.11b, complementary code keying (CCK) modulation has been adopted for the high data rate transmission mode, which can be considered as a special type of spread spectrum modulation with data-dependent spreading. In this paper, complexity reduction for block reduced-state sequence estimation (bRSSE), tailored for CCK transmission over frequency-selective channels, is considered. A trellis diagram for the chip phases of the codewords fully describes the CCK code properties. Subset trellises are derived from the full CCK trellis diagram based on set partitioning of the multidimensional CCK code set. The CCK subset trellises connect consecutive bRSSE states in order to form a compound trellis. The Viterbi algorithm (VA) with per-survivor processing is applied to the compound trellis to take the inter-chip interference into account. Inter-codeword interference is also accounted for by state-dependent decision feedback. The resulting scheme is denoted as bRSSE-pS and has a significantly lower complexity than bRSSE with brute-force search. By introducing a sphere constraint on the overall decoding trellis (SC-bRSSE-pS), the complexity of bRSSE-pS can be further reduced. Omitting states in the CCK subset trellises that violate the sphere constraint, edges that emanate from such states can be pruned, and the average number of metric calculations per CCK trellis segment can be reduced. Simulation results show that the performance of bRSSE-pS and SC-bRSSE-pS, respectively, is essentially equivalent to that of bRSSE with brute-force search, while complexity is significantly reduce

Spherical Diffusion Model with Semi-Permeable Boundary: A Transfer Function Approach - Schäfer, Maximilian; Wicke, Wayan; Haselmayr, Werner; Rabenstein, Rudolf; Schober, Robert (IEEE International Conference on Communications (ICC), 2020)
The derivation of suitable analytical models is an important step for the design and analysis of molecular commu- nication systems. However, many existing models have limited applicability in practical scenarios due to various simplifications (e.g., assumption of an unbounded environment). In this paper, we develop a realistic model for particle diffusion in a bounded sphere and particle transport through a semi-permeable bound- ary. This model can be used for various applications, such as modeling of inter-/intra-cell communication or the release process of drug carriers. The proposed analytical model is based on a transfer function approach, which allows for fast numerical evaluation and provides insights into the impact of the relevant molecular communication system parameters. The proposed solution of the bounded spherical diffusion problem is formulated in terms of a state-space description and the semi-permeable boundary is accounted for by a feedback loop. Particle-based simulations verify the proposed modeling approach.

STAR-RISs: A Correlated T&R Phase-Shift Model and Practical Phase-Shift Configuration Strategies - Xu, Jiaqi; Liu, Yuanwei; Mu, Xidong; Schober, Robert; Poor, H. Vincent (IEEE Journal of Selected Topics in Signal Processing, 2022)
A correlated transmission and reflection (T&R) phase-shift model is proposed for passive lossless simultaneously transmitting and reflecting reconfigurable intelligent surfaces (STAR-RISs). A STAR-RIS-aided two-user downlink communication system is investigated for both orthogonal multiple access (OMA) and non-orthogonal multiple access (NOMA). To evaluate the impact of the correlated T&R phase-shift model on the communication performance, three phase-shift configuration strategies are developed, namely the primary-secondary phase-shift configuration (PS-PSC), the diversity preserving phase-shift configuration (DP-PSC), and the T/R-group phase-shift configuration (TR-PSC) strategies. Furthermore, we derive the outage probabilities for the three proposed phase-shift configuration strategies as well as for those for the random phase-shift configuration and the independent phase-shift model, which constitute performance lower and upper bounds, respectively. Then, the diversity order of each strategy is investigated based on the obtained analytical results. It is shown that the proposed DP-PSC strategy achieves full diversity order simultaneously for users located on both sides of the STAR-RIS. Moreover, power scaling laws are derived for the three proposed strategies and for the random phase-shift configuration. Numerical simulations reveal a performance gain if the users on both sides of the STAR-RIS are served by NOMA instead of OMA. Moreover, it is shown that the proposed DP-PSC strategy yields the same diversity order as achieved by STAR-RISs under the independent phase-shift model and a comparable power scaling law with only 4 dB reduction in received power.
CRIS-Team Scopus Importer:2022-07-01
Keywords: Analytical models; Electromagnetics; Hardware; hardware modelling; NOMA; Numerical models; performance analysis; Probability; reconfigurable intelligent surfaces (RISs); Reflection; simultaneous transmission and reflection; Wireless networks

STAR: SIMULTANEOUS TRANSMISSION AND REFLECTION FOR 360 degrees COVERAGE BY INTELLIGENT SURFACES - Liu, Yuanwei; Mu, Xidong; Xu, Jiaqi; Schober, Robert; Hao, Yang; Poor, H. Vincent; Hanzo, Lajos (IEEE Wireless Communications, 2021)
A novel simultaneous transmitting and reflecting (STAR) system design relying on reconfigurable intelligent surfaces (RISs) is conceived. First, an existing prototype is reviewed, and the potential benefits of STAR-RISs are discussed. Then the key differences between conventional reflecting-only RISs and STAR-RISs are identified from the perspectives of hardware design, physical principles, and communication system design. Furthermore, the basic signal model of STAR-RISs is introduced, and three practical protocols are proposed for their operation, namely energy splitting, mode switching, and time switching. Based on the proposed protocols, a range of promising application scenarios are put forward for integrating STAR-RISs into next-generation wireless networks. By considering the downlink of a typical RIS-aided multiple-input single-output system, numerical case studies are provided for revealing the superiority of STAR-RISs over other baselines when employing the proposed protocols. Finally, several open research problems are discussed.
CRIS-Team WoS Importer:2022-02-04

Statistical Analysis of Time-Variant Channels in Diffusive Mobile Molecular Communications - Ahmadzadeh, Arman; Jamali Kooshkghazi, Vahid; Schober, Robert (GLOBECOM 2017 - 2017 IEEE Global Communications Conference, 2017)
In this paper, we consider a diffusive mobile molecular communication (MC) system consisting of a pair of mobile transmitter and receiver nano- machines suspended in a fluid medium, where we model the mobility of the nano-machines by Brownian motion. The transmitter and receiver nano-machines exchange information via diffusive signaling molecules. Due to the random movements of the transmitter and receiver nano-machines, the statistics of the channel impulse response (CIR) change over time. We introduce a statistical framework for characterization of the impulse response of time-variant MC channels. In particular, we derive closed-form analytical expressions for the mean and the autocorrelation function of the impulse response of the channel. Given the autocorrelation function, we define the coherence time of the time-variant MC channel as a metric that characterizes the variations of the impulse response. Furthermore, we derive an analytical expression for evaluation of the expected error probability of a simple detector for the considered system. In order to investigate the impact of CIR decorrelation over time, we compare the performances of a detector with perfect channel state information (CSI) knowledge and a detector with outdated CSI knowledge. The accuracy of the proposed analytical expression is verified via particle-based simulation of the Brownian motion.<br
Keywords: Receivers; Transmitters; Mobile communication; Nanobioscience; Stochastic processes; Correlation; Detectors

Statistical Modeling of Airborne Virus Transmission Through Imperfectly Fitted Face Masks - Lotter, Sebastian; Brand, Lukas; Schäfer, Maximilian; Schober, Robert (NANOCOM '21, Eight Annual ACM International Conference on Nanoscale Computing and Communication, 2021)
The rapid emergence and the disastrous impact of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic on public health, societies, and economies around the world has created an urgent need for understanding the pathways critical for virus transmission and counteracting the spread of SARS-CoV-2 efficiently. Airborne virus transmission by asymptomatic SARS-CoV-2-infected individuals is considered to be a major contributor to the fast spread of SARS-CoV-2 and social distancing and wearing of face masks in public have been implemented as countermeasures in many countries. Concerted research efforts in diverse scientific fields have meanwhile advanced the understanding of the physical principles of the manifold processes involved in airborne transmission of SARS-CoV-2. As part of these efforts, the physics and dynamics of aerosol filtration by various types of face masks have been studied. However, a comprehensive risk assessment framework for the airborne transmission of SARS-CoV-2 incorporating realistic assumptions on the filtration of infectious aerosols (IAs) by face masks is not available yet. In particular, in most end-to-end models for airborne virus transmission, it is neglected that the stochastic spread of IAs through imperfectly fitted face masks depends on the dynamics of the breathing of the wearer. In this paper, we consider airborne virus transmission from an infected but asymptomatic individual to a healthy individual, both wearing imperfectly fitted face masks, in an indoor environment. By framing the end-to-end virus transmission as a Molecular Communications (MC) system, we obtain a statistical description of the number of IAs inhaled by the healthy person subject to the respective configurations of the face masks of both persons. We demonstrate that the exhalation and inhalation air flow dynamics have a significant impact on the stochastic filtering of IAs by the imperfectly fitted face masks. Furthermore, we are able to show that the fit of the face mask of the infected person can highly impact the infection probability if the infectious dose for virus transmission to the healthy person is in a critical range. We conclude that the proposed MC model may contribute a valuable assessment tool to fight the spread of SARS-CoV-2 as it naturally encompasses the randomness of the transmission process and thus enables comprehensive risk analysis beyond statistical averages.

Statistical Modeling of FSO Fronthaul Channel for Drone-Based Networks - Najafi Kalyani, Marzieh; Ajam, Hedieh; Jamali Kooshkghazi, Vahid; Diamantoulakis, Panagiotis D.; Karagiannidis, George K.; Schober, Robert (2018 IEEE International Conference on Communications (ICC), 2018)
We consider a drone-based communication network, where several drones hover above an area and serve as mobile remote radio heads for a large number of mobile users. We assume that the drones employ free space optical (FSO) links for fronthauling of the users' data to a central unit. The main focus of this paper is to quantify the geometric loss of the FSO channel arising from random fluctuation of the position and orientation of the drones. In particular, we derive upper and lower bounds, corresponding approximate expressions, and a closed-form statistical model for the geometric loss. Simulation results validate our derivations and quantify the FSO channel quality as a function of the drone's instability, i.e., the variation of its position and orientation.<br
Keywords: Laser beams; Drones; Optical beams; Optical losses; Laser modes; Buildings; Atmospheric modeling

Statistical Modeling of the FSO Fronthaul Channel for UAV-Based Communications - Najafi, Marzieh; Ajam, Hedieh; Jamali, Vahid; DIamantoulakis, Panagiotis D.; Karagiannidis, George K.; Schober, Robert (IEEE Transactions on Communications, 2020)
In this paper, we investigate the statistics of the free space optics (FSO) communication channel between a hovering unmanned aerial vehicle (UAV) and a central unit. Two unique characteristics make UAV-based FSO systems significantly different from conventional FSO systems with static transceivers. First, for UAV-based FSO systems, the incident laser beam is not always orthogonal to the receiver lens plane. Second, both position and orientation of the UAV fluctuate over time due to dynamic wind load, inherent random air fluctuations in the atmosphere around the UAV, and internal vibrations of the UAV. On the contrary, for conventional FSO systems, the laser beam is always perpendicular to the receiver lens plane and the relative movement of the transceivers is limited. In this paper, we develop a novel channel model for UAV-based FSO systems by quantifying the corresponding geometric and misalignment losses (GML), while taking into account the non-orthogonality of the laser beam and the random fluctuations of the position and orientation of the UAV. In particular, for diverse weather conditions, we propose different fluctuation models for the position and orientation of the UAV and derive corresponding statistical models for the GML. We further analyze the performance of a UAV-based FSO link in terms of outage probability and ergodic rate and simplify the resulting analytical expressions for the high signal-to-noise ratio (SNR) regime. Finally, simulations validate the accuracy of the presented analysis and provide important insights for system design. For instance, we show that for a given variance of the fluctuations, the beam width should be properly adjusted to minimize the outage probability.
CRIS-Team Scopus Importer:2020-07-03
Keywords: channel modeling; free space optics (FSO) backhauling; geometric loss; pointing error; random UAV fluctuations; Unmanned aerial vehicle (UAV) communications

Statistical power allocation for downlink two-user power-domain MIMO-NOMA with excess degrees of freedom - Krishnamoorthy, Aravindh; Schober, Robert (WSA 2020 - 24th International ITG Workshop on Smart Antennas, 2020)
In this paper, we investigate statistical power allocation (SPA) for downlink two-user power-domain multiple-input multiple-output (MIMO) non-orthogonal multiple access (NOMA) to enhance the ergodic rate performance. We utilize a modified generalized singular value decomposition (M-GSVD) based precoding scheme which simultaneously diagonalizes the MIMO-NOMA channels of the users into multiple single-input single-output (SISO) NOMA channels, thereby reducing the decoding complexity. The M-GSVD precoding scheme is also able to exploit excess degrees of freedom at the base station to improve MIMO-NOMA performance. Based on finite-size random matrix theory, we derive novel expressions for the ergodic achievable rate of MIMO-NOMA with M-GSVD precoding and non-equal power allocation, which are then used for SPA and for obtaining the ergodic achievable rate region. The derived expressions are validated with Monte-Carlo simulations. Our results show that the proposed scheme outperforms M-GSVD precoding with equal power allocation and orthogonal multiple access, thereby demonstrating the benefits of SPA.
CRIS-Team Scopus Importer:2020-12-04

Stochastic Channel Modeling for Diffusive Mobile Molecular Communication Systems - Ahmadzadeh, Arman; Jamali Kooshkghazi, Vahid; Schober, Robert (IEEE Transactions on Communications, 2018)
In this paper, we consider mobile molecular communication (MC) systems which are expected to find application in several fields including targeted drug delivery and health monitoring. We develop a mathematical framework for modeling the time-variant stochastic channels of diffusive mobile MC systems. In particular, we consider a diffusive mobile MC system consisting of a pair of transmitter and receiver nano-machines suspended in a fluid medium with a uniform bulk flow, where we assume that either the transmitter or the receiver or both are mobile, and we model the mobility by Brownian motion. The transmitter and receiver nano-machines exchange information via diffusive signaling molecules. Due to the random movements of the transmitter and receiver nano-machines, the statistics of the channel impulse response (CIR) change over time. We derive closed-form expressions for the mean, the autocorrelation function (ACF), the cumulative distribution function (CDF), and the probability density function (PDF) of the time-variant CIR. Exploiting the ACF, we define the coherence time of the time-variant MC channel as a metric for characterization of the variations of the CIR. The derived CDF is employed for calculation of the outage probability of the system. We also show that under certain conditions, the PDF of the CIR can be accurately approximated by a Log-normal distribution. Based on this approximation, we derive a simple model for outdated channel state information (CSI). Moreover, we derive an analytical expression for the evaluation of the expected error probability of a simple detector for the considered MC system. In order to investigate the impact of CIR decorrelation over time, we compare the performances of a detector with perfect CSI knowledge and a detector with outdated CSI knowledge. The accuracy of the proposed analytical expressions is verified via particle-based simulation of the Brownian motion.<br
Keywords: Receivers; Transmitters; Stochastic processes; Nanobioscience; Probability density function; Mathematical model; Closed-form solutions

Stochastic Chemical Reaction Networks for MAP Detection in Cellular Receivers - Heinlein, Bastian; Brand, Lukas; Egan, Malcolm; Schäfer, Maximilian; Schober, Robert; Lotter, Sebastian (NanoCom 2023 - Proceedings of the 10th ACM International Conference on Nanoscale Computing and Communication, 2023)
In order to fully exploit the potential of molecular communication (MC) for intra-body communication, practically implementable cellular receivers are an important long-term goal. A variety of receiver architectures based on chemical reaction networks (CRNs) and gene-regulatory networks (GRNs) has been introduced in the literature, because cells use these concepts to perform computations in nature. However, practical feasibility is still limited by stochastic fluctuations of chemical reactions and long computation times in GRNs. Therefore, in this paper, we propose two receiver designs based on stochastic CRNs, i.e., CRNs that perform computations by exploiting the intrinsic fluctuations of chemical reactions with very low molecule counts. The first CRN builds on a recent result from chemistry that showed how Boltzmann machines (BMs), a commonly used machine learning model, can be implemented with CRNs. We show that BMs with optimal parameter values and their CRN implementations can act as maximum-a-posteriori (MAP) detectors. Furthermore, we show that BMs can be efficiently trained from simulation data to achieve close-to-MAP performance. While this approach yields a fixed CRN once deployed, our second approach based on a manually designed CRN can be trained with pilot symbols even within the cell and thus adapt to changing channel conditions. We extend the literature by showing that practical robust detectors can achieve close-to-MAP performance even without explicit channel knowledge.
CRIS-Team Scopus Importer:2023-10-27
Keywords: Boltzmann machine; chemical reaction network; machine learning; maximum-a-posteriori detection; Molecular communication

Successive Null-Space Precoder Design for Downlink MU-MIMO with Rate Splitting and Single-Stage SIC - Krishnamoorthy, Aravindh; Schober, Robert (2021 IEEE International Conference on Communications Workshops, ICC Workshops 2021 - Proceedings, 2021)
In this paper, we consider the precoder design for an under-loaded or critically loaded downlink multi-user multiple-input multiple-output (MU-MIMO) communication system. We propose novel precoding and decoding schemes which enhance system performance based on rate splitting at the transmitter and single-stage successive interference cancellation at the receivers. The proposed successive null-space (SNS) precoding scheme utilizes linear combinations of the null-space basis vectors of the successively augmented MIMO channel matrices of the users as precoding vectors to adjust the inter-user-interference experienced by the receivers. We formulate a non-convex weighted sum rate (WSR) optimization problem, and solve it via successive convex approximation to obtain a suboptimal solution for the precoding vectors and the associated power allocation. Our simulation results reveal that the proposed SNS precoders outperform block diagonalization based linear and rate splitting designs, and in many cases, have a relatively small gap to the maximum sum rate achieved by dirty paper coding.
CRIS-Team Scopus Importer:2021-08-27

SUDAS: mmWave relaying for 5G outdoor-to-indoor communications - Breiling, Marco; Ng, Derrick Wing Kwan; Rohde, Christian; Burkhardt, Frank; Schober, Robert (Advanced Relay Technologies in Next Generation Wireless Communications, 2016)
In this chapter, we have proposed a novel SUDAS with the objective of achieving the 10 Gbit/s data rate goal set by 5G for indoor UEs. The proposed SUDAS exploits the benefits of the licensed and unlicensed frequency bands simultaneously. In particular, it translates the spatial multiplexing in the licensed bands into frequency multiplexing in the unlicensed bands for boosting the end-to-end data rate via VMIMO. It is expected that the proposed SUDAS can further enhance the system performance when advanced resource allocation technique is employed. Besides, we have also discussed some potential application scenarios where deployment of SUDAS appears to be beneficial. Also, we have investigated different potential realizations of SUDAS and the corresponding implementation challenges. It is expected that the proposed SUDAS is able to bridge the gap between the current technology and the high data rate requirement of the next generation communication systems.
CRIS-Team Scopus Importer:2020-01-31
Keywords: 5G mobile communication; 5G outdoor-to-indoor communications; Advanced resource allocation technique; Data communication; Data rate; End-to-end data rate; Frequency multiplexing; Indoor UE; MIMO communication; Mmwave relaying; Next generation communication systems; Next generation networks; Resource allocation; Space division multiplexing; Spatial multiplexing; SUDAS; VMIMO

Superposition coding for cooperative BICM-OFDM systems - Islam, Toufiqul; Schober, Robert; Mallik, Ranjan K.; Bhargava, Vijay K. (Conference Record - Asilomar Conference on Signals, Systems and Computers, 2011)
In this paper, we study a cooperative diversity scheme for wireless systems based on symbol level superposition coding and the combination of bit-interleaved coded modulation (BICM) and orthogonal frequency division multiplexing (OFDM). The considered system comprises multiple sources, a single relay, and one common destination. The relay decodes the signal received from all sources over orthogonal channels, linearly combines the decoded symbols, and forwards the combined symbols to the destination. A simple cooperative maximum-ratio combining scheme is used at the destination which can successfully exploit the full spatial and frequency diversity offered by the channel for arbitrary numbers of sources and arbitrary linear modulation schemes. To gain insight for system design, we derive a closed-form upper bound for the asymptotic worst-case pairwise error probability and the diversity gain of the considered superposition-coded cooperative diversity (SCCD) scheme for BICM-OFDM systems. The diversity gain is a function of the free distance of the code and the frequency diversity of the involved links, but is independent of number of sources. Simulation results corroborate the derived analytical results and confirm that SCCD schemes enjoy better coding and diversity gains compared to Galois field network coding for the considered system and may be more attractive for application in wireless cooperative networks. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Sweet Streams are Made of This: The System Engineer’s View on Energy Efficiency in Video Communications (Preprint) - Herglotz, Christian; Kränzler, Matthias; Schober, Robert; Kaup, André (Ieee Circuits and Systems Magazine, 2023)

Switchable Signaling Molecules for Media Modulation: Fundamentals, Applications, and Research Directions - Brand, Lukas; Scherer, Maike; Lotter, Sebastian; tom Dieck, Teena; Schaufer, Maximilian; Burkovski, Andreas; Sticht, Heinrich; Castiglione, Kathrin; Schober, Robert (IEEE Communications Magazine, 2023)
Although visionary applications of molecular communication (MC), such as long-term continuous health monitoring by cooperative in-body nanomachines, have been proposed, MC is still in its infancy when it comes to practical implementation. In particular, long-term experiments and applications face issues such as depletion of signaling molecules (SMs) at the transmitter (TX) and inter-symbol interference (ISI) at the receiver (RX). To overcome these practical challenges, a new class of SMs with switchable states seems to be promising for future MC applications. In this work, we provide an overview of existing switchable SMs, and classify them according to their properties. Furthermore, we highlight how switchable SMs can be utilized as information carriers for media modulation. In addition, we present theoretical and experimental results for an end-toend MC system employing the green fluorescent protein variant "Dreiklang" (GFPD) as switchable SM. Our experimental results show, for the first time, successful information transmission in a closed-loop pipe system using media modulation. Finally, we discuss media modulation specific challenges and opportunities.
Created from Fastlane, Scopus look-up
Keywords: Information processing; Media; Modulation; Monitoring; Optical switches; Optical transmitters; Proteins

Switching rate in selective cooperative relaying - Michalopoulos, Diomidis S.; Lioumpas, Athanasios S.; Karagiannidis, George K.; Schober, Robert (IEEE Wireless Communications and Networking Conference, WCNC, 2010)
In selective cooperative relaying only a single relay out of the set of available relays is activated at a time, hence the available power and bandwidth resources are efficiently utilized. However, implementing selective cooperative relaying in time-varying channels may cause frequent relay switchings that deteriorate the overall performance. In this paper, we study the rate at which a relay switching occurs in selective cooperative relaying applications with two available relays, operating over time-varying fading channels. In particular, we derive closed-form expressions for the relay switching rate (measured in Hz) of opportunistic relaying (OR) and distributed switch and stay combining (DSSC). Numerical results manifest that DSSC yields a considerably lower relay switching rate than OR. ©2010 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Symbol-by-Symbol and Trellis-Based Equalization with Widely Linear Processing for Space-Time Block-Coded Transmission over Frequency-Selective Fading Channels - Gerstacker, Wolfgang; Obernosterer, Frank; Schober, Robert; Lehmann, Alexander; Lampe, Alexander; Gunreben, Peter (Conference Proceedings, 2002)
In this paper, we develop receiver concepts for transmission with space-time block codes (STBC's) over frequency-selective fading channels. The focus lies on Alamouti's STBC, but the results may be generalized to related STBC's. We show that a straightforward combination of conventional equalizers and a space-time block decoder is only possible if at least as many receive antennas as transmit antennas are employed, but not for the practically interesting case of pure transmit diversity. This restriction is circumvented by our approach. Equalizers with widely linear (WL) processing are designed, utilizing the structural properties of the transmit signal of space-time block coding, which is shown to be improper (rotationally variant). These schemes are especially suited for equalization of high-level modulated signals, which are used in third-generation time-division multiple access mobile communications standards such as EDGE (Enhanced Data Rates for GSM Evolution).
UnivIS-Import:2015-04-16:Pub.2002.tech.IE.mobilk.symbol
Keywords: Frequency-selective fading channels; Block codes; Equalizers; Receiving antennas; Decoding; Transmitting antennas; Process design; Signal design; Signal processing; Mobile communication

Symbol Level Precoding in the RF Domain for Low Hardware Complexity RIS-Assisted MU-MISO Systems - Tsinos, Christos G.; Tsiftsis, Theodoros A.; Schober, Robert (ICASSP, IEEE International Conference on Acoustics, Speech and Signal Processing - Proceedings, 2023)
In this paper, a radio-frequency (RF) domain symbol level precoding technique is developed for reconfigurable intelligent surface (RIS)-assisted downlink multiuser multiple-input single-output (MU-MISO) systems. We study a system with a base station (BS) employing an analog architecture formed by a phase shifting network which serves a number of single antenna users with the help of a RIS. Such an architecture facilitates significant reductions in power consumption and hardware complexity. The objective of this paper is to jointly derive the optimal RF precoder, RIS reflection matrix and receive processing coefficients, subject to constraints on the BS analog architecture, the total transmit power, and the structure of the RIS reflection matrix. To that end, a difficult nonconvex optimization problem is formulated and solved. An efficient algorithmic solution is developed for the considered problem. Numerical results show that the derived solution offers significant energy efficiency gains when compared to non-RIS-assisted approaches.
CRIS-Team Scopus Importer:2023-12-01

Symbol Synchronization for Diffusion-Based Molecular Communications - Jamali Kooshkghazi, Vahid; Ahmadzadeh, Arman; Schober, Robert (IEEE Transactions on Nanobioscience, 2018)
Symbol synchronization refers to the estimation of the start of a symbol interval and is needed for reliable detection. In this paper, we develop several symbol synchronization schemes for molecular communication (MC) systems where we consider some practical challenges, which have not been addressed in the literature yet. In particular, we take into account that in MC systems, the transmitter may not be equipped with an internal clock and may not be able to emit molecules with a fixed release frequency. Such restrictions hold for practical nanotransmitters, e.g., modified cells, where the lengths of the symbol intervals may vary due to the inherent randomness in the availability of food and energy for molecule generation, the process for molecule production, and the release process. To address this issue, we develop two synchronization-detection frameworks which both employ two types of molecule. In the first framework, one type of molecule is used for symbol synchronization and the other one is used for data detection, whereas in the second framework, both types of molecule are used for joint symbol synchronization and data detection. For both frameworks, we first derive the optimal maximum likelihood (ML) symbol synchronization schemes as performance upper bounds. Since ML synchronization entails high complexity, for each framework, we also propose three low-complexity suboptimal schemes, namely a linear filter-based scheme, a peak observation-based scheme, and a threshold-trigger scheme, which are suitable for MC systems with limited computational capabilities. Furthermore, we study the relative complexity and the constraints associated with the proposed schemes and the impact of the insertion and deletion errors that arise due to imperfect synchronization. Our simulation results reveal the effectiveness of the proposed synchronization schemes and suggest that the end-to-end performance of MC systems significantly depends on the accuracy of the symbol synchronization.<br
Keywords: Synchronization; Computational complexity; Molecular communication

Symbol synchronization for diffusive molecular communication systems - Jamali Kooshkghazi, Vahid; Ahmadzadeh, Arman; Schober, Robert (2017 IEEE International Conference on Communications (ICC), 2017)
Symbol synchronization refers to the estimation of the start of a symbol interval and is needed for reliable detection. In this paper, we develop a symbol synchronization framework for molecular communication (MC) systems where we consider some practical challenges which have not been addressed in the literature yet. In particular, we take into account that in MC systems, the transmitter may not be equipped with an internal clock and may not be able to emit molecules with a fixed release frequency. Such restrictions hold for practical nanotransmitters, e.g. modified cells, where the lengths of the symbol intervals may vary due to the inherent randomness in the availability of food and energy for molecule generation, the process for molecule production, and the release process. To address this issue, we propose to employ two types of molecules, one for synchronization and one for data transmission. We derive the optimal maximum likelihood (ML) symbol synchronization scheme as a performance upper bound. Since ML synchronization entails high complexity, we also propose two low-complexity synchronization schemes, namely a peak observation-based scheme and a threshold-trigger scheme, which are suitable for MC systems with limited computational capabilities. Our simulation results reveal the effectiveness of the proposed synchronization schemes and suggest that the end-to-end performance of MC systems significantly depends on the accuracy of symbol synchronization.<br
Keywords: Synchronization; Receivers; Optical transmitters; Clocks; Molecular communication

Synaptic Channel Modeling for DMC: Neurotransmitter Uptake and Spillover in the Tripartite Synapse - Lotter, Sebastian; Ahmadzadeh, Arman; Schober, Robert (IEEE Transactions on Communications, 2020)
In Diffusive Molecular Communication (DMC), information is transmitted by diffusing molecules. Synaptic signaling, as a natural implementation of this paradigm, encompasses functional components that, once understood, can facilitate the development of synthetic DMC systems. To unleash this potential, however, a thorough understanding of the synaptic communication channel based on biophysical principles is needed. Since synaptic transmission critically depends also on non-neural cells, such understanding requires the consideration of the so-called tripartite synapse. In this paper, we develop a comprehensive channel model of the tripartite synapse encompassing a three-dimensional, finite-size spatial model of the synaptic cleft, molecule uptake at the presynaptic neuron and at glial cells, reversible binding to individual receptors at the postsynaptic neuron, and spillover to the extrasynaptic space. Based on this model, we derive analytical time domain expressions for the channel impulse response (CIR) of the synaptic DMC system and for the number of molecules taken up at the presynaptic neuron and at glial cells, respectively. These expressions provide insight into the impact of macroscopic physical channel parameters on the decay rate of the CIR and the reuptake rate, and reveal fundamental limits for synaptic signal transmission induced by chemical reaction kinetics and the channel geometry. Adapted to realistic parameters, our model produces plausible results when compared to previous experimental and simulation studies and we provide results from particle-based computer simulations to further validate the analytical model. The proposed comprehensive channel model admits a wide range of synaptic configurations making it suitable for the investigation of many practically relevant questions, such as the impact of glial cell uptake and spillover on signal transmission in the tripartite synapse.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Analytical models; Glial cells; Mathematical model; Monte Carlo methods; Neurons; Solid modeling; Synapses

Tackling the load uncertainty challenges for energy consumption scheduling in smart grid - Samadi, Pedram; Mohsenian-Rad, Hamed; Wong, Vincent W. S.; Schober, Robert (IEEE Transactions on Smart Grid, 2013)
In this paper, we propose a novel optimization-based real-time residential load management algorithm that takes into account load uncertainty in order to minimize the energy payment for each user. Unlike most existing demand side management algorithms that assume perfect knowledge of users' energy needs, our design only requires knowing some statistical estimates of the future load demand. Moreover, we consider real-time pricing combined with inclining block rate tariffs. In our problem formulation, we take into account different types of constraints on the operation of different appliances such as must-run appliances, controllable appliances that are interruptible, and controllable appliances that are not interruptible. Our design is multi-stage. As the demand information of the appliances is gradually revealed over time, the operation schedule of controllable appliances is updated accordingly. Simulation results confirm that the proposed energy consumption scheduling algorithm can benefit both users, by reducing their energy expenses, and utility companies, by improving the peak-to-average ratio of the aggregate load demand. © 2010-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: cost minimization; Demand side management; energy consumption control; load uncertainties; smart power grid

Tackling the photovoltaic integration challenge in the distribution network with deferrable load - Yao, Enxin; Samadi, Pedram; Wong, Vincent W.S.; Schober, Robert (2013 IEEE International Conference on Smart Grid Communications, SmartGridComm 2013, 2013)
In recent years, there is an increasing deployment of photovoltaic (PV) units and energy storage systems (ESSs) in households. When the energy generated by PV units is greater than the aggregate load of households and the capacity of ESS, there will be a reverse energy flow from households to the substation. When the reverse energy flow exceeds a certain threshold, it will cause a voltage rise problem, which is a challenge for PV units to be effectively integrated with the distribution network. In this paper, we propose an energy consumption scheduling algorithm, which shifts the deferrable load (e.g., washing machines, dryers) from peak hours (e.g., 7 pm - 10 pm) to high solar radiation hours (e.g., 10 am - 2 pm) in order to jointly shave the peak load and reduce the reverse energy flow. We formulate the energy consumption scheduling problem as a stochastic optimization problem to capture the uncertainty of the amount of PV output power. The objective of our algorithm is to minimize the electricity bill for the household users which have PV units and ESS installed. We use inclining block rate (IBR) pricing and time of use (TOU) pricing to encourage users to shift their load. Numerical results show that our proposed algorithm can avoid the voltage rise problem and reduce the peak-to-average ratio (PAR) in the aggregate load. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

The diversity potential of relay selection with practical channel estimation - Michalopoulos, Diomidis S.; Chatzidiamantis, Nestor D.; Schober, Robert; Karagiannidis, George K. (IEEE Transactions on Wireless Communications, 2013)
We investigate the diversity order of decode-and-forward relay selection in Nakagami-m fading, in cases where practical channel estimation techniques are applied. In this respect, we introduce a unified model for the imperfect channel estimates, where the effects of noise, time-varying channels, and feedback delays are jointly considered. Based on this model, the correlation between the actual and the estimated channel values, ρ, is expressed as a function of the signal-to-noise ratio (SNR), yielding closed-form expressions for the overall outage probability as a function of ρ. The resulting diversity order and power gain reveal a high dependence of the performance of relay selection on the high SNR behavior of ρ, thus shedding light onto the effect of channel estimation on the overall performance. It is shown that when the channel estimates are not frequently updated in applications involving time-varying channels, or when the amount of power allocated for channel estimation is not sufficiently high, the diversity potential of relay selection is severely degraded. In short, the main contribution of this paper lies in answering the following question: How fast should ρ tend to one, as the SNR tends to infinity, so that relay selection does not experience any diversity loss? © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: imperfect channel estimation; Nakagami-m fading model; Relay selection

The Era of Wireless Information and Power Transfer - Ng, Derrick Wing Kwan; Duong, Trung Q.; Zhong, Caijun; Schober, Robert (Wireless Information and Power Transfer: Theory and Practice, 2019)
Wireless power transfer (WPT) offers a viable solution for facilitating efficient and sustainable communication networks serving energy‐limited communication devices. WPT technology enables simultaneous wireless information and power transfer (WIPT). The existing WPT technologies can be categorized into three classes: inductive coupling, magnetic resonant coupling, and RF‐based WPT. RF‐based energy harvesting technology enables the possibility of simultaneous WIPT (SWIPT), wireless‐powered communication (WPC), and wireless‐powered backscatter communication (WPBC).This introduction presents an overview of the key concepts discussed in the subsequent chapters of this book. The book addresses the challenges incurred by the nature of WPT and provides a comprehensive reference for various solutions for realizing efficient WIPT in practice. It also provides some background information on WPT and discusses exciting research directions. The book helps to study the fundamental problems in WIPT networks, including communication security in WIPT systems, energy transfer efficiency, and interference management in WIPT systems.<br
Keywords: Wireless communication; Wireless sensor networks; Energy harvesting; Communication Networks; Receivers; Radio frequency; RF signals

The First Cell Phone in Molecular Communications: A Pilot Model of a Biological Transmitter - Grebenstein, Laura; Kirchner, Jens; Stavracakis Peixoto, Renata; Fischer, Georg; Weigel, Robert; Schober, Robert; Burkovski, Andreas (3rd Workshop on Molecular Comunications, 2018)
In the past years, Molecular Communications were studied mainly from a communication engineering and theoretical point of view. To design nano- to micro-sized signaling networks, reliable communication-theoretical models and experimental testbeds are still missing. Inspired by microbial cells we established an organic, molecular signal converter as a modulator for MC signals. The transmitter is a bacterial cell expressing the light-driven proton pump gloeorhodopsin. In recent test runs, we were able to send short messages encoded in a light signal and converted to pH variation with a rate of 2 bits/min with the help of living bacteria.<br

The impact of relay selection on the tradeoff between information transmission and wireless energy transfer - Michalopoulos, Diomidis; Suraweera, Himal A.; Schober, Robert (2014 IEEE Global Communications Conference, 2014)
In certain applications, relay terminals can be employed to simultaneously deliver information and energy to a designated receiver and a radio frequency (RF) energy harvester, respectively. In such scenarios, the relay that is preferable for information transmission does not necessarily coincide with the relay with the strongest channel to the energy harvester, since the corresponding channels fade independently. Relay selection thus entails a tradeoff between the efficiency of the information transfer to the receiver and the amount of energy transferred to the energy harvester. The study of this tradeoff is the subject on which this work mainly focuses. We propose a relay selection policy that optimizes the quality of information transmission for a given energy transfer constraint. Additionally, we propose two suboptimal relay selection methods that apply to scenarios with limited availability of channel state information and facilitate closed-form analytical results. We conduct a performance analysis that sheds some light on the tradeoff between ergodic capacity and wireless energy transfer, and we prove that the optimal relay selection policy optimizes also other performance metrics for a given energy transfer, such as the outage probability and the error probability.<br
Keywords: Relays; Energy exchange; Information processing; Wireless communication; Signal to noise ratio; Radio frequency; Pareto optimization

The Internet of Bio-Nano Things in Blood Vessels: System Design and Prototypes - Lee, Changmin; Koo, Bon Hong; Chae, Chan Byoung; Schober, Robert (Journal of Communications and Networks, 2023)
In this paper, we investigate the Internet of bionano things (IoBNT) which pertains to networks formed by molecular communications. By providing a means of communication through the ubiquitously connected blood vessels (arteries, veins, and capillaries), molecular communication-based IoBNT enables a host of new eHealth applications. For example, an organ monitoring sensor can transfer internal body signals through the IoBNT to health-monitoring applications. We empirically show that blood vessel channels introduce a new set of challenges in the design of molecular communication systems in comparison to free-space channels. Then, we propose cylindrical duct channel models and discuss the corresponding system designs conforming to the channel characteristics. Furthermore, based on prototype implementations, we confirm that molecular communication techniques can be utilized for composing the IoBNT. We believe that the promising results presented in this work, together with the rich research challenges that lie ahead, are strong indicators that IoBNT with molecular communications can drive novel applications for emerging eHealth systems.
CRIS-Team Scopus Importer:2023-06-30
Keywords: health monitoring; Internet of bionano things (IoBNT); molecular communications; prototypes; Terms-Blood vessel

The Zeros of Random Polynomials: Further Results and Applications - Schober, Robert; Gerstacker, Wolfgang (IEEE Transactions on Communications, 2002)
In this letter, we consider the density of the zeros of random polynomials with nonzero mean correlated Gaussian coefficients. We show that for most communication problems the original result by Hammersley can be expressed in a simpler form. In order to illustrate the usefulness of the presented theory, two applications are considered. First, the zeros of frequency-selective Ricean fading channels are investigated. Second, the zeros of the transfer function corresponding to channel impulse response estimates obtained by a least-squares approach are calculated. For both applications implications for equalizer design are discussed.
UnivIS-Import:2015-03-09:Pub.2002.tech.IE.mobilk.thezer
Keywords: Channel estimation; Equalization; Random polynomials; Wireless channels

Three-Dimensional Placement and Transmit Power Design for UAV Covert Communications - Zhou, Xiaobo; Yan, Shihao; Ng, Derrick Wing Kwan; Schober, Robert (IEEE Transactions on Vehicular Technology, 2021)
This work tackles the joint optimization of a unmanned aerial vehicle's (UAV's) three-dimensional (3D) placement and transmit power for covert communications with the objective to maximize the communication covertness subject to a constraint on communication quality. We analytically prove that the optimal horizontal location of the UAV must be on the straight line connecting the legitimate receiver and the warden, while its optimal height is the minimum allowable flying altitude. Subsequently, we derive closed-form expressions to characterize the UAV's optimal 3D location and its optimal transmit power, taking into account the impact of finite blocklength coding. Our numerical results show that the developed optimal design can achieve a better covertness performance compared with an optimal two-dimensional (2D) UAV deployment, especially when the warden is close to the receiver. Besides, we show that, for a given requirement on the communication quality, communication covertness does not always improve as the number of channel uses increases.
CRIS-Team Scopus Importer:2021-11-12
Keywords: 3D UAV deployment; Covert communications; Error probability; finite blocklength; Receivers; Security; Signal to noise ratio; Three-dimensional displays; Throughput; transmit power design; Unmanned aerial vehicles

Throughput and diversity gain of buffer-aided relaying - Zlatanov, Nikola; Schober, Robert; Popovski, Petar (GLOBECOM - IEEE Global Telecommunications Conference, 2011)
In this paper, we consider a simple network consisting of a source, a half-duplex decode-and- forward relay, and a destination. In contrast to most of the existing literature, we assume that the relay is equipped with a buffer and show that this can lead to substantial performance gains. We propose a simple protocol which chooses either the source-relay or the relay-destination link for transmission depending on the instantaneous channel state information. For this simple protocol, we derive the throughput for adaptive rate transmission and the outage probability for fixed rate transmission. Our results show that, unlike conventional relaying, buffer-aided relaying yields a diversity gain of two. In addition, throughput gains of up to 100 % compared to conventional relaying are possible. © 2011 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Throughput-Efficient Scheduling and Interference Alignment for MIMO Wireless Systems - Ronasi, Keivan; Niu, Binglai; Wong, Vincent W.S.; Gopalakrishnan, Sathish; Schober, Robert (IEEE Transactions on Wireless Communications, 2014)
Multiple-input multiple-output (MIMO) wireless communication systems can achieve higher throughput through interference alignment. For a small number of users, determining the maximum possible degrees of freedom as well as the feasibility of interference alignment in MIMO systems is well studied. However, the issues of scheduling in systems employing interference alignment and serving a large number of users have received little attention so far. In this paper, we study the problem of joint scheduling, interference alignment, and packet admission control in MIMO wireless systems with the goal of maximizing system throughput subject to stability constraints. We formulate a stochastic network optimization problem and propose a scheduling and interference alignment (SIA) algorithm. In each time slot, SIA schedules some users among many competing ones to transmit data, and determines encoding and decoding matrices for the selected users. Packet admission control is performed in each time slot. In addition, we propose a heuristic semi-distributed algorithm (SDSIA), which has a lower computational complexity than the SIA algorithm. Via simulation, we evaluate the performance of SIA and SDSIA for different algorithm parameters and different numbers of users. We also compare the performance of SDSIA with other approaches which do not simultaneously exploit interference alignment and scheduling and find that the combination of these two techniques increases the achievable data rate dramatically.<br
Keywords: Interference; Receivers; Throughput; Transmitters; Scheduling; MIMO; Vectors

Throughput Optimization for Grant-Free Multiple Access with Multiagent Deep Reinforcement Learning - Huang, Rui; Wong, Vincent W.S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2021)
Grant-free multiple access (GFMA) is a promising paradigm to efficiently support uplink access of Internet of Things (IoT) devices. In this paper, we propose a deep reinforcement learning (DRL)-based pilot sequence selection scheme for GFMA systems to mitigate potential pilot sequence collisions. We formulate a pilot sequence selection problem for aggregate throughput maximization in GFMA systems with specific throughput constraints as a Markov decision process (MDP). By exploiting multiagent DRL, we train deep neural networks (DNNs) to learn near-optimal pilot sequence selection policies from the transition history of the underlying MDP without requiring information exchange between the users. While the training process takes advantage of global information, we leverage the technique of factorization to ensure that the policies learned by the DNNs can be executed in a distributed manner. Simulation results show that the proposed scheme can achieve an average aggregate throughput that is within 85% of the optimum, and is 31%, 128%, and 162% higher than that of acknowledgement-based GFMA, dynamic access class barring, and random selection GFMA, respectively. Our results also demonstrate the capability of the proposed scheme to support IoT devices with specific throughput requirements.
CRIS-Team Scopus Importer:2021-01-29
Keywords: deep reinforcement learning (DRL); Grant-free multiple access (GFMA); Internet of Things (IoT); medium access control (MAC) protocols

Throughput Optimization in Grant-Free NOMA with Deep Reinforcement Learning - Huang, Rui; Wong, Vincent W. S.; Schober, Robert (2019 IEEE GLOBAL COMMUNICATIONS CONFERENCE (GLOBECOM), 2019)
CRIS-Team WoS Importer:2020-08-14

Towards Power-Efficient Aerial Communications via Dynamic Multi-UAV Cooperation - Xiang, Lin; Lei, Lei; Chatzinotas, Symeon; Ottersten, Bjorn; Schober, Robert (IEEE Wireless Communications and Networking Conference, WCNC, 2020)
Aerial base stations (BSs) attached to unmanned aerial vehicles (UAVs) constitute a new paradigm for next-generation cellular communications. However, the flight range and communication capacity of aerial BSs are usually limited due to the UAVs' size, weight, and power (SWAP) constraints. To address this challenge, in this paper, we consider dynamic cooperative transmission among multiple aerial BSs for power-efficient aerial communications. Thereby, a central controller intelligently selects the aerial BSs navigating in the air for cooperation. Consequently, the large virtual array of moving antennas formed by the cooperating aerial BSs can be exploited for low-power information transmission and navigation, taking into account the channel conditions, energy availability, and user demands. Considering both the fronthauling and the data transmission links, we jointly optimize the trajectories, cooperation decisions, and transmit beamformers of the aerial BSs for minimization of the weighted sum of the power consumptions required by all BSs. Since obtaining the global optimal solution of the formulated problem is difficult, we propose a low-complexity iterative algorithm that can efficiently find a Karush-Kuhn-Tucker (KKT) solution to the problem. Simulation results show that, compared with several baseline schemes, dynamic multi-UAV cooperation can significantly reduce the communication and navigation powers of the UAVs to overcome the SWAP limitations, while requiring only a small increase of the transmit power over the fronthauling links.
CRIS-Team Scopus Importer:2020-07-10

Trajectory and Resource Optimization for UAV Synthetic Aperture Radar - Lahmeri, Mohamed Amine; Ghanem, Walid; Knill, Christina; Schober, Robert (2022 IEEE GLOBECOM Workshops, GC Wkshps 2022 - Proceedings, 2022)
In this paper, we study the trajectory and resource optimization for lightweight rotary-wing unmanned aerial vehicles (UAVs) equipped with a synthetic aperture radar (SAR) system. The UAV's mission is to perform SAR imaging of a given area of interest (AoI). In this setup, real-time communication with a base station (BS) is required to facilitate live mission planning for the drone. For this purpose, a non-convex mixed-integer non-linear program (MINLP) is formulated such that the UAV resources and three-dimensional (3D) trajectory are jointly optimized for maximization of the drone radar ground coverage. We present a low-complexity sub-optimal algorithm based on successive convex approximation (SCA) for solving the problem, and perform a finite search to optimize the total distance traversed by the UAV for maximal coverage. We show that the proposed 3D trajectory planning achieves at least 70% improvement in radar ground coverage compared to benchmark schemes employing constant powers for communication or radar imaging. We also show that positioning the BS near the AoI can significantly improve the radar coverage of the UAV.
CRIS-Team Scopus Importer:2023-03-07

Transceiver design for SC-FDE based MIMO relay systems - Wu, Peiran; Schober, Robert; Bhargava, Vijay K. (IEEE Transactions on Wireless Communications, 2013)
In this paper, we propose a joint transceiver design for single-carrier frequency-domain equalization (SC-FDE) based multiple-input multiple-output (MIMO) relay systems. To this end, we first derive the optimal minimum mean-squared error linear and decision-feedback frequency-domain equalization filters at the destination along with the corresponding error covariance matrices at the output of the equalizer. Subsequently, we formulate the source and relay precoding matrix design problem as the minimization of a family of Schur-convex and Schur-concave functions of the mean-squared errors at the output of the equalizer under separate power constraints for the source and the relay. By exploiting properties of the error covariance matrix and results from majorization theory, we derive the optimal structures of the source and relay precoding matrices, which allows us to transform the matrix optimization problem into a scalar power optimization problem. Adopting a high signal-to-noise ratio approximation for the objective function, we obtain the global optimal solution for the power allocation variables. We illustrate the excellent performance of the proposed system and compare it to that of conventional orthogonal frequency-division multiplexing MIMO relay systems based on computer simulations. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: MIMO Relay; Single-carrier frequency-domain equalization; Transceiver design

Transfer Function Models for Cylindrical MC Channels with Diffusion and Laminar Flow - Schäfer, Maximilian; Wicke, Wayan; Brand, Lukas; Rabenstein, Rudolf; Schober, Robert (IEEE Transactions on Molecular, Biological and Multi-Scale Communications, 2021)
The analysis and design of advection-diffusion based molecular communication (MC) systems in cylindrical environments is of particular interest for applications such as micro-fluidics and targeted drug delivery in blood vessels. Therefore, the accurate modeling of the corresponding MC channel is of high importance. The propagation of particles in these systems is caused by a combination of diffusion and flow with a parabolic velocity profile, i.e., laminar flow. The propagation characteristics of the particles can be categorized into three different regimes: The flow dominant regime where the influence of diffusion on the particle transport is negligible, the dispersive regime where diffusion has a much stronger impact than flow, and the mixed regime where both effects are important. For the limiting regimes, i.e., the flow dominant and dispersive regimes, well-known solutions and approximations for particle transport exist. For the mixed regime, approximations, numerical techniques, and particle based simulations are employed. However, the few analytical models that are applicable in all three regimes impose significant constraints on the possible transmitter locations and particle release profiles. In this paper, we develop a more general analytical model for the advection-diffusion problem in cylindrical environments, which is applicable in all three regimes and accounts for general particle release models. The proposed model exhibits a higher accuracy than existing models and is based on a transfer function approach, where the main challenge is the incorporation of laminar flow. The properties of the proposed model are analyzed by numerical evaluation for different scenarios including the uniform and point release of particles. We provide a comparison with particle based simulations and existing analytical models from the literature to demonstrate the validity of the proposed analytical model.<br
Keywords: Analytical models; Mathematical model; Numerical models; Dispersion; Biology; Transfer functions; Plugs

Transfer function models for particle diffusion in a horizontal cylindrical shape with a vertical force component - Schäfer, Maximilian; Wicke, Wayan; Rabenstein, Rudolf; Schober, Robert (2018)

Transmission and Reception Concepts for WLAN IEEE 802.11b - Jonietz, Christof; Gerstacker, Wolfgang; Schober, Robert (IEEE Transactions on Wireless Communications, 2006)
State-of-the-art wireless local area network (WLAN) IEEE 802.11b terminals employ complementary code keying (CCK) as modulation format. In this paper, receiver concepts tailored for CCK transmission over frequency-selective fading channels are presented in a unified and systematic framework. First, optimum maximum-likelihood (ML) detection for CCK signaling is considered. Second, for complexity reduction, minimum mean-squared error block decision-feedback equalization (MMSE-DFE) is investigated and reduced-state sequence estimation (RSSE) is considered on the basis of an Ungerböck-like set partitioning of the multidimensional CCK code word set. In order to improve the reliability of CCK transmission over fading channels, time-reversal space-time block codes (TR-STBCs) combined with receive diversity are applied. Simulation results of the considered suboptimum receivers are compared with a performance approximation for optimum detection. Our results demonstrate the excellent performance of the advocated equalization schemes and the significant gains that can be achieved with TR-STBCs and receive diversity in typical WLAN environments. © 2006 IEEE.
UnivIS-Import:2015-03-09:Pub.2006.tech.IE.mobilk.transm
Keywords: (time-reversal) space-time block codes; Complementary code keying; Decision feedback equalization; Diversity; Equalization; Reduced-state sequence estimation; WLAN IEEE 802.11b

Transmit antenna selection for security enhancement in MIMO wiretap channels - Yang, Nan; Yeoh, Phee Lep; Elkashlan, Maged; Schober, Robert; Collings, Iain B. (IEEE Transactions on Communications, 2013)
We propose and analyze transmit antenna selection (TAS) to enhance physical layer security in a wiretap channel with NA antennas at the transmitter, NB antennas at the receiver, and NE antennas at the eavesdropper. We focus on the practical scenario where the transmitter does not have any channel state information (CSI) of the eavesdropper's channel. The transmitter selects a single antenna that maximizes the instantaneous signal-to-noise ratio (SNR) at the receiver. The receiver and the eavesdropper employ either maximal-ratio combining (MRC) or selection combining (SC) to combine the received signals. For the proposed protocols, we derive new closed-form expressions for the probability of non-zero secrecy capacity. We consider Nakagami-m fading with non-identical fading parameters of the main channel, mB, and of the eavesdropper's channel, mE. Next, we derive new closed-form expressions for the exact secrecy outage probability, based on which the ε-outage secrecy capacity is characterized. Based on the exact expressions, we derive the asymptotic secrecy outage probability which accurately reveals the secrecy diversity order and the secrecy array gain. We confirm that the proposed protocols achieve identical secrecy diversity orders of NANBmB. An interesting conclusion is reached that this diversity order is independent of NE and m E. Furthermore, we prove that under the proposed protocols, the secrecy outage probability and the ε-outage secrecy capacity improve with increasing NA. © 1972-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: MIMO; Nakagami-m fading; physical layer security; transmit antenna selection

Transmit beamforming for QoE improvement in C-RAN with mobile virtual network operators - Wang, Zehua; Wing Kwan Ng, Derrick; Wong, Vincent W. S.; Schober, Robert (2016 IEEE International Conference on Communications (ICC), 2016)
Network slicing enables mobile virtual network operators (MVNOs) to lease network resources from a mobile network operator (MNO). The cloud radio access network (CRAN) architecture reduces the capital and operational expenditures for the MNO and also facilitates MVNOs running virtual machines on the cloud server. In this paper, we propose a beamforming scheme that coordinates multiple remote radio heads (RRHs) in C-RAN to improve the quality of experience (QoE) of users by maximizing their aggregate weighted quality of service (QoS). We model the QoS of each mobile user by a sigmoidal function and formulate the beamforming design as a non-convex optimization problem. By introducing an interference threshold, we first develop an iterative algorithm to determine a suboptimal solution of the original problem. Based on simulation results, we then show that a suitable interference threshold can be obtained in an off-line manner such that the suboptimal solution is a close-to-optimal solution of the original non-convex problem. Simulation results also show that the proposed scheme can significantly improve the aggregate weighted QoS of the mobile users compared to the traditional design where the weighted system sum rate is maximized.<br
Keywords: Mobile communication; Quality of service; Interference; Array signal processing; Mobile computing; Servers; Cloud computing

TTD Configurations for Near-Field Beamforming: Parallel, Serial, or Hybrid? - Wang, Zhaolin; Mu, Xidong; Liu, Yuanwei; Schober, Robert (IEEE Transactions on Communications, 2024)
True-time delayers (TTDs) are popular components for hybrid beamforming architectures to combat the spatial-wideband effect in wideband near-field communications. In this paper, a serial and a hybrid serial-parallel TTD configuration are investigated for hybrid beamforming architectures. Compared to the conventional parallel configuration, the serial configuration exhibits a cumulative time delay caused by multiple TTDs, which potentially alleviates the maximum delay requirements on the individual TTDs. However, independent control of individual TTDs becomes impossible in the serial configuration. Therefore, a hybrid TTD configuration is proposed as a compromise solution. Furthermore, a power equalization approach is proposed to address the cumulative insertion loss of the serial and hybrid TTD configurations. Moreover, the wideband near-field beamforming design for different configurations is studied to maximize the spectral efficiency in both single-user and multiple-user systems. 1) For single-user systems, a closed-form solution for the beamforming design is derived. The preferred user locations and the required maximum time delay of each TTD configuration are characterized. 2) For multi-user systems, a penalty-based iterative algorithm is developed to obtain a stationary point of the spectral efficiency maximization problem for the considered TTD configurations. In addition, a hybrid-forward-and-backward (HFB) implementation is proposed to enhance the performance of the serial configuration. Our numerical results confirm the effectiveness of the proposed designs and unveil that i) compared to the conventional parallel configuration, both the serial and hybrid configurations can significantly reduce the maximum time delays required for the individual TTDs and ii) the hybrid configuration excels in single-user systems, while the HFB serial configuration is preferred in multi-user systems.
CRIS-Team Scopus Importer:2024-03-22
Keywords: Array signal processing; Beamfocusing; Delay effects; Delays; Hybrid power systems; near-field communications; OFDM; Radio frequency; spatial wideband effect; true-time delayers; Wideband

Two-Stage Channel Estimation for RIS-Aided Multi-User mmWave Systems with Reduced Error Propagation and Pilot Overhead - Peng, Zhendong; Pan, Cunhua; Zhou, Gui; Ren, Hong; Jin, Shi; Popovski, Petar; Schober, Robert; You, Xiaohu (IEEE Transactions on Signal Processing, 2023)
In this paper, we propose a novel two-stage uplink channel estimation strategy with reduced pilot overhead and error propagation for reconfigurable intelligent surface (RIS)-aided multi-user (MU) millimeter wave (mmWave) multiple-antenna systems. The base station (BS) and the RIS are equipped with a uniform linear array (ULA) and a uniform planar array (UPA), respectively. Specifically, in Stage I, by carefully designing the RIS phase shift matrix and introducing a matching matrix, all users jointly transmit pilot signals for the estimation of the correlation factors between different paths of the common RIS-base station (BS) channel, which facilitates a significant MU diversity gain. Then, because of the inherent scaling and angle ambiguities of the mmWave cascaded channel, an ambiguous common RIS-BS channel composed of the estimated correlation factors is constructed. In Stage II, given the constructed ambiguous RIS-BS channel, each user independently sends a few pilots for estimating their own ambiguous user-RIS channel so as to obtain the entire cascaded channel. Simulation results demonstrate that the channel estimation accuracy of the proposed algorithm is improved as the number of users increases, and existing channel estimation algorithms are outperformed in terms of both pilot overhead and estimation accuracy.
CRIS-Team Scopus Importer:2023-10-20
Keywords: channel estimation; Channel estimation; Correlation; Estimation; millimeter wave; Millimeter wave communication; multi-user systems; Protocols; Reconfigurable intelligent surface; Signal processing algorithms; Transmission line matrix methods

Two-Timescale Design for Reconfigurable Intelligent Surface-Aided Massive MIMO Systems with Imperfect CSI - Zhi, Kangda; Pan, Cunhua; Ren, Hong; Wang, Kezhi; Elkashlan, Maged; Di Renzo, Marco; Schober, Robert; Vincent Poor, H.; Wang, Jiangzhou; Hanzo, Lajos (IEEE Transactions on Information Theory, 2022)
This paper investigates the two-timescale transmission scheme for reconfigurable intelligent surface (RIS)-aided massive multiple-input multiple-output (MIMO) systems, where the beamforming at the base station (BS) is adapted to the rapidly-changing instantaneous channel state information (CSI), while the nearly-passive beamforming at the RIS is adapted to the slowly-changing statistical CSI. Specifically, we first consider a system model with spatially independent Rician fading channels, which leads to tractable expressions and offers analytical insights on the power scaling laws and on the impact of various system parameters. Then, we analyze a more general system model with spatially correlated Rician fading channels and consider the impact of electromagnetic interference (EMI) caused by any uncontrollable sources present in the considered environment. For both case studies, we apply the linear minimum mean square error (LMMSE) estimator to estimate the aggregated channel from the users to the BS, utilize the low-complexity maximal ratio combining (MRC) detector, and derive a closed-form expression for a lower bound of the achievable rate. Besides, an accelerated gradient ascent-based algorithm is proposed for solving the minimum user rate maximization problem. Numerical results show that, in the considered setup, the spatially independent model without EMI is sufficiently accurate when the inter-distance of the RIS elements is sufficiently large and the EMI is mild. In the presence of spatial correlation, we show that an RIS can better tailor the wireless environment. Furthermore, it is shown that deploying an RIS in a massive MIMO network brings significant gains when the RIS is deployed close to the cell-edge users. On the other hand, the gains obtained by the users distributed over a large area are shown to be modest.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Analytical models; Array signal processing; channel estimation; Channel estimation; Correlation; Electromagnetic interference; electromagnetic interference (EMI); massive MIMO; Massive MIMO; Reconfigurable intelligent surface (RIS); Rician channels; spatial correlation; two-timescale transmission scheme

UAV-Assisted Wireless Powered Relay Networks with Cyclical NOMA-TDMA - Hadzi-Velkov, Zoran; Pejoski, Slavche; Zlatanov, Nikola; Schober, Robert (IEEE Wireless Communications Letters, 2020)
We optimize the performance of an unmanned aerial vehicle (UAV)-assisted wireless powered relay network (WPRN), where the UAV is used as a radio-frequency (RF) power transmitter and as a communication relay between energy harvesting users (EHUs) and a base station (BS). The EHUs are assigned to radial service sectors, centered around the base station (BS), and employ a combination of non-orthogonal multiple access (NOMA) and time-division multiple access (TDMA), referred to as cyclical NOMA-TDMA, for multiple access. For performance optimization, maximization of the sum rate in all service sectors and maximization of the minimal sum rate per service sector are considered, and the optimal radii of the UAV's circular trajectory and the optimal allocation of the UAV's transmit power across the service sectors are determined.
CRIS-Team Scopus Importer:2020-12-25
Keywords: multiple access techniques; relaying; unmanned aerial vehicles; Wireless power transfer

Unified asymptotic analysis of linearly modulated signals in fading, non-Gaussian noise, and interference - Nasri, Amir; Schober, Robert; Ma, Yao (IEEE Transactions on Communications, 2008)
In this paper, we present a unified asymptotic symbol error rate (SER) analysis of linearly modulated signals impaired by fading and (possibly) non Gaussian noise, which in our definition also includes interference. The derived asymptotic closed form results are valid for a large class of fading and noise processes. Our analysis also encompasses diversity reception with equal gain and selection combining and is extended to binary orthogonal modulation. We show that for high signal to noise ratios (SNRs) the SER of linearly modulated signals depends on the Mellin transform of the probability density function (pdf) of the noise. Since the Mellin transform can be readily obtained for all commonly encountered noise pdfs, the provided SER expressions are easy and fast to evaluate. Furthermore, we show that the diversity gain only depends on the fading statistic and the number of diversity branches, whereas the combining gain depends on the modulation format, the type of fading, the number of diversity branches, and the type of noise. An exception are systems with a diversity gain of one, since their combining gain and asymptotic SER are independent of the type of noise. However, in general, in a log log scale for high SNR the SER curves for different types of noise are parallel but not identical and their relative shift depends on the Mellin transforms of the noise pdfs. © 2008 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Asymptotic analysis; Diversity combining; Fading channels; Linearly modulated signals; Non Gaussian noise and interference

Unified Design of Wireless Information and Power Transmission - Wing Kwan Ng, Derrick; Duong, Trung Q.; Zhong, Caijun; Schober, Robert (Wireless Information and Power Transfer: Theory and Practice, 2019)
This chapter reveals that the efficiency in fact varies with both the radio frequency (RF) input power at the rectifier and the specific RF signal waveform being used for simultaneous wireless information and power transfer (SWIPT), which has motivated to implement dual mode SWIPT. It proposes a new transceiver architecture for SWIPT with adaptive mode switching (MS) between single and multi‐tone waveforms via an adaptive power management and information decoding (PM‐ID) module to control the operational range for energy neutral operation. The chapter presents nonlinear energy harvesting (EH) models along with the measured RF‐to‐direct current power conversion efficiency (PCE), which provides useful insights for designing dual mode SWIPT. It proposes a waveform and transceiver design for multi‐tone (PAPR) based SWIPT with higher WPT efficiency and dual mode SWIPT for an increased operational range. The chapter also proposes the reconfigurable energy harvester for enlarging the linear region of the PCE over wide input power ranges.<br
Keywords: Integrated circuit modeling; Peak to average power ratio; Transceivers; Shape; Smart devices; Power transmission

Unveiling the Importance of NOMA for Reducing AoI - Ding, Zhiguo; Schober, Robert; Poor, H. Vincent (IEEE International Conference on Communications, 2023)
The aim of this paper is to exploit cognitive-ratio inspired non-orthogonal multiple access (CR-NOMA) transmission to reduce the age of information (AoI) in wireless networks, where the key features of different data generation models are effectively utilized. Analytical results for the AoI achieved by CR-NOMA are developed to demonstrate two benefits of using NOMA to reduce the AoI in wireless networks. One is that the use of NOMA provides users more opportunities to transmit, which means that the users can update their base station more frequently. The other is that the use of NOMA can reduce access delay, i.e., the users are scheduled to transmit earlier than in the orthogonal multiple access (OMA) case, which is useful to improve the freshness of the data available in the wireless network.
CRIS-Team Scopus Importer:2023-12-15

Unveiling the Importance of SIC in NOMA Systems - Part 1: State of the Art and Recent Findings - Ding, Zhiguo; Schober, Robert; Poor, H. Vincent (IEEE Communications Letters, 2020)
The key idea of non-orthogonal multiple access (NOMA) is to serve multiple users simultaneously at the same time and frequency, which can result in excessive multiple-access interference. As a crucial component of NOMA systems, successive interference cancelation (SIC) is key to combating this multiple-access interference, and is the focus of this letter, where an overview of SIC decoding order selection schemes is provided. In particular, selecting the SIC decoding order based on the users' channel state information (CSI) and the users' quality of service (QoS), respectively, is discussed. The limitations of these two approaches are illustrated, and then a recently proposed scheme, termed hybrid SIC, which dynamically adapts the SIC decoding order is presented and shown to achieve a surprising performance improvement that cannot be realized by the conventional SIC decoding order selection schemes individually.
CRIS-Team Scopus Importer:2020-11-27
Keywords: hybrid successive interference cancellation (SIC); Non-orthogonal multiple access (NOMA); outage probability error floors

Unveiling the Importance of SIC in NOMA Systems - Part II: New Results and Future Directions - Ding, Zhiguo; Schober, Robert; Poor, H. Vincent (IEEE Communications Letters, 2020)
In most existing works on non-orthogonal multiple access (NOMA), the decoding order of successive interference cancellation (SIC) is prefixed and based on either the users' channel conditions or their quality of service (QoS) requirements. A recent work on NOMA assisted semi-grant-free transmission showed that the use of a more sophisticated hybrid SIC scheme can yield significant performance improvements. This letter illustrates how the concept of hybrid SIC can be generalized and applied to different NOMA applications. We first use NOMA assisted mobile edge computing (MEC) as an example to illustrate the benefits of hybrid SIC, where new results for offloading energy minimization are presented. Then, future directions for generalizing hybrid SIC with adaptive decoding order selection as well as its promising applications are discussed.
CRIS-Team Scopus Importer:2020-11-27
Keywords: hybrid successive interference cancellation (SIC); mobile edge computing (MEC); Non-orthogonal multiple access (NOMA)

Uplink and Downlink MIMO-NOMA with Simultaneous Triangularization - Krishnamoorthy, Aravindh; Schober, Robert (IEEE Transactions on Wireless Communications, 2021)
In this paper, we consider the uplink and downlink precoder design for two-user power-domain multiple-input multiple-output (MIMO) non-orthogonal multiple access (NOMA) systems. We propose novel uplink and downlink precoding and detection schemes that lower the decoding complexity at the receiver by decomposing the MIMO-NOMA channels of the users into multiple single-input single-output (SISO)-NOMA channels via simultaneous triangularization (ST) of the MIMO channels of the users and low-complexity self-interference cancellation at the receivers. The proposed ST MIMO-NOMA schemes avoid channel inversion at transmitter and receiver and take advantage of the null spaces of the MIMO channels of the users, which is beneficial for the ergodic achievable rate performance. We characterize the maximum ergodic achievable rate regions of the proposed uplink and downlink ST MIMO-NOMA schemes, and compare them with respective upper bounds, baseline MIMO-NOMA schemes, and orthogonal multiple access (OMA). Our results illustrate that the proposed schemes significantly outperform the considered baseline MIMO-NOMA schemes and OMA, and have a small gap to the respective upper bounds for most channel conditions and user rates. Moreover, we show that a hybrid scheme, which performs time sharing between the proposed uplink and downlink ST MIMO-NOMA and single-user MIMO, can improve performance even further.
CRIS-Team Scopus Importer:2021-01-29

Uplink Channel Estimation in Massive MIMO Systems Using Factor Analysis - Wei, Xiao; Peng, Wei; Chen, Da; Schober, Robert; Jiang, Tao (IEEE Communications Letters, 2018)
In this letter, we consider the channel estimation problem under pilot contamination in massive multiple-input multiple-output (MIMO) systems. We propose a novel channel estimation scheme, which decomposes the space supported by the covariance matrix of the received signals into three subspaces using factor analysis. For a large number of base station antennas, a practically interference-free subspace is created, in which an accurate channel estimate can be obtained. The proposed factor analysis based scheme exploits spatial correlation to significantly reduce the computational complexity. Simulation results are provided to show the efficacy of the proposed scheme.<br
Keywords: Channel estimation; MIMO communication; Covariance matrices; Contamination; Antennas; Estimation; Computational complexity

Uplink/downlink duality in massive MIMO systems with hardware impairments - Zarei, Shahram; Gerstacker, Wolfgang; Schober, Robert (2016 IEEE International Conference on Communications (ICC), 2016)
In this paper, we provide a new framework for the uplink/downlink duality in single-cell massive multiple-input multiple-output (MIMO) systems suffering from residual hardware impairments (HWIs) at the base station and the user terminals. Using the proposed duality, complex downlink optimization problems can be converted to equivalent dual uplink problems, which are easier to solve. As an example, we apply the proposed uplink/downlink duality to derive an HWI aware minimum mean square error (HWIA-MMSE) precoder, which minimizes the sum mean square error under a sum power constraint in a single-cell massive MIMO system with residual HWIs. Thereby, we use results from random matrix theory to derive an asymptotic expression for the downlink power allocation for large numbers of antennas, which only depends on the channel statistics and not on the individual channel realizations. Analytical results for the asymptotic achievable sum rate of the proposed HWIA-MMSE precoder for a large number of BS antennas are also provided. Our simulation and analytical results show that the proposed HWIA-MMSE precoder achieves a higher sum rate than the conventional regularized zero-forcing precoder for moderately large numbers of base station antennas.<br
Keywords: Downlink; Uplink; MIMO; Antennas; Signal to noise ratio; Covariance matrices; Resource management

Uplink/downlink duality in multi-cell Mu-MIMO systems with hardware impairments - Zarei, Shahram; Gerstacker, Wolfgang; Schober, Robert (WSA 2016 - 20th International ITG Workshop on Smart Antennas, 2019)
In this paper, we propose an uplink/downlink duality framework for multi-cell multi-user multiple-input multiple-output (MU-MIMO) systems with residual hardware impairments (HWIs) at the base station and the user terminals. By employing the proposed uplink/downlink duality framework, complex downlink optimization problems can be transformed to equivalent dual uplink problems which are easier to solve. Thereby, for the same total transmit power, the same per-user signal-to-interference-plus-noise ratios (SINRs) are achieved in downlink and uplink. We apply the proposed uplink/downlink duality, and derive a multi-cell HWI aware minimum mean square error (MCHWA-MMSE) precoder. Our simulation results show that the proposed MCHWA-MMSE precoder achieves a substantially higher sum rate than conventional MMSE and conjugate beamforming precoders.
CRIS-Team Scopus Importer:2019-10-25

Uplink/Downlink Duality in Multi-Cell MU-MIMO Systems with Hardware Impairments - Zarei, Shahram; Gerstacker, Wolfgang; Schober, Robert (WSA 2016; 20th International ITG Workshop on Smart Antennas, 2016)
In this paper, we propose an uplink/downlink duality framework for multi-cell multi-user multiple-input multiple-output (MU-MIMO) systems with residual hardware impairments (HWIs) at the base station and the user terminals. By employing the proposed uplink/downlink duality framework, complex downlink optimization problems can be transformed to equivalent dual uplink problems which are easier to solve. Thereby, for the same total transmit power, the same per-user signal-to-interference-plus-noise ratios (SINRs) are achieved in downlink and uplink. We apply the proposed uplink/downlink duality, and derive a multi-cell HWI aware minimum mean square error (MCHWA-MMSE) precoder. Our simulation results show that the proposed MCHWA-MMSE precoder achieves a substantially higher sum rate than conventional MMSE and conjugate beamforming precoders.<br

User Association in 5G Networks: A Survey and an Outlook - Liu, Dantong; Wang, Lifeng; Chen, Yue; Elkashlan, Maged; Wong, Kai-Kit; Schober, Robert; Hanzo, Lajos (IEEE Communications Surveys & Tutorials, 2016)
The fifth generation (5G) mobile networks are envisioned to support the deluge of data traffic with reduced energy consumption and improved quality of service (QoS) provision. To this end, key enabling technologies, such as heterogeneous networks (HetNets), massive multiple-input multiple-output (MIMO), and millimeter wave (mmWave) techniques, have been identified to bring 5G to fruition. Regardless of the technology adopted, a user association mechanism is needed to determine whether a user is associated with a particular base station (BS) before data transmission commences. User association plays a pivotal role in enhancing the load balancing, the spectrum efficiency, and the energy efficiency of networks. The emerging 5G networks introduce numerous challenges and opportunities for the design of sophisticated user association mechanisms. Hence, substantial research efforts are dedicated to the issues of user association in HetNets, massive MIMO networks, mmWave networks, and energy harvesting networks. We introduce a taxonomy as a framework for systematically studying the existing user association algorithms. Based on the proposed taxonomy, we then proceed to present an extensive overview of the state-of-the-art in user association algorithms conceived for HetNets, massive MIMO, mmWave, and energy harvesting networks. Finally, we summarize the challenges as well as opportunities of user association in 5G and provide design guidelines and potential solutions for sophisticated user association mechanisms.<br
Keywords: 5G mobile communication; MIMO; Energy harvesting; Wireless communication; Communication system security; Resource Management; Quality of service

User-Centric Energy Efficiency Maximization for Wireless Powered Communications - Wu, Qingqing; Chen, Wen; Wing Kwan Ng, Derrick; Li, Jun; Schober, Robert (IEEE Transactions on Wireless Communications, 2016)
In this paper, we consider wireless powered communication networks (WPCNs) where multiple users harvest energy from a dedicated power station and then communicate with an information receiving station in a time-division manner. Thereby, our goal is to maximize the weighted sum of the user energy efficiencies (WSUEEs). In contrast to the existing system-centric approaches, the choice of the weights provides flexibility for balancing the individual user EEs via joint time allocation and power control. We first investigate the WSUEE maximization problem without the quality of service constraints. Closed-form expressions for the WSUEE as well as the optimal time allocation and power control are derived. Based on this result, we characterize the EE tradeoff between the users in the WPCN. Subsequently, we study the WSUEE maximization problem in a generalized WPCN where each user is equipped with an initial amount of energy and also has a minimum throughput requirement. By exploiting the sum-of-ratios structure of the objective function, we transform the resulting non-convex optimization problem into a two-layer subtractive-form optimization problem, which leads to an efficient approach for obtaining the optimal solution. The simulation results verify our theoretical findings and demonstrate the effectiveness of the proposed approach.<br
Keywords: Wireless communication; Resource management; Throughput; Power generation; Optimization; Quality of service; Power control

Using dimensional analysis to assess scalability and accuracy in molecular communication - Noel, Adam; Cheung, Karen C.; Schober, Robert (2013 IEEE International Conference on Communications Workshops, ICC 2013, 2013)
In this paper, we apply dimensional analysis to study a diffusive molecular communication system that uses diffusing enzymes in the propagation environment to mitigate intersymbol interference. The enzymes bind to information molecules and then degrade them so that they cannot interfere with the detection of future transmissions at the receiver. We determine when it is accurate to assume that the concentration of information molecules throughout the receiver is constant and equal to that expected at the center of the receiver. We show that a lower bound on the expected number of molecules observed at the receiver can be arbitrarily scaled over the environmental parameters, and generalize how the accuracy of the lower bound is qualitatively impacted by those parameters. © 2013 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Utility-optimal random access for wireless multimedia networks - Cheung, Man Hon; Mohsenian-Rad, Hamed; Wong, Vincent W. S.; Schober, Robert (IEEE Wireless Communications Letters, 2012)
In this letter, we consider the uplink random access problem in a wireless multimedia network (WMN) with audio, video, and best effort applications. Since these multimedia applications have different quality-of-service (QoS) requirements, we model their utilities with concave, step, and quasi-concave functions. We assume that the access point performs admission control and assigns transmission probabilities to the users for random access, based on solving a non-convex network utility maximization problem. We propose a novel enumeration algorithm to obtain the global optimal solution by solving a number of computationally tractable convex optimization problems. We characterize the total number of iterations of the algorithm analytically. Simulation results show that our proposed algorithm achieves a higher average network aggregate utility than a carrier sense multiple access (CSMA) scheme implemented in a slotted time system. © 2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Random access; wireless multimedia networks

Utilizing renewable energy resources by adopting DSM techniques and storage facilities - Samadi, Pedram; Mohsenian-Rad, Hamed; Wong, Vincent W. S.; Schober, Robert (2014 IEEE International Conference on Communications (ICC), 2014)
A common assumption in the existing literature on energy consumption scheduling in smart grid is that users are aware in advance of their daily energy consumption needs. Therefore, most existing studies along this line of research have been inherently deterministic, e.g., see [1]-[3]. However, this assumption may not hold in practice. In particular, the energy consumption scheduling (ECS) devices may face load uncertainty. If a user is equipped with a behind-the-meter renewable generator, then the optimal operation of ECS devices becomes even more challenging due to combined load and supply uncertainties. Therefore, in this paper, we formulate a stochastic optimization problem to operate an ECS device in a residential unit that is equipped with a behind-the-meter renewable generator and a local battery bank. In our problem formulation, we consider different sets of must-run and controllable appliances. Our design only requires knowledge of some estimates of the users' future demand. To reduce computational complexity, we approximate the expected load in the upcoming time slots by adopting the certainty equivalent approximation technique. Simulation results show that the proposed energy consumption scheduling algorithm can tackle the uncertainties in load and supply and it can benefit both users and the utility companies.<br
Keywords: Home appliances; Batteries; Uncertainty; Energy consumption; Power generation; Schedules; Electricity

Weighted sum-rate maximization scheduling for MIMO ad hoc networks - Ma, Yao; Schober, Robert; Pasupathy, Subbarayan (IEEE International Conference on Communications, 2009)
In this paper, we propose a duality-optimization based framework to maximize the weighted sum throughput for a multiple-input multiple-output (MIMO) ad hoc network. The new schemes include an approximate global optimization approach and an iterative search approach based on the duality framework. Transmitter adaptive precoding and receiver minimum mean-square-error (MMSE) detection for interference suppression are considered. Simulation results show that a significantly higher throughput is achieved for the dual optimization schemes than for the fixed mode precoding schemes and the transmit iterative waterfilling (IWF) scheme. The negative effects of transmit and receive antenna correlations are also studied. Results show that the proposed schemes are more robust against both transmit and receive correlations than the fixed-mode and IWF schemes. ©2009 IEEE.
CRIS-Team Scopus Importer:2020-02-03

Welcome from the organizing committee - Gulliver, Aaron; Schober, Robert (IEEE Vehicular Technology Conference, 2014)
CRIS-Team Scopus Importer:2020-02-03

Wireless information and power transfer: Energy efficiency optimization in OFDMA systems - Derrick Wing Kwan Ng,; Lo, Ernest S.; Schober, Robert (IEEE Transactions on Wireless Communications, 2013)
This paper considers orthogonal frequency division multiple access (OFDMA) systems with simultaneous wireless information and power transfer. We study the resource allocation algorithm design for maximization of the energy efficiency of data transmission (bits/Joule delivered to the receivers). In particular, we focus on power splitting hybrid receivers which are able to split the received signals into two power streams for concurrent information decoding and energy harvesting. Two scenarios are investigated considering different power splitting abilities of the receivers. In the first scenario, we assume receivers which can split the received power into a continuous set of power streams with arbitrary power splitting ratios. In the second scenario, we examine receivers which can split the received power only into a discrete set of power streams with fixed power splitting ratios. For both scenarios, we formulate the corresponding algorithm design as a non-convex optimization problem which takes into account the circuit power consumption, the minimum data rate requirements of delay constrained services, the minimum required system data rate, and the minimum amount of power that has to be delivered to the receivers. By exploiting fractional programming and dual decomposition, suboptimal iterative resource allocation algorithms are developed to solve the non-convex problems. Simulation results illustrate that the proposed iterative resource allocation algorithms approach the optimal solution within a small number of iterations and unveil the trade-off between energy efficiency, system capacity, and wireless power transfer: (1) wireless power transfer enhances the system energy efficiency by harvesting energy in the radio frequency, especially in the interference limited regime; (2) the presence of multiple receivers is beneficial for the system capacity, but not necessarily for the system energy efficiency. © 2002-2012 IEEE.
CRIS-Team Scopus Importer:2020-02-03
Keywords: Energy efficiency; green communications; non-convex optimization; wireless information and power transfer

Wireless information and power transfer: Theory and practice - Ng, Derrick Wing Kwan; Duong, Trung Q.; Zhong, Caijun; Schober, Robert (wiley, 2018)
CRIS-Team Scopus Importer:2022-06-05

Wireless local area network service providers' price competition in presence of heterogeneous user demand - Kumar, Abhinav; Mallik, Ranjan K.; Schober, Robert (IET Communications, 2013)
Consider wireless local area network (WLAN) service providers (SPs) operating in an overlapping service area. The SPs compete with each other to attract users. The price charged is utilised by the SPs as a tool to maximise revenue, resulting in a price competition between the WLAN SPs. The users are assumed to be selfish, trying to maximise their individual utility. They have varied sensitivity towards quality of service experienced and the price charged. In such a scenario, the user demand distribution is the one that achieves Wardrop equilibrium. Approximate analytical expressions are obtained for the best response of SPs to each other's price. Existence of a Nash equilibrium (NE) between the competing SPs is proved and the price vector at which the NE occurs is obtained. It is found that, while in one extreme monopoly leads to very high revenue for WLAN SPs with minimal consumer surplus, in the other extreme unregulated duopoly/oligopoly leads to high consumer surplus at the cost of minimal revenue generation for the competing SPs. Thus, price regulation is proposed in the WLAN market for equitable distribution of the surplus among the SPs and the user

Wireless Powered ALOHA Networks with UAV-Mounted-Base Stations - Hadzi-Velkov, Zoran; Pejoski, Slavche; Schober, Robert; Zlatanov, Nikola (IEEE Wireless Communications Letters, 2020)
In this letter, we study wireless powered communication networks (WPCNs) with base stations (BSs) mounted on unmanned aerial vehicles (UAVs). For implementation simplicity and uncoordinated access, the energy harvesting (EH) users (EHUs) employ slotted ALOHA to transmit information at a fixed rate to a common UAV-mounted BS. The UAV flying along a circular trajectory facilitates a line of sight (LoS) between the BS and each EHU, and also mitigates the adverse double near-far effect as it periodically comes close to the EHUs. Due to the periodicity of the LoS channels, the channel can be tracked without performing energy-costly channel estimation, and the channel attenuation can be compensated to avoid channel outages. For such a WPCN, we optimize the UAV radius, the channel access probability, and the rate of each EHU to enable proportionally fair resource allocation. Our solution reveals that, when a certain UAV altitude is exceeded, proportional fairness is attained when the UAV is in the hovering mode.
CRIS-Team Scopus Importer:2020-02-04
Keywords: slotted ALOHA; unmanned aerial vehicles; Wireless powered communication networks

Wireless Power Transfer - Wing Kwan Ng, Derrick; Duong, Trung Q.; Zhong, Caijun; Schober, Robert (Wireless Information and Power Transfer: Theory and Practice, 2019)
Large‐scale wireless networks are characterized by the existence of multi‐user interference due to the concurrent transmission of the network's terminals. In networks where the main focus is wireless power transfer (WPT), interference is beneficial as it increases the harvesting efficiency. This chapter focuses on a wireless‐powered cooperative network where the relays harvest energy from the source in order to convey its transmitted information. It deals with a simultaneous wireless information and power transfer (SWIPT) scenario, where terminals employ successive interference cancellation (SIC) techniques to boost the harvesting efficiency. The chapter studies a wireless‐powered communication network (WPCN) implementing a wireless‐powered opportunistic beamforming (OBF) protocol. Closed‐form mathematical expressions are provided for the considered performance metric of each scenario as well as numerical results with useful insights regarding the network's performance.<br
Keywords: Relays; Batteries; Wireless communication; Power system reliability; Probability; Signal to noise ratio

WLAN Service Providers' Price Competition with Uncertainty in User Demand - Kumar, Abhinav; Mallik, Ranjan K.; Schober, Robert (IEEE Communications Letters, 2013)
In this letter, uncertainty in users' network selection is modeled by a Markov chain. In the presence of such uncertainty, the price competition game of wireless local area network (WLAN) service providers (SPs) is analyzed and the existence of Bayesian Nash equilibrium is proved. Using the price of anarchy as a metric of efficiency for social welfare maximization, it is shown that an increase in competition does not result in significant losses in efficiency. Compared to a monopoly, an unregulated duopoly of WLAN SPs is recommended as it results in a more equitable distribution of surplus amongst the SPs and the user